Who is Affirmative Action For? - N. Warikoo (Boston Globe, 2016)

The Limits of Chinese Soft Power - Nye, Joseph S., Jr. (Today's Zaman, 2015)
In 2007, then-President Hu Jintao told the Communist Party that the country needed to increase its soft power; President Xi Jinping repeated the same message last year. They know that, for a country like China, whose growing economic and military power risks scaring its neighbors into forming counter-balancing coalitions, a smart strategy must include efforts to appear less frightening. But their soft-power ambitions still face major obstacles.

Growing Up Alone - Putnam, Robert D. (The Atlantic, 2015)

‘Our Kids,’ by Robert D. Putnam - Putnam, Robert D. (New York Times Sunday Review, 2015)

Book review: ‘Empire of Cotton: A Global History,’ by Sven Beckert - Sven Beckert (Washington Post, 2015)
Global history is very much the fashion in leading university history departments today. Some of them seek to replace courses in Western civilization with classes in global history—but usually such courses have to be team-taught by a variety of specialists, since so few individual academics have such a broad reach. “Empire of Cotton” proves Sven Beckert one of the new elite of genuinely global historians.

Capitalism, As Woven Through Cotton - Sven Beckert (International New York Times, 2014)
After a quarter-century of tightly focused studies, historians are addressing extended periods of time and the global dimensions of history. As Thomas Piketty did in “Capital in the 21st Century,”his excellent recent study of wealth and inequality, Sven Beckert takes the long view in “Empire of Cotton: A Global History.” Mr. Beckert’s book is more broadly framed and more readable, but at its heart, as in Mr. Piketty’s book, is inequality.

‘Empire of Cotton,’ by Sven Beckert - Sven Beckert (International New York Times, 2014)
The history of an era often seems defined by a particular commodity. The 18th century certainly belonged to sugar. The race to cultivate it in the West Indies was, in the words of the French Enlightenment writer Guillaume-Thomas de Raynal, “the principal cause of the rapid movement which stirs the Universe.” In the 20th century and beyond, the commodity has been oil: determining events from the Allied partitioning of the Middle East after World War I to Hitler’s drive for Balkan and Caspian wells to the forging of our own fateful ties to the regimes of the Persian Gulf.

Empire of Cotton - Sven Beckert (The Atlantic, 2014)

Ferguson's Grand Jury Problem - Feldman, Noah (Bloomberg, 2014)

Obamacare May Die So Gay Marriage Survives - Feldman, Noah (Bloomberg, 2014)

The ECB Must Show Leadership to Fight Threat of Deflation - Bini Smaghi, Lorenzo (Financial Times, 2014)

Ranking the Rankings - Beth A. Simmons (The Economist, 2014)
Education ministers across the globe quake in the run-up to the publication, every three years, of the OECD’s Programme for International Student Assessment (PISA), which rates 15-year-olds’ academic performance in dozens of countries. Those that do well can expect glory; the first PISA ranking, published in 2001, surprised the world by putting unshowy Finland near the top in every subject and made it a mandatory stop-off for any self-respecting education policymaker. Germany’s poor showing, by contrast, led to national hand-wringing, school reforms and the creation of a €4 billion ($5 billion) federal education support programme.

Scotland Rejects Independence as U.K. Vows to Give It More Power - Mylonas, Harris (2014)
Scotland voted to stay in the U.K. in a referendum on independence, stepping back from a breakup of the 307-year-old union while wringing promises of more financial power from Prime Minister David Cameron. After a count through the night, 55.3 percent of Scottish voters supported the “no” campaign against 44.7 percent who backed independence. U.K. shares helped lead European equities to a 6 1/2-year high and the pound rose to the strongest level in two years against the euro after the Better Together campaign posted a wider margin of victory than opinion polls suggested. There was a record turnout of more than 90 percent in some of the 32 districts. The Scottish Independence Vote: Breakdown of Results “I accept the verdict” of the people, Alex Salmond, the leader of Scotland’s semi-autonomous government in Edinburgh, said in a speech. While conceding defeat, he stressed the broad movement that resulted in 1.6 million votes for independence. “The unionist parties made vows and Scotland will expect them to be delivered in rapid course,” he said. The referendum outcome follows two years of increasingly bitter arguments over the economic viability of independence, the currency to be used, custody of the health service and North Sea oil revenue, leaving a legacy of a divided Scotland while inspiring self-determination movements across Europe. The FTSE 100 Index added 0.7 percent in London, and the Stoxx Europe 600 Index rose 0.6 percent. The pound gained as much as 0.9 percent versus the euro and traded 0.4 percent higher at 78.52 pence at 12:09 p.m. in London. The benchmark 10-year U.K. government bond yield fell 1 basis point to 2.57 percent. The two-year gilt yield rose 3 basis points to 0.89 percent as investors bet the decision to reject independence clears the way for the Bank of England to raise interest rates as early as the spring. Extra Powers Cameron said he would stick with his promise to cede more policy-making powers for Scotland after a “no” vote. He also pledged a constitutional shakeup of the U.K. that would take into account how England and Wales are governed. Scotland's Vote for Independence Outside his Downing Street office in London, Cameron said the Scottish people had spoken and “we hear you.” “We will ensure those commitments are honored in full,” he said. The closeness of the contest before the vote, which saw one poll this month put the “yes” camp ahead, unnerved financial markets and triggered a last-ditch attempt by Better Together to persuade voters that “no” would herald some of the changes Scots say they want. The prime minister and opposition Labour Party leader Ed Miliband canceled parliamentary business and headed north a week before the vote to campaign in cities and towns across Scotland. They pledged more powers to the Scottish Parliament over taxation and welfare spending in an attempt to arrest momentum in the polls for Salmond after he outshone Better Together campaign leader Alistair Darling in a televised debate. ‘Positive Change’ Darling, a former Labour chancellor of the exchequer, used his victory speech to hail the vote for “positive change rather than needless separation.” Cameron called Darling this morning to congratulate him on his successful campaign. “They need to get their skates on and deliver,” Matt Qvortrup, senior researcher at Cranfield University and author of “Referendums and Ethnic Conflict,” said of the main U.K. parties -- Cameron’s Conservatives, his Liberal Democrat coalition partners and Labour. “They should have done this earlier.” As the results unfolded, early bellwethers suggested a let-off for Cameron and Miliband. In the end, only four local authorities -- Dundee, West Dunbartonshire, North Lanarkshire and Glasgow, Scotland’s biggest city -- voted “yes.” ‘Blew It’ Emily Gallagher, an 18-year-old student and “yes” supporter, said she was “devastated” by the result. “We had a great opportunity and we blew it,” she said over the din of pro-independence chants in central Glasgow. “We’ve had so many Tory governments we’ve never voted for and that’s just going to go on.” That the referendum took place at all reflected the gulf between politics in Scotland, where Salmond’s SNP has run the devolved administration since 2007, and the rest of the U.K., where Cameron’s Conservatives have the support of just one Tory lawmaker from Scotland. The situation was exacerbated by the weakening of Labour, traditionally a dominant force in Scotland. The party lost to Cameron in the 2010 election to the U.K. Parliament at Westminster before being trounced by the SNP in Scotland a year later. That win for the nationalists paved the way for the vote on establishing Europe’s newest sovereign state. Edinburgh Agreement Cameron and Salmond signed the Edinburgh Agreement that set out the terms of the referendum in October 2012 with both promising to uphold the result. The campaigns became increasingly heated and culminated this week in both sides appealing to the emotional side of voters. In the event, it appeared that more of the undecided respondents in opinion polls opted for the status quo. “This was an event that cannot be captured or understood just by looking at the percentages,” said Harris Mylonas, assistant professor of political science at George Washington University and author of “The Politics of Nation-Building.”

Scots Must Vote Nae - Ferguson, Niall (New York Times, 2014)
To most Americans, Scotland means golf, whisky and—if they go there—steady drizzle. Even to the millions of Americans whose surnames testify to their Scottish or Scotch-Irish ancestry, the idea that Scotland might be about to become an independent country is baffling.

All in the Family: the Dulleses, the Bundys and the End of the Establishment - Nye, Joseph S., Jr. (Foreign Affairs, 2014)

How to Kill the Death Penalty - Temkin, Moshik (Los Angeles Times, 2014)

Is Neoliberalism a Threat to Civil Rights? - Lamont, Michèle; Guay, Joseph (Boston Globe, 2014)

To Save the Girls, the World Must Help Nigeria - Jacob K. Olupona (Huffington Post, 2014)

Who gets Admitted to College? - N. Warikoo (Los Angeles Times, 2013)

When Imposing Sanctions, Target the Elite - von Soest, Christian (New York Times, 2013)

Robert Bowie, Presidents’ Aide, Dies at 104 - Bowie, Robert. R. (New York Times, 2013)

Clearing the Air in China - Nielsen, Chris P; Ho, Mun (New York Times, 2013)

China Needs Justice, Not Equality - Whyte, Martin K. (Foregin Affairs, 2013)

Korea ‘Lucky’ to Have Strong, Large Diaspora to Draw Upon - Mylonas, Harris (Korea Joongang Daily, 2013)

In Syria, Parents are Afraid Students Will 'Lose Their Future' - Dryden-Peterson, Sarah (The Globe and Mail, 2013)

The Supreme Court Decides to See No Evil Abroad - Feldman, Noah (Bloomberg, 2013)

Why India Trails China - Sen, Amartya (New York Times, 2013)

Wither Nation-Building? - Mylonas, Harris (e-International Relations, 2013)

The Boston Question - Varshney, Ashutosh (Indian Express, 2013)

China’s New Leader Follows Katy Perry’s Tune - Feldman, Noah (Bloomberg, 2013)

Declare Dignity: Donna Hicks at TEDxStormont - Hicks, Donna (TEDTalks, 2013)

Don't Risk Auschwitz Trials Ending in Fiasco - Weber, Thomas (Haaretz, 2013)

In History Departments, It’s Up With Capitalism - Sven Beckert (New York Times, 2013)

China Doesn't Belong in the BRICS - Allison, Graham T., Jr. (The Atlantic, 2013)

Are They Watching You? That’s a Secret - Feldman, Noah (Bloomberg, 2013)

Mexico Breaking Good? - Rogoff, Kenneth S. (Project Syndicate, 2013)

Military’s Limits Show Need for America’s Neglected Weapon - Burns, Nicholas (Boston Globe, 2013)

Our Pacific Predicament - Nye, Joseph S., Jr. (The American Interest, 2013)

Singapore's Lee Kuan Yew Talks America's Strengths And Weaknesses - Allison, Graham T., Jr. (Forbes, 2013)

Is This Any Way to Run US Foreign Policy? - Walt, Stephen M. (Foreign Policy, 2013)

Treat Millionaires Like They’re Billionaires - Feldman, Noah (Bloomberg, 2013)

A Chance at Justice in Guatemala - Weld, Kirsten A. (New York Times, 2013)

Currency War Denial is Wishful Thinking - Bini Smaghi, Lorenzo (Business Spectator, 2013)

Harvard Economist Gita Gopinath Offers a Euro Cure - Gopinath, Gita (Bloomberg Businessweek, 2013)

Will China Ever Be No. 1? - Allison, Graham T., Jr. (Foreign Policy, 2013)

Ethiopia: Brics Without Mortar - Nye, Joseph S., Jr. (All Africa, 2013)

Dignity in Resolving Conflicts is Topic of November 11 Cape Ann Forum - Hicks, Donna (Wicked Local, 2012)

Where Was Asia? - Grietens, Sheena Chestnut (New York Times, 2012)

God and Ceasar in America - Putnam, Robert D.; David E. Campbell (Foreign Affairs, 2012)

French Lottery Bonds Show Risky History of Property Bets - Yates, Alexia (Bloomberg, 2012)

Turkey's Miscarriage of Justice - Rodrik, Dani (The Washington Post, 2012)

US-Israel Ties - Martin, Lenore G.; Avnon, Dan (CRI English, 2012)

Innovation Key to Unlocking Africa's Horticultural Potential - Juma, Calestous (Fresh Fruit Portal, 2012)

Six choses que Valls doit savoir avant d'aller en Roumanie - Paul, Ruxandra (Courrier International, 2012)

Toward Better Aid - Leaning, Jennifer (The Harvard Gazette, 2012)

Why Obama is Winning - Ferguson, Niall (The Daily Beast, 2012)

How to Weather a Hurricane - Daniel P. Aldrich (New York Times, 2012)

Nova regra de financiamento produzirá campanha eleitoral amarga nos EUA - Keyssar, Alexander (Folha de Sao Paulo, 2012)

Voter Suppression Returns: Voting Rights and Partisan Practices - Keyssar, Alexander (Harvard Magazine, 2012)

The Crisis of European Democracy - Sen, Amartya (The New York Times, 2012)

Did the June 23 Movement Change Senegal? - Kelly, Catherine (Possible Futures, 2012)

Europe Needs a German Marshall Plan - Charles S. Maier (The New York Times, 2012)

Greek Left Embarks On Coalition Talks But No End Seen In Political Deadlock - Mylonas, Harris (The Wall Street Journal, 2012)

As Athens's Woes Grow, Neo-Nazis Gain Clout - Bouras, Stelios; Mylonas, Harris (Wall Street Journal, 2012)

Granting People Their Dignity - DelRosario, John S.; Hicks, Donna (Saipan Tribune, 2012)

Leading With Dignity in the Workplace - Hicks, Donna (FOX News, 2012)

Why Nations Fail - Friedman, Thomas L.; Robinson, James A.; Acemoglu, Daron (New York Times, 2012)

Five Myths About Syria - Owen, E. Roger (The Washington Post, 2012)

Why Do Nations Fail? (Boston Globe, 2012)
Several centuries ago, there was a nation that rose to become a world power on the strength of its innovation and its dedication to capitalist enterprise. It became a major center of trade, a financial powerhouse whose name was well known across the planet. It was blessed with an unusual society that rewarded talent and hard work, not social position—one of the few places where a person who had nothing could realistically dream of a far better life. And then this vibrant place, the envy of the world, suddenly collapsed. Its economy shrank; its people left. The place was Venice, and if it is hard to imagine the charming tourist destination was once one of the richest places on the Earth, then that is precisely what MIT economist Daron Acemoglu wants me to understand. I had come to the Sloan School of Management cafeteria, its tall windows framing the Charles River, for coffee and a discussion of his favorite topic—why nations fail. It is a question that has intrigued people for thousands of years, but now Acemoglu and Harvard’s James Robinson offer an answer in an ambitious new book. Their theory, the fruit of a long intellectual partnership and research that digs back to the origins of agriculture, explains why some countries succeed and others do not, why some are awash in prosperity, while others are consumed by poverty and suffering. It explains how a city-state like Venice can rise to prominence, then quickly fail. And it offers a chastening message about the prospects for our own country. So why do nations fail? Acemoglu has a one-word answer: “Politics.’’ What this means, he explains, is that nations succeed in the long term when they are able to share power broadly. They either develop inclusive institutions or “extractive institutions,’’ designed to plunder wealth for the few. Throughout history, says Acemoglu, “the great struggle is between the masses and elites who seek to capture the government and put it to their own uses.’’ It is a less obvious answer, with more surprising implications, than is immediately apparent. To begin with, consider the factors that the two reject. Geography, for example, has long been a favorite explanation for the success of nations. Some places are blessed with natural advantages, while others are not. Certainly, sitting on coveted goods brings great wealth: witness Saudi Arabia or, for that matter, Russia. But over the long reach of history, geography fails to explain which nations have staying power. One can make a convincing list of all the geographical benefits that have accrued to the United States, but when Europeans first arrived in the 15th century, it was South America, not North, that was rich and (relatively) thickly settled.

Top Ten Media Failures in the Iran War Debate - Walt, Stephen M. (Foreign Policy, 2012)
I did a brief interview for All Things Considered last Friday, on the topic of media handling of the current war scare over Iran. Here's a link to the story, which ran over the weekend. The interview got me thinking about the issue of media coverage of this whole business, and I'm sorry to say that most mainstream news organizations have let us down again. Although failures haven't been as egregious as the New York Times and Washington Post's wholesale swallowing of the Bush administration's sales pitch for war in 2002, on the whole the high-end media coverage has been disappointing. Here are my Top Ten Media Failures in the 2012 Iran War Scare. #1: Mainstreaming the war. As I've written before, when prominent media organizations keep publishing alarmist pieces about how war is imminent, likely, inevitable, etc., this may convince the public that it is going to happen sooner or later and it discourages people from looking for better alternatives. Exhibits A and B for this problem are Jeffrey Goldberg's September 2010 article in The Atlantic Monthly and Ronan Bergman's February 2012 article in the New York Times Magazine. Both articles reported that top Israeli leaders believed time was running out and suggested that an attack might come soon. #2: Loose talk about Iran's “nuclear [weapons] program.” A recurring feature of Iran war coverage has been tendency to refer to Iran's “nuclear weapons program” as if its existence were an established fact. U.S. intelligence services still believe that Iran does not have an active program, and the IAEA has also declined to render that judgment either. Interestingly, both the Times' public editor Arthur Brisbane and Washington Post ombudsman Patrick Pexton have recently chided their own organizations for muddying this issue. #3: Obsessing about Ahmadinejad. A typical insertion into discussions of Iran is to make various references to Iranian President Mahmoud Ahmadinejad, usually including an obligatory reference to his penchant for Holocaust denial and his famously mis-translated statement about Israel “vanishing from the page of time.” This feature is often linked to the issue of whether Iran's leaders are rational or not. But the obsession with Ahmadinejad is misleading in several ways: he has little or no influence over Iran's national security policy, his power has been declining sharply in recent months, and Supreme Leader Ali Khameini - who does make the key decisions - has repeatedly said that nuclear weapons are contrary to Islam. And while we're on the subject of Iranian “rationality,” it is perhaps worth noting that its leaders weren't goofy enough to invade Iraq on a pretext and then spend trillions of dollars fighting an unnecessary war there. #4: Ignoring Iranian weakness. As I've noted before, Iran is not a very powerful country at present, though it does have considerable potential and could exert far more international influence if its leaders were more competent. But its defense budget is perhaps 1/50th the size of U.S. defense spending, and it has no meaningful power-projection capabilities. It could not mount a serious invasion of any of its neighbors, and could not block the Strait of Hormuz for long, if at all. Among other things, that is why it has to rely on marriages of convenience with groups like Hezbollah or Hamas (who aren't that powerful either). Yet as Glenn Greenwald argues here, U.S. media coverage often portrays Iran as a looming threat, without offering any serious military analysis of its very limited capabilities. #5: Failing to ask why Iran might want a bomb. Discussions of a possible war also tend to assume that if Iran does in fact intend to get a nuclear weapon, it is for some nefarious purpose. But the world's nine nuclear powers all obtained these weapons first and foremost for deterrent purposes (i.e., because they faced significant external threats and wanted a way to guarantee their own survival). Iran has good reason to worry: It has nuclear-armed states on two sides, a very bad relationship with the world's only superpower, and more than three dozen U.S. military facilities in its neighborhood. Prominent U.S. politicians repeatedly call for “regime change” there, and a covert action campaign against Iran has been underway for some time, including the assassination of Iranian civilian scientists. #6: Failing to consider why Iran might NOT want a bomb. At the same time, discussions of Iran's nuclear ambitions often fail to consider the possibility that Iran might be better off without a nuclear weapons capability. As noted above, Supreme Leader Khameini has repeatedly said that nuclear weapons are contrary to Islam, and he may very well mean it. He could be lying, but that sort of lie would be risky for a regime whose primary basis for legitimacy is its devotion to Islam. For another, Iran has the greatest power potential of any state in the Gulf, and if it had better leadership it would probably be the strongest power in the region. If it gets nuclear weapons some of its neighbors may follow suit, which would partly negate Iran's conventional advantages down the road. Furthermore, staying on this side of the nuclear weapons threshold keeps Iran from being suspected of complicity should a nuclear terrorist attack occur somewhere. For all these reasons, I'd bet Iran wants a latent nuclear option, but not an actual nuclear weapon. But there's been relatively little discussion of that possibility in recent media coverage. #7: Exaggerating Israel's capabilities. In a very real sense, this whole war scare has been driven by the possibility that Israel might feel so endangered that they would launch a preventive war on their own, even if U.S. leaders warned them not to. But the IDF doesn't have the capacity to take out Iran's new facility at Fordow, because they don't have any aircraft that can carry a bomb big enough to penetrate the layers of rock that protect the facilities. And if they can't take out Fordow, then they can't do much to delay Iran's program at all and the only reason they might strike is to try to get the United States dragged in. In short, the recent war scare-whose taproot is the belief that Israel might strike on its own-may be based on a mirage. #8: Letting spinmeisters play fast and loose with facts. Journalists have to let officials and experts express their views, but they shouldn't let them spout falsehoods without pushing back. Unfortunately, there have been some egregious cases where prominent journalists allowed politicians or government officials to utter howlers without being called on it. When Rick Santorum announced on Meet the Press that “there were no inspectors” in Iran, for example, host David Gregory didn't challenge this obvious error. (In fact, Iran may be the most heavily inspected country in the history of the IAEA). Even worse, when Israeli ambassador Michael Oren appeared on MSNBC last week, he offered the following set of dubious claims, without challenge: “[Iran] has built an underground nuclear facility trying to hide its activities from the world. It has been enriching uranium to a high rate [sic.] that has no explanation other than a military nuclear program - that has been confirmed by the International Atomic Energy Agency now several times. It is advancing very quickly on an intercontinental ballistic missile system that's capable of carrying nuclear warheads.” Unfortunately, MSNBC host Andrea Mitchell apparently didn't know that Oren's claims were either false or misleading. 1) Iran's underground facility was built to make it hard to destroy, not to “hide its activities,” and IAEA inspectors have already been inside it. 2) Iran is not enriching at a "high rate" (i.e., to weapons-grade); it is currently enriching to only 20% (which is not high enough to build a bomb). 3) Lastly, Western intelligence experts do not think Iran is anywhere near to having an ICBM capability. In another interview on NPR, Oren falsely accused Iran of “killing hundreds, if not thousands of American troops,” a claim that NPR host Robert Siegel did not challenge. Then we got the following exchange: Oren: “Imagine Iran which today has a bunch of speedboats trying to close the Strait of Hormuz. Imagine if Iran has a nuclear weapon. Imagine if they could hold the entire world oil market blackmailed. Imagine if Iran is conducting terrorist organizations through its terrorist proxies - Hamas, Hezbollah. Now we know there's a connection with al-Qaida. You can't respond to them because they have an atomic weapon.” Siegel: “Yes. You're saying the consequences of Iran going nuclear are potentially global, and the consequences of a U.S. strike on Iran might also be further such attacks against the United States...” Never mind the fact that we have been living in the nuclear age for some 60 years now, and no nuclear state has even been able to conduct the sort of aggressive blackmail that Oren suggests Iran would be able to do. Nuclear weapons are good for deterrence, and not much else, but the news media keep repeating alarmist fantasies without asking if they make sense or not. Politicians and government officials are bound to use media moments to sell whatever story they are trying to spin; that's their job. But It is up to journalists to make this hard, and both Mitchell and Siegel didn't. (For another example of sloppy fact-checking, go here). #9. What about the human beings? One of the more bizarre failures of reporting on the war debate has been the dearth of discussion of what an attack might mean for Iranian civilians. If you take out some of Iran's nuclear facilities from the air, for example, there's a very real risk of spreading radioactive material or other poisonous chemicals in populated areas, thereby threatening the lives of lots of civilians. Yet when discussing the potentially dangerous consequences of a war, most discussions emphasize the dangers of Iranian retaliation, or the impact on oil prices, instead of asking how many innocent Iranian civilians might die in the attack. You know: the same civilians we supposedly want to liberate from a despotic clerical regime. #10. Could diplomacy work? Lastly, an underlying theme in a lot of the coverage is the suggestion that diplomacy is unlikely to work, because it's been tried before and failed. But the United States has had very little contact with Iranian officials over the past thirty years, and only one brief set of direct talks in the past three years. Moreover, we've insisted all along that Iran has to give up all nuclear enrichment, which is almost certainly a deal-breaker from Tehran's perspective. The bottom line is that diplomacy has yet to succeed - and it might not in any case - but it's also never been seriously tried. I'm sure you can find exceptions to the various points I've made here, especially if you move outside major media outlets and focus on online publications and the blogosphere. Which may be why more people are inclined to get their news and analysis there, instead of from the usual outlets. But on the whole, Americans haven't been well-served by media coverage of the Iran debate. As the president said last week, “loose talk” about an issue like this isn't helpful.

Why Afghanistan was Obama's Biggest Mistake - Walt, Stephen M. (Foreign Policy, 2012)
The killing of 16 Afghan civilians - nine of them children—by a rogue U.S. soldier is a tragedy in several senses. First, because of the loss of innocent life. Second, because the alleged perpetrator is likely someone whose psyche and spirit broke under the pressure of a prolonged counterinsurgency campaign. And third, because it was all so unnecessary. Because Barack Obama has run a generally hawkish foreign policy, his Republican opponents don't have a lot of daylight to exploit on that issue. But if they weren't so preoccupied with sounding tough, they could go after Obama's foolish decision to escalate the war in Afghanistan back in 2009, which remains his biggest foreign policy blunder to date. A brutal reality is that counterinsurgency campaigns almost always produce atrocities. Think My Lai, Abu Ghraib, the Haditha massacre, and now this. You simply can't place soldiers in the ambiguous environment of an indigenous insurgency, where the boundary between friend and foe is exceedingly hard to discern, and not expect some of them to crack and go rogue. Even if discipline holds and mental health is preserved, a few commanders will get overzealous and order troops to cross the line between legitimate warfare and barbarism. There isn't a “nice” way to wage a counterinsurgency—no matter how often we talk about “hearts and minds”—which is why leaders ought to think long and hard before they order the military to occupy another country and try to remake its society. Or before they decide to escalate a war that is already underway. And the sad truth is that this shameful episode would not have happened had Obama rejected the advice of his military advisors and stopped trying to remake Afghanistan from the start of his first term. Yes, I know he promised to get out of Iraq and focus on Central Asia, but no president fulfills all his campaign promises (remember how he was going to close Gitmo?) and Obama could have pulled the plug on this failed enterprise at the start. Maybe he didn't for political reasons, or because commanders like David Petraeus and Stanley McChrystal convinced him they could turn things around. Or maybe he genuinely believed that U.S. national security required an open-ended effort to remake Afghanistan. Whatever the reason, he was wrong. The sad truth is that the extra effort isn't going to produce a significantly better outcome, and the lives and money that we've spent there since 2009 are mostly wasted. That was apparent before this weekend's events, which can only make our futile task even more impossible. Here's what I wrote about this situation back in November 2009: “America's odds of winning this war are slim. The Karzai government is corrupt, incompetent and resistant to reform. The Taliban have sanctuaries in Pakistan and can hide among the local populace, making it possible for them simply to outlast us. Pakistan has backed the Afghan Taliban in the past and is not a reliable partner now. Our European allies are war-weary and looking for the exits. The more troops we send and the more we interfere in Afghan affairs, the more we look like foreign occupiers and the more resistance we will face. There is therefore little reason to expect a U.S. victory.” It didn't take a genius to see this, and I had lots of company in voicing my doubts. It gives me no pleasure to recall it now. Indeed, I wish the critics had been proven wrong and Obama, Petraeus, McChrystal, et al. had been proven right. I concede that the situation in Afghanistan may get worse after we depart, and the more civilians will die at the hands of the Taliban, or as a consequence of renewed civil war. But the brutal fact remains: the United States can't fix that country, it is not a vital U.S. interest that we try, and we should have been gone a long time ago.

GAM Risks Becoming What It Fought - Aguswandi (The Jakarta Globe, 2012)
George Orwell’s classic novel “Animal Farm” is the definitive depiction of how any rebellion or social revolt risks not just failure but a reversal where one type of domination is merely exchanged for another. After the leaders of the animal rebellion take over, they impose a single commandment: “All animals are equal, but some animals are more equal than others.” It is not exactly the same, but recent developments in Acehnese politics are reminiscent of the animal farm. The Aceh Party, which was spawned by the separatist Free Aceh Movement (GAM), is heading in a worrying direction. Internal conflict among former combatants, as well as their desire to dominate the seats of power in the province, is driving Aceh into another phase of uncertainty. If the Aceh Party members continue to behave undemocratically, they will go down in history as nothing more than a ragtag bunch of ignoble former rebels who behaved eerily like their former “enemies.” GAM was an ethnic nationalist movement that mobilized resistance through nationalistic fervor. The roots of the movement were in past injustices, but the conflict later evolved into an antagonistic identity dispute between Aceh and Jakarta. Especially during the New Order, the conflict reached a level where the idea of an independent Aceh became entrenched as a result of endless oppression and unjust treatment. As a movement, GAM took advantage of this. It pledged a promised land where democracy would rule and injustice would be a thing of the past. All of Aceh was dragged by the rebels into this independence narrative and into the lengthy struggle. The rebels in Aceh laid down their arms with the Helsinki peace agreement in 2005. The agreement brought an end to 30 years of war and provided a significant opportunity for the local people to manage their own affairs and participate in a democratic process as Aceh became a special autonomous region. All the trouble in Aceh was supposed to end there. Today, the reality is that it continues, and it is stubborn. The seeds for the current tension were planted with the first gubernatorial election soon after the peace agreement. The leadership of the rebels in exile supported a candidate who was not supported by the majority of former combatants. Ignoring the opinions of the former field commanders, the exiled leaders went ahead with their candidate — who ended up losing by a landslide. The field commanders had used their networks of former combatants to provide strong backing for their candidate. Irwandi Yusuf was elected as the first governor of post-peace agreement Aceh, but his defiant victory upset the exiled leaders. These divided camps seemed to have reconciled in the legislative elections, when the exiled leadership and the field commanders agreed to jointly form a political party called Partai Aceh (Aceh Party) to stand a better chance of winning. The reconciliation bore fruit, with the Aceh Party winning the majority of the seats. Again, the field commanders and their networks provided the crucial machinery to ensure the victory. Winning a majority of the seats in the provincial legislature was supposed to put GAM in full control of the province and close the chapter on the rebellion, but it did not. Another problem was to about to surface. The Aceh Party, which was and is closely controlled by the exiled former leadership, had not forgotten the embarrassment of that first gubernatorial election and began working toward revenge. It started a low-level campaign against their unwanted elected governor, meaning that Aceh’s legislature, since the 2010 elections, has been a legislature that measures its success by how badly it can undermine Irwandi. Most of the policies introduced by the executive arm of the government are constantly being undermined by its legislative arm. This time, the exiled leaders are in full control of the field commanders and legislature members who, by now, mostly pledge loyalty to the Aceh Party. For many field commanders, the Aceh Party is their vehicle to control the province both politically and economically. To achieve that goal, many of them have decided to stick together. This is the struggle that we see playing out today in the run-up to the second gubernatorial election. The Aceh Party supports the former exiled leader Zaini Abdullah and former GAM commander Muzakir Manaf, and refuses to support Irwandi despite the governor’s popularity. To ensure the governor cannot even compete in the election they went so far as to propose a revision of the Election Law to bar independent candidates from running in elections. The dispute over independent candidates was politically motivated, intended to stop Irwandi and many other ex-rebels running in the election. Fortunately, it failed, though only after the Constitutional Court’s decision safeguarded the national law. Had it been successful, this attempt to block independent candidates would have been a reversal of democratic progress for the entire country. It is a nasty game in Aceh, where the players are willing to go so far as to undermine democratic progress and the peace process for their own purposes of retaliation, punishment and control — where all parties are equal, but some are more equal than others.

A North Korean Corleone - Grietens, Sheena Chestnut (New York Times, 2012)
What kind of deal do you make with a 20-something who just inherited not only a country, but also the mantle of one of the world’s most sophisticated crime families? When Kim Jong-un, who is thought to be 28 or 29, became North Korea’s leader in December after the death of his father, Kim Jong-il, he became the de facto head of a mafia state. How the new leader combines the roles of head of state and mafia don will influence the regime’s future behavior. Crime bosses have different incentives, and dealing with them requires different policies. And any deal—including last week’s agreement by North Korea to suspend its nuclear program in exchange for American food aid - will eventually falter if that reality is ignored. Kim Jong-un confronts the same problem faced by every dictator: how to generate enough money to pay off the small group of elite supporters—army generals, party and family—who keep him in power. Other autocrats use oil wealth or parcel out whole industries to cronies. But whoever rules North Korea has less to work with than most. The country defaulted in the 1970s, losing access to international credit, and Soviet subsidies ended with the cold war. In the 1990s, the founder and “eternal president,” Kim Il-sung, died just as a series of natural disasters devastated food production. The country has been an economic and humanitarian basket case ever since. Kim Jong-il, who began training to run the country in the 1970s and inherited it after his father’s death, came up with an unconventional solution: state-sponsored organized crime. Counterfeit cigarettes and medicine, drugs, insurance fraud, fake money, trafficking people and endangered species - for decades, the Kim regime has done it all. Its operations became so extensive and well coordinated that American officials nicknamed it the “Soprano state,” after the hit HBO television series. In the 1970s, after the default, North Korea used diplomats as drug mules to keep embassies running. When that got them kicked out of multiple countries and the economy tanked in the 1990s, Kim Jong-il began producing drugs at home, thereby avoiding a major cost plaguing drug lords elsewhere: law enforcement. He managed these operations through Bureau 39, a mysterious office under the Central Committee of the Korean Workers’ Party. But to create plausible deniability, he outsourced distribution to Russian mafia, Japanese yakuza and Chinese triad gangs, who met North Korean military forces for drug drops at sea. The regime also manufactured the world’s best counterfeit dollars - so good that they reportedly forced the Treasury to redesign the $100 bill - and used a crime ring connected to the Official Irish Republican Army, a Marxist offshoot of the I.R.A., to launder them in Europe. They even made fake Viagra. The Agreed Framework that froze North Korea’s nuclear program in October 1994 didn’t stop these activities; they actually increased. Despite its other benefits, the framework didn’t address the fundamental hard currency needs of the North Korean leadership. This criminal legacy means that Kim Jong-un has even more on his plate than one might think. In addition to running a country that is an economic and humanitarian disaster and a geopolitical hot spot, he also has to manage a global criminal racket. That’s a lot for any 20-something to handle. (As “Sopranos” fans know, A. J.’s taking over for Tony might not have been good for business.) Despite the seemingly stable transition so far, Kim Jong-un is under pressure. Elite party members who supported his father will be skeptical of his untested ability to fulfill his side of their cash-for-support bargain. And North Korea needs more money than usual this year to celebrate the anniversaries of Kim Il-sung and Kim Jong-il. (In the '70s, one of the first things Kim Jong-il used foreign currency for was a campaign to glorify his father.) Any sign that Kim Jong-un can’t satisfy supporters could crack the facade of elite solidarity. What’s an aspiring kingpin to do? First, find the money. Kim Jong-un seems to have done that. One of the last photos released of Kim Jong-il shows him riding a supermarket escalator. Behind him are Kim Jong-un and Jon Il-chun, manager of the infamous Bureau 39. Second, control the people who earn the money. Illicit activity brings the risk of freelancing, especially when you’re forced to let others do the distribution. As North Korea outsourced the drug trade, its profit margins dropped—and more and more insiders skimmed off the system to line their pockets. Today, reports indicate that methamphetamine is widely used in North Korea (partly because it dulls hunger pains), and the state is cracking down on the trade it once monopolized. Even Kim Jong-il couldn’t maintain perfect control and had to send operatives abroad to retrieve misbehaving agents. These are delicate tasks easily botched by a novice. Finally, keep the money coming. Criminal activity was never North Korea’s ultimate objective; the aim was always hard currency. Kim Jong-un needs cash without political conditions to stay in power. But there aren’t many good options for getting it these days, which is why North Korea is likely to pursue new and expanded forms of illicit activity. Criminal activities are attractive because other sources of money have strings attached. Remittances from defectors, which have risen recently, don’t go to leaders, and they let in information. North Korea could bank on economic reform or Chinese aid, but reform won’t necessarily provide money for the elite, and aid makes Pyongyang uneasily dependent on Chinese patronage. The cardinal fear of national security experts—which partly motivated last week’s agreement - is that Pyongyang will make money through nuclear proliferation. After all, North Korea is alleged to have helped build the Syrian nuclear reactor that Israel destroyed in 2007. But it may be hard for North Korea to find a buyer; tests of its plutonium warheads have been a questionable technical success, and their uranium-enrichment program may not be advanced enough to make them an attractive seller. That leaves crime. Last week’s deal does not change the probability that North Korea will engage in it. And new lines of business probably won’t look like the old ones; North Korea’s schemes are creative and highly adaptable. When drugs and counterfeit dollars got too much exposure, the regime shifted toward cigarettes and insurance fraud. Last summer, South Korean authorities discovered North Korea’s involvement in a hacking ring that exploited online gaming sites to win points and exchange them for cash, making $6 million in two years. Given that cybercriminals across the world gross over $100 billion annually, a country with decent cyberwarfare capabilities could probably do well for itself. Or could North Korea go legit? Publicly at least, there haven’t been major seizures of its drugs or counterfeit currency in several years, leading analysts to speculate that targeting the country’s illicit finances successfully crippled those particular earning schemes. And Kim Jong-il’s death does give North Korea an opportunity to get out of the game. BUT legitimacy won’t solve Kim Jong-un’s problem. Right now his survival is guaranteed by hard currency, and the best source of it is illicit activity. That’s why previous American efforts sought to shut off these activities: to convince the regime it had to reform itself to survive. That didn’t go quite far enough. Shutting down those activities works only so long as North Korea can’t find new ones. The key to survival was not any one illicit activity but the ability to adapt from one to another—an ability that, with Kim Jong-il gone, likely rests with just a few trusted people. Those people, their loyalties and their relationships are now Kim Jong-un’s biggest vulnerability. If North Korea loses its capacity to adapt, it will lose the ability to make money illicitly—and will have to choose reform. For America to make successful deals with North Korea, we must first grasp that its leader faces not just a dictator’s problems, but those of a mafia boss. And if you make a deal with the Godfather, you must not overlook the interests of the consigliere standing behind him.

The Strange Career of Voter Suppression - Keyssar, Alexander (NYtimes.com, 2012)
The 2012 general election campaign is likely to be a fight for every last vote, which means that it will also be a fight over who gets to cast one. Partisan skirmishing over election procedures has been going on in state legislatures across the country for several years. Republicans have called for cutbacks in early voting, an end to same-day registration, higher hurdles for ex-felons, the presentation of proof-of-citizenship documents and regulations discouraging registration drives. The centerpiece of this effort has been a national campaign to require voters to present particular photo ID documents at the polls. Characterized as innocuous reforms to preserve election integrity, beefed-up ID requirements have passed in more than a dozen states since 2005 and are still being considered in more than 20 others. Opponents of the laws, mostly Democrats, claim that they are intended to reduce the participation of the young, of the poor and of minorities, who are most likely to lack government-issued IDs—and also most likely to vote Democratic. Conflict over exercising the right to vote has been a longstanding theme in our history. The overarching trend, which we celebrate, has been greater inclusion: property requirements were dropped; racial barriers were formally eliminated; women were enfranchised. Yet there have always been counter trends. While the franchise expanded during some moments and in some places, it contracted in others, depriving Americans of a right they had once held. Between 1790 and 1850 - the period when property requirements were being dropped—four Northern states disenfranchised African-American voters, and New Jersey halted a 17-year experiment permitting women to vote. During this same period, nine states passed laws excluding “paupers” from political rights. After Reconstruction, both major political parties attempted to constrict the electorate, albeit in different locales. In the South—as is well known—Democratic state legislatures employed a variety of devices, including literacy tests, poll taxes, “understanding” clauses and, eventually, Democratic primaries restricted to whites. As a result, African Americans were largely excluded from electoral participation from the 1890s until the 1960s. In the North, similar, if less draconian, legal changes, generally sponsored by Republicans, targeted (among others) the millions of immigrant workers pouring into the country. In 1921, for example, New York State adopted an English-language literacy requirement for voters that remained in force (and was enforced) for decades. Almost invariably, these new limits on the franchise were fueled by partisan interests and ethnic or racial tensions; they were embraced by respectable Americans, like the eminent historian Francis Parkman, who had come to view universal suffrage as a “questionable blessing.” Many of the late nineteenth- and early twentieth-century laws operated not by excluding specific classes of citizens but by erecting procedural obstacles that were justified as measures to prevent fraud or corruption. It was to “preserve the purity of the ballot box” that legislatures passed laws requiring voters to bring their sealed naturalization papers to the polls or to present written evidence that they had canceled their registration at any previous address or to register annually, in person, on one of only two Tuesdays. The new procedures were widely recognized, by both their advocates and their targets, as having a far greater impact on some groups of voters—immigrants, blue-collar workers, the poor—than on others, and they often succeeded. In Pittsburgh in 1906, a personal registration law, sponsored by Republicans to check the influence of a crusading reformer, cut the number of registered voters in half. In the 1930s, “pauper exclusion” laws were invoked to disenfranchise jobless men and women who were receiving relief. In 2000, Massachusetts disenfranchised prisoners after they formed an organization to promote inmate rights. The targets of exclusionary laws have tended to be similar for more than two centuries: the poor, immigrants, African Americans, people perceived to be something other than “mainstream” Americans. No state has ever attempted to disenfranchise upper-middle-class or wealthy white male citizens. The current wave of procedural restrictions on voting, including strict photo ID requirements, ought to be understood as the latest chapter in a not always uplifting story: Americans of both parties have sometimes rejected democratic values or preferred partisan advantage to fair democratic processes. Acknowledging the realities of our history should lead all of us to be profoundly skeptical of laws that burden, or impede, the exercise of what Lyndon B. Johnson called “the basic right, without which all others are meaningless.” More is at stake here than the outcome of the 2012 election. Even a cursory survey of world events over the last 20—or 100—years makes plain that democracies are fragile, that democratic institutions can be undermined from within. Ours are no exception.

Regional Multilateralism: The Next Paradigm in Global Affairs - Mylonas, Harris; Yorulmazlar, Emirhan (CNN World, 2012)
The Cold War and the early post-Cold War periods were relatively easy to define and comprehend. The first was roughly the struggle between two superpowers forming a bipolar system where almost every state had to choose a side. What followed was a period described by Fukuyama as “The End of History” announcing the triumph of liberal ideas. The US was a global hegemon: selecting when to intervene, expanding NATO’s reach, and dominating international institutions. Following the September 11 attacks unilateralism was exposed and thereafter multilateralism appeared—with its limitations. Today, “regional multilateralism” may be the next paradigm that can bring about peace, cooperation, and stability in global affairs. The rise and fall of US hegemony during the 1990s has been documented. The Unipolar moment, a Foreign Affairs article by Charles Krauthammer, encapsulates the main point in the title. It was a moment. Once this “moment” was over, Fareed Zakaria and others have been imagining a “post-American world.” US power and its global role remain at the core of the contemporary discussion. America still is—and probably will remain for a long time—the world’s undisputed leader in military, economic and technological power. However, the politics of austerity at home and pressing realities abroad necessitate a new US foreign policy. The US cannot go it alone. Indeed, the US has been refocusing its foreign policy and Obama has been using the term multilateralism repeatedly. Multilateralism is a prudent strategy for the U.S. and the international system at large, however it is incomplete. Multilateralism has reached its limits when it comes to Iran’s nuclear program, recognition of Palestine, the six party talks on North Korea, and Kosovo’s independence—to name just a few thorny issues. In a world of diminished US involvement and unsuccessful multilateralist endeavors, an alternative vision for global engagement is necessary. Instead we are faced with a reluctant China, an unprepared India, an European Union in the midst of a financial debacle and a host of regional powers that focus on their neighborhood rather than claiming a global role. Given these realities, regional multilateralism can serve as the way out from this dead end. Regionally, the Middle East is as explosive as ever. The Western Balkans are doubtful about their future within the European Union and may again implode. The African continent has many ongoing conflicts and even more potential ones unresolved. In Latin America at least two alternative visions for the region are competing. The Far East is actively searching ways to live with the rise of China. These and other contemporary problems can be better solved at the regional rather than the bilateral or global levels. This context highlights the importance of regional integration and multilateralism. Regional multilateralism is building on these very ideas. Bringing these two together is necessary in today’s world. The buds of regional integration are everywhere in the making but they have not yet been clearly connected with the principles of multilateralism. The EU serves as an example of regional integration and others are following its steps. The African Union has also stepped up its peacekeeping efforts and moved toward further economic integration. However, the quest for regional multilateralism should not be confined by a conventional understanding of geography. For instance, Russia may be a force for stability both in the Far East and Central Asia, China may have a stake in the affairs of Latin America and Africa, and different parts of what we call the Middle East may integrate with parts of Central Asia or Europe. The very prospect of Turkey joining the EU may be a sign of such developments. Cross-regional cooperation is key to regional multilateralism. The transatlantic dialogue model between the US and Europe can and should be exported. For instance, in the Far East the US and the EU both cooperate with ASEAN. China and Russia have extended their ties through the Shanghai Cooperation Organization. This however did not prevent Russia from establishing the Eurasian Union, in a way reclaiming its sphere of influence. The Middle East, on the other hand, is in dire need of broader—albeit imaginative—regional integration. The inability of any one power to confront global challenges will lead responsible powers into the fold of regional multilateralism. The transition will be facilitated if it builds on existing regional integration structures. This way, every state will ultimately become a stakeholder in the international system. For that to happen, regional leaders need to operate as focal points. They need to listen, persuade and inspire insiders, while coordinating with outsiders. This process is different from the traditional spheres of influence system. It is based not on Monroe Doctrine-type of arrangements and coercion but rather on reassuring security umbrellas and mutually beneficial trade blocs. Within this new paradigm, emerging regional leaders—such as China, Russia, India, Japan, Brazil, Turkey, and South Africa—will play a more significant role within their regions while at the same time will take part in cross regional and global issues.

Regional Multilateralism: The Next Paradigm in Global Affairs - Mylonas, Harris (CNN.com, 2012)
The Cold War and the early post-Cold War periods were relatively easy to define and comprehend. The first was roughly the struggle between two superpowers forming a bipolar system where almost every state had to choose a side. What followed was a period described by Fukuyama as “The End of History” announcing the triumph of liberal ideas. The US was a global hegemon: selecting when to intervene, expanding NATO’s reach, and dominating international institutions. Following the 9/11 attacks unilateralism was exposed and thereafter multilateralism appeared—with its limitations. Today, “regional multilateralism” may be the next paradigm that can bring about peace, cooperation, and stability in global affairs. The rise and fall of US hegemony during the 1990s has been documented. The Unipolar moment, a Foreign Affairs article by Charles Krauthammer, encapsulates the main point in the title. It was a moment. Once this “moment” was over, Fareed Zakaria and others have been imagining a “post-American world.” U.S. power and its global role remain at the core of the contemporary discussion. America still is—and probably will remain for a long time - the world’s undisputed leader in military, economic and technological power. However, the politics of austerity at home and pressing realities abroad necessitate a new U.S. foreign policy. The U.S. cannot go it alone. Indeed, the US has been refocusing its foreign policy and Obama has been using the term multilateralism repeatedly. Multilateralism is a prudent strategy for the U.S. and the international system at large, however it is incomplete. Multilateralism has reached its limits when it comes to Iran’s nuclear program, recognition of Palestine, the six party talks on North Korea, and Kosovo’s independence—to name just a few thorny issues. In a world of diminished US involvement and unsuccessful multilateralist endeavors, an alternative vision for global engagement is necessary. Instead we are faced with a reluctant China, an unprepared India, an European Union in the midst of a financial debacle and a host of regional powers that focus on their neighborhood rather than claiming a global role. Given these realities, regional multilateralism can serve as the way out from this dead end. Regionally, the Middle East is as explosive as ever. The Western Balkans are doubtful about their future within the European Union and may again implode. The African continent has many ongoing conflicts and even more potential ones unresolved. In Latin America at least two alternative visions for the region are competing. The Far East is actively searching ways to live with the rise of China. These and other contemporary problems can be better solved at the regional rather than the bilateral or global levels. This context highlights the importance of regional integration and multilateralism. Regional multilateralism is building on these very ideas. Bringing these two together is necessary in today’s world. The buds of regional integration are everywhere in the making but they have not yet been clearly connected with the principles of multilateralism. The EU serves as an example of regional integration and others are following its steps. The African Union has also stepped up its peacekeeping efforts and moved toward further economic integration. However, the quest for regional multilateralism should not be confined by a conventional understanding of geography. For instance, Russia may be a force for stability both in the Far East and Central Asia, China may have a stake in the affairs of Latin America and Africa, and different parts of what we call the Middle East may integrate with parts of Central Asia or Europe. The very prospect of Turkey joining the EU may be a sign of such developments. Cross-regional cooperation is key to regional multilateralism. The transatlantic dialogue model between the US and Europe can and should be exported. For instance, in the Far East the U.S. and the EU both cooperate with ASEAN. China and Russia have extended their ties through the Shanghai Cooperation Organization. This however did not prevent Russia from establishing the Eurasian Union, in a way reclaiming its sphere of influence. The Middle East, on the other hand, is in dire need of broader—albeit imaginative—regional integration. The inability of any one power to confront global challenges will lead responsible powers into the fold of regional multilateralism. The transition will be facilitated if it builds on existing regional integration structures. This way, every state will ultimately become a stakeholder in the international system. For that to happen, regional leaders need to operate as focal points. They need to listen, persuade and inspire insiders, while coordinating with outsiders. This process is different from the traditional spheres of influence system. It is based not on Monroe Doctrine-type of arrangements and coercion but rather on reassuring security umbrellas and mutually beneficial trade blocs. Within this new paradigm, emerging regional leaders—such as China, Russia, India, Japan, Brazil, Turkey, and South Africa—will play a more significant role within their regions while at the same time will take part in cross regional and global issues.

Interview with Michèle Lamont and Nissim Mizrachi: Special Issue of Ethnic and Racial Studies - Lamont, Michèle; Mizrachi, Nissim (Taylor and Francis, 2012)

Interview with Shinju Fujihira: Japan’s Party Politics and Foreign Policy - Fujihira, Shinju (Asahi Shimbun, 2012)
Interview on 02/06/2012 with Shinju Fujihira, Associate Director, Program on U.S.-Japan Relations in the Asahi Shimbun.

The Real Grand Bargain, Coming Undone - Keyssar, Alexander (The Washington Post, 2011)
Despite all the recent talk of “grand bargains,” little attention has been paid to the unraveling of a truly grand bargain that has been at the center of public policy in the United States for more than a century. That bargain—which emerged in stages between the 1890s and 1930s—established an institutional framework to balance the needs of the American people with the vast inequalities of wealth and power wrought by the triumph of industrial capitalism. It originated in the widespread apprehension that the rapidly growing power of robber barons, national corporations and banks (like J.P. Morgan’s) was undermining fundamental American values and threatening democracy. Such apprehensions were famously expressed in novelist Frank Norris’s characterization of the nation’s largest corporations—the railroads—as an “octopus” strangling farmers and small businesses. With a Christian rhetorical flourish, William Jennings Bryan denounced bankers’ insistence on a deflationary gold standard as an attempt to “crucify mankind upon a cross of gold.” A more programmatic, and radical, stance was taken by American Federation of Labor convention delegates who in 1894 advocated nationalizing all major industries and financial corporations. Hundreds of socialists were elected to office between 1880 and 1920. Indeed, a century ago many, if not most, Americans were convinced that capitalism had to be replaced with some form of “cooperative commonwealth”—or that large corporate enterprises should be broken up or strictly regulated to ensure competition, limit the concentration of power and prevent private interests from overwhelming the public good. In the presidential election of 1912, 75 percent of the vote went to candidates who called themselves “progressive” or “socialist.” Such views, of course, were vehemently, sometimes violently, opposed by more conservative political forces. But the political pressure from anti-capitalists, anti-monopolists, populists, progressives, working-class activists and socialists led, over time, to a truly grand bargain. The terms were straightforward if not systematically articulated. Capitalism would endure, as would almost all large corporations. Huge railroads, banks and other enterprises—with a few exceptions—would cease to be threatened with nationalization or breakup. Moreover, the state would service and promote private business. In exchange, the federal government adopted a series of far-reaching reforms to shield and empower citizens, safeguarding society’s democratic character. First came the regulation of business and banking to protect consumers, limit the power of individual corporations and prevent anti-competitive practices. The principle underlying measures such as the Sherman Antitrust Act (1890), the Pure Food and Drug Act (1906) and the Glass-Steagall Act (1933)—which insured bank deposits and separated investment from commercial banking—was that government was responsible for protecting society against the shortcomings of a market economy. The profit motive could not always be counted on to serve the public’s welfare. The second prong of reform was guaranteeing workers’ right to form unions and engage in collective bargaining. The core premise of the 1914 Clayton Act and the National Labor Relations Act of 1935—born of decades of experience—was that individual workers lacked the power to protect their interests when dealing with large employers. For the most poorly paid, the federal government mandated a minimum wage and maximum hours. The third ingredient was social insurance. Unemployment insurance (1935), Social Security (1935), and, later, Medicaid and Medicare (1965) were grounded in the recognition that citizens could not always be self-sufficient and that it was the role of government to aid those unable to fend for themselves. The unemployment-insurance program left unrestrained employers’ ability to lay off workers but recognized that those who were jobless through no fault of their own (a common occurrence in a market economy) ought to receive public support. These measures shaped the contours of U.S. political and economic life between 1940 and 2000: They amounted to a social contract that, however imperfect, preserved the dynamism of capitalism while guarding citizens against the power imbalances and uncertainties that a competitive economy produces. Yet that bargain—with its vision of balance between private interests and public welfare, workers and employers, the wealthy and the poor—has been under attack by conservatives for decades. And the attacks have been escalating. The regulation of business is decried now, as it was in 1880, as unwarranted interference in the workings of the market: Regulatory laws (including antitrust laws) are weakly enforced or vitiated through administrative rule-making; regulatory agencies are starved through budget cuts; Glass-Steagall was repealed, with consequences that are all too well known; and the financial institutions that spawned today’s economic crisis - by acting in the reckless manner predicted by early twentieth-century reformers—are fighting further regulation tooth and nail. Private-sector employers’ fierce attacks on unions since the 1970s contributed significantly to the sharp decline in the number of unionized workers, and many state governments are seeking to delegitimize and weaken public-sector unions. Meanwhile, the social safety net has frayed: Unemployment benefits are meager in many states and are not being extended to match the length of the downturn; Republicans are taking aim at Medicaid, Medicare, Social Security and Obamacare. The real value of the minimum wage is lower than it was in the 1970s. These changes have happened piecemeal. But viewed collectively, it’s difficult not to see a determined campaign to dismantle a broad societal bargain that served much of the nation well for decades. To a historian, the agenda of today’s conservatives looks like a bizarre effort to return to the Gilded Age, an era with little regulation of business, no social insurance and no legal protections for workers. This agenda, moreover, calls for the destruction or weakening of institutions without acknowledging (or perhaps understanding) why they came into being. In a democracy, of course, the ultimate check on such campaigns is the electoral system. Titans of industry may wield far more power in the economic arena than average citizens, but if all votes count equally, the citizenry can protect its core interests—and policies—through the political arena. This makes all the more worrisome recent conservative efforts to alter electoral practices and institutions. Republicans across the nation have sponsored ID requirements for voting that are far more likely to disenfranchise legitimate (and relatively unprivileged) voters than they are to prevent fraud. Last year, the Supreme Court, reversing a century of precedent, ruled that corporate funds can be used in support of political campaigns. Some Tea Partyers even want to do away with the direct election of senators, adopted in 1913. These proposals, too, seem to have roots in the Gilded Age—a period when many of the nation’s more prosperous citizens publicly proclaimed their loss of faith in universal suffrage and democracy.

A Eulogy for Financier Ted Forstmann - Ferguson, Niall (The Daily Beast, 2011)
Some of you knew Ted Forstmann much better than I did. Most of you knew him much longer. When Ted’s family and closest colleagues asked me to join Mayor Bloomberg and Charlie Rose in offering a eulogy to Ted, I must admit I was hesitant, not to mention humbled. What could be more presumptuous than for a British-born professor to try to do justice to one of the great American capitalists? And then I remembered the side of Ted that I suspect relatively few of you saw. Teddy the philosopher. Teddy, my coauthor. When I heard the news of Ted’s death—which we’d been dreading for weeks—my first thought was: he was the most American American I’ve ever known. Financier. Fun lover. Philanthropist. And a man who couldn’t abide cant—in both senses. Cant in the sense of insincere humbug. And can’t in the sense of “this can’t be done.” And yet there was another side to Ted that was a little less classically all-American. He was, after all, a single parent. He was a man for whom the color line—for so long this country’s curse - was simply not visible. He was also a matchmaker: a Cupid with a Gulfstream 5 instead of wings. He took a fatherly interest in my romance with Ayaan, whom he did so much to help after she was forced to leave the Netherlands, and who can’t be here for the very excellent reason that she’s about to give birth to our son. Ted was one of those people who didn’t advise her against me, and I’ll be grateful for that until the day I die. What I really want to remember today, however, is Ted’s secret life as an intellectual. Ted was no ordinary master of the financial universe. He saw things differently. He was what the Germans call a Querdenker, which the English “lateral thinker” doesn’t quite translate. . From the moment we met, he and I talked about his fears for this country’s financial and political system. He had shared my foreboding about the excesses of the early 2000s. And he also shared my fear that when the crisis struck, people would leap to the wrong conclusions. In a piece we wrote together for The Wall Street Journal back in April of last year, we made an argument that I believe still holds good: that in a mood of legitimate public anger at the consequences of the crisis, this country is drawing the wrong conclusions about its causes. Unlike many people in the financial world, Ted Forstmann was not afraid to criticize Wall Street. (It was I who had to tone down his invective.) But what Ted dreaded was that the backlash that was bound to follow the crisis would lead to precisely the hypertrophic regulation we now see emerging over literally thousands of pages - as well as to demagogic calls for redistribution via higher tax rates and expanded federal programs. Ted was convinced that any new regulation should focus strictly on excess leverage and the derivatives markets. Those, for him, were the root causes of the crisis. With Ronald Reagan, he also passionately believed that enlarging the government was not the answer to the problem; often, it was the problem. That was why he wanted to see more disadvantaged kids going to private schools. His ideal was social mobility, not state-mandated equality. In this, as in so many ways, Ted was very wise. A couple of years ago, two of my kids had the privilege of having lunch with Ted at one of his favorite restaurants, Harry Cipriani, just nine blocks from here. Last weekend I asked my younger son, who’s now 12, if he remembered the conversation. He did. Ted’s advice was this: “Don’t do the obvious thing. Don’t follow in anybody’s footsteps. Look around you and figure out what’s needed, what’s missing. Then do that.” I hope my son heeds that advice. I hope his whole generation heeds it. I know, Everest and Siya, that you will. I admit I was surprised by my own reaction to the news of his death. My first thought was: oh, no, now I won’t be able to ask Ted what he thinks anymore. What he thinks about the economy. What he thinks about politics. I won’t be able to get his take on the presidential candidates. And suddenly I felt really bereft. That morning I had to write a column for Newsweek. I couldn’t help myself: I just sat down and addressed it directly to him. What’s your take, Ted? As I was writing it—and boy, did the words flow—I realized just how much I am going to miss his wisdom. Because I could never predict what Ted’s take would be. To a pedestrian, risk-averse academic like me, the way he thought about the world was full of surprises—and always illuminating ones. Ted, you were in many ways the most American of Americans. You were the quintessential doer. But you were also a thinker. And we really do miss the unique way you thought. Wisdom is in short supply these days. You took so much with you when you left us.

Obama Team’s Al-Awlaki Memo Furthered Bush Legacy - Feldman, Noah (Bloomberg View, 2011)
Killing terrorists with drones is great politics. To the question, “Is it legal?” a natural answer might well be, “Who cares?” But the legal justifications in the war on terrorism do matter - and not just to people who care about civil liberties. They end up structuring policy. As it turns out, targeted killing, now the hallmark of the Barack Obama administration’s war on terrorism, has its roots in rejection of the legal justifications once offered for waterboarding prisoners. The leaking of the basic content (but not the text) of an Obama administration memo authorizing the drone strike that killed US citizen Anwar Al-Awlaki therefore calls for serious reflection about where the war on terrorists has been - and where it is headed next. The George W. Bush administration’s signature anti-terror policy after the September 11 attacks (apart from invading countries) was to capture suspected terrorists, detain them, and question them aggressively in the hopes of gaining actionable intelligence to prevent more attacks. In the Bush years, after the CIA and other agencies balked at the interrogation techniques being urged by Vice President Dick Cheney, the White House asked the Department of Justice to explain why the most aggressive questioning tactics were legal. Lawyers at the Office of Legal Counsel—especially John Yoo, now a professor at the University of California at Berkeley—produced secret memos arguing that waterboarding wasn’t torture. The Torture Memos What was more, the memos maintained, it didn’t matter if it was torture or not, because the president had the inherent constitutional authority to do whatever was needed to protect the country. Some of the documents were leaked and quickly dubbed “the torture memos.” A firestorm of legal criticism followed. One of the most astute and outraged critics was Marty Lederman, who had served in the Office of Legal Counsel under President Bill Clinton. With David Barron, a colleague of mine at Harvard, Lederman went on to write two academic articles attacking the Bush administration’s theories of expansive presidential power. Eventually, Jack Goldsmith, who led the Office of Legal Council in 2003–2004 (and is now also at Harvard), retracted the most extreme of Yoo’s arguments about the president’s inherent power. In the years leading to the 2008 election, all this technical criticism of the Bush team’s legal strategy merged with domestic and global condemnation of the administration’s detention policies. The Supreme Court weighed in, finding that detainees were entitled to hearings and better tribunals than were being offered. As a candidate, Obama joined the bandwagon, promising to close the prison at Guantanamo Bay, Cuba, within a year of taking office. Guantanamo is still open, in part because Congress put obstacles in the way. Instead of detaining new terror suspects there, however, Obama vastly expanded the tactic of targeting them, with eight times more drone strikes in his first year than in all of Bush’s time in office. Barron and Lederman, the erstwhile Bush critics, were appointed to senior positions in the Office of Legal Counsel—where they wrote the recent memo authorizing the Al-Awlaki killing. What explains these startling developments? If it’s illegal and wrong to capture suspected terrorists and detain them indefinitely without a hearing, how exactly did the Obama administration decide it was desirable and lawful to target and kill them? The politics were straightforward. Obama’s team observed that holding terror suspects exposed the Bush administration to harsh criticism (including their own). They wanted to avoid adding detainees at Guantanamo or elsewhere. A Father’s Appeal Dead terrorists tell no tales—and they also have no lawyers shouting about their human rights. Before Al-Awlaki was killed, his father sued the government for putting the son on its target list. The Obama Justice Department asked the court to dismiss the claim as being too closely related to government secrets. The court agreed—a result never reached in all the Guantanamo litigation. Anwar Al-Awlaki now has no posthumous recourse. In the bigger picture, Obama also wanted to show measurable success in the war on terrorism while withdrawing troops from Iraq and Afghanistan. But even here the means were influenced by legal concerns. Osama bin Laden is the best example. One suspects that the US forces who led the fatal raid in Abbottabad almost certainly could have taken him alive. But detaining and trying him would probably have been a political disaster. So they shot him on sight, as the international law of war allows for enemies unless they surrender. The authority for targeted killing—as expressed in the Lederman-Barron memo—offers the legal counterpart to the political advantages of the Obama targeting policy. According to the leaks, the memo holds that the U.S. can kill suspected terrorists from the air not because the president has inherent power, but because Congress declared war on Al-Qaeda the week after the September 11 attacks. The logic is that once Congress declares war, the president can determine whom we are fighting. The president found that Yemen-based Al-Qaeda in the Arabian Peninsula, which didn’t exist on September 11, had joined the war in progress. He determined that Al-Awlaki was an active member of the Yemeni groups with some role in planning attacks. And, the memo says, it’s not unlawful assassination or murder if the targets are wartime enemies. From a formal legal standpoint, Lederman and Barron can claim consistency with their attacks on the Bush administration. They relied on Congress and international law; Yoo’s “torture memos” didn’t. But this argument misses the more basic point: Most critics rejected Bush’s policies not on technical grounds based on the Constitution, but because they thought there was something wrong with the president acting as judge and jury in the war on terrorism. No Defense Allowed Anwar al-Awlaki was killed because the president decided he was an enemy. Like the Bush-era Guantanamo detainees, he had no chance to deny this—even when his father tried to go to court while he was still alive. Naturally, a uniformed soldier in a regular war also wouldn’t get a hearing. But like the Guantanamo detainees, Al-Awlaki wore no uniform. Nor was he on a battlefield, except according to the view that anywhere in the world can be the battlefield in the war on terrorism. Al-Awlaki might have maintained that he was merely a jihadi propagandist exercising his free speech rights as a U.S. citizen. Which might well have been a lie. Yet we have only the president’s word that he was an active terrorist—and that is all we will ever have. The future direction of the policy is therefore clear: Killing is safer, easier and legally superior to catching and detaining. Sitting beside Al-Awlaki when he was killed was another US citizen, Samir Khan, who was apparently a full-time propagandist, not an operational terrorist. Khan was, we are told, not the target, but collateral damage—a good kill under the laws of war. Legal memos are weapons of combat—no matter who is writing them.

Romney to the Rescue - Ferguson, Niall (The Daily Beast, 2011)
This column is for Ted Forstmann: financier, fun lover, and philanthropist, who died on Nov. 20. But it’s not just for him. It’s to him. Ted, I’m worried. I wish you were still around to help me get this right. The US is going nuts with populism. That’s always to be expected after a big financial crisis, I know. But this is dysfunctional. On one side, there are conservative fundamentalists—the Tea Party—who think we can turn the clock back to before the New Deal, if not further. Some of them want to get rid not just of the Federal Reserve but of most of the federal government itself. I have more sympathy with these Teapopulists than with the other lot, the motley crew who want to Occupy Wall Street (call them the Occupopulists). But when it comes to practical politics, this Tea Party has more in common with the Mad Hatter’s than Boston’s. To begin with, they’ve created a mood in the Republican Party that makes any kind of compromise on our fiscal crisis impossible. We just saw the ignominious failure of the supercommittee, which was supposed to come up with a plan to reduce the deficit. Predictably, each party blames the other side for this flop. Either way, the consequences are dire. First, the markets are spooked, just the way they were by the partisan dogfight over the debt ceiling earlier this year. Second, the country is now on course for more drastic spending cuts in 2013, which could not only slash our defense budget in an irresponsible way but also plunge the economy back into recession. There’s another problem. Just like the populists of a century ago, the Teapopulists are drawn compulsively to disastrous presidential wannabes. I never asked you what you thought of Mitt Romney, Ted. But I am sure you’d prefer him over the other contenders. Bachmann, Perry, Cain, Gingrich—the one thing these people have in common is that they would lose to Barack Obama next year even if the unemployment rate were twice what it is now. Their appeal to the crucial center—to the independents and the undecided—is just too low. What’s the case against Romney? That he’s a Mormon? Ted, you were a devout Catholic, just as I am a doubting atheist. But this is America. Religion and government are separate. And we tolerate all faiths, no matter how idiosyncratic, provided they tolerate ours too. That he’s changed his mind on hot-button issues? Well, so does any intelligent person. You often did. What is this, a dogmatism contest?

Addressing ‘the Kurdish Question’ - Martin, Lenore G. (New York Times, 2011)
It is obvious that the Turkish foreign minister Ahmet Davutoglu’s “zero problems with the neighbors” policy no longer works, in the face of Turkey’s support for the Syrian defectors who oppose the Assad regime. The foreign minister must now deal with potentially hostile reactions by Syria and its closest ally, Iran, that could have destabilizing regional implications. Iran, for one, cannot afford to allow the Assad regime to fail. It provides Iran with a foothold in the Levant from which to support Hezbollah and threaten Israel on its Lebanese border. Syrian and Iranian retaliation against Turkey can readily take the form of support for the Kurdistan Worker’s Party, or P.K.K. This group once again has become increasingly violent in its promotion of Kurdish separatism in the Turkish southeast. Syria, Iran and Turkey share a common cause in resisting demands by Kurdish opposition movements in their countries. Only months ago, all three were cooperating in suppressing the P.K.K. For Turkey, this was a welcome change from the 1990s, when Syria and Iran supported the P.K.K. in order to pressure Ankara for foreign policy concessions. Now Damascus and Tehran could again play the P.K.K. card. To counteract potential Syrian and Iranian subversion and the separatist appeals of the P.K.K., Turkey needs to adapt its zero problems policy to its own southeast. In 2009, the prime minister, Recep Tayyip Erdogan announced a “Kurdish opening”—a bid at reconciliation with Turkey’s Kurds. However, he quickly closed it, leaving many Kurdish demands for economic development, political rights and cultural recognition unanswered. The Turkish foreign minister’s recent veiled threat to send troops across the Syrian border may be insufficient to deter Syria and Iran from subversively supporting the P.K.K. For a comprehensive resolution of the “Kurdish question,” Ankara also needs to implement effective policies that will over the long term improve the economic, political, and cultural life of Turkey’s Kurds.

What Really Went Wrong in Greece? - Mylonas, Harris (CNN.com, 2011)
After reading about the Greek debt crisis for over a year now, you might think you understand what it’s all about. You’re probably wrong. International media focus on how the Greek government and people spend their money. But an equally important problem is the inability of the Greek state to collect revenues. The story constantly aired by various news outlets is simple enough. Greece, we are told, free-rode on the security offered by the rest of Europe to attract money from foreign investors, and then spent it lavishly on its bloated public sector. In case you don’t get it, BBC’s website has a recurring instructional slide show titled “What went wrong in Greece?” Apparently, Greece’s adoption of the euro “made it easier for the country to borrow money.... Greece went on a big, debt-funded spending spree, including paying for high-profile projects such as the 2004 Athens Olympics.” This brief media lesson on Greek economics has proven very appealing to audiences abroad for two reasons. First, it rhymes with the stereotype of lazy Mediterranean people conning their hard-working North European partners and then shamelessly asking for a bailout. (Now that Italy may be heading the same way, there will be more of this coming.) It also resonates in the ears of the euro’s sworn opponents, above all in the UK. Unfortunately, it is only half the story. Greek public debt as a percentage of GDP did not dramatically rise right after Greece joined the euro. Greek debt actually accumulated back in the 1980s and early 90s, years before Europe got its common currency. The size of the Greek public sector (as a percentage of GDP or share of the labor market) is around or even below average compared to the rest of Europe. Greece did try to spend its way out of the global recession in 2008-2009 and ran large deficits; but so did most other developed countries, including the UK and the US. There are two sides of the public finance coin: expenditure and revenue. What is left out is that while Greek public spending and debt crept up, government revenue fell or remained constant in the years after Greece adopted the euro. Between 2001 and 2007 Greece’s average government revenues totaled 39.4% of GDP, whereas the EU average was 44.4%. Taxes are by far the largest component of government revenue. The issue is not unique to Greece. Declining tax revenues were observed in Ireland, Spain, and in the US after the Bush tax cuts kicked in. In Greece the culprit has been rampant tax evasion by corporations owing millions in taxes and self-employed professionals who can hide their earnings, unlike salaried employees and pensioners. Under international pressure to balance its budget, the outgoing Greek government axed salaries and pensions and slapped new taxes on the bulk of citizens who were not tax-delinquent. This only drove the country deeper into recession and insolvency, making it necessary for EU leaders to write off part of Greece’s debt in July and then again in October. Whether the government is reluctant to tax the very wealthy (as in the US) or lax in its duty to punish tax evasion (as in Greece), the results are similar. Revenues can’t keep up with expenditures and lenders become uneasy. Meanwhile, those who are taxed too leniently have an interest in shifting public attention towards cutting government spending. The bitter partisan quarrels in Washington and Athens lately have this much in common. Yet, this obvious point is conspicuously absent from reports on Greece in the English-speaking world. There is no denying that Greece overspent on security for its Olympics - they were the first games after 9/11. There is also no denying that the Greek public sector is very inefficient. But this has to do with how the money is used. Deep cuts will not make an inefficient public sector better. Other reforms, however, just might. Finally, there is no denying that the euro deprived Greece of the flexibility to devaluate its currency. However, Greece’s revenue collection problem has been perennial and is unrelated to the euro. The first reforms Greece’s new government should focus on are the tax and judicial systems. Casting the crisis ravaging Greece and closing in on Italy as a fundamental story of governments drunk on loans, doling out stacks of euros to their shortsighted citizens is a half-truth. It makes it easy to caricature on a national basis and to categorize Greeks, Italians, Germans or Americans as people who collectively live either within or beyond their means. It also masks the fact that there are differences within each country: Those who benefit the most from high-profile government contracts are the hardest ones to tax when the creditors come banging on your door.

Are Greece's Leaders Being Reckless or Bold? - Mylonas, Harris (CNN.com, 2011)
Call it reckless, call it bold, but the Greek Prime Minister, George Papandreou, has attempted to transform a referendum on the European Union bailout plan for Greece into a referendum about whether the Greeks want to stay in the Eurozone or not. The last time Greece had a popular referendum was in 1974 to decide if the people wanted to keep King Constantine, a descendent of the Royal family that European Powers foisted on the Greek people in the 1860s. This time around, the Greek Prime Minister has shocked the rest of Europe—and even his own Vice President—with his plans to call for a popular vote on whether to accept the 50% haircut deal that EU heads of state agreed on last week to manage the country’s spiraling debt crisis. It’s the latest in a series of Hail Mary passes by Papandreou to keep his hold on power, but the proposed referendum is really only a distraction from the no-confidence vote he faces, which is scheduled in Greek Parliament this Friday. As hard as the Europeans leaders may have fought to prevent a Greek default, they failed to take into account the dire state of domestic Greek politics. But even at this moment the solution to the crisis must be a European one. The gravest threat facing Papandreou right now is from the Greek people. His government party, PASOK, was elected two years ago on an anti-austerity platform, but has since been forced into the position of calling for more austerity than any Greek government in the postwar era. The demonstrations across the country last weekend that disrupted the parades commemorating the Greek resistance in World War II culminated with the forced departure of the President of the Republic, Karolos Papoulias, from the parade in Thessaloniki. The current political system has been facing a legitimacy crisis for a while now. The social contract, based on patronage, established between Greek politicians and the electorate following the fall of the Greek Junta in 1974 is under severe strain. The second problem facing Papandreou is the dissent and distrust he is experiencing from his own party, which—for the moment—holds a bare majority of 152 seats out of 300 in the Greek Parliament. This past summer in a cabinet reshuffling, Papandreou tried to smooth out the problems in his party by appointing his main internal rival, Evangelos Venizelos, Vice President. But this accommodation reached its breaking point yesterday when Venizelos declared he had not been informed about the referendum by Papandreou, who nevertheless called on him to deliver the bad news to EU leaders. Meanwhile, the opposition parties claim that the government is blackmailing the Greek people and suggest that the only solution is to have early elections. The crisis of legitimacy reached its peak yesterday when rumors about tensions between the government and the military leadership of the country became credible when the minister of Defense called for the replacement of all the heads of divisions of the armed forces. It would be a controversial decision in the best of times, but one that’s nearly impossible to carry out for a government facing unprecedented unpopularity. The European Union leaders are dead against three outcomes: the collapse of the Greek parliament, the ouster of Papandreou on Friday, and the negative result of any kind of referendum on the bailout—all of which would ultimately spell the ejection of Greece from the Eurozone and spur financial chaos on the continent. The solution must come from Europe. The meeting at Cannes Thursday—where Papandreou has been invited by Merkel and Sarkozy—is his last chance to appease his European patrons. The real question is not whether Greece will proceed or not with the referendum, but rather who controls Europe? Is it the Germans who seem to be the only ones who can undo the European Central Bank policy about printing money? The French and the Germans together who want to keep the Euro strong? Is it the speculators, banks and their interests? Or is the EU open to more democratic control whereby the voters can have a voice? Whatever the outcome, Greece is now up against the wall thanks to Papandreou. The predicament has suddenly changed from a financial catastrophe and austerity measures to a question about political identity: Do Greeks belong in the European Union or not?

Greece's Legitimacy Crisis - Mylonas, Harris; Meaney, Thomas (CNN.com, 2011)
In the past 48 hours, Greek Prime Minister George Papandreou has succeeded in one thing: Stirring up the anger of nearly everyone around him. The European Union, his own party PASOK, the opposition party New Democracy and the Greek electorate are all pitted against Papandreou. The Greeks have a word for this special brand of rage—they call it “thymos.” This refers to the simmering resentment that arises when one's views are not recognized. It’s little wonder Papandreou has had to back down from his initial call for a national referendum on the 50% haircut deal decided by the European Union heads of state on October 27. First off, he failed to get the opposition to agree to the referendum. They called it blackmail, denounced Papandreou as an opportunist and asked for a grand coalition government or immediate elections. Main opposition leader Antonis Samaras’ consensus on Thursday was short-lived and with many conditions. Meanwhile, the European leaders—French President Nicolas Sarkozy and German Chancellor Angela Merkel—called Papandreou’s bluff. 'Go ahead and make our day,' they told him. “Imagine what would happen if we called a referendum on the bailout in our countries?' The International Monetary Fund, for its part, threatened to freeze all of its loans to Greece. Finally, for Papandreou’s party PASOK the situation is even more dire. Instead of shoring up support from his own party members, the referendum only emboldened cries for his resignation—including from his own Ministers and PASOK Parliamentarians. Papandreou has recalled his decision for a referendum because he failed in all fronts and it’s become clear that he can no longer be part of the solution. There are three possible ways the crisis will play out. First, Papandreou could refuse to resign and possibly win the no-confidence vote Friday. This is unlikely since his overall support has reached its all-time low. The second, more likely scenario is that Papandreou loses the vote tomorrow and the President of the Hellenic Republic, Karolos Papoulias, turns to the other political party leaders to determine if the existing Parliament could form a government. The final scenario, if these efforts fail to build a government, would be new elections, as called for by the Greek Constitution. But it is most likely that a one-party government will not emerge from these elections. The only way out of these three scenarios is to form a Grand Coalition government. What is a Grand Coalition government? In multi-party parliamentary systems, sometimes one-party governments cannot form. In such instances, coalition governments are often formed including more than one party in order to secure a Parliamentary majority, manage to form a government and pass legislation. Greece’s history with such governments in the late 1980s does not exactly inspire faith, and the global stakes were smaller then. A grand coalition would entail the cooperation of all the political parties that are in favor of a European future for Greece. They would be ready to support the austerity measures needed to balance the Greek budget and overcome the solvency problem, but most importantly they would be the the parties that can agree on the composition of such a government. This last feature of a Grand Coalition is particularly valuable at a time when consensus-building in the Greek parliament has become nearly impossible. What remains left out of this discussion is the Greek people. They voted two years ago for a party running on an anti-austerity platform and this is not what they received. Perhaps the current political system is afraid to hear their message. "Thymos" may not be the best state of mind to make choices. Regardless, the Greek political leadership's ownership of the austerity program and responsible governance are necessary steps toward resolving Greece's legitimacy crisis, which would then allow them to confront the Greek people with the responsibility they must take in order to end the financial crisis.

What Egypt Means for the US - Allison, Graham T., Jr. (The Mark, 2011)
What do the recent events in Egypt mean for the US? The answer is a lot more complicated than it might seem. Egypt is important to the US for a number of reasons. Topping the list is oil, and the flow of oil, for which the Suez Canal is an important transit conduit. There is no reason to believe that a successor to the Mubarak government would interrupt the flow of oil, but you could imagine events in the area that could interrupt the flow, and we’re seeing this concern reflected in the markets. There is also the concern that what is happening in Egypt is contagious, and that it could lead to instability in other, seemingly analogous states—the most important of which is Saudi Arabia. There are regions in which the governments seem very sclerotic, the people running them seem old, the youth vote seems large, and the number of educated citizens who don’t seem adequately challenged seems to be growing. Such elements characterize quite a number of states in the region, including those that are important to the US for various reasons. Egypt has been a major ally of the US when it comes to relations with Israel, where the resulting peace, though cold, has created a stable border, and is thus considered one of the great achievements of the last many decades. In the role of counterterrorism, Egypt has been a significant and cooperative ally on questions about Hamas, al-Qaida, or Hezbollah. Finally, with respect to governance, Egypt is dealing with an autocratic regime that significantly restricts the political rights of the population. This has been a problem for the US, as it directly conflicts with American objectives and rhetoric. Nevertheless, such issues are of a lesser concern in the hierarchy of interests, as things like oil attract greater attention. I suspect that peaceful relations between Egypt and Israel would be sustained. A new Egyptian government of any stripe will have so much to do that it will not want to take on any additional problems. On the other hand, Egypt’s current mix finds organized groups like the Muslim Brotherhood. The Brotherhood’s recent statements have been more internationally acceptable, but traditionally they have had quite strong and different views with respect to Israel. As you can imagine, if a Muslim Brotherhood group emerges after whatever process of transition Egypt undergoes, such a group might maintain a contrary view. The best way to think about the issue is to consider alternative futures. One possibility is that Mubarak and the current regime will survive. I’d say this is very unlikely, though, with only about a five to ten percent chance of happening. A second possibility is that a transitional process will take place, resulting in an emerging democratic government. I’d say that this second alternative is the most hopeful, but not the most likely scenario. Another scenario features a tumultuous process in which a more or less participatory and democratic system emerges. If this scenario were to play out, I would bet on the most organized groups emerging as leaders. In this case, the most organized group is the military, which means that we would see the emergence of a military-dominated regime with a civilian face. That would be a good outcome as far as the US is concerned. A variation of that scenario is the possibility that the Muslim Brotherhood could step up to take control of the government, an outcome that would present its own opportunities and risks. The key idea that we should take away from this is that future developments are uncertain, and that it is entirely possible to describe an outcome that looks more like Iran —though I don’t think such an outcome is likely. Think about Ayatollah Khomeini in Paris until the Iranian revolution, Lenin going home to Russia in a single-carriage train. True, those situations weren’t exactly like the one happening now, but history reminds us that outcomes are often quite different from the ones people anticipate—and that looking at the aspirations that have spurred a revolution is hardly a good way to predict what the outcomes will actually be.

The Costs of America’s Choices - Allison, Graham T., Jr. (Boston Globe, 2011)
America's last 10 years might be called “The Decade the Locusts Ate.’’ A nation that started with a credible claim to lead a second American century lost its way after the terrorist attacks of September 11, 2001. Whether the nation will continue on a path of decline, or, alternatively, find our way to recovery and renewal, is uncertain. The nation began the decade with a growing fiscal surplus and ended with a deficit so uncontrolled that its AAA credit rating was downgraded for the first time in its history. Ten years on, Americans’ confidence in our country and the promise of the American Dream is lower than at any point in memory. The indispensable superpower that entered the decade as the most respected nation in the world has seen its standing plummet. Seven out of every 10 Americans say that the United States is worse off today than it was a decade ago. While many of the factors that contributed to these developments were evident before 9/11, this unprecedented reversal pivots on that tragic day - and the choices made in response to it. Those choices had costs: the inescapable costs of the attack, the chosen costs, and the opportunity costs. Inescapable costs of 9/11 must be counted first in the 3,000 innocent lives extinguished that morning. In addition, the collapse of the World Trade Center and part of the Pentagon destroyed $30 billion of property. The Dow plunged, erasing $1.2 trillion in value. Psychologically, the assault punctured the “security bubble’’ in which most Americans imagined they lived securely. Today, 80 percent of Americans expect another major terrorist attack on the homeland in the next decade. Were this the sum of the matter, 9/11 would stand as a day of infamy, but not as an historic turning point. Huge as these directs costs are, they pale in comparison to costs of choices the United States made in response to 9/11: about how to defend America; where to fight Al Qaeda; whether to attack Iraq (or Iran or North Korea) on grounds that they had chemical or biological weapons that could be transferred to Al Qaeda; and whether to pay for these choices by taxing the current generation, or borrowing from China and other lenders, leaving the bills to the next generation. Unquestionably, much of what was done to protect citizens at home and to fight Al Qaeda abroad has made America safer. It is no accident that the United States has not suffered further megaterrorist attacks. The remarkable intelligence and Special Forces capabilities demonstrated in the operation that killed Osama bin Laden suggest how far we have come. But the central storyline of the decade focuses on two choices made by President George W. Bush - his decision to go to war with Iraq and his commitment to cut taxes, especially for wealthy Americans, and thus not to pay for the wars in Iraq and Afghanistan. The cost of his decision to go to war with Iraq is measured in 4,478 American deaths, 40,000 Americans gravely wounded, and a monetary cost of $2 trillion. Bush justified his decision to attack Iraq on the grounds that Saddam Hussein might arm terrorists with weapons of mass destruction, arguing that “19 hijackers armed by Saddam Hussein…could bring a day of horror like none we have ever known.’’ In retrospect, even Bush supporters agree that we went to war on false premises—since we now know that Saddam had no chemical or biological weapons. Suppose, however, that chemical weapons had been found in Iraq. Would that have made Bush’s choice a wise decision? What about the many other states that had chemical or biological weapons that could have been transferred to Al Qaeda, for example Libya, or Syria, or Iran? What about the state that unquestionably had an advanced nuclear weapons program, North Korea, which took advantage of the US preoccupation with Iraq to develop an arsenal of nuclear weapons and conduct its first nuclear weapons test? As for cutting taxes for the wealthy, Bush’s decision left the nation with a widening gap between government revenues and its expenditures. Brute facts are hard to ignore: having entered office with a budgetary surplus that the CBO projected would total $3.5 trillion through 2008, Bush left office with an annual deficit of over $1 trillion that the CBO projected would grow to $3 trillion over the next decade. Finally, and most difficult to assess, are opportunity costs, what could be Robert Frost’s “road not taken.’’ In the immediate aftermath of 9/11, the United States was the object of overwhelming international sympathy and solidarity. The leading French newspaper declared: “We are all Americans.’’ Citizens united behind their commander in chief, giving him license to do virtually anything he could plausibly argue would defend us against future attacks. This rare combination of readiness to sacrifice at home plus solidarity abroad sparked imagination. Would Americans have willingly paid a “terrorist tax’’ on gas that could kick what Bush rightly called America’s “oil addiction’’? Could an international campaign against nuclear terrorism or megaterrorism have bent trend lines that leave Americans and the world increasingly vulnerable to future biological or nuclear terrorist attacks? What impact could $2 trillion invested in new technologies have had on American competitiveness? That such a decade leaves Americans increasingly pessimistic about ourselves and our future is not surprising. American history, however, is a story of recurring, impending catastrophes from which there is no apparent escape—followed by miraculous recoveries. At one of our darkest hours in 1776 when defeat at the hands of the British occupying Boston seemed almost certain, the general commanding American forces, George Washington, observed: “Perseverance and spirit have done wonders in all ages.’’

Obama Should Test Iran’s Nuclear Offer - Allison, Graham T., Jr. (The Washington Post, 2011)
President Obama should take a page from Ronald Reagan’s playbook in winning the final inning of the Cold War. Obama can challenge President Mahmoud Ahmadinejad to put his enriched uranium where his mouth is—by stopping all Iranian enrichment of uranium beyond the 5 percent level. A quarter-century ago, Soviet leader Mikhail Gorbachev was touting a new “glasnost”: openness. President Reagan went to Berlin and called on Gorbachev to “tear down this wall.” Two years later, the Berlin Wall came tumbling down and, shortly thereafter, the Soviet “evil empire” fell as well. While in New York for the opening of the UN General Assembly in September, Ahmadinejad on three occasions made an unambiguous offer: He said Iran would stop all enrichment of uranium beyond the levels used in civilian power plants—if his country is able to buy specialized fuel enriched at 20 percent, for use in its research reactor that produces medical isotopes to treat cancer patients. Obama should seize this proposal and send negotiators straightaway to hammer out specifics. Iran has been enriching uranium since 2006, and it has accumulated a stockpile of uranium enriched at up to 5 percent, sufficient after further enrichment for several nuclear bombs. Iran is also producing 20 percent material every day, and it announced in June that it planned to triple its output. Halting Iran’s current production of 20 percent material and its projected growth would be significant. A stockpile of uranium enriched at 20 percent shrinks the potential timeline for breaking out to bomb material from months to weeks. In effect, having uranium enriched at 20 percent takes Iran 90 yards along the football field to bomb-grade material. Pushing it back below 5 percent would effectively move Tehran back to the 30-yard line - much farther from the goal of bomb-grade material. Even more important, extracting from Iran a commitment to a bright red line capping enrichment at 5 percent would stop the Islamic Republic from advancing on its current path to 60 percent enrichment and then 90 percent. Stopping Iran from enriching beyond 5 percent is not, in itself, a “solution” to its nuclear threat. Nor was Reagan’s proposal to Gorbachev. The question for Reagan was whether we would be better off with the Berlin Wall or without it. Iran today is the most sanctioned member of the United Nations; it has been the target of five Security Council resolutions since 2006 demanding that it suspend all uranium enrichment. The United States and Europe have organized their own, tougher economic sanctions forbidding businesses from trading with Iranian companies and limiting Iran’s access to financial markets. But Iran does not require the permission of the United Nations or, for that matter, the United States to advance its nuclear program within its borders. Nor are current or future sanctions likely to dissuade Iran from progressing steadily toward a nuclear weapon. So far, Obama has essentially continued the Bush administration’s policy toward Iran with one addition: an authentic offer from the start of his administration to begin negotiations. Negotiations, however, have not been feasible because of sharp divisions within Iran. Those rifts were exacerbated after the June 2009 elections, in which Iran’s ruling powers (Supreme Leader Ayatollah Ali Khamanei, Ahmadinejad and the Revolutionary Guard) rigged the presidential vote and then moved to suppress the opposition Green Movement protests. In the last two years, they have tightened control over their society. Enter Ahmadinejad’s proposal to stop all enrichment at the 5 percent level—without preconditions. Although differences between Ahmadinejad and the supreme leader have become evident, the United States should pay attention to the president’s offer. Arguments against testing the offer are easy to make. An embattled Ahmadinejad may not be able to deliver. Iran will use negotiations to seek to relax or escape current sanctions. If a deal were reached, it would be more difficult to win international support for the next round of sanctions. An agreement that stops only the 20 percent enrichment could imply a degree of acceptance of Iran’s ongoing enrichment up to 5 percent. Recognizing all of these negatives, however, the policy question remains: Would the United States be better off with Iran enriching its uranium to 20 percent or without it? President Obama should act now to test Ahmadinejad’s word.

Texting Makes U Stupid - Ferguson, Niall (The Daily Beast, 2011)
The good news is that today’s teenagers are avid readers and prolific writers. The bad news is that what they are reading and writing are text messages. According to a survey carried out last year by Nielsen, Americans between the ages of 13 and 17 send and receive an average of 3,339 texts per month. Teenage girls send and receive more than 4,000. It’s an unmissable trend. Even if you don’t have teenage kids, you’ll see other people’s offspring slouching around, eyes averted, tapping away, oblivious to their surroundings. Take a group of teenagers to see the seven wonders of the world. They’ll be texting all the way. Show a teenager Botticelli’s Adoration of the Magi. You might get a cursory glance before a buzz signals the arrival of the latest SMS. Seconds before the earth is hit by a gigantic asteroid or engulfed by a super tsunami, millions of lithe young fingers will be typing the human race’s last inane words to itself: C u later NOT :( Now, before I am accused of throwing stones in a glass house, let me confess. I probably send about 50 emails a day, and I receive what seem like 200. But there’s a difference. I also read books. It’s a quaint old habit I picked up as a kid, in the days before cellphones began nesting, cuckoolike, in the palms of the young. Half of today’s teenagers don’t read books—except when they’re made to. According to the most recent survey by the National Endowment for the Arts, the proportion of Americans between the ages of 18 and 24 who read a book not required at school or at work is now 50.7 percent, the lowest for any adult age group younger than 75, and down from 59 percent 20 years ago. Back in 2004, when the NEA last looked at younger readers’ habits, it was already the case that fewer than one in three 13-year-olds read for pleasure every day. Especially terrifying to me as a professor is the fact that two thirds of college freshmen read for pleasure for less than an hour per week. A third of seniors don’t read for pleasure at all. Why does this matter? For two reasons. First, we are falling behind more-literate societies. According to the results of the Organization for Economic Cooperation and Development’s most recent Program for International Student Assessment, the gap in reading ability between the 15-year-olds in the Shanghai district of China and those in the United States is now as big as the gap between the U.S. and Serbia or Chile. But the more important reason is that children who don’t read are cut off from the civilization of their ancestors. So take a look at your bookshelves. Do you have all - better make that any - of the books on the Columbia University undergraduate core curriculum? It’s not perfect, but it’s as good a list of the canon of Western civilization as I know of. Let’s take the 11 books on the syllabus for the spring 2012 semester: (1) Virgil’s Aeneid; (2) Ovid’s Metamorphoses; (3) Saint Augustine’s Confessions; (4) Dante’s The Divine Comedy; (5) Montaigne’s Essays; (6) Shakespeare’s King Lear; (7) Cervantes’s Don Quixote; (8) Goethe’s Faust; (9) Austen’s Pride and Prejudice; (10) Dostoevsky’s Crime and Punishment; (11) Woolf’s To the Lighthouse. Step one: Order the ones you haven’t got today. (And get War and Peace, Great Expectations, and Moby-Dick while you’re at it.) Step two: When vacation time comes around, tell the teenagers in your life you are taking them to a party. Or to camp. They won’t resist. Step three: Drive to a remote rural location where there is no cell-phone reception whatsoever. Step four: Reveal that this is in fact a reading party and that for the next two weeks reading is all you are proposing to do—apart from eating, sleeping, and talking about the books. Welcome to Book Camp, kids.

What If 9/11 Had Never Happened? - Ferguson, Niall (The Daily Beast, 2011)
How different would the world be today if there had been no 9/11? What if the attacks had been foiled or bungled? One obvious answer is that Americans would probably care a lot less than they do about the rest of the world. Back on the eve of destruction, in early September 2001, only 13 percent of Americans believed that the U.S. should be “the single world leader.” And fewer than a third favored higher defense spending. Now those figures are naturally much higher. Right? Wrong. According to the most recent surveys, just 12 percent of Americans today think the U.S. should be the sole superpower—almost exactly the same proportion as on the eve of the 9/11 attacks. The share of Americans who want to see higher spending on national security is actually down to 26 percent. Paradoxically, Americans today seem less interested in the wider world than they were before the Twin Towers were felled. In the past 10 years, the U.S. has directly or indirectly overthrown at least three governments in the Muslim world. Yet Americans today feel less powerful than they did then. In 2001 just over a quarter felt that the U.S. had “a less important role as a world leader compared to 10 years ago.” The latest figure is 41 percent. Three explanations suggest themselves. First, wielding power abroad proved harder in practice than in neoconservative theory. Second, the financial crisis has dampened American spirits. A third possibility is that 9/11 simply didn’t have that big an impact on American opinion. Yet to conclude that 9/11 didn’t change much is to misunderstand the historical process. The world is a seriously complex place, and a small change to the web of events can have huge consequences. Our difficulty is imagining what those consequences might have been. So let’s play a game like the one my friends at the Muzzy Lane software company are currently designing, which has the working title “New World Disorder.” The game simulates the complex interaction of economics, politics, and international relations, allowing us to replay the past. Let’s start in January 2001 and thwart the 9/11 attacks by having Condi Rice and Paul Wolfowitz heed Richard Clarke’s warnings about Al-Qaeda. The game starts off well. Al-Qaeda is preemptively decapitated, its leaders rounded up in a series of covert operations and left to the tender mercies of their home governments. President Bush gets to focus on tax cuts, his first love. But then, three years later, the murky details of this operation surface on the front page of The New York Times. John Kerry, the Democratic candidate for the presidency, denounces the “criminal conduct” of the Bush administration. Liberal pundits foam at the mouth. Ordinary Americans, unseared by 9/11, are shocked. Osama bin Laden issues a fierce denunciation of the U.S. from his Saudi prison cell. It triggers a wave of popular anger in the Middle East that topples any regime seen as too close to Washington. The government of Qatar - gone. The government of Kuwait - gone. Above all, the government of Saudi Arabia - gone. True to form, the experts are soon all over network TV explaining how this fundamentalist backlash against the U.S.-backed oil monarchies had been years in the making (even if they hadn’t quite gotten around to predicting it beforehand). “Who lost the Middle East?” demands Kerry, pointing an accusing finger at George W. Bush. (Remember, prior to 9/11 Bush favored a reduction of U.S. overseas commitments.) The Democrats win the 2004 election, where-upon bin Laden’s new Islamic Republic of Arabia takes hostages at the U.S. Embassy in Riyadh… In other words, if things had happened differently 10 years ago - if there had been no 9/11 and no retaliatory invasions of Afghanistan and Iraq - we might be living through an Islamist Winter rather than an Arab Spring. Replaying the history game without 9/11 suggests that, ironically, the real impact of the attacks was not on Americans but on the homelands of the attackers themselves.

World on Wi-Fire - Ferguson, Niall (The Daily Beast, 2011)
The human race is interconnected as never before. Is that a good thing? Ask the Lords of the Internet—the men running the companies Eric Schmidt of Google recently called “the Four Horsemen”: Amazon, Apple, Facebook, and Google—and you’ll get an unequivocal “yes.” But is it true? In view of the extraordinary economic and political instability of recent months, it’s worth asking if the Netlords are the Four Horsemen of a new kind of information apocalypse. Don’t get me wrong. I love all that these companies have achieved. I order practically everything except haircuts from Amazon. I write this column on a MacBook Pro. I communicate with my kids via Facebook. It’s 6:55 a.m., and I’ve already run six searches on Google. Did I forget to mention that I’ve already received 29 emails and sent 14? I also really like the Netlords. They are among the smartest guys on the planet. Yet they are also self-deprecating and sometimes very funny. (OK, not Steve Jobs.) So my question for them is a real question, not some kind of Luddite rant: does the incredible network you have created, with its unprecedented scale and speed, not contain a vulnerability? I’m not talking here about the danger of its exploitation by Islamist extremists or its incapacitation by Chinese cyberwarriors, though I worry about those things too. No, I mean the possibility that the global computer network formed by technologically unified human minds is inherently unstable—and that it is ushering in an era of intolerable volatility. The communications revolution we are living through has been driven by two great forces. One is Gordon E. Moore’s “law” (which he first proposed in 1965) that the number of transistors that can be placed inexpensively on an integrated circuit doubles approximately every 18 months. In its simplified form, Moore’s Law says that computing power will double every two years, implying a roughly 30-fold increase in 10 years. This exponential trend has now continued for more than half a century and is expected by the techies to continue until at least 2015 or 2020. The other force is the exponential growth of human networks. The first email was sent at the Massachusetts Institute of Technology in the same year Moore’s Law was born. In 2006 people sent 50 billion emails; last year it was 300 billion. The Internet was born in 1982. As recently as 1993 only 1 percent of two-way telecommunication went through it. By 2000 it was 51 percent. Now it’s 97 percent. Facebook was dreamed up by an über-nerd at my university in 2004. It has 800 million active users today—eight times the number of three years ago. Russian venture capitalist Yuri Milner sees this trend as our friend (it has certainly been his). As the number of people online doubles from 2 billion to 4 billion over the next 10 years and the number of Internet-linked devices quadruples from 5 billion to 20 billion, mankind collectively gets more knowledge—and gets smarter. Speaking at a conference in Ukraine in mid-September, Milner asserted that data equivalent to the total volume of information created from the beginning of human civilization until 2003 can now be generated in the space of just two days. To cope with this information overload, he looks forward to “the emergence of the global brain, which consists of all the humans connected to each other and to the machine and interacting in a very unique and profound way, creating an intelligence that does not belong to any single human being or computer.” In the future as imagined by Google, this global brain will do much of our thinking for us, telling us (through our handheld devices) which of our friends is just around the next corner and where we can buy that new suit we need for the best price. And if the best price is on Amazon, we’ll just click once and look forward to its next-day delivery. Maybe it’ll already be there when we get home. That’s the kind of sci-fi scenario that gets a true nerd out of bed in the morning. But is it just a bit too utopian? Exhibit one for a contrarian view is the recent behavior of global financial markets, the area of human activity furthest down the road of computerization and automation. According to math wonk Kevin Slavin, algorithms with names like the “Boston Shuffler” are the new masters of the financial universe. Whole tower blocks have been hollowed out to accommodate the computing power required by high-frequency (and very high-speed) trading. So how is this brave new world of robot traders doing? Well, the VIX index of volatility—Wall Street’s so-called fear gauge, which infers the expected volatility of the U.S. stock market from options prices—reached an all-time high of 80 in the aftermath of Lehman Brothers’ failure and surged back up above 30 in early 2010 and again this summer. Part of this is just a good old-fashioned, man-made financial crisis, of course. But some of the volatility we’ve seen in the past four years is surely attributable to technology: think only of the “flash crash” of May 6 last year, when the Dow Jones industrial average plummeted 9 percent and then rallied in a matter of minutes. Could the same kind of volatility spread into other markets as these become as wired and as integrated as Planet Finance? The answer must be yes. Consider how Greece’s fiscal woes have destabilized markets across Europe and around the world in recent months. Then there’s the market for consumer durables. We know that the speed with which new technologies have been adopted by American households has increased around eightfold over the past hundred years. But that speed of adoption has its obverse in the speed of obsolescence. Consumers are becoming ever more fickle. Millions bought RIM’s BlackBerry after its advent in 1999. But today the iPhone is the hotter handheld device, and I am far from alone in having a dead BlackBerry in my bottom desk drawer. In late September Amazon launched the Kindle Fire in a bid to challenge the iPad’s dominance of the tablet market. The name is appropriate. The market for such devices is on fire. The whole world is on wi-fire. In politics, too, online electorates are becoming more volatile. The current race to find a Republican candidate for the presidency is a case in point. Only the other day Sarah Palin was a serious contender. Then Mitt Romney was a shoe-in. Until Rick Perry came along. Until Chris Christie came along. Meanwhile, the number of independent voters who have uncoupled themselves from the traditional parties has reached a historic high of 37 percent. Floating voters are the high-frequency traders of the political market. Computing power has grown exponentially. So has the human network. But the brain of Homo sapiens remains pretty much the same organ that evolved in the heads of African hunter-gatherers 200,000 years ago. And that brain has a tendency to swing in its mood, from greed to fear and from love to hate. The reality may be that by joining us all together and deluging us with data, the Netlords have ushered in a new Age of Volatility, in which our primeval emotions are combined and amplified as never before. We are LinkedIn, but StressedOut. And that “cloud” of downloadable data may yet turn out to be a thundercloud.

You Were Expecting Statehood? - Ferguson, Niall (The Daily Beast, 2011)
The Palestinian leader Mahmoud Abbas’s bid for full U.N. membership was dead on arrival in New York. So why bother even raising the subject? The answer: to drum up international sympathy for the plight of the Palestinians. Yet other defeated peoples have suffered far more than they. Think only of how—and at whose expense—the U.N. itself began. Born in the gently foggy city of San Francisco, the U.N. was conceived in the Ukrainian resort of Yalta. Though nestled amid the green Crimean hills and lapped by the Black Sea’s languid waves, the city was severely battle-scarred in February 1945; Winston Churchill dubbed it “the Riviera of Hades.” Its diabolical master was the Soviet despot Joseph Stalin, who acted as host to Churchill and the ailing American President Franklin Roosevelt. Of the Big Three, as Sergei Plokhy shows in his riveting study Yalta: The Price of Peace, Roosevelt alone truly believed in the dream of a world parliament, and even he knew the U.N. would need to give greater weight to the great powers than its ill-starred predecessor, the League of Nations. Thus it was Roosevelt who proposed a Security Council on which the war’s victors—plus France and China—would be permanently represented and armed with veto powers. Churchill and Stalin were realists. They saw the postwar world in terms of “spheres of influence.” Though perfectly capable of such realism in practice, Roosevelt still yearned for the idealist’s world of peace based on collective security. Yet Churchill was deeply reluctant to accept that Stalin’s postwar sphere of influence would include Poland. His predecessor had acquiesced in the destruction of Czechoslovakia at Munich but had gone to war when Hitler (and Stalin) carved up Poland between them. Was Yalta to be the Poles’ Munich? “We can’t agree,” grumbled Churchill, “that Poland shall be a mere puppet state of Russia, where the people who don’t agree with Stalin are bumped off.” But that was exactly what postwar Poland became. A staggering 19 percent of the prewar population of Poland had been killed as a result of World War II, including a huge proportion of the country’s large Jewish population. Yalta inflicted further punishment. The country not only shrank; it was also shifted westward so that Stalin could keep his gains from the 1939 Nazi-Soviet Pact. And it became a Soviet vassal state for the next half century. After Yalta, chess players devised a variant of their game for three players, using a six-sided board. As at the conference, in the game “Yalta” two players can join forces against the third, but all such alliances are temporary. Briefly, Churchill got Roosevelt on his side over Poland, but the American cared more about getting Stalin to agree to join the U.N.; Poland was a pawn to be sacrificed. Having got what he wanted, Roosevelt left Yalta early. His destination? The Middle East, which he was intent on adding to ... the American sphere of influence. The conflicting commitments he made on that trip—to the Arabs and the Jews—have bedeviled U.S. foreign policy ever since. Asked by Roosevelt if he was a Zionist, Stalin replied elliptically that he “was one in principle, but he recognized the difficulty.” That “difficulty” remains that a Jewish state could be created only at the expense of non-Jews living in Palestine. The Arabs resisted Israel’s creation, but they lost. So it goes. A trip to Yalta provides a salutary reminder that throughout history those who lose at war generally lose land, too, and sometimes sovereignty with it. By comparison with what the Poles endured last century, the Palestinians have got off lightly. They will get their own state eventually. But not until all the permanent members of the Security Council are convinced the Palestinians will not abuse the privileges of statehood. Like it or not, that was how the U.N. was meant to work when the Big Three conceived it on Hell’s Riviera.

Blame the Baby Boomers - Ferguson, Niall (The Daily Beast, 2011)
After years when young Americans yearned only to be occupied on Wall Street, suddenly they have taken to occupying it. It’s easy to scoff at this phenomenon. I know, because I have. This is certainly not America’s answer to the Arab Spring—the Bobo Fall perhaps, unmistakably both bohemian and bourgeois. But it’s still worth taking seriously. What is it that makes evidently educated young people yearn to adopt leftist positions that are eerily reminiscent of the ones their parents adopted in 1968? Check out the protesters’ website, which on Monday featured a speech by Slovenian critical theorist Slavoj Žižek. At first I thought this must be some kind of parody, but no, he really exists—red T-shirt, Krugman beard, and all: “The only sense in which we are communists is that we care for the commons. The commons of nature. The commons of what is privatized by intellectual property. The commons of biogenetics. For this and only for this we should fight.” Yeah, man. Property is theft. Ne travaillez jamais. And all that. There are three possible explanations for this retrogression to the language of ’68.  1. Increasing inequality exemplified by Wall Street is worth protesting against. 2. So is the fact that only a handful of bankers have been prosecuted for their part in the financial crisis. 3. Demonstrating is way cool. Yet if I were a young American today, occupying Wall St. would not be my objective. Just reflect for a minute on the unbridled economic mayhem that would ensue if the protesters actually succeeded. The headline “Goldman Sachs Under Control of Hip Teenage Revolutionaries” would be the last straw for an already fragile economic recovery. Now ask yourself what the financial crisis really means for today's 15- to 24-year-olds. Not only has it raised the probability that they will be unemployed after graduation. More seriously, it has massively increased the debt that they will have to service when they do get jobs. Never in the history of intergenerational transfers has one generation left such a mountain of IOUs to another as the baby boomers are leaving to their grandchildren. When you do the math, there is only one logical political home for today’s teens and 20-somethings ... and that is the Tea Party. For who else is promising to slash Medicare and Social Security and keep the tax burden at its historical average? Let’s just remind ourselves of the report of the Trustees of the Social Security and Medicare trust funds back in 2007, which projected a rise in the cost of these two programs from 7.3 percent of gross domestic product to 17.5 percent by 2030. The trustees warned that to achieve actuarial balance—in other words, solvency—for these two programs would require (for Social Security) an increase of 16 percent in payroll tax revenues or an immediate reduction in benefits of 13 percent. For Medicare we are talking a 122 percent increase in payroll taxes or a 51 percent cut in spending. As Laurence Kotlikoff and Scott Burns pointed out in The Coming Generational Storm, by 2030 there will be twice as many retirees as there are today but only 18 percent more workers. Unless there is really radical reform of entitlement programs - especially Medicare - the next generation of American workers will be paying roughly double the taxes their parents and grandparents paid. This is what Kotlikoff and Burns mean by “fiscal child abuse.” Of these harsh realities the occupiers of Wall Street seem blissfully unaware. Fixated on the idea that they somehow represent the 99 percent of people who scrape by on 80 percent of total income, they fail to see that the real distributional conflict of our time is not between percentiles, much less classes, but between generations. And no generation has a keener interest in slashing future spending on entitlements than today’s teens and 20-somethings. So occupying Wall Street is not the answer to this generation’s problems. The answer is to occupy the Tea Party—and wrest it from the grumpy old men who currently run it. Call it the Iced Tea Party. Way cool.

The Coming Crises of Governments - Robert J. Barro (Financial Times, 2011)
The global crises of financial and housing markets are now being superseded by new crises of governments. The fiscal challenges for the weaker members of the eurozone are early warnings, as are analogous problems in American state governments weighed down by unfunded pension and healthcare liabilities. Without action, this new crisis of state competence could soon become just as damaging as its recent financial predecessor. This week's US debt deal, along with the prospect of debate on fiscal solutions in the run-up to the 2012 elections, provides some room for optimism. But America's fiscal problems have deep roots. The recession of 2007-2009 stemmed from the unprecedented bust in the housing market, driven by reduced lending standards and propelled by congressional pressures on private lenders and the reckless expansions of Fannie Mae and Freddie Mac. It is, however, important to recognise that this mistake is now understood and will not be repeated. In the aftermath of the debt ceiling agreement there will be calls for further stimulus for America's economy. This would be a grave mistake. In the financial turmoil of 2008, bail-outs by the US and other governments were unfortunate, but necessary. However, the subsequent $800bn American stimulus package was largely a waste of money that sharply enlarged the fiscal hole now facing our economy. President Barack Obama's administration has consistently overestimated the benefits of stimulus, by using an unrealistically high spending multiplier. According to this Keynesian logic, government expenditure is more than a free lunch. This idea, if correct, would be more brilliant than the creation of triple A paper out of garbage. In any event, the elimination of the temporary spending is now contractionary and, more importantly, the resulting expansion of public debt eventually requires higher taxes, retarding growth. I agree that budget deficits were appropriate during the great recession and, for that reason, the kind of balanced-budget rule currently proposed by some Republicans should be avoided. However, since government spending is warranted only if it passes the usual hurdles of social rates of return, the fiscal deficit should have concentrated on tax reductions, especially those that emphasised falls in marginal tax rates, which encourage investment and growth. Despite relief at the debt-ceiling agreement, America's fiscal situation remains deeply problematic. Any attempt to head off a crisis of government competence must begin with serious long-term reform. Reductions in the long-term path of entitlement outlays have to be put on the table, with increases in ages of eligibility a part of any solution. We also need sharp reductions in spending programmes initiated or expanded by Mr Obama and his extravagant predecessor, George W. Bush. Given the inevitable growth of the main entitlement programmes, especially healthcare, increases in long-term federal revenue must be part of an overall reform. So what, specifically, can be done? An effective future tax package would begin by setting US corporate and estate tax rates permanently to zero, given these taxes are inefficient and generate little revenue. Next, it would gradually phase out major "tax-expenditure" items, such as tax preferences for home-mortgage interest, state and local income taxes, and employee fringe benefits. The structure of marginal income-tax rates should then be lowered. Marginal rates should particularly not increase where they are already high, such as at upper incomes. The bulk of any extra revenue needed to make up the difference should then be raised via a broad-based, flat-rate expenditure tax, such as a value added tax. A rate of 10 per cent, with few exemptions, would raise about 5 per cent of gross domestic product. Of course, such a new tax would be a two-edged sword: a highly efficient tax, but politically dangerous. To paraphrase Larry Summers from long ago, we don't have VAT in the US because Democrats think it is regressive, and Republicans think it is a money machine. We will get VAT when Democrats realise it is a money machine, and Republicans realise it is regressive. Obviously, I worry about the money machine property, but I see no serious alternative for raising the revenue needed for an overall next-stage reform package. The raucous debt-ceiling debate represents a good start in forging a serious long-term fiscal plan. Substantial additional progress will be needed, sadly much of which will probably have to await the outcome of the next US election. Yet progress must be made - or the impending crises of governments, signalled by possible downgrades of US debt, will make the 2008-2009 recession look mild.

The Geniuses We'll Never Know - Ferguson, Niall (The Daily Beast, 2011)
This essay is not about Steve Jobs. It is about the countless individuals with roughly the same combination of talents of whom we’ve never heard and never will. Most of the 106 billion people who’ve ever lived are dead—around 94 percent of them. And most of those dead people were Asian—probably more than 60 percent. And most of those dead Asians were dirt poor. Born into illiterate peasant families enslaved by subsistence agriculture under some or other form of hierarchical government, the Steves of the past never stood a chance. Chances are, those other Steves didn’t make it into their 30s, never mind their mid-50s. An appalling number died in childhood, killed off by afflictions far easier to treat than pancreatic cancer. The ones who made it to adulthood didn’t have the option to drop out of college because they never went to college. Even the tiny number of Steves who had the good fortune to rise to the top of premodern societies wasted their entire lives doing calligraphy (which he briefly dabbled in at Reed College). Those who sought to innovate were more likely to be punished than rewarded. Today, according to estimates by Credit Suisse, there is approximately $195 trillion of wealth in the world. Most of it was made quite recently, in the wake of those great political and economic revolutions of the late 18th century, which, for the first time in human history, put a real premium on innovation. And most of it is owned by Westerners—Europeans and inhabitants of the New World and Antipodes inhabited by their descendants. We may account for less than a fifth of humanity, but we Westerners still own two thirds of global wealth. A nontrivial portion of that wealth ($6.7 billion) belonged to Steve Jobs and now belongs to his heirs. In that respect, Jobs personified the rising inequality that is one of the striking characteristics of his lifetime. Back in 1955 the top 1 percent of Americans earned 9 percent of income. Today the figure is above 14 percent. Yet there is no crowd of young people rampaging through Palo Alto threatening to “Occupy Silicon Valley.” The huge amounts of money made by Jobs and his fellow pioneers of personal computing are not resented the way the vampire squids of Wall Street are. On the contrary, Jobs is revered. One eminent hedge-fund manager (who probably holds a healthy slice of Apple stock as well as the full array of iGadgets) recently likened him to Leonardo da Vinci. So the question is not, how do we produce more Steves? The normal process of human reproduction will ensure a steady supply of what Malcolm Gladwell has called “outliers.” The question should be, how do we ensure that the next Steve Jobs fulfills his potential? An adopted child, the biological son of a Syrian Muslim immigrant, a college dropout, a hippie who briefly converted to Buddhism and experimented with LSD—Jobs was the type of guy no sane human resources department would have hired. I doubt that Apple itself would hire someone with his résumé at age 20. The only chance he ever had to become a chief executive officer was by founding his own company. And that—China, please note—is why capitalism needs to be embedded in a truly free society in order to flourish. In a free society a weirdo can do his own thing. In a free society he can even fail at his own thing, as Jobs undoubtedly did in his first stint in charge of Apple. And in a free society he can bounce back and revolutionize all our lives. Somewhere in his father’s native Syria another Steve Jobs has just died. But this other Steve was gunned down by a tyrannical government. And what wonders his genius might have produced we shall never know.

How to Get That AAA Rating Back - Robert J. Barro (The Wall Street Journal, 2011)
Ronald Reagan and Barack Obama have at least one similarity. They both were confronted by great economic challenges when they became president. Mr. Reagan's immediate challenge was that inflation and interest rates were out of control. He met this great test by allying with the Federal Reserve chairman, Paul Volcker, in accomplishing a return to price stability, even through the 1982 recession when the unemployment rate hit 10.8%. Reagan's success is not in doubt. Inflation and interest rates were reduced dramatically, and the recovery from the end of 1982 to the end of 1988 was strong and long with an average growth rate of real GDP of 4.6% per year. Moreover, Reagan focused on implementing good economic policies, not on blaming his incompetent predecessor for the terrible economy he had inherited. Mr. Obama was equally in position to get credit for turning around a perilous economic situation that had been left by a weak predecessor. But he has pursued an array of poor economic policies, featuring the grand Keynesian experiment of sharply raising federal spending and the public debt. The results have been terrible and now, two and a half years into his administration, Mr. Obama is still blaming George W. Bush for all the problems. Friday's downgrade of the U.S. credit rating by Standard & Poor's should have been a wake-up call to the administration. S&P is saying, accurately, that there is no coherent long-term plan in place to deal with the U.S. government's fiscal deficits. The U.S. Treasury could have responded in two ways. First, it could have taken the downgrade as useful information and then focused on how to perform better to earn back a AAA rating. Instead, it chose to attack the rating agency as incompetent and not credible. In this respect, U.S. officials were almost as bad as Italian Prime Minister Silvio Berlusconi, who responded to warnings from S&P and Moody's about Italian government debt by launching police raids on the offices of the rating agencies in Milan last week. The U.S. Treasury's response also reminds me of Lehman Brothers blaming its financial problems in the summer of 2008 on evil financial analysts and short-sellers. The way for the U.S. government to earn back a AAA rating is to enact a meaningful medium- and long-term plan for addressing the nation's fiscal problems. I have sketched a five-point plan that builds on ideas from the excellent 2010 report of the president's deficit commission. First, make structural reforms to the main entitlement programs, starting with increases in ages of eligibility and a shift to an economically appropriate indexing formula. Second, lower the structure of marginal tax rates in the individual income tax. Third, in the spirit of Reagan's 1986 tax reform, pay for the rate cuts by gradually phasing out the main tax-expenditure items, including preferences for home-mortgage interest, state and local income taxes, and employee fringe benefits—not to mention eliminating ethanol subsidies. Fourth, permanently eliminate corporate and estate taxes, levies that are inefficient and raise little money. Fifth, introduce a broad-based expenditure tax, such as a value-added tax (VAT), with a rate around 10%. The VAT's appeal to liberals can be enhanced, with some loss of economic efficiency, by exempting items such as food and housing. I recognize that a VAT is anathema to many conservatives because it gives the government an added claim on revenues. My defense is that a VAT makes sense as part of a larger package that includes the other four points. The loss of the U.S. government's AAA rating is a great symbolic blow, one that would cause great anguish to our first Treasury secretary, Alexander Hamilton. Frankly, the only respectable reaction by our current Treasury secretary is to fall on his sword. Then again, "the buck stops here" suggests that an even more appropriate resignation would come from our chief executive, who, by the way, is no Ronald Reagan.

How to Really Save the Economy - Robert J. Barro (The New York Times, 2011)
The United States is in the third year of a grand experiment by the Obama administration to revive the economy through enormous borrowing and spending by the government, with the Federal Reserve playing a supporting role by keeping interest rates at record lows. How is the experiment going? By the looks of it, not well. The economy is growing much more slowly than in a typical recovery, housing prices remain depressed and the stock market has been in a slump—all troubling indicators that another recession may be on the way. Most worrisome is the anemic state of the labor market, underscored by the zero growth in the latest jobs report. The poor results should not surprise us given the macroeconomic policies the government has pursued. I agree that the recession warranted fiscal deficits in 2008–2010, but the vast increase of public debt since 2007 and the uncertainty about the country’s long-run fiscal path mean that we no longer have the luxury of combating the weak economy with more deficits. Today’s priority has to be austerity, not stimulus, and it will not work to announce a new $450 billion jobs plan while promising vaguely to pay for it with fiscal restraint over the next 10 years, as Mr. Obama did in his address to Congress on Thursday. Given the low level of government credibility, fiscal discipline has to start now to be taken seriously. But we have to do even more: I propose a consumption tax, an idea that offends many conservatives, and elimination of the corporate income tax, a proposal that outrages many liberals. These difficult steps would be far more effective than the president’s failed experiment. The administration’s $800 billion stimulus program raised government demand for goods and services and was also intended to stimulate consumer demand. These interventions are usually described as Keynesian, but as John Maynard Keynes understood in his 1936 masterwork, “The General Theory of Employment, Interest and Money” (the first economics book I read), the main driver of business cycles is investment. As is typical, the main decline in G.D.P. during the recession showed up in the form of reduced investment by businesses and households. What drives investment? Stable expectations of a sound economic environment, including the long-run path of tax rates, regulations and so on. And employment is akin to investment in that hiring decisions take into account the long-run economic climate. The lesson is that effective incentives for investment and employment require permanence and transparency. Measures that are transient or uncertain will be ineffective. And yet these are precisely the kinds of policies the Obama administration has pursued: temporarily cutting the payroll tax rate, maintaining the marginal income-tax rates from the George W. Bush era while vowing to raise them in the future, holding off on clean-air regulations while promising to implement them later and enacting an ambitious overhaul of Wall Street regulations while leaving lots of rules undefined and ambiguous. Is there a better way? I believe that a long-term fiscal plan for the country requires six big steps. Three of them were identified by the Bowles-Simpson deficit reduction commission: reforming Social Security and Medicare by increasing ages of eligibility and shifting to an appropriate formula for indexing benefits to inflation; phasing out “tax expenditures” like the deductions for mortgage interest, state and local taxes and employer-provided health care; and lowering the marginal income-tax rates for individuals. I would add three more: reversing the vast and unwise increase in spending that occurred under Presidents Bush and Obama; introducing a tax on consumer spending, like the value-added tax (or VAT) common in other rich countries; and abolishing federal corporate taxes and estate taxes. All three measures would be enormously difficult—many say impossible—but crises are opportune times for these important, basic reforms. A broad-based expenditure tax, like a VAT, amounts to a tax on consumption. If the base rate were 10 percent, the revenue would be roughly 5 percent of G.D.P. One benefit from a VAT is that it is more efficient than an income tax—and in particular the current American income tax system. I received vigorous criticism from conservatives after advocating a VAT in an essay in The Wall Street Journal last month. The main objection—reminiscent of the complaints about income-tax withholding, which was introduced in the United States in 1943—is that a VAT would be a money machine, allowing the government to readily grow larger. For example, the availability of easy VAT revenue in Western Europe, where rates reach as high as 25 percent, has supported the vast increase in the welfare state there since World War II. I share these concerns and, therefore, favor a VAT only if it is part of a package that includes other sensible reforms. But given the likely path of government spending on health care and Social Security, I see no reasonable alternative. Abolishing the corporate income tax is similarly controversial. Any tax on capital income distorts decisions on saving and investment. Moreover, the inefficiency is magnified here because of double taxation: the income is taxed when corporations make profits and again when owners receive dividends or capital gains. If we want to tax capital income, a preferred method treats corporate profits as accruing to owners when profits arise and then taxes this income only once—whether it is paid out as dividends or retained by companies. Liberals love the idea of a levy on evil corporations, but taxes on corporate profits in fact make up only a small part of federal revenue, compared to the two main sources: the individual income tax and payroll taxes for Social Security and Medicare. In 2009-10, taxes on corporate profits averaged 1.4 percent of G.D.P. and 8.6 percent of total federal receipts. Even from 2000 to 2008, when corporations were more profitable, these taxes averaged only 1.9 percent of G.D.P. and 10.3 percent of federal receipts. If we could get past the political fallout, we could get more revenue and improve economic efficiency by abolishing the corporate income tax and relying instead on a VAT. I had a dream that Mr. Obama and Congress enacted this fiscal reform package—triggering a surge in the stock market and a boom in investment and G.D.P.—and that he was re-elected. This dream could become reality if our leader were Ronald Reagan or Bill Clinton—the two presidential heroes of the American economy since World War II—but Mr. Obama is another story. To become market-friendly, he would have to abandon most of his core economic and political principles. More likely, his administration will continue with more of the same: an expansion of payroll-tax cuts, short-term tax credits, promises to raise future taxes on the rich, and added spending on infrastructure, job training and unemployment benefits. The economy will probably continue in its sluggish state, possibly slipping into another recession. In that case, our best hope is for a Republican president far more committed to the principles of free markets and limited government than Mr. Bush ever was.

Keynesian Economics vs. Regular Economics - Robert J. Barro (The Wall Street Journal, 2011)
Keynesian economics—the go-to theory for those who like government at the controls of the economy—is in the forefront of the ongoing debate on fiscal-stimulus packages. For example, in true Keynesian spirit, Agriculture Secretary Tom Vilsack said recently that food stamps were an "economic stimulus" and that "every dollar of benefits generates $1.84 in the economy in terms of economic activity." Many observers may see how this idea—that one can magically get back more than one puts in—conflicts with what I will call "regular economics." What few know is that there is no meaningful theoretical or empirical support for the Keynesian position. The overall prediction from regular economics is that an expansion of transfers, such as food stamps, decreases employment and, hence, gross domestic product (GDP). In regular economics, the central ideas involve incentives as the drivers of economic activity. Additional transfers to people with earnings below designated levels motivate less work effort by reducing the reward from working. In addition, the financing of a transfer program requires more taxes—today or in the future in the case of deficit financing. These added levies likely further reduce work effort—in this instance by taxpayers expected to finance the transfer—and also lower investment because the return after taxes is diminished. This result does not mean that food stamps and other transfers are necessarily bad ideas in the world of regular economics. But there is an acknowledged trade-off: Greater provision of social insurance and redistribution of income reduces the overall GDP pie. Yet Keynesian economics argues that incentives and other forces in regular economics are overwhelmed, at least in recessions, by effects involving "aggregate demand." Recipients of food stamps use their transfers to consume more. Compared to this urge, the negative effects on consumption and investment by taxpayers are viewed as weaker in magnitude, particularly when the transfers are deficit-financed. Thus, the aggregate demand for goods rises, and businesses respond by selling more goods and then by raising production and employment. The additional wage and profit income leads to further expansions of demand and, hence, to more production and employment. As per Mr. Vilsack, the administration believes that the cumulative effect is a multiplier around two. If valid, this result would be truly miraculous. The recipients of food stamps get, say, $1 billion but they are not the only ones who benefit. Another $1 billion appears that can make the rest of society better off. Unlike the trade-off in regular economics, that extra $1 billion is the ultimate free lunch. How can it be right? Where was the market failure that allowed the government to improve things just by borrowing money and giving it to people? Keynes, in his "General Theory" (1936), was not so good at explaining why this worked, and subsequent generations of Keynesian economists (including my own youthful efforts) have not been more successful. Theorizing aside, Keynesian policy conclusions, such as the wisdom of additional stimulus geared to money transfers, should come down to empirical evidence. And there is zero evidence that deficit-financed transfers raise GDP and employment—not to mention evidence for a multiplier of two. Gathering evidence is challenging. In the data, transfers are higher than normal during recessions but mainly because of the automatic increases in welfare programs, such as food stamps and unemployment benefits. To figure out the economic effects of transfers one needs "experiments" in which the government changes transfers in an unusual way—while other factors stay the same—but these events are rare. Ironically, the administration created one informative data point by dramatically raising unemployment insurance eligibility to 99 weeks in 2009—a much bigger expansion than in previous recessions. Interestingly, the fraction of the unemployed who are long term (more than 26 weeks) has jumped since 2009—to over 44% today, whereas the previous peak had been only 26% during the 1982-83 recession. This pattern suggests that the dramatically longer unemployment-insurance eligibility period adversely affected the labor market. All we need now to get reliable estimates are a hundred more of these experiments. The administration found the evidence it wanted—multipliers around two—by consulting some large-scale macro-econometric models, which substitute assumptions for identification. These models were undoubtedly the source of Mr. Vilsack's claim that a dollar more of food stamps led to an extra $1.84 of GDP. This multiplier is nonsense, but one has to admire the precision in the number. There are two ways to view Keynesian stimulus through transfer programs. It's either a divine miracle—where one gets back more than one puts in—or else it's the macroeconomic equivalent of bloodletting. Obviously, I lean toward the latter position, but I am still hoping for more empirical evidence.

Obama Can Lead—Or He Can Continue to Blame Others - Robert J. Barro (The New York Daily News, 2011)
The way to restoring America's AAA credit-rating starts with President Obama moving beyond blaming the economy on the admittedly inept George W. Bush.  Standard & Poor's recent downgrade of the U.S. government shows how far the world has moved into a crisis of governments. The official reactions to the S&P action have not been promising. The Obama administration attacked S&P's competence, and the U.S. Congress has threatened hearings, apparently aimed at bullying S&P and the other agencies from further downgrades. The main substantive criticism was that S&P made a $2 trillion mistake in its baseline projection of 10-year deficits. Of course, these projections came from the Congressional Budget Office, which lost its credibility in these matters when it scored President Obama's health care reform plan as reducing 10-year deficits - mostly because of the inclusion of phantom reductions in Medicare payments to doctors. In truth, S&P's downgrade stemmed mainly from its legitimate concern that the U.S. government has no coherent medium- or long-term plan to eliminate budget deficits and stabilize the path of public debt. This judgment is accurate and courageous and goes some distance in offsetting the hit to S&P's reputation that came from the AAA ratings that it gave not so long ago to mounds of mortgage-backed securities built on subprime garbage. Unfortunately, Obama's main response to S&P's downgrade and the economic crisis more generally has been to continue blaming almost everything on his admittedly inept predecessor, George W. Bush, and on the Republican Congress. Another familiar theme is the unwillingness of the evil rich to pay more taxes. (I have one modest proposal that could save the President valuable time in this regard. Rather than continuing to repeat the long phrase "millionaires and billionaires," I suggest a merger: "mibillionaires." I know it looks funny and is hard to say on a first try, but after three or four repetitions it becomes strikingly mellifluous.) Enough. The way forward to restoring our AAA rating begins with Obama taking seriously the surprisingly sound report by his recent bipartisan debt and deficit commission. Building on those recommendations, I have constructed a fiscal plan: • Make structural reforms to the main entitlement programs starting with increases in ages of eligibility and a shift to an economically appropriate indexing formula. • Eliminate the unwise increases of federal spending by Bush and Obama, including added outlays for education, farm and ethanol subsidies, and expansions of Medicare and Medicaid. • Lower the structure of marginal tax rates in the individual income tax. • Pay for the rate cuts by gradually phasing out the main tax-expenditure items, including preferences for home-mortgage interest, state and local income taxes, and employee fringe benefits. • Permanently eliminate federal corporate and estate taxes, levies that are inefficient and raise comparatively little money. • Introduce a broad-based expenditure tax, such as a value-added tax (VAT). Depending on the structure of exemptions, a rate of 10% should raise about 5% of GDP in revenue. The VAT system is present in most developed countries and can be highly efficient because it has a flat rate, falls on consumption and has built-in mechanisms for ensuring compliance. However, a VAT is also a magnet for criticism by conservatives - who worry about the promotion of a larger government. I share this concern and would defend a VAT only if it can be firmly linked to the other parts of the reform package. But more fundamentally, given the projected path of entitlement spending, I see no reasonable alternative. It is hard to imagine President Obama becoming the leader of this kind of broad fiscal initiative. Though he has endorsed some pieces of some of these components, the embrace has been halting. He is hedging, not leading. Thus, as S&P observed, uncertainty about our fiscal path will likely not be resolved at least until the outcomes of next year's crucial elections. The one person with the power to eliminate part of this uncertainty is the President, who could nobly decide not to stand for reelection, thereby following in the footsteps of Lyndon Johnson and Calvin Coolidge. Johnson was forced out by a different type of crisis, Vietnam, and he hung on too long, delaying his announcement until he saw his poor performance in the New Hampshire primary and in subsequent electoral polls. Coolidge is a more dignified model, as he opted out in 1927 while things were going fine. In fact, Obama could borrow Coolidge's memorable phrase, "I do not choose to run."

Yes, Wall Street Helps the Poor - Ferguson, Niall (The Daily Beast, 2011)
It was a scene to curdle liberal blood. A ballroom full of New York hedge-fund managers playing poker…to raise money for charter schools. That’s where I found myself last Wednesday: at a Texas Hold ’Em tournament to raise money for the Success Charter Network, which currently runs nine schools in some of New York’s poorest neighborhoods. While Naomi Wolf was being arrested for showing solidarity with the Occupy Wall Street movement, there I was, consorting with the 1 percent the protesters hate. It’s no surprise that the bread-heads enjoy gambling. But to see them using their ill-gotten gains to subvert this nation’s great system of public education! I was shocked, shocked. Except that I wasn’t. I was hugely cheered up. America’s financial elite needs a compelling answer to Occupy Wall Street. This could be it: educate Harlem…with our poker chips. Life, after all, is a lot like poker. No matter how innately smart you may be, it’s very hard to win if you are dealt a bad hand. Americans used to believe in social mobility regardless of the hand you’re dealt. Ten years ago, polls showed that about two thirds believed “people are rewarded for intelligence and skill,” the highest percentage across 27 countries surveyed. Fewer than a fifth thought that “coming from a wealthy family is essential [or] very important to getting ahead.” Such views made Americans more tolerant than Europeans and Canadians of inequality and more suspicious of government attempts to reduce it. Yet the hardships of the Great Recession may be changing that, giving an unexpected resonance to the Occupy Wall Street movement. Falling wages and rising unemployment are making us appreciate what we ignored during the good times. Social mobility is actually lower in the U.S. than in most other developed countries—and falling. Academic studies show that if a child is born into the poorest quintile (20 percent) of the U.S. population, his chance of making it into the top decile (10 percent) is around 1 in 20, whereas a kid born into the top quintile has a better than 40 percent chance. On average, then, a father’s earnings are a pretty good predictor of his son’s earnings. This is less true in Europe or Canada. What’s more, American social mobility has declined markedly in the past 30 years. A compelling explanation for our increasingly rigid social system is that American public education is failing poor kids. One way it does this is by stopping them from getting to college. If your parents are in the bottom quintile, you have a 19 percent chance of getting into the top quintile with a college degree—but a miserable 5 percent chance without one. Your ZIP code can be your destiny, because poor neighborhoods tend to have bad schools, and bad schools perpetuate poverty. But the answer is not to increase spending on this failed system—nor to expand it at the kindergarten level, as proposed by Nicholas Kristof in The New York Times last week. As brave reformers like Eva Moskowitz know, the stranglehold exerted by the teachers’ unions makes it almost impossible to raise the quality of education in subprime public schools. The right answer is to promote the kind of diversity and competition that already make the American university system the world’s best. And one highly effective way of doing this is by setting up more charter schools—publicly funded but independently run and union-free. The performance of the Success Charter Network speaks for itself. In New York City’s public schools, 60 percent of third, fourth, and fifth graders passed their math exams last year. The figure at Harlem Success was 94 percent. The American Dream is about social mobility, not enforced equality. It’s about competition, not public monopoly. It’s also about philanthropy, not confiscatory taxation. I’ll cheer up even more when I hear those words at a Republican presidential debate. Or maybe next week we should just tell the candidates to shut up and play poker.

Dignity... We All Crave It, So Why Do We Keep Ignoring It? - Hicks, Donna (Fox News, 2011)
“Treat people as they want to be and you help them become what they are capable of being.” —Johann Wolfgang von Goethe   What is the motivating force behind all human interaction—in families, in communities, in the business world, and in relationships from the personal level to the international level? DIGNITY. It is the desire to be treated well. It is an unspoken human yearning that is at the heart of all conflicts, yet no one is paying attention to it. When dignity is violated, the response is likely to involve aggression, even violence, hatred, and vengeance; the human connection is the first thing to go. On the other hand, when people treat each others with dignity, they feel their worth is recognized, creating lasting and meaningful relationships. Surprisingly, most people have little understanding of dignity. While a desire for dignity is universal, knowing how to honor it in ourselves and others is not. After working as a conflict resolution specialist for twenty years, I have observed and researched the circumstances that give rise to dignity violations. On the other hand, when the following ten elements of dignity are honored, people feel their dignity has been recognized and that they have been treated well. Relationships flourish under these conditions. The Ten Essential Elements of Dignity Acceptance of Identity. Approach people as being neither inferior nor superior to you. Give others the freedom to express their authentic selves without fear of being negatively judged. Interact without prejudice or bias, accepting the ways in which race, religion, ethnicity, gender, class, sexual orientation, age, and disability may be at the core of the other people’s identities. Assume that others have integrity. Inclusion.Make others feel that they belong, whatever the relationship—whether they are in your family, community, organization, or nation. Safety. Put people at ease at two levels: physically, so they feel safe from bodily harm, and psychologically, so they feel safe from being humiliated. Help them feel free to speak without fear of retribution. Acknowledgement. Give people your full attention by listening, hearing, validating, and responding to their concerns, feelings, and experiences. Recognition. Validate others for their talents, hard work, thoughtfulness, and help. Be generous with praise, and show appreciation and gratitude to others for their contributions and ideas. Fairness. Treat people justly, with equality, and in an evenhanded way according to agreed-on laws and rules. People feel that you have honored their dignity when you treat them without discrimination or injustice. Benefit of the Doubt. Treat people as trustworthy. Start with the premise that others have good motives and are acting with integrity. Understanding. Believe that what others think matters. Give them the chance to explain and express their points of view. Actively listen in order to understand them. Independence.Encourage people to act on their own behalf so that they feel in control of their lives and experience a sense of hope and possibility. Accountability. Take responsibility for your actions. If you have violated the dignity of another person, apologize. Make a commitment to change your hurtful behaviors. Our desire for dignity resides deep within us, defining our common humanity. If our capacity for indignity is our lowest common denominator, then our yearning for dignity is our highest. And if indignity tears relationships apart, then dignity can put them back together again. Our ignorance of all things related to dignity—how to claim our own and how to honor it in others, has contributed to many of the conflicts we see in the world today. This is as true in the boardroom and in the bedroom, as it is in politics and international relations. It is true for all human interaction. If we are to evolve as a species, there is no greater need than to learn how to treat each other and ourselves with dignity. It is the glue that could holds us all together. And it doesn’t stop there. Not only does dignity make for good human relationships, it does something perhaps far more important—it creates the conditions for our mutual growth and development. It is a distraction to have to defend oneself from indignity. It takes up our time and uses up our precious energy. The power of dignity, on the other hand, only expands with use. The more we give, the more we get. There is no greater leadership challenge than to lead with dignity, helping us all to understand what it feels like to be honored and valued and to feel the incalculable benefits that come from experiencing it. The leadership challenge is at all levels—for those in the world of politics, business, education, religion, to everyday leadership in our personal lives. Peace will not flourish anywhere without dignity. There is no such thing as democracy without dignity, or can there be authentic peace if people are suffering indignities. Last but not least, feeling dignity’s power—both by honoring it and locating our own inner source of it—sets us up for one of humanities greatest gifts—the experience of being in relationship with others in a way that brings out the best in one another, allowing us to become more of what we are capable of being.

This is No 1989 Moment for the Arab World - Mylonas, Harris (Guardian.co.uk, 2011)
Analogies will be drawn in the coming weeks between the recent popular uprisings, most notably in Egypt, and the events beginning in 1989 and continuing into the early 1990s that brought democracy to much of the former Eastern bloc. In what is known as the third wave of democratisation (the first being in the early 1800s and the second being after the second world war), the Solidarity movement in Poland informed the peaceful transitions in Estonia, Latvia and Lithuania, the transition to democracy in Hungary and the reunification of Germany. It is no stretch to say that the political leadership and leaders of the opposition movements learned from one another throughout the tumult of the 1980s and into the 1990s. Much as social media today has been touted as a spur to democratic movements in the Middle East, pirate radio bombarded the Eastern bloc with information about democratic successes in other countries, as well as the ominous alternative posed by Tiananmen Square. But while the wave following the fall of the Berlin Wall created a period of unprecedented security across the European continent, the current wave of uprisings could create a corridor of failed states stretching from the Democratic Republic of Congo to the frontiers of Europe in southern Turkey. The "fourth wave" narrative goes something like this: just as a host of communist dictators—Jaruzelski in Poland, Honecker in Germany and Németh in Hungary—were swept away by the third wave, the fall of Bakiev in Kyrgyzstan and Ben Ali in Tunisia and the uncertain perches of Mubarak in Egypt and Saleh in Yemen signal a new wave of democratisation. The continuing crisis in Egypt, Saleh's announcement that he will not seek re-election, the reshuffling of the Jordanian cabinet and whispers of protest in Syria contain the promise of a "1989 moment" throughout the greater Middle East. But important differences between recent events and the third wave are already apparent. In the third wave, Romania was the only country that experienced a violent transition to democracy. Things look different this time around, in great part because today's nondemocratic leaders took their own lessons from the third wave. Instead of tanks and troops, and top-down repression a la Tiananmen Square the new oppressors of democratisation are the Basij, the "pro-government protesters," the plainclothes security personnel, the agents provocateurs inciting violence and instability. As the iron curtain began to fall in Europe, leaders such as Honecker and Jaruzelski weighed the costs of violent repression on the stability of their regimes, essentially deciding between increased authoritarianism and liberalisation. If there truly is a "new wave", it is characterised by a group of regimes that have learned to pass the decision between power and stability on to the protestors by creating environments of insecurity and fostering the conditions for state failure through tactics such as throwing open the prison doors and sponsoring thugs engaged in street violence. The opposition movements are left to decide whether to continue to press for their ideal outcome while the apparatus of governance teeters closer to collapse, or to negotiate with the regime while facing the potential erosion of the movement's credibility. Further complicating this "new wave" is the role political Islam plays in western security circles. The transition of Soviet bloc states into the democratic fold was seen and understood as a victory against an ideological enemy: the vast USSR. The third wave delegitimated the Soviet style of governance as the massive bureaucratic state crumbled under increasing pressure for political liberalisation, both internally and externally. In the "new wave", things are different. In the eyes of the west, the crowds are as likely to be its ideological enemies as are the regimes in power—autocracy in the presidential palace is balanced by the spectre of radical Islam in the streets. Whether these fears are well grounded remains to be seen, but western states look to the electoral successes of Hamas and Hezbollah as establishing a worrying precedent in the region. And for all the democratising potential of social media, today's improved analogue to Radio Free Europe, its powers are particularised and circumscribed. While it is true that social media have increased the capacity of the population to hold autocrats more accountable, they cannot solve pressing problems such as blocked social mobility and sky-high unemployment rates. Even if today's movements manage to oust dictators and move toward free and fair elections, the frustrations and grievances of the populations supporting the movements will not necessarily be addressed. Such a development might lead to further disillusionment inside the protest movements—and this time with democracy. The characteristics of this "new wave" matter for reasons that go beyond the potential satisfaction of seeing democracy flourish in new spots on the globe. Where in the past authoritarian leaders clamped down on their populations, snuffing democracy but maintaining security, there seems to be an emerging trend of authoritarian leaders letting their states collapse like poorly built houses of cards, with no guarantee of democracy or security. While it is possible that the Egyptian uprising may result in a Turkish-style democratic state, a corridor of state failure from Kinshasa to Beirut is also not an unlikely outcome. That such stakes are now in play only underscores the necessity of re-examining the west's historical role in supporting the type of personalistic dictatorships that are now under siege, and the familiar cultural arguments that these states have never been democratic—and lack the capacity ever to be become democratic.

What Role Should the U.S. Play in Middle East? - Nye, Joseph S., Jr.; Walt, Stephen M.; Allison, Graham T., Jr. (Belfer Center Newsletter, 2011)

Analysis of Greece’s Cabinet Reshuffle - Mylonas, Harris (CNN.com, 2011)
Three weeks of peaceful street protests; a couple of Panhellenic Socialist Movement (PASOK) members of parliament resigning this week; a few more PASOK members of parliament challenging the leadership qualities of Greek Prime Minister George Papandreou; rampant unemployment; violent clashes with the police; and one of the worst financial crises in modern Greek history culminated today in...a cabinet reshuffle. Prime Minister Papandreou is facing the most intense criticism since his election in October of 2009, both from his party and from Greek society. What on Wednesday night looked like a grand coalition government with the main opposition party, Nea Demokratia, was transformed on Thursday into an intra-party “reshuffling for elections.” The new government was sworn in on June 17 and will be up for a confidence vote on June 21. The opposition parties are not impressed with the reshuffle. Most citizens reacted by saying “same old, same old.” Not much is expected from this new government. Why is that? To begin with, Papandreou's effort to regain the confidence of the Greek public began with the ambitious idea of a coalition government including many technocrats but ended up with a mild cabinet reshuffling satisfying the narrow interests of the ruling political party rather than effectively tackling the mounting problems. For example, his efforts to recruit Lucas Papademos, an experienced economist that has served as vice president of the European Central Bank, as a Minister of Finance did not bear fruit. This is just one example of the failure of Papandreou to bring technocrats into the government. Instead, Evangelos Venizelos, a professor of constitutional law and until today defense minister, took up the burden. Moreover, Theodoros Pangalos remained deputy prime minister despite the fact that he has been the target of most of the chants of the street protesters for the past three weeks. Most ministers were not changed and three important ministers were demoted but not fired—the Ministers of Finance, Interior, and Justice. However, there is a more positive way to read the news. Papandreou managed to build a team that agrees with him, to improve the internal cohesion of the party, and to share the burden with the rest of PASOK. One step was to remove Katseli, who was probably a victim of her disagreements with the Troika (European Central Bank, IMF, European Commission), from the Ministry of Labor and Social Security. To appease the political base of PASOK and silence a wave of internal criticism that has been mounting within his party he removed from the government some of his close friends that had been intensely criticized and included some of his personal critics in the government. Last but not least, by promoting Venizelos—his party rival and contestant for the leadership of the party just a few years ago—to deputy Prime Minister. Adding a second deputy Prime Minister position for Venizelos, Papandreou significantly changed the dynamic within PASOK. Party cohesion is a arguably a precondition for the government to pass the new bundle of austerity measures required to secure more loans from the EU/IMF. Despite these cooptation tactics, however, the new government has already found its critics from within the party. A few minutes after the new government was sworn in, PASOK MP Voudouris argued that the reshuffle was unsatisfactory. Regardless, as a result of this reshuffle, the whole political party is seen as an “accomplice” of Prime Minister Papandreou in this effort. There are also important changes in the functioning of the government. The Prime Minister re-created a “Government Committee”—something that has been a demand of many party members—where the most important policies are normally decided. The irony is that it is both oversized, with ten Ministers participating, and lacks the key Ministers of Foreign Affairs and Defense. These changes aim to enhance Papandreou’s ability to delegate responsibility and for the government to coordinate more efficiently. Another important fact is that Pangalos will not be part of the “Government Committee” — something that might appease some of his many critics. Turning to the Ministry of Finance—the hot potato of this affair—most people believe that Venizelos may be better in the negotiations than the previous Minister of Finance, Papaconstantinou. Venizelos is an experienced politician and charismatic speaker. He has served as minister of culture, justice, transportation, and development. Nevertheless, he is not an economist and thus he will have to rely on the advice of others. Finally, two promising new faces in the government are Stavros Lambrinidis, (BA from Amherst, JD from Yale), the new Minister of Foreign Affairs, and LSE Professor Elias Mossialos, the new government spokesman and Minister of State. In the meantime, this Sunday the Eurogroup is meeting in Brussels to decide on the next installment from the EU/IMF bailout package. It seems that the developments in Greece have also alarmed Sarkozy and Merkel to the point that they rushed to declare that they will provide further assistance to Greece and that the private sector can also participate in this scheme on voluntary basis — a highly contested point so far. Nevertheless, with few exceptions, the changes have not impressed the Greek people—who are still waiting for social justice, more just redistribution, and have grown impatient with political parties— and it is unlikely that they will restore the confidence of our foreign creditors. If this new government fails to regain the confidence of the people then we will have early elections. And one thing is certain. From these elections a one party government will not emerge.

The Empire Strikes Back? - Mylonas, Harris (Kathimerini, 2011)
The ripples from the debates in the capitals of European powers concerning military intervention in an oil-producing Middle Eastern country run by an enigmatic dictator once thought to have a WMD program spread far. Accusations of military adventurism under the cloak of humanitarian intervention strain alliances. This could be a description of the relationship between the Bush administration and the United Kingdom on one side, and France and Germany in the 2002–03 buildup to the Iraq War. But now the roles have changed. US Defense Secretary Robert Gates urged caution and limited goals and methods. French President Nicolas Sarkozy and Foreign Minister Alain Juppe recognized the Libyan rebels as the legitimate government and flew the first sorties against targets in Libya before the allies could agree on a proper course of action. Only Germany has remained constant by effectively withdrawing from not only the campaign in Libya, but from its Mediterranean NATO presence. What has changed? The drama of the Surge, followed by the new administration in Washington, made uncertain the possibility of another military intervention in the Middle East or elsewhere. In the US and in France, Obama and the new French President Sarkozy opposed the war in Iraq and sought to rebuild their alliance. Although Sarkozy changed the direction of France’s foreign policy during the Chirac years, Rumsfeld’s label of Old Europe remained. Sarkozy pushed and received parliamentary support for France's military mission in Afghanistan and, while holding the EU rotating presidency, spearheaded the effort to begin negotiations and a ceasefire for the Russia-Georgia War in 2008. France, from the opposition, began turning into a member of the “coalition,” leading up to a more aggressive role patrolling the Horn of Africa, conducting military operations in West Africa, and most recently in the Libyan and Ivory Coast interventions. So what caused this change? New leadership in France, the United Kingdom and the United States? A spirit of multilateralism over unilateralism? Another period of UN activism, similar to the early 1990s—at least before the Somalia failure? The legal explanation would be to assert that unlike the current campaign in Libya, the invasion of Iraq in 2003 had no direct and public support from the United Nations, the European Union, NATO, or the Arab League. However, while UN Security Council Resolution 1973 authorized a no-fly zone over Libya, France acted unilaterally, conducting offensive operations before the allies, both Atlantic and Middle Eastern, agreed to a course of action and the scope of operations. The public support of Arab states, absent in 2003, might have also added to the legitimacy of the French unilaterally beginning kinetic operations and recognizing the rebel leadership. The Tricolor can be seen waving in the streets of Benghazi. But skeptics remain. Following a slow start getting in sync with the "Arab Spring," Sarkozy's charge in Libya comes from a desire to recover prestige lost in Egypt and Tunisia and hopes for his countrymen to rally around the flag during election season. A show of successful military intervention in the cause of humanitarian intervention can help in the polls. Still material determinists look to the oil refineries at Ras Lanuf or Brega and see an explanation there, but Ivory Coast is less of a clear-cut case. While the true motivators for France’s “return” may remain unclear in perpetuity, a more assertive France has large implications for business-as-usual across Europe, the Middle East and Africa. When many European powers have contributed men and firepower to the mission in Libya, the European Union has been remarkably absent. When discussions of the Common Security and Defense Policy of the EU begin, the question "Where were you in Libya?" might be a difficult one to overcome. Ironically, European states seem to take more action when the EU is not involved. Cathy Ashton, the bloc’s high representative for foreign affairs and security policy, was hardly central in the decision to intervene or the coordination of the multinational force. The unintended consequence of Sarkozy’s policy may be the erosion of the EU as a security policy-making institution. Until the crowds in places like Benghazi or Yamoussoukro cheer a flag with golden stars on a blue background, the Tricolor, the Union Jack, and the Stars and Stripes will continue to be the key players in international security.

The End of Peaceful Protest? - Mylonas, Harris (Kathimerini, 2011)
During the three days that the Greek Parliament was discussing and voting on the latest round of austerity measures, 138 police officers were injured, more than 500 protesters were hospitalized with breathing problems caused by the use of tear gas by the police, Syntagma metro station resembled a wartime hospital, tens of protesters were wounded, while 46 demonstrators were taken to police stations and 11 of them arrested on June 29 alone. The police brutality was unprecedented according to Skai news and many witness accounts. Through Twitter, Facebook, email, and text messages, the Greek protesters spread the word of indiscriminate police beatings. A peaceful protester injured by the police called a radio station to express his consternation at the attack he suffered at the hands of the police, “who are supposed to be there to protect citizens.” He further argued that he was there to “protest for Greece and its rights, so why was I attacked by another Greek?” Another citizen claimed that he was almost beaten by motorcycle police while walking around recording the events with a camera and that what saved him was an old expired press pass. At the same time, families were calling in reporting brute force without any provocation on their part. Many citizens, especially older ones, claim that they tried to talk to the police officers and dissuade them from using chemicals against simple protesters but to no avail. Amnesty International had already condemned Greece for the use of force against protesters on June 15. June 29 was much worse. There are several possible explanations for why Greek police used such force. One view is that it was hard for them to tell which were peaceful demonstrators and which were troublemakers. The police might have felt threatened by the mayhem. They may have determined that if they did not strike first, the protesters would attack them. An alternative explanation is that the government wanted to break the “Indignant” movement using force. The vast majority of protesters saw the events as a strategy employed by the state to keep them from protesting. After all, most protesters were family types who were not going to remain there under such circumstances. And as expected, they fled the scene. The ones left were younger, more determined and enraged and, again expectedly, engaged in street fights with the police. Thus, what was a peaceful demonstration that challenged the legitimacy of the government, if not the Parliament as a whole, turned into the “usual” fight between the “known unknowns” -- as they are often referred to -- and the police forces. On top of this, some believe the government planted provocateurs among the peaceful protesters to justify the escalation. Regardless of whether this hypothesis is true or not, the mere perception is damaging to the reputation of the government and the police. Let’s hope that these events have not killed peaceful protest. All this violence was happening while those inside the Parliament had just voted in favor of the new austerity measures. Many think that it was much more convenient for the government that people were discussing police brutality rather than the midterm plan that was being voted on. Regardless of motivation, that was indeed the case. The next day, June 30, when the government had to vote on the implementation law of the plan, there was hardly anyone in the ruins of Syntagma Square and the discussion within the Parliament had turned into a discussion about the quality of democracy and the right of people to demonstrate freely. Public Order Minister Christos Papoutsis, who is ironically now called the citizens’ protection minister, made an analytical distinction between governmental and police responsibility. The head of the main opposition New Democracy party, Antonis Samaras, suggested that the scenes raised questions about the existence of state-sponsored provocateurs. However, ND deputy Manolis Kefaloyiannis later rushed to congratulate the police officers and, together with Health Minister Andreas Loverdos, repeated the high number of police officers wounded during the street battles. The leader of the right-wing nationalist Popular Orthodox Rally (LAOS) party, Giorgos Karatzaferis, suggested that special recognition should be given to the Evzones presidential guards because they remained in position before the Parliament during the fighting despite the fact that tears were running down their faces due to the chemicals used against the protesters. Dora Bakoyannis, the head of the Democratic Alliance political grouping who was expelled from the main opposition ND party in 2010, commented only on the destruction of Hania MPs’ offices by a raging crowd. The parties of the left were furious and suggested that the democratic foundations of the political system have cracked. Of course, in the end the vote passed.

From Possibility to Austerity - Mylonas, Harris (Hürriyet Daily News and Economic Review, 2011)
In the wake of the Cold War, the United States faced an ongoing dilemma of superpower proportions: Should it accept the global policeman’s badge and use its military might to patrol the world’s trouble spots? In many cases, it did. Ironically, following a decade-long spending spree, the question is no longer whether the US should continue honoring this responsibility, but rather whether it can afford to do so. Trumpeting the benefits of economic interdependence around the globe, US policymakers have overlooked the potential costs of free trade and unrestricted capital flows that developing country politicians internalized years ago. Now U.S. officials are reminded that when economic interdependence turns into economic dependence, it creates a harsh reality where the politics of possibility can quickly become the politics of austerity. A growing foreign debt has not only changed US domestic politics, but also infused more of a multilateral tone into its global politics. Notwithstanding the US’s seismic economic and military strength, partisan conflict over domestic budgetary pressures exposes the fault lines of the post-Cold War hegemonic order. Over the last decade, the US government adopted a strategy from the Latin American playbook, opting to use foreign funds to finance its budget deficits. In a management blunder of historic magnitude, George W. Bush swung the federal budget surplus deeply into the red. Borrowing trillions of dollars from foreigners, including China, the Bush administration funneled debt proceeds toward lofty tax cuts, a dual-front war in Iraq and Afghanistan, “global war on terror,” and homeland security spending. Shockingly, the Bush administration not only expanded national debt by one-quarter of its size in eight short years, but in doing so, became increasingly reliant on foreign creditors. This practice was a clear break from the past. By the end of Bush’s time in office, foreigners held about two-thirds of the government’s total debt. In light of the dollar’s global reserve currency status, the US government should continue to readily attract foreign capital for the foreseeable future. However, the US suffers from a more immediate vulnerability. Against the backdrop of the Republicans’ mid-term election victory, spending cuts have again taken center stage. Reminiscent of the Contract for America, House Speaker John Boehner and his cadre of Republican peers are proposing billions in budget cuts that include foreign military and developmental aid. In his State of the Union address, President Obama similarly seized the “post-crisis” political window, emphasizing the need to reverse the country’s “legacy of deficit spending.” The emergence of austerity politics in North America has important geopolitical implications. Is the United States’ ability for global leadership waning? While a wave of democratization and the proliferation of new states flourished in the 1990s under the watchful eyes—and active support—of the United States (and its allies), today this commitment may be wavering. The substantial drop in US foreign aid, investments and contributions toward weak states around the developing world could be seen as important signs of this trend. Pundits have commented on the US absence in the most recent wave of protests in the Middle East; part of this was dictated by the politics of austerity at home. Despite its low-profile and multilateral approach during the Libyan intervention, the Obama administration still met significant domestic resistance from across the political spectrum. In the hopes of enhancing its geopolitical sphere of influence, the US government has often invested in the smallest nations (e.g. trading preferences, IMF financing privileges, military investments, and development aid). Indeed, although the economic rules of the game are skewed in its favor, the US sometimes changes these rules to benefit the smallest nations for political purposes. With the rise of austerity politics, however, the U.S. may not be as willing—or able—to extend such trade and finance benefits to smaller nations. Cloaked in a rhetoric of economic nationalism and austerity, the US may withdraw support from small, strategically less important countries, like Djibouti, placing the latter’s economic and political survival at risk. The US urges developing nations to open their borders, yet it champions “Buy American” shovel-ready projects and its own protection for pharmaceuticals. Refusing to liberalize its agricultural sector, the US has left the multilateral Doha development round mired in a stalemate, instead aggressively negotiating bilateral deals with South Korea, Panama, and Colombia. Faced with such economic institutional gridlock globally and higher budget constraints domestically, does the United States still have the political will and resources to preserve all of its spheres of influence? Is it willing to be the world’s sheriff, especially given its recent difficulties in Afghanistan and Pakistan? There is a very real temptation for the United States to neglect the prosperity and security of the periphery. Mired in its own economic struggles, the US may contemplate withdrawing from its geopolitical commitments. But there is rarely a void in the international system. Other actors, such as Iran, Russia or China, may seek to fill it. Whether conflict is instigated internally such as in Libya or by the interference of stronger neighbors such as in Bahrain, political opportunism could quickly escalate into full-blown conflict. Like the slow plunging of ice shelves into the arctic, the vulnerabilities least visible from the center may be precisely those that most threaten the global system’s long-term viability.

Zakaria's World - Nye, Joseph S., Jr. (Foreign Policy, 2011)
Fareed Zakaria is one of our most perceptive analysts of America's role in the world, and I generally agree with him. But in the case of his new special essay for Time, "Are America's Best Days Behind Us?," I think he paints too gloomy a picture of American decline. Americans are prone to cycles of belief in decline, and the term itself confuses various dimensions of changing power relations. Some see the American problem as imperial overstretch (though as a percentage of GDP, the United States spends half as much on defense as it did during the Cold War); some see the problem as relative decline caused by the rise of others (though that process could still leave the United States more powerful than any other country); and still others see it as a process of absolute decline or decay such as occurred in the fall of ancient Rome (though Rome was an agrarian society with stagnant economic growth and internecine strife). Such projections are not new. As Zakaria notes, America's Founding Fathers worried about comparisons to the decline of the Roman Republic. A strand of cultural pessimism is simply very American, extending back to the country's Puritan roots. English novelist Charles Dickens <a href="http://books.google.com/books?id=u4tnAAAAMAAJ&dq=%22always%20is%20depressed%2C%20and%20always%20is%20stagnated%2C%20and%20always%20is%20in%20an%20alarming%20crisis%2C%20and%20never%20was%20otherwise%22&pg=PA368#v=onepage&q&f=false" target="_blank">observed a century and a half ago: "[I]f its individual citizens, to a man, are to be believed, [America] always is depressed, and always is stagnated, and always is at an alarming crisis, and never was otherwise." In the last half-century, polls showed Americans believed in their decline after the Soviet Union launched Sputnik in 1957, after Richard Nixon's devaluation of the dollar and the oil shocks in the 1970s, and after the closing of Rust Belt industries and the budget deficits of Ronald Reagan's administration in the 1980s. At the end of that decade, a majority of Americans believed their country was in decline; yet within the next 10 years they believed that America was the sole superpower. And now, after the 2008 financial crisis and recession, polls show a majority believes in decline again. These cycles of declinism tell us more about Americans' collective psychology than underlying shifts in power resources, but as British journalist Gideon Rachman argued in these pages recently, maybe this time decline is real. After all, as the Congressional Budget Office warns, on current trends the U.S. national debt will be equal to its GDP in a decade, and that will undermine confidence in the dollar. Zakaria lists other worrying indicators related to education and infrastructure. According to the OECD, American 15-year-olds rank 17th in the world in science and 25th in math. The United States is 12th in college graduation rates, 23rd in infrastructure, and 27th in life expectancy. On the other side of the ledger, America ranks first among rich countries in guns, crime, and debt. All these are very real problems, but one could also note that the United States is still first in total R&D expenditures, first in university rankings, first in Nobel prizes, first on indices of entrepreneurship, and according to the World Economic Forum, the fourth-most competitive economy in the world (behind the small states of Switzerland, Sweden, and Singapore).The United States remains at the forefront of technologies of the future like biotechnology and nanotechnology. This is hardly a picture of absolute economic decay, ancient Rome style. The truth is that one can draw a picture of the United States today that emphasizes either dark or bright colors without being wrong. No one can be sure which shade better portrays the future because the number of potential futures is vast, and which one comes to pass will depend in part on decisions not yet made. Drawing on the thinking of Mancur Olson, the late great political economist, Zakaria believes that America's very success has made its decision processes sclerotic, like that of industrial Britain. But American culture is far more entrepreneurial and decentralized than that of Britain, where the sons of industrial entrepreneurs sought aristocratic titles and honors in London. If Olson is right, Zakaria says, the solution is to "stay flexible." And despite recurrent historical bouts of concern about it, immigration helps keep America flexible. In 2005, according to Forbes, foreign-born immigrants had participated in one of every four technology start-ups in the previous decade. As Singapore's Lee Kuan Yew once put it, China can draw on a talent pool of 1.3 billion people, but the United States not only draws on a talent pool of 7 billion, but can recombine them in a diverse culture that enhances creativity in a way that ethnic Han nationalism cannot. Zakaria also worries about the inefficient American political system. But the Founding Fathers created a system of checks and balances precisely to preserve liberties at the price of efficiency. Moreover, just because we are now going through a period of excessively partisan politics and mistrust of government doesn't mean the American political system is in decline. Some aspects of the current mood are probably cyclical and related to unemployment, while others represent discontent with the bickering and deadlock in today's political process. Compared with the recent past, party politics has indeed become more polarized, but nasty politics is nothing new and goes all the way back to the Founding Fathers. Supporters of John Adams reputedly once called Thomas Jefferson "a mean-spirited, low-lived fellow, the son of a half-breed Indian squaw, sired by a Virginia mulatto father." Part of the problem of accurate assessment is that faith in government became abnormally high among the generation that survived the Great Depression and won World War II. Over the long view of American history, it was overconfidence in government in the 1950s and early 1960s, not low levels thereafter, that was the anomaly. American government and politics have always had problems, sometimes worse than today's. In assessing political decline, one must beware of the golden glow of the past. It is easy to show decline if one compares the good in the past with the bad in the present. In addition, we sometimes mistakenly idealize the efficiency of the political process in authoritarian countries like China. When it comes to infrastructure, for example, it is far easier to build high-speed rail lines where there are weak property rights and few lawyers. But if one looks at the important question of how Chinese leaders are struggling to implement their 12th five-year plan -- reducing dependence on exports, shifting to internal demand, and reducing regional inequality by moving industry to the west -- China is far from efficient. Although central bankers and economic planners know that revaluing the yuan would promote these goals and help head off inflation, a strong coalition of coastal export industries and associated local party bosses seeks to preserve the status quo. Zakaria notes that one Asian country after another is learning the secrets of Western success, and he is right. In The Future of Power, I argue that one of the two great power shifts of this century is the recovery of Asia to what it represented before the Industrial Revolution led to the ascendance of the West: more than half the world's population and its economic production. We should herald Asia's recovery -- it has brought millions out of dire poverty-- but those with excessive fear of China should remember that Asia is not one entity. In his important book Rivals, Bill Emmott reminds us that Japan, India, and others that are concerned about the rise of China welcome an American presence. Can anyone similarly imagine Canada and Mexico seeking a Chinese alliance to balance American power in their neighborhood? Nor is China likely to surpass America anytime soon. Yes, barring political uncertainties, China's size and high rate of economic growth will almost certainly increase its strength relative to that of the United States. Still, China won't necessarily become the world's most powerful country as a result. Even if China suffers no major domestic political setback, many of the current projections based on GDP growth alone are too one-dimensional. They ignore what are likely to be enduring U.S. military and soft-power advantages, as well as China's geopolitical disadvantages in the internal Asian balance of power. Zakaria is correct that the United States faces serious problems. But issues that preoccupy us today, such as long-term debt, are not insoluble; see for example, the recommendations of the Simpson-Bowles commission, and remember that only a decade ago some people worried about the government surplus. Of course, such solutions may forever remain out of reach. But it is worth distinguishing situations for which there are no solutions from those that could, in principle, be solved. The greatest danger to America is not debt, political paralysis, or China; it is parochialism, turning away from the openness that is the source of its strength and resting on its laurels. As Zakaria says, in the past, worrying about decline has helped avert it. Let us hope that his intelligent though darkly drawn picture will yet again start that healthy process.

America’s Choices—and Their Costs - Allison, Graham T., Jr. (Boston Globe, 2011)
America's last 10 years might be called “The Decade the Locusts Ate.’’ A nation that started with a credible claim to lead a second American century lost its way after the terrorist attacks of Sept. 11, 2001. Whether the nation will continue on a path of decline, or, alternatively, find our way to recovery and renewal, is uncertain. The nation began the decade with a growing fiscal surplus and ended with a deficit so uncontrolled that its AAA credit rating was downgraded for the first time in its history. Ten years on, Americans’ confidence in our country and the promise of the American Dream is lower than at any point in memory. The indispensable superpower that entered the decade as the most respected nation in the world has seen its standing plummet. Seven out of every 10 Americans say that the United States is worse off today than it was a decade ago. While many of the factors that contributed to these developments were evident before 9/11, this unprecedented reversal pivots on that tragic day - and the choices made in response to it. Those choices had costs: the inescapable costs of the attack, the chosen costs, and the opportunity costs. Inescapable costs of 9/11 must be counted first in the 3,000 innocent lives extinguished that morning. In addition, the collapse of the World Trade Center and part of the Pentagon destroyed $30 billion of property. The Dow plunged, erasing $1.2 trillion in value. Psychologically, the assault punctured the “security bubble’’ in which most Americans imagined they lived securely. Today, 80 percent of Americans expect another major terrorist attack on the homeland in the next decade. Were this the sum of the matter, 9/11 would stand as a day of infamy, but not as an historic turning point. Huge as these directs costs are, they pale in comparison to costs of choices the United States made in response to 9/11: about how to defend America; where to fight Al Qaeda; whether to attack Iraq (or Iran or North Korea) on grounds that they had chemical or biological weapons that could be transferred to Al Qaeda; and whether to pay for these choices by taxing the current generation, or borrowing from China and other lenders, leaving the bills to the next generation. Unquestionably, much of what was done to protect citizens at home and to fight Al Qaeda abroad has made America safer. It is no accident that the United States has not suffered further megaterrorist attacks. The remarkable intelligence and Special Forces capabilities demonstrated in the operation that killed Osama bin Laden suggest how far we have come. But the central storyline of the decade focuses on two choices made by President George W. Bush—his decision to go to war with Iraq and his commitment to cut taxes, especially for wealthy Americans, and thus not to pay for the wars in Iraq and Afghanistan. The cost of his decision to go to war with Iraq is measured in 4,478 American deaths, 40,000 Americans gravely wounded, and a monetary cost of $2 trillion. Bush justified his decision to attack Iraq on the grounds that Saddam Hussein might arm terrorists with weapons of mass destruction, arguing that “19 hijackers armed by Saddam Hussein… could bring a day of horror like none we have ever known.’’ In retrospect, even Bush supporters agree that we went to war on false premises—since we now know that Saddam had no chemical or biological weapons. Suppose, however, that chemical weapons had been found in Iraq. Would that have made Bush’s choice a wise decision? What about the many other states that had chemical or biological weapons that could have been transferred to Al Qaeda, for example Libya, or Syria, or Iran? What about the state that unquestionably had an advanced nuclear weapons program, North Korea, which took advantage of the US preoccupation with Iraq to develop an arsenal of nuclear weapons and conduct its first nuclear weapons test? As for cutting taxes for the wealthy, Bush’s decision left the nation with a widening gap between government revenues and its expenditures. Brute facts are hard to ignore: having entered office with a budgetary surplus that the CBO projected would total $3.5 trillion through 2008, Bush left office with an annual deficit of over $1 trillion that the CBO projected would grow to $3 trillion over the next decade. Finally, and most difficult to assess, are opportunity costs, what could be Robert Frost’s “road not taken.’’ In the immediate aftermath of 9/11, the United States was the object of overwhelming international sympathy and solidarity. The leading French newspaper declared: “We are all Americans.’’ Citizens united behind their commander in chief, giving him license to do virtually anything he could plausibly argue would defend us against future attacks. This rare combination of readiness to sacrifice at home plus solidarity abroad sparked imagination. Would Americans have willingly paid a “terrorist tax’’ on gas that could kick what Bush rightly called America’s “oil addiction’’? Could an international campaign against nuclear terrorism or megaterrorism have bent trend lines that leave Americans and the world increasingly vulnerable to future biological or nuclear terrorist attacks? What impact could $2 trillion invested in new technologies have had on American competitiveness? That such a decade leaves Americans increasingly pessimistic about ourselves and our future is not surprising. American history, however, is a story of recurring, impending catastrophes from which there is no apparent escape—followed by miraculous recoveries. At one of our darkest hours in 1776 when defeat at the hands of the British occupying Boston seemed almost certain, the general commanding American forces, George Washington, observed: “Perseverance and spirit have done wonders in all ages.’’

The I-Word - Rogoff, Kenneth S.; Neyfakh, Leon (Boston Globe, 2011)
Like corruption, crime, and asbestos, “inflation” is a word that many Americans imagine in all-red capital letters, flashing across TV screens amid warnings of crisis. For anyone who remembers the gloomy, scary 1970s, when the inflation rate in the United States reached double digits, the word is shorthand for an economy that has spiraled out of control, the dollar losing value and prices climbing feverishly. “Inflation is as violent as a mugger, as frightening as an armed robber, and as deadly as a hit man,” said Ronald Reagan in 1978, as nervous citizens imagined the day when they’d have to push a wheelbarrow full of cash to the grocery store in order to buy a loaf of bread. That particular nightmare never came to pass, thanks to drastic measures taken by the Federal Reserve. For the better part of the past 30 years, the dollar has stayed stable, reassuring American families and the nation’s trading partners, with the central bank standing guard over the economy and doing everything necessary to keep inflation low. You might say that Kenneth Rogoff has been one of the guards. As a research economist at the Federal Reserve during the first half of the 1980s, he helped ensure that the word “inflation” would never again flash across American TV screens. His reputation as a conservative-minded inflation hawk followed him from the Fed to the International Monetary Fund to his current position in the economics department at Harvard. But then came the financial crisis of 2008, and the ensuing slump. And as the economy has continued to stagnate, Rogoff, 58, has become the flag-bearer for an unlikely position: that as we struggle to help the economy find its way out of the darkness, inflation could be the answer. It’s time, Rogoff says, to put Reagan’s “hit man” to work for the good guys. Over the past several years, Rogoff has emerged as one of the world’s leading experts on the history of financial crises and how they work, a unique perch that has given him a long view on what is happening to our economy and what lies ahead. In the bestselling 2009 book “This Time Is Different,’’ he and Carmen Reinhart, currently a senior fellow at the Peterson Institute for International Economics , laid out a detailed analysis of financial crises that have taken place around the world going back 800 years, and they put forth an alarming idea about our current predicament. What we’re going through, they argued—what we’ve been going through ever since the subprime mortgage crisis—has not been just a typical recession, as our leaders have been treating it, but something much worse, something that demands altogether different tools to stop it. One of these tools, Rogoff believes, is a temporary burst of inflation. And for the past several weeks, as the stock market has convulsed and debate raged over the Fed’s next move, he has been making his case publicly, through syndicated opinion columns, high-profile TV appearances, and numerous interviews. It’s an argument that Rogoff himself admits is “radical,” and one he says he’d rather not be making. But as he sees it, what’s holding the country back from recovery is not just a lack of consumer confidence or suppressed demand, as in a normal recession, but an immense overhang of debt: thanks to the collapse of the real-estate bubble, millions of American families owe so much to banks that they’re focusing all their energy on paying down their debts instead of spending their money on new investments. There will be no recovery until the painful process of working through that debt is behind us, Rogoff argues, and an increase in the annual inflation rate, which has floated around 2 percent since the early 1990s,would make it easier for debtors to pay down what they owe. “There’s no penicillin for this,” he said in an interview. “There’s no quick getting better. What you’re really talking about is taking the edge off the downturn and coming back to normal growth somewhat faster.” Rogoff’s call to raise inflation has come under attack from several different directions. Some economists think it wouldn’t do any good—that trying to raise inflation wouldn’t create demand or spur growth the way Rogoff thinks—while others believe that, given that prices actually seem to be in danger of falling at the moment, the Fed couldn’t make it happen if it wanted to. But perhaps the biggest problem for Rogoff is that, for most policymakers, elected and otherwise, the idea of courting inflation on purpose sounds downright crazy—not to mention politically disastrous. “Going around the country saying, ‘We need more inflation’ is not going to be a big seller,” said Michael Mussa, a senior fellow at the Peterson Institute and a former adviser to Reagan. “Inflation means that the costs of everybody’s goods and services are going up … And I believe it’s a substantial symbol of mismanagement by the government and the central bank.” Rogoff, however, remains convinced that as the situation grows more desperate, our leaders will feel pressure to start considering their options with more open minds. “As more and more people realize that we’re not quickly going back to normal,” he said, “they become more flexible.” Though Rogoff speaks with unflinching steadiness, hearing him explain how badly our leaders misdiagnosed the economy after the crash, one imagines a doctor banging his fists against the door of a surgery ward, trying to warn his colleagues that he has checked their patient’s chart and realized they’re about to make a huge mistake. The mistake we all made, as Rogoff sees it, was thinking this was going to be nothing more than a regular recession, the same kind of thing that has happened in the United States once or twice every decade for the past 150 years. These cyclical recessions come and go, and we have a pretty reliable playbook for dealing with them: usually, an increase in government spending and lower interest rates to encourage money to flow. Recessions tend to end after about a year, at which point unemployment starts to fall and normal growth resumes. Far less frequently, something more serious grips an economy: a financial crisis that breaks the pattern, and from which it is much more difficult to recover. Rogoff and Reinhart’s book suggests that such contractions are characterized above all by severe, widespread debt, which leads to long periods of economic stagnation and uncertainty. Rogoff puts our current situation in that category, along with the Great Depression, and he fears that if we do not act quickly and creatively to dig ourselves out of it, we risk settling into a long-term slowdown along the lines of what Japan has been going through since the 1990s. Mistaking this crisis for a typical recession, he says, is like mistaking pneumonia for a stubborn cold. “They’re very, very different animals.” The animal we’re wrestling with today, of course, was born of the vastly overheated real estate market that collapsed in 2007, temporarily paralyzing the global financial system and taking some powerful banks down with it. Today, its legacy is a towering mountain of consumer debt, government debt, and millions of underwater mortgages that are gumming up the economy and preventing it from coming back to life. “It’s very unlikely that all these debts are going to get repaid in full,” Rogoff said. Banks have loans on their books that people simply don’t have—won’t have—the money to pay off, and expecting it to happen means we’ll just stay frozen in place, waiting. What needs to happen, Rogoff says, is “some transfer from creditors to debtors.” The ideal way for that to happen, he says, would be through loan renegotiation, whereby banks would forgive some homebuyers and strike repayment deals with others. But that sort of piecemeal renegotiation has proved very difficult to carry out. A more viable way to start fixing the nation’s balance sheets, Rogoff argues, is by inducing a temporary bout of inflation. If the Federal Reserve raises its target inflation rate by several percentage points—up from around 2 percent, where it’s been for the past decade, to somewhere in the neighborhood of 4 to 6 percent—and injects new money into the economy until it gets there, then debtors will get some relief and the wheels of the economy will once again start to turn. Rogoff first laid out the argument for embracing inflation in one of his columns in December of 2008—a move that came as such a surprise to people who knew his reputation that he got letters from central bankers who were sure they’d misunderstood him. Rogoff had worked at the Fed under none other than Paul Volcker, whose mandate as Fed chairman was to drive inflation down at any cost. Under Volcker’s watch, inflation fell from 13.3 percent in December of 1979 to just 3.8 percent four years later. And though Rogoff at the time was just starting out as an economist—indeed, he was still transitioning from his first career as a professional chess player—he soon became an intellectual force in the movement to make central banks the economy’s first defense against inflation. In 1985, he published what would become one of his most widely cited academic papers in the Quarterly Journal of Economics, arguing that healthy economies depended on central banks being reliably committed to holding inflation down in all but the most extreme circumstances. Rogoff says he hasn’t changed his mind on how central banks should behave, and still thinks our fears of runaway inflation are well-founded. He just thinks that right now, it’s a risk worth taking. “There’s certainly some benefit in a society having a very, very strong conviction about keeping low inflation,” Rogoff said. “But I think right now it’s not helpful. You can have a very strong conviction that you don’t want to take medicines … And I respect that, but there are times when there’s really no choice.” Though Rogoff’s idea about raising inflation has so far not gained much purchase in the economics profession - Mussa, for instance, called it “a hare-brained crackpot scheme”— he is not alone in his thinking. Versions of the same call have been taken up by several prominent economists across the political spectrum, including Olivier Blanchard, the chief economist at the International Monetary Fund; Joshua Aizenman, co-editor of the Journal of International Money and Finance; Harvard’s Greg Mankiw, a former adviser to George W. Bush; and Paul Krugman, the Nobel Prize-winning New York Times columnist. THOSE WHO disagree with Rogoff cite several key objections. One is that inflation can be hard to stop once it starts: if the Fed turned on the spigot, there’s no guarantee they’d be able to turn it off before inflation got out of hand. Another objection is that if the Fed does raise its inflation target, pumping more money into the system and allowing the dollar to lose some of its value, lenders here and abroad will lose faith in the currency and respond by raising interest rates, which would ultimately make it harder for Americans to borrow money. A third objection is practical: that even if the Fed tried to trigger inflation, it simply might not be able to. The problem with the economy right now, some critics say, is a lack of demand for workers and products, and blowing air into the money supply would not change that. “This idea that there’s some separate policy instrument called ‘creating inflation,’ I think, is a little problematic,” said Lawrence Summers, the former secretary of the Treasury and Harvard president who also served as the director of President Obama’s National Economic Council. Increasing demand should be the primary goal, with inflation a possible byproduct, Summers said. “I don’t think the idea that you could simply get more inflation by saying you want more inflation is a promising one.” Rogoff is not swayed by these arguments. He emphasizes that the level of inflation he is calling for is very modest—and that there’s no really no reason to think that the Fed would be incapable of inducing it or reining it in at will. As for damaging the central bank’s credibility, Rogoff reiterates the extraordinary nature of the present circumstances. “This is a very exceptional situation—a once in Halley’s Comet kind of phenomenon,” he said. As he wrote in his column earlier this month, “These are times when central banks need to spend some of the credibility that they accumulate in normal times.” Trying to persuade central bankers to go for that plan involves a different kind of problem: a political one. Inflation devalues the dollar and makes things more expensive, making it an easy political target. Earlier this month, as Wall Street and Washington waited to hear how the Fed would approach monetary policy going forward, Texas Governor Rick Perry more or less threatened Fed chairman Ben Bernanke with violence if he “prints more money” before the next election. What he was talking about wasn’t even inflation, but a policy called “quantitative easing,” in which the Federal Reserve injects new money into the economy by buying billions of dollars worth of Treasury bonds from banks. The Fed has already tried this twice since 2008, and each time it has been controversial. While Rogoff’s plan to raise the inflation rate target is conceptually different from quantitative easing, it would involve the same mechanism, and would push the same political buttons in an even more extreme way. Underlying that opposition is more than just patriotism: it’s also a moral objection. Transferring the debt burden from borrowers to creditors, after all, effectively bails out borrowers by punishing the banks that lent them money, as well as devaluing the savings of their more prudent neighbors. That kind of rescue plan strikes many as fundamentally unfair. Rogoff understands this objection, and doesn’t dispute that what he’s proposing is on some level unfair. But ultimately, he argues, this contraction is dragging us all down together, and even those lenders and savers will be better off if America’s debt overhang is taken care of swiftly. Once that happens, and the economy starts to recover properly, we’ll be able to focus on designing better policies that will make us less vulnerable to financial crisis in the future. For now, a little inflation might just be the cost of getting us to where that might be possible. “One way or another,” said Rogoff, “we’re going to be doing things we would not dream we would ever do before this is over.”

Op-ed Moment: How to Protect the Homeland - Nye, Joseph S., Jr. (the New York Times, 2011)
Joseph S. Nye: ‘Protect the Homeland’ Joseph S. Nye reflects on his Op-Ed from Sept. 25, 2001, about the strategies needed to defeat terrorism. Read the original Op-ed, “How to Protect the Homeland.” <iframe src="http://graphics8.nytimes.com/bcvideo/1.0/iframe/embed.html?videoId=100000001044548&playerType=embed" marginheight="" marginwidth="" id="nyt_video_player" title="New York Times Video - Embed Player" frameborder="" height="373" scrolling="no" width="480">

Crashing the Tea Party - David E. Campbell; Putnam, Robert D. (New York Times, 2011)
Given how much sway the Tea Party has among Republicans in Congress and those seeking the Republican presidential nomination, one might think the Tea Party is redefining mainstream American politics. But in fact the Tea Party is increasingly swimming against the tide of public opinion: among most Americans, even before the furor over the debt limit, its brand was becoming toxic. To embrace the Tea Party carries great political risk for Republicans, but perhaps not for the reason you might think. Polls show that disapproval of the Tea Party is climbing. In April 2010, a New York Times/CBS News survey found that 18 percent of Americans had an unfavorable opinion of it, 21 percent had a favorable opinion and 46 percent had not heard enough. Now, 14 months later, Tea Party supporters have slipped to 20 percent, while their opponents have more than doubled, to 40 percent. Of course, politicians of all stripes are not faring well among the public these days. But in data we have recently collected, the Tea Party ranks lower than any of the 23 other groups we asked about—lower than both Republicans and Democrats. It is even less popular than much maligned groups like “atheists” and “Muslims.” Interestingly, one group that approaches it in unpopularity is the Christian Right. The strange thing is that over the last five years, Americans have moved in an economically conservative direction: they are more likely to favor smaller government, to oppose redistribution of income and to favor private charities over government to aid the poor. While none of these opinions are held by a majority of Americans, the trends would seem to favor the Tea Party. So why are its negatives so high? To find out, we need to examine what kinds of people actually support it. Beginning in 2006 we interviewed a representative sample of 3,000 Americans as part of our continuing research into national political attitudes, and we returned to interview many of the same people again this summer. As a result, we can look at what people told us, long before there was a Tea Party, to predict who would become a Tea Party supporter five years later. We can also account for multiple influences simultaneously—isolating the impact of one factor while holding others constant. Our analysis casts doubt on the Tea Party’s “origin story.” Early on, Tea Partiers were often described as nonpartisan political neophytes. Actually, the Tea Party’s supporters today were highly partisan Republicans long before the Tea Party was born, and were more likely than others to have contacted government officials. In fact, past Republican affiliation is the single strongest predictor of Tea Party support today. What’s more, contrary to some accounts, the Tea Party is not a creature of the Great Recession. Many Americans have suffered in the last four years, but they are no more likely than anyone else to support the Tea Party. And while the public image of the Tea Party focuses on a desire to shrink government, concern over big government is hardly the only or even the most important predictor of Tea Party support among voters. So what do Tea Partiers have in common? They are overwhelmingly white, but even compared to other white Republicans, they had a low regard for immigrants and blacks long before Barack Obama was president, and they still do. More important, they were disproportionately social conservatives in 2006—opposing abortion, for example—and still are today. Next to being a Republican, the strongest predictor of being a Tea Party supporter today was a desire, back in 2006, to see religion play a prominent role in politics. And Tea Partiers continue to hold these views: they seek “deeply religious” elected officials, approve of religious leaders’ engaging in politics and want religion brought into political debates. The Tea Party’s generals may say their overriding concern is a smaller government, but not their rank and file, who are more concerned about putting God in government. This inclination among the Tea Party faithful to mix religion and politics explains their support for Representative Michele Bachmann of Minnesota and Gov. Rick Perry of Texas. Their appeal to Tea Partiers lies less in what they say about the budget or taxes, and more in their overt use of religious language and imagery, including Mrs. Bachmann’s lengthy prayers at campaign stops and Mr. Perry’s prayer rally in Houston. Yet it is precisely this infusion of religion into politics that most Americans increasingly oppose. While over the last five years Americans have become slightly more conservative economically, they have swung even further in opposition to mingling religion and politics. It thus makes sense that the Tea Party ranks alongside the Christian Right in unpopularity. On everything but the size of government, Tea Party supporters are increasingly out of step with most Americans, even many Republicans. Indeed, at the opposite end of the ideological spectrum, today’s Tea Party parallels the anti-Vietnam War movement which rallied behind George S. McGovern in 1972. The McGovernite activists brought energy, but also stridency, to the Democratic Party—repelling moderate voters and damaging the Democratic brand for a generation. By embracing the Tea Party, Republicans risk repeating history.

The Downgrading of a Debtor Nation - Frieden, Jeffry; Chinn, Menzie D. (New York Times, 2011)
The Treasury can cry foul all it wants, but the decision by Standard & Poor’s to downgrade America’s credit rating by one notch last Friday, and the subsequent plunge in the stock market, are serious symptoms of a loss of confidence—an assessment that is fundamentally political, not economic. There is little question about the technical ability of America to make good on its debts—but there are grave questions about the political system’s ability to resolve our nation’s financial problems. The debt-ceiling deal between President Obama and Congressional Republicans merely staved off a crisis of confidence for the moment. It does not address our immediate need to avoid falling back into recession, or our longer-term need to raise enough revenue to pay for the social spending Americans want. Moreover, the deal sidesteps the fundamental challenge the country now faces: who will pay to fix what was broken during the past decade by irresponsible tax cuts, ruinously expensive wars, failures of regulation and the resulting housing and financial booms and busts? In the short term, the plan cuts a bit of discretionary nondefense spending, a category that in fact has not grown particularly rapidly. This is a mistake. With unemployment at 9.1 percent, and long-term joblessness at record levels, we need more spending, not less. But the agreement all but rules out new spending to boost the economy, at a dangerous time. The chances of a double-dip recession are growing—and a further slowdown will increase, not reduce, the budget deficit. The longer-term spending and revenue commitments are no better. Certainly spending, in particular on Medicare and Medicaid, needs to be restrained. But the deficits cannot be reined in without tax increases, and the “framework” does little or nothing in this regard. The S. & P. decision to downgrade reflects, in large part, the expectation that Republicans will not allow the Bush tax cuts to expire. The recent skirmishes all dance around the central issue: the United States is in the midst of the world’s largest debt crisis. The Treasury now owes the public almost $10 trillion, including $4.5 trillion to foreigners—and that doesn’t include what households and companies owe. For decades to come, Americans will face the core problem of every heavily indebted nation: who will bear the burden of adjustment? Countries borrow for many purposes: canals and railroads in the 19th century, factories and highways in the 20th, and in the last decade, a housing and financial boom in Europe and America. When the projects don’t pan out and the debtor country falls into crisis, what happens to the accumulated debts? Who pays? Creditors or debtors? Workers or investors? Rich or poor? The European Union is tearing itself apart over this question, which divides creditor nations from debtor nations and which divides groups within nations. The American variant of this conflict is just beginning. Perhaps, some Americans believe, we can shunt the adjustment costs onto foreigners. Indeed, our creditors worry that the United States will reduce its debt burden the old-fashioned way, by inflating it away. A few years of moderate inflation, and a weaker dollar, would significantly lessen the real cost of servicing the country’s debts—at our creditors’ expense. But adjusting to the reality of America’s accumulated debts will inevitably require sacrifices at home. The battle over who will be sacrificing has already begun, albeit under veils of rhetoric. The Republicans seem unconcerned about stimulating recovery, and primarily concerned that none of the long-term costs of balancing our budget be paid by upper-income taxpayers. No surprise: unemployment among the one-third of Americans with the highest incomes is barely 4 percent, while for the lowest third it is more than four times that level. The Democrats, for their part, seem content to insist that the adjustment burden not fall on beneficiaries of government spending, whether public employees or recipients of social spending. This reflects their base in the labor movement, the public sector and the poor. We lost the first decade of the 21st century by squandering our wealth and borrowing as if there was no tomorrow. We risk losing this decade to an incomplete recovery and economic stagnation. An economically responsible, politically feasible distribution of the costs of working our way out of the crisis will require higher taxes, a more efficient tax code, and restrained growth of social spending, particularly Medicare. To ignore these realities, and the contentious choices they entail, is merely to postpone the inevitable day of reckoning—and probably to make it worse.

Famine in Somalia: What Can the World Do About It? - Paarlberg, Robert L. (The Atlantic, 2011)
In Somalia today, there are ominous parallels with 1992: pervasive fighting among rival clans, far too little rain, and an inability among international peacekeeping forces to restore order or ensure that food aid reaches those in need. Nineteen years ago, the result was the death by starvation of 300,000 Somalis. Will it happen again? It doesn't have to. But everything depends on how the world responds. In some ways, the current situation is more complicated. One reason lies outside of Somalia altogether: the painful set of memories associated with our attempts to help in 1992, particularly in the United States. Then, the U.S. response was a forceful military intervention. President George H.W. Bush dispatched 25,000 American troops to Somalia, allowing food deliveries to resume, and preventing as many as 200,000 additional deaths. But in October 1993, famously, two Black Hawk helicopters were shot down in Mogadishu, 18 U.S. soldiers died, and the body of one dead American was dragged triumphantly through the streets. Public outrage forced President Clinton to terminate the mission. As a consequence, it's unlikely that U.S. policy makers will come close to taking similarly dramatic steps today. Meanwhile, two factors on the ground in Somalia itself threaten to make the current crisis more dangerous than the previous one. First, the drought is much worse this time -- perhaps the worst of its kind in 60 years. Second, there is now an Islamist militant organization, Al-Shabab, controlling the southern region of Somalia, where the drought has been most severe. The 2 million people living in this region cannot get food aid, because Al-Shabab's leadership, which brags about its close ties to Al-Qaeda, distrusts food-aid workers as spies. The propaganda they project among those living under their control is that it is better to starve than to accept help from the West. Under these seemingly intractable circumstances, what can those outside Somalia do to prevent mass deaths on the scale of the 1990s? Setting up relief camps in neighboring countries and waiting for starving Somalis to walk across the border is not a good option, because many do not survive the trip, and those that do become helpless refugees. Camps along Somalia's borders with Kenya and Ethiopia already hold 500,000 destitute people. Paying large bribes to Al-Shabab fighters could get some food through on the ground, but it is obviously not a sustainable solution, among the reasons being that the government agencies financing the aid will not ultimately tolerate it. Dropping food from UN airplanes will help, but not nearly on the scale needed to make a significant difference. The best policy option that the international community has available to it in Somalia is to support as much as possible the feeding operations now underway in the sizeable territories not controlled by Al-Shabab. The United Nations World Food Programme (WFP) is currently feeding 1.5 million people in Somalia, including 300,000 in Mogadishu itself, but these operations are constantly in danger of running out of resources. For the Horn of Africa as a whole, WFP is facing a funding shortfall of $252 million, so those wishing to help can start by focusing on ways to make up this shortfall. The international community can also do things beyond Somalia, and indeed beyond the exigencies of emergency food aid. Rich nations, including the United States, can start by delivering the support they have promised to build Africa's own food-production capabilities. Small farmers throughout sub-Saharan Africa need help to boost their productivity. If you visit a typical farming community in Uganda, or Kenya, or Cameroon, or Benin, most of those you meet will be women, most will be illiterate, and most will be living at least a 30-minute walk from the nearest paved road. As well, most will be farming with hand hoes, no irrigation, no electrical power, no modern seeds, and no veterinary medicine for their animals. These women are hardworking and highly resourceful, yet the returns on their labor are minimal because they have so little to work with. Their cereal crop yields are only one-tenth as high as those in Europe or North America, their average income is only $1 a day, and one-in-three of them is undernourished. What these farming communities need, above all else, is increased public investment in rural roads, electrical power, irrigation, clinics, schools, and agricultural research. But in recent decades, most African governments failed to make these investments because of a lack of international support. Between 1978 and 2006, the share of World Bank loans that went to agricultural development fell from 30 percent to only 8 percent. The United States has also reduced its aid to small farmers since the 1980s. U.S. official development assistance to agriculture in Africa fell from $400 million annually in the 1980s to only $60 million by 2006. The political right promoted this abandonment of agricultural-development assistance on the erroneous assumption that private investment alone could do the job. The political left went along on the equally erroneous belief that modernizing African farming might be bad for social justice and the environment. As international donors walked away from long-term agricultural-development efforts in Africa, per capita food production fell, leading predictably to an even greater need for emergency food aid. By 2006, perversely, the United States was spending 20 times as much shipping free food to Africa as it was spending to help Africans produce their own food. A shock of much higher world food prices in 2008 finally led donors to promise revived support for Africa's smallholder farmers. President Obama announced in 2009 that he would ask Congress for a doubling of U.S. agricultural-development assistance worldwide, up to more than $1 billion by 2010. Later that year, at a summit meeting of the G8, he convinced the world's rich nations to pledge $22 billion collectively over three years to promote food security and agricultural development. By 2010, however, donors in Europe were facing a debt crisis, opted for budget austerity, and began backing away from these promises. In the United States, the right - and the Tea Party movement, in particular -- began demanding budget cuts as well. In fiscal year 2011, Congress accordingly cut the expected U.S. contribution to a new Global Agricultural Food Security Program from $400 million down to only $100 million. And now a House Appropriations subcommittee has just cut FY 2012 funding for the Obama Administration's Feed the Future program by 18 percent. Only about half of 1 percent of our federal budget goes to poverty-focused foreign aid, so cutting these programs will have no significant budget impact at home -- only damaging humanitarian effects abroad. In Somalia, if these effects are to be prevented from cascading into a full-scale disaster of the kind the country suffered through in the 1990s, the international community will have to focus as much effort as possible, as quickly as possible, where we can be most effective. This will mean covering shortfalls to protect current WFP feeding operations in the Horn of Africa. But also, especially from the United States, it will mean delivering on promised support for farming across Africa (which in turn will depend on Congressional appropriations committees feeling as much pressure as the U.S. public can muster that they deliver on this promised support). Around the Horn of Africa today, roughly 11 million people face food risks, while on the continent as a whole there are now an estimated 390 million Africans consuming less than the nutritional target of 2,100 calories per day. Most of these hungry people are farmers. Understanding what they need for a sustainable response to the food crisis they face, and responding to that need directly, will be the pivotal challenge in alleviating African famine.

How to fix the U.S. economy - Rogoff, Kenneth S.; Krugman, Paul; Zakaria, Fareed (CNN World, 2011)
On Sunday, I talked about about Wall Street's wild week with two of the world's top economists. We discussed what the market volatility means or doesn't mean, and what may lay behind it and what lies ahead of us. Paul Krugman won the 2008 Nobel Prize in Economics, and he is a columnist for The New York Times. Kenneth Rogoff is a former chief economist at the International Monetary Fund, now a professor of economics at Harvard University. Here's a lightly edited transcript of our conversation: Fareed Zakaria: Paul, let me start with you. The one thing we saw over the week was markets up, markets down, but the one trend that seemed persistent was there is a great demand for U.S. treasuries despite the fact that the S&P downgraded it. You've been talking a lot about this. Explain in your view what does it mean that in moments like this U.S. treasuries are still in demand and what that does is push interest rates even lower than they are. Paul Krugman: Well, what it tells you is that the investors, the market, are not at all afraid of what the policy elite or people like Standard & Poor's are telling them they should be afraid of. You know, we've got all of Washington, all of Brussels, all of Frankfurt saying debt, deficits, this is the big problem. And what we actually have in reality is markets are terrified of prolonged stagnation, maybe another recession. They still see U.S. government debt as the safest thing out there, and are saying, if this was a reaction of the S&P downgrade, it was the market's saying, "We're afraid that that downgrade is going to lead to even more contractionary policy, more austerity, pushing us deeper into the hole." So it's a reality test, right? So we just had a wake-up call that said, "Hey, you guys have been worrying about the entirely wrong things. The really scary thing here is the prospect of what amounts toa somewhat reduced version of the Great Depression in  the Western world." Fareed Zakaria: Ken Rogoff, worrying about the wrong thing? Ken Rogoff: Well, I think the downgrade was well justified. It's a very volatile world. And the reason there's still a demand for treasuries is they've been downgraded a little bit to AA plus. That looks pretty good compared to a lot of the other options right now. It's a very, very difficult time for investors. There is a financial panic going on at some level. Some of it's adjusting to a lower growth expectations, maybe a third of what we're seeing. Two-thirds of it is the idea no one's home – not in Europe, not in the United States. There's no leadership. And I really think that's what's driving the panic. Fareed Zakaria: But you wrote in an article of yours that you think that this is part of actually a broader phenomenon which is that people are realizing this is not a classic recession, this is not a classic cyclical downturn. This is what you call a "Great Contraction". Explain what you mean by that. Ken Rogoff: Well, recessions we have periodically since World War II, but we haven't really had a financial crisis as we're having now. And Carmen Reinhart and I think of this as a great contraction, the second one, the first being the Great Depression, where it's not just unemployment, it's not just output, but it's also credit, housing and a lot of other things which are contracting. These things last much longer because of the debt overhang that we started with. After a typical recession, you come galloping out. Six months after it ended, you're back to where you started. Another six or 12 months, you're back to trend. If you look at a contraction, one of these post-financial crisis events, it can take up to four or five years just to get back to where you started. So people are talking about a double dip, a second recession. We never left the first one. Fareed Zakaria: So, Paul Krugman, what the implication of what Ken Rogoff is saying is spending large amounts of money on stimulus programs is not going to be the answer because, until the debt overhang works its way off, you're not going to get back to trend growth. So, in that circumstance, you'll be wasting the money. Is that – is - Paul Krugman: No, that's not at all what it implies. I think my analytical framework, the way I think about this, is not very different from Ken's. At least I certainly believed from day one of this slump that it was going to be something very different from one of your standard V-shaped, down and up recessions, that it was going to last a long time. One of the things we can do, at least a partial answer, is in fact to have institutions that are able to issue debt - namely the government - do so and sustain spending and, among other things, by maintaining employment, by maintaining income, you make it easier for the private sector to work down that overhang of debt. Fareed Zakaria: Ken, are you in favor of a – a second or a significant additional stimulus in the way that I think Paul Krugman is? Ken Rogoff: No. I think that's where we part ways on this. I think that creates a debt overhang in the terms of future taxes that is not a magic bullet because it's not a typical recession. I do think, if we used our credit to help facilitate one of these plans to bring down the mortgage debt in this targeted way, and it could involve a significant amount - that I would definitely consider. I mean, that's how I would do it. Now, obviously, things go from bad to worse, then you start taking out more and more things from the toolkit, but I would start with targeting the mortgages, then higher inflation, try to do some structural reforms and, of course, if things are still going badly, I'm open to more ideas. Paul Krugman: I would say things have already gone from bad to worse. I mean, this is a terrible, terrible situation out there. You know, we talk about it, we look at GDP, whatever. We have nine percent unemployment and, more to the point, we have long-term unemployment at levels not seen since the Great Depression. Just an incredibly large number of people trapped in basically permanent unemployment. This is something that desperately needs addressing. And I would be saying we should not be trying one tool after another from the toolkit a little bit at a time. At this point, we really want to be throwing everything we can get mobilized at it. I don't think fiscal stimulus is – is a magic bullet. I'm not sure that inflation is a magic bullet in the sense that it's kind of hard to get, unless you're doing a bunch of other things. So we should be trying all of these things. How did the Great Depression end?  It ended, actually, of course, with World War II, which was a massive fiscal expansion, but also involved a substantial amount of inflation, which eroded the debt. What we need - hopefully we don't need a world war to get there - but we need this kind of all-out effort which we're not going to get. Fareed Zakaria: You say World War II got us out of the Depression. This was a massive stimulus, massive fiscal expansion. But aren't we in a different world? We are, right now, the United States with a budget deficit 10 percent of GDP, which is the second highest in the industrial world. In two our debt-to-GDP ratio goes to 100 percent. That strikes me as a situation, which presumably has some upper limit. You can't just keep spending money and incur these larger and larger debt loads. Paul Krugman: I think those numbers are a bit high, about the debt levels a couple years out. It takes longer than that. But the main thing to say is, look, think about the costs versus benefits right now. Basically, the U.S. government can borrow money and repay in constant dollars less than it borrowed. Are we really saying that there are no projects that the federal government can undertake that have an even slightly positive rate of return? Especially when you bear in mind that many of the workers and resources that you employ on those projects would be otherwise be unemployed. The world wants to buy U.S. bonds. Let's supply some more, and let's use those bonds to do something useful which might, among other things, help to get us out of this terrible, terrible slump. Ken Rogoff: Well, I think you have to be careful about assuming that these low interest rates are going to last indefinitely. They were very low for subprime mortgage borrowers a few years ago. Interest rates can turn like the weather. But I also question how much just untargeted stimulus would really work. Infrastructure spending, if well spent, that's great. I'm all for that. I'd borrow for that, assuming we're not paying Boston Big Dig kind of prices for the infrastructure. Fareed Zakaria: But, even if you were, wouldn't John Maynard Keynes say that if you could employ people to dig a ditch and then fill it up again, that's fine. They're being productively employed, they pay taxes, so maybe the Boston's Big Dig was just fine after all? Paul Krugman: Think about World War II, right? That was actually negative for social product spending, and yet it brought us out. I mean, partly because you want to put these things together, if we say, "Look, we could use some inflation." Ken and I are both saying that, which is of course anathema to a lot of people in Washington, but is in fact what the basic logic says. It's very hard to get inflation in a depressed economy. But if you have a program of government spending plus an expansionary policy by the Fed, you could get that. So if you think about using all of these things together, you could accomplish a great deal. If we discovered that space aliens were planning to attack and we needed a massive buildup to counter the space alien threat - and really inflation and budget deficits took secondary place to that - this slump would be over in 18 months. And then if we discovered, oops, we made a mistake there aren't actually any space aliens. Ken Rogoff: So we need Orson Wells is what you're saying? Paul Krugman: There was a Twilight Zone episode like this, which scientists fake an alien threat in order to achieve world peace. Well, this time we need it in order to get some fiscal stimulus. Fareed Zakaria: But Ken wouldn't agree with that, right? The space aliens wouldn't work - Ken Rogoff:  I think it's not so clear that Keynes was right. I mean, there have been decades and decades of debate about whether digging ditches is such a good idea. And my read of the debate is when the government does really useful things and spends the money in useful ways, it's a good idea. But when it just dig ditches and fills them in, it's not productive and leaves you with debt. I don't think that's such a no-brainer. There are people going around saying, "Oh, Keynes was right. Everything Keynes said was right." I think this is a different animal, with this debt overhang that you need to think about from the standard Keynesian framework. Paul Krugman: I guess I just don't agree. I mean, the debt overhang was an issue in the '30s, too - private sector debt overhang. We came into this with higher public debt than I would have liked, right? We're really, in some ways, paying the cost to the Bush tax cuts and the Bush unfunded wars, which leave us with a higher starting point of debt. But the thing that drives me crazy about this debate, if I can say, is that we have these hypothetical risks. All those hypothetical things are leaving us doing nothing about the actual thing that's happening, which is mass unemployment, mass waste of human resources, mass waste of physical resources. This is what's happening. We are hemorrhaging economic possibilities and also destroying a lot of lives by letting this thing drift on. And we're inventing these phantom threats (sometimes ghosts are real, I guess) to keep us from acting. Fareed Zakaria: Do you think that the lesson from history, Ken, in terms of these kind of great contractions - we have not had something like this since the 1930s, but there have been other examples - tells you that until you get these debt levels down, no matter what the government does, it's not going to get you back to robust growth? Ken Rogoff: I do, because what happens as you're growing slowly, the debt problems start blowing up on you. That's happening very dramatically in Europe. They had a philosophy and approach of things are going to get much better - 'if we can just hang on, we're going to grow really fast, the debt problems will go away.' Well, guess what? They're not growing fast enough. The debt problems are imploding. That's slowing growth, and it's a self- feeding cycle. Paul Krugman: I guess I'm a little puzzled here because, again, the thing that's holding us back right now in the United States - although there are those peripheral European countries that are having a very different kind of problem, partly because they don't have their own currencies - but, in the United States, what's holding us back is private sector debt. And, yes, we're not going to have a self sustaining recovery unless that private sector debt could be brought down. Fareed Zakaria: Just to be clear, Paul, what you mean by that is individuals have a lot of debt on their balance sheets? Paul Krugman: Yes, that's what's holding us back, and we do need to bring that down - at least bring it down relative to incomes. So what you need to do is you need to have policies to make incomes grow. That can include government spending, which is going to add to public debt, but it's going to reduce the burden of private debt. It can include inflationary policies, and it can include deliberate forgiveness. The idea that this has all faded, that we cannot do anything to grow because we have to wait for some natural process to bring that debt down, that doesn't follow from the analysis. There is a huge overhang of debt, which is, at least as I see it, exactly the reason why we need very activist government policies.

The Right Way to Trim - Nye, Joseph S., Jr. (New York Times, 2011)
The recent debt deal will slash the defense budget over the next decade. And if Congress can’t agree on an additional $1.5 trillion in cuts, the law’s “trigger mechanism” will lead to deeper reductions in military spending. The initial cuts will not imperil America’s national security, but the deeper cuts could. The administration of George W. Bush nearly doubled the defense budget following 9/11. With the winding down of Mr. Bush’s two wars, we could cut our ground forces to 1990s levels, reduce the planned purchases of F-35 Joint Strike Fighters, make greater use of cheaper drones and other technologies, and deal with the escalating costs of the defense health care system — without serious damage to national security. Indeed, President Obama’s budget had already planned for $400 billion in defense savings by 2023. But it is not enough to tinker with the defense budget. We also need to rethink how we use our military power. Unlike the state of affairs during the cold war, the United States and its allies today account for over 70 percent of world military expenditure. The No. 1 power no longer has to patrol every boundary and seek to police every country. Opponents of defense cuts are raising the specter of isolationism and the weakening of American power. But there is a middle way. At the height of the cold war, President Dwight D. Eisenhower decided against direct military intervention on the side of the French in Vietnam in 1954 because he was convinced that it was more important to preserve the strength of the American economy. Today, such a strategy would avoid involvement of ground forces in major wars in Asia or in other poor countries. While it will take time to extricate ourselves from Mr. Bush’s post-9/11 strategy, we must start, as the National Security Strategy of 2010 states, “by recognizing that our strength and influence abroad begins with the steps we take at home.” Eisenhower could have said that — and no one could accuse Ike of being an isolationist. Counterinsurgency is attractive as a military tactic but it should not lead us into a strategy of nation-building in places where we do not have the capacity to engineer change. The maxim of avoiding major land wars in poor countries does not mean withdrawing our military presence from places like Japan and South Korea, or ending military assistance to countries like Pakistan and Egypt. Some analysts call this “off-shore balancing,” but that term must mean more than just naval and air force activity. For example, in Japan and South Korea, our allies pay a significant portion of the cost for basing American troops there because they want an insurance policy in a region faced with a rising China and a volatile North Korea. Over the course of this century, Asia will return to its historic status, with more than half of the world’s population and half of the world’s economic output. America must be present there. Markets and economic power rest on political frameworks, and American military power provides that framework. Military security is to order as oxygen is to breathing: underappreciated until it becomes scarce. That is why the new bipartisan Congressional commission must provide the revenues that allow America to continue to play this vital role while avoiding the trap of overly ambitious nation-building. Such a strategy is also sustainable at home. The British historian Niall Ferguson, an enthusiast for empire, lamented at the time of the Iraq war that the United States lacked the capacity for empire because of three domestic deficits: personnel (not enough boots on the ground); attention (not enough public support for long-term occupation); and financial (not enough savings and not enough taxation relative to public expenditure). He was correct. Lacking a stomach for empire or colonial occupation is one of the important ways in which American political culture differs from that of imperial Britain. Americans like to promote universal values. But rather than succumbing to the temptation to intervene on the side of “the good,” we can do it best by being what Ronald Reagan called “a shining city on a hill.” The alternatives we face today are not an untouchable defense budget or isolationism. A smart strategy for preserving America’s power and global role will depend on wisely tailoring our foreign policy to fit the cloth we have. Eisenhower knew this well.

Strong Evidence - Elkins, Caroline M. (Harvard Gazette, 2011)
The work of a Harvard history professor has bolstered the case of a group of elderly Kenyans who are seeking reparations from the British government for rape, castration, beatings, and other abuses that they say were part of systematic colonial-era efforts to suppress Kenya’s Mau Mau uprising. The case passed a critical milestone in July when a British judge allowed it to move forward despite government arguments that, if the abuses happened, the current government isn’t liable for colonial transgressions. The Kenyans are former detainees in British prison camps set up during the 1950s Mau Mau rebellion, which set the stage for Kenyan independence in 1963. The plaintiffs allege that their abuse came at the hands of British jailers in what was a systematic and government-sanctioned campaign to break the rebellion. Though there had been talk of reparations for colonial atrocities for years, the case was given new life by Professor Caroline Elkins’ Pulitzer Prize-winning book, Imperial Reckoning: The Untold Story of Britain’s Gulag in Kenya. The book, published in 2005, blended government documents and eyewitness accounts to tell a compelling story of a horrific, systematic campaign by the British colonial government to crush the rebellion not only in the field, but through abuse of those held in camps around the country. “Caroline’s work has been absolutely fundamental to the case,” said Daniel Leader, a barrister for the London law firm Leigh Day & Co., which is representing the former Kenyan detainees. “She was uniquely responsible for beginning to change the public’s understanding of that period in history….The victims are forever in her debt. She put their stories on the map.” It was Elkins’ work, Leader said, that indicated that the abuse was not only systematic, but known by the British government in London. George Morara, program officer for the Kenya Human Rights Commission, which has worked to identify plaintiffs who could bring the case before the courts, said that Elkins’ research built an important foundation that allowed the case to move forward. “Without her seminal work,” Morara said, “this story wouldn’t have come to the fore.” Elkins’ critics, however, have charged that, though there may have been abuses in the system, there was no systematic effort by the government to abuse detainees. The July 21 ruling denied a motion to dismiss the case on the grounds that the current British government has no responsibility for actions by the colonial government in Kenya. While the judge didn’t rule on the merits of the case itself, the decision represents a key victory for the former detainees. “I have decided that the claimants have arguable cases, fit for trial,” High Court Judge Richard McCombe wrote in a summary explaining his judgment. “I emphasize that I have not found that there was systematic torture in the Kenyan camps nor that, if there was, the U.K. government is liable to detainees, such as the claimants, for what happened. . . . I decided that the FCO [Foreign and Commonwealth Office] have not established that the claimants are bound to fail.” The decision sets up a hearing on a second government motion to dismiss the case, Elkins said, this one based on a statute of limitations for such cases. The court can make exceptions to the statute of limitations, however, and Leader said the plaintiffs will use examples of other atrocities cases that have been prosecuted long after the acts were committed to illustrate that a fair trial is possible. Should the case clear that hurdle, expected in early 2012, Elkins expects the trial itself to begin next spring or summer. In addition to revelations contained in “Imperial Reckoning,” Elkins and two other historians acting as expert witnesses have submitted lengthy reports to the court; they’re also reviewing thousands of pages of previously undisclosed, colonial-era documents the government has brought forward because of the case. Elkins said the experts’ review of these documents has already yielded numerous memoranda that further substantiate both her thesis of systematized violence and the witness testimony she collected recounting abuse and torture in the camps. For Elkins, the court decision and the new documents substantiating her work provide a bit of vindication. Though her book garnered a great deal of praise in the U.S., winning the 2006 Pulitzer Prize for general nonfiction, it was also attacked in both Britain and Kenya as inaccurate and based on unreliable witness testimony. Elkins said she’s grateful for those at Harvard who stood by her while, as a graduate student, she worked on her dissertation, which was the basis for “Imperial Reckoning,” and when, as a junior faculty member, she endured the attacks on her work. In 2006, Morara and the Kenya Human Rights Commission began interviewing veterans in hopes of bringing a case to British courts. Three men and two women were chosen, one of whom, Susan Ciong’ombe Ngondi, has since died.  The four remaining plaintiffs, Ndiku Mutua, Paulo Nzili, Wambugu Wa Nyingi, and Jane Muthoni Mara, are all elderly, in their 70s and 80s. The case was filed in 2009. The case itself seeks an apology from the British government for abuse in the camps and establishment of a welfare system for former detainees, some of whom, Leader said, were unable to have children due to their treatment. In Kenya’s traditional culture, where children provide for their elderly parents, detainees’ inability to have a family leaves them with little means of support, he said. From a historian’s viewpoint, the case is one of what actually happened versus what people say happened, Elkins said. The government and its supporters have dismissed the firsthand testimony and eyewitness accounts of those who suffered, compounding what occurred in the detention camps decades ago. “It’s now a duel between colonial-inspired history and revisionist history,” Elkins said. “On top of it all, some have called the people who survived these horrific tortures liars. The British government behaved badly in Kenya, and many have continued to do so in an effort to conceal or minimize colonial abuses.”

After the Scandal, More of the Same at the I.M.F. - Rogoff, Kenneth S. (New York Times, 2011)
As the world struggles to emerge from the greatest financial crisis since the Depression, the institution at the heart of the global economic system is facing a profound crisis of governance. Since the International Monetary Fund’s inception at the end of World War II, Europe and the United States have dominated decision-making. Incredibly, and possibly dangerously, decisions are now being made to keep the backward-looking status quo for at least another five years. True, the final stage of the race for the top job at the I.M.F. still offers the possibility that a Mexican candidate might beat out the French front-runner. Unfortunately, with Europe still controlling an excessive voting share, the outcome has all the suspense of a Soviet-era election. Worse, the I.M.F. board does not seem to feel the need to establish even a pretext of legitimacy for the powerful No. 2 position; everyone takes for granted that the board will rubber-stamp whomever the Obama administration nominates. In a world where markets already pay more attention to what happens in China than in Europe, and where loans from emerging economies are keeping the debt-challenged United States economy on life support, the I.M.F.’s outdated governance practices have become an accident waiting to happen. The I.M.F. has long been the last line of defense in emerging-market debt crises, combining big short-term loans with technical assistance that has proven effective far more often than not. Today it is on the front lines of the European debt crisis, with Greece, Ireland and Portugal teetering on the brink. Given Japan’s huge debts and demographic implosion, and China’s runaway growth boom, it is not hard to imagine a vast I.M.F. program in Asia in the next decade. Even the United States is a potential customer if it continues for another 10 or 15 years to neglect its soaring debt burden. If the fast-growing economies of Asia and Latin America feel disenfranchised from the I.M.F. — there is still a strong undercurrent of hostility in Asia over the fund’s handling of the 1997-98 Asian financial crisis — it will be difficult for the I.M.F. to raise money to deal with Europe and potentially Japan and to credibly do its work in emerging markets now and in the future. And because American and European leaders do not want to hear when their monetary, fiscal or regulatory policies are out of whack, the I.M.F. is really the only strong voice that can deliver the message; a non-European is best-equipped to deliver it. Until a few weeks ago, everyone seemed to agree that it was high time for a change. The presumption was that the I.M.F. board would choose its next managing director from the handful of supremely qualified candidates from emerging markets, thereby strengthening its claim to be a truly global institution. The incumbent, Dominique Strauss-Kahn of France, was on record supporting a transparent, merit-based approach for choosing his successor. Given the prestige he had amassed leading the I.M.F. during the crisis, it was assumed that he would use his influence to shepherd in the new era. Everything changed in mid-May. Mr. Strauss-Kahn was forced to resign after being accused of sexually assaulting a hotel housekeeper. Suddenly, the I.M.F. became tabloid fodder and the plans for an open and meritocratic selection process were tossed out the window. With the I.M.F.’s legitimacy now under unexpected attack on a second front, gender inequality, European leaders inventively coalesced around the French finance minister, Christine Lagarde. Just a short while ago, the fact that Ms. Lagarde is French would surely have been disqualifying, given that the French have held the I.M.F. leadership for most of the last three decades. Ms. Lagarde’s training as a lawyer, rather than as an economist, might also have been an obstacle. The head of the I.M.F. is like the head of a central bank, and is frequently confronted with difficult judgments on the sizing and timing of debt programs, not to mention on monetary policy and regulation. Ms. Lagarde has provided a strong and clear voice on the need for dramatic financial sector reform. But weighed against Mexico’s candidate, Agustín G. Carstens, she might have come up short, at least prior to the Strauss-Kahn debacle. Mr. Carstens, who has a Ph.D. from the University of Chicago, has a golden C.V. for the job. The head of the I.M.F. routinely deals with central bankers as well as finance ministers, and Mr. Carstens had held both positions in Mexico. He has also served as a deputy managing director of the I.M.F. and knows the institution inside and out. Mr. Carstens has rightly argued that a European is going to be hugely conflicted in managing the central challenge facing the I.M.F. today: Europe. Soon, the I.M.F. will likely have to help manage government debt defaults in more than one European nation, starting with Greece. European leaders want to kick the can down the road by bribing the Greeks with more loans to prevent them from defaulting. This is where the I.M.F. normally preaches tough love. The I.M.F. board has given itself until June 30 to decide. The circumstances of Mr. Strauss-Kahn’s departure have to be taken into consideration, and the fallout on gender issues is not over. There has never been a woman as head of a major multilateral lending institution, and Ms. Lagarde is a highly credible candidate. It seems a done deal, though perhaps there is some way to cap the length of her tenure and improve the selection process next time. And the managing director is not the only position that matters. At the end of August, John P. Lipsky, the first deputy managing director, who was named to the job by the Bush administration, is due to step down. Why not see if one of the top emerging-market candidates can be a replacement? An effective No. 2 would also be well-positioned to take over when Ms. Lagarde herself steps down. (The last three I.M.F. managing directors have departed without completing their terms.) There is still time to set in place a merit-based selection process that could eventually form the basis for filling the top job. The I.M.F. may be a poorly understood institution, but it does not have to be a poorly governed one.

Justice Goes Global - Friedman, Thomas L.; Sandel, Michael (the New York Times, 2011)
You probably missed the recent special issue of China Newsweek, so let me bring you up to date. Who do you think was on the cover—named the “most influential foreign figure” of the year in China? Barack Obama? No. Bill Gates? No. Warren Buffett? No. O.K., I'll give you a hint: He's a rock star in Asia, and people in China, Japan and South Korea scalp tickets to hear him. Give up? It was Michael J. Sandel, the Harvard University political philosopher. This news will not come as a surprise to Harvard students, some 15,000 of whom have taken Sandel's legendary “Justice” class. What makes the class so compelling is the way Sandel uses real-life examples to illustrate the philosophies of the likes of Aristotle, Immanuel Kant and John Stuart Mill. Sandel, 58, will start by tossing out a question, like, “Is it fair that David Letterman makes 700 times more than a schoolteacher?” or “Are we morally responsible for righting the wrongs of our grandparents' generation?” Students offer competing answers, challenge one another across the hall, debate with the philosophers—and learn the art of reasoned moral argument along the way. Besides being educational, the classes make great theater—so much so that Harvard and WGBH (Boston's PBS station) filmed them and created a public television series that aired across the country in 2009. The series, now freely available online (at http://www.JusticeHarvard.org), has begun to stir interest in surprising new places. Last year, Japan's NHK TV broadcast a translated version of the PBS series, which sparked a philosophy craze in Japan and prompted the University of Tokyo to create a course based on Sandel's. In China, volunteer translators subtitled the lectures and uploaded them to Chinese Web sites, where they have attracted millions of viewers. Sandel's recent book—Justice: What’s the Right Thing to Do?—has sold more than a million copies in East Asia alone. This is a book about moral philosophy, folks! Here's The Japan Times describing Sandel's 2010 visit: “Few philosophers are compared to rock stars or TV celebrities, but that's the kind of popularity Michael Sandel enjoys in Japan.” At a recent lecture in Tokyo, “long lines had formed outside almost an hour before the start of the evening event. Tickets, which were free and assigned by lottery in advance, were in such demand that one was reportedly offered for sale on the Web for $500.” Sandel began the lecture by asking: “Is ticket scalping fair or unfair?” But what is most intriguing is the reception that Sandel (a close friend) received in China. He just completed a book tour and lectures at Tsinghua and Fudan universities, where students began staking out seats hours in advance. This semester, Tsinghua started a course called “Critical Thinking and Moral Reasoning,” modeled on Sandel's. His class visit was covered on the national evening news. Sandel's popularity in Asia reflects the intersection of three trends. One is the growth of online education, where students anywhere now can gain access to the best professors from everywhere. Another is the craving in Asia for a more creative, discussion-based style of teaching in order to produce more creative, innovative students. And the last is the hunger of young people to engage in moral reasoning and debates, rather than having their education confined to the dry technical aspects of economics, business or engineering. At Tsinghua and Fudan, Sandel challenged students with a series of cases about justice and markets: Is it fair to raise the price of snow shovels after a snowstorm? What about auctioning university admissions to the highest bidder? “Free-market sentiment ran surprisingly high,” Sandel said, “but some students argued that unfettered markets create inequality and social discord.” Sandel's way of teaching about justice “is both refreshing and relevant in the context of China,” Dean Qian Yingyi of Tsinghua’s School of Economics and Management, explained in an e-mail. Refreshing because of the style and relevant because “the philosophic thinking among the Chinese is mostly instrumentalist and materialistic,” partly because of “the contemporary obsession on economic development in China.” Tsinghua's decision to offer a version of Sandel's course, added Qian, “is part of a great experiment of undergraduate education reform currently under way at our school. …This is not just one class; it is the beginning of an era.” Sandel is touching something deep in both Boston and Beijing. “Students everywhere are hungry for discussion of the big ethical questions we confront in our everyday lives,” Sandel argues. “In recent years, seemingly technical economic questions have crowded out questions of justice and the common good. I think there is a growing sense, in many societies, that G.D.P. and market values do not by themselves produce happiness, or a good society. My dream is to create a video-linked global classroom, connecting students across cultures and national boundaries—to think through these hard moral questions together, to see what we can learn from one another.”

Bitter Legacy, Injured Coast - Miller, Ian (New York Times, 2011)
The rugged Sanriku Coast of northeastern Japan is among the most beautiful places in the country. The white stone islands outside the port town of Miyako are magnificent. The Buddhist monk Reikyo could think of nothing but paradise when he first saw them in the 17th century. “It is the shore of the pure land,” he is said to have uttered in wonder, citing the common name for nirvana. Reikyo’s name for the place stuck. Jodogahama, or Pure Land Beach, is the main gateway to the Rikuchu Kaigan National Park, a crenellated seashore of spectacular rock pillars, sheer cliffs, deep inlets and narrow river valleys that covers 100 miles of rural coastline. It is a region much like Down East Maine, full of small, tight-knit communities of hardworking people who earn their livelihoods from tourism and fishing. Sushi chefs around the country prize Sanriku abalone, cuttlefish and sea urchin. Today that coast is at the center of one of the worst disasters in Japanese history. Despite the investment of billions of yen in disaster mitigation technology and the institution of robust building codes, entire villages have been swept out to sea. In some places little remains but piles of anonymous debris and concrete foundations. I taught school in Miyako for more than two years in the 1990s, and it was while hiking in the mountains above one of those picturesque fishing villages that I came across my first material reminder of the intricate relationship between the area’s breathtaking geography, its people — generous and direct — and powerful seismic forces. On a hot summer day a group of middle-school boys set out to introduce me to their town, a hamlet just north of Pure Land Beach. While I started up the steep mountainside the children bounced ahead of me, teasing me that I moved slowly for someone so tall. “Are you as tall as Michael Jordan, Miller-sensei?” yelled one boy as he shot past me up the trail. “Not quite,” I told him, pausing on a spot of level ground to look out over the neat collection of tile roofs and gardens that filled the back of a narrow, high-walled bay. “What is this?” I asked, pointing to a mossy stone marker that occupied the rest of the brief plateau. A chorus of young voices told me that it was the high-water mark for the area’s biggest tsunami: more than 50 feet above the valley floor. “When was that?” I asked, but the boys couldn’t say. They had learned about it in school, they said, but like children everywhere they had little sense of time. Everything seemed like ancient history to them, but the thought of a wave reaching so high over the homes of my friends sent a chill down my spine, and I began to investigate the region’s history. A major tsunami has hit the Sanriku Coast every few decades over the last century and a half. Waves swept the area in 1896, 1933 and 1960. The small monument was put there, high above the village, to mark the crest of the 1896 tsunami. The wave killed more than 20,000 people. The boys’ village, a place called Taro, was almost entirely destroyed. Seventy-five percent of the population died. The force of those waves was amplified by the area’s distinctive geography. The same steep valley walls and deep inlets that make Sanriku so beautiful also make its villages and towns especially hazardous. The valleys channel a tsunami’s energy, pushing swells that are only a few feet high in the open ocean up to stunning heights. Fast-moving water topped 120 feet in one village in 1896. In a landscape where earthquakes are a regular occurrence but major tsunamis happen irregularly, people naturally forget. The small monument— one of several commissioned for towns up and down the coast — was a mnemonic whose purpose was not commemoration but vigilance. “When there is an earthquake, watch for tsunami,” reads the rather practical poem engraved into one such slab. Japan became a modern industrial state between the 1896 tsunami and the next major one, in 1933. The country’s radio and newspapers brought the story of rural fisher-folk swept out to sea to metropolitan audiences. Three thousand people died in the disaster and the humanitarian crisis elicited strong feelings of sympathy. The Sanriku region was portrayed as the nation’s heartland, a place where tradition remained intact, and the disaster threatened that preserve. Once again, Taro was particularly hard hit: all but eight of its homes were destroyed and nearly half of the village’s population of 1,800 souls went missing. The hamlet became an embodiment of agrarian loss. It is paradoxical that the response to this threat to traditional ways was the application of cutting-edge engineering and technology. A huge concrete seawall was planned for Taro. Completed in 1958, that wall, 30 feet high at points, stretches over 1.5 miles across the base of the bay. Faith in technology over nature appeared to be vindicated in 1960 with the great Chilean earthquake, a 9.5-magnitude quake that remains the largest ever recorded, which set off a Pacific-wide tsunami that killed 61 people in Hilo, Hawaii, before surging unannounced into the Sanriku Coast seven hours later. More than 120 Japanese died, but Taro remained largely unaffected, safe behind its sluice gates and concrete wall. Based in part on this success, a new program of coastal defense was initiated. The Sanriku Coast is now one of the most engineered rural coastlines in the world. Its towns, villages and ports take shelter behind state-of-the-art seawalls and vast assemblages of concrete tetrapods designed to dissipate a wave’s energy. The region is home to one of the world’s best emergency broadcast systems and has been at the forefront of so-called “vertical evacuation” plans, building tall, quake-resistant structures in low-lying areas. In 2003 Taro announced that it would become a “tsunami preparedness town.” Working with teams from the University of Tokyo and Iwate University, the town instituted a direct satellite link to accelerate the arrival of tsunami warnings. Public education was expanded and mayors from other towns visited to study this model village. Detailed maps showing projected maximum tsunami heights — using 1896 as a baseline — informed the selection of evacuation markers: a reassuring thick line defined the projected maximum reach of a tsunami. Evacuation sites were placed above that line on the maps. Similar calculations were made up and down the coast. The lines were drawn in the wrong place. Despite the substantial infrastructure and technological investments in Sanriku, the wave on March 11 overwhelmed large portions of Taro and Miyako. Some of the evacuation points were not high enough. The walls were not tall enough. And the costs are still being tallied. Thousands of people are missing along this beautiful, injured coast, hundreds in the town that I called home. I am still waiting to hear from one of the groomsmen from my wedding, the owner of Miyako’s best coffee shop and a sometime reader of this newspaper. Google’s people-finder app tells me he is alive, but I have no idea where he is or how our other friends fared. As for those rambunctious boys and all of my other students, I can only hope for the best. Technology allowed me to learn my friend’s fate. It has also helped to inspire a worldwide humanitarian response. It may be, however, that a greater application of technology in the same direction is not the answer to the problems posed by the March 11 tsunami. As a historian, I am forced to recognize that there is nothing purely natural about this catastrophe. It is the result of a far longer negotiation between human culture and physical forces. Disasters have the counterintuitive tendency to reinforce the status quo. As the terrifying events at the Fukushima Daiichi nuclear plant continue to underline, there are very real costs to an uncritical application of technology. I look forward to returning to my old Japanese home, but I also look forward to finding something new and different when I make that journey.

Murder on the EU Express - Ferguson, Niall (Newsweek, 2011)

With a Mighty Hand - Daniel P. Aldrich (New Republic, 2011)
As the ongoing nuclear crisis at the Fukushima Daiichi plant in the town of Ohkuma continues, and plant engineers and first responders endanger their lives to keep fuel rods and containment units cool, it is critical to consider how Japan’s commitment to nuclear power arose in the first place. It was no twist of fate or invisible market-hand that created 55 nuclear reactors in a seismically active country smaller than the state of California. Japanese bureaucrats and politicians have made it a priority to create an indigenous source of power that provides an alternative to imported oil and coal. Despite this understandable rationale, it’s still surprising that the only nation in the world against which atomic weaponry has been used—twice, no less—has created the world’s most advanced commercial nuclear program. It is especially surprising when you consider that countries like France, Germany, and the United States have given up their attempts at fast breeder reactor technology because of concerns about proliferation and hazard. What has driven Japan to pursue its advanced program of nuclear power, and why have nuclear power plants ended up in incredibly vulnerable positions along Japan’s coasts? While the United States has provided some support for nuclear power (for example, the Price-Anderson Act, which commits the federal government to absorbing some of the financial costs of potential nuclear accidents), as a source of alternative energy, it has never been fully embraced. This tradition of fence-sitting continues today, as seen in the Obama administration’s decision to end funding for the planned high-level radioactive waste repository at Yucca Mountain after two and a half decades of struggle over the site. Completion of the facility would have helped pro-nuclear groups convince skeptics that offsite waste disposal was possible. (The difficulty in securing permanent storage sites for nuclear waste is what leads U.S. and Japanese nuclear power plants to store their used fuel rods on site where they are most vulnerable.) In contrast, the Japanese government has gone far beyond this approach. The origins of its enthusiasm can be traced to the postwar period. In 1955, at the urging of then-Diet Memberand later Prime Minister Yasuhiro Nakasone, the Japanese government granted more than 5 billion yen—about $14 million in 1955 currency—to the Japan-based Agency for Industrial Science and Technology to begin research under the aegis of the “atoms for peace” banner raised by Dwight Eisenhower. In recent decades, the Japanese central government has supported the regional power utilities—including Tokyo Electric Power Company (TEPCO), which runs Fukushima, and its counterparts—through research funding, risk amortization, and financial and logistical support. Unlike France, for example, which explicitly nationalized and then partly privatized their main nuclear-power-promoting utility company, Japan did not nationalize its energy industry, and some Japan experts have characterized the relationship between the state and utility firms as contentious. Yet both sides got what they wanted over the past 50 years: The government guided Japanese firms to produce nearly one-third of the nation’s power through nuclear plants, and the utilities obtained credible commitment against risk and financial backing for their expensive investments. The Japanese people, as readers might imagine, have not been solid supporters of these government-initiated policies. Just as the government hoped to start its nuclear program in 1954, a highly publicized accident—in which crewmates onboard the poorly named Lucky Dragon Number 5 ship were exposed to radioactive fallout from an American hydrogen bomb test—resulted in the death of a radioman from radiation exposure. This spurred the creation of one of the world’s first national anti-nuclear movements (known as Gensuikyō) and a petition against nuclear weapons that obtained more than 20 million signatures. Attempts to build a number of plants around the country since the mid-1950s have resulted in petitions, public outcries, demonstrations, sit-ins, marches, and the occupation of town councils by anti-nuclear activists. While the anti-nuclear movement has not demonstrated the kind of violence shown by the anti-Narita Airport protests in the 1960s—during which a number of police officers and anti-airport farmers and students were killed in struggle over land expropriation—the success rate for the building of nuclear power plant has been roughly 50 percent. (That is, for every two attempts to construct a new plant, only one has gone forward.) To minimize these fights over nuclear power in a society where people are deeply sympathetic to victims of atomic energy, the government has taken a two-pronged approach. First, it has worked tirelessly with the regional utilities to map out villages and towns that are the best locations for plants, according to the utilities’ needs. Bureaucrats within MITI (the Ministry of International Trade and Industry, which became METI, the Ministry of Economy, Trade, and Industry, as of 2001) provided funding for geographical and demographic surveys of potential grounds. Power companies have often targeted rural, depopulated coastal communities, where the population of local fishermen are declining. But, while legitimate criteria, such as distance from high-population areas, shock-resistant bedrock, and access to cooling water, have played a role in such plant site selections, the inability of the local population to coordinate anti-nuclear mobilization has often been the dominant factor. Second, the government has created an extensive framework of policy instruments to manage and dampen anti-nuclear contestation. Where the Japanese authorities have been content to use standard, Weberian tools against anti-facility movements in other areas—such as dam construction and airport building—they have never resorted to land-expropriation in struggles over nuclear power plants, despite clear legal precedent for them to do so. Rather, the government has created a series of hard- and soft-control tools alongside deep incentives for communities willing to take on nuclear reactors. For example, students in Japanese middle schools may take science courses emphasizing the safety and necessity of nuclear power plants, with curricula written by government bureaucrats rather than teachers. Farmers and fishermen in these communities are regularly offered jobs at government-sponsored facilities to compensate for signing away sea rights in the surrounding fishing area. To further assuage the resistance that fishermen and farmers have shown in the past (because of concerns over “nuclear blight”—potential customers avoiding crops or fish because of fears of nuclear contamination), the government sponsors a yearly fair in Yokohama, in which only communities that host nuclear power plants can display and sell their goods. Finally, the government has created a monumental program called The Three Power Source Development Laws (Dengen Sanpō), which funnels roughly $20 million per year to acquiescent host communities. The money—which comes not from the politically vulnerable and annually vetted budget, but, instead, from an invisible tax on all electricity use across the nation—purchases roads, buildings, job re-training, medical facilities, and good will. In these far-flung rural communities that are, by and large, dying through depopulation and aging, these funds can provide vital support. Japan’s choices—to sway public opinion through subsidies, social control tools, and manipulation—have left little room for public debate on the issue of nuclear power. The local residents—whom we see bearing the heaviest burden of the ongoing crisis in Fukushima and who have been exposed to radiation by past accidents at the Monju FBR, the fatal accident at Tokaimura, and elsewhere—are seen not as partners, but as targets for policy tools. A plan-rational approach, as Chalmers Johnson might have called it, has placed reactors in areas vulnerable to the threat of tsunami and pushed rural communities into dependence on the economic side payments which accompany these facilities. Now, as Japan struggles to avert catastrophe, it is the time for a real discussion between civil society and state over the future of nuclear power.

An Exit Plan for Mubarak - Masoud, Tarek (New York Times, 2011)
Hosni Mubarak’s promise this week to initiate constitutional reform in Egypt and then step down at the end of his presidential term in September did little to mollify the anger of the demonstrators protesting his rule. Many protesters seemed to agree with the assessment of the opposition leader Mohamed ElBaradei that it was “a trick” intended to buy time. With the regime-sponsored ugliness now engulfing Tahrir Square, demands for Mr. Mubarak’s immediate resignation have grown only more urgent, and the risk of a violent conclusion appears to have grown. But there may still be a chance to effect the “orderly transition” that Secretary of State Hillary Rodham Clinton has called for. Paradoxically, it requires that Mr. Mubarak stay on, but only for a short time, to initiate the election of an entirely new Parliament that could then amend all the power out of the presidency or even abolish it. This would no doubt disappoint those who want to put Mr. Mubarak on the next plane to Saudi Arabia, but there are two risks associated with his leaving so abruptly. The first is that the demonstrations might diminish or dissipate, leaving Mr. ElBaradei and his coalition trying to negotiate with the military or Vice President Omar Suleiman without the force of the crowds behind them. The second risk stems from the Egyptian Constitution, which gives the power to dissolve Parliament and call new elections only to an elected president. Mr. Mubarak’s successor, as an acting president, would be specifically prohibited from getting the parliamentary elections under way. A new Parliament is crucial to democratic reform, because only Parliament has the power to defang the Egyptian presidency, stripping it of its dictatorial powers through constitutional amendment. The current Parliament — bought and paid for by Mr. Mubarak’s National Democratic Party — is not fit for that task. Egypt’s next scheduled presidential election is only months away. If the Constitution isn’t amended before it is held, the notorious Article 76, which makes it difficult for independents like Mr. ElBaradei to get on the ballot, will still be in place. More important, the new president would have the same imperial powers Mr. Mubarak has had — the very powers that the Egyptian public wants taken away. The constitutionally sanctioned timeline would be this: Mr. Mubarak dissolves Parliament, forcing a new election within 60 days (international observers would be required to make sure the election is fair). Once the new Parliament is seated, Mr. Mubarak resigns, and an acting president, probably the new Parliament’s speaker, takes charge until a new president is elected. The new Parliament would work around the clock to amend the Constitution in ways that would put Mr. Suleiman or any would-be strongman out of a job. The final step is a national referendum on the amendments. For American policymakers, the most frightening possibility is that the Muslim Brotherhood would sweep the parliamentary elections and institute a constitution based on Islamic holy law. This is unlikely. The political momentum in Egypt is not with the Islamists. Moreover, the Brotherhood’s members have never sought to compete for a majority of seats in Parliament, and during the current protests have impressed people across the Egyptian political spectrum with their self-effacement. Brotherhood adherents know that a victory for them could be used by the military as an excuse to short-circuit the birth of democracy in Egypt. A likelier outcome is that the Islamists would join a coalition slate of candidates, becoming part of an ideologically diverse Parliament. The greater danger now is that Mr. Mubarak would corrupt the electoral process by unleashing the same thugs who are now attacking the peaceful protesters of Tahrir Square. One might wonder why, at this moment of change and tumult, anyone would talk about amending a constitution that everyone recognizes as a deformed confection of a corrupt regime. But by working with even a flawed constitution, the opposition would be helping to entrench and deepen a constitutionalist principle that has been steadily eroded. And with its built-in deadlines, the constitutional route also makes it harder for the military to draw out the transition and consolidate its hold. For any of this to happen, Mr. Mubarak must remain briefly in office, and he must agree to the changes as an answer to his people’s legitimate cry for democracy. The demand that can make him comply must come from President Obama. It has often been said in recent days that the United States can do nothing to affect the progress of democracy in Egypt, but the military’s dependence on American money and matériel suggests that this is untrue. The more the United States can make clear that continued military support depends on how the Egyptian Army conducts itself during this transition, the more likely the military is to play midwife to democracy. Much could go wrong, but finding an orderly way to get not just Mr. Mubarak but also the armed forces out of political life should be a more important priority than ensuring that Islamists don’t hijack the revolution. All that is required of us is to remind ourselves that democracy in Egypt, or any other part of the world, is not something we should fear.

History in the Making - Lewis, Mary D. (Harvard Gazette, 2011)
The seeds of Mary Lewis’ fascination with France were planted early. Her father spent a few years there as a young man, working in the offices of the Marshall Plan, so she grew up hearing a steady stream of stories about that country. “I had never been out of North America,” said the newly tenured professor of history, “but when my father would talk about France’s history, it sparked an interest that is still with me.” The geopolitically tense Reagan administration years were her political coming-of-age, and the native Californian went to college wanting to understand the Cold War, studying international relations when she attended the University of California, Davis.  She spent her junior year abroad in France, becoming increasingly interested in the diversity of its society. The final seed that would eventually bear Lewis’ intellectual fruit was planted during a political science class she took upon her return from studying abroad. It was November 1989, the month the Berlin Wall fell. “We were discussing the theory of mutually assured destruction,” she said. “A young man raised his hand and asked the professor, ‘Can we talk about Berlin?’ The professor was completely thrown. The real world was confronting his theoretical model, and he didn’t know what to do.” Lewis remembers the professor dismissing the question by telling the student to read The New York Times. That, she said, was the moment she knew she wanted to study history. “At that point, history had suddenly caught up to political science,” she said. “I realized you really needed history to understand politics.” After graduating from the University of California, Davis, and before beginning a Ph.D. program in history at New York University, Lewis spent two years working for the U.S. Department of Education in its Office for Civil Rights, an experience she said greatly affected how she studies and thinks about history today. “I learned a lot about bureaucracy and the layers of bureaucracy,” she said. “If I wrote a letter, it would go through six different levels of editing and end up with someone else’s signature on it.” “I got a sense of how policy and decisions are layered. It helped me become the kind of historian that I am today.” Lewis’ improbable interest in bureaucracy informed her first book, “The Boundaries of the Republic: Migrant Rights and the Limits of Universalism in France, 1918-1940” (Stanford University Press, 2007), recently translated into French as “Les Frontières de la République” (Éditions Agone, 2010). The book demonstrates how local actions — far removed from Parisian edicts — redefined the boundaries between French citizens and outsiders in the early decades of the 20th century. By focusing on the limits of legislation in a pluralistic society, the book challenges the common vision of France as a highly centralized nation. “We tend to think of France as a centralized country with uniform rights decreed in Paris,” Lewis said. “But the actions of immigrants themselves in the provinces, by forcing officials to recognize that they were going to stay in the country, instigated an expansion of those rights. In a sense, today’s diverse French society is a product of that history.” Today, Lewis’ studies are intersecting anew with current events: She is working on a book about Tunisia, using the case of the little-studied French protectorate there to study how imperial rivalry affected French colonial governance from the 1880s to the 1930s. Pent-up public unrest in the North African country exploded and brought down its government last month. “Having researched my forthcoming book there, I was surprised that the protests would lead so suddenly to a change in regime,” she said of Tunisia’s overthrow of its president. “It’s a police state.  People have conditioned themselves to be very guarded in conversation when speaking about politics because they know they’re being watched, so the fact that they would have the nerve to protest as they did is remarkable.” Lewis is also planning a new research project on intercolonial movement by studying colonial passports. “We think of these societies as being hermetically sealed, because we tend to study them from an imperialist point of view, but in fact people were on the move, and we can see challenges to imperial control based on these varied movements.” One of Lewis’ favorite parts of working at Harvard is interacting with students. “They make you think,” she said. “Even if you’ve taught a class before, you’ll get something new out of it because of the student participation. This is positive feedback on a whole other level.”

Sale of the Century - Ferguson, Niall (History News Network, 2011)
In my favorite spaghetti western, The Good, the Bad and the Ugly, there is a memorable scene that sums up the world economy today. Blondie (Clint Eastwood) and Tuco (Eli Wallach) have finally found the cemetery where they know the gold is buried. Trouble is, they’re in a vast Civil War graveyard, and they don’t know where to find the loot. Eastwood looks at his gun, looks at Wallach, and utters the immortal line: “In this world, there are two kinds of people, my friend. Those with loaded guns … and those who dig.” In the post-crisis economic order, there are likewise two kinds of economies. Those with vast accumulations of assets, including sovereign wealth funds (currently in excess of $4 trillion) and hard-currency reserves ($5.5 trillion for emerging markets alone), are the ones with loaded guns. The economies with huge public debts, by contrast, are the ones that have to dig. The question is, just how will they dig their way out?... The U.S. needs to do exactly what it would if it were a severely indebted company: sell off assets to balance its books. There are three different arguments against such asset sales. The first concerns national security. When Dubai Ports World bought the shipping company P&O in 2006—which would have given it control of facilities in a number of U.S. ports—the deal was killed in Congress in a fit of post-9/11 paranoia. The second argument is usually made by unions: private or foreign owners will be tougher on American workers than good old Uncle Sam. Finally, there’s the chauvinism that surfaced back in the 1980s when the Japanese were snapping up properties like Pebble Beach. How could the United States let its national treasures—the family silver—fall into the hands of inscrutable Asian rivals? Such arguments were never very strong. Now, in the midst of the biggest crisis of American public finance since the Civil War, they simply collapse....

Sometimes, Justice Can Play Politics - Feldman, Noah (New York Times, 2011)
What is it about those robes? They are only flimsy bits of wools, enlivened in a few cases by some very European lace at the collar. Yet the moment our Supreme Court justices put them on, a segment of the concerned public imagines that they have become priests consecrated to the sacred order of the Constitution. Recently, Justice Antonin Scalia has been criticized for meeting with a group of (gulp) conservative members of Congress and accused of participating in an event organized by the conservative billionaire Charles Koch. Justice Clarence Thomas has been excoriated because his wife, Virginia, last year took a leading role in organizing Liberty Central, a Tea Party offshoot that received anonymous, First Amendment-protected donations (she has since stepped down). He also belatedly amended 13 years’ worth of disclosure reports to include details of his wife’s employment. Justices are required to disclose their income sources and those of their spouses. But the core of the criticisms against Justices Thomas and Scalia has nothing to do with judicial ethics. The attack is driven by the imagined ideal of the cloistered monk-justice, innocent of worldly vanities, free of political connections and guided only by the gem-like flame of inward conscience. It was not ever thus. John Marshall, undoubtedly the greatest chief justice ever, spent his first month on the court as the secretary of state of the United States. That’s right, the chief justice and the secretary of state were the same person — an arrangement permitted by the Constitution, which only prohibits members of Congress from holding other offices. Marshall’s most famous decision — Marbury v. Madison, which established the principle of judicial review — arose from Marshall’s own failure as secretary of state to deliver the obscure William Marbury his commission as justice of the peace in the waning hours of the Adams administration. No one cared. The political activities of the justices increased over time. Charles Evans Hughes, who would later become another great chief justice, resigned from his first stint as associate justice on June 10, 1916, to run for the presidency on the Republican ticket. Although this represented a separation from his judicial role, the Republican convention had begun at the Chicago Coliseum on June 7; Hughes did not resign until the nomination was in the bag. In 1948, Americans for Democratic Action tried to draft Justice William O. Douglas as a Democratic presidential candidate. In their political literature, they used excerpts from his Supreme Court opinions, which (his colleagues noted privately) sounded suspiciously like stump speeches. (In the end, he decided against a run.) Equally important, in the pre-monastic age, justices often took on politically charged government responsibilities when the world needed them. Their experiences in public service not only helped the country, but informed their subsequent jurisprudence. Justice Robert Jackson, a valued player in Franklin Delano Roosevelt’s regular poker game (and a hero to many court observers today), took a year away from the court to serve as the chief prosecutor at Nuremberg, a presidential appointment. Later, when the Supreme Court had to decide whether German detainees convicted by United States war crimes tribunals were entitled to habeas corpus rights, Jackson did not recuse himself. Instead, he wrote the opinion in Johnson v. Eisentrager, the case that formed the precedent for the extension of habeas rights to the detainees at Guantánamo Bay. Justice Owen Roberts was chosen by Roosevelt to head the commission investigating the attack on Pearl Harbor. What he learned made him one of only three justices to defy Roosevelt and dissent from the court’s shameful decision to uphold the wartime internment of more than 100,000 Japanese-Americans who had been convicted of no crime at all. The 1970s saw the beginning of a retreat by the justices from public engagement with national affairs. Some of this was defensive. In 1969, Justice Abe Fortas, one of Lyndon Johnson’s closest advisers on Vietnam even while on the court, had to resign after revelations that he had been on retainer to a financier under investigation for securities violations. The next year, Gerald Ford, then the House minority leader, sought unsuccessfully to impeach Douglas for taking money from a nonprofit foundation. Yet, probably the greater reason for the justices’ growing circumspection by the early 1970s was that the Supreme Court was taking its most active role ever in running the nation’s affairs: when the court ruled against Richard Nixon in the Watergate tapes case, it effectively forced a president from office. Empowered to break a president (making one had to wait until Bush v. Gore in 2000), the justices sought to deflect attention from the obvious fact that they were political. The disengagement from public life that followed has had real costs. Isolated justices make isolated decisions. It is difficult to imagine justices who drank regularly with presidents deciding that a lawsuit against a sitting executive could go forward while he was in office, or imagining that the suit would not take up much of the president’s time. Yet that is precisely what the court did by a 9-to-0 vote in the 1997 case of Clinton v. Jones. The court’s mistaken practical judgment opened the door to President Bill Clinton’s testimony about Monica Lewinsky and the resulting impeachment that preoccupied the government for more than two years as Osama bin Laden laid his plans. Today, even the justices’ minimal extrajudicial activities come in for public condemnation — some of it suspiciously partisan. Does anyone seriously think Justice Thomas would become more constitutionally conservative (if that were somehow logically possible) as a result of his wife’s political activism? It is true that Justice Thomas voted to protect the anonymity of some corporate contributions in the Citizens United case. But this vote reflected his long-established principles in favor of corporate speech. The personal connection was nowhere near close enough to demand recusal, any more than a justice who values her privacy should be expected to recuse herself from a Fourth Amendment decision. After all, Martin Ginsburg, a model of ethical rectitude until his death last year, was for many years a partner in an important corporate law firm. But surely no one believes that his career made his wife, Justice Ruth Bader Ginsburg, more positively inclined toward corporate interests on the court than she would already be as a member in good standing of America’s class of legal elites. Justice Antonin Scalia, for his part, naturally spends time with like-minded conservatives including Representative Michele Bachmann and Charles Koch. But when the brilliant, garrulous Justice Scalia hobnobs with fellow archconservatives, he is not being influenced any more than is the brilliant, garrulous Justice Stephen Breyer when he consorts with his numerous friends and former colleagues in the liberal bastion of Cambridge, Mass. A FEW years ago, many insisted that Justice Scalia should not sit in judgment of Vice President Dick Cheney’s claims to enjoy executive privilege, noting that the two had been on the same duck-hunting trip. Justice Scalia memorably explained that the two men had never shared the same blind. He could as easily have pointed out that before President Harry Truman nationalized the steel mills, he asked Chief Justice Fred Vinson, a poker buddy and close friend, if the court would find the action constitutional. (Vinson incorrectly said yes.) The upshot is that the justices’ few and meager contacts with the real world do little harm and perhaps occasionally some good. Justice Anthony Kennedy makes an annual trip to Salzburg, Austria, to discuss ideas with European and other global judges and intellectuals. This contact is often invoked to explain why Justice Kennedy occasionally cites foreign law (a taboo for Justice Scalia) and why his jurisprudence has been relatively liberal on such matters as gay rights and Guantánamo. It is absurd for conservatives to criticize the cosmopolitan forums where judges from around the world compare notes. And it is absurd for liberals to criticize the conservative justices for associating with people who share or reinforce their views. The justices are human — and the more we let them be human, the better job they will do. Let the unthinkable be said! If the medieval vestments are making people think the justices should be monks, then maybe, just maybe, we should to do away with those robes.

Viewpoint: China's Hubris Colours U.S. Relations - Nye, Joseph S., Jr. (BBC News, 2011)
When Barack Obama became US president, one of his top foreign policy priorities was to improve relations with China. Yet on the eve of President Hu Jintao's state visit to Washington, US-China relations are worse, rather than better. Administration officials feel their efforts to reach out to China have been rebuffed. Ironically, in 2007, President Hu Jintao had told the 17th Congress of the Communist Party that China needed to invest more in its soft, or attractive, power. From the point of view of a country that was making enormous strides in economic and military power, this was a smart strategy. By accompanying the rise of its hard economic and military power with efforts to make itself more attractive, China aimed to reduce the fear and tendencies to balance Chinese power that might otherwise grow among its neighbours. But China's performance has been just the opposite, and China has had a bad year and a half in foreign policy. Rising nationalism For years, China had followed the advice of Deng Xiaoping to keep a low profile. However, with its successful economic recovery from the recession, China passed Japan as the world's second largest economy, and America's slow recovery led many Chinese to mistakenly conclude that the United States was in decline. Given such beliefs, and with rising nationalism in China as it prepares for the transition of power to the fifth generation of leaders in 2012, many in China pressed for a more assertive foreign policy. In 2009, China was justly proud of its success in managing to emerge from the world recession with a high 10% rate of economic growth. But many Chinese believed that this represented a shift in the world balance of power, and that China should be less deferential to other countries, including the US. Chinese scholars began writing about the decline of the US. One dated the year 2000 as the peak of American power. "People are now looking down on the West, from leadership circles, to academia, to everyday folks," said Professor Kang Xiaoguang of Renmin University. This Chinese view is seriously mistaken and China is unlikely to equal American economic, military or soft power for decades to come. Nonetheless, this over-confidence in power assessment (combined with insecurity in domestic affairs) led to more assertive Chinese foreign policy behaviour in the last two years. China miscalculated by deviating from the smart strategy of a rising power and violating the wisdom of Deng Xiaoping who advised that China should proceed cautiously and "skilfully keep a low profile". But perceptions matter, even when they are wrong. China's new attitudes alienated the Obama administration. China stage-managed President Obama's trip to Beijing in November 2009 in a heavy-handed way; it over-reacted to Obama's meeting with the Dalai Lama, and the administration's long-expected and relatively modest arms sales to Taiwan. When asked why they reacted so strongly to things they had accepted in the past, some Chinese responded, "because we were weaker then". Obama administration officials began to believe that efforts at co-operation or conciliation would be interpreted by the Chinese as proof that the US was in decline. Alienation and irritation China's new assertiveness affected its relations with other countries as well. Its policies in the South China Sea created fear among the Asean nations; and its over-reaction to Japan's actions after a ship collision near the Senkaku Islands put an end to the Democratic Party of Japan's hopes for a closer relationship with China. Instead, the Kan administration reaffirmed the American alliance. Beijing alienated South Korea by failing to criticise North Korea's shelling of a South Korean island; irritated India over border and passport issues; and embarrassed itself in Europe and elsewhere by over-reacting to the Nobel Peace Prize granted to the jailed dissident Liu Xiaobo. How will these issues play out in the coming year? It is likely that China's leaders will draw back somewhat from the overly assertive posture that has proven so costly. President Hu Jintao's stated desire to co-operate on terrorism, non-proliferation and clean energy will help to lead to a reduction of tensions, but powerful domestic interest groups in the export industries and in the People's Liberation Army will limit economic or naval co-operation. And most important, given the nationalism that one sees on the blogosphere in China, it will be difficult for Chinese top leaders to change their policies too dramatically. Mr Hu's state visit will help improve matters, but the relationship will remain difficult as long as the Chinese suffer from hubris based on a mistaken belief in American decline.

Wanted: A Grand Strategy for America - Ferguson, Niall (Newsweek, 2011)
“The statesman can only wait and listen until he hears the footsteps of God resounding through events; then he must jump up and grasp the hem of His coat, that is all.” Thus Otto von Bismarck, the great Prussian statesman who united Germany and thereby reshaped Europe’s balance of power nearly a century and a half ago. Last week, for the second time in his presidency, Barack Obama heard those footsteps, jumped up to grasp a historic opportunity … and missed it completely. In Bismarck’s case it was not so much God’s coattails he caught as the revolutionary wave of mid-19th-century German nationalism. And he did more than catch it; he managed to surf it in a direction of his own choosing. The wave Obama just missed—again—is the revolutionary wave of Middle Eastern democracy. It has surged through the region twice since he was elected: once in Iran in the summer of 2009, the second time right across North Africa, from Tunisia all the way down the Red Sea to Yemen. But the swell has been biggest in Egypt, the Middle East’s most populous country. In each case, the president faced stark alternatives. He could try to catch the wave, Bismarck style, by lending his support to the youthful revolutionaries and trying to ride it in a direction advantageous to American interests. Or he could do nothing and let the forces of reaction prevail. In the case of Iran, he did nothing, and the thugs of the Islamic Republic ruthlessly crushed the demonstrations. This time around, in Egypt, it was worse. He did both—some days exhorting Egyptian President Hosni Mubarak to leave, other days drawing back and recommending an “orderly transition.” The result has been a foreign-policy debacle. The president has alienated everybody: not only Mubarak’s cronies in the military, but also the youthful crowds in the streets of Cairo. Whoever ultimately wins, Obama loses. And the alienation doesn’t end there. America’s two closest friends in the region—Israel and Saudi Arabia—are both disgusted. The Saudis, who dread all manifestations of revolution, are appalled at Washington’s failure to resolutely prop up Mubarak. The Israelis, meanwhile, are dismayed by the administration’s apparent cluelessness. Last week, while other commentators ran around Cairo’s Tahrir Square, hyperventilating about what they saw as an Arab 1989, I flew to Tel Aviv for the annual Herzliya security conference. The consensus among the assembled experts on the Middle East? A colossal failure of American foreign policy. This failure was not the result of bad luck. It was the predictable consequence of the Obama administration’s lack of any kind of coherent grand strategy, a deficit about which more than a few veterans of U.S. foreign policy making have long worried. The president himself is not wholly to blame. Although cosmopolitan by both birth and upbringing, Obama was an unusually parochial politician prior to his election, judging by his scant public pronouncements on foreign-policy issues. Yet no president can be expected to be omniscient. That is what advisers are for. The real responsibility for the current strategic vacuum lies not with Obama himself, but with the National Security Council, and in particular with the man who ran it until last October: retired Gen. James L. Jones. I suspected at the time of his appointment that General Jones was a poor choice. A big, bluff Marine, he once astonished me by recommending that Turkish troops might lend the United States support in Iraq. He seemed mildly surprised when I suggested the Iraqis might resent such a reminder of centuries of Ottoman Turkish rule. The best national-security advisers have combined deep knowledge of international relations with an ability to play the Machiavellian Beltway game, which means competing for the president’s ear against the other would-be players in the policymaking process: not only the defense secretary but also the secretary of state and the head of the Central Intelligence Agency. No one has ever done this better than Henry Kissinger. But the crucial thing about Kissinger as national-security adviser was not the speed with which he learned the dark arts of interdepartmental turf warfare. It was the skill with which he, in partnership with Richard Nixon, forged a grand strategy for the United States at a time of alarming geopolitical instability. The essence of that strategy was, first, to prioritize (for example, détente with the Soviets before human-rights issues within the U.S.S.R.) and then to exert pressure by deliberately linking key issues. In their hardest task—salvaging peace with honor in Indochina by preserving the independence of South Vietnam—Nixon and Kissinger ultimately could not succeed. But in the Middle East they were able to eject the Soviets from a position of influence and turn Egypt from a threat into a malleable ally. And their overtures to China exploited the divisions within the Communist bloc, helping to set Beijing on an epoch-making new course of economic openness. The contrast between the foreign policy of the Nixon-Ford years and that of President Jimmy Carter is a stark reminder of how easily foreign policy can founder when there is a failure of strategic thinking. The Iranian Revolution of 1979, which took the Carter administration wholly by surprise, was a catastrophe far greater than the loss of South Vietnam. Remind you of anything? “This is what happens when you get caught by surprise,” an anonymous American official told The New York Times last week. “We’ve had endless strategy sessions for the past two years on Mideast peace, on containing Iran. And how many of them factored in the possibility that Egypt moves from stability to turmoil? None.” I can think of no more damning indictment of the administration’s strategic thinking than this: it never once considered a scenario in which Mubarak faced a popular revolt. Yet the very essence of rigorous strategic thinking is to devise such a scenario and to think through the best responses to them, preferably two or three moves ahead of actual or potential adversaries. It is only by doing these things—ranking priorities and gaming scenarios—that a coherent foreign policy can be made. The Israelis have been hard at work doing this. All the president and his NSC team seem to have done is to draft touchy-feely speeches like the one he delivered in Cairo early in his presidency. These were his words back in June 2009: America and Islam are not exclusive and need not be in competition. Instead, they overlap, and share common principles—principles of justice and progress; tolerance and the dignity of all human beings. Those lines will come back to haunt Obama if, as cannot be ruled out, the ultimate beneficiary of his bungling in Egypt is the Muslim Brotherhood, which remains by far the best organized opposition force in the country—and wholly committed to the restoration of the caliphate and the strict application of Sharia. Would such an outcome advance “tolerance and the dignity of all human beings” in Egypt? Somehow, I don’t think so. Grand strategy is all about the necessity of choice. Today, it means choosing between a daunting list of objectives: to resist the spread of radical Islam, to limit Iran’s ambition to become dominant in the Middle East, to contain the rise of China as an economic rival, to guard against a Russian “reconquista” of Eastern Europe—and so on. The defining characteristic of Obama’s foreign policy has been not just a failure to prioritize, but also a failure to recognize the need to do so. A succession of speeches saying, in essence, “I am not George W. Bush” is no substitute for a strategy. Bismarck knew how to choose. He understood that riding the nationalist wave would enable Prussia to become the dominant force in Germany, but that thereafter the No. 1 objective must be to keep France and Russia from uniting against his new Reich. When asked for his opinion about colonizing Africa, Bismarck famously replied: “My map of Africa lies in Europe. Here lies Russia and here lies France, and we are in the middle. That is my map of Africa.” Tragically, no one knows where Barack Obama’s map of the Middle East is. At best, it is in the heartland states of America, where the fate of his presidency will be decided next year, just as Jimmy Carter’s was back in 1980. At worst, he has no map at all.

Wielding 'Smart Power' in World Affairs - Nye, Joseph S., Jr. (The Boston Globe, 2011)
In his new book The Future of Power, Joseph S. Nye Jr. analyses the changing nature of power in the 21st century as upheavals man-made and environmental alter the global terrain and as both state and non-state entities jostle for dominance. Nye is a proponent of “smart power,” a term he coined in 2004 to describe the strategic combination of coercion and persuasion. Nye, a former assistant secretary of defense, is a professor and former dean of the Harvard Kennedy School of Government. His other books include Soft Power: The Means to Success in World Politics and The Powers to Lead. He spoke from his home in Boston. Q. Has the term “smart power” been corrupted over time? A. The term has been picked up by the Obama administration and used by Hillary Clinton to describe US foreign policy. But it is the older term “soft power” that is more often corrupted when it’s mistakenly used to describe anything that is not military power. More correctly, it refers to the ability to get what you want through attraction and persuasion. The Chinese president, for example, declared in 2007 that China needed to increase its soft power, and they have invested billions of dollars to that end. Q. Are you saying that smart power is soft power backed up by hard power? A. I think of smart power as the ability to combine hard and soft power. There may be situations in which you don’t want any hard power, and there may be others where soft power is not effective; stopping North Korea’s nuclear weapons program, for example. Q. Does it require an underlying belief in American dominance? A. Soft power and smart power are both available to any size country, not just the US or China. But the US, when it lives up to its values, probably has more soft power than a small country and certainly has more hard power. Our leadership resides in our ability to create the right combinations in the right circumstances. Q. You use the term “values.’’ But don’t you characterize smart power as morally neutral? A. Well, smart power is neutral in the sense that it can be used by bad states as well as good states. But it does depend in part on values which are more often the sources of soft power. Ironically, Osama bin Laden had soft power when he inspired people to fly into the World Trade Center and the Pentagon. They did so because they believed in bin Laden’s values. In that sense values matter. They can, however, be used as instruments by bad as well as good people. Q. Do you have a moral position that you edited out of this book? A. I try to write as an analyst when I argue that there is something to be said for soft power as a more ethical means. For example, even if I have bad ends and want to steal your money, I can use hard power — shoot you and take your money — or soft power — persuade you that I’m a guru and that you should give me your money. In the first case you don’t have anything to say about it, in the second case you do. If one believes in the value of individual autonomy and choice, as I do, soft power allows more of that individual autonomy even if the overall action is a bad one. Q. Your strategy has been called the friendly face of American imperialism. How do you respond to that? A. That criticism is often made by people who don’t understand the theory. Other countries besides the US can use soft power therefore it’s not an apology for the US or an instrument of American imperialism. In this book I try to describe the role of military, economic and soft power in an information age and to persuade people that we need to think in a more sophisticated way about what power means whether it be American, Chinese, or otherwise. Q. With all that you’ve seen, do you find it hard to write a phrase such as “winning hearts and minds” without irony? A. There is a risk of trivializing ideas. “Winning hearts and minds” has been around since the Vietnam War. On the other hand, when one tries to understand General Petraeus’s counterinsurgency doctrine (and whether he’ll succeed or not we don’t know) it is interesting to note that what he is trying to do is save civilian lives. The idea is not to kill as many people as possible but to win the minds of those who form the sea in which the insurgents swim. The insight is an important one and has a long standing in history. Q. Do you see the uprising in Tunisia and now in Egypt as a test case of US commitment to smart power? A. Smart power in this current case will require US foreign policy to align with the aspirations of people seeking democracy while at the same time not creating chaos in the region which would undercut our support for Israel and our efforts to prevent the spread of nuclear weapons. Smart power would aim to accomplish both a human rights democracy agenda as well as a more traditional agenda. Q. Do you see that happening? A. I’m always hopeful.

The Future of American Power - Nye, Joseph S., Jr. (Foreign Affairs, 2010)
The twenty-first century began with a very unequal distribution of power resources. With five percent of the world's population, the United States accounted for about a quarter of the world's economic output, was responsible for nearly half of global military expenditures, and had the most extensive cultural and educational soft-power resources. All this is still true, but the future of U.S. power is hotly debated. Many observers have interpreted the 2008 global financial crisis as the beginning of American decline. The National Intelligence Council, for example, has projected that in 2025, "the U.S. will remain the preeminent power, but that American dominance will be much diminished." Power is the ability to attain the outcomes one wants, and the resources that produce it vary in different contexts. Spain in the sixteenth century took advantage of its control of colonies and gold bullion, the Netherlands in the seventeenth century profited from trade and finance, France in the eighteenth century benefited from its large population and armies, and the United Kingdom in the nineteenth century derived power from its primacy in the Industrial Revolution and its navy. This century is marked by a burgeoning revolution in information technology and globalization, and to understand this revolution, certain pitfalls need to be avoided. First, one must beware of misleading metaphors of organic decline. Nations are not like humans, with predictable life spans. Rome remained dominant for more than three centuries after the peak of its power, and even then it did not succumb to the rise of another state. For all the fashionable predictions of China, India, or Brazil surpassing the United States in the next decades, the greater threat may come from modern barbarians and nonstate actors. In an information-based world, power diffusion may pose a bigger danger than power transition. Conventional wisdom holds that the state with the largest army prevails, but in the information age, the state (or the nonstate actor) with the best story may sometimes win. For the complete article go to the Foreign Affairs website.

The Multiple Crises of French Universities - Lamont, Michèle; Cousin, Bruno (Council of National Associations, 2010)
Between February and June 2009, French universities were the theatre of an exceptional protest movement against the latest flavour of governmental reform concerning academic careers. Protest sometimes seems to be a way of life in the French academy, and in France at large, but this time the situation is serious, with potentially huge consequences for the future of the sector. Indeed, the nation that gave birth to je pense, donc je suis is in a deep crisis on the intellectual front, and nowhere is this as obvious as in academic evaluation. The protest movement did not take off in the grandes écoles (which train much of the French elite), or in professional and technical schools. Instead, it took off in the 80 comprehensive universités – the public institutions that are the backbone of the French educational system. Until two years ago, they were required to admit any high-school graduate on a first-come, first-served basis. A selection process was recently introduced, but even today most students are there because they could not gain entry elsewhere. Faculty work conditions are generally poor, as their institutions are chronically underfunded. Classes are large and programmes are understaffed. More than half of all students leave without any kind of diploma. Public universities can be very different from each other and are research-intensive in varying degrees, but they carry out the bulk of French scientific research. Research is largely conducted in centres that are located within these institutions, and which often bring together overworked university teachers and full-time researchers who are attached to national institutes such as the Centre National de la Recherche Scientifique (CNRS). In a context where the output of these joint centres is not, or is only partially, covered by international ratings, French academics feel doubly underrated owing to the combination of low salaries and low ratings. This feeling was exacerbated on 22 January when President Nicolas Sarkozy declared that the poor performance of French universities in international rankings was, above all, the consequence of the absence of continuous evaluation, which encourages sloth. Of course, he was displeased that the extensive set of higher education reforms undertaken by his Government during the preceding two years were met with opposition by large segments of the academic community. Everyone agrees that the current system poses a great many problems, but there is no agreement on how to improve it and get beyond the current gridlock. It is la société bloquée all over again. To wit: While most academics believe that the system is far too centralised, a 2007 law establishing the progressive financial “autonomy” (and accountability) of universities has been met with criticism and resistance, because it is perceived to be part of a strategy of withdrawal on the part of the State that will result in fewer resources being available for higher education. A number of scholars also fear that the increased decision-making power conferred on university presidents is a threat to the autonomy of faculty members. While there is a need to design new, more universalistic procedures for evaluating performance and distributing resources, many academics are sceptical of the new institutions recently created to do this, namely the national agencies for the evaluation of universities and research units (Agence d’Evaluation de la Recherche et de l’Enseignement Superieur, or AERES) and research projects (Agence Nationale de la Recherche, or ANR). The former, in particular, has been criticised for its reliance on bibliometrics (publication and citation counts), even if the agency is now moving towards using less quantitative standards. Moreover, whereas the former mechanisms for distributing research funds depended on the decisions of elected peers (for instance, on the national committee of the CNRS), AERES appoints its panel members, and this is seen as a blow to researchers’ autonomy. For this and other reasons, many academics have refused to serve on its evaluation panels. - While academics often agree that the old CNRS needed further integration with the universities, many denounce its gradual downsizing and transformation from a comprehensive research institution to a simple funding and programming agency as the work of uninformed politicians and technocrats intent on dismantling what works best in French research. In 2004, a widespread national protest arose against this dismantling, with 74,000 scholars signing a petition against it. Critics also say that the ongoing reorganisation of the CNRS into disciplinary institutes will reinforce the separation between the sciences, reorient research towards more applied fields and work against the interdisciplinary collaborations that are crucial to innovation in many fields. While many agree on the need to improve teaching, moves to increase the number of teaching hours are among the most strongly contested reforms. French academics, who very rarely have sabbaticals, already perceive themselves as overworked in a system where time for research is increasingly scarce. These factors help to explain the resistance to expanded classroom hours and new administrative duties. In the longest strike ever organised by the French scientific community, tens of thousands of lecturers and researchers began in early February to hold protests over a period of several weeks, demonstrating in the streets and (with the support of some students) blocking access to some university campuses. Many also participated in a national debate via print, online and broadcast media, and in general meetings. Some faculty members held teach-ins and action-oriented “alternative courses” for students. Several universities saw their final exams and summer holidays delayed and many foreign exchange students were called back by their home institutions. Despite this frontal assault, the Government did not back down: the much disparaged decree reorganising academic careers (with regard to recruitment, teaching loads, evaluations and promotions) and giving more prerogatives and autonomy to university presidents came into effect on 23 April. This outcome will probably lead academics and their unions to rethink their strategies and repertoires of collective action. The traditional protest forms are losing legitimacy. As the dust settles, it is becoming clear that demonstrating has little traction in a context where the French public increasingly perceives academics as an elite bent on defending its privileges, even if it requires depriving students of their courses. Negotiation is also perceived as ineffectual, as many suspect that governmental consultations were conducted to buy time until the end of the academic year, when mobilisation would peter out. A third strategy—the radical option that would have prevented the scheduling of exams and the handing out of diplomas at the end of this spring – was ruled out even on the campuses most committed to the cause for fear of alienating the public even further. As yet, however, no clear alternative has surfaced. We are now witnessing a cleavage between those who voice their opposition (in the main, scholars in the humanities) and the increasing number of academics (primarily scientists) who espouse a “wait-and-see” or a collaborative position as the only realistic path to improving the situation in their own universities. If the majority of academics appear to share the same diagnosis about what needs to be changed in the French system, they disagree on the solution (and on its scale—national or local). The root of the crisis lies not only in the Government’s difficulties in generating consensus, but also in the academics’ own scepticism, cynicism or fatalism about meritocracy, the absence of the administrative resources needed to support proper evaluation, the possibility of impartial evaluation, and the system’s ability to recognise and reward merit. Deep problems remain in the institutions charged with evaluating the work of academics. The interference of political power, and the (admittedly diminishing) influence of trade unions and corporatist associations have long been viewed as obstacles to a collegial system of academic evaluation. The legitimacy of the 70 disciplinary sections of the Conseil National des Universites (CNU)—charged with certifying individuals as eligible for faculty positions, and with directly granting some promotions – is under question. Some of its committee members are appointed by the Government and as such are suspected of being second-rate, of benefiting from governmental patronage, or of defending governmental interests. Others are chosen from electoral lists that include a disproportionate number of partisan members, who are often perceived to be there because of their political involvement rather than because of their scientific status. The legitimacy of these committees is further called into question because they include only academics employed by French institutions and are often viewed as perpetuating a longstanding tradition of favouritism. To give only one particularly scandalous example: in June, panellists in the sociology section allocated to themselves half of the promotions that they were charged with assigning across the entire discipline of sociology. This led to the resignation of the rest of the commission and to multiple protests. Such an occurrence sent deep waves of distrust not only between academics, but also towards the civil servants charged with reforming a system that is increasingly viewed as flawed. Peer review is also in crisis at the local level. While selecting young doctoral recipients to be maîtres de conférences (the entry level permanent position in the French academy, similar to the British lecturer), French universities on average fill 30 per cent of available posts with their own graduates, to the point where local clientelism is often decried as symbolising the corruption of the entire system. The typical (and only) job interview for such a post lasts 20 to 30 minutes—probably the European record for brevity and surely too short to determine whether an individual deserves what is essentially a lifelong appointment. Many view the selection process as little more than a means to legitimise the appointment of pre-selected candidates—although the extent to which this is genuinely the case varies across institutions. What is to be done? Because both the CNU and the local selection committees have recently been reorganised or granted new responsibilities, it seems the right moment to think about how to improve the evaluation processes in very practical ways. As part of a new start, academics should aim to generate a system of true self-governance at each level, grounded in more explicit principles for peer review. This would put them in a position to defend academic autonomy against the much-feared and maligned governmental or managerial control. While this is certainly occurring in some disciplines and institutions, progress is far from being equally spread across the sector. Obvious and costless regulatory measures could easily be implemented—for instance, discouraging universities from hiring their own PhD graduates (as AERES recently started to), or forbidding selection committees from promoting their own members. One could also look abroad for examples of “best practice”. The UK’s Economic and Social Research Council has created colleges of trained academic evaluators who are charged with maintaining academic and ethical standards in peer review; although not all aspects of the British approach to academic reform should be emulated, this one is particularly worthy. The Deutsche Forschungsgemeinschaft (German Research Foundation) uses teams of elected experts to evaluate proposals, and academic reputation weighs heavily in determining which names will be put on electoral lists and who will serve on evaluation panels. Canada’s Social Sciences and Humanities Research Council recently asked an independent panel of international experts to evaluate its peer review process in order to improve impartiality and effectiveness. In a recent book on peer review in the US, one of the present authors (Michéle Lamont) showed the ways in which American social scientists and humanists operate to maintain their faith in the idea that peer review works and that the academic system of evaluation is fair. In this case, academics exercise their right as the only legitimate evaluators of knowledge by providing detailed assessment of intellectual production in light of their extensive expertise in specialised topics. The exercise of peer evaluation sustains and expresses professional status and professional autonomy. But it requires significant time (and thus good working conditions) and moral commitment—time spent comparing dossiers, making principled decisions about when it is necessary to withdraw on the grounds of personal interest, and so forth. Of course no peer review works perfectly, but US academics, while being aware of its limitations, appear to view the system as relatively healthy and they engage in many actions that contribute to sustaining this faith. In our view, fixing the current flaws in the French system does not merely demand organisational reforms, including giving academics more time to evaluate the research of colleagues and candidates properly. It may also require French academics to think long and hard about their own cynicism and fatalism concerning their ability to make judgments about quality that would not be driven by cronyism or particularism, and that would honour their own expertise and connoisseurship. Not that proper governmental reform is not needed, but sometimes blaming the Government may be an easy way out. Above all, it is increasingly a very ineffectual way of tackling a substantial part of the problem. A little more collaborative thinking and a little less cynicism among both academics and administrators—if at all possible—may very well help French universities find a way out of the crisis. And it will help the French academic and research community to become, once again, much more than the sum of its parts.

A Failure to Imagine the Worst - Allison, Graham T., Jr. (Foreign Policy, 2010)

Jamaica’s Bloody Democracy - Patterson, Orlando (New York Times, 2010)
The violence tearing apart Jamaica, a democratic state, raises serious questions not only about its government’s capacity to provide basic security but, more broadly and disturbingly, the link between violence and democracy itself. The specific causes of the turmoil are well known. For decades political leaders have used armed local gangs to mobilize voters in their constituencies; the gangs are rewarded with the spoils of power, in particular housing and employment contracts they can dole out. Opposition leaders counter with their own gangs, resulting in chronic violence during election seasons. These gangs eventually moved into international drug trafficking, with their leaders, called “dons,” becoming ever more powerful. The tables turned quite some time ago, with the politicians becoming dependent on the dons for their survival. A case in point is the reliance of Prime Minister Bruce Golding on one notorious don, Christopher Coke, whose refusal to surrender for extradition to the United States to stand trial on gun and drug charges led last week to virtual warfare on the streets of the capital, Kingston, and the deaths of scores of civilians. Endemic political corruption is hardly Jamaica’s only problem. Add to it paltry rates of economic growth, widespread poverty and income inequality, vast urban slums and a police force considered brutal and despised by the poor, and it is little surprise that the island nation’s homicide rate is always among the handful of the world’s highest. Yet Jamaica, to its credit, has by global standards achieved a robust democracy. However great the violence during elections, voting is fair and governments change at the national level regularly and fairly smoothly. The judiciary, if overburdened, is nonetheless independent and relatively uncorrupt. There is a vigorous free press, and a lively civil society. Freedom House has continuously categorized the island as a “free” country. For most observers of democracy, Jamaica’s violence seems an anomaly. Democracy is held to be inherently prone to good order and peace. According to this “democratic peace” doctrine, democracies do not go to war with each other, and in domestic life they provide nonviolent means of settling differences. Violence, writes the political theorist John Keane, is anathema to democracy’s “spirit and substance.” It may or may not be true that democracies do not wage war with each other, but a growing number of analysts have concluded that, domestically, democracies are in fact more prone to violence than authoritarian states, measured by incidence of civil wars, communal conflict and homicide. There are many obvious examples of this: India has far more street crime than China; the countries of the former Soviet Union are more violent now than they were under Communism; the streets of South Africa became more dangerous after apartheid was dismantled; Brazil was safer before 1985 under its military rule. Three good explanations are offered for this connection between democracy and violent crime. First, it has been persuasively shown by social scientists like David Rapoport of the University of California at Los Angeles and Leonard Weinberg of the University of Nevada at Reno that the electoral process itself tends, on balance, to promote violence more than peace. Sometimes the ballot can substitute for the bullets of civil wars, as in Nicaragua in 1990 when the Sandinista government was voted out peacefully. However, the opposite is more often the case, as in Greece in 1967, when electoral uncertainty led to a military coup, and Algeria in 1992, when elections were canceled in the face of a certain victory by a fundamentalist Islamic party, leading to civil war. Another well-supported argument is that democracies are especially vulnerable to ethnic conflict and organized crime. In diverse democracies, the temptation of leaders to exploit ethnic identity for political ends is an all too frequent source of major conflict, sometimes culminating in oppression of minorities and even genocide. We saw this happen in Rwanda in 1994 and the former Yugoslav states in the 1990s. Dennis Austin, who has studied political strife in India and Sri Lanka, has concluded that in such societies “democracy is itself a spur to violence” adding “depth to the sense of division.” Organized crime, especially international trafficking in drugs, has become a serious threat to democracies worldwide. Felia Allun and Renate Siebert, the editors of an important scholarly collection, “Organized Crime and the Challenge to Democracy,” argue that “it is by exploiting the very freedoms which democratic systems offer that organized crime is able to thrive ... although mortifying democratic rights, these kinds of crimes need the democratic space to flourish.” A third, more nuanced argument is suggested by the work of the Norwegian political scientist Havard Hegre, who has shown that nondemocratic regimes become more prone to civil unrest, and more likely to threaten or start wars with neighboring countries, as they enter the transition period toward becoming democratic. The arc to democratic peace is therefore U-shaped. Authoritarian regimes can tyrannize their citizens into less violence. But as their states become more democratic, the mix of persisting authoritarian traditions and democratic freedoms can be lethal, sometimes resulting in complete state collapse, as in Yugoslavia. It is only when such countries get very close to democratic maturity that social violence rapidly declines. At least that is the conclusion that my Harvard colleague Ethan Fosse and I came to after examining the relationship between homicide rates and Freedom House’s democracy rankings. Yet even in these countries on the cusp of democracy there is a complicating factor — they are usually also going through the transition from a poor economy to a more developed one. The expectations of citizens in these transitional economies often outrun the capacity of society to meet them; people get frustrated and feel unfairly treated, leading to high risks of violence. The worst possible situation for a state, however, is for its economic transition to stall or fail before the transition to mature democracy is complete. And this is what Jamaica now faces. For the first dozen years after independence from Britain in 1962, progress toward democracy and self-sustained economic growth moved nicely in tandem. But then the oil crisis and recession of 1973, and the efforts by the democratic socialist government of Prime Minister Michael Manley to deal with hard times, knocked the wind from the sails of economic progress, and Jamaica has never really recovered. (Disclosure: I was an adviser to Prime Minister Manley at that time.) To see what happens when a country accomplishes both transitions, we need only look at the neighboring Afro-Caribbean island of Barbados. It has a similar colonial past, and became independent just three years after Jamaica. Yet Barbados’ per capita income is now more than twice that of Jamaica, its standard of living puts it among the developed world and Freedom House places it on a par with Western Europe in terms of the maturity of its democracy. Sure enough, Barbados also has one of the lowest homicide rates in the hemisphere. Barbados, unfortunately, is not typical. Jamaica, though an extreme case, is more in line with other democracies of the hemisphere, including Colombia, Venezuela, Trinidad and Tobago, Mexico and even Brazil, where the treacherous joint transition to democratic maturity and economic security has been accompanied by horrendous levels of crime. As the American government decides how to respond to the crisis in Jamaica, a product of the (proper) insistence on the extradition of Christopher Coke, it would do well to view developments there in these broader terms. The problem of Jamaica might not seem so insoluble if Americans were to have a more sympathetic understanding of the transitional plight of this little country, brought on in large part by its unwavering struggle toward a more mature and equitable democracy.

An Alliance Larger Than One Issue - Nye, Joseph S., Jr. (New York Times, 2010)
Seen from Tokyo, America’s relationship with Japan faces a crisis. The immediate problem is deadlock over a plan to move an American military base on the island of Okinawa. It sounds simple, but this is an issue with a long back story that could create a serious rift with one of our most crucial allies. When I was in the Pentagon more than a decade ago, we began planning to reduce the burden that our presence places on Okinawa, which houses more than half of the 47,000 American troops in Japan. The Marine Corps Air Station Futenma was a particular problem because of its proximity to a crowded city, Ginowan. After years of negotiation, the Japanese and American governments agreed in 2006 to move the base to a less populated part of Okinawa and to move 8,000 Marines from Okinawa to Guam by 2014. The plan was thrown into jeopardy last summer when the Japanese voted out the Liberal Democratic Party that had governed the country for nearly half a century in favor of the Democratic Party of Japan. The new prime minister, Yukio Hatoyama, leads a government that is inexperienced, divided and still in the thrall of campaign promises to move the base off the island or out of Japan completely. The Pentagon is properly annoyed that Mr. Hatoyama is trying to go back on an agreement that took more than a decade to work out and that has major implications for the Marine Corps’ budget and force realignment. Secretary of Defense Robert Gates expressed displeasure during a trip to Japan in October, calling any reassessment of the plan “counterproductive.” When he visited Tokyo in November, President Obama agreed to a high-level working group to consider the Futenma question. But since then, Mr. Hatoyama has said he will delay a final decision on relocation until at least May. Not surprisingly, some in Washington want to play hardball with the new Japanese government. But that would be unwise, for Mr. Hatoyama is caught in a vise, with the Americans squeezing from one side and a small left-wing party (upon which his majority in the upper house of the legislature depends) threatening to quit the coalition if he makes any significant concessions to the Americans. Further complicating matters, the future of Futenma is deeply contentious for Okinawans. Even if Mr. Hatoyama eventually gives in on the base plan, we need a more patient and strategic approach to Japan. We are allowing a second-order issue to threaten our long-term strategy for East Asia. Futenma, it is worth noting, is not the only matter that the new government has raised. It also speaks of wanting a more equal alliance and better relations with China, and of creating an East Asian community—though it is far from clear what any of this means. When I helped to develop the Pentagon’s East Asian Strategy Report in 1995, we started with the reality that there were three major powers in the region—the United States, Japan and China—and that maintaining our alliance with Japan would shape the environment into which China was emerging. We wanted to integrate China into the international system by, say, inviting it to join the World Trade Organization, but we needed to hedge against the danger that a future and stronger China might turn aggressive. After a year and a half of extensive negotiations, the United States and Japan agreed that our alliance, rather than representing a cold war relic, was the basis for stability and prosperity in the region. President Bill Clinton and Prime Minister Ryutaro Hashimoto affirmed that in their 1996 Tokyo declaration. This strategy of “integrate, but hedge” continued to guide American foreign policy through the years of the Bush administration. This year is the 50th anniversary of the United States–Japan security treaty. The two countries will miss a major opportunity if they let the base controversy lead to bitter feelings or the further reduction of American forces in Japan. The best guarantee of security in a region where China remains a long-term challenge and a nuclear North Korea poses a clear threat remains the presence of American troops, which Japan helps to maintain with generous host nation support. Sometimes Japanese officials quietly welcome “gaiatsu,” or foreign pressure, to help resolve their own bureaucratic deadlocks. But that is not the case here: if the United States undercuts the new Japanese government and creates resentment among the Japanese public, then a victory on Futenma could prove Pyrrhic. <nyt_author_id>   </nyt_author_id>

Chronicler of History’s Sweep (Harvard Gazette, 2009)
“Growing up, I don’t know if I ever thought of becoming a teacher,” said Erez Manela, recently tenured professor of history in the Faculty of Arts and Sciences. “I was always supposed to become a doctor or a lawyer.” Manela actually began by studying foreign languages as an undergraduate at the Hebrew University of Jerusalem, not far from his hometown of Haifa, Israel. He soon discovered that courses in East Asian and Middle Eastern history complemented his interests in Chinese, Arabic, and Persian. Though he saw a future in academia, history was not a field he had expected to pursue. “I didn’t yet conceive of it as something you could do as a profession, but rather something you might study to know more about the world,” he said. Previously the Dunwalke Associate Professor of American History, Manela now specializes in modern international history and the history of the United States in the world. His first book, “The Wilsonian Moment: Self-Determination and the International Origins of Anticolonial Nationalism” (Oxford, 2007), explored the impact of President Woodrow Wilson’s rhetoric on nationalist movements in Asia and the Middle East in the wake of World War I. Manela’s current research revolves around the global campaign to eradicate smallpox in the 1960s and ‘70s. Manela considers his undergraduate experience the source of some of his main intellectual questions. In college, “I realized that in the modern period—during the 19th and early 20th centuries—there were really fascinating parallels between the history of the Ottoman Empire and the history of East Asia, particularly China,” Manela said. “That really intrigued me…I kept wondering how I could study these parallels in a way that wasn’t simply comparative. I wanted to put everything into one big framework and tell the story as connected.” Manela decided to concentrate on international history as a graduate student at Yale, partly because he was reluctant to give up studying any of the countries or languages he had embraced in college. “I couldn’t bear the thought of focusing on just one of them,” he said. “I wanted to put it all to good use.” Studying international history has allowed Manela to break free of the nation as an analytical framework and devote new attention to transnational actors, organizations, and themes. When Manela arrived at Harvard in 2003, history professors Akira Iriye (now emeritus) and the late Ernest May served as inspirational figures for him, as they too were concerned with these pioneering directions in international history. (May even taught Manela the basics of PowerPoint by jotting a few commands on an index card during his first semester at Harvard.) “Teaching with them…was a tremendously formative experience for me,” Manela said. “Together, they established an amazing tradition of international history in this department.” A member of Harvard’s Weatherhead Center for International Affairs, Manela considers the interdisciplinary community of scholars and students his “second home” within the University. He served as the Weatherhead’s director of undergraduate student programs for four years, and is now director of graduate student programs. Manela spends most of his free time with his three daughters, but sometimes revisits an old interest: chess. Occasionally he challenges the regulars in Harvard Square. “Once upon a time I used to play chess fairly well,” he said, “but that’s history.” Manela is grateful to have the chance to study a subject that many people can pursue only as a hobby, even though he never did live up to expectations of becoming a doctor or a lawyer. “I think this is a decent alternative,” he said with a grin.

Dead Men Walking - Ferguson, Niall (Foreign Policy, 2009)
There is nothing like a really big economic crisis to separate the Cassandras from the Panglosses, the horsemen of the apocalypse from the Kool-Aid-swigging optimists. No, the last year has shown that all is not for the best in the best of all possible worlds. On the contrary, we might be doomed. <!-- SHARE BOX --><!-- END SHARE BOX --> At such times, we do well to remember that most of today’s public intellectuals are mere dwarves, standing on the shoulders of giants. So, if they had e-mail in the hereafter, which of the great thinkers of the past would be entitled to send us a message with the subject line: “I told you so”? And which would prefer to remain offline? It has, for example, been a bad year for Adam Smith (1723-1790) and his “invisible hand,” which was supposed to steer the global economy onward and upward to new heights of opulence through the action of individual choice in unfettered markets. By contrast, it has been a good year for Karl Marx (1818-1883), who always maintained that the internal contradictions of capitalism, and particularly its tendency to increase the inequality of the distribution of wealth, would lead to crisis and finally collapse. A special mention is also due to early 20th-century Marxist theorist Rudolf Hilferding (1877-1941), whose Das Finanzkapital foresaw the rise of giant “too big to fail” financial institutions. Joining Smith in embarrassed silence, you might think, is Friedrich von Hayek (1899-1992), who warned back in 1944 that the welfare state would lead the West down the “road to serfdom.” With a government-mandated expansion of health insurance likely to be enacted in the United States, Hayek's libertarian fears appear to have receded, at least in the Democratic Party. It has been a bumper year, on the other hand, for Hayek's old enemy, John Maynard Keynes (1883-1946), whose 1936 work The General Theory of Employment,Interest and Money has become the new bible for finance ministers seeking to reduce unemployment by means of fiscal stimuli. His biographer, Robert Skidelsky, has hailed the “return of the master.” Keynes's self-appointed representative on Earth, New York Times columnist Paul Krugman, insists that the application of Keynesian theory, in the form of giant government deficits, has saved the world from a second Great Depression. The marketplace of ideas has not been nearly so kind this year to the late Milton Friedman (1912-2006), the diminutive doyen of free-market economics. “Inflation,” wrote Friedman in a famous definition, “is always and everywhere a monetary phenomenon, in the sense that it cannot occur without a more rapid increase in the quantity of money than in output.” Well, since September of 2008, Ben Bernanke has been printing dollars like mad at the U.S. Federal Reserve, more than doubling the monetary base. And inflation? As I write, the headline consumer price inflation rate is negative 2 percent. Better throw away that old copy of Friedman's Monetary History of the United States, 1867-1960 (co-authored with Anna J. Schwartz, who is happily still with us). Invest, instead, in a spanking new edition of The Great Transformation by Karl Polanyi (1886-1964). We surely need Polanyi's more anthropological approach to economics to explain the excesses of the boom and the hysteria of the bust. For what in classical economics could possibly account for the credulity of investors in Bernard Madoff's long-running Ponzi scheme? Or the folly of Richard Fuld, who gambled his personal fortune and reputation on the very slim chance that Lehman Brothers, unlike Bear Stearns and Merrill Lynch, could survive the crisis without being sold to a competitor? The biggest intellectual losers of all, however, must be the pioneers of the theory of efficient markets—economists still with us, such as Harry M. Markowitz, the University of Chicago-trained economist who developed the theory of portfolio diversification as the best protection against economic volatility, and William Sharpe, inventor of the capital asset pricing model. In two marvelously lucid books, the late Peter Bernstein extolled their “capital ideas.” Now, with so many quantitative hedge funds on the scrap heap, their ideas don't seem quite so capital. And the biggest winners, among economists at least? Step forward the "Austrians" —economists like Ludwig von Mises (1881-1973), who always saw credit-propelled asset bubbles as the biggest threat to the stability of capitalism. Not many American economists carried forward their work into the later 20th century, but one heterodox figure has emerged as a posthumous beneficiary of this crisis: Hyman Minsky (1919-1996). At a time when other University of Chicago-trained economists were forging the neoclassical synthesis—Adam Smith plus applied math—Minsky developed his own math-free “financial instability hypothesis.” Yet it would surely be wrong to make the Top Dead Thinker of 2009 an economic theorist. The entire discipline of economics has flopped too embarrassingly for that to be appropriate. Instead, we should consider the claims of a historian, because history has served as a far better guide to the current crisis than any economic model. My nominee is the financial historian Charles Kindleberger (1910-2003), who drew on Minsky's work to popularize the idea of financial crisis as a five-stage process, from displacement and euphoric overtrading to full-fledged mania, followed by growing concern and ending up with panic. (If those five steps to financial hell sound familiar, they should. We just went down them, twice in the space of 10 years.) Of course, history offers more than just the lesson that financial accidents will happen. One of the most important historical truths is that the first draft of history —the version that gets written on the spot by journalists and other contemporaries —is nearly always wrong. So though superficially this crisis seems like a defeat for Smith, Hayek, and Friedman, and a victory for Marx, Keynes, and Polanyi, that might well turn out to be wrong. Far from having been caused by unregulated free markets, this crisis may have been caused by distortions of the market from ill-advised government actions: explicit and implicit guarantees to supersize banks, inappropriate empowerment of rating agencies, disastrously loose monetary policy, bad regulation of big insurers, systematic encouragement of reckless mortgage lending—not to mention distortions of currency markets by central bank Consider this: The argument for avoiding mass bank failures was made by Friedman, not Keynes. It was Friedman who argued that the principal reason for the depth of the Depression was the Fed's failure to avoid an epidemic of bank failures. It has been Friedman, more than Keynes, who has been Bernanke’s inspiration over the past two years, as the Fed chairman has honored a pledge he made shortly before Friedman's death not to preside over another “great contraction.” Nor would Friedman have been in the least worried about inflation at a time like this. The Fed's balance sheet may have expanded rapidly, but broader measures of money are growing slowly and credit is contracting. Deflation, not inflation, remains the monetarist fear. From a free market perspective, the vital thing is that legitimate emergency measures do not become established practices. For it cannot possibly be a healthy state of affairs for the core institutions of the Western financial system to be effectively guaranteed, if not actually owned, by the government. The thinker who most clearly discerned the problems associated with that kind of state intervention was Joseph Schumpeter (1883-1950), whose “creative destruction” has been one of this year's most commonly cited phrases. “[T]his evolutionary…impulse that sets and keeps the capitalist engine in motion,” wrote Schumpeter in Capitalism, Socialism and Democracy, “comes from…the new forms of industrial organization that capitalist enterprise creates…This process of creative destruction is the essential fact about capitalism.” This crisis has certainly unleashed enough economic destruction in the world (though its creativity at this stage is still hard to discern). But in the world of the big banks, there has been far too little destruction, and about the only creative thing happening on Wall Street these days is the accounting. “This economic system,” Schumpeter wrote in his earlier The Theory of Economic Development, “cannot do without the ultima ratio [final argument] of the complete destruction of those existences which are irretrievably associated with the hopelessly unadapted.” Indeed, he saw that the economy remained saddled with too many of “those firms that are unfit to live.” That could serve as a painfully accurate description of the Western financial system today. Yet all those allusions to evolution and fitness to live serve as a reminder of the dead thinker we should all have spent at least part of 2009 venerating: Charles Darwin (1809-1882). This year was not only his bicentennial but the 150th birthday of his paradigm-shifting On the Origin of Species. Just reflect on these sentences from Darwin's seminal work: All organic beings are exposed to severe competition.” “As more individuals are produced than can possibly survive, there must in every case be a struggle for existence.” “Each organic being…has to struggle for life and to suffer great destruction.... The vigorous, the healthy, and the happy survive and multiply.” Thanks in no small measure to the efforts of his modern heirs, notably Richard Dawkins, we are all Darwinians now—except in the strange parallel worlds of fundamentalist Christianity and state-guaranteed finance. Neither Cassandra nor Pangloss, Darwin surely deserves to top any list of modern thinkers, dead or alive.

The French Disconnection - Lamont, Michèle; Cousin, Bruno (Times Higher Education, 2009)
Bruno Cousin and Michèle Lamont say academics at France's public universities need to rethink their strategy after this year's protests alienated the public and had little impact on the Government. Between February and June 2009, French universities were the theatre of an exceptional protest movement against the latest flavour of governmental reform concerning academic careers. Protest sometimes seems to be a way of life in the French academy, and in France at large, but this time the situation is serious, with potentially huge consequences for the future of the sector. Indeed, the nation that gave birth to je pense, donc je suis is in a deep crisis on the intellectual front, and nowhere is this as obvious as in academic evaluation. The protest movement did not take off in the grandes écoles (which train much of the French elite), or in professional and technical schools. Instead, it took off in the 80 comprehensive universités—the public institutions that are the backbone of the French educational system. Until two years ago, they were required to admit any high-school graduate on a first-come, first-served basis. A selection process was recently introduced, but even today most students are there because they could not gain entry elsewhere. Faculty work conditions are generally poor, as their institutions are chronically underfunded. Classes are large and programmes are understaffed. More than half of all students leave without any kind of diploma. Public universities can be very different from each other and are research-intensive in varying degrees, but they carry out the bulk of French scientific research. Research is largely conducted in centres that are located within these institutions, and which often bring together overworked university teachers and full-time researchers who are attached to national institutes such as the Centre National de la Recherche Scientifique (CNRS). In a context where the output of these joint centres is not, or is only partially, covered by international ratings, French academics feel doubly underrated owing to the combination of low salaries and low ratings. This feeling was exacerbated on 22 January when President Nicolas Sarkozy declared that the poor performance of French universities in international rankings was, above all, the consequence of the absence of continuous evaluation, which encourages sloth. Of course, he was displeased that the extensive set of higher education reforms undertaken by his Government during the preceding two years were met with opposition by large segments of the academic community. Everyone agrees that the current system poses a great many problems, but there is no agreement on how to improve it and get beyond the current gridlock. It is la société bloquée all over again. To wit: - While most academics believe that the system is far too centralised, a 2007 law establishing the progressive financial “autonomy” (and accountability) of universities has been met with criticism and resistance, because it is perceived to be part of a strategy of withdrawal on the part of the State that will result in fewer resources being available for higher education. A number of scholars also fear that the increased decision-making power conferred on university presidents is a threat to the autonomy of faculty members. - While there is a need to design new, more universalistic procedures for evaluating performance and distributing resources, many academics are sceptical of the new institutions recently created to do this, namely the national agencies for the evaluation of universities and research units (Agence d'Evaluation de la Recherche et de l'Enseignement Superieur, or AERES) and research projects (Agence Nationale de la Recherche, or ANR). The former, in particular, has been criticised for its reliance on bibliometrics (publication and citation counts), even if the agency is now moving towards using less quantitative standards. Moreover, whereas the former mechanisms for distributing research funds depended on the decisions of elected peers (for instance, on the national committee of the CNRS), AERES appoints its panel members, and this is seen as a blow to researchers' autonomy. For this and other reasons, many academics have refused to serve on its evaluation panels. - While academics often agree that the old CNRS needed further integration with the universities, many denounce its gradual downsizing and transformation from a comprehensive research institution to a simple funding and programming agency as the work of uninformed politicians and technocrats intent on dismantling what works best in French research. In 2004, a widespread national protest arose against this dismantling, with 74,000 scholars signing a petition against it. Critics also say that the ongoing reorganisation of the CNRS into disciplinary institutes will reinforce the separation between the sciences, reorient research towards more applied fields and work against the interdisciplinary collaborations that are crucial to innovation in many fields. - While many agree on the need to improve teaching, moves to increase the number of teaching hours are among the most strongly contested reforms. French academics, who very rarely have sabbaticals, already perceive themselves as overworked in a system where time for research is increasingly scarce. These factors help to explain the resistance to expanded classroom hours and new administrative duties. In the longest strike ever organised by the French scientific community, tens of thousands of lecturers and researchers began in early February to hold protests over a period of several weeks, demonstrating in the streets and (with the support of some students) blocking access to some university campuses. Many also participated in a national debate via print, online and broadcast media, and in general meetings. Some faculty members held teach-ins and action-oriented “alternative courses” for students. Several universities saw their final exams and summer holidays delayed and many foreign exchange students were called back by their home institutions. Despite this frontal assault, the Government did not back down: the much disparaged decree reorganising academic careers (with regard to recruitment, teaching loads, evaluations and promotions) and giving more prerogatives and autonomy to university presidents came into effect on 23 April. This outcome will probably lead academics and their unions to rethink their strategies and repertoires of collective action. The traditional protest forms are losing legitimacy. As the dust settles, it is becoming clear that demonstrating has little traction in a context where the French public increasingly perceives academics as an elite bent on defending its privileges, even if it requires depriving students of their courses. Negotiation is also perceived as ineffectual, as many suspect that governmental consultations were conducted to buy time until the end of the academic year, when mobilisation would peter out. A third strategy—the radical option that would have prevented the scheduling of exams and the handing out of diplomas at the end of this spring—was ruled out even on the campuses most committed to the cause for fear of alienating the public even further. As yet, however, no clear alternative has surfaced. We are now witnessing a cleavage between those who voice their opposition (in the main, scholars in the humanities) and the increasing number of academics (primarily scientists) who espouse a “wait-and-see” or a collaborative position as the only realistic path to improving the situation in their own universities. If the majority of academics appear to share the same diagnosis about what needs to be changed in the French system, they disagree on the solution (and on its scale—national or local). The root of the crisis lies not only in the Government's difficulties in generating consensus, but also in the academics' own scepticism, cynicism or fatalism about meritocracy, the absence of the administrative resources needed to support proper evaluation, the possibility of impartial evaluation, and the system's ability to recognise and reward merit. Deep problems remain in the institutions charged with evaluating the work of academics. The interference of political power, and the (admittedly diminishing) influence of trade unions and corporatist associations have long been viewed as obstacles to a collegial system of academic evaluation. The legitimacy of the 70 disciplinary sections of the Conseil National des Universites (CNU)—charged with certifying individuals as eligible for faculty positions, and with directly granting some promotions—is under question. Some of its committee members are appointed by the Government and as such are suspected of being second-rate, of benefiting from governmental patronage, or of defending governmental interests. Others are chosen from electoral lists that include a disproportionate number of partisan members, who are often perceived to be there because of their political involvement rather than because of their scientific status. The legitimacy of these committees is further called into question because they include only academics employed by French institutions and are often viewed as perpetuating a longstanding tradition of favouritism. To give only one particularly scandalous example: in June, panellists in the sociology section allocated to themselves half of the promotions that they were charged with assigning across the entire discipline of sociology. This led to the resignation of the rest of the commission and to multiple protests. Such an occurrence sent deep waves of distrust not only between academics, but also towards the civil servants charged with reforming a system that is increasingly viewed as flawed. Peer review is also in crisis at the local level. While selecting young doctoral recipients to be maîtres de conférences (the entry level permanent position in the French academy, similar to the British lecturer), French universities on average fill 30 per cent of available posts with their own graduates, to the point where local clientelism is often decried as symbolising the corruption of the entire system. The typical (and only) job interview for such a post lasts 20 to 30 minutes—probably the European record for brevity and surely too short to determine whether an individual deserves what is essentially a lifelong appointment. Many view the selection process as little more than a means to legitimise the appointment of pre-selected candidates—although the extent to which this is genuinely the case varies across institutions. What is to be done? Because both the CNU and the local selection committees have recently been reorganised or granted new responsibilities, it seems the right moment to think about how to improve the evaluation processes in very practical ways. As part of a new start, academics should aim to generate a system of true self-governance at each level, grounded in more explicit principles for peer review. This would put them in a position to defend academic autonomy against the much-feared and maligned governmental or managerial control. While this is certainly occurring in some disciplines and institutions, progress is far from being equally spread across the sector. Obvious and costless regulatory measures could easily be implemented—for instance, discouraging universities from hiring their own PhD graduates (as AERES recently started to), or forbidding selection committees from promoting their own members. One could also look abroad for examples of “best practice”. The UK's Economic and Social Research Council has created colleges of trained academic evaluators who are charged with maintaining academic and ethical standards in peer review; although not all aspects of the British approach to academic reform should be emulated, this one is particularly worthy. The Deutsche Forschungsgemeinschaft (German Research Foundation) uses teams of elected experts to evaluate proposals, and academic reputation weighs heavily in determining which names will be put on electoral lists and who will serve on evaluation panels. Canada's Social Sciences and Humanities Research Council recently asked an independent panel of international experts to evaluate its peer review process in order to improve impartiality and effectiveness. In a recent book on peer review in the US, one of the present authors (Michele Lamont) showed the ways in which American social scientists and humanists operate to maintain their faith in the idea that peer review works and that the academic system of evaluation is fair. In this case, academics exercise their right as the only legitimate evaluators of knowledge by providing detailed assessment of intellectual production in light of their extensive expertise in specialised topics. The exercise of peer evaluation sustains and expresses professional status and professional autonomy. But it requires significant time (and thus good working conditions) and moral commitment—time spent comparing dossiers, making principled decisions about when it is necessary to withdraw on the grounds of personal interest, and so forth. Of course no peer review works perfectly, but US academics, while being aware of its limitations, appear to view the system as relatively healthy and they engage in many actions that contribute to sustaining this faith. In our view, fixing the current flaws in the French system does not merely demand organisational reforms, including giving academics more time to evaluate the research of colleagues and candidates properly. It may also require French academics to think long and hard about their own cynicism and fatalism concerning their ability to make judgments about quality that would not be driven by cronyism or particularism, and that would honour their own expertise and connoisseurship. Not that proper governmental reform is not needed, but sometimes blaming the Government may be an easy way out. Above all, it is increasingly a very ineffectual way of tackling a substantial part of the problem. A little more collaborative thinking and a little less cynicism among both academics and administrators—if at all possible - may very well help French universities find a way out of the crisis. And it will help the French academic and research community to become, once again, much more than the sum of its parts.

How Joblessness Hurts Us All - Putnam, Robert D.; Sander, Thomas H. (USA Today, 2009)
<intro> The unemployment rate has topped 10% for the first time in a quarter-century. More than one in six adults are unemployed or underemployed, the most since the <kwd gen="auto" title="More news, photos about Great Depression">Great Depression. By any measure this is troubling, but the long-term effects of unemployment are more devastating than most Americans grasp. Economists warn that high unemployment may persist for years.</kwd> </intro> Misery, it turns out, doesn't love company. Distressing new research shows that unemployment fosters social isolation not just for the unemployed but also for their still-employed neighbors. Moreover, the negative consequences last much longer than the unemployment itself. Policymakers have focused on short-term help for the jobless, but they must address these longer-term community effects, too. Impact studied Recent studies confirm the results of research during the Great Depression— unemployment badly frays a person's ties with his community, sometimes permanently. After careful analysis of 20 years of monthly surveys tracking Americans' social and political habits, our colleague Chaeyoon Lim of the University of Wisconsin has found that unemployed Americans are significantly less involved in their communities than their employed demographic twins. The jobless are less likely to vote, petition, march, write letters to editors, or even volunteer. They attend fewer meetings and serve less frequently as leaders in local organizations. Moreover, sociologist Cristobal Young's research finds that the unemployed spend most of their increased free time alone. These negative social consequences outlast the unemployment itself. Tracking Wisconsin 1957 high school graduates, sociologists Jennie Brand and Sarah Burgard found that in contrast to comparable classmates who were never unemployed, graduates who lost jobs, even briefly and early in their careers, joined community groups less and volunteered considerably less over their entire lives. And economist Andrew Clark, psychologist Richard Lucas and others found that, unlike almost any other traumatic life event, joblessness results in permanently lower levels of life satisfaction, even if the jobless later find jobs. Equally disturbing, high unemployment rates reduce the social and civic involvement even of those still employed. Lim has found that Americans with jobs who live in states with high unemployment are less civically engaged than workers elsewhere. In fact, most of the civic decay in hard-hit communities is likely due not to the jobless dropping out, but to their still-employed neighbors dropping out. Moreover, beyond civic disengagement, places with higher joblessness have more pervasive violence and crimes against property. They have more fragile families with harsher parenting, and higher rates of mental disorder and psychological distress among both the unemployed and the employed. These social consequences are a powerful aftershock to communities already reeling economically. What might explain the civic withdrawal during recessions? The jobless shun socializing, shamed that their work was deemed expendable. Economic depression breeds psychological depression. The unemployed may feel that their employer has broken an implicit social contract, deflating any impulse to help others. Where unemployment is high, those still hanging onto their jobs might work harder for fear of further layoffs, thus crowding out time for civic engagement. Above all, in afflicted communities, the contagion of psychic depression and social isolation spreads more rapidly than joblessness itself. What to do? The lasting social consequences of unemployment demand remedy. President Obama has extended individual unemployment benefits.These new findings call for special aid to communities with high and persistent unemployment. Government and business should ensure that unemployment is a last cost-cutting move, not the first. Millions of employed Americans are silently thankful that the sword of Damocles has not yet fallen on them. Meanwhile, they and their leaders overlook the fact that unemployment is causing long-run social disintegration in their communities. <kwd gen="auto" title="More news, photos about Albert Camus">Albert Camus was right: “Without work, all life goes rotten.”</kwd>

A Job Too Big for One Man - Patterson, Orlando (New York Times, 2009)
IN the year since his election, as he has since he first appeared on the national stage, Barack Obama has embodied the fundamental paradoxes of race in America: that we live in a still racially fragmented society; that we share a public culture with an outsized black presence, but that in the privacy of homes and neighborhoods we are more segregated than in the Jim Crow era; that we worship more fervently than any other advanced nation, in churches and synagogues that define our separate ethnic identities and differences, to gods proclaiming the unity of mankind. Why are we this strange way? Is President Obama the ultimate expression of our peculiarities? Has he made a difference? Can he? Will he? We became this way because of the peculiar tragedies and triumphs of our past. Race and racism scar all advanced nations, but America is peculiar because slavery thrived internally and race became a defining feature of personal identity. Slavery was quintessentially an institution of exclusion: the slave first and foremost was someone who did not belong to and had no claims on the public order, nor any legitimate private existence, since both were appropriated by the slaveholder. The Act of Emancipation abolished only the first part of slavery, the master’s ownership; far from removing the concept of the ex-slave as someone who did not belong, it reinforced it. The nightmare of the Jim Crow era then extended and reinforced the public slavery of black Americans right up through the middle of the 20th century. At the same time, the status of blacks as permanent outsiders made whiteness a treasured personal attribute in a manner inconceivable to Europeans. Whiteness had no real meaning to pre-immigration Swedes or Irishmen because they were all white. But it became meaningful the moment they landed in America, where it was eagerly embraced as a free cultural resource in assimilating to the white republic. In America race had the same significance as gender and age as defining qualities of personhood. The great achievement of the civil rights movement was to finally abolish the lingering public culture of slavery and to create the opportunities that fostered the black middle class and black political leadership. This was a sea change. But Mr. Obama, by virtue of his unusual background as a biracial child reared by loving, though not unprejudiced, white caregivers, is acutely aware that the crude, dominating racism of the past simply morphed into a subtler cultural racism of the private sphere—significantly altered though hardly less damaging. Seeing blacks as culturally different—a perception legitimized by the nation’s celebration of diversity and identity—permits all kinds of complicated attitudes and misjudgments. Their differences can be celebrated on playing fields, dance floors and television, in theaters, hip-hop and cinema, and not least of all in that most public and ambivalently regarded arena of mass engagement: politics. But in the disciplined cultural spaces of marriages, homes, neighborhoods, schools and churches, these same differences become the source of Apollonian dread. What then can we expect of Mr. Obama? One thing we can be sure of is that he will not be leading any national conversations on race, convinced as he must be that they exacerbate rather than illuminate. During the campaign last year he spoke eloquently on the subject, but only when he was forced to do so by the uproar over the Rev. Jeremiah Wright. And since he took office, his one foray into racial politics—his reaction to the arrest of Henry Louis Gates Jr.—was a near political disaster that must have reinforced his reluctance. Mr. Obama’s writings, politics and personal relations suggest instead that he prefers a three-pronged strategy. First, he is committed to the universalist position that the best way to help the black and Latino poor is to help all disadvantaged people, Appalachian whites included. The outrage of black over-incarceration will be remedied by quietly reforming the justice system. Second, Mr. Obama appears convinced that residential segregation lies at the heart of both black problems and cultural racism. He is a committed integrationist and seems to favor policies intended to move people out of the inner cities. Third, he clearly considers education to be the major solution and has tried to lavishly finance our schools, despite the fiscal crisis. More broadly, he will quietly promote policies that celebrate the common culture of America, emphasizing the extraordinary role of blacks and other minorities in this continuing creation. At the same time, Mr. Obama seems to believe that the problems of black Americans are in part attributable to certain behaviors among them—most notably absentee fathers, dropping out of school and violence—which not only constrain their choices but rationalize the disfiguring processes of white cultural racism that extend the pathologies of the few to all black Americans. As a deeply committed family man, Mr. Obama has already made clear that he will use the bully pulpit of the presidency to encourage internal cultural reformation. All of these approaches are likely to alienate the identity-seeped segment of black leadership, and they will not prevent the extreme cultural right from accusing him of overplaying race, whatever he does. The uniqueness of Mr. Obama provides both obstacles and opportunities. My students have found that many young inner city blacks, while they admire him, find him too remote from their lives to be a role model. His policies, if properly carried out, might very well improve their chances in life, but in the end he is more likely to influence the racial attitudes of middle-class blacks and younger white Americans. This is all we can reasonably expect. It will take far more than a single presidency to fully end America’s long struggle with race.

State of the Union - Varshney, Ashutosh (Indian Express, 2009)
The emerging security debate on the first anniversary of the Mumbai attacks has neglected a vital constitutional question. Does federalism by any chance weaken India’s counter-terrorism effort? Without considering the relationship between federalism and national security, we will not understand the underlying factors driving India’s counter-terrorism effort. The nation’s centre-state laws and practices are a principal obstacle in developing a stronger response. If not addressed imaginatively, Mumbai-style attacks simply cannot be ruled out. Scholars of comparative federalism generally call India’s linguistic federation a spectacular institutional success. One of the greatest indicators of the success is the disappearance of language riots, common in the 1950s and 1960s, after the linguistic reorganisation of states was completed. But for all its successes, India’s federalism now faces a new and extremely serious challenge. <!--google --> Central to India’s internal security are three laws and practices. First, according to India’s Constitution, internal law and order are entirely on the so-called “state list”, not on the “Central list” or “concurrent list”. Only under President’s rule can Delhi take over the internal security of a state. “Federal crime” is not a concept in Indian law, as is it in the US, and it cannot be introduced unless the Constitution is amended. Its relevance has been debated within government circles since the late 1960s, but the idea of federal crimes remains legally elusive. Even when the Indian Airlines flight from Kathmandu was diverted to Kandahar in December 1999, leading to India’s external affairs minister agreeing to a humiliating agreement that released well-known terrorists from Indian jails in return for the safety of passengers, the case was not, and could not be, registered as a federal crime. Indian Airlines reported to Delhi police that its plane, due to arrive in Delhi, was missing. “Hamaara hawaai jahaaz nahin aayaa”. It was registered as a Delhi-based crime. Second, Central agencies—including the national security guards (or commandos), who are especially trained for urban terrorism—simply cannot function without the cooperation of state police. Requisition from state governments is legally required before the commandos can be used. India’s commandos were all based in Delhi when Mumbai was terrorised. After Mumbai, hubs have been created in Hyderabad, Chennai, Kolkata and Mumbai. As a consequence, they can be deployed more quickly, but for operations, they still need the assistance of state police. NSG commandos have no knowledge of local specificities. State police remains the greatest repository of ground-level intelligence in India. Third, all serious students of terrorism recognise that intelligence is central to the prevention of terrorism. Since terrorists are willing to sacrifice their lives, one can only try to minimise damage, not avoid it, once the act of terror has begun. Unfortunately, India’s intelligence system is fractured and weak. The Central Bureau of Investigation (CBI), the institution often identified as the leading intelligence agency of India, is most unlike America’s Federal Bureau of Investigation (FBI). In contrast to the FBI, which combines intelligence and investigation functions, the CBI is primarily an ex-post investigation body, not an intelligence collecting agency. For the latter, it depends primarily on state police, and secondarily on Delhi’s Intelligence Bureau (IB). The CBI was established under the Delhi Special Police Establishment Act, 1946. Its direct jurisdiction covers Delhi and the centrally administered Union Territories. Unlike the FBI, it can not pursue investigation at the state level on its own. To investigate, it must receive state requisition or consent, or be ordered to do so by the Supreme Court or a High Court. In other words, for it to function well, it depends heavily on state police. It can also team up with Delhi’s Intelligence Bureau (IB), but the IB reports to India’s home ministry, whereas the CBI reports to the ministry of personnel. The cooperation is not always forthcoming. More importantly, the IB simply does not have the same intelligence-gathering machinery as the state police does. State governments have the constitutional right to deny permission for CBI investigations. Goa, for example, did so during the late 1990s. Maharashtra did not hand over cases concerning the Mumbai blasts of 1993 to the CBI for almost a year. Northeastern states have often denied permission to the CBI. At the root of this problem is the dark underbelly of Indian politics: corruption and vendetta. The CBI is not trusted by state leaders for they believe it is politically used by Delhi to target adversaries. The adversaries may be accused of corruption, or even violent crime. It does not matter that such corruption or criminal conduct may often be real, not imagined. But over the last 20-30 years, as politicians accused of crime and corruption have, in particular, risen in politics, the CBI has been caught in a political crossfire. Delhi often wants to use it, but the CBI faces enormous resistance at the state level, especially if the state government is run by a coalition or political party different from that ruling in Delhi. So long as the Congress party ruled both in Delhi and the states, there was no such resistance. Such matters were handled as internal negotiations within the party. Moreover, in the 1950s and 1960s, the era of Congress dominance, no one had imagined the possibility of terror, let alone cross-border terror. The rise of a coalitional era might have made Indian politics much more democratic, federal and competitive, but national security has suffered as a consequence. Although this problem cannot be fully resolved unless corruption and crime begin to disappear from Indian politics, India’s political process has thrown up a potential solution. Via a Parliamentary act, a National Investigation Agency (NIA) was created after the Mumbai attacks. In theory, the NIA can become India’s FBI, but serious impediments remain. The NIA Act was created using an entry related to defence of India on the Central list. Of all security matters, only defence of India is handled by Delhi. What is generally called internal, as opposed to external, security is almost entirely under state jurisdiction. The NIA Act is not a constitutional amendment, which would have required approval of two thirds of Parliament and half the states, not easily possible in a coalitional era. The concept of a federal crime, requiring a constitutional amendment, has still not been introduced precisely for the same reason. States would not give consent if they believe that the NIA might become a much more powerful CBI. The NIA does not yet have an elaborate organisational structure of its own. And that may not happen until two conditions are satisfied. First, if more Mumbai-style attacks happen, it is possible for security to become an overriding national objective that no political party can ignore without peril. Thus far, terrorism is an element in India’s elite politics, not in its mass politics. It does not determine election outcomes. Second, if the Congress party, currently showing signs of revival, becomes even stronger, both in national Parliament and at the state level, it would also allow the possibility of a constitutional amendment. The first condition is not desirable, the second somewhat improbable, if not impossible, at the moment. India’s home minister is well known for his intellectual firepower, but his hands are tied. He can only do the following: modernise the intelligence system through new technologies; try to generate a better knowledge system—for example, a national counter-terrorism centre—that supports national security; create institutions that seek to coordinate the rather fractured intelligence. State governments might also create their own commando forces, as Maharashtra appears to be doing and Andhra did some years back. All of these measures would help, but the home minister cannot legally force a state government to accept the dictates of the NIA unless a constitutional amendment introducing the concept of federal crime is put through. However desirable such a concept in the 21st century might be, India’s federal polity will not easily allow it to come about.

In Afghanistan, Kerry Keeps US Goals Modest - Allison, Graham T., Jr. (Boston Globe, 2009)
PRESIDENT OBAMA confronts the most fateful foreign policy decision so far of his administration. Rapidly deteriorating security in Afghanistan, the post-election political crisis in Kabul, highlighted by Abdullah Abdullah’s decision to drop out of the runoff vote, and General Stanley McChrystal’s request for 44,000 troops rightly spurred Obama to call a timeout for reflection. Over the past eight weeks, in a process with little precedent in American presidential decision-making, the president and his advisers have held more than a half-dozen no-holds-barred seminars examining and reexamining every dimension of this challenge. Reduced to a single bottom line, Obama must decide whether to accept the recommendation of his chosen military commander in the field to Americanize this war. McChrystal’s call for more troops would expand US forces in Afghanistan to more than 100,000 in order to execute what he terms a “classic counterinsurgency campaign.’’ Meanwhile, Senator John Kerry, chairman of the Senate Foreign Relations Committee, delivered a major speech last week summarizing his own analysis of the issue and offering advice about the president’s choices. The judgments are nuanced, but no more so than the realities. On the bottom line question - yes or no on McChrystal’s request—Kerry says no. He argues that McChrystal reaches “too far, too fast.’’ Kerry recommends that further troop increases must meet three conditions: reliable Afghan troops to partner with American forces, local political leaders, and civilian advisers to speed development. Truth be told, none of these three will be in place soon. Kerry’s analysis begins with the most important consideration: US national interests. What should Americans care about here? What matters more than other things that matter? Kerry says: Pakistan—not Afghanistan. His focal question about Afghanistan is how developments there impact Pakistan. Over the past months he has led efforts to spotlight the anomaly that allocates 30 times more American time and resources to Afghanistan when our much larger interests lie in Pakistan. Thanks to his efforts with Senator Richard Lugar, the United States has committed $7½ billion over five years to help stabilize this nuclear-armed nation at risk of becoming the “epicenter of extremism in the world.’’ Second, what are America’s vital interests in Afghanistan? Kerry answers that it is to “prevent the Taliban—with their long-standing ties to Al Qaeda—from once again providing terrorists with an unfettered Afghan safe haven.’’ Period. Note what this sparse summary does not include: nation-building of a stable centrally-governed Afghanistan. Like all Americans, Kerry applauds the progress Afghanistan has made in becoming more democratic, expanding rights for women, building schools. None of these, however, is included in his minimum essentials for success. Third, he defines success as “the ability to empower and transfer responsibility to Afghans as rapidly as possible and achieve a sufficient level of stability to ensure that we can leave behind an Afghanistan that is not controlled by Al Qaeda or the Taliban.’’ He does not say an Afghanistan in which some Taliban are not ruling in some areas. Fourth, he rejects “all-in’’ counterinsurgency. In its place he recommends “smart counterinsurgency,’’ the crux of which is “limited geographic area…as narrowly focused as possible.’’ Counterinsurgency’s central objective is to “foster development of effective governance by a legitimate government.’’ In contrast, the strategy Kerry recommends could be achieved by “good enough’’ stability in Kabul and the major population centers of a minimalist state cooperative enough to rent bases and supply lines, provide an operating environment for attacks against Al Qaeda, and assist with intelligence gathering. Kerry’ advances the argument by distinguishing between the vivid and the vital, lowering ambitions to “what is achievable, measured against the legitimate interests of the United States’’ and outlining a strategy to that end. It is a speech that the president should, and no doubt will, examine closely. Graham Allison is director of the Belfer Center for Science and International Affairs at Harvard’s John F. Kennedy School of Government and author of “Nuclear Terrorism: The Ultimate Preventable Catastrophe.’’

A Fairer Credit Card? Priceless - Bubb, Ryan; Kaufman, Alex (New York Times, 2009)
Industry representatives would have you believe that the Credit Card Accountability, Responsibility and Disclosure Act enacted last month spells the end of the credit card as we know it. President Obama’s proposal last week to create a Consumer Financial Protection Agency to enforce the law has increased the industry’s concerns. But the example of cards issued by credit unions puts the lie to these claims. Credit unions largely conform to the new rules already, while profitably maintaining the basic features that users know and love. The credit card act is under fire for limiting a number of fees commonly used in credit card contracts, like the charge for going over the credit limit and the increased interest rate that applies once a borrower has missed a payment. These changes might look like a boon for the average card user, but industry advocates claim that fees on delinquent borrowers subsidize the perks for those who pay on time. Take away the lucrative fees, the argument goes, and credit card issuers will be forced to ax free plane rides, slash generous credit limits and impose hefty annual dues for all. Some in the industry even say that profitability would require issuers to charge interest from the moment of purchase, thus eliminating the grace period of interest-free lending that borrowers have long enjoyed. These fears are largely unfounded. We have performed a study that compared credit cards issued by investor-owned banks to those issued by customer-owned credit unions. We found that credit unions are less likely to charge the fees and penalties that the new act hopes to eliminate — and when they do, they charge less than other issuers. While virtually all banks and other for-profit issuers increase the interest rate if the borrower fails to make a minimum payment on time, most credit unions do not. Similarly, credit union fees for exceeding the credit limit are on average just half those of other issuers. But contrary to industry assertions, more responsible card users don’t pay the price. Credit union cards actually offer lower annual fees and longer grace periods than regular cards. Is the lending model used by credit unions feasible for banks and other issuers? Absolutely. Banks and credit unions compete for customers in the same market. The primary distinguishing characteristic of credit unions is that they answer to a different group of owners: profits that are not reinvested are paid to the union’s shareholder-customers as a dividend, much as investor-owned banks reinvest or pay dividends to their shareholder-investors. True, unlike typical banks, credit unions have the advantage of being exempt from corporate income taxes, thus some might argue that this gives them an edge. But this is a proportional tax on profits. In other words, if credit unions were not exempt from the tax, their model would still make profits, they would just retain less of them. Credit union cards are a great test case for how regular cards will perform under the new law. The evidence so far suggests that the credit card act is likely to bring about moderate, and even positive, changes. Card issuers, after all, need to retain customers. Any bank that attempts to pad its bottom line by, say, levying large annual fees will likely see its customers flee to credit unions or to banks that emulate the credit union model. To be sure, the new law will require some sacrifices. Our data indicate that rewards programs, for example, may become less generous or less common. But is this necessarily a bad thing? While you may be reluctant to sacrifice your airline miles, rewards programs are anything but free for the nation as a whole. Debt-laden and often low-income borrowers tend to pay high fees to subsidize the vacations of those who manage to pay on time. Credit union cards demonstrate that punishing fees are not an essential ingredient of profitable lending. This should help assuage fears that the credit card act will bring disaster for credit cards. Rather, it should nudge them toward the gentler credit union model that many Americans already enjoy.

Hello from Havana: Nuanced but unmistakable stirrings of change in Cuba - Domínguez, Jorge I. (Harvard Magazine, 2009)
President Raúl Castro’s principal contribution thus far to the lives of ordinary Cubans has been that television soap operas now start on time. He often reminds his fellow citizens of this seemingly impossible accomplishment, after decades during which his elder brother commanded the airwaves and disrupted all public and personal schedules. But he alluded to this achievement most cleverly last December, prompting laughter with the opening sentence of his remarks before a summit meeting of the presidents of the Latin American countries in Bahia, Brazil, hosted by Brazilian president Luiz Inácio Lula da Silva. According to Cuba’s official press reports, Castro began, “I hope that our colleague and dear friend Lula will not complain because I give shorter speeches than Chávez’s.” The presidential summit was one stop on Raúl Castro’s first international trip since becoming Cuba’s acting president in August 2006 (when Fidel Castro was rushed to the hospital), and in that one sentence, he made several points. To most of the Latin American presidents, who did not know him well, and indeed to his fellow Cubans, he demonstrated that even a 78-year-old General of the Army could have a sense of humor. To the same audiences, but also to the incoming Obama administration, he demonstrated some distance and independence from Venezuela’s president, Hugo Chávez, notwithstanding the tight economic and political bonds between their two countries. This was only the most recent and most public instance of Raúl Castro’s reiterated mocking comparison between Chávez’s propensity to speak forever and his own much shorter and self-disciplined speeches. (Of course, all those in the audience also knew that he was poking fun not just at Chávez but at his brother, who never met a time limit he did not despise.) And, finally, he highlighted, especially for his own people, that he honors and respects the time of others. Raúl Castro’s military style of life cherishes punctuality and efficiency. Schedules, all schedules, even those for TV telenovelas, should be observed. Even during the waning moments of Fidel Castro’s rule, the time of Cubans was frequently occupied by marches, mobilizations, and the need to listen to the logorrheic Maximum Leader. There was even a cabinet minister in charge of what Fidel Castro called the “Battle of Ideas.” Now, marches occur on designated public holidays. And the minister in charge of the Battle of Ideas lost his job in March--and his ministry was disbanded. Economic Evolution The nuances in Cuban public life since Raúl became president in his own right in February 2008 are evident as well in the enactment of economic-policy reforms that were rolled out immediately following his formal installation. Consider some examples. Previously, Cubans had not been able to stay at hotels or eat at restaurants designed for international tourists, even if they had the funds to pay, unless they were on official business; now they were given access to all these facilities, so long as they could pay. Cubans had also been prohibited from purchasing cell phones and subscribing to such services unless officially authorized to do so. They were not allowed to purchase computers or DVD players. Now they were able to purchase such products so long as they had the funds. How the Cuban government adopted these changes is important. It could simply have announced a general deregulation of prohibitions regarding purchases of consumer durables, for example. Instead, the government made each of these announcements separately: one week you could stay at tourist hotels, the next week you could purchase a computer, the following week you could obtain cell-phone services, and so forth. The government even announced that some products would be deregulated for purchase in 2009 (air conditioners) or 2010 (toasters). This method of deregulating implied a desire to win political support over time, not all at once. It communicated that the government retained the right to micromanage the economy, deregulating product by product and service by service. The government also signaled that it expected to remain in office for years to come, behaving in the same way. Finally, most Cubans knew that they could have been purchasing these same consumer durables all along, albeit only on the black market. Thus the policy of postponed deregulation implied an official tolerance of some current criminality (knowing that some Cubans would buy toasters illegally in 2008, instead of waiting for 2010), because the government valued its economic micromanagement more. Whom the government sought to benefit was equally newsworthy. In its most revolutionary phase, during the 1960s, the Cuban government adopted strongly egalitarian policies. Many Cubans came to believe in egalitarian values and resented the widening of inequalities in the 1990s. Consider, then, Raúl’s reforms. Hotels and restaurants designed for international tourist markets are expensive; so, too, are computers and DVD players. When these economic changes were announced in 2008, the median monthly salary of Cubans amounted to about $17: that is, the average monthly salary was below the World Bank’s worldwide standard for poverty, which is one dollar per day. To be sure, Cubans had free access to education and healthcare and subsidized access to some other goods and services. Nevertheless, only a small fraction of Cubans could take advantage of these new economic policies, because the purchases of such consumer durables and the access to such tourist services had to be paid for in dollar-equivalent Cuban currency at dollar-equivalent international prices. (Cuba has two currencies; the peso convertible is a close equivalent to the dollar, whereas the peso is worth about $0.04.) Raúl’s government was appealing to the upper-middle-class professionals. Making Difficult Decisions I have emphasized Raúl’s penchant for humor and nuance because Washington and Miami have not taken much notice of these traits. At the same time, no one should underestimate his capacity for decisiveness. A salient feature in his biography is his long-standing role as Cuba’s equivalent of a chief operating officer. President Fidel Castro made the decision to dispatch some 300,000 Cuban troops to two wars in Angola and one in Ethiopia from the mid 1970s to the early 1990s, but it was Minister of the Revolutionary Armed Forces and General of the Army Raúl Castro whose officers recruited, trained, promoted, equipped, and steeled these armies for battle. The United States lost the war in Vietnam. The Soviet Union lost the war in Afghanistan. Cuban troops won the three African wars in which they fought. Cuba’s was the only communist government during the entire Cold War that successfully deployed its armed forces across the oceans. And the “worker bee” for those victories was Raúl. Within the first calendar year of his presidency, Raúl gave another example of this decisiveness: the reform of Cuba’s pension laws. Cuban law authorized and funded the retirement of women at age 55 and of men at age 60. In December 2008, the retirement ages were raised to 60 and 65 respectively. The speed of the change signaled as well a key difference between the Castro brothers. It had long been a matter of public record that Cuban life expectancy had lengthened to reach the levels of the North Atlantic countries. Cuban demographers had also faithfully recorded that Cuba has been below the population replacement rate since 1978. They had developed various forecasts that showed that its population would age rapidly, creating a vast problem of pension liabilities, and then decline. The demographers committed only one error: they expected the demographic decline to set in near the year 2020, but the population has already declined (net of emigration) in two of the last three years. Notwithstanding this abundance of information, Fidel chose not to act. The fiscal crisis of the state was much less fun than leading street marches to denounce U.S. imperialism. But Raúl’s prompt and effective change of the pension laws, making use of information supplied by social scientists, is yet another illustration of the difference between the brothers as rulers. And, of course, the one obvious change that was not made to the pension laws demonstrates as well that even a powerful government senses some limits to its power: although the life expectancy of women is longer, the pension reform retained the lower retirement age for them. Raúl Castro doesn’t dare take a perk like early retirement away from Cuban women. Political Authoritarianism The Castro brothers’ styles of rule of course show important similarities on matters that do and should matter in assessing their political regime. Cuba remains a single-party state that bans opposition political parties and independent associations that may advance political causes. The government owns and operates all television and radio stations, daily newspapers, and publishing houses. The number of candidates equals the number of seats to be filled in elections for the National Assembly. The constraints on civil society remain severe, even if there has been since the early 1990s a somewhat greater margin of autonomy for communities of faith, some of which (including Roman Catholic archdioceses) are permitted to publish magazines. The two brothers have also demonstrated a strong preference for ruling with a small number of associates whom they have known for many years. For example, when Raúl became president formally in February 2008, he had the right to make wholesale changes in the top leadership. Instead, the president and his seven vice presidents had a median birth year of 1936. Raúl went a step further. He created a small steering committee within the larger Political Bureau of the Communist Party--and the members of the new committee were the exact same seven. Raúl’s buddies are the gerontocrats with whom he chooses to govern. Yet there are stirrings of change. Although National Assembly elections are uncompetitive, they provide a means to express some opposition to the government. The official candidates are presented in party lists; each voting district elects two to five deputies from those lists and the number of candidates equals the number of posts to be filled in that district. The government urges voters to vote for the entire list, but voters have been free to vote for some but not all candidates on the list, thereby expressing some displeasure. The number of nonconforming voters (voted blank, null, or selectively) exceeded 13.4 percent of the votes cast in the most recent (January 2008) National Assembly elections--1.1 million voters. Both the percentage and the number of nonconforming voters were slightly larger than in the 2003 election, with the largest expression of nonconformity recorded in the province named City of Havana. Yet another sign of change arises from Raúl’s own family. His daughter, Mariela Castro, has been for some years the director of Cuba’s center for the study of sexuality. This center has been principally known, however, for its advocacy for, and defense of, the rights of homosexuals, including special training for Cuban police officers, formulating changes in regulations, and disseminating information designed to create safer spaces for homosexuals. From the 1960s to the 1980s, the Cuban government pursued very harsh policies toward homosexuals. In the early stages of the HIV/AIDS epidemic in the 1980s, those who tested HIV-positive were automatically compelled to enter a quarantined facility at the cost of their jobs and family lives. At the time of the Mariel emigration crisis in 1980, the government activated its affiliated mass organizations to make life impossible for homosexuals, fostering their emigration under duress. And in the mid 1960s, the government had established the “military units to aid production” (UMAP). These were concentration camps to which “social deviants,” mainly but not exclusively male homosexuals, were sent to be turned, somehow, into “real men.” The commander in chief of the UMAP was, of course, Armed Forces Minister Raúl Castro. It is unlikely that Raúl is a closet liberal, though there is evidence that he has been a loving father. It is not impossible, however, that he regrets having served as an architect of repression over the lives of many Cubans--not just homosexuals--especially in the 1960s, but also at other times. His daughter’s work during the current decade may be an instrument for elements of social liberalism. U.S.-Cuban Relations Raúl Castro understood earlier than his brother that the collapse of the Soviet Union and European communist regimes implied that Cuba had to change more and faster than Fidel wanted. In 1994, in the most public difference yet between the brothers, Raúl favored liberalizing agricultural markets, allowing producers to sell at market prices, even though Fidel remained opposed. Raúl showed more sustained interest in the economic reforms of China and Vietnam than did Fidel. And by the late 1990s, Raúl began to give the speech that he has now repeated many times, most notably this April in response to the Obama administration’s beginning of changes in U.S.-Cuba policies (authorizing Cuban Americans to travel and send remittances to Cuba): his government is ready to discuss anything on the U.S. government agenda. In January 2002, Raúl even praised the Bush administration for having given advance notice of the incarceration of Taliban prisoners at the U.S. base at Guantánamo Bay. He also praised the professional military-to-military cooperation between the two countries’ officers along the U.S. base’s boundary perimeter, as well as between the coast guards in the Straits of Florida. In August 2006, his first public remarks upon becoming acting president made just two points: he did not much like to speak in public, and he was ready to negotiate with the United States. And this April, he took the time to make it clear that negotiating with the United States about any topic did, indeed, include discussion about political prisoners in Cuban jails. He made a specific proposal to exchange such political prisoners (estimated by Cuban human-rights groups as between 200 and 300 people) for five Cuban spies in U.S. prisons. The Context for Change The pace of political and economic change in Cuba has been slow by world standards. But the pace of social change has been very fast. Cuba’s people live long lives, thanks in part to good, albeit frayed, healthcare services--free of charge. Cuban children go to school and many become professionals. Indeed, Cuba’s principal area of export growth is the provision of healthcare services to the people of other countries. Until this most recent development, however, Cuba had exemplified how a half-century of investment in human capital could generate very poor economic-growth returns. Yet Cubans since the early 1990s have demonstrated entrepreneurial capacities in creating small businesses, whenever the government has permitted them, suggesting that with better economic incentives there could be a productive combination that would lead to economic growth. Cubans can talk seemingly endlessly at officially sponsored meetings, yet they demonstrate in other settings a capacity for insight, criticism, and imagination that could readily contribute as well to much faster political transformation. U.S. policy toward Cuba for the bulk of this past decade has assisted the Castro government’s state security in shutting out information from the outside world: the United States banned the shipment of information-technology products, instead of facilitating Cuban electronic access to the world, and allowed Cuban Americans to visit their relatives only once every three years, instead of enabling cousins from both sides of the Straits of Florida to speak face to face about how a different, better Cuba might be constructed. (The United States has even protected ordinary Cubans from the Harvard Alumni Association, which could not lead tour groups there.) Perhaps the United States will stop being an obstacle to change in Cuba during the century’s second decade.

An IMF We Can Love? - Rodrik, Dani (Business Standard, 2009)
What a difference the crisis has made for the International Monetary Fund. It was just a few months ago that this important but unloved institution, a landmark of post-war global economic arrangements, seemed destined to irrelevance. The IMF has long been a whipping boy for both left and right—the former because of the Fund’s emphasis on fiscal rectitude and economic orthodoxy, and the latter because of its role in bailing out indebted nations. Developing nations grudgingly took its advice, while advanced nations, not needing the money, ignored it. In a world where private capital flows dwarf the resources at its disposal, the IMF had come to seem an anachronism. And, when some of the IMF’s largest debtors (Brazil and Argentina) began to prepay their debts a few years ago with no new borrowers in sight, it looked like the final nail in the coffin had been struck. The IMF seemed condemned to run out of income, in addition to losing its raison d’être. It shrank its budgets and began to downsize, and, while it was handed some new responsibilities in the meantime—surveillance over "currency manipulation," in particular—its deliberations proved largely irrelevant. But the crisis has invigorated the IMF. Under its capable managing director, Dominique Strauss-Kahn, the Fund has been one of the few official agencies ahead of—instead of behind — the curve. It moved quickly to establish a fast-disbursing emergency line of credit for countries with "reasonable" policies. It ardently championed global fiscal stimulus on the order of 2 per cent of world GNP—a position that is all the more remarkable in view of its traditional conservatism on all fiscal matters. And, in the run-up to the G-20 summit in London, it thoroughly overhauled its lending policies, de-emphasising traditional conditionality and making it easier for countries to qualify for loans. Even more significantly, the IMF has emerged from the London meeting with substantially greater resources, as well as new responsibilities. The G-20 promised to triple the Fund’s lending capacity (from $250 billion to $750 billion), issue $250 billion of new Special Drawing Rights (a reserve asset made up of a basket of major currencies), and permit the Fund to borrow in capital markets (which it has never done) if necessary. The IMF was also designated as one of two lead agencies—along with an expanded Financial Stability Forum (now renamed the Financial Stability Board)—charged with providing early warning of macroeconomic and financial risks and issuing the requisite policy recommendations. Another piece of good news is that the Europeans have now given up their claim on naming the IMF’s managing director (as have the Americans their corresponding claim on the World Bank presidency). These senior officials are henceforth to be selected "through an open, transparent, and merit-based selection process." This will provide for better governance (although Strauss-Kahn’s leadership has been exemplary), and will enhance both institutions’ legitimacy in the eyes of developing nations. So the IMF now finds itself at the centre of the economic universe once again. How will it choose to deploy its newfound power? The greatest risk is that it will once again over-reach and over-play its hand. That is what happened in the second half of the 1990s, as the IMF began to preach capital-account liberalisation, applied over-stringent fiscal remedies during the Asian financial crisis, and single-handedly tried to reshape Asian economies. The institution has since acknowledged its errors in all these areas. But it remains to be seen if the lessons have been fully internalised, and whether we will have a kinder, gentler IMF in lieu of a rigid, doctrinaire one. One encouraging fact is that developing countries will almost certainly get a larger say in how the Fund is run. This will ensure that poorer nations’ views receive a more sympathetic hearing in the future. But simply giving developing nations greater voting power will make little difference if the IMF’s organisational culture is not changed as well. The Fund is staffed by a large number of smart economists, who lack much connection to (and appreciation for) the institutional realities of the countries on which they work. Their professional expertise is validated by the quality of their advanced degrees, rather than by their achievements in practical policymaking. This breeds arrogance and a sense of smug superiority over their counterparts—policymakers who must balance multiple, complicated agendas. Countering this will require proactive efforts by the IMF’s top leadership in recruitment, staffing and promotion. One option would be to increase substantially the number of mid-career recruits with actual practical experience in developing countries. This would make the IMF staff more cognizant of the value of local knowledge relative to theoretical expertise. Another strategy would be to relocate some of the staff, including those in functional departments, to "regional offices" in the field. This move would likely face considerable resistance from staff who have gotten used to the perks of Washington, DC. But there is no better way to appreciate the role of context than to live in it. The World Bank, which engaged in a similar decentralisation a while back, has become better at serving its clients as a result (without facing difficulties in recruiting top talent). This is an important moment for the IMF. The international community is putting great store in the Fund’s judgment and performance. The Fund will require internal reforms to earn that trust fully.

India returns to the Grand Old Party - Varshney, Ashutosh (Financial Times, 2009)
It is impossible to deny that all of us underestimated the resurgence of India’s Congress party. It is also equally clear that undaunted by soaring heat and a long and exhausting campaign, roughly 420 million voters have produced the best possible outcome for India in what was the largest election of world history. Multiple factors are always involved in producing a clear outcome in Indian elections, but these elections will be widely read as a moment of national redemption and renewal and a retreat, though not the end of, parochial political noise. India’s economic downturn and security dilemmas require political stability and national resolve. Whether that is why the electorate produced such an unexpected verdict in favor of the Congress alliance remains unclear, but the election results will take India in that direction. The wisdom of the electorate is often congratulated for such results. Only with greater election statistics, which will come later, can we establish the existence of such wisdom. It is, however, beyond doubt that a rising power like India, located in a dangerous neighborhood, needs such luck. Both South Asia and the world will be a better place as a result. The victory of the Congress alliance needs to be put in historical perspective. Right since the birth of the Indian republic -- indeed, right since the freedom movement—India’s tallest leaders have always intuitively grasped what their greatest challenge was: how to stitch the nation’s diversities together. It was called nation-building to begin with. Of late, it has come to be viewed as giving the various groups a share in the power structure. Historically, more than any other political organization, the Congress party has understood the centrality of this task. In terms of language, it was always federal, incorporating the various regional diversities into its internal structure. In terms of religion, it sought to bring Hindus, Muslims, Sikhs and Christians together. But in terms of castes within Hindu society, India’s divided majority community, the challenges have been unexpectedly formidable. The Congress sought to put the upper castes, middle castes and the ex-untouchable Dalits together, but sandwiched between the upper castes and Dalits and feeling uncomfortable with both, the middle castes, the largest demographic category of Indian society, started leaving the Congress in the 1950s and 1960s. By the 1990s, the migration of middle castes from the Congress in much of Northern India was nearly complete. In two of India’s biggest states, Uttar Pradesh (UP) and Bihar, the Congress was decimated by the mid-1990s. Once the middle castes and later the Dalits formed their own political parties, Muslims and the upper Hindu castes also did not wish to back a losing horse. They left the Congress, making its hold over power in Delhi extremely shaky. Basically, UP’s size is so huge that without substantial support in UP, it is extremely hard to form a stable government in Delhi. The electoral revival of the Congress party in UP is the biggest news of these elections. It means a return of substantial parts of the Muslim community and upper castes, in addition to some middle castes. It also signifies weakening of lower caste parties that had begun to worry even those, who supported the ideology of social justice and greater power for lower castes. Unlike the plebeian parties of Southern India, the lower caste parties of UP, and also the neighboring Bihar, had become passionate advocates of a rather coarse form of identity politics. Arguing that “Robin Hoods” corrected social injustices on the ground, they openly celebrated “Robin Hoods”, inducted them in large numbers in their parties, and gave them offices. Identity politics came to overwhelm law and order, governance and policy seriousness. The shock delivered to such parties in Northern India in these elections almost certainly represents new citizen aspirations for governance and development, not simply an embrace of caste identity. The defeat of the Communists, especially in West Bengal, also represents a triumph of national purpose. During 2004-2008, India’s Communists were noted for their resistance to economic reforms and nuclear deal. It is one of the hidden transcripts of Indian politics that in West Bengal, the Communists also represented a regionalist aspiration. Right through the 20th century, Kolkata and Delhi had an uneasy relationship. Kolkata was the center of British India till 1912, when the capital moved to Delhi. Since then, Kolkata and Bengal in general have felt an increasing erosion of power. The victory of a Congress alliance in West Bengal brings Kolkata into the national mainstream for the first time in over three decades. Two of India’s historic cities—Kolkata and Delhi—will now have a much better conversation, a development worth applauding. Finally, these elections have boosted the fortunes of Rahul Gandhi as a national leader and deepened the anxieties of the BJP about its future. In a coming-of-age press conference two weeks ago, Rahul Gandhi made two arguments with clarity and passion. First, economic growth, he said, is a necessary (though not a sufficient) condition for poverty removal. No politician of consequence in India’s mass politics (as opposed to its elite politics) has made this argument openly on public stage for decades. Second, he argued that internal elections were a pre-requisite for the revival of the Congress party, especially in UP but also elsewhere. For more than three decades, the discipline of political science has had a professional consensus on this point. It is striking to see a rising political figure agree so much with what the intellectuals and researchers have been saying. The rise of the Congress in UP is mostly due to Rahul Gandhi’s efforts. Many of the national gains of the Congress will also be attributed to his electoral campaign. The Congress party now has a leader not only known in the country for the accident of his birth, but also one whose politics appear to be based on ideas and arguments. For a whole variety of reasons, combining mass appeal with serious arguments has not been easy in Congress politics for a long time. The Congress also has other younger-generation leaders of promise. In contrast, the BJP’s future appears to be very shaky. Its current leader is too old to have the energy to lead for long, and the next in line is Mr Modi, Chief Minister of the state of Gujarat. Mr Modi, a hero of Gujarat and of the right wing of the party, is a deeply divisive figure. In March 2002, he presided over the greatest massacre of Muslims in independent India. The BJP’s future is unlikely to be bright, unless it gets rid of its anti-Muslim prejudice and becomes a Tory or Republican-style right-of-centre party. If Mr. Modi takes over the leadership of the BJP, this historical challenge is likely to be more elusive than ever. The 2009 elections redeem a pluralist and inclusive view of India, defeating narrower visions. The elections also promise political stability. When the campaign began in March, it was hard to imagine such a benign outcome for the country, South Asian region and the international system.

The Way We Live Now: Diminished Returns - Ferguson, Niall (New York Times Magazine, 2009)
If financial crises were distributed along a bell curve—like traffic accidents or people’s heights—really big ones wouldn’t happen very often. When the hedge fund Long-Term Capital Management lost 44 percent of its value in August 1998, its managers were flabbergasted. According to their value-at-risk models, a loss of this magnitude in a single month was so unlikely that it ought never to have happened in the entire life of the universe. Just over a decade later, many more of us now know what it’s like to lose 44 percent of our money. Even after the recent stock-market rally, that’s about how much the Standard & Poor’s 500 index is down compared with October 2007. Financial crises will happen. In the 1340s, a sovereign-debt crisis wiped out the leading Florentine banks of Bardi, Peruzzi and Acciaiuoli. Between December 1719 and December 1720, the price of shares in John Law’s Mississippi Company fell 90 percent. Such crashes can also happen to real estate: in Japan, property prices fell by more than 60 percent during the ’90s. For reasons to do with human psychology and the failure of most educational institutions to teach financial history, we are always more amazed when such things happen than we should be. As a result, 9 times out of 10 we overreact. The usual response is to introduce a raft of new laws and regulations designed to prevent the crisis from repeating itself. In the months ahead, the world will reverberate to the sound of stable doors being shut long after the horses have bolted, and history suggests that many of the new measures will do more harm than good. The classic example is the legislation passed during the British South-Sea Bubble to restrict the formation of joint-stock companies. The so-called Bubble Act of 1720 remained a needless handicap on the British economy for more than a century. Human beings are as good at devising ex post facto explanations for big disasters as they are bad at anticipating those disasters. It is indeed impressive how rapidly the economists who failed to predict this crisis—or predicted the wrong crisis (a dollar crash)—have been able to produce such a satisfying story about its origins. Yes, it was all the fault of deregulation. There are just three problems with this story. First, deregulation began quite a while ago (the Depository Institutions Deregulation and Monetary Control Act was passed in 1980). If deregulation is to blame for the recession that began in December 2007, presumably it should also get some of the credit for the intervening growth. Second, the much greater financial regulation of the 1970s failed to prevent the United States from suffering not only double-digit inflation in that decade but also a recession (between 1973 and 1975) every bit as severe and protracted as the one we’re in now. Third, the continental Europeans—who supposedly have much better-regulated financial sectors than the United States—have even worse problems in their banking sector than we do. The German government likes to wag its finger disapprovingly at the "Anglo Saxon" financial model, but last year average bank leverage was four times higher in Germany than in the United States. Schadenfreude will be in order when the German banking crisis strikes. We need to remember that much financial innovation over the past 30 years was economically beneficial, and not just to the fat cats of Wall Street. New vehicles like hedge funds gave investors like pension funds and endowments vastly more to choose from than the time-honored choice among cash, bonds and stocks. Likewise, innovations like securitization lowered borrowing costs for most consumers. And the globalization of finance played a crucial role in raising growth rates in emerging markets, particularly in Asia, propelling hundreds of millions of people out of poverty. The reality is that crises are more often caused by bad regulation than by deregulation. For one thing, both the international rules governing bank-capital adequacy so elaborately codified in the Basel I and Basel II accords and the national rules administered by the Securities and Exchange Commission failed miserably. It was the Basel system of weighting assets by their supposed riskiness that essentially allowed the Enronization of banks’ balance sheets, so that (for example) the ratio of Citigroup’s tangible on- and off-balance-sheet assets to its common equity reached a staggering 56 to 1 last year. The good health of Canada’s banks is due to better regulation. Simply by capping leverage at 20 to 1, the Office of the Superintendent of Financial Institutions spared Canada the need for bank bailouts. The biggest blunder of all had nothing to do with deregulation. For some reason, the Federal Reserve convinced itself that it could focus exclusively on the prices of consumer goods instead of taking asset prices into account when setting monetary policy. In July 2004, the federal funds rate was just 1.25 percent, at a time when urban property prices were rising at an annual rate of 17 percent. Negative real interest rates at this time were arguably the single most important cause of the property bubble. All of these were sins of commission, not omission, by Washington, and some at least were not unrelated to the very considerable political contributions and lobbying expenditures of the financial sector. Taxpayers, therefore, should beware. It is more than a little convenient for America’s political class to blame deregulation for this financial crisis and the resulting excesses of the free market. Not only does that neatly pass the buck, but it also creates a justification for . . . more regulation. The old Latin question is highly apposite here: Quis custodiet ipsos custodes?—Who regulates the regulators? Until that question is answered, calls for more regulation are symptoms of the very disease they purport to cure.

Which Globalization Will Survive? - Nye, Joseph S., Jr. (Korea Times, 2009)
The world economy will shrink this year for the first time since 1945, and some economists worry that the current crisis could spell the beginning of the end of globalization. Hard economic times are correlated with protectionism, as each country blames others and protects its domestic jobs. In the 1930s, such "beggar-thy-neighbor" policies worsened the situation. Unless political leaders resist such responses, the past could become the future. Ironically, however, such a grim prospect would not mean the end of globalization, defined as the increase in worldwide networks of interdependence. Globalization has several dimensions, and, though economists all too often portray it and the world economy as being one and the same, other forms of globalization also have significant effects—not all of them benign—on our daily lives. The oldest form of globalization is environmental. For example, the first smallpox epidemic was recorded in Egypt in 1350 B.C. It reached China in 49 A.D., Europe after 700, the Americas in 1520, and Australia in l789. Bubonic plague, or the Black Death, originated in Asia, but its spread killed a quarter to a third of Europe's population in the fourteenth century. Europeans carried diseases to the Americas in the 15th and 16th centuries that destroyed up to 95 percent of the indigenous population. In 1918, a flu pandemic caused by a bird virus killed some 40 million people around the world, far more than the recently concluded world war. Some scientists today predict a repeat of an avian flu pandemic. Since 1973, 30 previously unknown infectious diseases have emerged, and other familiar diseases have spread geographically in new, drug-resistant forms. In the 20 years after HIV/AIDS was identified in the 1980s it killed 20 million people and infected another 40 million around the world. Some experts project that that number will double by 2010. The spread of foreign species of flora and fauna to new areas has wiped out native species, and may result in economic losses of several hundred billion dollars per year. Global climate change will affect the lives of people everywhere. Thousands of scientists from more than 100 countries recently reported that there is new and strong evidence that most of the warming observed over the last 50 years is attributable to human activities, and average global temperatures in the 21st century are projected to increase between 2.5 and 10 degrees Fahrenheit. The result could be more severe variations in climate, with too much water in some regions and not enough in others. The effects will include stronger storms, hurricanes, and floods, deeper droughts, and more landslides. Rising temperatures have lengthened the freeze-free season in many regions, and glaciers are melting. The rate at which the sea level rose in the last century was 10 times faster than the average rate over the last three millennia. Then there is military globalization, consisting of networks of interdependence in which force, or the threat of force, is employed. The world wars of the twentieth century are a case in point. The prior era of economic globalization reached its peak in 1914, and was set back by the world wars. But, while global economic integration did not regain its 1914 level until half a century later, military globalization grew as economic globalization shrank. During the Cold War, the global strategic interdependence between the United States and the Soviet Union was acute and well recognized. Not only did it produce world-straddling alliances, but either side could have used intercontinental missiles to destroy the other within 30 minutes. This was distinctive not because it was totally new, but because the scale and speed of the potential conflict arising from military interdependence were so enormous. Today, al-Qaida and other transnational actors have formed global networks of operatives, challenging conventional approaches to national defense through what has been called "asymmetrical warfare." Finally, social globalization consists in the spread of peoples, cultures, images, and ideas. Migration is a concrete example. In the 19th century, some 80 million people crossed oceans to new homes ― far more than in the 20th century. At the beginning of the 21st century, 32 million U.S. residents (11.5 percent of the population) were foreign-born. In addition, some 30 million visitors (students, businesspeople, tourists) enter the country each year. Ideas are an equally important aspect of social globalization. Technology makes physical mobility easier, but local political reactions against immigrants had been growing even before the current economic crisis. The danger today is that short-sighted protectionist reactions to the economic crisis could help to choke off the economic globalization that has spread growth and raised hundreds of millions of people out of poverty over the past half-century. But protectionism will not curb the other forms of globalization. Modern technology means that pathogens travel more easily than in earlier periods. Easy travel plus hard economic times means that immigration rates may accelerate to the point where social friction exceeds general economic benefit. Similarly, hard economic times may worsen relations among governments, as well as domestic conflicts that can lead to violence. At the same time, transnational terrorists will continue to benefit from modern information technology, such as the Internet. And, while depressed economic activity may slow somewhat the rate of greenhouse-gas build-up in the atmosphere, it will also slow the types of costly programs that governments must enact to address emissions that have already occurred. So, unless governments cooperate to stimulate their economies and resist protectionism, the world may find that the current economic crisis does not mean the end of globalization, but only the end of the good kind, leaving us with the worst of all worlds.

Diversity in diversity - Varshney, Ashutosh (Hindustan Times, 2009)
Two points about the current elections ought to be noted. First, a rather large number of parties, campaigning for votes, may give the appearance of chaos on the surface, but there is a dominant narrative that ties up the loose political threads. The central issue in these elections is: how will India’s power structure accommodate the nation’s key diversities? Second, though the overall political prognosis is confusing, some of the basic policies that will emerge are easily predictable. The first issue—political incorporation of diversities—has, of course, never left India’s political process. Using politics to knit together a highly diverse nation has been a significant cornerstone of Indian democracy. Historically, India has had four underlying social diversities: language, tribe, religion and caste. The first two are geographically concentrated; the last two are present all over the country. Federalism is the main mechanism through which India has handled its geographically-centred diversities. However, because of their national spread, caste and religion do not submit themselves to a federal solution. Affirmative action for lower castes and personal laws for religious minorities have been the principal methods of political accommodation. In the ongoing elections, though all these diversities are playing a role, the primarily lower caste parties are especially important. Some like the Samajwadi Party (SP) and the Rashtriya Janata Dal (RJD) are regional in scope, while others like the Bahujan Samaj Party (BSP) are showing signs of national ambition. The BSP is running from more seats than even the Congress and BJP individually. And both the SP and RJD have demonstrated unexpected assertiveness. To understand these parties in terms of the political ambitions of their leaders alone is inadequate. Even the most overtly ambitious politicians must mobilise voting constituencies. Metropolitan India has no experience of how caste operates in small towns and rural India, which constitute over 85 per cent of the country. Outside India’s big cities, lower castes have been ill-treated for a very long time, and lower caste parties have historically sought to change that through the use of State power. Depending on the region, their fight is against the upper castes or the upper OBCs. Poverty is not just a low-income category in India. For most poor people, it comes with the denial of human dignity. The largest proportion of the poor in India has historically come from the Dalits, OBCs and adivasis, groups that have customarily suffered humiliation and discrimination in a vertical Hindu social order. Being treated badly is not the same as being poor, and that’s why the politics of poverty has taken the form of the politics of dignity. To describe its political thrust, every lower caste party has always used some version of the term ‘samman ki raajniti’. (In the US, when issues like this arose with respect to the African Americans, it was called the politics of civil rights.) Sooner or later, democracy privileges numbers. The numerous lower castes are now exercising their democratically acquired political muscle. Achieving political power in South India since the 1950s and 1960s, the lower caste parties have also made a serious political entry in the North over the last two decades. Moreover, since each region mostly speaks a different language, these parties have fragmented the country’s party system. But they are not simply important in the regions; they are now playing a significant role in the formation of a national government. Basically, little Indias are trying to negotiate their overall place in the larger India. Until India is 50 per cent urban and/or it reaches a per capita income of $5,000, which is a serious possibility in the next 15 years, the ‘little India’ pressures in politics will continue. Until then, the two national parties will have to find ways of incorporating the democratically-induced plebeian thrust. Unlike post-Mao China, India’s villages are not yet part of the bustling Indian economy that the world has celebrated over the last ten years and will take some time to get there. Their relative lack of incorporation in rising urban incomes leads to the continuing influence of lower caste parties. Regional lower caste parties are India's version of plebeian politics. However, regardless of which government comes to power, or its composition, India’s foreign and economic policy will remain basically unaltered—just like under the Third Front government during 1996-98. There is no fundamental political dispute in India over the country’s new economic and foreign policy direction. Serious changes in these two policy realms can be expected only if the communists become central to the next government. For economic policy, that means embrace of markets, with regulations; and for foreign policy, the new consensus favours friendship with the US, albeit with hiccups, as the basic national interests of India and the US are increasingly beginning to converge. India’s big disputes are, and will be, over religion and caste. The three most wrenching political issues in the near future can be easily predicted: whether affirmative action should be expanded to the private sector; whether India should pay special attention to better integrating its Muslims in the socio-economic mainstream; and whether propagation of religious ideas and conversion can be free and without constraints, as the Constitution currently permits. These disputes will require political adroitness. Fundamentally, elections in India are no longer about policy disputes. They have become an occasion for various communities to negotiate a better space in the power structure. Policy discussions acquire seriousness after elections are over and governments come to power.

Eighteen faculty, affiliates named to 2009 class of AAAS Fellows (Harvard University Gazette, 2009)
The American Academy of Arts and Sciences (AAAS) today (April 20) announced the election of leaders in the sciences, the humanities and the arts, business, public affairs, and the nonprofit sector. The 210 new AAAS Fellows and 19 Foreign Honorary Members join one of the nation’s most prestigious honorary societies and a center for independent policy research. Included among this field are 17 Harvard faculty members and a Radcliffe Institute Fellow. The academy, established in 1780 by founders of the nation, undertakes studies of complex and emerging problems. Current projects focus on science, technology, and global security; social policy and American institutions; the humanities and culture; and education. The academy’s membership of scholars and practitioners from many disciplines and professions gives it a unique capacity to conduct a wide range of interdisciplinary, long-term policy research endeavors. Harvard’s new AAAS inductees include Philippe Aghion, Robert C. Waggoner Professor of Economics; Richard Cavanagh, adjunct lecturer on public policy; Scott Edwards, Alexander Agassiz Professor of Zoology and curator of ornithology at the Museum of Comparative Zoology; Paul Farmer, Maude and Lillian Presley Professor of Social Medicine in the Department of Global Health and Social Medicine; Benjamin Friedman, William Joseph Maier Professor of Political Economy; James Haber, fellow, Radcliffe Institute for Advanced Study; Jeffrey Hamburger, Kuno Francke Professor of German Art and Culture; Lene Hau, Mallinckrodt Professor of Physics and Applied Physics; Guido Imbens, professor of economics; Stein Jacobsen, professor of geochemistry; Jamaica Kincaid, visiting lecturer, African and African American studies and on English and American literature and language; Michael Klarman, Kirkland and Ellis Professor of Law; Carol Mancusi-Ungaro, founding director of Harvard’s Center for the Technical Study of Modern Art; Anjana Rao, professor of pathology; Mark J. Roe, David Berg Professor of Law; Gary Ruvkun, professor of genetics; Steven Shapin, Franklin L. Ford Professor of the History of Science; and Beth Simmons, director of the Weatherhead Center for International Affairs and Clarence Dillon Professor of International Affairs. The scholars, scientists, jurists, writers, artists, civic, corporate, and philanthropic leaders come from 28 states and 11 countries and range in age from 33 to 83. They represent universities, museums, national laboratories, private research institutes, businesses, and foundations. This year’s group also includes Nobel laureates and recipients of the Pulitzer and Pritzker prizes; MacArthur fellowships; Academy, Grammy, and Tony awards; and the National Medal of Arts. "These remarkable men and women have made singular contributions to their fields, and to the world," said Academy President Emilio Bizzi. "By electing them as members, the academy honors them and their work, and they, in turn, honor us." The new class will be inducted at a ceremony on Oct. 10, at the academy’s headquarters in Cambridge, Mass.

Looking at the world through a comparative lens - Walsh, Colleen (Harvard University Gazette, 2009)
When Steven Levitsky talks politics, a boyish enthusiasm takes over. It’s hardly surprising. He fell in love with the topic at the age of 5. The New York native’s passion for the workings of governments derived from an uncle, a social worker with a keen political eye who liked to discuss the Middle East with his young nephew. “It’s a passion that I grew up with... and I certainly give my uncle the credit, or the blame,” Levitsky, professor of government at Harvard, said with a laugh. The intensity is palpable when he discusses his 2003 work, “Transforming Labor-Based Parties in Latin America: Argentine Peronism in Comparative Perspective,” the book that developed out of his Ph.D. dissertation. The work examines Peronism—the political movement created by Juan Peron in the 1940s that incorporates social democracy and nationalism—and the radical shifts in its ideology during the past 30 years. Traditionally the voice of the poor and of labor and trade unions in Argentina—and largely hated by the middle classes and wealthier sectors of society—the movement switched from a fairly statist populist party in the 1980s to one responsible for carrying out radical free market reforms in the 1990s, said Levitsky. Recently, it has shifted dramatically again, moving back toward the left. “It’s a party that did a programmatic 180 and I wanted to explain how it did that. Political parties aren’t supposed to go from Reaganism to Ted Kennedy liberalism overnight, and that is basically what the Peronists did.” To understand the shifts, Levitsky spent a year and a half in Argentina meeting and interviewing party members. He found that both the movement’s massive membership (deeply entrenched in the working class) and its loosely structured organization help explain the recent changes. “The rules and procedures that structure party life: how to choose candidates, how to make decisions, how to choose a platform—all of that stuff is constantly up in the air,” he said. But such turbulence, while chaotic, he noted, can be beneficial. “It makes for quite a bit of flexibility. It allows the party, at least under certain circumstances, to adapt much more quickly than more bureaucratic parties.” The young professor, who never took an introductory course on comparative politics (the examination of the similarities and differences of governments) as an undergraduate at Stanford because of its “deadly boring” reputation, is dedicated to teaching the subject in a compelling way. To engage his class, Levitsky examines four topics: revolution, economic development, democracy, and ethnic conflict, all in a contemporary context. Students compare and evaluate different theories in an effort to understand the reasons behind ethnic violence in Yugoslavia and Rwanda, social revolutions in Russia and Iran, and democratic reform in South Africa. His course’s steadily rising enrollment numbers is an indication of the effectiveness of his approach. “Comparative politics,” he said on a recent afternoon in his cluttered office, “is inherently sexy; it’s really exciting.” It was global political turmoil occurring in Levitsky’s formative years that drew him toward Central and Latin America. In high school and early on in college, the drama of the Nicaraguan civil war and events in El Salvador inspired him to get personally involved. His opposition to the United States’ efforts to overthrow the Sandinistas in Nicaragua and U.S. support for the military-backed government in El Salvador led him to take part in protests, join letter-writing campaigns, and participate in what he calls his greatest contribution: “guerilla theater.” Levitsky and his friends would dress in fatigues, storm the college cafeteria, kidnap a diner who was in on the plan, and hand out leaflets that stated such abductions were a regular occurrence in El Salvador. His interest in the conflict led to a trip to the country in 1989, where he conducted research for his undergraduate thesis; it was a trip that sealed his academic fate. “Just jumping in the middle of things and talking to people was absolutely decisive in my choice to go on and become a scholar. I had no real training in research, but the experience of being there and sticking my nose in the middle of politics was a very powerful one for me.” Levitsky entered graduate school at the University of California, Berkeley, in 1992, about a year after the collapse of the Soviet Union. The “momentous time,” he recalled, pulled him again toward Latin America as the demise of the socialist model of the USSR forced the region’s labor-based and leftist parties to re-evaluate their approach. “The world was really being thrown up in the air. I knew from early on that I wanted to study this question of how labor-based parties, particularly in Latin America, were responding to globalization.” The avid Mets fan who proudly displays a baseball signed by Willie Mays on his desk, met his wife during his graduate school years. After attending one of his talks where he described Peru’s government as an “authoritarian democracy,” Liz, a Peruvian journalist studying at Berkeley for a year, challenged him a week later. “She started ripping into my talk,” he said, “and I immediately fell in love.” Today the couple has a daughter, Alejandra, who seems to be following in her father’s passionate political footsteps. During the primary season, when Levitsky and his wife were split about supporting Hillary Clinton or Barack Obama, their then 4-year-old adamantly weighed in one morning at breakfast. “She jumped into the discussion,” said Levitsky, “pounded her fist on the table and said, ‘No! We’re all voting for Obama!’” Back in class, Levitsky said he hopes to impart his own passion for politics, along with a lesson about critical thinking. Surprised by how many first-year undergraduates enter his class wanting to “know the answer,” he tries to teach them “how to think critically, how to compare and evaluate different arguments. “The vast majority of the students that I teach are not going to be political scientists,” he said. “They are going to be citizens, and here at Harvard in many cases, fairly influential and powerful citizens, so it means a lot to me to have a small amount of influence into how these guys think, and hopefully get them a little bit more engaged in politics.”

"What Just Happened? What’s Next?" An interdisciplinary examination of the current economic crisis - Walker, Ruth (Harvard University Gazette, 2009)
You might think of the little bits of good news that came out last week as the macroeconomic equivalent of the first crocuses of spring. There was the heartening word that initial jobless claims are slowing. The stock market continues its modest rebound. And some analysts are cautiously suggesting that there might be economic growth again before 2009 is out. But over at Two Arrow Street, participants in a daylong conference offered April 15 by the Weatherhead Center’s Project on Justice, Welfare, and Economics were looking at the economy through a much longer lens. The conference was called "What Just Happened? What’s Next?" and its subtitle was "An Interdisciplinary Examination of Our Current Economic Crisis." In a presentation titled “The Crisis as an Opportunity for Structural Change,” Thomas Pogge, Ph.D. ’83, of Yale University set forth his proposal for what he calls a Health Impact Fund (HIF). It’s meant to do nothing less than revolutionize the way medicines are provided to the global poor. The fund, he explained, would reconfigure financial incentives for drugmakers. The current system rewards them for selling lifetime "maintenance" drugs to rich Westerners, rather than curative or even preventive medications to fight the diseases of the developing world. But Pogge’s fund "promises to reward... any new medicine on the basis of its global health impact." Under Pogge’s proposal, worked out with University of Calgary economist Aidan Hollis, affluent nations would chip in a share of their gross national income to support the fund. He suggested that a 0.01 percent contribution would yield about $6 billion a year, which should be a large enough pool to start the program. Each year’s pool would be divided up among the manufacturers whose drugs were listed at any given time. He foresees about 20 drugs on the list at a time. “It’s registered and you get health impact rewards,” Pogge said. “You don’t give up any intellectual property rights.” A pharmaceutical manufacturer would, however, give up the right to a profit on the sales price. Under the Pogge/Hollis proposal, “the registrant must agree to make the new medicine available wherever it is needed at the lowest feasible cost of manufacture.” The reward is for contributing to public health, not for selling pills, in other words. “Perverse incentives” is a phrase on the lips of many analysts of the current financial crisis: Too many actors have been rewarded for taking risks but not punished for poor performance. But Pogge made the case that the current system of compensating drugmakers has its own perversities as well. He explained that under the current system of international commerce, a country joining the World Trade Organization must sign on to a package of accords including the so-called Trips Agreement, which covers trade-related aspects of intellectual property rights. This agreement obliges signatories to grant 20-year product patents for, among other things, drugs. This locks countries into the high-markup business model for medicine, and that, in turn makes it hard if not impossible to make drugs available at low cost. The current system provides incentives for counterfeiting, Pogge said. In the pharmaceutical world, this means making knockoffs with just enough of the active ingredient to pass for the real thing but not enough to be medically effective. Instead, these underpowered fakes help create drug-resistant strains of diseases. And by making it profitable for drugmakers to serve the poor, the Health Impact Fund would also protect against diseases such as Severe Acute Respiratory Syndrome (SARS) that fester largely untreated in the developing world for years and then burst suddenly onto the scene in the developed world. SARS apparently originated in China and spread to 37 countries, infecting thousands and killing nearly 800 during a near pandemic from November 2002 and July 2003. It could have been much worse, Pogge suggested. “We were lucky with SARS,” he said. One challenge to the Health Impact Fund concept was raised in a question from the floor posed by Norman Daniels, Mary B. Saltonstall Professor of Population Ethics and Professor of Ethics and Population Health at the Harvard School of Public Health, who told Pogge, “A presupposition of your scheme is that we know how to measure the contribution of a specific drug. I’m not sure we do.” He went on to say that many drugs are delivered in systems, which themselves make a contribution to patient health. Nonetheless, Pogge ticked off the advantage of the Health Impact Fund as a “focal point of structural reform”: It isn’t driven only by concern for the poor—it helps benefit the pharmaceutical industry, too. It’s scalable: The fund could be increased or adjusted in light of experience. And manufacturers could decide to transfer some drugs from the patent track to the fund track depending on whom they benefit. The fund “strengthens those with objective interest in reform” and thus leads to “the empowerment of global poor.” It is an exemplar of realistic moral leadership, genuine moralization, and global public good. It would lead, he suggested, to “a reduction in global public evil.”

Europe needs a stronger France inside Nato - Kaiser, Karl; Moïsi, Dominique (Financial Times, 2009)
The debate on whether to return to Nato’s permanent command structure that has recently been unleashed in France—43 years after Charles de Gaulle pulled his country out—has impassioned its political class much more than the wider public. The opposition has seized the opportunity to attack President Nicolas Sarkozy on an issue where his governing centre-right party happens to be divided. But if one goes beyond the political calculations and ideological reflexes of this debate and considers the long-term strategic implications, what is at stake? In the first place common sense requires that an anachronism be eliminated and that the appropriate lessons be drawn from the fundamental changes happening in today’s world, in the US as well as in Europe. By remaining a member of Nato without taking part in its integrated military structure France has first and foremost penalised itself. Precisely because the future of Nato’s strategy is at stake and legitimate questions must be raised about the choices to be made regarding Afghanistan, France should assume its responsibilities inside Nato and thereby increase Europe’s weight in redefining western strategy. Only from inside will France be able to assert its own interests. But the developments in the international environment make a change of France's status inside Nato seem even more advisable, indeed necessary. The world has changed profoundly; the west is no longer as dominant as it has been for two centuries, either economically or in terms of strategic importance. The economic crisis, though global in nature, is accelerating the historic shift from the west to Asia. Moreover, Europe’s primary problem is no longer to define itself as distinct from, if not at times in opposition to, the US. That is an obsolete mindset. Today’s challenge is to form a common front by asserting our values, not against others but in co-operation with them and in recognition of an emerging multi-polarity. Since the election of Barack Obama as president of the US these changes have been accompanied by a revolution: not only has there been a big change in the image of America in the world but the behaviour of the US vis á vis its allies has changed even more radically. Though it is too early to know whether President Obama will succeed in reinvigorating the US economy, it is not too early to support his measures and efforts to relaunch multilateralism with strong action taken by our two countries. The French population as well as the Germans—we remember the enthusiastic crowds that cheered him in Berlin—strongly support Mr Obama. France should seize the hand extended by America. Its return as a full member of Nato would constitute a strong symbolic and political act, sealing a historic reconciliation of two allies that are willing to put their common challenges above the quarrels and prejudices of the past. Europe itself is changing before our eyes. There is no contradiction between the desire to advance European defence and to "normalise" France’s status inside Nato; on the contrary, France’s position thereby would come closer to that of Britain and Germany. A stronger France inside the alliance would strengthen the European defence effort. The return of France to Nato is not a guarantee of a successful European defence, but it certainly is a necessary precondition. This becomes all the more true considering the new challenges facing Europe such as the return of Russia, now seeking a more powerful role in the international system. We should not allow Russia to exploit potential differences between Europe and Nato. But at the same time we must seek to open a dialogue with Russia on the necessary reopening of arms control negotiations in Europe, hopefully building a new partnership. These negotiations require strong and harmonised positions within Nato. The authors of this article have devoted an important part of their lives to Franco-German rapprochement, which they consider to be a key to European unification. They regard the complete return of France to Nato as a logical step towards the European goal. They are convinced that General de Gaulle, with his pragmatic and realist vision of the world and of a Europe based on the Franco-German relationship, would be shocked to hear that his name is evoked today to oppose an adjustment that he himself would have considered natural, given the profound changes that are happening in the world.

An alternative to NATO membership - Kaiser, Karl (International Herald Tribune, 2009)
NATO membership for Georgia and Ukraine is not a realistic possibility, no matter what the Atlantic alliance may say about their potential in principle, as it did at the last two summit meetings. That alternative has been closed, not because some NATO members—notably France and Germany—fractiously opposed an unpopular Bush administration in its enlargement drive, but for deeper structural reasons. First, domestic conditions speak against membership. The reckless engagement with a superior Russian military by Georgia's president, Mikheil Saakashvili, although he had been thoroughly briefed by the United States about the Russian potential, demonstrated to NATO how bad leadership in combination with a very old conflict can drag the Atlantic alliance into a war it does not want. In Ukraine there is no majority support for membership among the general population; indeed, in the eastern part of the country there is strong opposition. If ever the leadership were to force this issue it would risk a deep split, with potentially disastrous consequences for the integrity of Ukraine. Second, contrary to the expectations at the end of the Cold War, large-scale conventional warfare in Europe has reappeared as a threatening possibility. The worst possible scenario for NATO would be that the alliance would be unable to defend an ally under Article V because of lack of political will (even now the majority of people in some NATO countries do not support going to war over Central European members), or for military reasons—as would be the case for Georgia and Ukraine under the present circumstances. This would expose NATO as a paper tiger and cause it to loose the essence of its credibility and meaning. Third, Russia's relations with the West have reached their lowest point since the end of the Cold War. The enlargement of NATO, the breakdown of strategic and conventional arms control, the installment of missile defenses in Central Europe, and the West's failure to consult Russia on issues it considers vital to its interests, have created a concoction of resentment and perceptions of not being treated as a major power. Georgian and Ukrainian membership in NATO represents a red line that gives them disproportionate significance. The West has to take this into account if it wants to improve the situation in Europe and regain Russia as a partner in global affairs. Georgia and Ukraine deserve and will get substantial aid from NATO and the European Union. But it makes little sense to address their long-term security problems separately since they are part of the necessary overhaul of the West's Russia policy that the Obama administration has promised and the European Allies eagerly await. Such an overhaul would have to include, among other things, strategic arms control, a nonproliferation policy and missile defense. As far as Georgia and Ukraine are concerned, two items are central to the alleviation of their problems. First, a general dialogue between the West and Russia is necessary in order to review the problems of European security and develop approaches that could improve the overall situation. Presidents Dmitri Medvedev of Russia and Nicolas Sarkozy of France have supported such an idea with the quiet and explicit approval of many European governments. Second, the military security of both countries can be addressed by reviving the Treaty on Conventional Forces in Europe. The treaty was concluded in 1990 and adapted to changed circumstances with an additional agreement in 1999. It has the advantage of providing for upper limits to conventional forces in geographic zones, for the destruction of equipment, for inspections, and rules for stationing foreign troops. To be sure, the treaty is now blocked by linked conditionality of NATO and Russia and has been suspended by Russia, and is, of course, no panacea. Problems left to themselves for two decades must be dealt with. But reopening conventional arms control in Europe offers a chance to address the concrete security problems of Georgia and Ukraine (as well as of other European countries) and become part of a hopefully constructive redefinition of the West's relationship with Russia.

Avoiding the worst: International economic cooperation and domestic politics - Frieden, Jeffry (Vox, 2009)
If the crisis turns into a new Great Depression, it will most likely be due to a breakdown of cooperation among the major economies. But sustaining international cooperation requires domestic support; ignoring the demands of poor and middle-class citizens for relief will inflame more extreme anti-globalisation views, making international cooperation much more difficult. If the current crisis turns into a disaster on the order of the Great Depression, it will most likely be due to a breakdown of cooperation among the major economies. The history of the modern world economy—and especially of its collapse in the 1930s—makes clear that the principal powers have to work together if they are to maintain an integrated international economic order. International cooperation needs domestic support for openness Yet governments are only able to make the sacrifices necessary to sustain international cooperation if they can rely, in turn, on domestic political support for an open world economy. National publics unconvinced of the value of international integration will not back policies—often costly and difficult policies—to maintain it. This can lead—again, as in the 1930s—to a perverse process in which global economic failure undermines support for economic openness, which leads governments to pursue uncooperative policies, which further weakens the global economy. On both dimensions, international and domestic, we are in trouble. So far, despite high-sounding internationalist rhetoric, governments have responded to the crisis with policies that take little account of their impact on other nations. And the crisis has dramatically reduced domestic public support for globalisation, and for national policies to sustain it. Why reasonable governments do unreasonable things On the international dimension, the threat is not so much of explicit protectionism but rather of nationally specific policies that impose costs on others, directly or indirectly. These beggar-thy-neighbour policies are not normally the result of some inexplicable bloody-mindedness on the part of venal governments, or of purposeful antagonism toward rivals. They are, instead, desperate attempts to defend national economies from gathering storms. But they impose negative externalities on other countries, and in so doing can provoke hostile reactions that can drag all parties concerned into bitter conflict. Not out of arrogant nationalism but out of domestic desperation Domestic constituents demand action, and governments have to respond, even at the expense of international cooperation. This can easily lead down a path toward conflict. Financial intervention to restore liquidity or solvency to the banking system can come at the expense of financial partners, sucking funds out of neighbours. The early-October Irish blanket deposit guarantee, implemented with the perfectly understandable goal of avoiding a bank panic in a small and vulnerable economy, nearly induced a run on British banks as British depositors rushed to transfer funds from British to Irish banks. The current American financial bailout is drawing capital from the rest of the world—including from emerging markets that urgently need it—not out of arrogant nationalism but out of domestic desperation. And the buy-American provisions of the current stimulus package demonstrate the ease with which well-intentioned policies can turn into uncooperative predation. The range of policies of this type—sincere national initiatives with counter-productive international implications—is virtually endless. Negative externalities galore Support for troubled national firms can turn into anti-competitive subsidies to national champions. Currency depreciation, a common recommendation for difficult times, can put competitive pressure on trading partners, leading to round after round of "competitive devaluations." Debt-averse governments can limit the size of their fiscal stimulus, thereby free riding on the deficit spending of neighbours. Countries with intolerable foreign debt burdens can seek debt write-downs that further cripple creditor-country financial markets. And all of these can interact to create powerful protectionist pressures. One country’s fiscal stimulus can "leak" into a neighbour, draw in a surge of imports from the neighbour, and provoke a bitter protectionist backlash. Even with the best of intentions, governments can act in ways that drive wedges among countries, block cooperative responses to the crisis, and ultimately make everyone worse off. And despite today’s flowery rhetoric, there is little evidence that national policymakers are willing or able to take into account the international implications of their actions. If this pattern continues, it will be a major obstacle to a rapid recovery. Will anyone speak for the rest of the world? National governments rarely consider global consequences, because their constituents are domestic and national publics are very skeptical about the contemporary world economy. Even before the crisis hit, there had been real erosion in popular support for globalisation. Economic integration has come to be associated with job losses, competitive pressures, and a worsening of income distribution in developed and developing countries alike. Nearly universally, the lower registers of the income distribution are most dubious about the benefits of international economic integration, and these doubts are particularly widespread in more unequal societies. The crisis has heightened suspicion of a world economy that appears to be the source of much of our current predicament. There is increasing resentment that the expansion of the past ten years primarily helped the wealthy, while the poor and middle classes are being asked to sacrifice to deal with the hangover of the binge. This is coupled with similar resentment that governments appear to privilege the concerns of international banks and corporations. There is an advancing popular view that insulation will help reinforce national attempts to deal with the crisis. National publics will increasingly resist making national sacrifices in order to honour international economic obligations. Meanwhile, concentrated interests who support globalisation—such as the international financial and corporate sectors—have been undermined by international economic weakness. Broad popular sentiment is increasingly widespread and powerful that national responses to the crisis must take priority over international obligations. Attention must be paid: Crisis’s impact on income distribution The impact of the crisis on income distribution cannot be ignored, for it will determine much of the politics of government responses to the crisis. Ignoring the demands of poor and middle-class citizens for relief will inflame more extreme anti-globalisation views, making international cooperation that much more difficult. These two dimensions, the international and the domestic, are closely interrelated. The less domestic support there is for globalisation, the harder it will be for national governments to reach cooperative agreements with partners. The less international cooperation there is, the greater the likelihood of a deterioration in the global economy. As in the 1930s, beggar-thy-neighbour policies, distributional conflicts, and international economic stagnation could feed on each other in a downward dance. Into the maelstrom?Governments have to act consciously to counteract this dismal possibility At the domestic level, governments need to work out an equitable and politically sustainable allocation of austerity across the population. This means ensuring that those sectors of society hit hardest by the crisis are not also the ones asked to bear the stiffest sacrifices. Societies with existing social safety nets will have to expand them and make sure they work for wider segments of the population than they were planned. Countries with weak or non-existent social programs for the victims of crises such as this will have to create them, and quickly. By the same token, basic principles of equity—and even more basic political realities—demand that those who received the main benefits of the boom have to bear their share of the costs of the bust. Governments that ignore the social and distributional implications of the crisis are likely to find themselves either driven toward extreme and counter-productive policies, or swept away. Even sustaining existing social programs is extraordinarily difficult in such hard times. This is true of all governments, which face powerful fiscal pressures as tax revenues dry up and demands for spending soar. The difficulties are especially challenging for developing countries, many of which have lost whatever access they may have had to external sources of capital. Yet governments that do not provide effective relief to those hardest hit by the crisis face the prospect of dramatically increased social and political strife, which will only deepen the disaster. At the international level, governments need to work just as consciously to coordinate not just words, but actions. This will not happen of its own accord. So far, the solidarity of OECD central bankers has been impressive. However, this builds upon a long-standing tradition of the solidarity of central bankers, and upon decades of institutionalised collaboration, and can only take us a very short part of the way. There is nothing analogous on other dimensions. The free interplay of government policies will not spontaneously bring forth international cooperation Collaboration among governments has to be intended, designed, and monitored. This almost certainly requires some international institutional framework, some set of agreed-upon rules and ways of enforcing them. The governments of the major economic centers need to consult regularly on the international dimensions of the crisis, and of its resolution. They need to hold each other to account, and they need some reasonably independent mechanism to identify policies that risk driving governments toward conflict rather than mutual assistance. Other foreign policy goals can and should be linked to supportive efforts on the economic front. Conclusion If governments do not pay real attention to the domestic distributional impact of the emergency, and to the international implications of their national policies, the current calamity will feed on itself. The Great Depression of the 1930s was more a failure of national policy, and of international cooperation, than it was a failure of markets. Success in confronting the current crisis will similarly depend on socially responsive and viable national policies, and on globally responsive and viable international cooperation. Editors' note: This column is a Lead Commentary on Vox's Global Crisis Debate page; see further discussion on Vox’s Global Crisis Debate page. References Frieden, Jeffry A. 2006. Global Capitalism: Its Fall and Rise in the Twentieth Century. W.W. Norton. Frieden, Jeffry. 2007. "Will Global Capitalism Fall Again?" Bruegel Essay and Lecture Series (Brussels: Bruegel, 2007). Frieden, Jeffry. 2008. "Global Governance of Global Monetary Relations: Rationale and Feasibility." Economics. Discussion Paper number 2008-32.

Gaza sours Israel-Turkey relations - Martin, Lenore G. (Al Jazeera English, 2009)
<param name="movie" value="http://www.youtube.com/v/ISfP84rMPCc&color1=0xb1b1b1&color2=0xcfcfcf&feature=player_embedded&fs=1"></param><param name="allowFullScreen" value="true"></param><embed src="http://www.youtube.com/v/ISfP84rMPCc&color1=0xb1b1b1&color2=0xcfcfcf&feature=player_embedded&fs=1" type="application/x-shockwave-flash" allowfullscreen="true" width="425" height="344"></embed> Inside Story: Gaza sours Israel-Turkey relations Aftershocks of the war on Gaza signal a possible rift between Israel and Turkey. Last month, at the World Economic Forum in Davos, Erdogan angrily accused Israeli president Shimon Peres of "knowing very well how to kill". He also criticised Israeli policies and actions towards the Palestinians, who he said lived in an "open-air prison." In response, Israeli Major General Avi Mizrahi was quoted as saying Turkey was not in a position to criticise Israel when it stations troops in northern Cyprus. He also accused Turkey of repressing its Kurdish minority and massacring Armenians during World War one. Where does the relationship between Israel and Turkey currently stand? Israel and Turkey have a strategic alliance tightened by military, diplomatic and political cooperation and often refer to themselves as the only democracies in the Middle East. They share a number of common interests. Both counties are largely dependent on the United States for security and are against the rise of Islamic radicalism. Turkey has provided considerable support to an isolated Israel in the Middle East. Turkey was the first majority Muslim country to recognise Israel as a state and it has built up more than $3 billion in annual trade with it. Has their relationship reached an unprecedented low and possibly a point of no return? Are there unknown causes behind this swift souring in their relationship? And is their long friendship in danger of collapsing? Inside Story presenter Imran Garda is joined by Umut Arik, a former Turkish ambassador and the secretary general of Turkey's Democratic Party; Ofra Bengio, a senior research fellow at the Dayan Center for Middle East and African Studies at Tel Aviv University, and Lenore Martin, a professor of political science at Emmanuel College and author of the book The Future of Turkish Foreign Policy.

A Stimulus Package for Reviving the Peace Process - Martin, Lenore G. (Israel Policy Forum, 2009)
The recently enacted stimulus package for reviving the worst U.S. economic recession in decades should serve as a model for reviving the Palestinian-Israeli peace process. The peace process has been in its own recession since the failure of the Taba talks in January 2001. The steady expansion of Israeli settlements in the West Bank has deepened that recession. By all accounts, Israeli settlements block the implementation of a two-state solution to the Palestinian-Israeli dispute. The stimulus package should consist of a multi-billion dollar international fund with a first priority of reversing the growth of Israeli settlements and financing the resettlement of Israelis from the West Bank essentially within the 1967 borders. The next application of the fund will be to house Palestinians in the vacant Israeli settlements. The ultimate goal of the stimulus package will be the creation of an economically viable Palestinian state. This proposal will go a long way to ending the occupation, changing the oppressive conditions the Palestinians are enduring and moving towards peace with an Israeli State and a Palestinian State. Consistent with the Obama Administration's declared objective of engaging in multilateral diplomacy to address troublesome international political issues, the United States should be the lead investor in the fund. Washington should then invite substantial contributions from other parties that have an interest in the peace process, including the Arab League, the European Union, and Russia. The stimulus package should not encourage another Israeli "unilateral" move, as in Ariel Sharon's withdrawal from Gaza. The package should stimulate a negotiating process that will create new "facts on the ground" that are conducive to the resolution of the "final status" issues. Negotiations over the application of the fund will not be easy. For example, with the assistance of the fund managers the Palestinian Authority under Abu Mazen's leadership and representatives of the next Israeli government will need to work out the details of removing Israeli road blocks to enable Palestinian goods and people to move throughout the West Bank. The parties will also need to negotiate maintaining Israel's security including the movement of IDF forces in and through the West Bank while enabling the Palestinians to extend local security into the former settlements where Palestinians should be settling. The Obama Administration has already signaled to Israelis, Palestinians and the international community that it is willing to dedicate U.S. prestige as well as resources to reviving Palestinian-Israeli peace negotiations. The American "dream team" for this effort includes former Senator George Mitchell, who brings to the negotiating table his reputation as the proponent of the Good Friday Peace Agreement that resolved the intractable ethnic/religious conflict in Northern Ireland. It also includes Secretary of State Hilary Clinton, whose husband, former President Bill Clinton proposed the "Clinton parameters" which could serve as the forerunner of a potential resolution of the intractable Palestinian-Israeli dispute. Establishing the international stimulus package as soon as possible would be a good way to put the dream team and a tangible demonstration of the U.S. commitment to ending the "recession" in the peace process. No one doubts that there will be potentially violent opposition to the resettlement of Israelis from the West Bank. Extremist factions from Hamas and Islamic Jihad on the one side and religious nationalist settlers on the other will seek to sabotage the stimulus by violent attacks. However, as in the treatment of the "toxic assets" that have contributed to the economic recession, the promoters of the economic stimulus should not let violent extremists poison the political stimulus to reviving peace negotiations. One can also expect vociferous opposition to the stimulus package from Benjamin Netanyahu and his Likud party. In the campaign for the recent Israeli elections they loudly declared that they want to maintain the settlements and even allow their "natural expansion"- albeit without promoting the construction of new settlements. As a pre-condition to the negotiation of peace with the Palestinians, Netanyahu proposes the rapid development of the Palestinian economy. Glossed over in this proposal are the realities of the myriads of Israeli settlements throughout the West Bank and the numerous road blocks that serve to secure them, all of which impede the flow of people and goods that cripple Palestinian economic development. The United States can overcome such opposition by applying pressure to the next Israeli government, whether it be controlled by Likud or shared with Kadima. As a condition to the stimulus package Washington can insist that Israel should stop settlement construction and start the process of removing settlers from the West Bank. Appointing George Mitchell as special envoy to the Middle East was an indication to the Israelis of America's seriousness in insisting on this turnaround. Mitchell was the author of the 2001 Mitchell Report for then President Clinton that, among other things, stipulated that Israel should stop building settlements in the Occupied Territories. The speed with which President Obama has acted on the Palestinian-Israeli dispute makes it clear that he recognizes its resolution is in the national interest of the United States in order to restore American influence in the region, firm up U.S. alliances in the Arab world and stabilize the Middle East. An international stimulus package to revive peace negotiations would work towards achieving this goal. Resettling the West Bank settlers would halt the dynamic towards a one state outcome that will frustrate the national dreams of both Palestinians and Israelis. It will deny the extremists on both sides their claims to all of the land, claims that condemn the rest of the population to a never ending cycle of violence. It is good for the United States, Israel, the Palestinians, and our friends throughout the region.

American Academy of Arts and Sciences Names Manela Visiting Scholar (American Academy of Arts and Sciences, 2009)
Erez Manela, the Dunwalke Associate Professor of American History at Harvard University, is among eight individuals who have been awarded fellowships as part of the American Academy of Arts and Sciences' Visiting Scholars Program for 2009. The fellowship program supports scholars and practitioners in the early stages of their careers—both post-doctoral fellows and untenured junior faculty—who show potential of becoming leaders in the humanities, policy studies, and social sciences. "Fellowships in the humanities and social sciences are limited," noted Academy Chief Executive Officer Leslie Berlowitz. "Our experience shows that these types of fellowships can be a significant factor in developing the careers of new scholars." During his residency in Cambridge, Manela will be working on a project titled, "The Eradication of Smallpox: An International History." The project is a study of the World Health Organization’s Global Smallpox Eradication Program, which provides insight into the history of the Cold War, postcolonial international relations, the role of transnational organizations in globalization, and the development of modern medicine and international public health. Manela directs undergraduate programs at the Weatherhead Center for International Affairs at Harvard and authored The Wilsonian Moment: Self-Determination and the International Origins of Anticolonial Nationalism (Oxford University Press, 2007). He received his PhD from Yale University and his undergraduate degree from Hebrew University in Jerusalem. The Academy fellowships combine the scholars' individual research with participation in the many ongoing programs and activities at the Academy, including the opportunity to interact with Academy Fellows, who bring an unparalleled wealth of knowledge from diverse scholarly and professional backgrounds. "The Academy’s Visiting Scholars Program gives emerging scholars the chance to engage in studies of complex social and intellectual issues in an environment that is both interdisciplinary and intergenerational," Berlowitz added. Launched in 2002, the Visiting Scholars Program is co-chaired by Patricia Meyer Spacks, former President of the Academy, and Edgar F. Shannon Professor of English Emerita at the University of Virginia. During the program's first six years, 53 emerging academic leaders have participated. They have gone on to secure teaching and research positions at Columbia, Harvard, Northwestern, Yale, Case Western Reserve, and Boston universities, among others, and have used their residency at the Academy to complete more than 40 books and numerous articles.

Assault on India’s fabled city of dreams - Varshney, Ashutosh (Financial Times, 2008)
Terror has rocked India before but never have terrorists been so audacious. South Mumbai is India’s economic heart. This attack is "India’s 9/11". Mumbai is no routine urban agglomeration. It is a fabled city, where millions of Indians, migrating from poor hinterlands, seek a living; where rags-to-riches stories are not uncommon; where vast business deals are struck. It is where dreams are manufactured by a film industry that gives countless Indians relief from the struggles of life. Millions identify with the city. Mumbai is a paradox. It has areas of appalling squalor but is India’s city of hope. It is in south Mumbai that the Tatas honed world-class business skills, Zubin Mehta learnt how to conduct Beethoven’s Fifth and Salman Rushdie understood how to turn the drama of everyday life into novels. By targeting south Mumbai, the terrorists have not only attacked the economic symbol of a rising India but also its most globalised quarters. A big hypothesis beckons: India is a highly unequal democracy in a bad neighbourhood, and as long as its democracy, inequalities and regional misfortunes remain unreformed, it will be vulnerable to terrorism. Consider how Indian democracy has addressed terrorism. India’s politicians have asked: are terrorists simply terrorists, or are they Muslim or Hindu terrorists? This question is tied up with electoral politics. Muslims comprise about 13 per cent of India’s population. Given how they are geographically distributed, they form a crucial electoral segment of at least a quarter of India’s parliamentary seats. Seeking Hindu votes, some politicians have been quick to equate terror with Islam. Others, especially pro-Muslim political parties, focus on the unfair treatment of Muslims by the police rather than the fight to eliminate terror. Recently Indian democracy has been treated to the obverse of "Muslim terror". Prima facie evidence and intelligence suggest the rise of Hindu networks practising terror against Muslims. In India’s democracy, terror has become identified not as an evil but as an outgrowth of the grievances of Muslims or Hindus, or as a sign of whether the Indian state is unfair to Muslims or Hindus. That is a recipe for further disasters. Inequalities are the second part of the problem. The Indian economy has been booming, but while some business leaders, film stars and sports icons are Muslim, Muslims mostly come from the poorest, least educated and most poorly skilled communities. Nowhere is this contradiction more evident than in Mumbai. It has some of the richest Indian Muslims but there is a huge Muslim underclass and a connection between Mumbai’s underworld and its poor Muslims has been noted. Muslim gangs are among the most powerful players in Mumbai’s organised crime. To many, crime appears to offer greater and easier rewards than a dogged pursuit of regular employment. Finally, Indian democracy functions in a region, whose failings are second only to the Middle East’s. Recent works by Pakistani scholars make it clear that the state in Pakistan has long been fractured between agencies that support terrorism and those that seek to control it. India has its troubles in Kashmir and the north-east, but these conflicts have never reduced the Indian state to a shambles. Alone in south Asia, India has had sufficient institutional strength to hold regular elections. India has to ask how long it can continue to be institutionally strong if the neighbourhood is so violent. Its borders are porous and the prospect of maritime terrorism, raised by the Mumbai carnage, makes them more so. Foreign policy and national security are increasingly tied up with India’s political health, with potential consequences for India’s economic resilience. What can be done? How to include India’s Muslims in the economic mainstream is key. India’s political parties need to learn that terrorism cannot be seen as a vote-winner. It is an evil and a security threat. If political parties link terrorism with Muslims or Hindus, they will only bring greater catastrophe closer. Finally, India must vigorously cultivate peace with Pakistan. Luckily, a government today exists in Pakistan that has made the most resolute gestures towards peace in decades. President Asif Ali Zardari has opened up a unique opportunity for regional peace. After Mumbai, India needs to respond.

Seminar focuses on human rights - Simon, Emily T. (Harvard University Gazette, 2008)
The undergraduates who gather around the seminar table at 61 Kirkland St. have a lot on their minds. Not just final papers, athletic matches, and music performances, but a range of issues that run far beyond the daily stresses of college: Refugee resettlement. Human trafficking. Child soldiers. These human rights issues—along with many others—are the challenges that have inspired this group of passionate students to add another course to their jam-packed schedules. This fall marks the inaugural semester of the Human Rights Scholars Seminar, a biweekly, noncredit class for juniors and seniors with a dedicated interest in human rights-related research. The yearlong course provides a forum for the discussion of human rights scholarship, research methods, and practices. "The seminar aims to introduce students to a range of methodologies relevant to human rights research, to put them in touch with ongoing human rights research by faculty and leading experts in the field, and to give them an opportunity to discuss this material in a small, interdisciplinary group context,” said Jacqueline Bhabha, director of the Harvard University Committee on Human Rights Studies (UCHRS). Conceived and developed by UCHRS committee members, the course is one of many Harvard initiatives to celebrate the 60th anniversary of the Universal Declaration of Human Rights. The seminar is led by Cosette Creamer, a Ph.D. candidate in the Department of Government and a J.D. candidate at Harvard Law School. "For me... the most rewarding aspect of teaching this seminar is what I hope is also the most rewarding aspect for the students: a broadened perspective on how to think about conducting human rights research," Creamer said. Entry to the seminar was determined by a competitive application process in September. The group numbers 24 students from a variety of concentrations, including government, history and literature, social studies, and biology. Sara O’Rourke ’09, a social studies concentrator, applied to the seminar to "learn about the dominant discourse and literature on human rights, and to meet other students whose work has to do with human rights." She is interested in women’s rights, current issues facing Islam, and the relationship between international and domestic law. On alternate Thursday evenings, Creamer and students like O’Rourke gather to discuss various aspects of human rights scholarship. They have addressed ways to conceptualize human rights, how human rights norms develop, and the relationship between advocacy and scholarship. The class has also considered sociological, anthropological, and political science approaches to human rights research. "The study of human rights can play a key role in introducing students to ethical dilemmas, normative approaches to their resolution, and cutting-edge contemporary problems and research findings," said Bhabha. "This is an inherently interdisciplinary field which offers students a wide range of disciplinary methodologies and the possibility of engaging with urgent real-life issues in a way that is both academic and practical." The theoretical framework of the course is complemented by practical examples. Students read case studies from leading scholars and enjoy talks by practitioners and researchers whose work is shaping the field. In early November, for example, Tamara Kay, assistant professor of sociology in the Faculty of Arts and Sciences, presented her work on the ways in which Sesame Street International helps to promote human rights worldwide. Workshops with scholars and practitioners will continue in the spring. At the most recent course meeting on Nov. 20, the students discussed research methods with Beth A. Simmons, Clarence Dillon Professor of International Affairs and director of the Weatherhead Center for International Affairs. The group analyzed two chapters from Simmons’ forthcoming book, "Mobilizing for Human Rights: International Law in Domestic Politics" (Cambridge University Press, 2009). The text explores how the ratification of international treaties influences state behavior, to see if such treaties actually lead to better protection of human rights. Simmons uses both qualitative and quantitative analysis to evaluate issues such as equality for women, the prevalence of torture, and children’s rights. Simmons answered questions about how she came to the topic, why she chose certain case studies, and the challenges of approaching human rights research from a social science perspective. She also recounted the difficulties of translating, or "coding," qualitative descriptions of human rights violations into a quantitative system for statistical analysis. "I fully expect that this book will make people mad," she said. "There are those who will have a moral reaction—‘Why should we be quantifying human suffering? Is it not dehumanizing to cram this information into a regression?’ "I don’t want to belittle that point of view," she continued. “But my goal is to systemize the data as best we can to get a broad sense for what’s going on, so that we can add to—not supplant—the literature and accounts we have of individual cases of suffering. This will enable us to provide a different kind of reference." In addition to the workshops with scholars such as Simmons, the seminar also provides undergraduates the opportunity to present their own research projects. Many of the students are working on a junior essay, senior thesis, or independent project that is focused on human rights issues. O’Rourke, for example, is writing her thesis on the French Muslim Council, the official interlocutor between the Muslim community and the French state. She is exploring the politics of recognition and political representation in relation to national narrative. "It has been rewarding to have a place where I can discuss ideas with students from a variety of fields and with a variety of interests, but who all share a common foundation—a deep interest in human rights," said O’Rourke.

Team 'Chimerica' - Ferguson, Niall (Washington Post, 2008)
Future historians, I suspect, will look back on Saturday's anticlimactic G-20 gathering in Washington less as Bretton Woods 2.0 and more as a rerun of the London Economic Conference of 1933. Back then, representatives of 66 nations completely failed to agree on a concerted international response to the Great Depression. The fault lay mainly with the newly elected U.S. president, Franklin D. Roosevelt, who vetoed European proposals for currency stabilization. This time around, it wasn't the newly elected Democrat but the outgoing Republican who wielded the veto. Even before his counterparts reached Washington, President Bush made it clear that recent events had done nothing to diminish his faith in free markets and minimalist regulation. Over the weekend, it was the United States that resisted European calls for a new international regulatory body, opposed significant redefinition of the International Monetary Fund's role and showed no interest in the idea of a global stimulus package. A real opportunity has been missed. Just as happened in the 1930s, what began as an American banking panic has now escalated into a global economic crisis. And just as happened in the 1930s, a lack of international coordination has the potential to turn a recession into a deep and protracted depression. The problem that seems scarcely to have been discussed over the weekend is that each national government is currently responding to the crisis with its own monetary and fiscal measures. Some central banks have already slashed official rates to close to zero. Some treasuries have already launched multibillion-dollar bailouts and stimulus packages. The devil lies in the different timing and magnitudes of these measures. The absence of coordination makes it almost inevitable that we will see rising volatility in global foreign exchange and bond markets, as investors react to each fresh national initiative. The results could be nearly as disruptive as the protectionist measures adopted by national governments during the Depression. Now, as then, a policy of "every man for himself" would be lethal. At the heart of this crisis is the huge imbalance between the United States, with its current account deficit in excess of 1 percent of world gross domestic product, and the surplus countries that finance it: the oil exporters, Japan and emerging Asia. Of these, the relationship between China and America has become the crucial one. More than anything else, it has been China's strategy of dollar reserve accumulation that has financed America's debt habit. Chinese savings were a key reason U.S. long-term interest rates stayed low and the borrowing binge kept going. Now that the age of leverage is over, "Chimerica"— the partnership between the big saver and the big spender—is key. In essence, we need the Chinese to be supportive of U.S. monetary easing and fiscal stimulus by doing more of the same themselves. There needs to be agreement on a gradual reduction of the Chimerican imbalance via increased U.S. exports and increased Chinese imports. The alternative—a sudden reduction of the imbalance via lower U.S. imports and lower Chinese exports— would be horrible. There also needs to be an agreement to avoid a rout in the dollar market and the bond market, which is what will happen if the Chinese stop buying U.S. government bonds, the amount of which is now set to increase massively. The alternative to such a Chimerican deal is for the Chinese to turn inward, devoting their energies to "market socialism in one country," increasing the domestic consumption of Chinese products and turning away from trade as the engine of growth. Memo to President-elect Barack Obama: Don't wait until April for the next G-20 summit. Call a meeting of the Chimerican G-2 for the day after your inaugural. Don't wait for China to call its own meeting of a new "G-1" in Beijing. Niall Ferguson is a faculty associate of the Weatherhead Center; Laurence A. Tisch Professor of History, Department of History; and William Ziegler Professor of Business Administration, Business, Government, and the International Economy Unit, Harvard Business School.

Why It Won’t Happen: The improbability of an Indian Obama - Varshney, Ashutosh (Times of India Delhi, 2008)
On January 20, when Barack Obama is formally inaugurated as president, the US will have a tryst with destiny. As famously defined by Jawaharlal Nehru, a national tryst with destiny is “a moment...when an age ends, and when the soul of a nation, long suppressed, finds utterance”. Scholars of nationalism agree that the US was founded upon an ideology, not ethnicity or race. The ideology was contained in the Declaration of Independence of 1776. “We hold these truths to be self-evident”, it said, “that all men are created equal”. Europe, the Old World, was horribly tied up in feudal hierarchies. The New World would have political and social equality at its core. As a corollary, rising from below became the socalled American dream. In reality, however, the US has not fully lived up to this ideal. Indeed, the creed of political equality came entwined with a founding ambiguity. The founders did not abolish slavery, an institution diametrically opposed to equality. This original ambiguity has haunted the US. The election of Obama as president liberates America from its basic contradiction. It is a shining moment in the historical journey of American nationhood and a landmark moment for world history. No society has yet elected someone from its deepest subaltern trenches to the highest office of the nation. Obama is not a slave’s descendant, but he is African-American. It should be no surprise that an international debate about whether other nations can produce an Obama has begun. The debate in India, too, has been vigorous. Can Mayawati become India’s Obama? Can a Muslim be elected India’s prime minister? A Muslim PM would, indeed, be a celebratory landmark for Indian secularism, but that is not an exact comparison. No community of India has suffered more than the nation’s Dalits. Muslims have historically had a dualistic structure: a ruling class and an aristocracy on one side and a vast mass of poor on the other side. In significant ways, that dualism continues to this day: the Azim Premjis and Shah Rukh Khans on the one hand, and the teeming millions on the other. In contrast, no film and sports stars or business leaders have come from the Dalit community. Though not enslaved, at least in modern times, Dalits, much like the African-Americans, have been segregated, stamped upon, and treated shabbily. India also has a founding ambiguity. Our Constitution abolished untouchability, but it is still widely practised. A Dalit PM would constitute a true parallel to the election of Obama. Can India produce an Obama? Three great differences between India and the US make it unlikely. First, party establishments cannot easily be challenged until there are open intra-party elections for the leadership of political parties. American elections start with the primaries, allowing anyone in a political party to stake a claim to leadership. Lacking internal elections, India’s parties today are on the whole family properties. The partial exceptions are the BJP and CPM. But the BJP cannot easily have a leader not approved by the RSS. And the CPM is ruled by an unelected politburo. The Congress was historically based on internal elections, but with the exception of a feeble attempt in the 1990s, internal elections, suspended by Indira Gandhi in 1973, have not been restored. The institutional decay of India’s political parties means that rank outsiders, like Mayawati, tend to create new political parties, but it is well known that it is much harder to create a new nationwide political organisation than use an existing one. The competition between political parties in India is remarkably vigorous, but competition inside is its exact opposite. Second, the US has a presidential system, India a parliamentary one. Since a US president is elected by the whole nation, a presidential system creates a national political arena. Every presidential candidate has to think of how to lead the nation. In a parliamentary system, the electorate votes for an MP, but there is no national election for the PM. Only when a parliamentary system has two (or three) nationwide parties, as in the UK, do political leaders tend to compete the way American presidential candidates do. India does not have a two-party system. Third, to mobilise citizens for vote, one has to speak in a language that the citizens can understand. Political campaigns take place in a linguistic register. Until India becomes more or less fully literate and also bilingual, India’s primary political arenas will be linguistically diverse provincial units. As a result, state-level Obamas will emerge, but national-level Obamas will be extremely hard to come by. Mayawati is at best a provincial Obama, with one major difference. Obama never ran a campaign of bitterness and anger; he subscribed to post-racial politics. In contrast, before the current Brahmin-Dalit brotherhood phase began, Mayawati conflated the politics of dignity with the politics of revenge. Only movement politics, aimed at putting the various communities together, can tear down India’s institutional constraints. The freedom movement was the last great movement that built unity in India. It produced impressive national political leaders. The JP movement in the 1970s presented an alternative version of national unity, but it could not really take off. The Advani-led rath yatra was also one of the biggest movements of 20th century India. But it did not unite; it only divided. Until such time as India’s political parties become more internally democratic, a national level two-party system emerges, or strong movements of national unity come to the scene, India’s national leaders will continue to come from party establishments, not from the lower reaches of society.

Along With Trials, Iraq Needs Truth - Philpott, Daniel (Boston Globe, 2008)
The trial of Saddam Hussein will likely result in his execution. Thus satisfied will be the Greek goddess of justice. Blind, with scales in her hand, she balances evil with justice, dollar for dollar, punishment equaling debts. It was her signature principle—retributive justice—that animated the trials of Nazi war criminals at Nuremberg, and trials following war, dictatorship, and genocide in Yugoslavia, East Germany, Greece, Argentina, and Rwanda. Only retribution for the ancient regime, claim the defenders of trials, can establish the rule of law in Iraq under its new Constitution. But trials have their limitations. Politically they often backfire. Erich Honecker, the deposed premier of communist East Germany, arrived at his trial in the newly unified Germany pumping his fist in the air, decrying victors' justice—and became more popular for it. Trials rarely succeed in prosecuting more than a fraction of major perpetrators, even when they are lengthy and expensive. The International Criminal Tribunal for Rwanda has spent more than $1 billion over eight years to produce 20 convictions—out of 125,000 alleged genocidaires awaiting trial. Political pressures frequently undermine verdicts. Due process, legal procedures, and adversarial incentives often hinder the public revelation of the truth about past injustices. Under pressure for a speedy execution, Saddam's prosecutors may exclude from their case his colossal massacres of Shi'ites and Kurds, thus inhibiting their public exposure. Most of all, trials will contribute little to the chief US foreign policy goal of a stable, democratic regime. The persistent hindrance is hatred. Historical wounds fester between Sunnis and Shi'ites, Kurds and Arabs, Islamists and secularists, and now Iraqis and Americans, breaking out in continual attack, revenge, and counter-revenge. Steps forward—elections, rebuilt institutions, and a new Constitution—seem constantly checked by steps backward—assassinations, detonations, and proliferating jihadi factions. Trials are unlikely to assuage these wounds. In fact, news reports indicate that Saddam's trial is already pitting his sympathizers against his avowed enemies—yet another source of division. What is needed is a dulcet in the din, a strong antidote to communal violence. Where might such medicine be found? One source of hope lies in a truth commission, a body charged by a state to investigate its past. Roughly 30 countries have turned to this solution in dealing with their own troubled histories. Arising from the rhetoric is an ancient principle found in Jewish, Christian, and Muslim scriptures: reconciliation. Connoting the restoration of right relationship, reconciliation provides a blueprint for dealing with the past. It begins by publicly acknowledging the suffering of thousands of victims of political violence. One of the remarkable themes to emerge from truth commissions in South Africa, Guatemala, El Salvador, and East Timor was victims finding healing through public testimony. Recent interviews with ordinary Iraqis find them welcoming just such an opportunity to speak publicly about the injustices that they and their loved ones have suffered at the hands of the state and to discover the truth about injustices that the state has hidden. The same exposure of deeds can foster accountability for perpetrators and assist trials. Truth commissions even encourage apology and forgiveness. Following the publication of the final report of Chile's truth commission, President Patricio Aylwin called for nationwide repentance for injustices committed during the dictatorship of Augusto Pinochet. Enjoined by the Koran, apology and forgiveness might also be realized in Iraq. For entire societies, truth commissions create a public historical record. The report of Argentina's truth commission, Nunca Mas ("Never Again"), became a bestseller on the streets. Perpetrators are thereby denied the lies through which they vindicate and reempower themselves, and new regimes are founded on truth and accountability. To realist ears, reconciliation sounds remote from the necessities of sandbags, M-16s, and barbed wire. But to sound the principle is not to expect a utopian reconciliation of all with all. It is rather to urge a set of practices that can begin to heal the social divisions that now endanger a new regime. On this logic, many Iraqis have called for a truth commission, including a broad consensus of Iraqi citizens interviewed for a report of the International Center for Transitional Justice. As history's schisms roil on, their plea emerges not merely as an alternative concept of justice but also as sound foreign policy.

America needs realists, not William Kristol - Walt, Stephen M. (Salon.com, 2008)
In its response to letters protesting the recent hiring of hard-line neoconservative William Kristol as a weekly Op-Ed columnist, the New York Times described the decision as the result of a "long and thoughtful process" by a paper committed to "vibrant political discourse." Editorial page editor Andrew Rosenthal said critics of the move were being "intolerant" and complained about a "weird fear of opposing views." Hiring Kristol did not bring an "opposing view" to the Times' Op-Ed page, of course, because columnist David Brooks already represents the same worldview that Kristol does. Nor does the Times' roster of liberal pundits provide a full complement of "opposing views." Most liberal commentators share the neocons' belief that it is America's right and responsibility to exercise "global leadership," even when that role involves the aggressive use of American military power and constant interference in other countries' affairs. The Times' Thomas Friedman was an energetic supporter of the Iraq war until it went south, and Nicholas Kristof is a passionate advocate of U.S. intervention in Darfur. Columnists like Maureen Dowd and Frank Rich have been sharply critical of the neoconservatives' worst follies, but both proceed from the familiar liberal internationalism that has characterized the American foreign policy establishment for many years. Even now, neoconservatives do not lack other mainstream outlets for their ideas. Charles Krauthammer, Robert Kagan, Fred Hiatt and Jonah Goldberg appear regularly on the editorial pages of the Washington Post or Los Angeles Times, and prominent neocons routinely publish in the Wall Street Journal, the Washington Times and the New York Sun. Not to be outdone, the supposedly liberal Boston Globe publishes neocon Jeff Jacoby twice a week. The neoconservative outlook is ubiquitous in journals of opinion like the New Republic, Commentary or Kristol's own Weekly Standard and is regularly heard on major radio and TV talk shows. Even National Public Radio and Comedy Central give neoconservatives a platform with surprising frequency. What's missing in America's mainstream media is the voice of realism. As the label implies, realists think foreign policy should be based on the world as it really is, rather than what we might like it to be. Realists see international politics as an inherently competitive realm where states constantly compete for advantage and where security is often precarious. But realists understand that being overly alarmist and aggressive can get states into just as much trouble as being excessively trusting or complacent. So realists keep a keen eye on the balance of power, but they oppose squandering blood or treasure on needless military buildups, ideological crusades, or foolish foreign wars. Realists cherish America's commitment to democracy and individual liberty, but they know that ideals alone are no basis for conducting foreign policy. They also understand that endless overseas adventures will inevitably provoke a hostile backlash abroad and eventually force us to compromise our freedoms here at home. Such views are hardly heretical, but there is not a single major columnist, TV commentator or radio pundit who consistently presents a realist perspective on world politics and American foreign policy. In America today, the mainstream media is a realism-free zone. The exclusion of realism is surprising for three reasons. First, realists enjoyed distinguished positions in the American foreign policy community in the past and remain a respected group today. Prominent statesmen whose views generally reflected a realist approach include the late George Kennan, Henry Kissinger, Zbigniew Brzezinski, Colin Powell, Richard Haass and Brent Scowcroft, as well as politicians like outgoing Sen. Chuck Hagel and current Secretary of Defense Robert Gates. To give a realist regular space on a major Op-Ed page is hardly like hiring a Maoist, a Scientologist or a die-hard World Federalist. Second, realists are an important constituency in the academic world. Realism is still the dominant paradigm in the academic study of international politics, and the writings of realist scholars like E.H. Carr, Hans J. Morgenthau and Kenneth Waltz have cast a long and lasting shadow over the academic landscape. One would think editors and publishers would be eager to hire someone whose views reflected that distinguished intellectual tradition. Third, realism's track record as a guide to foreign policy is quite impressive, especially when compared to the neocons' catalog of blunders. Morgenthau, Waltz and Kennan were among the first to recognize that the Vietnam War was a foolish diversion of American power, and Waltz was one of the few foreign policy experts who understood the Soviet Union was a Potemkin colossus with feet of clay. When assorted hawks were sounding frantic alarms about Soviet dominance in the late 1970s, Waltz was writing that the real issue was whether the Soviets could hope to keep up with the far wealthier and more powerful United States. The 1980s proved they couldn't, and that Waltz and his fellow realists had been essentially correct. Realism has done rather well since. Liberals and neoconservatives greeted the end of the Cold War by proclaiming the "end of history" and imagining a long era of peaceful American hegemony, but realists foresaw that the end of the Cold War would unleash new forms of security competition and produce new tensions within existing alliances. And when both hawks and doves foresaw a difficult and bloody battle in the 1990-91 Gulf War, realist scholars like Barry Posen of MIT and John Mearsheimer of the University of Chicago wrote articles that correctly predicted America's easy victory. Most important, realists were among the most visible opponents to America's more recent misadventure in Iraq. In September 2002, for example, 33 international security scholars paid for an ad in the New York Times declaring "War With Iraq Is Not in the U.S. National Interest." About half of the signatories were prominent realists, and several others wrote articles before the war explaining why it was unnecessary and unwise. By contrast, it was the neocons who conceived and promoted the Iraq war, while many prominent liberals endorsed it. Surely Americans deserve to hear from a perspective that has been an accurate guide to recent events, instead of relying on pundits who have been consistently wrong. A realist would provide readers with insights that have been largely absent from mainstream discussion for a decade or more. Realism emphasizes that states defend their interests vigorously and that successful diplomacy requires give-and-take; that advancing our own interests often requires us to do business with regimes whose values we find objectionable; that nationalism is a powerful force and most societies resist when outsiders try to tell them how to run their own affairs; that global institutions can be useful tools of statecraft but require great power support to work effectively; and that even well-intentioned democracies sometimes do foolish and cruel things. Most important of all, a realist would emphasize that military force is a blunt and costly instrument whose ultimate effects are unpredictable, and that it should be employed only when vital interests are at stake. In short, a realist would be a valuable antidote to the self-righteous hubris that pervades contemporary U.S. commentary on foreign affairs, an attitude that has encouraged many of the policies that have undermined America's image around the globe. A realist would also cast a skeptical eye on virtually all of the current presidential candidates, whose views on foreign policy do not stray far from the current neoconservative/liberal consensus. Realists aren't infallible and some readers will undoubtedly object to their views, but that's hardly the issue. The point is that Americans would be better informed if they regularly heard what realists had to say, and media institutions that are genuinely interested in presenting a diverse array of views should be signing up a few of them.

Israel's False Friends - Walt, Stephen M.; Mearsheimer, John (Los Angeles Times, 2008)
U.S. presidential candidates aren't doing the Jewish state any favors by offering unconditional support. Once again, as the presidential campaign season gets underway, the leading candidates are going to enormous lengths to demonstrate their devotion to the state of Israel and their steadfast commitment to its "special relationship" with the United States. Each of the main contenders emphatically favors giving Israel extraordinary material and diplomatic support—continuing the more than $3 billion in foreign aid each year to a country whose per capita income is now 29th in the world. They also believe that this aid should be given unconditionally. None of them criticizes Israel's conduct, even when its actions threaten U.S. interests, are at odds with American values or even when they are harmful to Israel itself. In short, the candidates believe that the U.S. should support Israel no matter what it does. Such pandering is hardly surprising, because contenders for high office routinely court special interest groups, and Israel's staunchest supporters—the Israel lobby, as we have termed it—expect it. Politicians do not want to offend Jewish Americans or "Christian Zionists," two groups that are deeply engaged in the political process. Candidates fear, with some justification, that even well-intentioned criticism of Israel's policies may lead these groups to turn against them and back their opponents instead. If this happened, trouble would arise on many fronts. Israel's friends in the media would take aim at the candidate, and campaign contributions from pro-Israel individuals and political action committees would go elsewhere. Moreover, most Jewish voters live in states with many electoral votes, which increases their weight in close elections (remember Florida in 2000?), and a candidate seen as insufficiently committed to Israel would lose some of their support. And no Republican would want to alienate the pro-Israel subset of the Christian evangelical movement, which is a significant part of the GOP base. Indeed, even suggesting that the U.S. adopt a more impartial stance toward the Israeli-Palestinian conflict can get a candidate into serious trouble. When Howard Dean proposed during the 2004 campaign that the United States take a more "evenhanded" role in the peace process, he was severely criticized by prominent Democrats, and a rival for the nomination, Sen. Joe Lieberman, accused him of "selling Israel down the river" and said Dean's comments were "irresponsible." Word quickly spread in the American Jewish community that Dean was hostile to Israel, even though his campaign co-chair was a former president of the American Israel Public Affairs Committee and Dean had been strongly pro-Israel throughout his career. The candidates in the 2008 election surely want to avoid Dean's fate, so they are all trying to prove that they are Israel's best friend. These candidates, however, are no friends of Israel. They are facilitating its pursuit of self-destructive policies that no true friend would favor. The key issue here is the future of Gaza and the West Bank, which Israel conquered in 1967 and still controls. Israel faces a stark choice regarding these territories, which are home to roughly 3.8 million Palestinians. It can opt for a two-state solution, turning over almost all of the West Bank and Gaza to the Palestinians and allowing them to create a viable state on those lands in return for a comprehensive peace agreement designed to allow Israel to live securely within its pre-1967 borders (with some minor modifications). Or it can retain control of the territories it occupies or surrounds, building more settlements and bypass roads and confining the Palestinians to a handful of impoverished enclaves in Gaza and the West Bank. Israel would control the borders around those enclaves and the air above them, thus severely restricting the Palestinians' freedom of movement. But if Israel chooses this second option, it will lead to an apartheid state. Prime Minister Ehud Olmert said as much when he recently proclaimed that if "the two-state solution collapses," Israel will "face a South African-style struggle." He went so far as to argue that "as soon as that happens, the state of Israel is finished." Similarly, Israel's deputy prime minister, Haim Ramon, said earlier this month that "the occupation is a threat to the existence of the state of Israel." Other Israelis, as well as Jimmy Carter and Anglican Archbishop Desmond Tutu, have warned that continuing the occupation will turn Israel into an apartheid state. Nevertheless, Israel continues to expand its settlements on the West Bank while the plight of the Palestinians worsens. Given this grim situation, one would expect the presidential candidates, who claim to care deeply about Israel, to be sounding the alarm and energetically championing a two-state solution. One would expect them to have encouraged President Bush to put significant pressure on both the Israelis and the Palestinians at the recent Annapolis conference and to keep the pressure on when he visits the region this week. As Secretary of State Condoleezza Rice recently observed, settling this conflict is also in America's interest, not to mention the Palestinians'. One would certainly expect Hillary Clinton to be leading the charge here. After all, she wisely and bravely called for establishing a Palestinian state "that is on the same footing as other states" in 1998, when it was still politically incorrect to use the words "Palestinian state" openly. Moreover, her husband not only championed a two-state solution as president but he laid out the famous "Clinton parameters" in December 2000, which outline the only realistic deal for ending the conflict. But what is Clinton saying now that she is a candidate? She said hardly anything about pushing the peace process forward at Annapolis, and remained silent when Rice criticized Israel's subsequent announcement that it planned to build more than 300 new housing units in East Jerusalem. More important, both she and GOP aspirant Rudy Giuliani recently proclaimed that Jerusalem must remain undivided, a position that is at odds with the Clinton parameters and virtually guarantees that there will be no Palestinian state. Sen. Clinton's behavior is hardly unusual among the candidates for president. Barack Obama, who expressed some sympathy for the Palestinians before he set his sights on the White House, now has little to say about their plight, and he too said little about what should have been done at Annapolis to facilitate peace. The other major contenders are ardent in their declarations of support for Israel, and none of them apparently sees a two-state solution as so urgent that they should press both sides to reach an agreement. As Zbigniew Brzezinski, a former U.S. national security advisor and now a senior advisor to Obama, noted, "The presidential candidates don't see any payoff in addressing the Israel-Palestinian issue." But they do see a significant political payoff in backing Israel to the hilt, even when it is pursuing a policy —colonizing the West Bank—that is morally and strategically bankrupt. In short, the presidential candidates are no friends of Israel. They are like most U.S. politicians, who reflexively mouth pro-Israel platitudes while continuing to endorse and subsidize policies that are in fact harmful to the Jewish state. A genuine friend would tell Israel that it was acting foolishly, and would do whatever he or she could to get Israel to change its misguided behavior. And that will require challenging the special interest groups whose hard-line views have been obstacles to peace for many years. As former Israeli Foreign Minister Shlomo Ben-Ami argued in 2006, the American presidents who have made the greatest contribution to peace—Carter and George H.W. Bush—succeeded because they were "ready to confront Israel head-on and overlook the sensibilities of her friends in America." If the Democratic and Republican contenders were true friends of Israel, they would be warning it about the danger of becoming an apartheid state, just as Carter did. Moreover, they would be calling for an end to the occupation and the creation of a viable Palestinian state. And they would be calling for the United States to act as an honest broker between Israel and the Palestinians so that Washington could pressure both sides to accept a solution based on the Clinton parameters. Implementing a final-status agreement will be difficult and take a number of years, but it is imperative that the two sides formally agree on the solution and then implement it in ways that protect each side. But Israel's false friends cannot say any of these things, or even discuss the issue honestly. Why? Because they fear that speaking the truth would incur the wrath of the hard-liners who dominate the main organizations in the Israel lobby. So Israel will end up controlling Gaza and the West Bank for the foreseeable future, turning itself into an apartheid state in the process. And all of this will be done with the backing of its so-called friends, including the current presidential candidates. With friends like them, who needs enemies?

What about austerity? - Domínguez, Jorge I.; Enriquez, Juan (Boston Globe, 2008)
Within the billions of sentences about the financial bailout there is one word notably absent, austerity. All talk is of payments, supports, subsidies, incurring more debt, stimulus packages. The thesis seems to be: If only we spend more the party can go on. True, only if the financial meltdown is a temporary mismatch and dislocation in housing and credit markets. But suppose there is something fundamentally wrong with the US economy. Then spending more will not fix it. Getting the diagnosis right means getting the treatment right. It may save us a trillion or two. The subprime collapse is one symptom of years of little regulation, under-taxing, overspending, and massive debt. One way to understand what is happening in the United States is to look at what occurred time and again in Latin America and Asia, hotbeds of financial and banking crises. What we are living through happened time and again in Brazil, Argentina, and Mexico, as well as Korea and Thailand. If there is too much debt, people lose confidence in the banks, then credit markets, currency, and government. For more than a decade, the international financial cop, the International Monetary Fund, forecast a hurricane was heading toward US shores. As did many heads of the treasury and the Fed. It is, to paraphrase a great writer, a chronicle of an agony foretold. There are five basic drivers of these crises, all based on excess: high income concentration, too much debt, too much reliance on foreign money, not enough tax revenue, and reckless government spending. Time after time governments believe they are different. They are bombarded by warnings but ignore, postpone, spend even more, and crash. Over past decades, most US wages have fared poorly. Despite stagnant wages, consumer spending and debt increased, fueled by cheap credit. Companies also went on a debt binge. Careless deregulation allowed financial cowboys to run the system. Responsible CEOs who kept some cash, maintained moderate debt, invested for the long term, got pink slips. Financial chop shops did leveraged buyouts using a company's own cash and credit. To survive, companies piled on debt. Many politicians decided reelection depended on cutting taxes and offering more benefits. Increase Medicare, postpone Social Security reform, hire more bureaucrats, and pay for a two-front war. Debt grew to pay for this party. These were not true tax cuts, just postponed debt; now we owe more and the bill has come due with interest. Complicating this crisis is US economic hegemony. There were few places to park a lot of money. Despite the euro, European policies on debts and deficits are not much to brag about. So foreigners have gorged on US debt. The United States continues importing more than it exports. Middle Easterners and Asians who save and invest bought dollars for decades, but some of this money is now fleeing. The dollar has dropped sharply. Gold and oil have skyrocketed. In financial crises, huge pools of capital cross borders very quickly; a few can make a great deal of money shorting the country's currency. The United States requires a massive restructuring to address its debt, cutting back on its borrowing, spending, and wars. The bailout package is essential to keep the credit markets open. But absent sentences that include the word austerity all the bailout will accomplish is a temporary postponement. Bailout and stimulus are a stopgap. A solution requires the country to begin to spend what it earns, reduce its mountainous debt, and address massive liabilities, restructure Social Security, pension deficits, military, and Medicare. No wonder politicians would rather spend more of your money now rather than address these problems. Because we have been spending 5 to 7 percent more each year than we earn, a forced restructuring, triggered by a currency collapse, would have the same effect on wages and purchasing power that the housing collapse had on housing prices. So let's learn from our Latin and Asian friends and act before it is too late. Juan Enriquez, managing director of Excel <org idsrc="CDNX" value="MEV"></org>Medical Ventures, is author of "The Untied States of America: Polarization, Fracturing, and Our Future." Jorge Dominguez is vice provost for international affairs and a professor of Mexican and Latin American Politics and Economics at Harvard University.

Why Islam Lies at the Heart of Iraq's Civil War - Toft, Monica Duffy (Christian Science Monitor, 2008)
It matters what we call things. It took too long for the Bush administration to admit that its intended liberation of Iraq had become an occupation, that US forces faced a home-grown insurgency there, and that a transition to Iraqi democracy might not result in a nation that supports US interests. Finally, not until 2007 did the Pentagon acknowledge that Iraqi sectarian violence had crossed a threshold to become a civil war. But policymakers still haven't come to terms with the implications of that fact. If they did, they'd see that a wisely executed withdrawal of US-led forces could well be the surest path to peace. That's because withdrawal is likely to transform the fighting in Iraq into a defensive struggle for power in a nation-state, as opposed to an offensive battle rooted in religion. The evidence overwhelmingly suggests that the war in Iraq is a religious civil war and that—even putting aside Al Qaeda in Iraq—Islam is at the heart of it for three reasons. First, Iraq's Sunnis and Shiites themselves see the war in these terms. They identify first and foremost as Shiites and Sunnis. Second, they use religious identity both to target opponents and define threats. Finally, they have appealed beyond the borders of Iraq for aid—fighters, arms, cash—in religious terms. Islam is not based in a specific territory; it is a transnational faith that unites its community, or umma, in the minds of men. Further, Islam does not have one leader who can dictate what is right or who is wrong. The absence of an ultimate authority figure means that Shiites—who, unlike Sunnis, believe that religious scholars are needed to help interpret the will of God—often latch on to charismatic imams. This helps explain why the cleric Moqtada al-Sadr has recently committed himself to further religious study in Iran. It also helps to explain why Iraqi Prime Minister Nouri al-Maliki will fail to gain acceptance as a leader among the vast majority of Iraq's Shiite population. Not only does Mr. Maliki not have support in the street—his government's failure to deliver even basic security and life's needs is apparent to most Iraqis—but he has no religious credentials of his own to fall back on. By contrast, Mr. Sadr's ability to deliver security and services through his Mahdi Army, and his authority as cleric and the son of the martyred Grand Ayatollah Mohammed al-Sadr, has assured him a devoted following. Sectarian conflict in Iraq was previously limited to fighting between Sunnis and Shiites. But today, the conflict has grown to include Shiites against fellow Shiites. Despite signs that security has improved, the religious civil wars in Iraq may have only just begun. My research on civil wars from 1940 to 2000 highlights three important facts about such wars, all of which apply to Iraq. First, nearly half of all ongoing civil wars (46 percent) involve religion in some form. Second, Islam has been involved in more than 80 percent of all religious civil wars. Third, religious civil wars are less likely to end in negotiated settlement. Instead, combatants tend to duke it out until one side achieves victory. In Iraq, a negotiated settlement is going to be very difficult for two reasons. First, the Shiites will want to remain in almost complete control due to two entirely legitimate concerns: (1) fears of Sunni repression as experienced in the past, and (2) a sense of majority-rule justice. Second, the Shiites themselves are divided on how Iraq should be ruled, so it's difficult to know whom to bargain with on the Shiite side, and therefore who can credibly commit to abide by the terms of any settlement. What then can the United States and its allies do to bring about a negotiated settlement? Ironically, the best way to support a negotiated settlement would be to leave Iraq. The withdrawal of US forces would allow Iraq's predominantly Arab Shiites and Sunnis to find common interest in opposing their two more classical historical adversaries: Kurds and Persians. The longer the US and Britain stay, the more they facilitate a shift away from the identity that long unified Iraq to the religious identity that is tearing it apart and facilitating its manipulation by Iran. There are three obvious downsides to this approach. First, the end of violence in Iraq following a US withdrawal would lead to the emergence of a nonsecular, nondemocratic government in Iraq. It would be more friendly toward Iran (though not Iran's puppet, as currently feared), but less friendly toward Israel, although a democratic Iraq would be no improvement in this regard. Second, since US withdrawal has been conditioned on a de-escalation of violence in Iraq, the Bush and Brown governments would be left the unenviable task of explaining to their countries that "withdrawal is the best way to create the conditions for, withdrawal." Third, withdrawal before violence has fully ceased will look like failure to most Americans and Britons. The idea of victory versus failure is really a false dichotomy, however. The real choice for US and British policymakers is between the more costly failure that will obtain from current policy and the less costly failure that might obtain from a well-thought-out and well-executed withdrawal.

Bush's doomed Mideast peace efforts - Sheehan, Edward R. F. (Boston Globe, 2008)
President Bush does not seem to know it yet, but his peace plan for the Middle East is moribund. That is my chief impression from a recent three-month journey through the troubled region. A viable Palestinian state will not exist by the time Bush leaves office. Nor will one exist, probably, in the predictable future—not least because of the failures of US policy. Cynicism prevails among Palestinians, and Israelis also. Azmi Bishara, a prominent Palestinian intellectual, decries what he calls “the Palestine settlement industry—that inexhaustible source of quasi-initiatives [and] pseudo-dialogues” that after 41 years of harsh Israeli occupation have led nowhere. To virtually every Palestinian I talked to, Bush's peace process has become a black comedy. To them, Secretary of State Condoleezza Rice has become a forlorn figure, frequently flying to Jerusalem to entreat the Israelis to remove roadblocks and cease building settlements in the West Bank and East Jerusalem, and then the Israelis blithely do the opposite. Palestinian Authority President Mahmoud Abbas in his grandfatherly way has become a nearly pathetic figure—regarded by his own people as an American stooge, dependent on the United States to pay his huge bureaucracy, and constantly disappointed by Bush's refusal to pressure Israel. The Israeli government is split between Prime Minister Ehud Olmert and Defense Minister Ehud Barak, the stronger of the two. Olmert fears for the future of Israel as a Jewish state under Palestinian demographic pressure and favors some sort of peace deal, but he will soon resign from office on accusations of corruption. Barak is leisurely in cracking down on settlements and wants to delay a final deal indefinitely. Israeli peace advocates complain that the army in effect has a veto over Olmert and slows down or sabotages civilian orders to remove roadblocks and settlement outposts. Even if an accord is achieved before Bush leaves office, it will probably be no more than a cloudy declaration of goals that would take many years to implement. Olmert has admitted that no agreement on the division of Jerusalem can be reached this year. Bush has done little to satisfy the Palestinians who entrusted their fate to November's Annapolis declaration, which promised “every effort” to conclude an agreement on a two-state solution before the end of 2008. At the White House in April, Abbas told Bush that when the Palestinian negotiators saw the latest Israeli proposals, they laughed. According to the eminent Israeli analyst Akiva Eldar, Olmert and his foreign minister Tzipi Livni demanded all of East Jerusalem except the Temple Mount, much of the Jordan Valley except for a walled enclave around Jericho, and the retention of all settlement clusters, such as Ariel in the heart of the West Bank. The territory reserved for the Palestinians would be a patchwork of Bantustans cut off from Jerusalem with no continuity, no sovereignty, and subject still to incursions by the Israeli Army. A referendum containing such limitations would inevitably be rejected by the Palestinian population. A struggle resumes? When the peace process collapses, as seems so likely, the broad Palestinian struggle will probably resume. Dr. Mustafa Barghouti, the dynamic physician who heads the Palestinian National Initiative, told me in Ramallah that he hopes the struggle will be Gandhian and peaceful. But Nasser al-Qudawi, Yasser Arafat's nephew, thinks not. “The resistance will resume,” Qudawi told me, “but it will bring more splintering of Palestinian society, more extremism, and more blood.” In the West Bank, Hamas and Islamic Jihad may flourish. Will Hamas fire rockets at Israel from the West Bank? Hamas and Islamic Jihad militants have launched thousands of primitive Qassam rockets from the Gaza Strip into southern Israel since 2000, killing 17 Israeli civilians, wounding scores, and destroying much property. Yet more than 2,000 Palestinian civilians, many of them children, have been killed by Israeli retaliatory attacks, and it is heart-rending to tour tiny Gaza and witness the devastation. In the north of the Gaza Strip sits a lake of human waste. It exudes the stench of excrement and is threatening to burst because the Israelis have rationed the importation of cement. The waste seeps into the ground of Gaza and pollutes the aquifers, causing rampant diarrhea and infestations that afflict children most. At Khan Younis near the sea, buildings chopped in half by Israeli bombs are still inhabited, and laundry hangs from the ruins. A man named Ahmed, who has lost a leg, invites me upstairs into his flat to meet his wife and 10 children. The ceiling sags. “Aren't you afraid it will collapse?” I ask. “We have nowhere else to go," he answers. Since Hamas chased Abbas's secular government out of Gaza in June 2007, it has governed the Strip untainted by the Fatah faction's corruption and with modest benefits to the population of 1.5 million. Women feel compelled to wear the veil, the sexes are rigidly separated, and the judiciary can be severe. Sharia law has not been officially introduced, but the trend is toward more Islamization. The Internet is monitored for pornography, but Hamas has cracked down on more radical Islamist groups that have attacked Internet café's. The police seem everywhere, but they have generally imposed order. Hamas's rivalry with Fatah remains savage. Despite recent efforts at reconciliation, blood continues to be shed between them. The role of Hamas Sheikh Ahmed Yassin, the mystical quadriplegic who founded Hamas, said that the fate of Israel must be left to the will of God and future generations of Palestinians. But in June 2006 Prime Minister Ismail Haniyeh declared Hamas's willingness to sign a document jointly with all Palestinian factions that it accepts Israel's existence. Hamas will not formally recognize Israel, preferring to offer only a hudna, a truce of 10 or even 30 years. But Hamas would accept a negotiated settlement between Israel and the Palestinian Authority that produces an independent Palestinian state on the pre-1967 borders. Israel and the United States have shunned Hamas until it explicitly recognizes Israel, and they have discouraged Abbas from negotiating with it. Bush regards Hamas not as a government but as purely a terrorist organization, as if any peace could be achieved by excluding more than a third of the Palestinian people. Barak believes that in good time and by brute force he can emasculate Hamas and crush its governance of Gaza. Yet in mid-June, Israel accepted a cease-fire of six months in Gaza mediated by the Egyptians. The agreement won Israel a reprieve from Qassam rockets, and Hamas a suspension of Israel's military attacks and an easing of its economic blockade of Gaza. The deal was acclaimed in the Arab world, and deplored in Israel, as a victory for Hamas. Hamas did not surrender in Gaza; its crude rockets forced Israel to sue for calm. To Palestinians, Hamas proved its creed that Israel understands only the language of force. Not only have Israel and the United States failed to topple the Hamas government, but Hamas has forced Israel to deal with it—even as President Abbas has achieved so little in his negotiations with Israel. The Israelis fear that Hamas will use the calm to regroup its militia of perhaps 15,000 men and import more arms, and they may be right. The asymmetrical warfare between Israel and Hamas may continue in cycles, periods of quiet interspersed with periods of great violence and attrition, for many years. The Palestinians of Gaza have proved their capacity to absorb suffering. Though the West Bank is more bourgeois, it may come to do likewise under the banner of resistance. Many secular Palestinian intellectuals have despaired of a two-state solution and have resumed their old dream of a unitary, democratic state for Jews and Arabs in all of historical Palestine. But there might still be a meager chance of achieving a two-state solution, depending on the will of the next US president. Will he exert effective pressure not only on the Palestinians to end all violence, but on Israel to evacuate the settlements and retreat substantially to the borders of 1967? Should he do so, he will need also to create a formula to include Hamas in the solution if he truly wants peace. Paradoxically, the key to peace may be held by Hamas. Edward R.F. Sheehan is a former fellow of Harvard's Weatherhead Center for International Affairs.

India's Global Ambition and the Nuclear Deal - Miller, Manjari (Christian Science Monitor, 2008)
Unlike China, India doesn't have a clear vision for its role in the world. For three decades, India has craved a nuclear energy deal that would bring prestige and advanced technology. Yet when the coalition government declared this week that it would move ahead with one, it triggered a crisis and a no-confidence motion in Parliament, which it had to scramble to survive. Watching this drama unfold, the international community may be forgiven for feeling a little baffled. After all, the landmark Indo-US nuclear deal is immensely advantageous for India. It allows India to buy nuclear technology from the US in exchange for abiding by International Atomic Energy Agency safeguards. It would give India's growing economy much-needed energy without endangering its strategic capabilities or influencing its sovereignty in foreign policy. To understand the political anguish and hand-wringing in India over a nuclear deal with the US, one needs to understand a very simple fact. Unlike China, its rival rising power, India lacks a grand strategy or concept of its role in the world. India thinks it should be a great power but has no clear vision of its path. In contrast, China thinks it is a great power and expends a great deal of time and energy outlining its "peaceful rise" to itself and the world. China's rise on the world stage is constantly discussed by Chinese academics, journalists, policy experts, political leaders, and the elite. This discourse emphasizes that despite China's growing power and the need for resources and markets, it will not pursue militarization and hegemony as Germany and Japan did before and during World War II. Rather, it intends to rise peacefully and harmoniously. Simultaneously, this idea draws on the concept of tianxia ("all under heaven") which, simply put, promotes order over chaos and has been key to understanding governance in China for the past 2,000 years. With defined ideas of the world and their role in the world, China acts like a confident great power and pursues its international goals with single-minded zeal. The last time India had a defined concept of its international role, Jawaharlal Nehru was the prime minister. Nehru made some notable foreign policy mistakes, particularly his disastrous Forward Policy that resulted in the 1962 war and bitter defeat at the hands of China. But there is no doubt the man was a visionary. Designed by Nehru, the Non-aligned Movement (NAM) was a domestic and international triumph for India. It was poor, struggling to develop economically and militarily, but there was a sense of purpose and national pride that it had, at least, cornered the moral market in international relations and assumed the leadership of the developing nations. Post Nehru and post cold war, India failed to adapt or abandon NAM, even when it had little significance. Nor, unlike China after Mao, did any Indian leader articulate an alternate ideology of the world and India's role in it. It is, therefore, not surprising that such bitter ideological divisions now exist in India. What is the way forward for India as a would-be great power? Does signing a nuclear deal with the US make its old antagonist its new BFF? Does it mean that even paying lip service to the long-obsolete idea of NAM is no longer possible? Or does great power mean, as the communists suggest, proudly rejecting the nuclear deal and thereby showing the international community who's boss? Even as the nuclear deal steams ahead, unless India articulates a vision for itself and gains the confidence of a great power, such splits will continue to plague its international relationships and negotiations. Manjari Chatterjee Miller is a post-doctoral fellow at the Woodrow Wilson School at Princeton University and an affiliate of the Weatherhead Center for International Affairs at Harvard University. She is working on a book about Indian and Chinese foreign policy.

Russia can play a vital role in the west’s security - Maurizio Massari (Financial Times, 2008)
The enlargement of NATO to include Georgia and Ukraine could become the most dangerous spoiler in relations between Russia and the west next year. It would also set the new US president off to a bad start. If NATO’s foreign ministers were to decide in December that the two former Soviet republics were ready for the membership action plan and if Russia retaliated by freezing its relations with the alliance, that would create a lose-lose situation for everybody—for NATO, for Russia and, ultimately, also for Kiev and Tbilisi. An already nationalistic Russia would fall prey to its fear of being encircled again and it would dangerously isolate itself from the west. The alliance, in turn, would revert to its 20th-century raison d’être—containing an increasingly hostile Russia—instead of focusing on more crucial tasks, including its adaptation to the new security challenges. This would further exacerbate the rifts within the European Union over its Russia policy. But in a different scenario, could Georgia’s and Ukraine’s legitimate aspiration to join the alliance turn a potential spoiler into a win-win situation for both NATO and Russia? Yes, it could, but only if both sides show political courage. Contrary to today’s received wisdom, Georgia’s and Ukraine’s wish to join the alliance could provide the right conditions for two positive developments: NATO could at last shake off its legacy as a cold war and anti-Russian alliance; and a new mindset could take hold in Russia, involving a vision of security based on co-operation, not on competition or on spheres of influence. How can this be achieved? A strategy based on three elements could work. First, the US, NATO, Russia, the EU and the Organization for Security and Co-operation in Europe should forge a new compact jointly to manage security threats in their common neighbourhood, which stretches from Ukraine, through the Caucasus to Central Asia (an area whose geostrategic importance has grown as a result of the conflict in Afghanistan). The group of these organizations would share responsibility for combating common threats in the area, ranging from terrorism to Islamic fundamentalism, to drug-trafficking and organized crime. They would also commit themselves to finally resolving the frozen conflicts in Transnistria, Abkhazia and Nagorno-Karabakh. Russia has been resentful of the west since the end of the cold war, claiming that it is unfairly treated as a junior partner and demanding formal recognition as an equal. A new security compact would grant Russia that status: the sharing of power between Russia, the EU, NATO, the US and the OSCE would go hand in hand with shared responsibility for “securing security”. The new compact should complement these institutions, not replace them. Second, within this new co-operative security framework Russia would shelve its opposition to Georgia and Ukraine accessing the membership access plan. In fact, if NATO becomes part of a larger, co-operative security framework in which Russia is an equal partner, Moscow should have nothing to fear from Georgian or Ukrainian membership. Indeed, Moscow would benefit from the fact that NATO membership would encourage its two neighbors to become more responsible regional players. Russia would thus boost its legitimacy in the eyes of the “new” Europe, which still mistrusts it and sees it as a sovereign democracy bent on denying sovereignty to others. Finally, in return for Russia shelving its opposition to the membership access plan, both Georgia and Ukraine would commit to negotiating new bilateral pacts of friendship and co-operation with Russia to consolidate trust. Implementing such a strategy depends on both the west and Russia showing the political will to do so. In just over a year we will celebrate the 20th anniversary of the end of the cold war. What better way could there be to dispel the tensions between Russia and the west than to work together in addressing the common challenges of the 21th century? A US-Russia-NATO-EU-OSCE summit and the signing of a new Eurasian security charter could help to consign this hangover from the past to the archives and allow us to start afresh. It is high time that happened. A reformulation of the terms of security co-operation between the west and Russia in their common neighbourhood would also bode well for future co-operation in other hot areas, with Iran and Afghanistan heading the list.

The Rich Get Hungrier - Sen, Amartya (New York Times, 2008)
Will the food crisis that is menacing the lives of millions ease up—or grow worse over time? The answer may be both. The recent rise in food prices has largely been caused by temporary problems like drought in Australia, Ukraine and elsewhere. Though the need for huge rescue operations is urgent, the present acute crisis will eventually end. But underlying it is a basic problem that will only intensify unless we recognize it and try to remedy it. It is a tale of two peoples. In one version of the story, a country with a lot of poor people suddenly experiences fast economic expansion, but only half of the people share in the new prosperity. The favored ones spend a lot of their new income on food, and unless supply expands very quickly, prices shoot up. The rest of the poor now face higher food prices but no greater income, and begin to starve. Tragedies like this happen repeatedly in the world. A stark example is the Bengal famine of 1943, during the last days of the British rule in India. The poor who lived in cities experienced rapidly rising incomes, especially in Calcutta, where huge expenditures for the war against Japan caused a boom that quadrupled food prices. The rural poor faced these skyrocketing prices with little increase in income. Misdirected government policy worsened the division. The British rulers were determined to prevent urban discontent during the war, so the government bought food in the villages and sold it, heavily subsidized, in the cities, a move that increased rural food prices even further. Low earners in the villages starved. Two million to three million people died in that famine and its aftermath. Much discussion is rightly devoted to the division between haves and have-nots in the global economy, but the world’s poor are themselves divided between those who are experiencing high growth and those who are not. The rapid economic expansion in countries like China, India and Vietnam tends to sharply increase the demand for food. This is, of course, an excellent thing in itself, and if these countries could manage to reduce their unequal internal sharing of growth, even those left behind there would eat much better. But the same growth also puts pressure on global food markets—sometimes through increased imports, but also through restrictions or bans on exports to moderate the rise in food prices at home, as has happened recently in countries like India, China, Vietnam and Argentina. Those hit particularly hard have been the poor, especially in Africa. There is also a high-tech version of the tale of two peoples. Agricultural crops like corn and soybeans can be used for making ethanol for motor fuel. So the stomachs of the hungry must also compete with fuel tanks. Misdirected government policy plays a part here, too. In 2005, the United States Congress began to require widespread use of ethanol in motor fuels. This law combined with a subsidy for this use has created a flourishing corn market in the United States, but has also diverted agricultural resources from food to fuel. This makes it even harder for the hungry stomachs to compete. Ethanol use does little to prevent global warming and environmental deterioration, and clear-headed policy reforms could be urgently carried out, if American politics would permit it. Ethanol use could be curtailed, rather than being subsidized and enforced. The global food problem is not being caused by a falling trend in world production, or for that matter in food output per person (this is often asserted without much evidence). It is the result of accelerating demand. However, a demand-induced problem also calls for rapid expansion in food production, which can be done through more global cooperation. While population growth accounts for only a modest part of the growing demand for food, it can contribute to global warming, and long-term climate change can threaten agriculture. Happily, population growth is already slowing and there is overwhelming evidence that women’s empowerment (including expansion of schooling for girls) can rapidly reduce it even further. What is most challenging is to find effective policies to deal with the consequences of extremely asymmetric expansion of the global economy. Domestic economic reforms are badly needed in many slow-growth countries, but there is also a big need for more global cooperation and assistance. The first task is to understand the nature of the problem. Amartya Sen, is the Chair, Project on Justice, Welfare, and Economics, a Weatherhead Center Faculty Associate, and Thomas W. Lamont University Professor, Department of Economics, Harvard University.

Sitting Down at the Nuclear Table with Iran - Allison, Graham T., Jr. (Boston Globe, 2008)
IN A SPEECH this week, Iran's supreme leader found himself in rare agreement with President Bush. Echoing Bush's judgment that nuclear terrorism is "the single most serious threat to American national security," Ayatollah Ali Khamenei warned that, "sooner or later, international terrorists will get their hands on nuclear weapons and bring the security of the world…to an end." Bush has insisted that "for the sake of peace, the world must not allow Iran to have a nuclear weapon." Unfortunately, however, as a result of the failure of the Bush administration's strategy toward Iran, today Tehran stands seven years further down its path to nuclear weapons than it did on Jan. 20, 2001. Specifically, when Bush entered office, Iran had no operational uranium enrichment facilities. Today, as last month's International Atomic Energy Agency report documents, Iran is operating 3,492 centrifuges in a cascade that has produced 500 pounds of low-enriched uranium. This is one-third of what is required for Iran's first nuclear bomb. The Bush administration's strategy to prevent Iran's mastering technology for enriching uranium and producing nuclear weapons has been characterized as a "diplomatic slow squeeze." The administration has hoped that UN Security Council resolutions isolating Iran, enforced by sanctions, would persuade Tehran to suspend enrichment activity. Ironically, the IAEA chose Memorial Day to inform its member governments that for the third time, Iran has stiffed the demands of the Security Council resolution. In baseball, it's three strikes and you're out. After the undeniable failure of the third Security Council resolution imposing sanctions to slow Iran's nuclear program, Bush's Iran strategists should recognize that they have struck out. Hoping to divert attention from this record, the Bush administration has further confused the issue with exaggerated rhetorical attacks on those who advocate an alternative strategy of direct diplomacy including negotiations. Speaking to the Israeli Knesset on the 60th anniversary of Israel's creation, Bush accused proponents of negotiations with unfriendly regimes of "appeasement." More diplomatically, but equally pointedly, in addressing the American Israel Public Affairs Committee this week, Secretary of State Condoleezza Rice called for another dose of the same medicine the administration has been prescribing, and sought to shift the blame to Iran, asserting that "The real question is: Why won't Tehran talk to us?" Facts are only obliquely relevant to political debate. But for the record, the charge of appeasement leveled against British Prime Minister Neville Chamberlain focused not on his willingness to talk, but on his unwillingness to act. In the run-up to World War II, negotiation was not the issue. The question was whether Britain and France would act when Adolf Hitler violated Germany's Versailles Treaty commitments. Winston Churchill criticized the governments for capitulating when Hitler remilitarized the Rhineland, arguing that if they had responded, "There is no doubt that Hitler would have been compelled by his own General Staff to withdraw.…They had only to act to win." Instead, a confident Hitler went on to absorb Austria, and after Munich, Czechoslovakia. If Bush recognized the fact that his diplomatic squeeze has failed, and asked what he could do in his final eight months to advance US interests in relations with Iran, he would not have to look beyond his own Cabinet. In a 2004 report titled "Iran: Now is the Time for a New Approach," Defense Secretary Robert Gates urged that "the United States deal with the current regime rather than wait for it to fall." When asked about this recommendation during recent testimony on the Hill, Gates noted that he had been "in a happier place" then. But it is clear that Gates remains convinced that direct negotiations are imperative for solving the nuclear standoff. As he told the Academy of American Diplomacy last month, "We need to figure out a way to develop some leverage…and then sit down and talk with them." Negotiations are never certain to yield results. The alternative, a world of nuclear anarchy, is of great concern to both nations. Having seen the results of seven years of nonengagement, Bush could do his successor—whether Democrat or Republican—a great favor by proposing to negotiate with Iran now. Graham Allison is a Weatherhead Center Faculty Associate; Douglas Dillon Professor of Government and Director, Belfer Center for Science and International Affairs, John F. Kennedy School of Government, Harvard University.

It's not the price that causes hunger - Paarlberg, Robert L. (International Herald Tribune, 2008)
International prices of rice, wheat and corn have risen sharply, setting off violent urban protests in roughly a dozen countries in Asia, Africa and Latin America. But is this a "world food crisis?" It is certainly a troubling instance of price instability in international commodity markets, leading to social unrest among urban food-buyers. But we must be careful not to equate high crop prices with hunger around the world. Most of the world's hungry people do not use international food markets, and most of those who use these markets are not hungry. International food markets, like international markets for everything else, are used primarily by the prosperous and secure, not the poor and vulnerable. In world corn markets, the biggest importer by far is Japan. Next comes the European Union. Next comes South Korea. Citizens in these countries are not underfed. In the poor countries of Asia, rice is the most important staple, yet most Asian countries import very little rice. As recently as March, India was keeping imported rice out of the country by imposing a 70 percent duty. Data on the actual incidence of malnutrition reveal that the regions of the world where people are most hungry, in South Asia and Sub-Saharan Africa, are those that depend least on imports from the world market. Hunger is caused in these countries not by high international food prices, but by local conditions, especially rural poverty linked to low productivity in farming. When international prices are go up, the disposable income of some import-dependent urban dwellers is squeezed. But most of the actual hunger takes place in the villages and in the countryside, and it persists even when international prices are low. When hunger is measured as a balanced index of calorie deficiency, prevalence of underweight children and mortality rates for children under five, we find that South Asia and sub-Saharan Africa in 2007 had hunger levels two times as high as in the developing countries of East Asia, four times as high as in Latin America, North Africa or the Middle East, and five times as high as in Eastern Europe and Central Asia. The poor in South Asia and sub-Saharan Africa are hungry even though their connections to high-priced international food markets are quite weak. In the poorest developing countries of Asia, where nearly 400 million people are hungry, international grain prices are hardly a factor, since imports supply only 4 percent of total consumption—even when world prices are low. Similarly in sub-Saharan Africa, only about 16 percent of grain supplies have recently been imported, going mostly into the more prosperous cities rather than the impoverished countryside, with part arriving in the form of donated food aid rather than commercial purchases at world prices. The region in Africa that depends on world markets most heavily is North Africa, where 50 percent of grain supplies are imported. Yet food consumption in North Africa is so high (average per capita energy consumption there is about 3,000 calories per day, comparable to most rich countries) that increased import prices may cause economic stress for urban consumers (and perhaps even street demonstrations) but little real hunger. Import dependence is also high in Latin America (50 percent for some countries) but again high world prices will not mean large numbers of hungry people, because per capita GDP in this region is five times higher than in sub-Saharan Africa. There is a severe food crisis among the poor in South Asia and sub-Saharan Africa, but it does not come from high world prices. Even in 2005 in sub-Saharan Africa, a year of low international crop prices, 23 out of 37 countries in the region consumed less than their nutritional requirements. Africa's food crisis grows primarily out of the low productivity, year in and year out, of the 60 percent of all Africans who plant crops and graze animals for a living. The average African smallholder farmer is a woman who has no improved seeds, no nitrogen fertilizers, no irrigation and no veterinary medicine for her animals. Her crop yields are only one third as high as in the developing countries of Asia, and her average income is only $1 a day. One third of these poor African farmers are malnourished. In part because of the added burden of climate change, the number of undernourished people in Africa is now expected to triple by 2080, whatever the level of prices on the world market. The long-term solution to such problems is not lower international prices or more food aid, but larger investments in the productivity of farmers in Africa. African governments essentially stopped making these investments 25 years ago, when the international donor community pulled back from supporting agricultural modernization in the developing world. Over the past two decades the U.S. Agency for International Development has cut its support for agricultural science in Africa by 75 percent. World Bank lending for agriculture has dropped from 30 percent of bank lending in 1978 to just 8 percent. In 2005, the World Bank president at the time, Paul Wolfowitz, told a business forum: "My institution has largely gotten out of the business of agriculture." This may be changing, and if high world food prices help speed the change, so much the better. In a recent interview, the new World Bank president, Robert Zoellick, said he planned to raise agricultural lending to Africa next year from $450 million to $800 million. Since 2006, the Bill and Melinda Gates Foundation has also begun to focus more of its grant-making on the needs of poor smallholder farmers in Africa through an Alliance for a Green Revolution in Africa (AGRA) chaired by Kofi Annan. These are encouraging initiatives, because the productivity of farms in Africa—not food prices on the world market—should be the long-term focus. Robert Paarlberg, professor of political science at Wellesley College, is the author of Starved for Science: How Biotechnology is Being Kept out of Africa.

Turkey's Constitutional Crisis—From Lose-Lose to Win-Win - Martin, Lenore G. (Middle East Progress, 2008)
The March 31, 2008 decision of Turkey’s Constitutional Court to hear a case that could bring down the governing Justice and Development Party (also known in Turkey as AKP) has provoked a constitutional crisis. The Court must decide if their allegedly anti-secular activities warrant shutting down the AKP and/or banning Prime Minister Erdogan, President Abdullah Gul and sixty-nine members of the party from politics for five years. The Court has banned other parties and politicians from politics in the past, including the previous two Islamist parties. This case, however, represents an increased threat to the democratic process and a thwarting of the popular will. The moderate Islamist AKP received 47 percent of the popular vote in the elections of July 2007, giving it a parliamentary majority and entitling it to run the government. Shutting down the party and banning its leaders from politics could set off political and economic turmoil in Turkey. Anticipated reactions range from potentially violent popular protests that could invite intervention by the Turkish military to a set back for Turkey’s economic recovery and further cause for the Europeans to block Turkey’s accession to the European Union. The Court is also considering a ban on the Kurdish political party, the Democratic Society Party (DTP). If both the DTP and AKP (which garnered a large number of Kurdish votes) are kept out of politics, this could increase support amongst Turkey’s Kurds for the Kurdistan Workers Party (PKK). Turkey desperately needs to address the Kurdish issue in its southeast and the PKK terrorism emanating from northern Iraq. This constitutional crisis diverts the governmental efforts needed to address those issues. Political chaos in Turkey could also upset U.S. foreign policy objectives in Iraq and the greater Middle East. The administration has only recently begun to repair the relations with the republic that were ruptured over the Iraq war. Washington has shared intelligence over PKK havens in northern Iraq and permitted limited military intervention to root them out. The United States needs a stable Turkey that can cooperate with respect to the war in Iraq, Iranian nuclear proliferation and other issues affecting Gulf security. This crisis has its roots in the very foundation of the Turkish Republic. Its founding father, Kemal Ataturk, promoted the principle of secularization in order to further the goal of modernizing the new Turkish state. The Turkish military considers itself the guardian of this Kemalist concept of a secular state. It has not hesitated to take action against what it views as the increasing Islamization of Turkish politics under the majority rule of the AKP. The AKP first achieved majority rule in 2002. Even though it won only 34 percent of the popular vote, AKP gained a parliamentary majority because of the peculiarities of the Turkish electoral system. Among those who voted for the Justice and Development Party were people who were not necessarily Islamist but were seeking an alternative to the allegedly more corrupt, ineffective and splintered secular political parties. The AKP subsequently sought to consolidate its position of power by electing then Foreign Minister Gul as President of Turkey. The Turkish military opposed this move and attempted an “electronic coup” by issuing an online statement warning against Gul’s election. This backfired. In a showdown with the military, Prime Minister Erdogan won the elections in July 2007 and secured Gul’s election as President of the Republic. What spurred the public prosecutor to bring the case to the court was his belief that the AKP was using its parliamentary majority to aggressively promote an Islamist agenda. The AKP-led parliament has passed legislation allowing women to wear headscarves in universities. It has also unsuccessfully attempted to allow students who attend secondary religious schools (Imam Hatip schools) to more easily enter the general university system. Other actions by AKP-dominated municipalities include the banning of alcohol and the separation of men and women in parks and at festivities. The prosecutor is concerned that the AKP will be able to amend the constitution to allow the accelerated Islamization of Turkish politics. Ironically, by bringing the case, the prosecutor put the Constitutional Court in an untenable position. The Court has the power to impose the harsh remedy of shutting the AKP and its politicians out of the political process. It could also impose a lesser remedy of limiting state funding for the party. If it orders the ban, the Court will be viewed as interfering with the will of the people and the deepening of Turkish democracy. If it orders a lesser remedy, it will be viewed as approving the AKP’s actions. Whatever the Court’s ruling, AKP politicians may gain even greater popular support as happened when the military challenged it in 2007. The immediate solution to this lose-lose situation is for the Court to fashion a compromise remedy that will restrain what the prosecutor believes is the AKP’s aggressive pursuit of an Islamization agenda, while at the same time permitting it to participate in the Turkish political arena. The real answer to Turkey’s crisis is to be found in its political system. A compromise judicial outcome would enable a longer-term win-win solution. The constitutional crisis should sound a wake-up call to the opposition political parties in Turkey; they need to reform themselves and Turkey’s political system. Party leaders are autocrats who make all financial decisions and choose the candidates who run for office. The main opposition party, the Republican Peoples Party, in particular, needs to reform its leadership if it seeks to regain its credibility in the Turkish polity. Turkey’s opposition parties need to overcome their divisive politics and structure a coalition that has both the platform and the grassroots organization that can challenge what many see as the Islamization of Turkish politics, by democratic contest in the political arena and not by judicial or military intervention.

Consumers Want to Do the Right Thing - Schorow, Stephanie (Harvard University Gazette, 2008)
Data suggest buyers willing to pay more to humane producers. A majority of consumers want to do the right thing. That is, in numerous studies, consumers say that they are willing to pay more for products produced under good working conditions, rather than those that come from sweatshops. But what consumers say and what they actually do when they pull out their wallets at the cash register is not as clear. Michael J. Hiscox, professor of government, has been developing models to test actual consumer behavior when shoppers are confronted with a choice to buy a higher-priced item certified as produced under good conditions and cheaper items that are not so designated. Preliminary results suggest that, indeed, consumers are willing to pay a premium if they believe that a product is made under good working conditions, Hiscox said during a Feb. 28 seminar sponsored by the Mossavar-Rahmani Center for Business and Government at the John F. Kennedy School of Government. More research is needed, but “if this holds up, it’s pretty compelling evidence,” Hiscox told his audience during his talk on “Consumer Demand for Labor Standards: Experiments with Ethical Labeling of Imported Products.” Hiscox, author of the Riker Prize-winning book “International Trade and Political Conflict” (2002), draws his conclusions from innovative study methods he and graduate students have devised over the past three years. One such study was conducted in a major home goods retail store in New York City in 2005 with two products: candles and towels. Hiscox created special labels that indicated that an item was “made under fair labor conditions, in a safe and healthy working environment which is free of discrimination, and where management has committed to respecting the rights and dignity of workers.” These labels were posted on one set of candles and one set of towels—when, in reality, all the candles and towels in the displays were produced under good conditions. The labeled towels and candles were priced higher than unlabeled items, and the prices changed over time. Hiscox’s crew also switched labels at key points to the previously unlabeled products. The result: “Sales rose for items labeled as being made under good labor standards, and demand for the labeled product actually rose with the price increases of 10 to 20 percent above pretest (unlabeled) levels,” according to Hiscox’s paper on his work. Moreover, a higher price on a labeled towel seemed to actually stimulate demand. The higher price might be telling shoppers it’s a better product,” Hiscox said. They think, “Aha! The label is credible because I have to pay more for the goods.” Still, the study was done in a high-end shop in a company with a known commitment to fair practice. The items may have had “snob appeal” to wealthy consumers already predisposed to buy ethical items. What about consumers really looking for a bargain? So Hiscox turned to one of the biggest bargain-hunting markets in the world: eBay. Hiscox’s team devised auctions around two items, gourmet coffee and polo shirts. All were produced under good conditions and all were extremely similar in presentation. (“It’s very good coffee,” Hiscox added.) But one set of coffee beans was labeled as “fair trade” and the other as “premium.” One set of shirts was described as “ethically made” while the other had no designation. And again, “eBay shoppers were willing to pay a substantial premium for goods certified by label” as produced under fair standards,” Hiscox said. The results were, however, more dramatic for coffee than for the shirts. Perhaps, suggested moderator F.M. Scherer, professor of public policy and corporate management emeritus, eBay shoppers are more “world-oriented,” a possibility that Hiscox conceded. What, asked Jack Waxman, a master’s student in public policy, would happen to fair-trade markets in an economic downturn? “Yes, that’s a fear,” Hiscox said. Jennifer Kurz, also a master’s student in public policy, wondered if products produced under good conditions would really—in the long run—cost more. “Maybe certification doesn’t increase prices,” she said. It’s a possibility, Hiscox said. Perhaps healthy workers operating under safe conditions are actually more efficient, thus increasing productivity and lowering prices, he said. “It’s a really inherently open question.” Hiscox cautioned against basing any business decisions on these initial results. More studies are needed, he said. “At the moment there’s a prior question: Is there even a market for this that would support the expansion of these [socially accountable] systems? We don’t know that,” he said. “Before you start championing, “‘This is the answer,’ you have to know whether or not it’s feasible.”

A 'declaration of principles' for the Mideast - Kelman, Herbert C. (Boston Globe, 2008)
HAIM RAMON, a vice prime minister of Israel, recently stated that Israel hoped to reach agreement with its Palestinian negotiating partners by the end of 2008 on a "declaration of principles" for peace, but not on a detailed peace treaty. At this time of escalating violence and diminishing hope, the call for such a declaration offers an opportunity for revitalizing the Israeli-Palestinian peace process. To represent a dramatic breakthrough, a declaration would have to go beyond a vague, general commitment to a two-state solution, and lay out the fundamental principles on which such a solution must be based if it is to be perceived as fair and just by the two populations and offer them a positive vision of their future relationship. The statement must address the key final-status issues - notably borders, Jerusalem, settlements, and refugees - that a viable two-state agreement would have to resolve. In essence, the statement would frame the envisaged final agreement as a principled peace, based on a historic compromise that meets the fundamental needs of both peoples, validates their national identities, and declares an end to the conflict and to the occupation consistent with the requirements of fairness and attainable justice. To concretize the components of a statement of basic principles for framing a negotiated agreement, I offer the following hypothetical draft of what such a statement, issued by the two leaderships, might contain, in the hope that it might stimulate thought. Israeli-Palestinian joint statement of principles The parties agree that the land that has been in dispute between the Jewish and the Palestinian peoples - the land that includes the State of Israel and the occupied territories (the West Bank and Gaza) - belongs to both peoples: both have historic roots in it, both are deeply attached to it, and both claim it as their national homeland. We are convinced that there is no military solution to the conflict resulting from these competing claims. The attempt to impose a solution by violence has caused pain and suffering to both peoples for generations, which we deeply regret. The conflict threatens to destroy the future of both peoples and of the land itself. We are therefore committed to ending the conflict by negotiating a principled peace, based on a historic compromise in the form of a two-state solution. We agree to share the land in a way that allows each people to exercise its right to national self-determination, express its national identity, and fulfill its national aspirations in its own independent, viable state within the shared land. The details of a peace agreement that concretizes this historic compromise have to be negotiated, but we are committed to certain basic principles, dictated by the logic of the historic compromise, that must be followed in resolving the key issues in the negotiations. Specifically: The borders between the two states will follow the 1967 armistice lines, with minor, mutually agreed-upon adjustments, based on an exchange of West Bank territories that contain most of the Israeli settlements for Israeli territories of equal size and value, and with a secure link between the West Bank and Gaza. These borders are necessary in order to enable the Palestinian state to meet the criteria of true independence, viability, governability, and contiguity within the West Bank. Palestinians can accept the fairness of these borders because they conform with international legitimacy, as expressed in appropriate United Nations resolutions. Jerusalem will be shared by the two states and contain the national capital of each state, in recognition of the central importance of the city to the national identities of both peoples. Jerusalem's Jewish neighborhoods will be under Israeli sovereignty and its Arab neighborhoods under Palestinian sovereignty, with jointly administrated arrangements for security, freedom of movement, and municipal services for the entire city and for governance of the Old City. A plan of shared or joint sovereignty will be negotiated for the holy sites, allowing each side control over its own sites and assuring free access to them from both parts of the city. Israeli settlements with extraterritorial rights and status (including separate roads and protection by Israeli troops) will be removed from the Palestinian state in order to ensure the state's independence, viability, governability, and contiguity. The right of individual settlers to stay in place as Palestinian citizens or as resident aliens, subject to Palestinian law, will be negotiated. In negotiating solutions to the problem of Palestinian refugees, Israel recognizes that the refugee problem and the right of return are central to the Palestinian national identity and national narrative, and acknowledges its share of responsibility for the plight of the refugees. Concretely, the refugee problem will be addressed in all its dimensions, with comprehensive plans for financial compensation, regularization of the status of refugees in host countries, and resettlement when needed or desired. Refugees will be granted citizenship in and the right of return to the Palestinian state. Only a limited number, however, will return to Israel proper, in order to allow Israel to maintain its character as a Jewish-majority state. The final negotiated agreement, based on a historic compromise as reflected in the above principles, is designed to yield a principled peace, characterized by the following conditions: Mutual recognition of the national identity of the other people and of each people's right to express this identity in an independent state within the shared land. A sense that the agreement is not merely a product of the balance of power, but is consistent with the principle of attainable justice and with international law and the international consensus. Integration of both states in the region and the international community. As we commit ourselves to negotiating a final agreement based on the concept of a historic compromise and meeting the conditions of a principled peace, we are enabled to develop and to communicate to our publics a positive vision of a common future for the two peoples in the land they are agreeing to share. Our vision contemplates: A secure and prosperous existence for each society. Mutually beneficial cooperation between the two states and societies in various fields, including economic relations, public health, environmental protection, telecommunications, cultural and educational programs, and tourism. Regional development. Stable peace with ultimate reconciliation. Our positive vision extends not only to the future of the two peoples in their independent states within the land they are agreeing to share, but to the future of the shared land itself: a land to which both peoples are attached, even though each agrees to claim only part of it for its independent state. In this spirit, our vision of a common future includes freedom of movement across state borders, as well as a range of cooperative activities that treat the shared land as a unit and are designed to benefit it in its entirety. A joint statement of principles along the lines proposed above would reassure the two publics about the intentions of the other side and help to reestablish trust in the availability of a negotiating partner. By advocating a principled peace that acknowledges each side's national identity and national narrative, that conforms to the dictates of attainable justice, that provides a rationale for the concessions each side is expected to make, and that offers a positive vision of the future, it has the potential for energizing the two publics and eliciting their full support for the negotiated agreement on a two-state solution. Given the apparent readiness of the two leaderships to formulate a declaration of principles, the challenge now is to utilize this moment as an opportunity to create a visionary document that will reassure and energize the two publics and elicit their enthusiastic support for negotiating a historic compromise. Civil society efforts, in the form of unofficial Israeli-Palestinian dialogue, can be instrumental in generating ideas for such a document and conveying them to the political leadership. The US government and other third parties can contribute significantly by encouraging the parties to formulate a statement of basic principles and identifying the issues that it must address, keeping in mind that, in the end, the document must be crafted by the parties themselves in order to reflect their concerns and engender their commitment. Finally, to be maximally effective, movement toward and beyond the proposed joint statement of basic principles must be accompanied by significant changes in the conditions on the ground, designed to improve the security, economic well-being, quality of life, and personal dignity of the two populations. Herbert C. Kelman is a professor social ethics emeritus and cochairman of the Middle East Seminar at Harvard.

Africa's organic farms - Paarlberg, Robert L. (International Herald Tribune, 2008)
Approach any serious-looking college student in the Boston area, where I teach, and ask them what kind of food and farming system they would like to see. Most will say they don't want food from factory farms with a large carbon footprint. They want foods locally grown on small family farms. They don't want crops grown using synthetic chemical fertilizers or pesticides; they want crops grown "organically." They want farm animals to be able to range freely. They want "slow" food rather than fast food. And they don't want "Frankenfoods"—crops developed through genetic engineering. What might such an idealized food system actually look like? Take a trip to Africa. The small farmers who populate the continent's impoverished countryside are living out something close to this post-materialist fantasy. Two-thirds of all Africans depend on farming or animal grazing for their food and income, and nearly all of their operations are small-scale. Eighty percent of the labor on these farms is done by women and children, in part because it provides so little income for working-age men. There is no power machinery (only two tractors for every thousand agricultural workers) and only 4 percent of crops are irrigated. More than two thirds of all cropland is still planted with traditional crop varieties rather than with scientifically improved varieties. The animals—mostly cattle and goats—for age for their own food. Agribusiness firms are nowhere to be seen, and chemical fertilizer applications per hectare are less than one-tenth the industrial world average. Insecticides and herbicides are not affordable, so crops suffer pest damage, and the weeding is done by children who would be better off in school. Nobody grows genetically engineered crops because governments in Africa—following Europe's lead—have not approved such crops for use. Nearly all of Africa's farms are thus de facto "organic." Poor and non-productive, but organic. Africa's traditional rural food systems are definitely "slow." To serve maize meal (called nsima) to her family, an African woman must first spend a season planting, weeding, harvesting and storing her corn, then she must strip it, winnow it, soak it, lay it out to dry, carry it to a grinder or pound it by hand, dry it again, and finally—after walking to gather enough fuel wood—cook it over a fire. Cereal crop yields in Africa are only one-third as high as in developing Asia, and only one-tenth as high as the United States. Average income from this kind of farming amounts to only a dollar a day, which is why nearly 80 percent of all those officially classified as poor in Africa are farmers, and why one third of all farmers are chronically malnourished. Without modern agricultural science, food production in Africa has fallen ominously behind population growth. Total agricultural production per capita today has fallen 19 percent below the level of 1970. Increasingly, Africans must depend on imported food aid. Africa's urgent need for agricultural modernization is being rudely ignored. When elite urbanites in rich countries began turning away from science-based farming in the 1980s, external assistance for agriculture in poor countries was cut sharply. As late as 1980 the U.S. Agency for International Development was still devoting 25 percent of its official development assistance to the modernization of farming, but today it is just 1 percent. Nearly 30 percent of World Bank lending once went to agricultural modernization, but now it is just 8 percent. In Europe, meanwhile, some official donors and nongovernmental agencies are working to block farm modernization in Africa. Despite Africa's worsening soil nutrient deficits, European donors like to promote costly organic farming techniques as the alternative to chemical fertilizer use. This is not how European farmers escaped poverty. Only 4 percent of cropland in Europe is currently being farmed organically (and less than 1 percent in America), but European NGOs such as Friends of the Earth and Greenpeace tell Africa's poor this is the path they should follow. European governments and NGOs also promote regulatory systems that block the use of genetically engineered crops, including crops capable of resisting insects without pesticide sprays. Europe's own science academies have found no new risks to human health or the environment from any of the genetically engineered crops placed on the market so far, but since overfed Europe can do without this technology, underfed Africa is told to do the same. In this fashion, and perhaps without realizing it, wealthy countries are imposing the richest of tastes on the poorest of people. The rich are, in effect, telling Africa's farmers they should just as well remain poor. Robert Paarlberg is a professor of political science at Wellesley College in Massachusetts and the author of "Starved for Science: How Biotechnology is Being Kept Out of Africa" (Harvard University Press, March 2008).

The rebirth of American civic life - Putnam, Robert D. (Boston Globe, 2008)
In the mushrooming procedural debate about Democratic superdelegates and the uncontested Florida and Michigan primaries, more is at stake than the identity of the presidential nominee or even the Democrats' chances of victory in November. Primaries and caucuses coast to coast in the last two months have evinced the sharpest increase in civic engagement among American youth in at least a half-century, portending a remarkable revitalization of American democracy. But that rebirth of American civic life would be aborted if the decision rendered by millions of ordinary Americans could be overturned by a backroom deal among political insiders. The issue is not public jurisprudence or obscure party regulations or the alleged "wisdom" of party elders, but simple playground notions of fairness. Throughout the last four decades of the 20th century, young people's engagement in American civic life declined year after year with depressing regularity. In fall 1966, well before the full flowering of Vietnam War protests, a UCLA poll of college freshmen nationwide found that "keeping up with politics" was a "very important" goal in their lives for fully 60 percent. Thirty-four years later that figure had plummeted to 28 percent. In 1972, when the vote was first extended to 18-year-olds, turnout in the presidential election among 18- to 24-year-olds was a disappointing 52 percent. But even beginning at that modest level, rates of voting in presidential elections by young people steadily fell throughout the '70s, '80s, and '90s, reaching barely 36 percent in 2000. National commissions bemoaned the seemingly inexorable increase in youthful apathy and incivism. The National Commission on Civic Renewal said, "When we assess our country's civic and moral condition, we are deeply troubled... We are in danger of becoming a nation of spectators." Then came the attacks of Sept. 11, 2001, a national tragedy, but also a vivid reminder that we are all in this together. Civic seismometers across the land showed a sharp spike in virtually every measure of community-mindedness. It was, I wrote at the time, not only a tragedy, but also the sort of opportunity for civic revival that comes along once or twice a century. Just as Pearl Harbor had spawned the civic-minded "Greatest Generation," so too Sept. 11 might turn out to produce a more civically engaged generation of young people. For most Americans the half-life of the civic boomlet after the attacks was barely six months. Within a year measures of civic engagement had returned to the previous levels, from which they have barely budged since. Except among young people. Among the cohort of Americans caught by 9/11 in their formative years, the effects of the attacks on their civic consciousness were more enduring. The annual UCLA chart of interest in politics jumped upward in 2001 for the first time in decades and has kept rising every year since. Last month the UCLA researchers reported that "For today's freshmen, discussing politics is more prevalent now than at any point in the past 41 years." This and other evidence led us and other observers to speak hopefully of a 9/11 generation, perhaps even a "new Greatest Generation." In the 2004 and 2006 elections, turnout among young people began at last to climb after decades of decline, reaching the highest point in 20 years in 2006. As we approached the presidential season of 2008, young Americans were, in effect, coiled for civic action, not because of their stage of life, but because of the lingering effects of the unifying national crisis they had experienced in their formative years. The exceptionally lively presidential nominating contests of this year—and, it must be said, the extraordinary candidacy of Barack Obama—have sparked into white hot flame a pile of youthful kindling that had been stacked and ready to flare for more than six years. The 18-year-olds first eligible to vote in 2008 were in sixth grade when the twin towers fell, and their older sisters and brothers who were college seniors in September 2001 are now 28 or 29. It is precisely this group, above all others in America, that has pushed participation rates in this spring's caucuses and primaries to record levels. Turnout in this spring's electoral contests so far has generally been higher than in previous presidential nominating contests, but for twenty-somethings the rise has been truly phenomenal—turnout often three or four times greater than ever before measured. The 2008 elections are thus the coming-out party of this new Greatest Generation. Their grandparents of the original Greatest Generation were the civic pillars of American democracy for more than a half-century, and at long last, just as that generation is leaving the scene, reinforcements are arriving. Americans of every political persuasion should rejoice at this epochal swing of the generational pendulum, for it portends precisely the sort of civic renaissance for which Jeremiahs have been calling for many years. This, then, is what is at stake in the otherwise inside-baseball controversies about superdelegates and pledged delegates and the uncontested Florida and Michigan primaries—controversies now roiling Democratic party leaders. If the results of the caucuses and primaries are, despite record-breaking rates of popular participation, overturned by unelected (though officially legitimate) superdelegates or by delegates from states that all candidates had previously agreed not to contest, the lesson for the young civic stalwarts would be unmistakable—democratic politics is a sham. Politics is actually controlled by party bosses behind the scenes. Civic engagement is for suckers. From Little League to student council races, we all learn to accept defeats we have lost fair and square. But losing in a contest in which the rules can be rigged teaches that the game is not worth the candle. Who can honestly doubt that if the Democratic presidential candidate preferred by a majority of the delegates elected in this spring's competitive contests (and by the overwhelming majority of young voters) were to be rejected solely by the power of unelected delegates (or those "elected" without any serious competition), the unmistakable civics lesson would be catastrophic for this incipient cadre of super citizens? So as the superdelegates, the two campaigns, and Democratic Party leaders contemplate how to resolve the procedural issues before them - what to do about Michigan and Florida, and how superdelegates should vote—let's hope that they weigh the consequences not merely for their own candidates this year, and not merely for the Democratic prospects in the fall, but for the future vitality of American democracy. Robert D. Putnam, a professor of public policy at Harvard University's John F. Kennedy School of Government, is author of Bowling Alone: The Collapse and Revival of American Community and Better Together: Restoring the American Community.

Reading the Tea Leaves in Pakistan - Allison, Graham T., Jr. (Boston Globe, 2008)
Presdent Pervez Musharraf's stunning defeat in Monday's elections in Pakistan represents a decisive rejection of what his opponents called his policies of "subservience" to the United States. An American press that has been virtually unanimous in opposing Musharraf will now predictably call for his resignation in favor of "genuine democracy." Since this outcome is a possibility, it is essential to ask where a government that accurately reflects the views of Pakistani citizens would stand on issues that matter most to America. Would such a government follow Musharraf's lead as a grudging shot-gun ally? Recall that after the Sept. 11, 2001, attacks, as Musharraf tells the story, the United States gave him the choice of becoming an ally or being "bombed back to the Stone Age." How vigorously would a new democratic government support the US-led war on terrorism in which Pakistan's army is now fighting Al Qaeda and its affiliates headquartered in Pakistan's ungoverned Northwest Territories? Would such a government be more likely to cooperate with the United States and NATO in the ongoing but faltering war against the Taliban in Afghanistan? Recall again that the rise of the Taliban took place during the term of Musharraf's civilian predecessors, including Nawaz Sharif, the leader of one of the parties that won in Monday's election. The answer to each of these questions is as unambiguous as it is uncomfortable. A Pakistani government whose actions align with its citizens' views on these issues would be at loggerheads with the United States. Over the past year, polls have highlighted the sharp decline in Musharraf's popularity, with his approval ratings dropping to 15 percent in December. Several recent polls, including ones from the Pew Global Attitudes Project, the International Republican Institute, and Terror Free Tomorrow echo those sentiments, with one showing that 70 percent of Pakistanis "want Musharraf to immediately resign." But what most American commentators have missed is that however much Pakistanis dislike Musharraf, they are more hostile toward the United States. When asked to name the "single greatest threat" to their country, 64 percent of Pakistanis named the United States. Historic archrival India, with whom Pakistan has fought five bloody wars, was second, well behind America. Eighty-nine percent of Pakistanis said they disapprove of the US war on terrorism. Eight in 10 Pakistanis oppose allowing the United States to pursue Al Qaeda terrorists in their country. A similar percentage rejects US pursuit of Taliban forces into Pakistan. In opposing Musharraf, opposition parties called him "Busharraf" and accused him of being a "lackey" of the United States in the "so-called war on terrorism," which they say is a US-led war on Islam. The US military presence in Afghanistan, where earlier Pakistani governments were the primary sponsors of the Taliban, is opposed by 83 percent of Pakistanis. Critics of Musharraf's limited cooperation with the US-NATO campaign should recognize that a government that more closely followed the wishes of its people would be less cooperative in combating the Taliban. The United States has two vital national interests in Pakistan: first, to prevent any of Pakistan's nuclear arsenal and bomb-making materials from being stolen, sold or transferred to terrorists; second, to destroy Al Qaeda's leadership, sanctuary, and training camps. Neither interest will be advanced by a transition from the devil we know to the new democratic Pakistani government. Fortunately, Pakistan's nuclear weapons are secured by its army, the country's most effective national institution. Unless the army were destabilized or became substantially disaffected because of extended political instability, it will fulfill its custodial responsibilities. In contrast, a government that truly reflects the current views of the Pakistani people is more likely to be an unspoken opponent than an ambiguous ally in the US war against Al Qaeda and other terrorists in the region.Hard as it is to believe, Osama bin Laden is four times as popular among Pakistanis as President Bush, whose approval rating is 7.7 percent. That leading US opinion pages generally critical of Bush's democracy crusade in Iraq should now so uncritically promote democratic shock-therapy as a panacea for Pakistan's problems is puzzling. The inconvenient, painful truth is that a truly democratic Pakistan would be, at least in the foreseeable future, less inclined to act in ways that advance urgent American interests. Advocates of instant democracy should be careful what they wish for. Graham Allison Faculty Associate; Douglas Dillon Professor of Government and Director, Belfer Center for Science and International Affairs, John F. Kennedy School of Government, Harvard University

Moving forward in Kenya - Bowman, Warigia (Boston Globe, 2008)
The recent presidential election in Kenya has declined into a bloodbath with the deaths of more than 300 people, jeopardizing the nation and the stability and democracy in East Africa as a whole. Both the government and the opposition must authorize and support an independently directed recount of votes and begin a process of national reconciliation. The election, the most competitive in the country's history, began peacefully on Dec. 27. The Commonwealth Observer Group commended the Election Commission of Kenya for its professionalism. Early returns on Dec. 29 gave opposition leader Raila Odinga a lead of nearly a million votes. Vote counting was stopped by the election commission that day with 189 of 210 constituencies reporting. On Dec. 30, the election commission announced that in a mysterious overnight switch incumbent Mwai Kibaki had won by 231,728 votes. European Union observers have condemned the delay in releasing the final presidential result. In addition they have noted that there were irregularities in ballot numbers, and that the presidential election results are not credible. Further, at least four election commissioners have since come forth and asked for a full investigation into vote tampering. There is credible evidence that the elections were rigged. The current electoral violence in Kenya has historical roots. Kibaki was elected on a multiparty, multiethnic democratic ticket in 2002 promising to “sweep away” corruption and one-party rule. He presided over a renewal of the once moribund economy: Kenya grew 6.1 percent in 2006. Under Kibaki, the press became freer, and civil society flourished. Bill Clinton praised Kibaki for introducing free primary education throughout the country. Yet, Kibaki reneged early in his administration on a memorandum of understanding with the Liberal Democratic Party regarding governmental power sharing. Although the Kenyan economy grew at a rapid pace, so did economic inequality, resulting in a concentration of wealth in a small oligarchical elite, while most Kenyans earn less than $1 a day. Senior members of Kibaki's government resigned under a cloud of corruption and his anticorruption czar went into exile in fear for his life. In a sharp turnaround from his 2002 entry as a democratic reformer, Kibaki has behaved like an autocrat in the days after the election, muzzling live broadcasts by the private media, banning opposition protests, and allowing the police to fire live ammunition upon unarmed civilians. For the sake of the nation and the region, Kenya must move forward to a peaceful democratic transition. Kibaki should immediately unmuzzle the press, and allow the opposition to assemble peacefully in public. Church leaders, civil society, and international observers must urge the police to stop firing on innocent civilians. As urged by Nobel Peace Prize laureate Wangari Maathai, an independent recount of contested ballots is required. The African Union, the United Nations, and the Commonwealth Group should rapidly assist in convening an independent body of Kenyans from all backgrounds to conduct the recount. African figures with unassailable democratic credentials, such as Desmond Tutu of South Africa and John Kufuor of Ghana should work with all Kenyan political parties to form an interim unity government that can rule in a transition period. Crucially, Odinga, Kalonzo Musyoka, and other Kenyan leaders must help lower temperatures by tempering inflammatory rhetoric, participating in good faith in negotiations, and urging those who claim to be supporters of Odinga's Orange Democratic Movement to halt politically motivated violence. Finally, credible new elections for the position of president must be scheduled in the next six months. The violence we are seeing in Kenya is not ethnic or tribal; it is political and has deep roots in social and economic inequities that have deepened continuously since independence. For hundreds of years, 42 ethnic and linguistic groups have lived peacefully together in Kenya, with high rates of intermarriage, trade, and in-migration. This violence obscures deep social inequities in economic distribution that cross ethnic lines among all groups. For 40 years, Kenya has been as a haven for refugees and a broker for peace settlements, avoiding the type of wrenching violence that has torn neighbors Sudan, Rwanda, and Somalia apart while earning a reputation as the most democratic nation in the region. Without immediate efforts toward national reconciliation, and a recount of disputed ballots, Kenya risks descent into autocracy and civil war. Warigia Bowman is graduate student associate at the Weatherhead Center and a doctoral candidate at the John F. Kennedy School of Government, Harvard University.

Rothschild explores economics’ human side - Lavoie, Amy (Harvard University Gazette, 2008)
Blackmail and attempted murder are not typically studied as part of economic history. However, a credit crisis among 18th century French silk and brandy merchants led to just such dramatic incidents, the accounts of which piqued the interest of Emma Rothschild, a historian of economic life, empires, and Atlantic connections. Rothschild, Jeremy and Jane Knowles Professor of History in the Faculty of Arts and Sciences (FAS), has recently come to Cambridge, Mass., from Cambridge, England, where she has worked to facilitate interaction among historians, economists, and scholars from other disciplines, while maintaining rigorous historical methods within her own research. Rothschild is the director of the newly formed Joint Center for History and Economics (JCHE). In Cambridge, England, she co-founded the Centre for History and Economics at King’s College in 1991, which encouraged conversation among scholars from varying disciplines at a time when the world was changing in profound ways. The JCHE will similarly encourage such scholarly inquiry at Harvard. When she learned of the events surrounding a credit crisis among silk and brandy merchants that occurred in a small French town in 1769, Rothschild was intrigued. The merchants, when threatened with bankruptcy, struck back by accusing their lenders of usury. The incident had hitherto been studied as a footnote in the history of lending, but Rothschild was gripped by the story, which involved not only accounts of lending and interest, but also blackmail and attempted murder. It helped shift Rothschild’s area of interest within the study of the history of economic life. "[This] was a story of people’s lives that could be described in other terms than, ‘Was the market rate of interest the same as the natural rate of interest?’ or ‘What were the consequences for the French economy?’ It had to do with their sentiments about the economy, and I thought that was very interesting," says Rothschild. "Everyone has economic experiences, and the way that we think about them changes." While she is now living full time in Cambridge, Mass., Rothschild was already quite familiar with the area. She first came to Cambridge in 1967 to study economics with a strong interest in economic history, at the Massachusetts Institute of Technology (MIT). Later, from 1978 to 1988, she taught at MIT. She has been a part-time visiting professor at Harvard since 2004. Her marriage was also trans-Atlantic. She married Amartya Sen, Thomas W. Lamont University Professor, in 1991, and for a number of years the two commuted between the two Cambridges. The couple is now happy to be closer to Sen’s children, who live in the area. Rothschild’s most recent book is Economic Sentiments: Adam Smith, Condorcet and the Enlightenment (Harvard University Press, 2001). In her forthcoming book, The Inner Life of Empires, she traces the history of an 18th century Scottish family of seven brothers and four sisters called the Johnstones. The book is an expansion of a series of lectures that she gave in Princeton in 2006, as Tanner Lectures on Human Values. The Johnstone siblings were involved with the armed forces, politics, and the law, and they traveled widely—to Africa, North America, India, and the West Indies. Some were in the slave trade, to which others in the family were vehemently opposed. As they engaged in these activities, the family wrote letters, detailing their lives and their feelings about the changing world around them. They were also parties in a variety of legal disputes. Rothschild has been increasingly interested in the lives of the sisters, but as is often the case, information about women in the 18th century has been difficult to discover. "By centering on a particular family, I am trying to question the distinctions between the economic side of their life, the political side, and the legal side, because for them, they didn’t divide up events, and say, ‘This is an economic problem, and this is a legal problem.’ It becomes easier to think oneself into a world where these distinctions weren’t as clear," says Rothschild. The letters explored the moral implications of some of the family’s actions at a time when Britain was becoming an empire. In their own words, the brothers and their friends also made comparisons to other imperial regimes, including the Roman, Dutch, Mogul, and Portuguese empires. "The brothers and sisters wrote to each other over the course of half a century, and expressed deep differences of opinion. It intrigued me to think about how they observed the changes that were taking place in their worlds. The title refers as much to their interest in empires as my own," says Rothschild. Rothschild explains that the study of the history of economic life differs from the study of the history of economics. The former looks at the ways individuals have been affected by economic events, such as changes in property rights or debts and credit, while the latter concerns itself with the intellectual history of the discipline. Her own research has involved both areas. The JCHE is one of the first centers of its kind to take on such topics across both scholarly boundaries and geographical divides. Both faculty and graduate students often travel back and forth between the two institutions, and graduate students have been involved with the JCHE on both sides of the ocean. The centers have tackled many large-scale questions through a series of projects addressing economic and social security, environmental history, transnational exchanges of ideas, and the history of globalization. One such project, about which Rothschild is particularly excited, is "The Digitization of History," which explores the role of new technology in increasing access to historical sources and archives, and changing the way that historians are accessing visual, printed, and manuscript sources. Initiatives such as the Google books program have put a vast quantity of material online, she explains. The British National Archives have made available—and searchable—wills dating back to the 14th century, and shipping records of the port of Bordeaux, France, have been digitized and made available at no cost. The JCHE project also explores the technical challenges involved with digital preservation, and the increasing divide between the access to digital materials for wealthy, English-speaking institutions and those of developing countries. "This is changing the ways that we do history and think about doing history, in respects that we don’t understand yet," Rothschild says. "It raises quite new questions, because one could find out details of lives of people in the past that couldn’t have been put together in the same way before."

A One-Size-Fits-All Solution - Mullainathan, Sendhil; Barr, Michael S.; Shafir, Eldar (New York Times, 2007)
While the causes of the mortgage crisis are myriad, a central problem was that many borrowers took out loans that they did not understand and could not afford. Brokers and lenders offered loans that looked much less expensive than they really were, because of low initial monthly payments and hidden, costly features. Families commonly make mistakes in taking out home mortgages because they are misled by broker sales tactics, misunderstand the complicated terms and financial tradeoffs in mortgages, wrongly forecast their own behavior and misperceive their risks of borrowing. How many homeowners really understand how the teaser rate, introductory rate and reset rate relate to the London interbank offered rate plus some specified margin, or can judge whether the prepayment penalty will offset the gains from the teaser rate? While disclosure alone is unlikely to help, there's another option. In retirement policy, behavioral research has led Congress to promote “opt out” plans under which employers sign workers up for retirement benefits unless the worker chooses not to participate. This policy has significantly improved people's retirement savings. Why not have an opt-out home mortgage plan, based, for example, on a 30-year, fixed-rate loan, with sound underwriting and straightforward terms? Eligible borrowers would be offered a standard mortgage (or set of mortgages) and that's the mortgage they would get—unless they choose to opt out in favor of another option, after honest and comprehensible disclosures from brokers or lenders about the risks of the alternative mortgages. An opt-out mortgage system would mean borrowers would be more likely to get straightforward loans they could understand. But given lender incentives to hide true costs from borrowers, we need to give the opt-out plan some bite. Under our plan, lenders would have stronger incentives to provide meaningful disclosures to those whom they convince to opt out, because if default occurs when a borrower opts out, the borrower could raise the lack of reasonable disclosure as a defense to bankruptcy or foreclosure. If the court determined that the disclosure would not effectively communicate the key terms and risks of the mortgage to the typical borrower, the court could modify or rescind the loan contract. This approach would allow lenders to continue to develop new kinds of mortgages, but only when they can explain them clearly to borrowers. To avoid the next mortgage crisis, we should use behavioral insights to make it harder for lenders to put borrowers where they will make predictable and consequential mistakes.

Tutu Condemns U.S. Foreign Policy - Perloff-Giles, Alexandra (Harvard Crimson, 2007)
Desmond Tutu, Archbishop Emeritus of Cape Town and 1984 Nobel Peace Prize laureate, spoke yesterday on American foreign policy at an event commemorating the 50th anniversary of Harvard’s Weatherhead Center for International Affairs. Five hundred people lined up outside the American Repertory Theater beginning two and a half hours before the event to hear from the noted South African social justice advocate. Hundreds more were turned away at the door. Tutu’s talk, entitled “Goodness Triumphs Ultimately,” denounced current American foreign policy and stressed the importance of the United States’ position as a global leader. While Tutu counted the U.S. as a strong ally in the fight against apartheid, he has been critical of American foreign policy during the Bush administration. “You taught us no government worth its salt can subvert the rule of law. We believed you,” Tutu said at a gathering of Nobel laureates last year, according to The Washington Post. “That’s part of what you have as a gift for the world. Then how can you commit Guantanamo Bay? Take back your country.” The crowd at yesterday’s talk appreciated Tutu’s message. “He’s incredible. The zeal, the way he speaks—he could sell toilet paper and you’d want to buy it,” Libby A. Cunningham, a student at the Harvard School of Public Health, said. “He was just so affable, he addressed the management of world affairs but with a real personal touch,” Brian S. Reale said. “I think he inspired faith in the possibility of progress in a sometimes confusing world,” Utpal Sandesara ’08 said. Sandesara added that, while the talk was motivational, he felt Tutu somewhat over-simplified the dichotomy between justice and injustice. He cited Tutu’s attempt to explain the current situation in the Middle East in terms of absolute good and evil. “His framework is a very different one,” said Yinliang He ’08. “It’s beyond argument and counterargument. It’s theologically based.” Outside the Loeb, a handful of protesters held signs denouncing Tutu and accused him of being “an imperialist.” Tutu is here for the two-day conference of Weatherhead Center alumni fellows called “The Search for Solutions to the World’s Intractable Problems.” “Archbishop Emeritus Desmond Tutu’s opposition to apartheid, his commitment to stopping AIDS and treating its victims, his advocacy of inclusiveness for his church, and his dedication to peace distinguish him as one of the most significant social figures as well as humane individuals of our time,” Beth A. Simmons, director of the Weatherhead Center, said in a press release. “I think it was very fitting and appropriate that Desmond Tutu was chosen and invited to be the keynote speaker,” Kathleen S. Molony, director of the fellows program at the center, said after the talk. “It was a great launchpad for our whole conference.”

Tutu sees lots of negatives, a few positives, in American foreign policy - Gewertz, Ken (Harvard University Gazette, 2007)
Desmond Tutu was a high school teacher in Johannesburg before he entered the ministry, and all these years later he is still very much the pedagogue. “Good afternoon,” he said emphatically as he stepped to the podium at the Loeb Drama Center to deliver the Warren and Anita Manshel Lecture in American Foreign Policy on Nov. 15. The answer from the standing-room-only audience was feeble, and Tutu responded with a look of affronted surprise, a familiar goad in the arsenal of effective teachers everywhere. There was a burst of laughter, followed by a hearty second try: “Good afternoon!” Now the archbishop emeritus of Cape Town, Tutu rose to international prominence in the 1980s for his opposition to South Africa’s apartheid government. He received the Nobel Peace Prize for that work in 1984. After the fall of apartheid, Tutu headed the Truth and Reconciliation Commission. In 2007, Tutu convened a group of world leaders known as the Global Elders, dedicated to bringing their collective experience and insight to bear on some of the world’s most intractable problems. He began his talk, titled “Goodness Triumphs Ultimately,” by remarking that the journal Foreign Policy recently asked him and other world figures to answer the question, “What gesture can the incoming United States president make to counteract anti-American feeling abroad?” Tutu said he was not aware of any anti-American feeling. What he was aware of was “resentment and hostile opposition to this particular administration.” This was not the first time he has made such a distinction. The Reagan administration, for example, turned a deaf ear to Tutu’s call for sanctions against South Africa’s apartheid government. But, Tutu said, “that did not make me anti-American. We appealed over the head of the president to the American people, and soon afterward Congress passed anti-apartheid legislation.” Far from harboring anti-American feeling, Tutu said that he has been inspired by the United States ever since picking up a copy of Ebony magazine as a child and reading about Jackie Robinson breaking into major league baseball. “I didn’t know anything about baseball, but what mattered was that a black man had made it against huge odds. I was sold on America from then on.” News of African-American sports heroes and entertainers provided “an antidote to self-hatred” for black South Africans living under apartheid, Tutu said. In fact, the apartheid government tried to expunge American history from the school curriculum because it feared that the struggle of African Americans for equality would encourage South African blacks to rise up against oppression. When the United States was attacked on 9/11, the world responded with “an outpouring of love, sympathy, and support,” Tutu said. President Bush should, Tutu suggested, have responded to the attacks “not as an act of war, but as an egregious crime. The perpetrators should have been apprehended and tried before an international criminal court. If that had happened, the whole world would have cooperated.” Instead, Tutu contended, the Bush administration responded to the attacks according to “a simplistic world view” that looked at events in terms of “them and us, baddies and goodies.” Such a view required that the United States respond to 9/11 not as a criminal act, but as an act of war. “But according to the rules of war, there has to be a nation, so Iraq was recruited,” Tutu said. “The emergence of an enemy galvanized U.S. patriotism,” Tutu said, enabling the administration to manipulate patriotic feeling in order to pursue its own agenda. He compared this purported manipulation to methods used in South Africa. “The apartheid government used similar techniques to impugn the patriotism of anyone who dared to criticize the government.” Through its unilateral policies in Iraq, Tutu said, the United States has “thumbed its nose at the rest of the world” and has been “intent on throwing its weight around like a reckless bully.” Tutu said he was shocked by what he sees as America’s willingness to abrogate the rule of law and to equivocate about the legality of waterboarding and other interrogation methods. Evoking the specter of an evil and powerful enemy as an excuse to jettison established values is another technique the Bush administration has in common with the apartheid government of South Africa, he claimed. But despite the harshness of his criticism of recent U.S. foreign policy, Tutu’s feelings for the United States remain on the whole extremely positive. “I speak as one who has not just admiration but a big love for this country.” He praised President Bush’s recent stand against the military junta in Burma and thanked the United States for its generosity in the global struggles against AIDS, tuberculosis, and malaria. Returning to the question posed by Foreign Affairs, Tutu said, “There is one magnanimous act the new president could make. The new president would be surprised by the world’s reaction if he were to say, ‘We made a big mistake over Iraq. We’re sorry.’” Such a gesture would not only serve to sweeten world opinion, Tutu said, but would help to bring about the outcome promised in the title of his lecture. “This is a moral universe. Right and wrong actually do matter. Ultimately, truth, justice, goodness, and compassion will triumph over their ghastly counterparts.”

International Flavor to Innovation Forum - Weisman, Robert (Boston Globe, 2007)
Emmanuel K. Akyeampong, a social historian of Africa, helped to establish the African Public Broadcasting Foundation to generate television, radio, and Internet programming that would be accessible to ordinary Africans. A partnership between academic researchers and African broadcasters and producers, the foundation plans to create programming on topics ranging from health and nutrition to democracy and economic development to the impact of African music on jazz. "The continent most in need of knowledge has been the continent most deprived of knowledge," said Akyeampong, one of the noted innovators from the Boston area slated to speak Thursday at IDEAS Boston 2007, a conference that celebrates innovation across multiple disciplines. The conference, first organized by the Boston Globe in 2004, resumes at the Federal Reserve Bank of Boston after a one-year hiatus during which it was restructured as a nonprofit venture and broadened its roster of sponsors. This year's event will run for a single day, rather than two, and will introduce a fresh cast of innovators in fields ranging from music to physics and architecture to cell biology. It also features the return of Deborah Henson-Conant, an internationally known musician and performance artist based in Boston. Her participation at the 2005 IDEAS conference led to a series called "Inviting Invention" in which she asked scientists, dancers, and innovators from other fields to appear with her in joint performances. In some, she played the harp while scientists conducted experiments onstage. "I was totally inspired by the last event," Henson-Conant said. "I would say it was life-changing for me." But the event will retain the same spirit and approach as the first two IDEAS gatherings, said conference director Kathy Plazak. Unlike industry and academic forums organized around narrow themes, IDEAS showcases emerging concepts, breakthroughs, and Boston-area researchers, performers, and entrepreneurs in a variety of fields. "It continues the tradition of bringing together the great thinkers connected with this region," Plazak said. "The approach is to highlight cutting-edge thinking and share ideas across cultures. Innovation often happens when ideas are shared or adapted from other cultures. It's a very intellectual cross-disciplinary brainstorming." This year's IDEAS conference, again moderated by Tom Ashbrook, host of National Public Radio's "On Point" news-talk show, will have an international flavor. Among the speakers will be Akyeampong, a Harvard University professor of history and African studies; David C. Kang, an expert on the history and politics of China and North Korea; and, Bisola Ojikutu, director of international programs at Harvard Medical School's AIDS division. Sponsors of Thursday's conference are the Boston Foundation, Partners Healthcare, the Greater Boston Chamber of Commerce, Longworth Venture Partners, Plymouth Rock Assurance, McDermott Ventures, Business Wire, and Conventures. Its media partners are The Boston Globe, WCVB-TV, and 90.9 WBUR.

Jena, O. J. and the Jailing of Black America - Patterson, Orlando (New York Times, 2007)
The miscarriage of justice at Jena, La.—where five black high school students arrested for beating a white student were charged with attempted murder—and the resulting protest march tempts us to the view, expressed by several of the marchers, that not much has changed in traditional American racial relations. However, a remarkable series of high-profile incidents occurring elsewhere in the nation at about the same time, as well as the underlying reason for the demonstrations themselves, make it clear that the Jena case is hardly a throwback to the 1960s, but instead speaks to issues that are very much of our times. What exactly attracted thousands of demonstrators to the small Louisiana town? While for some it was a simple case of righting a grievous local injustice, and for others an opportunity to relive the civil rights era, for most the real motive was a long overdue cry of outrage at the use of the prison system as a means of controlling young black men. America has more than two million citizens behind bars, the highest absolute and per capita rate of incarceration in the world. Black Americans, a mere 13 percent of the population, constitute half of this country’s prisoners. A tenth of all black men between ages 20 and 35 are in jail or prison; blacks are incarcerated at over eight times the white rate. The effect on black communities is catastrophic: one in three male African-Americans in their 30s now has a prison record, as do nearly two-thirds of all black male high school dropouts. These numbers and rates are incomparably greater than anything achieved at the height of the Jim Crow era. What’s odd is how long it has taken the African-American community to address in a forceful and thoughtful way this racially biased and utterly counterproductive situation. How, after decades of undeniable racial progress, did we end up with this virtual gulag of racial incarceration? Part of the answer is a law enforcement system that unfairly focuses on drug offenses and other crimes more likely to be committed by blacks, combined with draconian mandatory sentencing and an absurdly counterproductive retreat from rehabilitation as an integral method of dealing with offenders. An unrealistic fear of crime that is fed in part by politicians and the press, a tendency to emphasize punitive measures and old-fashioned racism are all at play here. But there is another equally important cause: the simple fact that young black men commit a disproportionate number of crimes, especially violent crimes, which cannot be attributed to judicial bias, racism or economic hardships. The rate at which blacks commit homicides is seven times that of whites. Why is this? Several incidents serendipitously occurring at around the same time as the march on Jena hint loudly at a possible answer. In New York City, the tabloids published sensational details of the bias suit brought by a black former executive for the Knicks, Anucha Browne Sanders, who claims that she was frequently called a “bitch” and a “ho” by the Knicks coach and president, Isiah Thomas. In a video deposition, Thomas said that while it is always wrong for a white man to verbally abuse a black woman in such terms, it was “not as much…I’m sorry to say” for a black man to do so. Across the nation, religious African-Americans were shocked that the evangelical minister Juanita Bynum, an enormously popular source of inspiration for churchgoing black women, said she was brutally beaten in a parking lot by her estranged husband, Bishop Thomas Weeks. O. J. Simpson, the malevolent central player in an iconic moment in the nation’s recent black-white (as well as male-female) relations, reappeared on the scene, charged with attempted burglary, kidnapping and felonious assault in Las Vegas, in what he claimed was merely an attempt to recover stolen memorabilia. These events all point to something that has been swept under the rug for too long in black America: the crisis in relations between men and women of all classes and, as a result, the catastrophic state of black family life, especially among the poor. Isiah Thomas’s outrageous double standard shocked many blacks in New York only because he had the nerve to say out loud what is a fact of life for too many black women who must daily confront indignity and abuse in hip-hop misogyny and everyday conversation. What is done with words is merely the verbal end of a continuum of abuse that too often ends with beatings and spousal homicide. Black relationships and families fail at high rates because women increasingly refuse to put up with this abuse. The resulting absence of fathers—some 70 percent of black babies are born to single mothers—is undoubtedly a major cause of youth delinquency. The circumstances that far too many African-Americans face—the lack of paternal support and discipline; the requirement that single mothers work regardless of the effect on their children’s care; the hypocritical refusal of conservative politicians to put their money where their mouths are on family values; the recourse by male youths to gangs as parental substitutes; the ghetto-fabulous culture of the streets; the lack of skills among black men for the jobs and pay they want; the hypersegregation of blacks into impoverished inner-city neighborhoods—all interact perversely with the prison system that simply makes hardened criminals of nonviolent drug offenders and spits out angry men who are unemployable, unreformable and unmarriageable, closing the vicious circle. Jesse Jackson, Al Sharpton and other leaders of the Jena demonstration who view events there, and the racial horror of our prisons, as solely the result of white racism are living not just in the past but in a state of denial. Even after removing racial bias in our judicial and prison system—as we should and must do—disproportionate numbers of young black men will continue to be incarcerated. Until we view this social calamity in its entirety—by also acknowledging the central role of unstable relations among the sexes and within poor families, by placing a far higher priority on moral and social reform within troubled black communities, and by greatly expanding social services for infants and children—it will persist.

A Quiet Battle for Rights in Iran - Christia, Fotini (Washington Post, 2007)
TEHRAN—It was during a recent visit to a middle-class beauty salon here, amid the women getting their upper lips threaded and their legs waxed, that I saw what the One Million Signature Campaign is up against. A female volunteer approached another customer and encouraged her to sign a petition, which organizers hope to submit to Iran's parliament along with a request for legal reforms on gender equality. The woman said she supported the demands for equality but shied away from what she considered overt political activity against the regime. The campaign against gender discrimination is encountering resistance on multiple fronts. Activists gave themselves two years to collect a million signatures, but tomorrow, the campaign's one-year anniversary, they will not have more than 100,000 to report. But unlike other human rights movements battling repressive regimes, which have traditionally looked to the West for a lifeline, Iran's activists are adamant that for all the gratitude they may feel for their Western supporters, they would prefer that we keep our distance. Their efforts offer a fascinating window on how one aspect of the Iranian democracy movement is struggling to survive in a period of growing government repression and paranoia. The campaign for the million signatures was born after the arrest of 70 women who staged a demonstration against gender discrimination last year in Tehran's Haft-e-Tir Square. Nine of those women were convicted on charges of "endangering national security" and face lengthy prison sentences, beatings with whips and, in some cases, both. (They are free pending appeal.) The crackdown prompted Iranian women's rights activists to embark on a new strategy based on quiet campaigning, face-to-face organizing—and disavowing any Western help. With extraordinary tenacity, the activists seek out all possible venues in which to gather support without incurring the wrath of the Ahmadinejad regime. They collect signatures not just in beauty salons but in living rooms and parks, on street corners and at bus stops. In Tehran, they have assembled and trained at least 400 volunteers through private parties at organizers' homes, over popcorn and watermelon. Yet for all the campaign's efforts to elude government attention—and to disown any connection with the West—the regime has been aware of and has reacted to the activists. In March, 34 members were arrested in front of Tehran's Revolutionary Court, where they had gathered in solidarity for their nine convicted colleagues. Over the past year, 13 others involved in the campaign have been arrested. The campaign's Web site—a key tool in a country that lacks an independent media—has routinely been blocked. Members repeatedly have been denied permission to assemble in public places. The regime aims to paralyze the movement by instilling fear. Even so, many women are undeterred. "The regime wants to scare us. But we won't let them win. When they push, we resist," Parvin Ardalan, a journalist who was one of the nine convicted in March, told me this month. She is appealing her three-year sentence. Despite all the institutional repression, perhaps the trickiest issue for organizers is their relationship with the West. In recent months, a number of prominent Iranian Americans with Western passports—such as Haleh Esfandiari and Kian Tajbakhsh—have been charged with conspiring against the Iranian government. Political leaders increasingly voiced charges of a "velvet revolution conspiracy," allegedly aimed at toppling the government and backed by "lackeys of the West." The omens aren't good. Already, the country's intelligence minister has described the movement as comprised of "elements of soft subversion"—an unsubtle attempt to link them to foreigners. In public statements and in conversations with prospective signers, campaign activists emphasize their Iranian roots and their respect for Islam—if only to avoid giving the regime an excuse to discredit them. "What hurts the most is hearing people who claim to be for democracy and reform accuse us of being tools of the West," said Parastoo Alahyaari, a computer engineer and campaign member. "We want to prove that we can do this on our own." Financial independence is also important. The movement raises funds through documented membership dues and donations and explicitly states on its Web site that it does not accept financial or other support from organizations or governments. Volunteers are asked to strictly adhere to this rule. "Our regime has phobia," Nobel Peace Prize winner and campaign advocate Shirin Ebadi told me at her Tehran office. "When people talk about human rights they get immediately accused of being with America. But we are Iranian and want to work for our rights…And we know we are doing something right because we are being persecuted." About aid from the West, Ebadi was just as firm. "No money. Never."

Immigration in America, Now - Ashbrook, Tom; Peggy Levitt (WBUR, On Point with Tom Ashbrook, 2007)
“For a nation of immigrants, America has always had a complicated relationship with immigration. Some came in splendor, some came in chains, and everything in between. In the half century since Ellis Island closed, immigration and the immigrant experience have changed massively, again. Do we still want to absorb? Do they still want to assimilate? Are we open to a permanent underclass? In a globalized world, do immigrants ever really leave the old country? This hour On Point: the realities of the new American immigrant experience.” Show's guests: Jim Pethokoukis, senior writer for U.S. News & World Report Ruben Rumbaut, sociology professor at University of California Irvine and author of Immigrant America: A Portrait Hector Tobar, Mexico City bureau chief for the Los Angeles Times and author of Translation Nation Peggy Levitt, sociology professor at Wellesley College and author of God Needs No Passport Peggy Levitt is a Weatherhead Center for International Affairs Associate; Faculty Co-Director, Transnational Studies Initiative and Associate Professor of Sociology, Department of Sociology, Wellesley College. Her new book, God Needs No Passport: Immigrants and the Changing American Religious Landscape, will be published by The New Press in June.

Life, Liberty, and the Folks Back Home - Peggy Levitt (Boston Globe, 2007)
First they come to America. Then they start changing the world. It was a puzzling sight: Young women walking in the 80–degree heat, wearing boots and long-sleeved sweaters. I first saw this in 1992, when I traveled to a village in the south of the Dominican Republic called Miraflores to do research about migration. At the time, at least three–quarters of the 5,000 households in Miraflores had relatives living in the Boston area. And it was this geographic connection, it turned out, that explained the women's choice of clothing. During the winter months in Boston, the women heard, boots and sweaters are fashionable, so they wanted to dress that way too. What I saw in the Dominican Republic was just a small sign of a powerful phenomenon that has been overlooked in the great debate over this nation's immigration policy. The debate, which is now consuming Washington, has focused largely on the domestic effects of immigration, and particularly on money—on the economic costs and benefits here at home. There has been some discussion of "remittances," the billions of dollars that migrants send back each year to start businesses, build roads, or fund medical care—money that is hailed as the new antidote to underdevelopment. But immigrants also send back social remittances: New ideas from America, and about America, that are changing societies around the world in ways that are far more profound than winter fashions. Although we usually think of immigration in terms of what immigrants bring to our shores, immigration has in fact become one of America's most effective tools for spreading national values beyond our borders. Immigrants who maintain close ties to their home countries, far from being a threat to American society, are often, in effect, our development workers, sending skills and ideas about good governance, diversity, and equality back to their homelands. They are also our diplomats. They talk about their experiences in the United States, overcoming ignorance and suspicion among people in the countries they come from. And immigrants, having seen what is possible, can be forceful, grass-roots advocates for change. All across the world, there are migrant hometown committees, made up of immigrants and people who remain behind, that raise money to fund social services and public works projects back home. For example, there are now around 3,000 of these hometown committees working with Mexican immigrants in the United States, according to the Migration Policy Institute in Washington. These committees have become increasingly assertive. They demand that projects be managed openly and fairly, so that everyone knows where the money is going. They require that contracts go to the lowest bidder, not the local power broker. In Miraflores, for example, the committee has raised so much money and become so influential that it was able to pressure the government to pave the village's sidewalks and roads. Immigrants are also challenging long-standing social inequalities. After hearing stories about how men and women relate to each other in the United States, many young women in Miraflores said that they wanted to spend their lives with someone who would help around the house and take their opinions seriously "like American men do" (an idea some American women might question). These women had also seen women who ran their own businesses and managed their own money in the United States, and so they pressed for that as well. Even painful experiences in the United States can bring about positive changes. Before migrating, many people from Governador Valadares, in the eastern state of Minas Gerais in Brazil, considered themselves near the top of the Brazilian racial hierarchy. When they arrived in the United States, they quickly realized that Americans often treated them as people of color. This direct experience of prejudice inspired some to tell people back home to treat their darker-skinned neighbors more fairly. Social remittances also contribute to improvements in education and healthcare. In the small villages outside of Governador Valadares, many people now take for granted ideas that were once foreign: that children should finish high school and newborns should be vaccinated. Why? Because that is what their relatives living in Framingham told them to do. Pakistani and Indian doctors change health behavior by taking time off from their visits home to provide free medical care and by talking to their patients about nutrition and prenatal care. Delegations of Pakistani businessmen and engineers go back each year to speak to ministry officials about labor and education, suggesting changes in the ways the state does business. How religion is practiced is affected too. Pakistani women tell their relatives that they pray in the same room as their Muslim brothers in the United States, and that they are actively involved in running the mosque. While some women back in Karachi aren't interested, because they consider it their special privilege to pray at home, others are intrigued by the idea of women participating in communal prayers. Their efforts to carve out a new space for women in the Islamic community and to experiment with new rituals creates a wider range of religious alternatives in Pakistan and builds bridges to other Muslim women around the world. This is not to say that everything that migrants observe and send back is positive. Young people, for example, hear about those who work hard and honestly to get ahead, and others who advance by beating the system. Both strategies have their fans. There are the obvious fears, among people back home, that the flow of ideas from America devalues family, emphasizes materialism, and encourages moral and sexual permissiveness. And the United States is far from a perfect model—witness Hurricane Katrina, the flawed presidential election in 2000, or police brutality in Los Angeles. And yet, when it comes to the debate about immigration, our focus on economics, and in particular the economic impact in the United States, is far too narrow. Ideas and values matter. Immigrants bring ideas to this country, making our society richer. And they send ideas back, enriching and improving their home countries. Anti–Americanism is at an all–time high, in part because we are waging a war in Iraq to spread values that immigrants spread peacefully. The stories our immigrants tell every day give America a more human face—and an image boost we sorely need. Peggy Levitt is a Weatherhead Center for International Affairs Associate; Faculty Co-Director, Transnational Studies Initiative and Associate Professor of Sociology, Department of Sociology, Wellesley College. Her new book, God Needs No Passport: Immigrants and the Changing American Religious Landscape, will be published by The New Press in June.

Preconditions in Mideast Negotiations - Kelman, Herbert C. (Boston Globe, 2007)
The long-term survival of Israel as a Jewish-majority state, giving political expression to the national identity of the Jewish people, depends on negotiating a fair two-state solution that establishes an independent, viable Palestinian state in the West Bank and Gaza, with its capital in East Jerusalem. Early return to the negotiating table is not a favor to the Palestinians, but an urgent requirement for protecting the vital interests of both peoples. Under the circumstances, it is counterproductive to impose conditions on Palestinian negotiating partners that are unbalanced, unrealistic, and unnecessary. The three conditions that have been set—recognition of Israel's right to exist, renunciation of violence, and acceptance of prior agreements—are in themselves not unreasonable. Israel cannot be expected to sign an agreement with a partner who does not recognize its right to exist and hence is not committed to ending the conflict; violence contributes to creating an environment that is not conducive to constructive negotiations, and failure to live up to past agreements helps to erode the trust that negotiations require. But if the goal is to promote negotiations, application of these conditions must be guided by the principles of flexibility and reciprocity. Flexibility in the requirement of Palestinian recognition of Israel relates primarily to the issue of timing. Thus, it is not necessary for Hamas to take the ideologically difficult step of recognizing Israel's right to exist in order for Israel to begin negotiations with a Palestinian unity government, even though such recognition is necessary to conclude a negotiated agreement. Experience suggests that engagement in a serious negotiation process is, in fact, one of the best ways to promote such an ideological shift. In the meantime, the implied recognition represented by Hamas's willingness to negotiate with Israel can move the process forward. On the issue of renunciation of violence, the key requirement is a commitment by the Palestinian negotiating partner to make every effort to prevent acts of violence. It would be a mistake, however, to make the start or continuation of negotiations contingent on the total elimination of any incidence of violence. Such an inflexible application of this condition for negotiations would hand to the anti negotiation elements the power to block or derail negotiations at will. As for the third condition, Hamas seems to have met it implicitly by agreeing to “respect” previous agreements, along with international and Arab resolutions. A rigid insistence that Hamas make this concession explicit—admitting, in effect, that it has changed its ideological position—would create an unnecessary impediment to the restart of negotiations. It would be much wiser to accept a degree of ambiguity and leave it to the dynamics of the negotiating process to overcome the ideological resistances. Along with the need for flexibility in their application, the conditions for negotiations must adhere scrupulously to the principle of reciprocity. Reciprocity is an essential ingredient of a negotiating process that addresses the needs and interests of both parties and can therefore yield an agreement conducive to a stable, lasting peace, mutually enhancing cooperation, and ultimate reconciliation between the two peoples. Furthermore, the principle of reciprocity provides a sound basis for assessing the reasonableness and appropriateness of preconditions: Israel should be prepared to adhere to the same conditions that are being set for its Palestinian negotiating partners. Thus, Palestinian commitment to end the conflict and recognition of Israel's right to exist in peace and security have to be matched by Israeli commitment to end the occupation and recognition of the Palestinians' right to establish an independent, viable state in the West Bank and Gaza, with its capital in East Jerusalem, living peacefully and securely alongside of Israel. Palestinian commitments to forgo violence must be matched by parallel Israeli undertakings, such as a pledge to maintain a cease-fires and to discontinue military incursions into the occupied territories. Palestinian acceptance of past agreements and commitment to live up to them must be matched by an Israeli commitment to live up to past agreements, such as the understanding—implicit in the Oslo accord and explicit in the road map—that there would be no further building and expansion of Israeli settlements in the West Bank. The precise wording of these reciprocal conditions will have to be prenegotiated, perhaps with the facilitation of one or another third party. But the general rule is clear: If negotiations are to be constructive and conducive to a mutually satisfactory outcome, they must be based on the principle of reciprocity. Neither party can ask the other to negotiate under conditions that it is itself unwilling to accept. Herbert C. Kelman is a Faculty Associate of the Weatherhead Center for International Affairs. He is also Richard Clarke Cabot Professor of Social Ethics, Emeritus, Department of Psychology, Harvard University.

Bargaining with Russia to Contain Iran - Nye, Joseph S., Jr. (Boston Globe, 2007)
Relations between the United States and Russia have hit their lowest point since the Cold War. Just last week, Russian President Vladimir Putin accused the United States of igniting a global arms race and blasted those “who want to dictate their will to all others regardless of international norms and law”—a comment clearly aimed at the United States. That comes on top of Putin's remarks earlier this spring, in which he appeared to liken the United States to Germany's Third Reich. Meanwhile, US Secretary of State Condoleezza Rice said that Russia, at times, “seems to think and act in the zero-sum terms of another era.” This growing tension has real and dangerous implications for US security: Washington is struggling to get Russia's help in sanctioning Iran for its nuclear program—one of the top American defense priorities. If we in the United States want that help, we need to offer something in return. The latest International Atomic Energy Agency report paints a bleak picture: Iran is making faster progress than expected toward uranium enrichment. And our options are limited. A military attack against Iran not only would fail to stop an Iranian bomb, but it also would add to our difficulties in Iraq and the Muslim world more generally. Clearly, robust UN sanctions against Iran offer the best possible chance of persuading Iran to give up or at least slow down its plan to enrich uranium as part of its nuclear program. But diplomatic efforts to tighten UN sanctions on Iran's nuclear program can only succeed if Russia agrees not to wield its veto in the Security Council. Russia is torn between its interests in non proliferation, its commercial interests in trade (including equipment for nuclear reactors), and its irritation with the United States. The latest spark for disagreement between the United States and Russia is the American plan to build a missile defense system in Eastern Europe. The Bush administration argues that the missile installations in Poland and the Czech Republic will help counter Iran and do not endanger Russian security. Technically, that is correct. Rice and Secretary of Defense Robert Gates have both pointed out that Russian missiles and decoys could easily swamp our defensive systems. But the Russians see the situation differently, with Putin accusing the United States of “filling Eastern Europe with new weapons.” They object to the political symbolism of the US advance into former Soviet satellites, and also worry that someday our technological capabilities can develop the system as a threat to Russia. Our efforts to convince Russia otherwise have been fruitless. Yet these tensions also create an opportunity. We should offer Russia a grand bargain: We would delay our plans for missile defense in Eastern Europe, while the Russians would agree to back stronger sanctions against Iran. Since our technology is not fully developed and Iran is not on the brink of having long range missiles that can accommodate nuclear warheads, we could afford to offer Russia a delay in deployment while we engage in broader discussions of our military relationship. At the same time, since an Iranian nuclear weapon will undercut Russian security, and Russia has already offered to provide enrichment services to Iran if the Iranians forgo their own enrichment program, Russia might find the bargain tempting. Critics might worry that we would give away too much. But we can afford to buy ourselves a little time. It's not likely that Iran could develop missiles capable of reaching Europe or the United States for at least a decade. Therefore, we can take our best shot at blocking Iran's nuclear ambitions without compromising our immediate security. The United States clearly intends for any missile defense in Eastern Europe to protect against Iran, as well as any other hostile states. But we have the opportunity right now to prevent Iran from getting the nuclear bomb we're trying to defend ourselves against. By striking a deal with Russia to support sanctions against Iran, we would get a chance to make our strongest bid yet to prevent Iran from becoming the newest nuclear state. Everything else should be second to that goal. Although the administration will be reluctant to alter its missile defense plans, Rice often speaks of transformational diplomacy. What better example than for Bush to suggest this bargain to Putin when they meet at Kennebunkport this summer? Joseph S. Nye Jr., is a Faculty Associate and Executive Committee member of the Weatherhead Center for International Affairs. He is also Sultan of Oman Professor of International Relations, John F. Kennedy School of Government, and University Distinguished Service Professor, Harvard University and author of Soft Power: The Means to Success in World Politics.

Le Professeur: From Vichy to Iraq with a widely cultured "citizen of Harvard" - Lambert, Craig (Harvard Magazine, 2007)
In Vichy France, there were few diversions; among them were Hollywood musicals and comedies, such as those starring Fred Astaire and Bing Crosby, which helped lift the spirits of French audiences. One great success was Frank Capra’s Mr. Smith Goes to Washington, the story of a decent, average citizen who unexpectedly finds himself in the U.S. Senate, where he stubbornly persists in his ultimately victorious fight against a corrupt group in power. Although they controlled much of daily life, the German occupiers could not stop the French audiences from identifying with James Stewart as Mr. Smith. “They came to applaud,” says Stanley Hoffmann, who as a young boy was among those applauding. Now 78 years old, Hoffmann has been, since 1997, Buttenwieser University Professor; he ranks as one of the world’s preeminent authorities on international relations, with specialties in French politics and history and American foreign policy. He has written 18 books and countless articles, including, since 1978, regular essays in the New York Review of Books. Having taught at Harvard since 1955, Hoffmann also founded what is now the University’s Gunzburg Center for European Studies (where his recorded voice greets callers) and was among those who created the social-studies concentration in the College. “He probably holds the record for the greatest number of different courses taught in Harvard’s Core curriculum,” says Bass professor of government Michael Sandel, who has known Hoffmann for more than 30 years, taught a course on globalization with him, and calls him a “towering figure. Stanley has voracious intellectual interests and a range of knowledge of politics, history, and culture that is unrivaled in the academic world, as far as I know.” Rarely does a scholar’s life show such an intimate connection between personal experiences and academic pursuits as Hoffmann’s does. “It wasn’t I who chose to study world politics,” he wrote in a memoir published in a 1993 festschrift, Ideas and Ideals: Essays on Politics in Honor of Stanley Hoffmann.“World politics forced themselves on me at a very early age.” Born in Vienna in 1928, he grew up in the early 1930s in Nice, France, with his Austrian mother (his distant American father returned to the States and had scant contact with his son thereafter). “Nice was filled with foreigners,” he recalls. “Russian émigrés, people from Central Europe who had retired to the Riviera.” In 1936 Hoffmann mère et fils moved to Paris. “My mother thought the schools would be tougher there,” Hoffmann says. “She was right. For me, it was like moving from paradise to purgatory: the sky was gray, there was no sea, and Hitler was beginning to spread his wings.” On May 10, 1940, acute appendicitis afflicted the boy just as the radio reported the German attack on Belgium, Holland, and France. “I was under the knife in between air raid sirens,” he wrote. Hoffmann was baptized at birth as a Protestant, but his anti-clerical mother’s family fit the Nazi racial definition of Jews, and so the two of them, essentially stateless people, fled Paris. “My mother and I were two small dots in that incredible and mindless mass of ten million people clogging the roads of France,” he wrote. They finally reached Lamalou-les-bains, a tiny spa in Languedoc—and then, as the school year began, they returned to Nice, by then part of Vichy France. Once they left Paris, “my fate had become inseparable from that of the French,” Hoffmann wrote. “It wasn’t simply the discovery of the way in which public affairs take over private lives, in which individual fates are blown around like leaves in a storm once History strikes, that had marked me forever. It was also a purely personal sense of solidarity with the other victims of History and Hitler with whom we had shared this primal experience of free fall.” In Nice, after the Germans occupied the city in September 1942, the Gestapo were around every corner. “It was three months of waiting for the bell to ring at 3 a.m.,” he recalls. “Fear never left us.” And the little family had almost no resources; Hoffmann’s mother sold her jewels and borrowed from a friend, though in the empty markets there wasn’t much to eat anyway. Although they remained without citizenship through the war, “I had one great advantage: I was a very good student,” he says. “The French were willing to forgive anybody anything if one was a good student and spoke good French.” But excursions to enjoy the music, films, and walks that the studious Hoffmann loved were made hazardous by the sudden rafles, police and Gestapo round-ups such as the one in which his only close friend, the French-born son of Hungarian Jewish émigré's, disappeared, with his mother, forever. Carrying French documents that his history teacher had forged for them, Hoffmann and his mother returned to Lamalou-les-bains on a blacked-out night train. There, they found that 1,000 young German soldiers had encamped in the village of 800. The two groups didn’t speak to each other, but there was no Gestapo, it was perfectly safe, and there was no more fear. The villagers somehow found places for them to stay, even if it meant frequent moves as the Germans kept occupying hotels. “There was a basic decency in those French people,” he says, adding a quote from The Plague by Camus, “There is more in man to be admired than condemned.” Throughout their ordeal, the kindness and protectiveness of so many French countrymen and teachers made an indelible impression and stamped Hoffmann as irretrievably French. The voices of the Free French and General de Gaulle on the BBC helped sustain the hope “that kept one’s soul from freezing,” he wrote. But it was not until 1972, in a review of The Sorrow and the Pity, the Marcel Ophuls film on the Occupation, that Hoffmann spoke publicly of his wartime experiences; he ended the review by recalling the compassionate history teacher who had helped their flight from Nice: “He and his wife were not Resistance heroes, but if there is an average Frenchman, it was this man who was representative of his nation; for that, France and the French will always deserve our tribute, and have my love.” In 1944, the Lamalou-les-bains villagers flocked to see the first newsreels of the liberation of Paris. Hoffmann, who got his first look at the “tall and imperturbable” de Gaulle, has never forgotten the exhilaration of that moment. The “euphoria of a national general will was palpable,” he wrote, adding, “For the rest of my life, I was going to be stirred by the drama of peoples rising for their freedom, or breaking their chains, more deeply than by any other public emotion and by most private ones.” Despite his prodigious scholarly output, it is difficult to categorize Hoffmann’s approach to international relations. “There is no ‘school of Hoffmann’—he doesn’t have doctrinal disciples,” says Michael J. Smith ’73, Ph.D. ’82, Sorensen professor of political and social thought at the University of Virginia, who studied with Hoffmann and later co-taught a course with him. “Stanley has a horror of mimesis; he doesn’t want you to ape what he thinks—his students are the polar opposite of ‘dittoheads.’ They aren’t people who share a set of conclusions; they share a mode of inquiry, and come to their own conclusions using the best available arguments.” Hoffmann also is hostile to radical cures, allergic to communism and Marxism, and in fact profoundly “suspicious of anything that smacks of utopia and ideology, of a grand vision for the People with a capital P, or any millennial movement,” says his student Ellen Frost ’66, Ph.D. ’72, an international-relations scholar and former U.S. government official. (Hoffmann himself cites the French philosopher and political scientist Raymond Aron, a critic of French leftists, as a mentor, and calls him “a great anti-utopian.” Hoffmann writes that, like Aron, he naturally tends to “think against,” noting that he has had the “intellectual romps of a fox, and the convictions of a hedgehog.”) Furthermore, Hoffmann has never been tempted by government service, either as a policy adviser or bureaucrat, explaining that he is temperamentally unsuited for such work and values his independence too highly. “When I’m in Washington, I want to take the next plane out of there,” he says. “People who come back from this Washington world take a good time to become normal again.” He observes that he has remained “too French to be a convincing American policymaker,” adding, with characteristic wit, that his Harvard contemporaries Henry Kissinger ’50, Ph.D. ’54, and Zbigniew Brzezinski, Ph.D. ’53, didn’t have this problem. And unlike those two, “[M]y reaction to power is more dread than desire,” Hoffmann writes. “I study power so as to understand the enemy, not so as better to be able to exert it.” Hoffmann’s analysis of American politics may be “more influential overseas than it is here,” says Louise Richardson, Ph.D. ’89, executive dean of the Radcliffe Institute, a former Hoffmann student who studies terrorism. “He is humanistic, and he brings history into the equation and focuses on the importance of individual leaders.” (De Gaulle is his personal hero.) This approach, which eschews the quantitative data and theoretical models now fashionable in international relations, nonetheless, in Hoffmann’s hands, produces astonishingly insightful analyses. “He has an old-fashioned approach to the study of politics that emphasizes history, diplomacy, and political philosophy,” says Sandel. “Some might accuse Stanley of being a dinosaur, but if that’s true, then more of us should aspire to be dinosaurs.” “He’s been prescient—and right—on all the major issues of the postwar period,” says Smith. Hoffmann opposed the French war in Algeria and supported de Gaulle’s efforts to extricate the French from their colonial past there. In 1963, when John F. Kennedy was commander-in-chief, Hoffmann predicted that the Vietnam War would prove an exercise in futility (and in his memoirs, Pentagon Papers source Daniel Ellsberg ’52, JF ’59, Ph.D. ’63, credits Hoffmann with changing his mind on Vietnam—the two debated at Radcliffe in 1965). In 1975, Hoffmann wrote an article recommending a new foreign policy for Israel to advance the cause of peace there, an essay that he says he could republish today without changing a single word (“At least half” of terrorism would disappear, he believes, if the Israel/Palestine conflict were resolved). And in March 2003, Hoffmann wrote an essay in the Boston Globe on the eve of the invasion of Iraq; all of its gloomy predictions have since come true. In 2004 he advocated a phased military withdrawal from Iraq, an idea that seemed outré at the time but that has since been backed by a majority in Congress. Experience and learning have combined in Hoffmann to produce a singular outlook on world politics. Start with a brilliant intellect: he graduated at the top of his class at the Institut d’Études Politiques (“Sciences Po”) in 1948 and received tenure at Harvard in 1959, only four years after joining the faculty. And in the life of the mind, powerful ideas often come from those who reside both inside and outside some discipline or community; they combine the fresh eyes of the outsider with the deep knowledge of a participant. Hoffmann considers himself someone whose nature, choices, and fate have made him “marginal in almost every way.” Having spent his formative years in France, he has now lived in the United States for twice as long as he did there, and has been a citizen of both countries since 1960. His writings, while often critical of American foreign policy, also aim to support the United States in living with greater security and respect in the world. He often provides perspectives that are unavailable to those (there are many) who lack his worldliness and deep historical knowledge. Take, for example, McGeorge Bundy, JF ’48, LL.D. ’61, a former dean of the Faculty of Arts and Sciences and an admired friend, who Hoffmann says “shared the belief of all who have been in the U.S. foreign policy establishment: that America could do practically anything it wanted, because of its combination of force and wisdom.” When Bundy, as national security adviser in the Kennedy administration, was helping to mount the Vietnam War, he had a correspondence with Hoffmann in which the latter questioned whether the United States could succeed in this venture, arguing in part from the French experience in the region. Bundy replied, “We are not the French—we are coming as liberators, not colonialists.” “The only problem,” Hoffmann says, “was the Vietnamese.” He adds that American foreign policy tends to commit “the sin of excessive benevolence: we will make people happy whether they want it or not.” Americans, he feels, “have to understand the foreignness of foreigners, instead of believing that they are simply misguided Americans or not well-guided Americans.” Even Zbigniew Brzezinski, he notes, “still has this conception that the United States can make decisions for everybody.” Recently, at a Faculty of Arts and Sciences meeting on general education, a young economist rose to declare that people everywhere are pretty much the same and want the same things, so the one course that all undergraduates ought to take is economics. “I exploded,” Hoffmann recalls, “and said, ‘This is why we have been so successful in Vietnam and Iraq.’ The assumption that ‘people everywhere are all alike’ is something you have to get out of your system. In old age, I am more and more convinced that people are intensely different from country to country. Not everyone is motivated by the same things. “Americans mean well, but they don’t understand that acting with all one’s might to do good can be seen as a form of imperialism,” Hoffmann continues. “Within 10 minutes, these good intentions can turn into a benevolent condescending attitude toward the lesser tribes.” In one of his early books on U.S. foreign policy, Gulliver’s Troubles (1968), Hoffmann deploys the metaphor of a giant besieged by tiny adversaries who nonetheless fetter him effectively. An apt analogy to the United States’s predicament 40 years ago, it appears nearly oracular today, when there is daily proof that, as Hoffmann says, “Populations with even a small number of rebels can make large armies ineffective.” (His 2004 sequel with Frédéric Bozo, Gulliver Unbound: America’s Imperial Temptation and the War in Iraq, argues that the United States blunders into snares when it lumbers forward, heedless of foreign nations’ histories and indigenous sentiments.) “The people surrounding Paul Bremer [M.B.A. ’66, head of the provisional authority governing Iraq in 2003-04] had never been in the Mideast and knew nothing of the region,” Hoffmann says. The years since 2001 “have shown the absolute fiasco of unilateralism,” he declares. “We make reality, but if we make it alone, it will boomerang.” The United States seemingly needs to relearn expensive lessons it has already paid for, and forgets things it used to know. “In 1945 and in the immediate postwar period, the United States did respect, within limits, what Europeans wanted,” Hoffmann explains. “We had an enemy, the Soviet Union, which was repressing its satellites, and we had to do better than that. But remove the Soviet Union, and we tried to tell the world what to do—it doesn’t work. And it only got worse with the rise of the neocons. “The French, for example, get terribly annoyed when Americans and conservative British tell them that France has to cut down on social security and work longer hours,” he continues. “The French know enough about America to know that there are aspects of American life that they don’t want—overwork, short vacations, and rather poor social and public services, for example.” Not long ago, during a taxi ride to Boston’s Logan Airport (Hoffmann was about to fly to Holland), the driver asked how the Dutch were doing. “They are doing fine,” Hoffmann replied. “They are at least as prosperous as we are, maybe even more so.” The driver said, “But that’s not possible! We are the most prosperous country in the world!” With his dual citizenship, writing in both French and English (he sometimes translates himself), and with strong sympathies toward both nations, Hoffmann is ideally equipped to explain France to Americans and Americans to France. His full-year course, “Political Doctrines and Society: Modern France,” which he taught for more than three decades beginning in 1957 and into which, he has written, “I poured everything I knew and thought about France, and out of which came most of what I have written on her,” he calls the achievement of which he is most proud, because there was nothing like it. “I was, I am, French intellectually,” he wrote. “My sensibility is largely French—I like the frequent obliqueness, indirection, understatement and pudeur [modesty] of French feelings. But in my social being, there is something that rebels against the French harness, style of authority, and of human relations.” Historical perspectives inform Hoffmann’s explanations of modern France. World War I, for example, was fought in France and the Low Countries—not in England or the United States. In the war, France lost 1.4 million soldiers out of a national population of 40 million; an equivalent loss for the United States today would be 10.5 million troops—nearly 3,000 times the current U.S. military death toll in Iraq. “France had a very, very rocky time after World War I,” Hoffmann explains. “Many came back mutilated, there was general exhaustion, and most people were turning pacifist because they didn’t want another war. In World War II they lost ‘only’ 600,000. But the period after World War II was one of extraordinary creativity in France; they came out of that war less exhausted and with a growing birth rate and much more vitality.” That postwar vitality energized the young Hoffmann, who as a 16-year-old recharged his energies by spending the summer of 1945 lounging on the benches of the Bois de Boulogne, absorbed in the novels of André Malraux. (“If anybody ever gave me the impression of a genius, it was Malraux,” Hoffmann says, recalling a 1972 meeting he and his wife Inge [Schneier] Hoffmann had with the writer. “You cannot reproduce a conversation with Malraux; he started at 20,000 feet, there was no small talk. He was utterly charming, witty, sardonic.”) Hoffmann became a naturalized French citizen in 1947, enrolled in doctoral studies in law, and went to the Salzburg Seminar in American studies in the summer of 1950, deepening his fascination with the United States. In 1951 he came to study in Harvard’s government department, receiving an A.M. in 1952. He then returned to France for army service (“sheer boredom”), and when he wrote to Harvard to say he wouldn’t mind returning, the department surprised him by offering, not the chance to write a Ph.D. thesis, but an instructorship. His “rather monstrous” law thesis, published in 1954, sufficed as a credential. When he came to Cambridge to stay in 1955, Hoffmann decided, “This was a wonderful place. I felt I could live here and remain French. It was a cosmopolitan place in which one could function without anyone wondering where your passport was issued.” He smiles, adding, ”I am French, and a citizen of Harvard.” Hoffmann is a professor in the grand classical sense, a man of wide learning rather than a discipline-bound specialist. “He’s a profoundly cultured man,” says Ellen Frost. New York Times columnist Thomas Friedman, who, as a visiting lecturer in the government department in 2000, taught a course on globalization with Hoffmann and Sandel, says, “What I like about Stanley’s writings in the New York Review of Books is that he doesn’t engage in these crazy numerical or quantitative analyses of international relations. You live it and breathe it when you listen to him, because it’s really textured by deep knowledge of history, philosophy, sociology—he weaves all the strands together.” Albert Camus had a major influence on Hoffmann, who this spring gave a new course (in French) on the writer. “His existentialism is the philosophy to which I feel the closest,” he says. He met Camus only once, when the latter was giving a talk to American students in Paris. “He was irresistible,” Hoffmann recalls. “Very charming. He looked like a handsomer version of Humphrey Bogart. Camus’ influence on society and culture was a much greater one [than Sartre’s], because he was much more readable—he wrote unbelievably beautiful French.” The myth of Sisyphus, which Camus used as a touchstone for an eponymous 1942 essay, also informs Hoffmann’s philosophy. “There are two main ideas I take from Camus,” he says. “One, that there is no such thing as linear progress: the rock has a tendency to roll back down the hill again, and nothing is ever finally accomplished. Second, one has to keep trying anyhow; that the rock will roll down again shouldn’t prevent you from trying to push it back up.” Hoffmann typically closed the last lecture of his course on ethics and international relations (which he first offered in 1980 with Michael Smith, and will give again with J. Bryan Hehir, Montgomery professor of practice of religion and public life, next spring) by reading the two final paragraphs of The Plague, where Camus explains that after the end of the plague, “the rats will return to the city.” The victories won for humanity are always provisional ones. His mentor Raymond Aron declared that “Anyone who believes that all good things will come together at the same time is a fool,” Hoffmann says. “My quarrel with Thomas Friedman is that he believes that thanks to globalization, individual liberty, democracy, prosperity, and peace will all arrive together. That requires a breathtaking optimism or naïveté, and also explains his initial enthusiasm for the invasion of Iraq. Friedman is not an imperialist, but he does have this conviction that America has this formula for the world that will be good for everybody.” Hoffmann finds the contemporary international situation grim and much of current U.S. foreign policy both benighted and disheartening. “One reason I haven’t been teaching international relations this year is I find it so discouraging, I can’t face it,” he confides. “If someone told me that after the end of the Cold War, one would hear about nothing but terrorism, suicide bombings, displaced people, and genocides, I would not have believed it.” Twenty-seven students and auditors, ranging in age from undergraduates to some in their 60s and 70s, sit at their places in Sever this spring for French 190, Hoffmann’s course on Camus. In front of the room, their professor is eloquent, graceful, and gently humorous; when a student opens the window shades, he quotes Goethe’s dying words, “Mehr Licht!” [“More light!”] Hoffmann’s lectures “are finished works in themselves,” says Louise Richardson, noting that Harvard faculty often sit in the back, auditing the artful presentations. “How many international relations scholars will you find teaching Camus?” asks Thomas Friedman. “They don’t make them like Stanley anymore.” Hoffmann once asked Richardson, who has studied the 1956 Suez crisis in depth, to suggest some relevant readings because he was preparing a lecture that dealt with it. “I recommended five books,” she recalls. “And he read all five!—even though the Suez crisis was only a small piece of the lecture. Stanley takes scholarship and teaching very seriously. He reads an extraordinary amount.” In true European style, he is also happy to ask his students to do the same, and compiled impressively long reading lists for full-year courses like “War,” which had three lectures per week, plus a section. War and Peace could be the assigned text for just one of those lectures. When asked if that was unreasonable, and if an excerpt from Tolstoy’s magnum opus might not suffice, Hoffmann asked, “Which part of War and Peace summarizes the themes?” Ellen Frost had Hoffmann for her junior tutorial in social studies. “He was brilliant, and because I was young, that was intimidating,” she recalls. “But he was also very caring. He saw through any kind of pretension, hypocrisy, or bluff, and has a deliciously wicked sense of humor, tinged with paradox. Humor permeates him.” Hoffmann once observed that, “What the classical economists called ‘harmony of interest through accumulation of goods,’ Rousseau summed up in one word: ‘greed.’” Discussing Woodrow Wilson’s Fourteen Points, he might casually quote Clemenceau to the effect that “Even God didn’t need 14 points.” Michael Smith describes Hoffmann’s teaching style as “rigorous presentation of competing points of view at their most persuasive, followed by a devastating critique, followed by his own take on the issue. There are two ways of teaching: provide a suit straight off the rack, so to speak, or plant seeds and let them grow. Stanley plants seeds; he allows you to develop your own arguments.” Smith adds that “one of Stanley’s signal virtues as a teacher is that he treats everyone as an intellectual equal. You can be a freshman or a head of state and you’ll get exactly the same Stanley: he doesn’t dumb anything down and he doesn’t flatter you for the sake of your position. There’s not an ounce of condescension in him.” (Right after earning her doctorate, Frost wrote her mentor a long letter about her first job, working in the U.S. Senate. “Back came the loveliest handwritten letter,” she recalls. “It said, ‘Dear Ellen, Please call me Stanley, unless you want me to call you Dr. Frost.’”) During the Harvard student protests in the spring of 1969, Hoffmann led teach-ins on Vietnam and became something of a hero to undergraduates. “Some of the students’ grievances were perfectly understandable, and the decision to call the police was an unbelievable mistake. [President Nathan] Pusey said that the confrontation had nothing to do with politics, that this was a problem of ‘manners.’ On the right, some conservatives in several departments were on a rampage. At the first faculty meeting after the University Hall occupation, [economic historian] Alexander Gerschenkron explained that the students were exactly like the Bolsheviks in Russia, and that there was only one thing you could do with such students: ‘Beat them! Beat them! Beat them!’” At the same time, Hoffmann didn’t countenance the left-wing students’ ambition to shut down the University, and felt it was important “to prevent the ‘ultras’ [extremists] from taking over. I was really concerned with trying to keep it together,” he recalls. “Stanley is passionately committed to open debate and free intellectual exchange,” Frost explains. “To him, that is the soul of a university.” That, and of course, its students. “What mattered [in 1969] was that one listened to what the students had to say,” Hoffmann says, “because students were what the University was about.” Hoffmann listens carefully to his own students, who frequently end as colleagues and friends. “I’ve been a teacher first, and a writer second,” he says, notwithstanding his 18 books. “I like writing, but it’s a lonely job and I am happier in front of a classroom than a blank page. I need the input and the stimulation that the students provide. They are fun. I am not ready to give up yet—or rather, I am ready, each time I am away from my students. But when I am with them, I want to go on forever.” A traditional debate among international-relations scholars pits “realists,” who believe that national self-interests and power considerations ought to guide decisions, against “cosmopolitans,” who emphasize universal values like human rights over national self-interest. Hoffmann, a complex and subtle thinker, does not fit easily into either camp. “I’ve always considered Stanley a liberal realist,” says Sultan of Oman professor of international relations and former dean of the Kennedy School of Government Joseph Nye, a Hoffmann student. “He has always understood both dimensions.” Like Camus, Hoffmann has a passion for human rights, broadly conceived, and a powerful ethical sense. Ellen Frost contrasts the pragmatism of the realist Henry Kissinger with Hoffmann’s cosmopolitanism. “Kissinger feels that the American public accepts foreign-policy initiatives only if they are tied to some ethical rationale,” she says. “Stanley has a different approach: he thinks foreign policy should be infused with universal ethical principles.” Smith notes that Hoffmann “was influential in bringing the study of norms and ethics to mainstream international relations. It had been marginalized.” “As an academic, I have had one thread to guide me in my divagations: concern for world order,” Hoffmann writes. He defines world order as including how states arrange their relations to prevent a permanent state of war, and how they orient themselves in the postwar international system. That said, he is not a pacifist, and if he generally favors international cooperation, it is not so much for moral reasons as because, as Frost explains, “Things are more likely to work if you have other countries helping out.” Though Hoffmann disagreed with his domestic policies, he feels that President George H.W. Bush did a “masterful” job managing the transition to the post-Cold War era. “Without gloating, he handled the Soviet breakup, the reunification of Germany, even the Gulf War very well,” Hoffmann says. In his estimate, the greatest statesman of his lifetime was Charles de Gaulle. “There is no exact equivalent for the word ‘leadership’ in French,” Hoffmann says. “I recently reread de Gaulle’s speeches and marveled at the eloquence of his style, the pedagogical talent he had—he was the son of a schoolteacher. For the French, leadership means pedagogy: the capacity to explain the world, and to make people feel that the leadership takes them seriously. We haven’t had a real teacher since de Gaulle, and that has produced a funk in France. One component of leadership is making people feel that they are intelligent, that they understand. It’s something that has been missing in both France and America for a long time. People want to be enlightened. If you don’t do that, if it is all electoral tricks, or canned speeches, then there is going to be nothing but contempt and distrust of the people in power.” Similarly, “In the old days, international relations was understood by average people, and today it is not,” Hoffmann declares. “Jargon has invaded everything and the relationship of theories to reality has faded. There are all these wonderful equations, but how are they affected by a real-world phenomenon like death? When I came to Harvard, American foreign policy was near the top of the hierarchy of subjects taught here. Today, there is no tenured government professor teaching American foreign policy. At present, the hierarchy of prestige values everything that is abstract and theoretical, and you cannot do that with foreign-policy studies. They have to be concrete and deal with concrete issues.” Reality, with its complexities and paradoxes, continues to absorb him. He enjoys welcoming former French prime minister Dominique de Villepin to Harvard as much as he does teaching a freshman seminar on “Moral Choices in Literature and Politics.” The best word for Hoffmann’s thinking and writing might be “nuanced,” reflecting his deep reading of the facts, including those that seem to have escaped everyone else’s attention. His goal is always to understand, and, on a good day, perhaps exert a bit of influence as well, but never to reach fixed conclusions. In Hoffmann’s festschrift, the late Judith Shklar, former Cowles professor of government and Hoffmann’s close friend, summed up the pleasures of teaching and learning with him. Her essay tried, she said, to give an idea of “what it was like to have gone on a long intellectual journey with him that contemplates no arrival, but only the pleasures of the open road.” Stanley Hoffmann is a Faculty Associate of the Weatherhead Center for International Affairs. He is also Paul and Catherine Buttenwieser University Professor, Department of Government, Harvard University. Craig A. Lambert ’69, Ph.D. ’78, is deputy editor of Harvard Magazine.

The Lobster Summit - Allison, Graham T., Jr. (Boston Globe, 2007)
President George W. Bush's decision to award President Vladimir Putin the unique distinction of a weekend in Kennebunkport with two American presidents flummoxed supporters and critics alike. Over the past year, no international leader has been more critical of the president than his Russian guest. From his January State of the Union reference to “Comrade Wolf,” to his recent comparison of Bush's America to Hitler's Third Reich, Putin has many chattering about a new Cold War. Moreover, in preparing for election of a new parliament in December and new president next March, Putin has tightened Kremlin's grip on all instruments of power, from the economy to the press. Why then did Bush decide to reward what most American opinion leaders believe he should be condemning? Senator John McCain, for example, has called for Russia to be evicted from the G-8 club of leading industrial democracies. Bush and Secretary of State Condoleeza Rice made the right decision in inviting Putin on the basis of a sound assessment of how best to advance American national interests. Four considerations informed their judgment. First, hysterics aside, Russia is not the Soviet Union, and the United States is not entering a new Cold War. For four decades the Soviet Union was America's focal enemy. A Communist totalitarian government consumed 40 percent of its gross national product in a military-dominated state whose troops occupied what Ronald Reagan rightly called an “evil empire.” Today, Russia's borders have shrunk back to territory controlled by Catherine the Great 200 years ago. Russia now spends $1 on defense for every $11 in the American defense budget. In short, this is not his father's Soviet Union. Second, President Bush understands that Russia is a former superpower struggling to recover its balance. For Russia, the 1990s were a traumatic roller coaster ride that turned the society upside-down and inside out. Over the decade, the Soviet Union disappeared to be replaced by Russia and 14 newly independent states; a centrally commanded and controlled economy was destroyed in an economic depression worse than the great American depression; and Communism was buried. A superpower rival of the United States became a supplicant, groveling for economic assistance. Under Putin, Russia's economy has grown at 7 percent per year; Russia's debt has been repaid; Russia has emerged as a petro-power. Third, as a fellow politician, Bush understands the power of public symbols. In both countries, baiting the former Cold War adversary is politically productive. Especially in a society that felt humiliated and thus craves to be proud of their country, Putin's readiness to stand up to the world's sole superpower has given him the highest approval rating among his fellow citizens of any leader in the world today. Thus especially when cooperating, Putin is always at pains to describe this in his own term—not as concessions to the United States. Fourth and most important, as the president stated bluntly at the Kennebunkport press conference, the United States needs Russia. Success in combating the greatest threats to Americans' security and well-being requires Russia's active cooperation. Iran is only the most urgent illustration of the central proposition: Without deep Russian cooperation, the United States has no hope of preventing the proliferation of nuclear weapons, nuclear terrorism, and nuclear war. Words aside, Putin's hidden hand has been extremely helpful in the current bargaining with Iran: delaying completion of the civilian nuclear reactor at Bushehr, refusing to supply nuclear fuel to Iran, and urging Iran to accept an arrangement in which fuel for its civilian nuclear reactors would be produced by an international consortium outside Iran. Russia has joined the United States in three UN resolutions calling on Iran to suspend enrichment of uranium and enter negotiations. As Bush underlined at the press conference, when the United States and Russia stand together, Iran takes note. Bush was right to host Putin in a setting conducive to serious conversation about how they can block Iran's acquisition of nuclear bombs. In the weeks ahead, expect the two countries to move directly to conduct a joint assessment of the Iranian threat on the basis of which they produce a joint strategy for stopping Iran. The unnecessary controversy over missile defenses against nuclear warheads delivered by Iranian missiles can readily be resolved in that context since such defenses would be required only if the United States and Russia fail to prevent Iran's acquiring nuclear bombs. The proof of what was achieved at this “lobster summit” will be in Russian and American actions in the months ahead. But if by this invitation, Bush solidified Putin's cooperation as a real partner in stopping Iran, Kennebunkport will be noted by historians as an accomplishment of which two soon-to-be former presidents can be proud. Graham Allison is a Faculty Associate of the Weatherhead Center for International Affairs. He is also Douglas Dillon Professor of Government, and Director, Belfer Center for Science and International Affairs, John F. Kennedy School of Government, Harvard University.

Diversity and Community - Ashbrook, Tom; Putnam, Robert D. (WBUR, 2007)
By host Tom Ashbrook WBUR's On Point, August 9, 2007 Harvard political scientist Robert Putnam is a self-described full-on liberal who worries a lot about community in America. He made his name in the 1990s with his finding that hordes of Americans were, in his famous phrase, "bowling alone"—living without the traditional community ties of bowling leagues and Moose clubs that bound people together. Then he set out on a huge project to find out why. The answer looks like a liberal's nightmare: diversity. Diverse communities, Putnam found, show dysfunction. At least for a while. This hour On Point: Robert Putnam, Pat Buchanan and Lani Guinier on diversity and community in America. To listen to this conversation go to: http://www.onpointradio.org/shows/2007/08/20070809_b_main.asp Robert Putnam is a faculty associate at the Weatherhead Center and Peter and Isabel Malkin Professor of Public Policy.

The Downside of Diversity - Jonas, Michael (The Boston Globe, 2007)
A Harvard political scientist finds that diversity hurts civic life. What happens when a liberal scholar unearths an inconvenient truth? It has become increasingly popular to speak of racial and ethnic diversity as a civic strength. From multicultural festivals to pronouncements from political leaders, the message is the same: our differences make us stronger. But a massive new study, based on detailed interviews of nearly 30,000 people across America, has concluded just the opposite. Harvard political scientist Robert Putnam—famous for “Bowling Alone,” his 2000 book on declining civic engagement—has found that the greater the diversity in a community, the fewer people vote and the less they volunteer, the less they give to charity and work on community projects. In the most diverse communities, neighbors trust one another about half as much as they do in the most homogenous settings. The study, the largest ever on civic engagement in America, found that virtually all measures of civic health are lower in more diverse settings. “The extent of the effect is shocking,” says Scott Page, a University of Michigan political scientist. The study comes at a time when the future of the American melting pot is the focus of intense political debate, from immigration to race-based admissions to schools, and it poses challenges to advocates on all sides of the issues. The study is already being cited by some conservatives as proof of the harm large-scale immigration causes to the nation's social fabric. But with demographic trends already pushing the nation inexorably toward greater diversity, the real question may yet lie ahead: how to handle the unsettling social changes that Putnam's research predicts. “We can't ignore the findings,” says Ali Noorani, executive director of the Massachusetts Immigrant and Refugee Advocacy Coalition. “The big question we have to ask ourselves is, what do we do about it; what are the next steps?” The study is part of a fascinating new portrait of diversity emerging from recent scholarship. Diversity, it shows, makes us uncomfortable—but discomfort, it turns out, isn't always a bad thing. Unease with differences helps explain why teams of engineers from different cultures may be ideally suited to solve a vexing problem. Culture clashes can produce a dynamic give-and-take, generating a solution that may have eluded a group of people with more similar backgrounds and approaches. At the same time, though, Putnam's work adds to a growing body of research indicating that more diverse populations seem to extend themselves less on behalf of collective needs and goals. His findings on the downsides of diversity have also posed a challenge for Putnam, a liberal academic whose own values put him squarely in the pro-diversity camp. Suddenly finding himself the bearer of bad news, Putnam has struggled with how to present his work. He gathered the initial raw data in 2000 and issued a press release the following year outlining the results. He then spent several years testing other possible explanations. When he finally published a detailed scholarly analysis in June in the journal Scandinavian Political Studies, he faced criticism for straying from data into advocacy. His paper argues strongly that the negative effects of diversity can be remedied, and says history suggests that ethnic diversity may eventually fade as a sharp line of social demarcation. “Having aligned himself with the central planners intent on sustaining such social engineering, Putnam concludes the facts with a stern pep talk,” wrote conservative commentator Ilana Mercer, in a recent Orange County Register op-ed titled “Greater diversity equals more misery.” Putnam has long staked out ground as both a researcher and a civic player, someone willing to describe social problems and then have a hand in addressing them. He says social science should be “simultaneously rigorous and relevant,” meeting high research standards while also “speaking to concerns of our fellow citizens.” But on a topic as charged as ethnicity and race, Putnam worries that many people hear only what they want to. “It would be unfortunate if a politically correct progressivism were to deny the reality of the challenge to social solidarity posed by diversity,” he writes in the new report. “It would be equally unfortunate if an ahistorical and ethnocentric conservatism were to deny that addressing that challenge is both feasible and desirable.” . . . Putnam is the nation's premier guru of civic engagement. After studying civic life in Italy in the 1970s and 1980s, Putnam turned his attention to the US, publishing an influential journal article on civic engagement in 1995 that he expanded five years later into the best-selling “Bowling Alone.” The book sounded a national wake-up call on what Putnam called a sharp drop in civic connections among Americans. It won him audiences with presidents Bill Clinton and George W. Bush, and made him one of the country's best known social scientists. Putnam claims the US has experienced a pronounced decline in “social capital,” a term he helped popularize. Social capital refers to the social networks—whether friendships or religious congregations or neighborhood associations—that he says are key indicators of civic well-being. When social capital is high, says Putnam, communities are better places to live. Neighborhoods are safer; people are healthier; and more citizens vote. The results of his new study come from a survey Putnam directed among residents in 41 US communities, including Boston. Residents were sorted into the four principal categories used by the US Census: black, white, Hispanic, and Asian. They were asked how much they trusted their neighbors and those of each racial category, and questioned about a long list of civic attitudes and practices, including their views on local government, their involvement in community projects, and their friendships. What emerged in more diverse communities was a bleak picture of civic desolation, affecting everything from political engagement to the state of social ties. Putnam knew he had provocative findings on his hands. He worried about coming under some of the same liberal attacks that greeted Daniel Patrick Moynihan's landmark 1965 report on the social costs associated with the breakdown of the black family. There is always the risk of being pilloried as the bearer of “an inconvenient truth,” says Putnam. After releasing the initial results in 2001, Putnam says he spent time “kicking the tires really hard” to be sure the study had it right. Putnam realized, for instance, that more diverse communities tended to be larger, have greater income ranges, higher crime rates, and more mobility among their residents—all factors that could depress social capital independent of any impact ethnic diversity might have. “People would say, ‘I bet you forgot about X,’” Putnam says of the string of suggestions from colleagues. “There were 20 or 30 X's.” But even after statistically taking them all into account, the connection remained strong: Higher diversity meant lower social capital. In his findings, Putnam writes that those in more diverse communities tend to “distrust their neighbors, regardless of the color of their skin, to withdraw even from close friends, to expect the worst from their community and its leaders, to volunteer less, give less to charity and work on community projects less often, to register to vote less, to agitate for social reform more but have less faith that they can actually make a difference, and to huddle unhappily in front of the television.” “People living in ethnically diverse settings appear to ‘hunker down’—that is, to pull in like a turtle,” Putnam writes. In documenting that hunkering down, Putnam challenged the two dominant schools of thought on ethnic and racial diversity, the “contact” theory and the “conflict” theory. Under the contact theory, more time spent with those of other backgrounds leads to greater understanding and harmony between groups. Under the conflict theory, that proximity produces tension and discord. Putnam's findings reject both theories. In more diverse communities, he says, there were neither great bonds formed across group lines nor heightened ethnic tensions, but a general civic malaise. And in perhaps the most surprising result of all, levels of trust were not only lower between groups in more diverse settings, but even among members of the same group. “Diversity, at least in the short run,” he writes, “seems to bring out the turtle in all of us.” The overall findings may be jarring during a time when it's become commonplace to sing the praises of diverse communities, but researchers in the field say they shouldn't be. “It's an important addition to a growing body of evidence on the challenges created by diversity,” says Harvard economist Edward Glaeser. In a recent study, Glaeser and colleague Alberto Alesina demonstrated that roughly half the difference in social welfare spending between the US and Europe—Europe spends far more—can be attributed to the greater ethnic diversity of the US population. Glaeser says lower national social welfare spending in the US is a “macro” version of the decreased civic engagement Putnam found in more diverse communities within the country. Economists Matthew Kahn of UCLA and Dora Costa of MIT reviewed 15 recent studies in a 2003 paper, all of which linked diversity with lower levels of social capital. Greater ethnic diversity was linked, for example, to lower school funding, census response rates, and trust in others. Kahn and Costa's own research documented higher desertion rates in the Civil War among Union Army soldiers serving in companies whose soldiers varied more by age, occupation, and birthplace. Birds of different feathers may sometimes flock together, but they are also less likely to look out for one another. “Everyone is a little self-conscious that this is not politically correct stuff,” says Kahn. . . . So how to explain New York, London, Rio de Janiero, Los Angeles—the great melting-pot cities that drive the world's creative and financial economies? The image of civic lassitude dragging down more diverse communities is at odds with the vigor often associated with urban centers, where ethnic diversity is greatest. It turns out there is a flip side to the discomfort diversity can cause. If ethnic diversity, at least in the short run, is a liability for social connectedness, a parallel line of emerging research suggests it can be a big asset when it comes to driving productivity and innovation. In high-skill workplace settings, says Scott Page, the University of Michigan political scientist, the different ways of thinking among people from different cultures can be a boon. “Because they see the world and think about the world differently than you, that's challenging,” says Page, author of The Difference: How the Power of Diversity Creates Better Groups, Firms, Schools, and Societies. “But by hanging out with people different than you, you're likely to get more insights. Diverse teams tend to be more productive.” In other words, those in more diverse communities may do more bowling alone, but the creative tensions unleashed by those differences in the workplace may vault those same places to the cutting edge of the economy and of creative culture. Page calls it the “diversity paradox.” He thinks the contrasting positive and negative effects of diversity can coexist in communities, but “there's got to be a limit.” If civic engagement falls off too far, he says, it's easy to imagine the positive effects of diversity beginning to wane as well. “That's what's unsettling about his findings,” Page says of Putnam's new work. Meanwhile, by drawing a portrait of civic engagement in which more homogeneous communities seem much healthier, some of Putnam's worst fears about how his results could be used have been realized. A stream of conservative commentary has begun—from places like the Manhattan Institute and “The American Conservative”—highlighting the harm the study suggests will come from large-scale immigration. But Putnam says he's also received hundreds of complimentary emails laced with bigoted language. “It certainly is not pleasant when David Duke's website hails me as the guy who found out racism is good,” he says. In the final quarter of his paper, Putnam puts the diversity challenge in a broader context by describing how social identity can change over time. Experience shows that social divisions can eventually give way to “more encompassing identities” that create a “new, more capacious sense of ‘we,’” he writes. Growing up in the 1950s in small Midwestern town, Putnam knew the religion of virtually every member of his high school graduating class because, he says, such information was crucial to the question of “who was a possible mate or date.” The importance of marrying within one's faith, he says, has largely faded since then, at least among many mainline Protestants, Catholics, and Jews. While acknowledging that racial and ethnic divisions may prove more stubborn, Putnam argues that such examples bode well for the long-term prospects for social capital in a multiethnic America. In his paper, Putnam cites the work done by Page and others, and uses it to help frame his conclusion that increasing diversity in America is not only inevitable, but ultimately valuable and enriching. As for smoothing over the divisions that hinder civic engagement, Putnam argues that Americans can help that process along through targeted efforts. He suggests expanding support for English-language instruction and investing in community centers and other places that allow for “meaningful interaction across ethnic lines.” Some critics have found his prescriptions underwhelming. And in offering ideas for mitigating his findings, Putnam has drawn scorn for stepping out of the role of dispassionate researcher. “You're just supposed to tell your peers what you found,” says John Leo, senior fellow at the Manhattan Institute, a conservative think tank. “I don't expect academics to fret about these matters.” But fretting about the state of American civic health is exactly what Putnam has spent more than a decade doing. While continuing to research questions involving social capital, he has directed the Saguaro Seminar, a project he started at Harvard's Kennedy School of Government that promotes efforts throughout the country to increase civic connections in communities. “Social scientists are both scientists and citizens,” says Alan Wolfe, director of the Boisi Center for Religion and American Public Life at Boston College, who sees nothing wrong in Putnam's efforts to affect some of the phenomena he studies. Wolfe says what is unusual is that Putnam has published findings as a social scientist that are not the ones he would have wished for as a civic leader. There are plenty of social scientists, says Wolfe, who never produce research results at odds with their own worldview. “The problem too often,” says Wolfe, “is people are never uncomfortable about their findings.” Michael Jonas is acting editor of CommonWealth magazine, published by MassINC, a nonpartisan public-policy think tank in Boston. Robert Putnam is a faculty associate at the Weatherhead Center and Peter and Isabel Malkin Professor of Public Policy.

Bush Must Honor the Rule of Law - Heymann, Philip B. (Boston Globe, 2006)
BASED ON his constitutional powers and the authorization for the use of military force granted by congressional resolution after the events of Sept. 11, 2001, President Bush has declared himself free to ignore any law that he thinks limits his ability to fight terrorism. This is an extraordinary claim for any president in a country that prides itself on a rule of law binding government officials as well as ordinary citizens. In signing the McCain amendment outlawing cruel, inhuman, and degrading treatment of detainees this month, Bush announced that he might ignore the amendment in order to fight terrorism, the very field that the amendment, adopted by overwhelming majorities in both Houses, had specifically addressed. The statute forbids the president only to do anything that, in the circumstances, “shocks the conscience,” thus violating the due process clause of the Fifth Amendment. This leaves him broad discretion and little reason to claim powers Congress has specifically denied him. But that is what he has done. This is at least the fourth occasion Bush has announced that he is not bound by statutes or treaties. He has said he is also free to ignore statutes prohibiting torture, detention of Americans without legislative authority, and electronic surveillance for intelligence purposes without compliance with laws set up to regulate that activity. These claims could be consistent with obedience to statutory law only if either the Constitution had given him exclusive powers (a contention that few accept), or the situations in which he claims authority were so unusual as not to have ever been contemplated by Congress. Certainly the general words of the congressional authorization to use force to deal with Al Qaeda were not meant to overrule every statute the president felt was a hindrance in fighting terrorism. In each of these cases, Congress plainly addressed the very situations in which Bush now claims an exemption from law. The statute regulating electronic surveillance for intelligence purposes includes emergency and wartime exceptions. Congress had in mind the wartime detention of Japanese-Americans when it forbade detention of an American seized far from a war zone without a specific statute. The McCain amendment was intended to leave the president with discretion to apply the vague constitutional standard of “shocking the conscience,” but only that much discretion. Only the prohibition of torture is absolute and without exception, and Congress wanted it that way. Indeed, the president's defiance of statutory law is even bolder than this suggests. Each of these executive actions, taken in violation of specific statutory prohibitions, has been treated as a matter of national security secrecy, and therefore anyone who reveals the fact that the president is violating statutes passed by Congress is subject to the immediate threat of prosecution under the espionage statutes. The result in the recent case of wiretaps of Americans without judicial warrants is particularly bizarre. There was nothing secret about our technical capacity to monitor phone calls coming to or from the United States. Nor was there anything secret about our desire to do so to prevent terrorism. No one has, finally, revealed whose calls or e-mail messages were the subject of surveillance. All that could have been secret about the activities described in the New York Times was that the president was defying a law that most thought he had to obey. It is a fundamental mistake to think that the central domestic conflict about fighting terrorism is only between supporters of national security and supporters of civil liberties of Americans. The prior question is about the effect of law in the form of duly enacted statutes, negotiated between Congress and the president, reconciling these competing claims. The president is claiming that his powers to deal with terrorism as commander-in-chief override a negotiated compromise with the Congress, embodied in a statute signed by the president. He is saying, simply and flatly, that no law can stand in his way. We should not accept that claim. If the threat of terrorism is to be with us for decades, will our children and grandchildren remember a time when our president's actions were ruled by law? Philip B. Heymann, former US deputy attorney general, is a professor at Harvard Law School and a faculty associate of the Weatherhead Center for International Affairs.

Degrees of Latitude: Can US, Latin America Find Common Ground? - Coatsworth, John H. (Boston Globe, 2006)
The map tells the story. Latin Americans are voting for leftist or center-left governments in record numbers. Only El Salvador and Colombia seem certain to end 2006 with conservative governments still in power. While Latin America is moving to the left, the US government has moved to the right. The Bush administration is far more likely to oppose and far less interested in accommodating Latin American hopes for change than its predecessors. Can a collision between the United States and Latin America be avoided? Why is Latin America moving to the left? Should (North) Americans worry or cheer? Latin America freed itself from Spanish and Portuguese rule in the 1820s, but it took another half-century of civil strife to secure legal equality for indigenous citizens, end slavery, modernize institutions, and get economic growth started. But economic growth also made Latin America more unequal than ever before. With plenty of unskilled labor, wages stagnated while rents and profits rose rapidly. Worse yet, those at the top excluded others. Literacy and property requirements deprived most Latin American men and all women of the right to vote until well after World War II. In the 1930s and 1940s, Latin America began to change. Old dictatorships collapsed and democratic elections brought new, reformist governments to power. The new democracies nurtured vibrant civil societies by legalizing labor unions and encouraging organizations representing farmers and farm workers, rural communities and city neighborhoods, women, and minorities. Among the organizers and participants in this democratic upsurge were socialists, anarchists, liberals, and progressive-minded church people—along with communists and other radicals. In Brazil, Chile, Cuba, Guatemala, Mexico, and Peru, communists won wide support because of their role in supporting democratic movements. Many in Latin America saw this as dangerous—especially wealthy elites, conservative politicians and military officers, and the influential hierarchy of the Catholic Church. When the Cold War began, the United States allied itself with these reliably anticommunist groups. Governments of the left and center-left that failed to confront and exclude communists and their followers soon became anathema in Washington. The United States encouraged and even directly aided its Latin American allies to overthrow such governments, even when they were freely elected. By the early 1950s, the dictators were back. The Cuban Revolution formed part of a much larger wave of revolts against military dictatorships that brought democratic governments back to power in 10 Latin American countries between 1956 and 1960. Rather than work with this trend, the United States came to see it as potentially dangerous. The Castro regime fulfilled the prophecy when it sought Soviet aid to resist US efforts to destroy it. To prevent another Cuba, the United States called back the dictators again, despite the democratic rhetoric of the Alliance for Progress. By 1970, only Venezuela and Costa Rica were still holding open, competitive elections. For more than 40 years, from 1948 to the early 1990s, the United States used its power and resources to make sure that Latin Americans had governments more conservative (and thus anticommunist) than Latin American voters were willing to elect. The human cost of this effort was immense. Between 1960, after the Soviets had dismantled most of their gulags, and the Soviet collapse in 1990, the number of political prisoners, torture victims, and executions of nonviolent dissenters in Latin America vastly exceeded that of the Soviet Union and its East European satellites. Even when economic problems and protests drove the military from power in the 1980s, voters tended at first to elect conservative administrations to make sure the military would have no excuse to return to power. By the 1990s, however, voters had lost their fear. Civilian governments had succeeded in downsizing and purging military establishments and with the collapse of the Soviet Union, the United States was no longer so obsessed with keeping the left out of power. The conservative, mostly military governments of the Cold War had little interest in fixing inequality. Politicians and citizens who worried about inequality were the people these regimes jailed, tortured, and executed. Instead of overcoming inequality as their economies grew, the Latin American countries became more unequal. And then they stopped growing. The 1982 debt crisis helped to push military regimes from power but undermined the new democratic governments that replaced them. The centrist and center-right political parties and politicians that won the first democratic elections usually lost re-election bids. Second-time elections often benefited centrist and populist parties anxious to jump start economic growth. Many opted for a package of reforms that came to be called the “Washington Consensus”—balanced budgets, freer trade, deregulation, and privatization. With a few exceptions, such as Chile, these orthodox economic reforms did not generate sustained economic growth. Most countries experienced short spurts of growth followed by reversals, some linked to volatile capital outflows as investment fund managers in the United States and Europe panicked when slow growth undermined currencies and governments failed to raise the revenues they needed to pay off their debts. In the quarter century from 1980 to 2005, Latin America has barely grown at all—the worst quarter century in Latin American economic history since the civil wars after independence from the 1820s to the 1850s. It is important not to forget, however, that despite its recent travails, most of Latin America ended the 20th century much better off than at the beginning. The per capita gross domestic product of the region's major economies averaged about 1.5 percent, roughly equal to the US economy. The fastest growing economy in the western hemisphere for the past hundred years was not the United States but Brazil. Living standards also improved. Latin America is not the poorest region in the world, though some Latin American countries, including Bolivia, Haiti, and Honduras, rival the poverty of Africa and South Asia. In fact, Latin America has a large number of middle class voters impatient with the failure of the governments they elect to improve conditions for their poverty-stricken fellow citizens. Political systems that seem rigged for wealthy elites, persistent and highly visible inequalities, and economies where living standards have not risen for 20 years have pushed Latin American voters back to the left. The only surprise is how long it has taken. Some leftist and center-left governments have performed brilliantly. The best example is Chile, where a coalition of Socialists and Christian Democrats has raised economic growth from less than 1.5 percent under the Pinochet dictatorship to over 5 percent since the restoration of democracy in 1990—and managed to reduce poverty dramatically at the same time. In fact, economic growth in countries with leftist or center-left governments was more than twice as fast in 2005 as in countries with conservative or center-right governments. For US policy makers accustomed to having their way in the hemisphere, the temptation to intervene, overtly or covertly, to reverse Latin America's leftward drift will likely grow harder to resist in 2006. The likely strategy will be to look for ways to drive a wedge between the noisier anti-American, pro-Cuban regimes in Venezuela and Bolivia and the more moderate administrations elsewhere. This strategy will probably fail, because the United States has so little to offer even its conservative friends after essentially giving up on new free trade agreements. Faced with few peaceful options, the United States may drift back to the Cold War policies of the 1960s and 1970s—or to the dollar diplomacy that preceded it. Between 1898 and 1994, the US government succeeded in overthrowing, or inducing friends to overthrow, no fewer than 41 Latin American governments (a dozen of them freely elected). That's one every 28 months. Before it goes that route again, the United States should probably consider modifying its ideologically driven hostility to such regimes. A little pragmatism, coupled with a ban on overthrowing elected governments, would make a good start. John H. Coatsworth is a professor of Latin American affairs, director of the David Rockefeller Center for Latin American Studies, and a member of the Executive Committee of the Weatherhead Center for International Affairs at Harvard University.

Assessing China's Power - Nye, Joseph S., Jr. (Boston Globe, 2006)
When China's President Hu Jintao visits Washington this week, George W. Bush will confront one of the key challenges of his presidency—how to respond to China's increasing economic and military power. Everyone agrees that the rise of China is one of the transformative changes of this century, but Washington is divided between “panda huggers” who welcome it and “China hawks” who express alarm. Secretary of Defense Donald Rumsfeld, for example, complains that China's defense budget has increased by double digits since the mid-1990s, and will grow this year by 14.7 percent. Senators Charles Schumer, Lindsey Graham, and others believe that China's manipulation of the yuan is costing American jobs, and they threaten retaliation. Democracy and human rights advocates point to China's abysmal ratings in Freedom House's survey of the least free countries in the world. A recent poll reports that one-third of Americans believe that China will “soon dominate the world,” while 54 percent see the emergence of China as a “threat to world peace.” Some commentators have argued that China will be as disruptive to the beginning of the 21st century as the Kaiser's Germany was to the 20th century. But such views exaggerate China's power. Measured by official exchange rates, China is the fourth largest economy in the world and is growing at 9 percent annually, but its income per capita is only $1,700, or one-twenty-fifth that of the United States. China's research and development is only 10 percent of the American level. If both the United States and China continue to grow at their current rates, it is possible that China's total economy could be larger than ours in 30 years, but American per capita income will remain four times greater. In addition, China's military power is far behind, and it lacks the soft power resources such as Hollywood and world-class universities that America enjoys. In contrast, the Kaiser's Germany had already passed Great Britain in industrial production by 1900, and launched a serious military challenge to Britain's naval supremacy. The fact that China is a long way from overtaking the United States does not prevent a possible war over Taiwan, which China regards as a lost province. Weaker countries sometimes attack stronger countries—witness Japan at Pearl Harbor. But such a conflict is not inevitable as long as Taiwan does not declare formal independence and China does not become impatient. With time and generational change, this might be one of the rare conflicts that becomes more tractable over time. We faced these problems a decade ago when the Clinton administration formulated our strategy for East Asia. We knew that hawks who called for containment of China would not be able to rally other countries to that cause. We also knew that if we treated China as an enemy, we were ensuring future enmity. While we could not be sure how China would evolve, it made no sense to foreclose the prospect of a better future. Our response combined balance of power with liberal integration. We reinforced the US-Japan alliance so that China could not play a “Japan card” against us, while inviting China to join the World Trade Organization. In a rare case of bipartisan comity, the Bush administration has continued that strategy. China is now our third largest trade partner and second largest official creditor. Critics contend this trade with China has made us vulnerable. China could hurt us by dumping its holdings of dollars, but to do so would also damage its own economy. The yuan may be somewhat undervalued, but China accounts for only a third of the increase in America's trade deficit over the past five years, and a revaluation will not remove our deficit. As for jobs, even if America bars low-cost goods from China, we will import them from somewhere else. To solve our economic problems, we must get our own house in order by raising savings, cutting deficits, and improving our basic education. China's internal evolution remains uncertain. It has lifted 400 million people out of poverty since 1990, but another 400 million live on less that $2 per day. It has enormous inequality, a migrant labor force of 140 million, severe pollution, and rampant corruption. Political evolution has failed to match economic progress. While more Chinese are free today than ever before in Chinese history, China is far from free. Some 110 million Chinese use the Internet, but the government censors the Internet. The danger is that party leaders, trying to counter the erosion of communism, will use nationalism as their ideological glue, and this could lead to an unstable foreign policy. Faced with such uncertainty, President Bush has offered China a strategic dialogue to encourage it to evolve as a “responsible stakeholder.” He can take a lead from Ronald Reagan, who used the phrase “trust but verify.” For China, the right strategy is “embrace, but hedge.” Joseph Nye, a Harvard University professor, was assistant secretary of defense for international security affairs in 1994 and 1995. He is author of The Power Game: A Washington Novel. He is a member of the Executive Committee of the Weatherhead Center for International Affairs.

France Shows Its True Colors - Lamont, Michèle; Laurent, Éloi (Boston Globe, 2006)
More than six months have passed since last fall's violent urban riots, and France finds itself engaged in another parliamentary debate on the integration of immigrants. The right wing, which advocates a “chosen immigration,” and the left, which anticipates a “disposable immigration,” share a firm belief in French Républicanisme, a social contract that owes much to Jean-Jacques Rousseau's fantasy of an irresistible general will overcoming particular interest. Républicanisme, the French ideological equivalent of the American dream, proposes that a universal citizen, abstracted from social and economic conditions (whether residential, religious, ethnic, or racial), engages in a direct relationship with the state. It reciprocates by downplaying the role of such identities in the political process. In so doing, the state rejects what it perceives as political balkanization and identity politics as incompatible with the realization of the common good. The main flaw of this near-sacrosanct ideal of Républicanisme is that it inhibits the use of anti-discrimination laws. Even while studies repeatedly reveal widespread discrimination in France, few people are motivated to seek legal redress. The first report of the new anti-discrimination authority shows that only 1,800 claims were filed in 2005, and that only 600 have been followed by action. The frustration and resentment expressed by French minorities is largely caused by the contradiction between a fantasized equality and real-life discrimination. Yet, there is nothing inevitable in this sorry state of affairs. Over the last few months, developments have opened new perspectives. Last November, the first federation of “Blacks of France” was created, bringing together blacks who are French citizens by birth, because they were born in French overseas departments such as Martinique and Guadeloupe; black youth of the second generation, often from Sub-Saharan Africa, who become citizens when they turn 18; and other blacks, who have a range of backgrounds. Another positive development was the appointment in March of the first black prime-time anchor on the most widely watched television channel. Only a few weeks ago, the cover of an influential newsmagazine read “Us, Blacks of France” and featured Keyza Nubret, a French black woman manager. Not surprisingly, this colorful France (estimates vary between 2.5 million and 5 million for the number of blacks in France) is made visible outside of the realm of the Republican state. May 10, the commemoration day of the abolition of slavery, was marked by tensions between the austere gravitas of the Republic and the wish of most black associations for more lively ceremonies. Still these events signal the official entry into the French public sphere of an interest group whose “groupness” is based on shared ascribed characteristics—a minor earthquake in the French political landscape. Sadly, since this welcomed wind of change has started to blow, the academic world has remained intriguingly silent. With the exception of a few courageous souls, what still marks so many members of the French intellectual class is their overall commitment to the ideology of Républicanisme and its ideal of assimilation. While Paul Gilroy's “There Ain't no Black in the Union Jack” had a palpable effect on debates about what Englishness means, France has yet to produce an intellectual of comparable influence. Only by coming to terms with their own cultural imperialism will French intellectuals contribute to the challenges of better incorporating the members of minority groups into the French polity. Only then will they live up to the powerful (Sartrian) tradition of the engaged intellectual. The slowly emerging reality of a colorful France does not mean that the principles of French citizenship are to be thrown overboard and that ethnic quotas have to be instituted everywhere from prime time to public service. Rather, it means that representation matters, and that France cannot prosper if it continues to deceive its immigrants by promising equality while delivering segregation. Michèle Lamont is professor of sociology and African and African-American Studies at Harvard University. She is also a faculty associate of the Weatherhead Center. Éloi Laurent is an economist at l'Observatoire Français des Conjonctures Economiques in Paris and a visiting scholar at the Center for European Studies at Harvard University.

Globalizing Good Government - Fisher, Richard W.; Cox, W. Michael (New York Times, 2006)
The protests in France over job security for young workers have exposed the fault lines between globalization and public policy. On the one hand, the French government has recognized that the country's labor laws are uncompetitive and a drain on the economy. The public reaction, however, shows the depth of popular misunderstanding regarding the realities of our globalizing economy. Nations can no longer sit within their borders and pursue policies incompatible with an increasingly integrated world economy. The types of services, manufacturing and entrepreneurship that generate national wealth are more mobile than ever, and they will forsake countries that shackle business and labor with unnecessary burdens. With this in mind, the Federal Reserve Bank of Dallas set out to document the connection between globalization and public policy. We found that the more globalized nations tend to pursue policies that achieve faster economic growth, lower inflation, higher incomes and greater economic freedom. The least globalized countries are prone to policies that interfere with markets and lead to stagnation, inflation and diminished competitiveness. For our study, we began with research by Foreign Policy magazine and AT Kearney, a management consultancy firm, which ranked 60 countries by degree of globalization. Singapore, Ireland, the United States and other countries at the top of the rankings are far more integrated into the world economy than the insulated nations at the bottom like Iran, Egypt and Bangladesh. As the accompanying charts show, we divided the countries into four groups and looked at how each faction performed on policies that shape economic performance. Take inflation. In a world where investment capital can flit anywhere in the world with the click of a computer mouse, nations should see the virtue of price stability and preserving the value of money. And they do: the more globalized countries we studied had an average inflation rate of 2.3 percent from 2001 to 2003, compared with 10 percent for the nations in the least globalized quarter. This pattern is repeated in more than a dozen aspects of effective public policy, as measured by the World Bank, Harvard University, the Heritage Foundation, Transparency International and the Fraser Institute, a Canadian public policy group. (Although these groups used various ranking systems to portray their data, we took the liberty of converting each to a 1-to-10 scale, with 10 being the most successful, for the accompanying graphs.) The gist is clear: as nations become more integrated into the world economy, they tend to maintain fewer barriers to trade and the movement of money. They are less likely to impose punishing corporate taxes and onerous regulations. Their technology policies are more favorable to innovation. Nations more open to the world economy score above the less globalized countries in respect for the rule of law and protection of property rights. More globalized countries also offer greater political stability. Not all policies fit neatly into this framework. We found that more globalized counties do no better in limiting the size of government, which we consider vital to economic prosperity. They are worse than the less globalized in containing public entitlements and subsidies, which must be paid for by higher individual income taxes. Perhaps it is because they are richer and have the means to spread those riches through their societies. The French contretemps illustrates why labor policies are less sensitive to globalization than factors like taxation and trade barriers. As long as workers refuse to acknowledge that they are competing in a world economy, they will petition a wealthy government to protect their jobs. This in turn slows job growth and raises unemployment, creating a greater demand for expensive and expansive safety nets for idle workers. Still, globalization may yet alter labor policies. France, Germany and other countries are beginning to recognize that their labor rules are uncompetitive, and the timing of change is a political question, not an economic one. So, do our statistics show that globalization is necessarily the cause of good policies? That would be overstating it—our data simply show the two trends are complementary. But it is clear that countries with solid policies will be more successful in the global economy, encouraging further openness and deeper cross-border connections. The chicken-and-egg debate shouldn't detract from the fundamental fact that globalization and good policies go together. Globalization's critics argue that a more open world economy sets off a race to the bottom by encouraging countries to jettison protections for consumers, workers and the environment. In reality, the opposite is true. If our data demonstrate anything, it is that globalization prompts a race to the top by pushing countries to abandon policies that burden their economies in favor of those that fuel growth and economic opportunity. Richard W. Fisher and W. Michael Cox are, respectively, the president and the chief economist of the Federal Reserve Bank of Dallas. Peter Hoey is an illustrator in Arcata, Calif. Richard W. Fisher is also a former Fellow of the Weatherhead Center for International Affairs.

Hamas at the Helm - Christia, Fotini; Mitter, Sreemati (New York Times, 2006)
Nablus, West Bank THE crescent has risen. The militant Islamic group Hamas won an astonishing 76 of 132 seats in the Palestinian legislative elections this week. The United States and the European Union must finally recognize Hamas's ascendance as a fait accompli. Until now, these key third parties have equivocated: they pressed Israel to allow Hamas to participate in the elections but threatened to cut aid and ties to a Hamas-dominated Palestinian Authority. The practical reality, however, is that Hamas is a pivotal player in Palestinian politics, and no peace process can succeed without at least the tacit acceptance of its leaders. Moreover, Hamas's participation in Palestinian politics is not necessarily a bad thing, and resisting it will very likely do more harm than good. As a political party, Hamas revealed itself to be disciplined, pragmatic and surprisingly flexible. It fielded well-regarded candidates, including doctors and academics. In some cases, Hamas aligned itself with independents once affiliated with the secular Fatah party. And although the Hamas charter calls for the destruction of Israel and the liberation of Palestine “from the river to the sea,” the party's campaign manifesto made no mention of these goals. Instead, when asked about making peace with Israel, Hamas representatives offered nuanced, if evasive, answers. As Ziad Daiah, a Hamas representative in Ramallah, told us: “We are not interested in the Oslo-type peace process that went on for 10 years and wasted time. But if Israel will start new negotiations, with direct benefits for Palestinians in a useful time frame, we will accept that.” Judging from the thousands of green posters plastered around the West Bank and Gaza, external matters like the peace process were not central to Hamas's electoral agenda. Rather, its campaign focused on popular concerns like fighting corruption, establishing good governance and restoring the rule of law. Hamas's victory speeches have emphasized the need to revamp public services. To be sure, we should be careful not to read too much into Hamas's electioneering. The Hamas charter retains poisonous language toward Israel, and the group has yet to renounce its views on the place of violence in the Palestinian resistance. And Hamas's Islamist agenda continues to alarm many secular Palestinians, even those who welcome its entry into politics. Still, Hamas statements indicate that these attitudes are not set in stone. As Mohammed Ghazel, a Hamas leader in Nablus, told the Israeli newspaper Ha'aretz, “The charter is not the Koran.” And Hamas has done more than any other armed faction to honor the truce that President Mahmoud Abbas brokered in February. Although Israel continues to arrest its members, Hamas has done little to retaliate. Such restraint might have been an electoral strategy, but it still proves that if the incentives are right, Hamas can hold its fire. In any case, the United States and Europe cannot trumpet democratic ideals abroad and then ignore the popular will of Palestinian voters, 78 percent of whom turned out for this election. Refusing to engage with Hamas, however skeptical one may be of its intentions, will only further legitimize the party; it could even give rise to violence. Moreover, cutting off aid to the Palestinian Authority, which is already in a fiscal crisis and enormously dependent on foreign aid, could bankrupt it, further destabilizing the region. Hamas has indisputably become the force to be reckoned with in Palestinian politics. Even Israel seems to have awakened to this reality. A radio reporter recently asked Shimon Peres, the former Israeli prime minister, about negotiating with Hamas. “We are not fighting against a name,” he said. “We are fighting against a situation. If the situation changes, then what difference does a name make?” If the Israelis are contemplating engagement, it's time the Americans and Europeans did, too. Fotini Christia is a fellow at the Olin Institute for Strategic Studies at Harvard. Sreemati Mitter works for the Palestinian Initiative for the Promotion of Global Dialogue and Democracy in Ramallah, West Bank.

Identity and Violence - Ashbrook, Tom; Sen, Amartya (WBUR, On Point with Tom Ashbrook, 2006)
Nobel prize-wining economist Amartya Sen has long since looked beyond the numbers of development and growth and into the affairs of the human heart. What he sees there these days he finds deeply troubling. From East to West, he warns, people around the world are being boxed into narrow, dangerous understandings of their own identity. Reduced from full and complex human beings to simply Muslim, Christian, Shiite, Sunni, Jew. Sen has a bone to pick with Samuel Huntington's “Clash of Civilizations” thesis. It is the road to hell, he says. But maybe we were already on it. Hear Nobelist Amartya Sen talk about identity, violence and what he calls the “illusion of destiny”. Listen to On Point with Tom Ashbrook and Amartya Sen. Amartya Sen is Lamont University Professor at Harvard University and a Faculty Associate at the Weatherhead Center for International Affairs.

A Poverty of the Mind - Patterson, Orlando (New York Times, 2006)
Cambridge, Mass. Several recent studies have garnered wide attention for reconfirming the tragic disconnection of millions of black youths from the American mainstream. But they also highlighted another crisis: the failure of social scientists to adequately explain the problem, and their inability to come up with any effective strategy to deal with it. The main cause for this shortcoming is a deep-seated dogma that has prevailed in social science and policy circles since the mid-1960's: the rejection of any explanation that invokes a group's cultural attributes—its distinctive attitudes, values and predispositions, and the resulting behavior of its members—and the relentless preference for relying on structural factors like low incomes, joblessness, poor schools and bad housing. Harry Holzer, an economist at Georgetown University and a co-author of one of the recent studies, typifies this attitude. Joblessness, he feels, is due to largely weak schooling, a lack of reading and math skills at a time when such skills are increasingly required even for blue-collar jobs, and the poverty of black neighborhoods. Unable to find jobs, he claims, black males turn to illegal activities, especially the drug trade and chronic drug use, and often end up in prison. He also criticizes the practice of withholding child-support payments from the wages of absentee fathers who do find jobs, telling The Times that to these men, such levies “amount to a tax on earnings.” His conclusions are shared by scholars like Ronald B. Mincy of Columbia, the author of a study called “Black Males Left Behind,” and Gary Orfield of Harvard, who asserts that America is “pumping out boys with no honest alternative.” This is all standard explanatory fare. And, as usual, it fails to answer the important questions. Why are young black men doing so poorly in school that they lack basic literacy and math skills? These scholars must know that countless studies by educational experts, going all the way back to the landmark report by James Coleman of Johns Hopkins University in 1966, have found that poor schools, per se, do not explain why after 10 years of education a young man remains illiterate. Nor have studies explained why, if someone cannot get a job, he turns to crime and drug abuse. One does not imply the other. Joblessness is rampant in Latin America and India, but the mass of the populations does not turn to crime. And why do so many young unemployed black men have children—several of them—which they have no resources or intention to support? And why, finally, do they murder each other at nine times the rate of white youths? What's most interesting about the recent spate of studies is that analysts seem at last to be recognizing what has long been obvious to anyone who takes culture seriously: socioeconomic factors are of limited explanatory power. Thus it's doubly depressing that the conclusions they draw and the prescriptions they recommend remain mired in traditional socioeconomic thinking. What has happened, I think, is that the economic boom years of the 90's and one of the most successful policy initiatives in memory—welfare reform—have made it impossible to ignore the effects of culture. The Clinton administration achieved exactly what policy analysts had long said would pull black men out of their torpor: the economy grew at a rapid pace, providing millions of new jobs at all levels. Yet the jobless black youths simply did not turn up to take them. Instead, the opportunity was seized in large part by immigrants—including many blacks—mainly from Latin America and the Caribbean. One oft-repeated excuse for the failure of black Americans to take these jobs—that they did not offer a living wage—turned out to be irrelevant. The sociologist Roger Waldinger of the University of California at Los Angeles, for example, has shown that in New York such jobs offered an opportunity to the chronically unemployed to join the market and to acquire basic work skills that they later transferred to better jobs, but that the takers were predominantly immigrants. Why have academics been so allergic to cultural explanations? Until the recent rise of behavioral economics, most economists have simply not taken non-market forces seriously. But what about the sociologists and other social scientists who ought to have known better? Three gross misconceptions about culture explain the neglect. First is the pervasive idea that cultural explanations inherently blame the victim; that they focus on internal behavioral factors and, as such, hold people responsible for their poverty, rather than putting the onus on their deprived environment. (It hasn't helped that many conservatives do actually put forth this view.) But this argument is utterly bogus. To hold someone responsible for his behavior is not to exclude any recognition of the environmental factors that may have induced the problematic behavior in the first place. Many victims of child abuse end up behaving in self-destructive ways; to point out the link between their behavior and the destructive acts is in no way to deny the causal role of their earlier victimization and the need to address it. Likewise, a cultural explanation of black male self-destructiveness addresses not simply the immediate connection between their attitudes and behavior and the undesired outcomes, but explores the origins and changing nature of these attitudes, perhaps over generations, in their brutalized past. It is impossible to understand the predatory sexuality and irresponsible fathering behavior of young black men without going back deep into their collective past. Second, it is often assumed that cultural explanations are wholly deterministic, leaving no room for human agency. This, too, is nonsense. Modern students of culture have long shown that while it partly determines behavior, it also enables people to change behavior. People use their culture as a frame for understanding their world, and as a resource to do much of what they want. The same cultural patterns can frame different kinds of behavior, and by failing to explore culture at any depth, analysts miss a great opportunity to re-frame attitudes in a way that encourages desirable behavior and outcomes. Third, it is often assumed that cultural patterns cannot change—the old “cake of custom” saw. This too is nonsense. Indeed, cultural patterns are often easier to change than the economic factors favored by policy analysts, and American history offers numerous examples. My favorite is Jim Crow, that deeply entrenched set of cultural and institutional practices built up over four centuries of racist domination and exclusion of blacks by whites in the South. Nothing could have been more cultural than that. And yet America was able to dismantle the entire system within a single generation, so much so that today blacks are now making a historic migratory shift back to the South, which they find more congenial than the North. (At the same time, economic inequality, which the policy analysts love to discuss, has hardened in the South, like the rest of America.) So what are some of the cultural factors that explain the sorry state of young black men? They aren't always obvious. Sociological investigation has found, in fact, that one popular explanation—that black children who do well are derided by fellow blacks for “acting white”—turns out to be largely false, except for those attending a minority of mixed-race schools. An anecdote helps explain why: Several years ago, one of my students went back to her high school to find out why it was that almost all the black girls graduated and went to college whereas nearly all the black boys either failed to graduate or did not go on to college. Distressingly, she found that all the black boys knew the consequences of not graduating and going on to college ("We're not stupid!" they told her indignantly). SO why were they flunking out? Their candid answer was that what sociologists call the “cool-pose culture” of young black men was simply too gratifying to give up. For these young men, it was almost like a drug, hanging out on the street after school, shopping and dressing sharply, sexual conquests, party drugs, hip-hop music and culture, the fact that almost all the superstar athletes and a great many of the nation's best entertainers were black. Not only was living this subculture immensely fulfilling, the boys said, it also brought them a great deal of respect from white youths. This also explains the otherwise puzzling finding by social psychologists that young black men and women tend to have the highest levels of self-esteem of all ethnic groups, and that their self-image is independent of how badly they were doing in school. I call this the Dionysian trap for young black men. The important thing to note about the subculture that ensnares them is that it is not disconnected from the mainstream culture. To the contrary, it has powerful support from some of America's largest corporations. Hip-hop, professional basketball and homeboy fashions are as American as cherry pie. Young white Americans are very much into these things, but selectively; they know when it is time to turn off Fifty Cent and get out the SAT prep book. For young black men, however, that culture is all there is—or so they think. Sadly, their complete engagement in this part of the American cultural mainstream, which they created and which feeds their pride and self-respect, is a major factor in their disconnection from the socioeconomic mainstream. Of course, such attitudes explain only a part of the problem. In academia, we need a new, multidisciplinary approach toward understanding what makes young black men behave so self-destructively. Collecting transcripts of their views and rationalizations is a useful first step, but won't help nearly as much as the recent rash of scholars with tape-recorders seem to think. Getting the facts straight is important, but for decades we have been overwhelmed with statistics on black youths, and running more statistical regressions is beginning to approach the point of diminishing returns to knowledge. The tragedy unfolding in our inner cities is a time-slice of a deep historical process that runs far back through the cataracts and deluge of our racist past. Most black Americans have by now, miraculously, escaped its consequences. The disconnected fifth languishing in the ghettos is the remains. Too much is at stake for us to fail to understand the plight of these young men. For them, and for the rest of us. Orlando Patterson, a professor of sociology at Harvard and a faculty associate of the Weatherhead Center for International Affairs, is the author of Rituals of Blood: Consequences of Slavery in Two American Centuries.

Saving the World, a Carpet at a Time - Owens, Mitchell (The New York Times, 2006)
Two years ago Paulette Cole had a big idea that would alter the fundamental nature of her company. She not only wanted its furniture to be environmentally conscious; she wanted, to whatever degree possible, every chair, lamp and pillow sham to have social resonance beyond the cash-and-carry transaction, whether that meant the preservation of a dwindling rain forest or help for an impoverished, widowed weaver. So she called a meeting with her senior management and laid out a new business plan. Not everybody was thrilled. “Some people thought my vision was flaky,” Ms. Cole said. A few staff members later chose to leave, she said, in “a natural peel-away of people who didn't understand that vision.” “They didn't understand,” she said, “that we were in a position to create the demand.” Ms. Cole's company isn't just the kicky little boutique that could. It is ABC Carpet and Home, the trendsetting Manhattan department store, which had nearly $80 million in sales last year, according to Hoover's business reports. It is where pricey Frette sheets share sales floors with French handmade chocolates and antique Chinese beds. But increasingly ABC shoppers can also buy jewelry made by Ugandan women afflicted with AIDS, ceramics whose proceeds go to foster schools in rural Guatemala and $1,000 gift certificates that help support Masai girls who refuse to undergo genital mutilation. “Knowing that your investment in a product actually has a positive effect on somebody's life makes the design in your hands more important,” Ms. Cole, 46, ABC's president and chief executive, said recently at her engagingly funky Manhattan apartment, where breakfast is taken at an elaborately carved Anglo-Indian table in a stainless-steel kitchen. “My goal is for the store to be 100 percent responsible design.” She may never reach that level, she admitted, but she said that 20 percent of ABC's stock now fulfills the goal. That's 3 percentage points more than last year, she explained, and it includes ambitious offerings like made-to-order solar energy systems and furniture with all-organic upholstery. The store's packing materials have been replaced with biodegradable alternatives, and all inks used in packaging and stationery are soy-based. A trailer from “An Inconvenient Truth,” the documentary that opened last night on Al Gore and his campaign about global warming, is shown on continuous loop on the second floor amid furniture made from sustainable materials. The company promotes not only the ABC Home and Planet Foundation, which encourages people to “align their spending choices with their personal values,” but also its associations with 15 organizations including Doctors Without Borders and the Rainforest Action Network. As Home Furnishings News, an industry weekly, put it this week in its cover story about environmentally correct home products, ABC “has made social consciousness a mainstay of its business plan.” Back in the 1990's, however, ABC was best known for its boho bling. Working with her husband and co-chief executive at the time, Evan Cole, Ms. Cole transformed the carpet business that her paternal great-grandfather founded in 1897 into a hippie-chic lifestyle destination. She was the engaging but somewhat reserved creative director; the flamboyant Mr. Cole attended to the bottom line and pumped up the publicity volume. The huge display windows seemed decorated by Miss Havisham with help from Tim Burton, with piles of lovingly battered antiques and artfully dusty candelabra. Indoors was—and still is—an extravaganza of elegant flea-market finds (ormolu-encrusted headboards, Art Deco dressing tables) and boutiques leased to name-brand manufacturers (Harvey Electronics, Mitchell Gold furniture, Pratesi linens). Profits soared, but the Coles's partnership took a beating. Two of their children died in infancy (the couple have a daughter, Lena, who is 11), and professional disagreements drove them further apart. Mr. Cole's eagerness to expand ABC's reach (a branch opened at Harrods in London in 1998) clashed with his wife's rising interest in making social issues an official company statement. “Post-9/11, I took a leave of absence,” Ms. Cole said, adding diplomatically, “It was the most realistic scenario.” With her daughter often in tow, she went to Mexico, Morocco, Peru and points beyond, experiencing what she called “a different level of travel.” She sought out environmentalists, became involved in anti-hunger campaigns and studied poverty in the developing world. “I chose to look at things the business didn't allow me to experience,” she said. Ms. Cole also began to see the possibility of using ABC as a soapbox for her causes. It was a vision her husband did not share. The couple divorced, and Mr. Cole sold her his shares in the family-owned company. He now lives in Los Angeles, where he founded H. D. Buttercup, a 100,000-square-foot home furnishings mall. Once Ms. Cole became the company's sole chief executive she began to steer it in a new direction. Concerns over fair-labor issues and environmental responsibility are fast becoming part of the home furnishings world, but not all shoppers will become converts. As Marshal Cohen, the chief industry analyst at the NPD Group, a market research company in Port Washington, N.Y., and the author of “Why Customers Do What They Do” (McGraw-Hill) put it in a telephone interview, “In many cases the consumer is not overly responsive to philanthropic causes.” “It's a big challenge convincing people that there's a good reason behind a higher price point,” Mr. Cohen said. “Often the most successful way to do that is through the lifestyle connection, to convince consumers to do the right thing or the healthy thing, which is why the fastest-growing segment of the beverage industry is organic milk.” But according to a study of shoppers' behavior at ABC from June to November of last year, customers willingly paid up to 20 percent more for products bearing labels that cited a positive social impact—in particular, the use of fair labor practices in their manufacture. (The study, by Michael J. Hiscox, a government professor at Harvard, and Nicholas F. B. Smyth, a Harvard senior, compared purchases of similar products to see if the presence of the labels made any difference; they did.) In a store like ABC, with affluent customers and a reputation for a commitment to social causes, Dr. Hiscox and Mr. Smyth wrote, the data showed that “firms that switch to labeled goods could charge between 10-20 percent extra and expect sales to rise, with stronger effects likely for luxury goods (like candles) than for normal goods (such as towels).” Dr. Hiscox explained via e-mail on Tuesday that ABC was the focus of his study because Ms. Cole was “bold enough to participate in our study when other retailers would not, because they were worried about raising the labor standards issue with their customers.” Ms. Cole may be raising the consciousness of ABC, but her concerns are not purely altruistic. “Beauty is the major criterion for me,” she said. “This isn't charity; this is commerce. If there's a product I fall in love with that doesn't have a socially redeeming value attached to it, I might not be able to resist it.” And when that happens, she has a practical, unapologetic solution: “It just won't get a ‘Good Wood’ label.” Michael J. Hiscox is a professor of government at Harvard University and a faculty associate of the Weatherhead Center for International Affairs.

Wanted: A Leader for Harvard - Putnam, Robert D. (Boston Globe, 2006)
Larry Summers's experience says much about what Harvard—and any great university—should look for in a president. Summers was not forced out by a radical segment of the faculty of arts and sciences. He was not forced out because bold visions threatened a complacent faculty. Most faculty in arts and sciences are eager to reinvigorate undergraduate education, strengthen cutting-edge science, internationalize the university, develop the Allston campus, and encourage collaboration among the schools. Any president of Harvard at this time would have essentially the same goals. Achieving such goals requires raw intelligence, which Summers has in abundance. But more crucial to leadership than IQ is the ability to inspire others with your vision and to help them come to see it as their vision, too. You must understand the culture of an institution even as you try to change it. Business Week wrote: “Summers joins the ranks of recent leaders brought in to generate change in organizations only to misfire and fail, [such as] Carly Fiorina at Hewlett-Packard.” Giving orders goes only so far. As the late Richard Neustadt, America's premier student of the US presidency, put it: Presidential power is the power to persuade. During his presidency, Summers planned the Allston campus and rationalized the budget, but failed to make progress toward his central academic goals. He came in with much political capital, but frittered it away on battles he did not need to fight. He alienated even those—from all disciplinary and ideological backgrounds—most committed to his goals and to Harvard. Take one of Summers's highest priorities—reforming the undergraduate curriculum. Successful curricular reform requires that hundreds of instructors change their behavior in hundreds of classrooms that cannot be policed. The hard part about curricular reform is not finding the right answer, because there is no single right answer. The hard part is inspiring and persuading. Harvard's justly famed (though now outdated) Core Curriculum of the 1970s succeeded not because of its rationale or rules, but because the process of reform itself reinvigorated an entire generation of instructors who (for several decades) then took teaching more seriously. Most Harvard faculty agree that our undergraduate education needs change, perhaps even radical change. But to forge a consensus out of many creative but discordant ideas requires deft leadership. That was what Derek Bok brought to the task then. That is the quality Harvard should seek now in its next president. Bold statements and a forceful personality are not enough. Indeed, clumsily applied, boldness and forcefulness can lead to weakness. What was most dispiriting about Summers's final year to those who shared his values was that he relinquished the capacity to say no, even to bad ideas. “Superman is surrounded by kryptonite,” said one irrepressible colleague. “Now is the time to move.” Political correctness was not the root of the problem, and politically correct decisions could not solve it. One especially misguided idea is that deans and presidents should be chosen by faculty. Harvard is already unduly decentralized, and faculty-chosen executive leadership is a recipe for blandness. Larry Summers understood that perfectly well, but having squandered political capital through four arrogant years, he acquiesced in unwise limits on presidential discretion. Harvard's next leader must have sufficient emotional and social intelligence to preserve the ability to say no. Above all, the power to persuade depends on the capacity to maintain trust. Colleagues need to believe that leaders will not only act honorably but speak truthfully. Once a faculty comes to believe that their president is “less than truthful” (as a former dean reportedly said of this president), the basis for leadership of any kind has vanished. Harvard is a strong university. Its faculties, including its Faculty of Arts and Sciences, want bold change. Professors do not agree on exactly what the changes should be. That is the nature of a great faculty—the more creative, the more likely to disagree. But Harvard faculty have followed strong leaders in the past, and they will follow them in the future. What Harvard needs now is a boldly reformist leader, but one who actually knows how to make reform happen. Robert D. Putnam is the Malkin Professor of Public Policy at Harvard University and a member of the Executive Committee of the Weatherhead Center for International Affairs.

When Terrorists Go Mainstream - Toft, Monica Duffy (Boston Globe, 2006)
PERHAPS THE biggest surprise about this week's election results, in which the terrorist group Hamas won a majority of seats in the Palestinian parliament, is that it was a surprise to us at all. There are two main reasons why. First, many in this country have fallen victim to the notion that if today's rogue states are bad neighbors, democratization will make them good neighbors. A central pillar of the current Bush administration's foreign policy is that dictators make bad neighbors. In other words, we can expect authoritarian governments to start wars and support terrorism more readily than democratic governments. When the current US administration first took office, the security concern of the day was “rogue states,” a euphemism for Afghanistan, North Korea, Iraq, and Iran. After Sept. 11, the threat of rogue states morphed into the terrorist threat, along with the conviction that because these states were led by dictators, they would be more susceptible to terrorism and they would eventually have “to be dealt with.” But apt as the characterization of these states might have been, and as troubling as they were to their respective neighbors, the corollary does not follow. It is not the case that democratic states necessarily make good neighbors on account of their form of government alone. Japan is a democracy, but China does not rest easy on that account, even though Japan has no formal military to speak of, and even though pacifism is a part of its constitution. Democracies, even traditional allies, often don't see eye to eye; and historically they are as likely to start wars as dictatorships. Second, most Americans buy into the romantic notion that “there are no bad people, only bad leaders.” By extension, giving power to the people must result in “good” policy. The trouble is, what is “good” depends on where you sit. If you live among the minority of states that are rich and getting richer, then war and violence are a bad idea: There is little to gain and everything to lose. If, however, you live among the majority of states that are poor and getting poorer, then war and violence seem a good idea: There is everything to gain and nothing to lose. Thus, as in Woodrow Wilson's day, exporting democracy is as useful for gaining domestic political support as it is destructive as foreign policy. Logic notwithstanding, we have a real-world example of what happens when the people of a poor Islamic state are offered democracy. In the early 1990s, Algeria's government held democratic elections to head off widespread dissent and riots. The Islamic Salvation Front—the first legal Islamic political party in North Africa—worked hard to win. When the Algerian people were given a choice (twice), they chose the theocracy (twice), and the government of Algeria was toppled by a military coup that repudiated the election results and imposed martial law. What can we learn from this? First, the United States and its allies have the power to bring their own foreign policies in line with their professed democratic values. It may be difficult, but the United States must stop supporting military dictatorships simply because they are “allies in the war against terror.” The United States must also support Israel by pressuring it to concede to a genuine Palestinian state, while at the same time guaranteeing Israel's security. Second, the more democratic Palestinians and Iraqis become, the less likely they are to support US strategic and economic interests. Israel is a strategic interest for the United States; but it is unlikely that given a choice, most people in the Middle East would accept Israel's right to exist. In other words, ideal election outcomes may not result in ideal foreign policy outcomes, from a US perspective. Countering the popular appeal of groups such as Hamas requires controlling habitat, not population. Killing terrorists can't stop the violence until and unless you destroy the habitat that produces them. That in turn demands serious effort at providing basic needs, such as food, shelter, clean water, education, and healthcare. Hamas has historically done much better at providing for the basic needs of Palestinian Arabs than the Palestinian Authority (Fatah). That's why Hamas won, and that's why, when seeking to export democracy, the United States and its allies must remain careful of what they wish for. Monica Duffy Toft is an associate professor at the Kennedy School of Government and assistant director of the John M. Olin Institute of Strategic Studies at Harvard University.

Le mal américain - Lamont, Michèle; Laurent, Éloi (La libération, 2006)
La presse américaine la plus féroce a chroniqué avec consternation et délice l'annus horribilis de la France, et c'est peu dire, que les réactions à l'épisode funeste du <acronym title="Contrat Première Embauche" lang="fr">CPE</acronym> ne furent pas tendres. Mais, dans le concert harmonieux des moqueries faciles, des critiques narquoises et des attaques virulentes (pas toutes injustifiées), une note dissonante s'est fait entendre. Alors que le New York Times avait fait paraître quelques jours plus tôt un article particulièrement fielleux à l'endroit du «modèle» français, certains de ses lecteurs, dont les opinions furent reproduites plus tard, ont réagit vigoureusement—en sens inverse. L'un des réfractaires, s'étonnant que les Américains eux-mêmes ne défilent pas dans les rues, s'indignait du fait que ses concitoyens aient accepté «sans broncher» au cours des années récentes «la disparition de la sécurité des emplois, la destruction du système des retraites et l'érosion des revenus au profit du 1% d'Américains les plus riches». Il accuse ces derniers d'avoir confisqué les fruits de la croissance économique. Aussi sommaire que puisse paraître ce constat, il n'est pas très éloigné de la réalité qu'économistes et sociologues dévoilent, étude après étude, depuis dix ans. C'est l'économiste Edward Wolff qui, parmi les premiers, dans un ouvrage de 1995, attira l'attention de l'opinion américaine sur le creusement vertigineux des inégalités de revenu et de richesse depuis le milieu des années 80. Dans un article d'octobre 2002, s'appuyant en partie sur les travaux de Thomas Piketty et d'Emmanuel Saez, Paul Krugman exprimait même la crainte d'une régression collective vers les niveaux d'inégalité victoriens du «Gilded Age» («l'âge doré», et non «l'âge d'or», du début du XXe siècle). Il y a quelques mois, les recherches de Robert Gordon ont confirmé que cette tendance s'était encore accélérée dans la période la plus contemporaine, alors même que la productivité de l'économie américaine atteint des sommets. Au total, selon l'économiste de Northwestern, la croissance annuelle des revenus de 90% des Américains n'a été que de 0,3% depuis 1973, contre 3,4% pour les 1% les plus riches et 5,6% pour les 0,1% encore plus riches. Une des conséquences de ce retournement du progrès social est que les inégalités de revenus entre le <acronym title="président-directeur général" lang="fr">PDG</acronym> et le travailleur américain moyen sont passées d'un facteur 27 en 1973 à un facteur 300 en 2000. Le problème crucial n'est pas seulement que les inégalités de revenu augmentent, c'est que la mobilité sociale qui les rend tolérables décline, comme le montrent plusieurs études, complexes et discutées, dans la période récente. L'accès de plus en plus difficile à une éducation supérieure, qui se privatise à tous les niveaux de sélectivité (droits d'inscription en hausse, financements publics en baisse), est au centre du blocage de l'ascension sociale et du caractère explosif de la dynamique inégalitaire. Parce que l'université fonctionne de moins en moins bien comme machine à redistribuer les cartes sociales, les classes se sédimentent progressivement, et la peur du déclassement, bien analysé par Barbara Ehrenreich, grandit. Pour spectaculaires qu'ils soient, les écarts de revenu et d'éducation ne sont qu'une partie de l'iceberg d'inégalités que l'Amérique est en train de découvrir. Sous la plume de deux journalistes du New York Times, une série d'articles a montré l'année dernière comment les inégalités sociales conduisaient à des inégalités de santé et finalement de qualité de vie, la possibilité de pouvoir se faire soigner correctement et à temps impliquant des conséquences souvent irréversibles dans un pays où l'espérance de vie est effroyablement faible compte tenu du poids des dépenses de santé (parmi les plus élevées du monde). L'inefficacité du système n'explique pourtant pas tout de l'exclusion sociale. Les inégalités de santé sont encore aggravées par les codes et les structures culturels, qui laissent peu de place symbolique aux perdants sociaux. Et pourtant, dans le cadre d'un programme d'étude de la Russell Sage Foundation, la sociologue Leslie McCall a montré que les Américains sont non seulement en majorité défavorables aux inégalités sociales, mais qu'ils y sont de plus en plus sensibles. Sans faire de psychologie collective hasardeuse, il n'est donc pas impossible que la volée de bois vert administrée à une France jugée «malade», «archaïque» et «dépassée» soit au moins en partie le symptôme des doutes et des frustrations des Américains au sujet de leur propre adaptation à un nouvel ordre économique dans lequel les insécurités individuelles augmentent et les protections collectives s'affaiblissent. Cette charge peut se lire comme la revanche de l'Amérique sur un système culturel en quête de refondation. Mais qu'importe la rhétorique: le (la) prochain(e) président(e) devra impérieusement répondre à la montée de l'angoisse sociale et au dénouement du lien civique d'un côté comme de l'autre de l'Atlantique. Michèle Lamont is professor of sociology and African and African-American Studies at Harvard University. She is also a faculty associate of the Weatherhead Center. Éloi Laurent is an economist at l'Observatoire Français des Conjonctures Economiques in Paris and a visiting scholar at the Center for European Studies at Harvard University.

Misplaced ‘misunderestimation’ - Allison, Graham T., Jr. (Boston Globe, 2006)
President George W. Bush has complained that opponents tend to “misunderestimate” him. Could he be misunderestimating his North Korean opponent, Kim Jong Il? At his recent press conference, President Bush's exchange with CNN White House correspondent Suzanne Malveaux left observers scratching their heads. Malveaux: “Four years ago you labeled North Korea a member of the ‘axis of evil.’ Since then it's increased its nuclear arsenal, it's abandoned six-party talks, and now these missile launches…” Bush: “That's an interesting statement: ‘North Korea has increased its nuclear arsenal.’ Can you verify that?” Malveaux: “Well, intelligence sources say—if you'd like to dispute that, that's fine.” Bush: “No, I'm not going to dispute, I'm just curious.” Malveaux: “It's increased its nuclear capabilities. It's abandoned six-party talks, and it's launched these missiles.” Bush: “Yes.” Malveaux: “Why shouldn't Americans see the US policy regarding North Korea as a failed one?” Unquestionably, Bush is familiar with the basic facts about North Korea's expansion of its arsenal of plutonium during his presidency. However, his response suggests an extreme case of cognitive dissonance. Given his image of Kim Jong Il, the score in the face-off between the leader of the world's most powerful nation and one of the weakest states on the globe does not compute. This discrepancy is enhanced by Bush's personal distaste for North Korea's “Dear Leader,” in Pyongyang-speak. Calling him “a pygmy,” whom he “loathes,” the president views him as “irrational” and “strange.” How then is it possible that in the contest to prevent North Korea's acquisition of nuclear weapons, the score today is Kim Jong Il 8, Bush 0? Unpalatable as they are, the brute facts cannot be denied. When Bush entered office in 2001, North Korea had one to two bombs' worth of plutonium, according to CIA estimates. That material had been diverted from its Yongbyon research reactor during the presidency of George H.W. Bush and reprocessed to extract the plutonium in 1991. Today, according to American intelligence estimates, Kim Jong Il has acquired an additional eight bombs' worth of plutonium and thus has an arsenal of as many as 10 weapons. Furthermore, he has restarted his operational production line, making two additional bombs of plutonium every year. If one widens the lens to the broader US objectives in its policy toward North Korea, the bottom line is even worse. After taking office in 2001, the Bush administration rejected the Clinton approach to North Korea as a “flagrant failure” and trumpeted a new approach. The essence of the Bush administration's North Korean policy was: no North Korean nuclear weapons; no ambiguity about violations of the terms of the 1994 Agreed Framework; no more missile tests; and no rewards to induce better behavior on Pyongyang's part. Before the end of the first year in office, this policy had taken the further step to “regime change.” In contrast, Kim Jong Il's overriding objective has been regime survival, including the survival of the dear leader himself and his family. In addition to sustaining the regime, he wanted money, oil, and food to keep his desperate economy afloat. And the extent that he could get away with it, he wanted to produce additional fissile material for additional nuclear weapons as well. Measured against their respective objectives, which of the parties deserves higher marks? Kim Jong Il often seems crazy, but he may be crazy like a fox. Graham Allison is director of the Belfer Center for Science and International Affairs at Harvard's Kennedy School of Government and a faculty associate of the Weatherhead Center. He is a former assistant secretary of defense and author of Nuclear Terrorism: The Ultimate Preventable Catastrophe.

Researchers Say U.S. Policy Influenced by Israel - Inskeep, Steve; Walt, Stephen M.; Mearsheimer, John (National Public Radio (NPR), 2006)
Aired Monday on Morning Edition, NPR “The Israel Lobby and U.S. Foreign Policy” is a controversial paper written by John Mearsheimer and Stephen Walt, professors at the University of Chicago and Harvard's Kennedy School of Government. They talk to Steve Inskeep about their view of the influence Israel exerts on Washington. It's a view disputed by many. Listen to Morning Edition with Steve Inskeep, John Mearsheimer and Stephen Walt Stephen Walt is a faculty associate of the Weatherhead Center for International Affairs.

Voices of Iranian Reform, Silenced - Christia, Fotini (Washington Post, 2006)
TEHRAN—Today marks the seventh anniversary of the student protests that took post-revolutionary Iran by storm. On July 9, 1999, after the forcible closure of several liberal media outlets and a coordinated attack on a dormitory at the University of Tehran, Iranian students poured into the streets by the thousands, calling for political reform. Just as at Tiananmen Square a decade before, the Iranian students gave the world a glimpse of what might be—only to be quickly silenced by Ayatollah Ali Khamenei's Revolutionary Guard. Naturally, Iran's regime will not celebrate today's anniversary, but neither will Iran's opposition. The Iranian student movement is a shambles—divided, confused and lacking any cause for celebration. In extensive conversations with students and student veterans of the 1999 protests, who asked to remain anonymous because of fears about their safety, I found that one message emerged loud and clear: Iran does not need another revolution, but it is in desperate need of reform. The atmosphere at the University of Tehran is eerily quiet these days. Nothing remains from the 1999 protests, which were in fact the most notable outbreak of unrest since the Islamic Revolution 20 years earlier. The protests were directed at the rule of the ayatollahs, and they revealed the pronounced internal divisions between the reformist president, Mohammed Khatami—then in the middle of his first term—and Iran's supreme leader, Ayatollah Khamenei. Khatami, who was trying to loosen Khamenei's tight control of the judiciary, security services and media, was facing strong resistance from the clerics when the students came to his aid. But unlike the Islamic Revolution, in which the legitimacy of the country's whole system was called into question, the 1999 protests sought reform within the existing regime, and for an Islamic democracy, that would be in accordance with Iran's constitution. That reform didn't happen, and now, under President Mahmoud Ahmadinejad's leadership, the process has been completely sidelined. The Iranian political scene is dominated by the nuclear issue. Confrontation with the West has made the public more tolerant of authoritarian methods, damaging reformers and making concern for individual rights and civil liberties seem utterly irrelevant. The student movement very much wants a reemergence of the reform process, but it has no good ideas on how to make it happen. Indeed, the student movement has found no place in Iran's new political reality, and its stance has moved from the politics of realistic change to the politics of survival through inaction. The old guard—the 1999 student leaders—is either in jail or abroad, and those of its members still in Iran desperately want out. Their successors—the new leaders of the liberal student union Daftare Tahkim Vahdat—have no organized structure and are weak and fragmented. Their manifestos espouse a Marxist ideal—the orthodox left as they call it—and surreal plans for communist change. These are mostly poor students from Iran's provinces who find themselves repelled by the big city's bourgeois way of life. They see the move to the left as an outlet for change, but they have no real ideological base or sense of direction. “The government could crush them any day, but they don't because it is convenient to have some sort of weak opposition,” said a student participant in the 1999 protests and a former member of the group. “It makes the regime look more democratic.” Said another disillusioned veteran of the 1999 student uprising: “Everyone talks about radical change, but nobody wants to do anything about it, and they don't want it to come from America.…We need to bring together the student movement, the women's movement, the workers' movement and the ethnic minority movements and create a united front to face the regime's radical ideas.” When I asked this person about his contribution to the student movement, he told me he is working on a book. “I am using the <acronym title="United States">U.S.</acronym> student protests from the late 1960s to show the students that revolution and radicalism is a bust,” he said, adding that “lessons may come from America after all, but they will be for reform, not revolution.” The writer is a fellow in National Security at the John M. Olin Institute for Strategic Studies of the Weatherhead Center for International Affairs at Harvard. She is currently at the International Center for Persian Studies, University of Tehran.

Assessing our Adversaries - Allison, Graham T., Jr. (Boston Globe, 2006)
As the World Trade Center and Pentagon attacks become a more distant memory, many Americans comfort themselves with the thought that 9/11 was a freak accident or a 100-year flood. Yesterday's arrest of 21 suspected terrorists, who were in the operational stage of preparation to blow up airplanes en route from Britain to the United States, serves as another stark wake-up call to the brute fact that so many find so hard to believe: There are a large number of people in the world who seriously want to kill us. As we applaud the diligence of British security services that unraveled this plot, there are deeper questions Americans should reflect on. Why are so many people prepared to give up their own lives to kill Americans? Why are there so many people in the world who support them? Why do so many people believe that their methods are justifiable? A year into the war in Iraq, Secretary of Defense Donald Rumsfeld posed a similar question to his four closest colleagues in the Pentagon in a memo that was subsequently leaked. About US strategy in the global war on terrorism, he asked: “Are we capturing, killing, or deterring and dissuading more terrorists every day than the madrassas and the radical clerics are recruiting, training, and deploying against us?” Assessing our adversaries' numbers dynamically and seeking to understand their motivation clinically is not to sympathize with them, but to attempt to design better strategies to defeat them. That requires understanding how our actions increase sympathy, support, and incentives for would-be killers. As commanders of US forces in Iraq have observed, if by calling down airstrikes on a house containing one terrorist and 10 innocents we subtract one terrorist but recruit 10 replacements, we move backward in our mission. Nine months after 9/11, Al Qaeda announced its goal to kill four million Americans. As an affiliated website stated: “We have the right to kill four million Americans—two million of them children—and to exile twice as many and wound and cripple hundreds of thousands” to compensate for the Muslims killed by what Osama bin Laden called the “Jewish-Christian crusaders.” One can only imagine how bin Laden's target number is growing as the war in Iraq continues, and now as Israel pursues its campaigns in Gaza and Lebanon. The capture of the would-be plane bombers in London should cause us to reflect on our longer-run strategy for what the president has rightly called the “long war” on terrorism. In that war, there are today more people who see the United States as the major threat to themselves than there were on 9/11. In that war, the war in Iraq has caused more people around the world to support terrorists who want to kill us. Clearly, we must continue efforts at monitoring, disrupting, capturing, incarcerating, or eliminating determined killers. But a strategic reassessment of our longer-term strategy for the war on terrorism would highlight at least three areas that require substantial change on our part. First, we must acknowledge that the surest way to generate terrorists is to occupy their territory. The French learned this in Algeria; the Israelis, in the occupation of Lebanon from 1978 to 2000. To the extent that US troops are seen as occupiers in Iraq or Israeli troops occupiers in Lebanon, history would predict we motivate terrorists. The quiet, unadvertised withdrawal of US forces from bases in Saudi Arabia removed one of bin Laden's raison d'etre: to force American and other “crusaders” to remove their troops from Arab lands. Second, we must recognize that most of the actions required to discover and capture terrorist plotters like the “London 21” will be taken by other governments—or not at all. However great our effort, it cannot approach the extent and effectiveness of the British government in Britain, the Saudi government in Saudi Arabia, the Pakistani government in its country. But gaining their assistance will require greater sensitivity to these governments' and their citizens' concerns on issues at the top of their agendas. To Americans who ask why we care that majorities even in allied countries disapprove of the United States and especially the Bush administration and believe that America is the greatest threat to international security, the answer is that their cooperation in outing a jihadist in their midst may be essential to our security. Finally, we must delegitimize terrorism—making it as internationally unacceptable as slavery or piracy. As President Bush has rightly said, we live in a “dangerous world.” Effectively combating this threat will, however, require more imagination and harder choices in the long run. Graham T. Alliston, Jr. is a Faculty Associate of the watherhead; Douglas Dillon Professor of Government and Director, Belfer Center for Science and International Affairs, John F. Kennedy School of Government, Harvard University

In a Teenage Waistland, Fitting In - N. Warikoo (The Washington Post, 2005)

After Withdrawal, Engagement - Erdmann, Andrew (New York Times, 2005)
Electing a Parliament under the new permanent Constitution was a significant achievement for the Iraqi people, who once again faced down terrorist violence and political intimidation to demonstrate their desire for a democratic future. For better or worse, in the election's aftermath, the United States will almost certainly begin to withdraw its military from Iraq in 2006. But that does not mean that the time has come to disengage. On the contrary, a broader, more diverse engagement with Iraqi society is needed to help Iraqis develop the institutions, practices and values essential to real and enduring democracy. As President Bush emphasized in his second inaugural address, change of this sort—from tyranny to democracy—is a generational challenge. Our strategy in Iraq must be generational as well. We should reorient our efforts and reallocate some of our resources as our military presence scales down. The needs of Iraqi civic institutions, from the news media and universities to professional associations and nongovernmental organizations, are both vast and urgent. While the National Endowment for Democracy, the United States Agency for International Development and others have done important work to bolster such groups, overall, American efforts have so far been inadequate. Higher education is a case in point. In a country whose median age is about 19.5 years, universities play a crucial role in shaping public opinion and producing future leaders. Today's Iraqi political parties, like the Baath party before them, understand this—so much so that Iraq's universities have become battlegrounds, with dozens of students and educators killed. Iraq's elite tends to emerge from the country's most competitive academic programs, including those for medicine, engineering and science. That the first two prime ministers of postwar Iraq, Ayad Allawi and Ibrahim al-Jafaari, were trained as doctors is no accident. But after decades of neglect, brain drain and sanctions, Iraq's universities and colleges are unable to train sufficient numbers of professors or schoolteachers to educate the next generation. Today, Iraq's 20 public universities and more than 40 technical colleges and institutes struggle to educate more than 250,000 students annually. Hundreds of millions of dollars are needed to build the system back up to where it was before Saddam Hussein took power; billions will be needed to meet today's regional standard, set by countries like Qatar. How can we help build a better Iraq unless we focus on its vast population of young people, whose views of their country and its politics have yet to harden into dogma? But despite higher education's strategic importance, American support for it has been paltry. From 2003 to 2005, a United States Agency for International Development program allocated $20 million to building partnerships between American and Iraqi universities. That program ended without a successor; no agency funds are allocated for Iraqi higher education for 2006. The American Embassy in Baghdad backed the founding of an American University in Iraq in Sulaimaniya, but future support is uncertain. The State Department offers Fulbright scholarships to about 30 Iraqis annually to study at universities in the United States. But these concentrate on the humanities and social sciences, rather than the scientific and technical disciplines that attract Iraq's best and brightest. With few exceptions, American educational institutions have not tried to fill this gap. The costs being equal, which is the better investment in Iraq's future: some 250 annual scholarships for future Iraqi leaders to study in the United States, or another fighter jet? We can greatly expand our efforts to reach out to Iraqi elites across the board, from ministry technocrats to journalists to doctors. Conferences and seminars, often in the region, have begun to reconnect Iraqis to the outside world. We can find other ways to bypass the current security situation by dramatically increasing our investment in communications technology like the Internet (including access to seemingly mundane but critical resources, like online journal databases) and video conferencing. We should expand "train and equip" programs for Iraqi editors, journalists, and publishers. We should also increase financing for the National Endowment for Democracy, the United States Institute of Peace and other organizations that are helping Iraqis build and sustain civic institutions. Such investments cannot be postponed and must not be considered merely "supplemental." We need to lock them into our budgets today. But the United States government should not carry the load alone. Americans of all types—including educators, management consultants and municipal officials—can contribute and need to step forward. More organizations should follow the lead of Columbia University's Center for International Conflict Resolution, which works with civic leaders in regions of Iraq that are relatively peaceful. American trade unions, professional associations, educational institutions, journalists, students, human rights activists, scientists and business executives should establish ties with their Iraqi counterparts. So far, many Americans who opposed the war have not extended a helping hand to the Iraqi people in its aftermath. Others sit on the fence. With elections under a new Constitution, the time has come to focus on Iraq's future and put aside the politics of the past. A strategy that emphasizes building Iraqi civil society may clear the way for bipartisan cooperation, as well as for more international participation. To be sure, if the United States does not do the heavy lifting, the lifting will not get done. Many partners have already paid heavily for their engagement in Iraq. The North Atlantic Treaty Organization is virtually tapped out in Afghanistan. Germany, France and others face domestic challenges. Nonetheless, persuading the Germans, for example, to train 100 Iraqis as vocational educators would be infinitely easier than trying to convince them to put one military trainer on the ground. To many ears, it sounds unrealistic, even idealistic, to say that we should begin concentrating our efforts on improving Iraq's civic life at its grassroots. But such a strategy is a realistic response to the challenges we and our Iraqi allies face, as well as a hedge against possible reversals. Those in office under the new Constitution will almost certainly seek to advance their own interests—personal, party, sectarian, ethnic, tribal—just as their predecessors in the transitional government did. Some tactics will be savage. Powerful militias will continue to stoke fear. Islamists will try to silence secular voices. Sunni extremists will mount attacks, and the attacks will provoke retaliation. Having seen the evidence of death squads and new torture chambers, we should be under no illusions about the dark possibilities of the coming era. Some leaders will try to make their power permanent. Should we expect otherwise, where the political stakes are still often life and death? While we work with the party leaders of today, a new generation will determine what kind of country Iraq becomes. The forces we hope prevail should be the Shakespeare scholar turned newspaper editor, the architect leading an organization devoted to spreading Internet connections among students, and the independent candidate for Parliament advised by the National Democratic Institute. Promoting their success is not an "extra," but is essential to long-term strategic success. We must not underestimate the tenacity of the Iraqi people or lose sight of the lessons of history. Photocopiers, after all, became samizdat weapons against Soviet tyranny. American unions assisted their brethren behind the Iron Curtain in becoming independent forces for change. A once jailed playwright eventually led the Czech Republic. Serbian youth groups galvanized the peaceful uprising that toppled Slobodan Milosevic. Videos of that success inspired activists in Ukraine and elsewhere. And leaders of Georgia's Rose Revolution were once Muskie fellows in the United States. Secretary of State Condoleezza Rice has correctly emphasized that the political transition process in Iraq will not be a "straight line." It will be long, difficult, and bloody. It will be uncertain. There will be more setbacks, even if the insurgency is checked. But our current predicament in Iraq centers on the question not of when to withdraw, but of how to broaden and deepen our engagement.

Asia is in Danger of Repeating Europe's Mistakes - Kaiser, Karl (Financial Times, 2005)
Just like Europe in the late 19th century, east Asia is experiencing a period of extraordinary industrialisation, economic growth and arms build-up. Warships have been deployed to mark positions on territorial disputes, chauvinism and national stereotyping abound and crucial countries fail to deal adequately with—or learn from—the past. In Europe such developments ended in disaster. Is Asia repeating Europe's mistakes? Europe overcame its war-prone past through the process of community building and today has established internal peace by working in unison towards two goals. The first was economic integration, an approach that Asia has emulated with extraordinary success, resulting in unprecedented intra-regional trade, transnational investment and networks of multinational production. But this economic interdependence is no guarantee against disastrous escalation of conflicts. Given the region's present economic interdependence, war in Asia would be even more disruptive and costly than it was in 20th century Europe. Will that prevent governments from unleashing a military conflict? Remember that the first world war broke out amid Europe's most advanced international trade integration and that, as Europeans know all too well, chauvinism is capable of drowning all rationality. Europeans put their relations on a radically different footing by basing their policies on three premises: first, every nation must honestly and credibly face its wrongdoings and failures of the past; second, a clear distinction must be made between the actual guilty parties and the nations they came from; and, third, between the guilt of the perpetrators, now mostly dead, and the surviving generation who are responsible for preventing a repetition. It is perhaps understandable that facing historical facts is painful for some, but it is hard to understand why the honour and memory of people long dead is more important than the future of the living and their chance to live in peace and prosperity The reconciliation between France and Germany and later between Germany and Poland paved the way for others to follow. Much was done jointly, for example by establishing common commissions to review schoolbooks, organising youth exchanges, or promoting city partnerships. Demonstrative gestures and credible acts of asking for forgiveness were crucial. In this respect China, Japan and Korea should play a role similar to that of France, Germany and Poland What mattered particularly in Europe and what is missing in Asia now is a transnational consensus among governments and societal elites to combat nationalism as it existed in Europe. On the contrary, nationalist tendencies are being fostered by governments. In a mistaken belief in the short-term gains in such policy, they neglect the long-term cost of conflict they are likely to induce. Europeans owe their success partly to governments choosing to ignore extremist voices in partner countries as expressions of minorities that should not derail co-operation and reconciliation. Moreover, as Europe has shown, the process of reconciliation and political co-operation is not a one-way street. Positive gestures should be acknowledged and rewarded by the other side. On the 60th anniversary of the end of the second world war, Prime Minister Junichiro Koizumi of Japan did not visit Yasukuni Shrine, which commemorates Japan's war-dead. Instead, by attending a secular ceremony with Emperor Akihito while apologising to Japan's wartime victims, he did exactly what many Asians had hoped and asked for. But this gesture will only work if the outstretched hand is seized and neighbours such as China and South Korea react positively. Using the leeway gained from his recent poll victory, Mr Koizumi could now make a courageous step in this direction. Though his visit to Yasukuni Shrine this week took place in a semi-official manner, it has regrettably pointed in the opposite direction and unleashed the predictable cycle of accusations and resentment. Asia's achievements towards economic integration and interdependence are now threatened by rising political tensions and nationalism in the region. Acts of reconciliation and co-operation by governments and elites are therefore urgently necessary to strengthen community building. As Asia becomes increasingly important to global peace and the international economy, the world can only hope for such a development.

Beyond the Gaza Disengagement - Kelman, Herbert C. (Boston Globe, 2005)
Israeli Prime Minister Ariel Sharon's plan to disengage from the Gaza Strip by evacuating Israeli settlements there and withdrawing troops is scheduled to begin today. Advocates of a negotiated Israeli-Palestinian peace agreement, based on a genuine two-state solution, have understandable misgivings about Sharon's ultimate intentions. Nevertheless, they have fully supported the Gaza initiative, and, indeed, they must do everything in their power to ensure its success. Disengagement from Gaza would set an important precedent for evacuating settlements in the West Bank—an essential condition for establishing a viable, contiguous Palestinian state. It is particularly important that this precedent is set by Sharon, a key architect of the settlement project (even though, from Sharon's point of view, a major purpose of disengaging from Gaza is to make it possible to hold on to most of the West Bank and the settlements there). Failure of the Gaza disengagement would set the opposite precedent by demonstrating that the settler movement and its supporters—a distinct minority in Israeli society—can exercise a veto over any step toward peace, even a modest step that has the support of a broad consensus in Israeli society. Along with their full support of the Gaza disengagement, advocates of a negotiated peace have rightly stressed the critical importance of carefully planning for the day after. Otherwise, the disengagement could easily become a dangerous trap for proponents of a two-state solution. As a unilateral initiative, it has succeeded in marginalizing negotiations and diverting attention from efforts, such as the Road Map, to move toward establishment of a Palestinian state. It has focused the internal debate in Israel on the pros and cons of disengagement at the expense of addressing final-status issues. It has given Sharon an excuse for putting off negotiations toward ending the occupation of the West Bank and an opportunity, in the meantime, to continue expanding and consolidating West Bank settlements and erecting the separation barrier within the West Bank and the area of East Jerusalem. It has fostered within the Israeli public (despite its majority support for a negotiated two-state solution) a sense of pessimism about further progress and an inclination to put final-status negotiations on hold, while waiting to see what happens in Gaza in the aftermath of the disengagement. This attitude, which plays right into Sharon's hands, probably reflects fatigue arising from the internal Israeli conflict over the evacuation of the Gaza settlements and reluctance to take further risks without assurance of Palestinian reciprocation, which, of course, cannot be offered in the absence of a bilateral process. Perhaps the greatest threat to the peace process posed by the Gaza disengagement would be linking the resumption of negotiations to what happens in Gaza in the wake of the Israeli withdrawal. According to this view, further steps in the peace process would depend on evidence that Palestinian President Mahmoud Abbas can establish an effective government in Gaza and prevent anti-Israeli violence. But the unilateral character of the Israeli withdrawal severely undermines the prospects for a post-disengagement Gaza that is governable, economically viable, and peaceful. Unless there is detailed planning, in close coordination and cooperation between Israel and the Palestinian Authority, and with the active support of the international community, Gaza may end up being cut off from the outside world, restricted in the ability to move people and goods across its borders, lacking in opportunities for economic activity and development, plagued by internal violence and lawlessness, and possibly devastated (if there is anti-Israeli violence during the disengagement, which is likely to draw a massive response). If Gaza is left in disarray, Abbas will not be able to govern effectively or prevent terrorist actions, and he might even lose power. More generally, in order to maintain public support and control violence in the West Bank, as well as in Gaza, Abbas needs to achieve concrete benefits in the daily lives of the population and show progress in negotiations toward an end of the occupation and the establishment of a Palestinian state. Thus, to condition negotiations on Abbas's effectiveness in governing Gaza and controlling violence creates a vicious circle. Only coordination before the Gaza disengagement and the resumption of negotiations immediately after the disengagement will enable Abbas to govern effectively and control violence. Under the circumstances, there are two clear priorities at this time for the proponents of a negotiated two-state solution. First, in the preparation, execution, and follow-up of the Gaza disengagement, it is essential to assure in every way possible that Gaza emerges from the process as a secure, economically viable, and governable area, and to strengthen the hands of Abbas and his administration by enabling them to present concrete achievements on the ground and in the peace process to the Palestinian population. The United States and its partners that drew up the Road Map must encourage Israeli and Palestinian coordination and cooperation for a secure withdrawal and disposition of the properties left behind in the settlements; by helping to plan and coordinate arrangements for mutual security and movement across Gaza's borders; by providing financial and technical assistance for economic development, for reopening the airport, and for building a seaport in Gaza; and by providing international observation and peacekeeping teams. The United States could make a significant contribution by appointing a high-level envoy and a team of monitors to help coordinate and implement agreements, as urged by Brit Tzedek v'Shalom, the US-based Jewish Alliance for Justice and Peace. Second, it is essential to put the resumption of negotiations over the final terms of the two-state solution on top of the agenda for the coming fall. The United States and the international community can make important contributions by encouraging an immediate return to the negotiating table, reminding the parties of their obligations under the Road Map, and offering ideas for the outlines of a final agreement. The most important work, however, needs to be done within and between the two societies, with an emphasis on countering the pervasive mood of pessimism and mutual distrust, reviving the lost sense of possibility, and creating a vision of a positive common future. Joint, non-official Israeli-Palestinian efforts to formulate the terms of a final agreement, such as the Geneva initiative, have made extremely valuable contributions by demonstrating that a pragmatic solution to the conflict that addresses the vital concerns of both parties is possible. But, even though majorities on both sides have consistently supported a negotiated two-state solution, the two publics have not fully embraced these initiatives because of their profound mutual distrust. The initiatives ask the public to make major concessions, on deeply emotional and existential issues, at a time when they have no confidence that the other side will reciprocate and follow through on its commitments. The Gaza disengagement has, if anything, increased the level of mutual distrust and the reluctance to make risky concessions. There is a need, therefore, to go beyond pragmatic formulations, essential though they be, in order to overcome the profound mutual distrust and assure the public that it is possible to negotiate a solution that is fair, safe, and conducive to a better future for both peoples. Calls for renewed negotiations and proposals for a final agreement, like the Geneva initiative, must now be complemented and framed by a joint vision of a principled peace, based on a historic compromise that meets the fundamental needs of both peoples, validates the national identity of both sides, and allows them to declare an end to the conflict consistent with the requirements of attainable justice. A jointly constructed framework for a principled peace might include the following components: Acknowledgment of both peoples' historic roots in the land and authentic links to it. Expression of regret for the suffering that the two peoples have caused each other in the pursuit of their national aspirations. Recognition that this destructive conflict cannot be solved by military means and commitment to ending it with a historic compromise, whereby the two peoples agree to share the land to which both are so deeply attached in a way that allows each to fulfill its national aspirations in a state of its own, in peaceful coexistence with its neighboring state. Affirmation that the logic of the historic compromise requires each people to make adjustments in its national narrative—in particular, for Palestinians to accept limitations on the return of refugees to the state of Israel, for Israelis to remove settlements with extraterritorial rights from the Palestinian state, and for both to give up the claim to exclusive sovereignty over Jerusalem or its holy places—in order to enable the other to maintain its national existence and express its national identity in its own state. Development of a positive vision of a common future for the two peoples in the land to which both are attached and which they have agreed to share a vision that contemplates a secure and prosperous existence for each society, mutually beneficial cooperation in various spheres between the societies, regional development, and stable peace and ultimate reconciliation.

Fruit that Falls Far from the Tree - Kapur, Devesh (Economist, 2005)
Might poor countries gain when their best and brightest leave? In the 2002 football World Cup, France, the reigning world champions, suffered a humiliating defeat to unfancied Senegal. All 11 members of the victorious Senegalese team had played for European clubs. They were not alone. By 2000, the first and second divisions of Europe's leagues had poached enough African players to field 70 teams. So, have greedy European clubs deprived Senegal of its best footballers, or has the prospect of a lucrative career in Europe encouraged more Senegalese to take up the beautiful game? This question is posed by a new book, Give Us Your Best and Brightest, by Devesh Kapur and John McHale. The authors are development economists first, football fans second (if at all). But they see the emigration of African players as a highly visible example of the “brain drain”. Less visible, but more worrying, is the departure of the poor world's doctors, nurses and teachers to more lucrative job markets in the rich world. Ghana, for example, has only 6.2 doctors per 100,000 people. Perhaps three-quarters of its doctors leave within ten years of qualifying. The answer to the Senegal conundrum is of course "both": the best players leave, and the dream of emulating them motivates many others to take their place. The real question is whether the second effect outweighs the first, leaving the game in Senegal stronger or weaker than it otherwise would be. A few economists, including Andrew Mountford, of Royal Holloway (part of the University of London), and Oded Stark, of the University of Bonn, think the net effect of the brain drain is similarly ambiguous. The prospect of securing a visa to America or Australia should tempt more people in poor countries to invest in education. Mr Stark calls this a "brain gain". If the temptation is strong enough, and the chances of landing a visa low enough, the poor country could even come out ahead: it might gain more qualified (if disappointed) doctors and engineers than it loses. As with all debates about the brain drain, theory has run ahead of evidence. The numbers on international flows of people are much patchier than those on cross-border flows of goods or capital. In a recent paper, Mr Stark and his co-authors investigate internal migration instead. The rural villages of Mexico lose many of their brightest sons and daughters to jobs in cities or border towns. Those Mexicans who leave their home villages tend to be better educated than those who stay. But despite this, the example the leavers set (and the job leads they provide) raises the average level of schooling of those left behind. Because they can aspire to a world beyond the village, even if they never reach it, young Mexicans have an added reason to stay in school beyond a ninth year, the authors show. Branches picked bare Even if the brain drain does leave a country with a better-educated populace, is this necessarily a good thing? Education is not free, and some of those who gambled on a diploma as a ticket overseas will regret their decision. But Mr Stark assumes that people in poor countries tend to demand too little education. A person's productivity depends on the skills of those around him, as well as his own. Because of these spillovers, an individual's education is worth more to the economy as a whole than it is to himself, and he will underinvest in it as a result. Mr Stark sees limited emigration as one way to fix this market failure. India's software engineers are perhaps an example of this principle at work. Indian students had little reason to learn computer coding before there was a software industry to employ them. But such an industry could not take root without computer engineers to man it. The dream of a job in Silicon Valley, however, was enough to lure many of India's bright young things into coding, and that was enough to hatch an indigenous software industry where none existed before. India's valley-dwellers represent just one contingent in a much larger diaspora. According to the most exhaustive study of the brain drain, released last month by the World Bank, there were 1.04m Indian-born people, educated past secondary school, living in the 30 relatively rich countries of the OECD in 2000. (An unknown number of them acquired their education outside their country of birth, the report notes.) This largely successful diaspora is more than just something to envy and emulate. Its members can be a source of know-how and money, and provide valuable entrées into foreign markets and supply chains. But Messrs Kapur and McHale think India's relatively happy experience with its educated emigrés is more likely to be the exception than the rule. Its million-strong brain drain represents just 4.3% of its vast graduate population, according to the Bank. By contrast, almost 47% of Ghana's highly educated native sons live in the OECD; for Guyana, the figure is 89%. This is not a stimulative leeching of talent; it is a hemorrhage. Emigration, as Mr Stark suggests, might be a spur to greater accomplishment, and the poor world's talent, like Senegal's footballers, deserves a chance to compete on a global stage. But it is not easy to run a managed "emigration" policy. The drain of educated minds from poor countries is mostly determined by host countries' rules, not home countries' interests. There will be tremendous pressure to loosen those rules in the future, not least because, as the baby-boom generation retires, it will seek to "backfill the taxpaying workforce behind it," as Messrs Kapur and McHale put it. The rich world no longer welcomes the tired and the huddled; it looks set to compete ever more fiercely for the bright and the qualified.

Koizumi's new party - Estévez-Abe, Margarita (International Herald Tribune, 2005)
Another victory for Japan's governing Liberal Democratic Party. What's new? This time a lot. Japanese politics has changed forever. This month's election was not just another victory for the LDP over the Democratic Party, its major contender. More important, it was also a victory for incumbent Prime Minister Junichiro Koizumi in his attempt to centralize power within his own party and unite the forces in favor of change. Call it the UK-ization of Japan. Whether voters intended it or not, Koizumi's landslide victory means that the dice have been cast in favor of a British-style parliamentary system that centralizes power in the hands of the prime minister. The election results promise to transform Japan and its relations with the rest of the world. Four years ago, Koizumi bid for the presidency of the governing Liberal Democrats by vowing to "destroy the LDP." In his post-election interview, Koizumi boasted that "the old LDP was destroyed and a new party emerged." He is right. He effectively rendered the old protectionist wing of the LDP powerless, by simply refusing to let it to run for office under the LDP banner. Instead, he nominated a whole crop of first-time candidates to run. More than a quarter of the LDP candidates elected this month are new faces. Nothing like this has ever happened before. In the past, LDP prime ministers never controlled the party nomination. From now on, the LDP will be more like the British political parties. The Democratic Party will have to follow the suit. The days of weak leaders are over in Japan. With or without Koizumi, the change in leadership style is here to stay. Japan introduced a number of important institutional reforms in the 1990s, including a change in the electoral rules in 1994, and the strengthening of the cabinet and the prime ministerial office in the late 1990s. All these changes were designed to turn Japan in-to a British-style parliamentary democracy. Koizumi is a product of this new political structure. He was the first to understand how the new political rules of the game worked. Under them, individual politicians cannot survive by bucking party leaders. Koizumi's victory has taught ambitious politicians the need to rally behind a strong leader. There is no going back. What will happen now? In the short run, there will be bolder policy shifts. Postal privatization is just the first step. We can expect Japan to address its multiple challenges. Japan is experiencing an unprecedented degree of demographic aging. By 2025, nearly a third of the population will be above 65. In the United States, in contrast, less than one-fifth of the population will be older than 65. Japan also has one of the worst fiscal deficits among the industrialized countries. Major reforms to address these issues are finally on the agenda. The most likely scenario is a reduction in benefits for the elderly as resources shift toward the active working population. Tax increases will most likely take two forms. One is a moderate hike in the consumption tax rate coupled with a social security reform that increases the government's commitment to a basic social minimum. The other is elimination of existing tax loopholes. Internationally, Japan has to redefine its role in the world. Japan's so-called Peace Constitution has prevented the country from deploying its troops abroad for military purposes. Koizumi wants to change Article 9 of the Constitution in order to legitimate the Self Defense Forces as a "military" and to facilitate future deployments outside Japanese territories. With only one year of his term remaining, Koizumi may not deliver all these reforms himself. But the "new party" that he brought to power is likely to carry forward this agenda. The end result is likely to be a Japan that looks very much like Britain both domestically and internationally. Japan will develop a more pro-market face and be ready to take on a more active role in the U.S. global security strategy. American business and policy makers will certainly find the new Japan easier to understand and to deal with. Whether a country like China will welcome the change is another issue.

Strange bedfellows in Afghanistan - Christia, Fotini (Boston Globe, 2005)
Before its rise to fame as a battleground in the war on terror, Afghanistan was known as a bubbling geyser of the Cold War. During the 1980s Afghan communists, installed and backed by the Soviet Army, struggled for years to overcome resistance from US-backed mujahideen. Now—over a decade after the Soviet withdrawal and bloody ethnic strife that followed—the communists are making a comeback. Running for office in today's Afghan parliamentary elections, they have assumed the mantle of modernism against fundamentalism. And in the highly unstable and ethnically fragmented political landscape, the United States seems to have found a friend in their former foe. Arguably, there is some logic to this apparent madness; but our new-found love for the communists could prove perilous unless handled with care. Indeed, the former communists—along with some newly returned Afghan diaspora—are the only locals with experience in running a country: They are the only literate bureaucrats around. And in a country plagued by illiteracy and ravished by decades of civil war, the scarcity of trained local officials has made them a desirable commodity. Similarly, former comrades are the only Afghans who are tried and tested in party organization. The Afghan communist party, regardless of its factionalism and shortcomings, was a true party of sorts: It had cadres, a semi-formalized membership structure, as well as women's wings and youth organizations. Peter Dimitroff, the country director of the National Democratic Institute, a leading, mostly US-funded NGO, appreciates the irony in his organization's support for former communist groups. "We support all registered parties, but we support some in a deeper fashion. We like groups that get together on the basis of ideas not ethnicity or geographical background. That is why we are supporting groups like the communists with US money, which is kind of funny... They are good guys and well organized. They are the closest to a professional political party you can get." In the traditionalist and highly conservative Afghan political context, the former communists are openly "women-friendly," fielding a sizeable number of female candidates. Given the party's gender equity policy, it is hardly surprising that some of the leading women on the political scene have a communist affiliation. And the female quota—which stipulates that 25 percent of the parliamentary seats will have to be filled by women even though they make up only 10 percent of the candidates' pool—will undoubtedly boost not only female but also communist representation in parliament. Laudable though the former communists' agenda may be, the risks associated with backing a former foe—particularly one with such a negative precedent in Afghanistan—can easily outweigh the benefits. First, our support for the former communists risks alienating the local population. UN Political Affairs Officer Eckhart Schiewe says that US rhetoric on the war on terror closely echoes Soviet justifications for the invasion of Afghanistan. "Once again a major world power has chosen to depict the conflict in Afghanistan as the forces of good against the forces of evil, much like the Soviet Union did," according to Schiewe. "The communists are back in business." Afghans appear highly apprehensive, if not outright negative, about a potential communist return. According to former Afghan president Burhanuddin Rabbani, "some Western governments working in our country have given place to those who entered on the tanks of the [Soviet] invaders of our country... indirectly telling us that it was bad to stand against the Soviets, the Taliban, and terrorism." Rather than using remnants of an "evil" empire (the former communists) to take down the new evil-doers (the fundamentalists), and risk alienating the local population, the United States should concentrate on good practices. A young Afghan, who blamed Russia "for everything that has gone wrong in Afghanistan in the last 30 years," attributed the resilience of the Afghan communists to the Soviets' human capital strategy. "The Soviets offered a significant number of scholarships to Afghans and trained scores of people in the Soviet Union. These people then came back to Afghanistan as the staunchest supporters of Soviet ideology," he said. "The Americans, if they want to succeed in winning the hearts and minds of Afghans, need to establish educational exchange programs. They should stop worrying about weapons of mass destruction and instead concentrate on building human capital. Trained people make the best ideological weapons. And this is what Americans need: ideological weapons of mass construction." Judging by the Afghan communists' return and resilience, the United States can possibly outsmart its current enemy by learning from its former one. But to do it right, it would have to train its own people rather than rely on what the Soviets left behind.

The World Watches as America Attempts its Restoration - Walt, Stephen M. (Financial Times, 2005)
Americans normally shrug off newspaper headlines overseas, unconcerned by what the rest of the world thinks of us. But the events of recent months have turned a not-so-flattering mirror back upon the US, forcing us to think seriously about what it is the rest of the world is seeing. The hurricanes that struck America's Gulf coast this autumn were just the beginning of a series of storms—both physical and political—that have done significant damage to the already fragile US image overseas. Seen through the eyes of an international audience, the images of destitute African Americans left to fend for themselves in a wasted New Orleans, of Tom DeLay, Speaker of the House, indicted and of a White House struggling to salvage a Supreme Court nominee and belatedly waking up to the dangers of bird flu, combined to create a powerful impression of insensitivity and ineptitude. Coming on the heels of a war that cast grave doubt on US leadership, these storms and our response threaten America's stature in the world. The US's ability to shape world events rests on three pillars. The first is our economic and military power. The second is others' belief that we are using that power properly. And the third is confidence in US competence. When other countries recognise our strength, support our aims and believe that we know what we are doing, they are more likely to follow our lead. If they doubt our power, our wisdom or our ability to act effectively, US global influence shrinks. Even before the storms, the Iraq war was corroding all three elements of US power. Our armed forces have been weakened and our economy burdened by the costs of occupation, and the abuses at Abu Ghraib jail are a stain on the US's reputation. The new Iraqi constitution will not end the insurgency and the bungled occupation has given others ample reason to doubt the US's ability to handle complex political challenges. At home, the aftermath of the storms has made matters worse in every way, as noted by foreign observers. The Russian newspaper Novosti described the US as "a giant on legs of clay, with one foot planted in New Orleans and the other in Baghdad". Germany's Die Zeit asked: "How can America expect to save the world when it cannot even save itself?" Katrina reinforced foreign perceptions of the US as a wealthy but heartless country where racism is endemic and safety nets are lacking. The China Daily said these events revealed "just how fragile much of America's social fabric is" and Japan's Asahi Shimbun declared that "Katrina showed the world the seriousness and the sorrow of the racial disparities facing the US". Finally, the inept US response to sequential natural disasters reinforced foreign doubts about America's competence. As Austria's Salzburger Nachrichten put it: "How is it possible that the country is so ill prepared?" Thus, as Americans turn to the task of reconstruction, we must do so in a way that restores confidence in our values and our abilities. First, to ensure that the US's overall power remains intact, President George W. Bush must ask the American people to accept the full burden of their national ambitions. If we want to repair the damage the storms wrought, prepare for bird flu, maintain a military that is second to none, have world-class schools and exercise energetic global leadership, it is going to cost money—and it is going to require sacrifices from those who have it, rather than those who do not. Anyone who says differently is either lying or deluded. Rebuilding New Orleans is also an opportunity to demonstrate our commitment to provide for all our citizens. If New Orleans is rebuilt with condominiums for the rich, financed by cutting needed social programmes, or if the reconstruction effort is derailed by corporate greed and congressional pork, the rest of the world will have even more reason to question our values and competence. But if reconstruction is swift and New Orleans becomes a showcase of local opportunity and social justice, we will begin to restore the world's faith in US leadership. In the past, the US was respected because its public institutions could set ambitious goals and then achieve them: recall the New Deal, the Manhattan Project, the Marshall Plan and the moon landing. This stormy season produced tragedies for many but we now have the opportunity to show what America can do. The world is watching; we had better not blow it.

China must reduce its excessive savings rate - Hausmann, Ricardo (Financial Times, 2005)
Much of the recent debate on global economic imbalances has centred on Chinese exchange-rate policy. China has a balance of payments surplus. The People's Bank of China has been buying some $20bn a month in its attempt to keep the renminbi's parity with the US dollar stable. American legislators are concerned about the advantage that a weak currency gives Chinese exporters. The US Treasury has given the Chinese six months to act on the currency and has appointed Olin Wethington as a special envoy to carry the message to Beijing. The Chinese authorities fear that a currency appreciation might worsen social and regional imbalances. An appreciation might slow job creation in manufacturing, worsening urban unemployment. It would lower the relative price of agricultural products, thus reducing rural income. Is there an alternative solution? Excessive savings are at the root of the imbalance in China. In spite of China's impressive investment rate, its domestic savings rate is even higher and it attracts massive foreign direct investment. This abundance of savings is what is expressed in the external imbalance. A misallocation of resources occurs. Consumption is foregone, sacrificing the welfare of today's low-income generation not for the benefit of future, wealthier generations but in order to accumulate unneeded low-yielding foreign assets. A reduction in China's savings rate could correct the imbalance. It would lead to faster growth and job creation and improve the welfare of the present generation. It would reduce the balance of payments surplus and stimulate faster global growth through increased exports to China. The increased internal demand would raise the rate of return of investment projects in China that cater to the domestic market. With proper macroeconomic management, even higher rates of investment and growth could be achieved. But can China grow even faster than its current high rate? High growth becomes unsustainable when the economy becomes constrained by an insufficient supply of critical inputs. Usually, investment demand exceeds savings, bringing about a destabilising current account deficit. In other cases, high growth is checked by labour shortages and inadequate infrastructure. These shortages create inflationary pressures associated with currency depreciation, rising labour costs and bottlenecks. In spite of China's rapid growth, these symptoms appear to be absent. The country exhibits an excess of savings over investment. Policymakers are concerned about unemployment rather than labour shortages. Infrastructure is expanding at an impressive pace. Inflation has remained low, with core inflation (excluding energy and food) almost nil. This suggests that the economy's speed limit may well be higher than the current growth rate. An acceleration of growth would create pressures towards real appreciation, because the supply of importable goods is usually more elastic than that of non-tradables. In the context of faster job growth and incipient inflationary pressures, the Chinese authorities would be much more willing to allow an appreciation of the renminbi. The reduction in savings could be engineered through either fiscal or monetary expansion. There are reasons not to choose the latter. First, an eventual credit expansion would be channelled through an already fragile banking system. Credit booms often end in tears. Second, a credit-induced expansion is likely to allocate the additional spending to those who can provide collateral. This would have the wrong distributive consequences both socially and regionally. A fiscal solution has several advantages. First, it can be targeted to favour the regions and the social groups that have fallen behind. Second, it avoids the problem-ridden banking system. Third, it can address other developmental and social goals, such as housing, urban development and infrastructure. Moreover, the country can afford a fiscal expansion. Its debt level is barely 26 per cent of gross domestic product. A fiscal solution is not without dangers. These include corruption, the risk of poorly designed programmes, allocations that are not compatible with sustainable development and the creation of entitlements that may be difficult to reverse. As a response to the 2001 recession, the US Treasury allowed the fiscal deficit to widen by more than 5 percentage points of GDP. Public debt was put on a rising trend. When Mr Wethington meets the Chinese authorities, he might mention the US experience with expansionary fiscal policy. After all, what is good for the goose...

David Brooks, champion of the people? - Skocpol, Theda (Salon.com, 2005)
The right-wing columnist used my work to bash Dean and MoveOn as elitists—conveniently ignoring the big-money interests that pull the GOP's strings. Are MoveOn.org and Howard Dean, who is about to be named chairman of the Democratic National Committee, major threats to democracy in America -- and bastions of elitism within the Democratic Party? That is what David Brooks would have us believe. His Feb. 5 Op-Ed column in the New York Times invoked my 2003 book, "Diminished Democracy: From Membership to Management in American Civic Life," in support of the notion that a secularist, "newly dominant educated class" is using advocacy groups and Internet fundraising to take over the Democratic Party. In Brooks' vision of politics, Republicans have meanwhile morphed into a true party of ordinary people. I was not a "Deaniac" in the 2004 election, but I must protest the way Brooks has used my research to support his claims. Democrats today certainly face challenges in building broad coalitions of educated professionals and populist supporters. But MoveOn and the Dean campaign have gotten more people involved, not fewer, in the party. Republicans, meanwhile, can hardly brag that they represent the values of ordinary Americans. Their effort to destroy the popular and inclusive Social Security program, a plan hatched by ultra-right advocacy groups and think tanks, is a textbook case of manipulative elitism and faux-populist conservatism. Brooks got part of my argument right. For much of U.S. history, large voluntary associations and social movements mobilized millions of Americans from all walks of life to become active in community life and national politics. Reform crusades, fraternal associations, women's federations, veterans associations, farm organizations and trade unions all encouraged members to meet regularly and pool their energies to affect social trends and political decisions at the local, state and national level. Women's groups championed programs for families and children; trade unions and fraternal groups supported Social Security; and the American Legion—a rather conservative veterans association—wrote and lobbied for the G.I. Bill of 1944, one of the most generous social programs in American history. But voluntary associations changed rapidly after the 1960s. Many that linked men or women across class lines went into sharp decline, with aging memberships and faltering local chapters. Battered by opposition from business as well as industrial shifts, blue-collar trade unions also went into a free fall. Meanwhile, professionally run advocacy groups proliferated. Big social and political changes converged to remake the face of American civic democracy after 1960. The civil rights and feminist movements challenged the racism and gender segregation of traditional membership associations. Foundation grants, television and computers made it easy for educated professionals to launch single-issue national associations without regular members or local chapters. In the late 1960s and 1970s, hundreds of freshly fashioned advocacy groups, think tanks and PACs pursued liberal causes such as equal rights for women and environmentalism. By the 1980s, conservatives had counterattacked, founding their own professionally run groups, mostly funded by the very wealthy, to advocate for causes such as lower taxes, deregulation of business, "family values" and opposition to abortion. Through the 1990s, conservatives became more adept than liberals at building bridges between professionally run groups and surviving voluntary associations, learning to coordinate with evangelical churches and groups like the National Right to Life Association and the National Rifle Association. The Republican Party mobilized millions and reaped the benefits in the voting booth. By contrast, most of the Democratic Party's advocacy groups lacked local roots or the capacity to mobilize large numbers of citizens into politics. Issues also divided Democrats, as old-style New Deal liberalism was often at odds with "new" liberalism and public interest liberalism. Brooks reports these findings from my research accurately enough, but he presents an oddly one-sided and partisan picture of elitist threats in American politics and civic life today. True, just as educated middle-class people often send checks to public interest advocacy groups, liberals with college degrees may appear in disproportionate numbers on the e-mail lists of MoveOn.org and the Dean campaign. But both of these efforts at mobilization have surely expanded the ranks of people involved in politics, reducing the sway of big donors and "insider" professional consultants in the Democratic Party. The Dean campaign encouraged voters to gather in one another's houses, not just send checks to a central office. And not all "educated class" Americans (Brooks' phrase) live in Berkeley, Calif., or Cambridge, Mass. My sister is a librarian in West Virginia who regularly gives small amounts to support MoveOn's ad campaigns—which, Brooks to the contrary, are mounted on populist issues as well as in opposition to the Iraq war. These days, for example, MoveOn is running a campaign to expose the huge cuts in guaranteed Social Security benefits that privatization would entail. Republicans are suing to stop the campaign—obviously concerned that it might resonate with ordinary voters well beyond Berkeley. Brooks is not entirely wrong about tensions among more and less privileged Democrats. But notice that he never mentions class tensions and advocacy ideologues in the Republican Party. Right after the 2004 election, President Bush and many of his party and elite allies suddenly claimed a mandate to "reform" Social Security, going to great lengths to disguise the fact that the reform they favor would actually unravel Social Security in short order. Conservatives' campaign to sell the privatization of Social Security is a prime example of the manipulative elitism that now dominates so much of the Republican Party's agenda. Republicans may have populist allies when patriotism and certain lifestyle issues appear to be at stake, but when it comes to tax cuts for the rich and social policy cuts for the majority they disguise what they are doing—because on these matters ordinary Americans, even those who vote Republican, do not always share the values and priorities of Republican business supporters and ideological elites. Even conservative Christian associations allied with the Republican Party are wary about trying to persuade their members to buy into Social Security privatization. Crucial for the poor, the disabled, survivors of deceased workers and the elderly, Social Security is a supremely pro-family program. Its decent retirement benefits are guaranteed for life, allowing beneficiaries to live in dignity and freeing working parents to invest in their children's future (rather than devoting most of their time and resources to caring for Grandma and Grandpa). Ideologues who want to shatter Social Security into millions of isolated market accounts know that they can succeed only by bamboozling large numbers of people—labeling modest, long-term problems an immediate "crisis" and failing to own up to the cuts they plan in guaranteed benefits. Although Brooks implies that the Republican Party is the true populist party these days, the party did not adopt the privatization proposal at the urging of voluntary, grass-roots membership associations or a broad-based social movement. Bush got the idea from right-wing think tanks such as the Cato Institute and the Heritage Foundation. What's more, the privatization campaign has been fueled by big-money donors who favor unfettered markets and, in many cases, hope to profit from fees paid by the government to Wall Street for managing the new private accounts. Democrats should no doubt be touched that Brooks is so worried about the challenges our party faces in building broad coalitions and appealing to vast numbers of ordinary citizens—in both red and blue states. But since 2000, when the need to hang together became starkly clear, Democrats, organized in all kinds of associations, have been trying hard to bridge the concerns of different social constituencies. Still, Democrats do need to take care lest single-issue causes appealing to the privileged take our focus away from broad appeals to average citizens, many of whom have not been to college. But Brooks should worry more about the elitist ideologues and unhinged advocacy groups in his own party and movement. Perhaps he should pursue a sociology of "W. Bushism," examining how the pet causes of right-wing think tanks could undercut the populist appeal of Republicans. Right-wingers determined to fetter government as a tool for spreading opportunity and ensuring security for most citizens are much more of an elitist threat to American democracy than "Deanism." Before long, millions of voters may come to realize this.

A Skeptic of Human Nature: George F. Kennan was an Early Advocate for the New Europe - Kaiser, Karl (Atlantic Times, 2005)
George F. Kennan, diplomat, historian, writer, died on March 17. Excerpts from Karl Kaiser’s eulogy. I am one of the millions of Europeans who benefited from George Kennan’s contribution, for I speak to you as a citizen of the peacefully united Germany, a democracy again, and the new Europe which is no longer divided into two hostile camps of communism and democracy, where the possibility of war has practically disappeared, and unprecedented unity is being created by the European Union. It is this new Europe, for which George Kennan strove throughout his extraordinary life, as an analyst who frequently exposed its problems with surgical precision, as an advocate who was often ahead of his time, changing views and affecting policies, often misunderstood and criticized, ready to oppose what he considered wrong, always relevant. Europeans remember him for his essential contribution to rebuilding Europe with the Marshall Plan and the Containment Policy as the two complementary centerpieces of U.S. policy. Containment, for which he laid the conceptual foundation, formed the basis of American foreign policy from the Truman Doctrine to the creation of NATO. The freedom of Berlin and of Western Europe is unimaginable without them. It is true that Kennan later complained that containment was misunderstood and that the policy overreacted in military terms to the Soviet threat. But in 1967, NATO did exactly what Kennan had always advocated by adding to its goals a political dimension that sought dialogue and accommodation with the adversary. In the end, it was this combination of the military and political dimension, of deterrence and detente, which led to the demise of communism. Kennan played a vital role in establishing the Marshall Plan, perhaps the most intelligent and forward-looking act of American foreign policy. It helped to rebuild Western Europe’s economy, supported the restoration of democracy and established the foundation for transatlantic economic interdependence. Without the Marshall Plan and America’s continuous support of European integration with Franco-German reconciliation at its heart, we would not have Europe as an essential part of our Western community today, nor could that community continue to play a crucial role in this turbulent century without America actively supporting European unity. Europeans also remember Kennan for his contribution to detente and to overcoming the division of Europe. Of course, that outcome is unthinkable without the contribution of the detente policy of American administrations from John F. Kennedy onward. Nor is it imaginable that Gorbachev would have been able to release East Germany, the most important trophy of the world war unleashed by Germany, without the groundwork laid in the preceding decades by Western detente policy and German "Ostpolitik" which helped to rebuild trust and cooperation between Bonn and Moscow. But Kennan’s views and voice played a crucial role in these processes by proposing alternative ideas for dealing with the East-West conflict and by offering interpretations of the Soviet Union which stressed the evolutionary potential of the country. Throughout his life, he preached patience when it came to fostering democracy in other countries and that statecraft should rely on and encourage the indigenous forces that could create it. As I know from personal experience, Chancellor Willy Brandt revered him. In the early sixties, Kennan once came through Berlin on his way back from Moscow and gave Brandt his assessment of developments in Soviet leadership at the time. He told Brandt not to be afraid in pursuing new policies with the East. "Have courage," he said. His assessment and advice undoubtedly encouraged Brandt to develop a new approach, which later took shape as "Ostpolitik." Brandt met with Kennan repeatedly and always paid attention to his writings. As a skeptic of human nature, Kennan considered nuclear weapons to be too dangerous to be put in human hands. As he put it: "War between great peoples in the modern age—total war—is a madness from which nobody can benefit." The destruction of Hamburg and Berlin, two cities he knew very well, shocked him profoundly. As nuclear weapons became increasingly important in Western security policy, he constantly criticized what he called "grotesque deterrence," supporting and inspiring those critics in the U.S. and Europe who advocated arms control and disarmament in this field—a stance more important today than ever as these awful weapons may fall in the hands of jihad terrorists. When the Berlin Wall fell in 1989, it was not a forgone conclusion that the Cold War would end without a bloodbath. To be sure, the wise and prudent statesmanship of the leaders of that time was decisive, but they acted within an environment of trends and ideas that encouraged them to recognize a historical opportunity they fortunately grasped. Kennan’s contribution was vital in creating that very environment. Today is therefore the moment for Europeans who now live in a free and reunited continent to express thanks to this extraordinary man. We Europeans honor him as an example of the very best in the American diplomatic tradition that proceeds on the basis of careful analysis, that seeks to understand the driving forces of other countries, in particular its adversaries, and that attempts to act as much as possible on the basis of a consensual and multilateral approach which respects international law and involves allies. As Germany’s Federal President Horst Koehler put it in a letter of condolence to Mrs. Kennan: "He remains an example to every young diplomat."

To win the war on terror, you need the carrot - Nye, Joseph S., Jr. (Independent, 2005)
If hard power is characterised by the use of military force to project our will, then the essence of soft power lies in values, in our culture and in the way we handle ourselves internationally. Soft power is about creating a sense of legitimacy for a nation's international aims. To understand what's happening in US foreign policy you have to start with 9/11. Before that date the Bush administration had been running on a fairly traditional realist platform; no more nation-building, and a broadly unilateralist approach to foreign policy. After 9/11 the Bush administration realised this had to change. Credit must be given to the Bush government for the speed in which they realised traditional conceptions of threats to national security had changed. However, what they are still struggling with is how to combat diffuse non-state actors, primarily in the form of al-Qa'ida. Hard power, which is so successful at one level, does play a role in the war on terrorism, but it is not quite the role you first expect. Hard military power did topple the Taliban, something soft-power was in no position to do. However, if you look at the number of Taliban fighters actually killed in Afghanistan, you're looking at maybe no more than a third. In order to win the war on terror therefore, you also need soft power. You need the stick but you also need the carrot. Bombing and land invasions of countries harbouring and fomenting terrorism are important, but we must employ greater public diplomacy in order to attract people away from militant Islam. If the US would divert even 1 per cent of its defence budget to public diplomacy it would signal a quadrupling of the budget currently given to those looking to implement soft power rather than hard. To conclude, what is important is not soft power or hard power alone. It's a combination. Our military power stopped Soviet aggression, but it was our soft power which fostered cultural progression and sympathy to our aims and stopped states from falling into the hands of communism.

Uzbekistan's Tiananmen - Christia, Fotini (Boston Globe, 2005)
THE BLOODY protests in Uzbekistan's Andijan square have exposed the Bush administration's Janus-faced policy on regime change. Recent talk of spreading democracy and bringing freedom to the oppressed sits very uneasily with the ''yes, he is a bastard but he is our bastard" approach, reminiscent of the Cold War, which has guided US relations with Uzbekistan. In this case—unlike Georgia, Ukraine and Kyrgyzstan—America's ally of choice is not a pro-democracy revolutionary but a proven despot, the Uzbek leader Islam Karimov. Plagued with political repression and economic disenfranchisement as well as a rise in Islamism, Uzbekistan is a case in point as to why the United States cannot and should not have it both ways. The most populous republic in Central Asia, Uzbekistan is rich in natural resources and the world's second biggest cotton producer after China. Despite its economic potential, Uzbekistan's growth and living standards are among the lowest in the former Soviet Union. Dominated by Karimov since the republic's independence in 1991, the Uzbek political scene has become increasingly repressive. After strategically aligning himself with the United States in the war against terror and offering an Uzbek military base for US military operations in neighboring Afghanistan, Karimov has used the threat of radical Muslim unrest to justify the persecution and oppression of his political opponents. No opposition parties are recognized and Karimov's regime has decimated Uzbek civil society: there are practically no independent local NGOs and no freedom of expression or association. Independent media operations have been driven underground and foreign correspondents forced to leave the country. Despite a constitutional ban on censorship, local journalists opposing the regime have been blacklisted. With the media neutered, no one really knows how many people have been killed or wounded in the recent protests. Estimates currently range from a few dozen to several hundred and the UN has called for an independent investigation on last week's violence. Karimov's persecution of the secular opposition has increasingly pushed ordinary Uzbeks into the arms of radical Islamist groups. The Islamist group with the broadest appeal is Hizb-ut-Tahrir (the Islamic Party of Liberation), which claims to stand for the peaceful overthrow of the Uzbek government and the creation of a caliphate throughout Central Asia. Karimov has branded Hizb-ut-Tahrir a terrorist organization (though it is not on the US State Department List of Foreign Terrorist Organizations) and blames it for bombings and suicide attacks that took place in Tashkent last spring and summer. The recent protests in Andijan were in opposition to the government's indiscriminate arrests on the grounds of membership to Hizb-ut-Tahrir. Uzbekistan therefore combines political oppression and the rise of Islamism with economic opportunity for rebellion. So far the mix has proved highly volatile. If the United States wants to avoid increased violations of human rights and the possibility of a future Islamist takeover, it must take immediate steps to strengthen civil society in Uzbekistan. Karimov has to be pressured to allow the registration of opposition parties such as ERK (Freedom), BIRLIK (Unity) and OZOD DEHQON (Free Peasants) as well as the registration of truly independent NGOs. The reintroduction of an independent media and guarantees that freedom of conscience, expression and association will be respected are also essential. But for Karimov to commit to change credibly, all reforms have to be tied to monetary incentives. The United States, as well as international financial institutions, should make aid and loans conditional on tangible reform. This pressure would be most effective if it involved coordinated action from the United States and Russia as well as international political and financial organizations. Action has to be immediate to avert further refugee flows to Kyrgyzstan and other neighboring states that could prove highly destabilizing for the broader region. According to one of the leading opposition figures, the Free Peasants Party General Secretary Nigora Khidoyatova, a revolution is on the way in Uzbekistan. ''Our revolution will be green," she said, alluding to her peasants' party color and pointing to an orange poster of Ukraine's Victor Yushchenko hanging on her cabinet. Unless the United States effectively pressures President Karimov to strengthen civil society and its fledgling democratic forces, a revolution will sweep Uzbekistan. And once it erupts it may very well be green: Islamist green.

War by other means - Laura Secor (The Boston Globe, 2005)
Boston's Gene Sharp learned how to turn nonviolence into a weapon - and helped quite literally change the world.

A Bush Plan for the Mideast - Martin, Lenore G. (Boston Globe, 2005)
Condoleezza Rice's first trip to Europe and the Middle East as secretary of state this month creates a perfect opportunity for the Bush administration to accelerate the resolution of the Palestinian-Israeli conflict. The stalled road map for peace envisages a final and comprehensive resolution of the Israeli-Palestinian conflict in 2005. Israeli Prime Minister Ariel Sharon, on the other hand, envisages not a peace treaty but a ''disengagement" of Israeli settlers and soldiers from Gaza by the end of 2005. Disengagement will reduce the tension created by the 21 Israeli settlements and the Israeli military deployed to protect them. But it does not address the need for a final peace agreement and it does nothing to remove the Israeli stranglehold over the Palestinian economy by control over Gaza's borders, port and airport. At a time when Palestinian President Mahmoud Abbas is trying to fulfill the road map's preconditions for negotiating peace and recent polls show a majority of Palestinians and Israelis favor a two-state solution for the conflict, it would be a mistake to allow the unilateral disengagement to frustrate negotiated peace efforts. Why accelerate the peace process? The United States and its European allies are locked in a global struggle against jihadi Islamic-inspired terrorism that feeds off Muslim frustration, one source of which is perceived support for the Israeli occupation of Gaza and the West Bank. Ending the occupation through a negotiated peace will help win the war against terror. Cooperating with Europe within NATO to further the peace process will also help the United States heal its rift with Germany and France over Iraq. The United States has expended substantial resources without the aid of most of Europe in trying to defeat terrorism and build democracy in Iraq. It will take far fewer resources with European assistance for the United States to help Abbas control terrorism and build democracy in Palestine. Sharon wants to slow down the peace process. He believes that Israel will achieve more security from unilateral moves such as disengaging from Gaza or building a ''security fence," than from negotiating a peace treaty. This is illusory. Palestinian violence will spiral from increased frustration with economic deprivation and the indignities of personal humiliation from the Israeli occupation with no end in sight. Real security for Israel will be found in real peace. The United States can use the disengagement from Gaza to reduce the prospect of spiraling violence and increase Israel's long-term security with a three-part plan. First, a US-led NATO force can help the Palestinians achieve security within Gaza. With Israeli and Egyptian cooperation, the NATO force can provide security training for the Palestinian Authority and patrol Gaza's borders, port, and airport. Second, the United States, Europe, wealthier Arab states, and other members of the international community can coordinate economic development efforts to improve the daily lives of Palestinians. Third, the United States should propose a comprehensive peace plan and help the Israelis and Palestinians negotiate and implement it in order to resolve the critical issues of Jerusalem, borders, Palestinian refugees, and Israeli settlements. Using NATO to coordinate security in Gaza is not far-fetched. There have already been discussions of Israel upgrading its relationship with NATO and using NATO in Gaza. To overcome Israel's historically based distrust of international peace-keeping forces, the United States should command the NATO force. An immediate benefit of a US-led NATO force in Gaza would be to ease the import and export of Palestinian goods and services. This will enable a donor-dependent Palestine to develop a more self-sustaining economy. However, only by expediting the process of achieving a comprehensive peace agreement will the United States and its allies help to strengthen security and promote economic development in Palestine, important preconditions for a sustained democracy. Abbas needs the strong support of the United States and the international community in order to combat Islamic extremists and violence in Gaza and the West Bank. He will gain the political legitimacy he needs with a fair resolution of the conflict. There is no lack of model agreements that propose such resolution, including the Clinton Plan, the Nusseibeh-Ayalon Plan, and the Geneva Initiative. Let the secretary of state and the administration propose their own Bush Plan and create a lasting legacy for this president by getting the parties to implement it now while the opportunity exists.

Cowboys and Indians - Ferguson, Niall (New York Times, 2005)
"I think that this could still fail." Those words—uttered by a senior American officer in Baghdad last week—probably gave opponents of the war in Iraq, particularly those clamoring for a hasty exit, a bit of a kick. They should be careful what they wish for. For history strongly suggests that a hasty American withdrawal from Iraq would be a disaster. "If we let go of the insurgency," said another of the officers quoted anonymously last week, "then this country could fail and go back into civil war and chaos." As many of the war's opponents seem to have forgotten, civil war and chaos tend to break out when American military interventions have been aborted. Think not only of Vietnam and Cambodia, but also of Lebanon in 1983 and Haiti in 1996. To talk glibly of "finding a way out of Iraq," as if it were just a matter of hailing a cab and heading for the Baghdad airport, is to underestimate the danger of a bloody internecine conflict among Kurds, Sunni Arabs and Shiites. Instead of throwing up our hands in an irresponsible fit of despair, we need to learn not just from past disasters but also from historical victories over insurgencies. Indeed, of all the attempts in the past century by irregular indigenous forces to expel regular foreign forces, around a third have failed. In 1917 British forces invaded Mesopotamia, got to Baghdad, overthrew its Ottoman rulers and sought—in the words of the general who led them, Sir Stanley Maude—to be its people's "liberators." The British presence in Iraq was legitimized by international law (it was designated a League of Nations mandate) and by a modicum of democracy (a referendum was held among local sheiks to confirm the creation of a British-style constitutional monarchy). Despite all this, in 1920 there was a full-scale insurgency against the continuing British military presence. Some may object that warfare today is a very different matter from warfare 85 years ago. Yet the striking thing about the events of 1920 is how very like the events of our own time they were. The reality of what is sometimes called "asymmetric warfare" is how very symmetrical it really is: an insurgency is about leveling the military playing field, and exploiting the advantages of local knowledge to stage hit-and-run attacks against the occupiers, as well as anybody thought to be collaborating with them. Indeed, if there is asymmetry it lies in the advantages enjoyed by the insurgents. The cost of training and equipping an American soldier is high; by contrast, life is tragically cheap among the young men of Baghdad and Falluja. Even if the insurgents lose 10 men for every 1 they kill, they are still winning, not least because the American side takes its losses so much harder. How, then, did the British crush the insurgency of 1920? Three lessons stand out. The first is that, unlike the American enterprise in Iraq today, they had enough men. In 1920, total British forces in Iraq numbered around 120,000, of whom around 34,000 were trained for actual fighting. During the insurgency, a further 15,000 men arrived as reinforcements. Coincidentally, that is very close to the number of American military personnel now in Iraq (around 138,000). The trouble is that the population of Iraq was just over three million in 1920, whereas today it is around 24 million. Thus, back then the ratio of Iraqis to foreign forces was, at most, 23 to 1. Today it is around 174 to 1. To arrive at a ratio of 23 to 1 today, about one million American troops would be needed. The United States also faces two other problems that the United Kingdom did not 85 years ago. The British were able to be ruthless: they used air raids and punitive expeditions to inflict harsh collective punishments on villages that supported the insurgents. The United States has not been above brutal methods on occasion in Iraq, yet humiliation and torture of prisoners have not yielded any significant benefits compared with what it has cost the country's reputation. The Americans' other problem has to do with timing and expectations. Secretary of Defense Donald Rumsfeld has said that American forces should aim to work to a "10-30-30" timetable: 10 days should suffice to topple a rogue regime, 30 days to establish order in its wake, and 30 more days to prepare for the next military undertaking. I am all in favor of a 10-30-30 timetable—provided the measurement is years, not days. For it may well take around 10 years to establish order in Iraq, 30 more to establish the rule of law, and quite possibly another 30 to create a stable democracy. Those American officers who say that it could take years to succeed in Iraq are therefore right. But the Bush administration has just three and a half years left. Is it credible that American troops will still be in Iraq for even another four years after that? The insurgents don't think so. They know that American democracy puts time on their side. Once again, the contrast with the British experience is instructive. Although Iraq was formally granted its independence in 1932, there was still some form of British presence in the country until the late 1950's. So, if we acknowledge that the United States simply does not have the luxury of time that the British enjoyed and cannot be similarly ruthless, can it at least increase the manpower at its disposal in Iraq? The official answer from Washington is that Iraqi security forces will soon be ready to play an effective role in policing. Few who have seen those forces on the ground find this strategy realistic. Some fear that the training that Iraqi soldiers are receiving may prove useful only when they fight one another in an Iraqi civil war. What, then, of America's own resources? Almost no one (least of all the Pentagon) wants to go back to the draft. So could today's all-volunteer force somehow be expanded to double (at least) the troops available? That too seems unlikely. Indeed, the current system is already showing alarming signs of stress and strain as more and more is asked of the "weekend warriors" of the reserves and National Guard, who account for roughly two-fifths of the force in Iraq. In December, the Army National Guard acknowledged that it had fallen 30 percent below its recruiting goals in the preceding two months. Many members of the Individual Ready Reserve have been contesting the Army's right to call them up. How did the British address the manpower problem in 1920? By bringing in soldiers from India who accounted for more than 87 percent of troops in the counter-insurgency campaign. Perhaps, then, the greatest problem faced by the Anglophone empire of our own time is very simple: the United Kingdom had the Indian Army; the United States does not. Indeed, by a rich irony, the only significant auxiliary forces available to the Pentagon today are none other than ... the British Army. But those troops are far too few to be analogous to the Sikhs, Mahrattas and Baluchis who fought so effectively in 1920. No one should wish for an overhasty American withdrawal from Iraq. It would be the prelude to a bloodbath of ethnic cleansing and sectarian violence, with inevitable spillovers into and interventions from neighboring countries. Rather, it is time to acknowledge just how thinly stretched American forces in Iraq are and to address the problem: whether by finding new allies (send Condoleezza Rice to New Delhi?); radically expanding the accelerated citizenship program for immigrants who join the army; or lowering the (historically high) educational requirements demanded by military recruiters. YES, as that anonymous officer said, the Bush administration's policy in Iraq could indeed still fail. But too few American liberals seem to grasp how high the price will be if it does. That is a point, unfortunately, that also eludes most of this country's allies. Does it also elude the secretary of defense? If "10-30-30" are the numbers that concern him, I begin to fear that it does. The numbers that matter right now are 174 to 1. That is not only the ratio of Iraqis to American troops. It is starting to look alarmingly like the odds against American success.

End-of-Life Issues: Terri Schiavo deserved to die with more dignity - Perju, Vlad; Daflon Barrozo, Paulo (San Francisco Chronicle, 2005)
Too busy taking sides in the tragedy that has befallen Terri Schiavo, we have forgotten to question the choices open to us and to her. In fact, this debate is less about dying than about how to die. Schiavo wanted and deserved to die with dignity, yet nothing of what she received came close to a dignified death. Together with food and water, society withheld from her the option of a quiet, peaceful and swift death by active euthanasia. We should think of Schiavo as not just the victim of an accident that occurred 15 years ago, but also of a society that has structured its public conversation about matters of life, death and dignity in ways that fail to do justice to those who need it most. Instead of asking only whether a person would prefer to die should she find herself in a permanent vegetative state, we ought to factor in the ancillary question of what kind of death she would be willing to die. As we know, in Schiavo's case, the withholding of food and water over a period of two weeks triggered chemical imbalances in her organism, and ultimately her death. She died slowly, gradually. Although she apparently did not feel any of this, her family did, and so did we. From close or from afar, the spectacle of a human being fading away had a symbolism to it that is a heavy burden to carry. It is not unreasonable to intimate that forcing her to die this kind of death violates her right to decide how she wanted to be remembered, as U.S. Supreme Court Justice William Brennan argued in his dissent in Cruzan vs. Director in 1990. Schiavo was probably unfamiliar with the distinction between acts and omissions that is still a pillar of her country's legal system. She probably could not have fathomed that in her society it is legal to let someone starve to death, but illegal, unless when motivated by society's will to punish, to inject a lethal substance into that person. We find it more acceptable to see a human being dying away slowly without food and water than to imagine euthanasia. It is hard to grasp why that should be so. The experience of other countries has proved flat wrong the familiar argument that euthanasia can be abused, which is regularly invoked in this context and has figured prominently whenever courts confronted this question. Another possible argument to the effect that actively killing someone would have a negative impact on the image of the medical profession in society wrongly assumes that removing the feeding tube followed by inaction is less damaging to how we look at our medical doctors. We are left with the conclusion that such a framework is steeped in a hypocritical belief that we society, we judges, we doctors, are not the ones ending Schiavo's life. That is a lie, and not a noble one. We all want to die with dignity. We hope to exit this life uncrushed by the fear of our passing and of the unknown that awaits us. Death is as deeply personal as it incomprehensible, and a mature society should aim at respecting the decisions of its members about when and how to die. The laws of Terri Schiavo's country made it impossible for her to die with dignity, as she wanted, and virtually no voice echoed her all-too-human wish. She deserved better.

Iraq: One Nation Under Allah: Why it's unrealistic to expect a separation of mosque and state - Robert J. Barro (Business Week, 2005)
The insurgency in Iraq goes on, but attention has shifted toward the structure of an independent government. One key issue is whether the new regime will have a state religion, as envisioned by the U.S.-imposed transitional administrative law. Research by Rachel M. McCleary and me at Harvard University's Project on Religion, Political Economy & Society suggests that the Iraqi government will have an official religion. Although separation of religion and state has long been a Western ideal, it seems politically unrealistic for Iraq. The consequences of state religion are complicated in practice. We find that the presence of state religion encourages participation in formal religious services (likely because of governmental subsidies to organized religion) and provides a smaller boost to religious beliefs. There is a weak negative impact on economic growth. And although some rich countries such as Britain and most of Scandinavia maintain religious liberties despite having official religions, state religions tend to coincide with curbs on religious freedoms. In our research, we used international data to isolate the demographic, social, and economic factors that lead to the establishment of a state religion. Most important is whether a country has a diversity of religions or is concentrated in a single faith. For example, in 2000, the largest U.S. group was Protestants, with 44%, whereas in Morocco it was Sunni Muslims, with 98%. We estimate that this difference made the probability of a state religion in Morocco (which had one) higher by 69 percentage points than in the U.S. (which did not). LESS CLEAR IS WHETHER the identity of a country's main religion influences the likelihood of state religion. In 2000, among the 40 countries where more than 50% of the people were Muslim, 28 (or 70%) had a state religion. In contrast, among the 91 countries with more than 50% in a single non-Muslim religion, 42 (or only 46%) had a state religion. We found that half of the Muslim/non-Muslim difference arose because the share of population that adhered to the most popular religion was higher in Muslim countries. The rest of the difference involves a greater tendency by government to curb religious freedoms in Muslim countries. Another important factor is that communist countries rarely have a state religion (if communism does not count as a religion). However, this influence lacks staying power: Since 1990, 15 ex-communist countries, including six Muslim ones, set up state religions. The size of a country matters; neither very small nor very large countries tend to have state religions. For small nations, the cost of maintaining an official religious administration is simply too great. For large countries, even a small proportion of the population in minority religions constitutes a large number of people and, therefore, creates resistance to a monopoly religion supported by the government. For Iraq, a big question is whether the stronger force toward state religion is the 96% of the population that is Muslim or the 61% that is Shiite Muslim. We analyzed this issue using estimated breakdowns of Muslim populations into Sunni, Shiite, and other sects. Sunni is by far the largest worldwide, and only Iran is mainly Shiite (86% of the people). Only a few Muslim countries have substantial representation in more than one category: Azerbaijan, Bahrain, Iraq, Kuwait, Oman, and Yemen. Some other Muslim countries -- Afghanistan, Pakistan, Syria, Turkey, and the United Arab Emirates -- are 10% to 20% Shiite. But our results suggest that overall Muslim share, not size of the most popular sect, is what influences the creation of state religion. No model predicts perfectly, but ours gets the right answer more than 80% of the time. Thus, it is instructive that the model's probability for a state religion in Iraq is 96%. True, our method also gives neighboring Turkey an 88% probability for state religion, even though it has been officially secular for decades. One can view this mistaken prediction two ways. One is that, despite forces that favor state religion, Turkey can be a model for Iraq on how to separate church and state. The other is that Turkey's secular status represents hard-to-duplicate political influence by its strong President, Mustafa Kemal Ataturk, in the 1920s and '30s. Conceivably, the factors that favor a state religion will eventually generate an Islamic state in Turkey. That reversal seems more likely than Iraq's becoming a secular state.

Pushing through the ethical thicket - Sandel, Michael (Boston Globe, 2005)
With stem cell legislation pending on Beacon Hill, proponents and opponents have taken to the airwaves, as lawmakers and citizens struggle to think their way through the ethical and scientific thicket. In Massachusetts, the real debate is not about stem cell research as such, but about whether scientists should be allowed to use cloning techniques to create embryos for stem cell research. The bills passed this week by the Legislature would permit stem cell cloning; Governor Mitt Romney would ban it. While much of the discussion has focused on scientific complexities, the debate is at heart about ethics. There are two main objections to cloning embryos for stem cell research—the "right-to-life" objection, and the "brave new world" objection. The right-to-life objection regards the embryo as inviolable, as morally equivalent to a fully developed human being. Since extracting stem cells from the blastocyst (the cluster of cells that comprise the early embryo) destroys it, those who consider the embryo a person regard such research as the taking of a human life. The brave new world objection worries less about the embryo than about where our new scientific powers may take us. It fears that allowing scientists to use cloning techniques for stem cell research will lead us down a slippery slope to dehumanizing practices such as cloning human babies or growing fetuses in the lab for spare parts. How persuasive are these objections? The right-to-life objection raises hard questions about the origins and sanctity of human life. But it is important to notice that the right-to-life question is not really at issue in the debate between Romney and the Legislature. At first glance, Romney's opposition to stem cell cloning seems to be based on the idea that the embryo is inviolable and should never be destroyed for the sake of science. The principle at stake is that "no life should be exploited for the benefit of another," Romney wrote in explaining his opposition to the stem cell bill. "Every human being has inalienable rights, and first among them is life." But this principle is too broad for Romney's position. For if he believes that embryos are human beings with inalienable rights, he should oppose all embryonic stem cell research, not only research on cloned embryos. If extracting stem cells from a blastocyst is morally equivalent to yanking organs from a baby, then it is abhorrent no matter how the embryo came into being. But Romney favors stem cell research on embryos left over from fertility clinics, provided the parents consent. Given the rigors and uncertainties of in-vitro fertilization, most fertility clinics create more fertilized eggs than are ultimately implanted. The "spare" or "surplus" embryos are typically frozen and ultimately discarded. Some argue that, even if embryos are persons with inalienable rights, those already doomed might as well be used for stem cell research. As Romney reasoned in a radio ad that aired this week, "These embryos would otherwise be destroyed." The doomed embryo argument seems to offer Romney the distinction he wants: It is ethical to sacrifice surplus embryos that will die anyway, but deplorable to create embryos for the sake of research. But the distinction does not hold up, because it evades the question whether the surplus embryos should be created in the first place. The fact that US fertility clinics are allowed to create and discard excess embryos is as much a policy choice as whether to permit cloning for stem cell research. If Romney believes that embryos are persons, he should condemn the creation and destruction of excess embryos in fertility clinics as vigorously as he is opposing stem cell cloning. If, on the other hand, he believes the creation and sacrifice of embryos in fertility clinics is morally acceptable, it's not clear why he doesn't consider the creation and sacrifice of embryos for stem cell research also acceptable. After all, both practices serve worthy ends; in fact, curing diseases such as diabetes and Parkinson's is at least as important as treating infertility. There is nothing inconsistent in a principled right-to-life position that opposes all stem cell research and all fertility treatments that create and discard excess embryos. But Romney can't have it both ways. He cannot oppose stem cell cloning on the grounds that it violates the embryo's inalienable right to life and at the same time defend fertility treatments that create surplus embryos and stem cell research that uses them. In the face of this difficulty, Romney might retreat to the brave new world objection. Permitting scientists to use cloning techniques for stem cell research, he might argue, will lead down a slippery slope of exploitation and abuse—therapeutic cloning today, cloned human babies tomorrow. The danger that embryo research will lead to exploitation and abuse is worth taking seriously. But sensible regulations can prevent our sliding down the slippery slope. Rather than ban cloning for stem cell research, the governor should join the Legislature in banning human reproductive cloning, limiting the length of time that research embryos can be grown in the lab, and restricting the commodification of eggs to prevent the exploitation of women. Such regulations are the friend, not the foe, of responsible science. They can enable us to redeem the promise of biomedical advance while saving us from slouching toward a Brave New World.

Abbas Has a Mandate; Now He Needs Allies - Kelman, Herbert C. (Boston Globe, 2005)
The decisive victory of Mahmoud Abbas in the Palestinian elections creates a new opportunity for resuming Israeli-Palestinian negotiations toward a mutually beneficial two-state solution. The fact that Fatah, the mainstream Palestinian party, united in support of Abbas's candidacy and that he won the election with an overwhelming majority gives him the legitimacy that he lacked during his earlier brief term as prime minister and a mandate to enter into peace negotiations. The opportunity created by the outcome of the Palestinian elections will almost certainly be lost, however, unless the Israeli government and relevant third parties—particularly the US government—are able to respond to it actively and creatively. To do so, in turn, requires an understanding of the meaning of Abbas's victory and the nature of the mandate it has given him. To begin with, the outcome of the vote must be understood as a demonstration of the political maturity of the Palestinian electorate and its eagerness to end the violence and return to the negotiating table. Even though Abbas is not a charismatic leader and has only a limited popular base, a large majority voted for him because they see him as most capable of reviving the negotiating process and undertaking internal reforms. Abbas has been clear in his rejection of violence as a means of achieving Palestinian national goals. But his goals are the same as those that have been proclaimed by Arafat and the Fatah leadership: establishment of an independent, viable Palestinian state in the West Bank and Gaza alongside and in peaceful coexistence with Israel; borders along the 1967 lines, with negotiated minor adjustments based on a 1:1 exchange of territories; Jerusalem as a shared city containing the capitals of both states; and a resolution of the Palestinian refugee problem that addresses the human needs and sense of justice of the refugee population without undermining the character of Israel as a majority-Jewish state. Abbas cannot accept less than that without losing the legitimacy the election has conferred on him and the mandate to negotiate a peaceful solution. The Israeli and US response to the Palestinian elections must meet several requirements if the opportunities presented by Abbas's strong showing are to fulfill their promise. First, negotiation of a final peace agreement must be resumed rapidly. Abbas's legitimacy would be undermined if negotiations were postponed until after the disengagement planned by Israel's prime minister, Ariel Sharon. Moreover, resumption of negotiations must not be based on conditions that Abbas cannot possibly meet in the short term, among them a total cessation of Palestinian acts of violence or a major of overhaul of Palestinian institutions. Such conditions would hand veto power to those elements on both sides that seek to block peace negotiations. Second, negotiations at this stage need to begin with a commitment by both sides to the end point that these negotiations are designed to achieve. The general outline of an agreement based on a historic compromise in terms of a two-state solution are well known. What has been lost in recent years is the mutual trust required to work out the details. Restoring this trust by committing to the end point will strengthen the majorities in the two populations that favor a negotiated agreement but do not believe they have a partner on the other side. Third, Israel and the United States must avoid any implication that Abbas is “their man,” replacing the unacceptable Arafat. Such an image can only undermine Abbas's legitimacy among Palestinians. The fact is that he was chosen by Palestinians as Arafat's successor. A major source of his legitimacy, in fact, is his close, longtime association with Arafat. Moreover, it was Arafat more than anyone else who promoted the idea of an independent Palestinian state alongside Israel and helped legitimate it, although in the end his tactics presented an obstacle to negotiations. Abbas's election has give him legitimacy to pursue these negotiation goals but to do so by more constructive means. Finally, Israel—with strong urging by the United States—must take steps on the ground that would strengthen Abbas's legitimacy by demonstrating that he is able to achieve both visible improvements in Palestinians' daily lives and movement toward ending the occupation. Such steps would include release of Palestinian political prisoners, an increase in Palestinian freedom of movement, a decrease in various forms of violence toward Palestinian people and property, and a halt in the settlement process.

Beyond the Gaza Disengagment - Kelman, Herbert C. (Boston Globe, 2005)
Israeli Prime Minister Ariel Sharon's plan to disengage from the Gaza Strip by evacuating Israeli settlements there and withdrawing troops is scheduled to begin today. Advocates of a negotiated Israeli-Palestinian peace agreement, based on a genuine two-state solution, have understandable misgivings about Sharon's ultimate intentions. Nevertheless, they have fully supported the Gaza initiative, and, indeed, they must do everything in their power to ensure its success. Disengagement from Gaza would set an important precedent for evacuating settlements in the West Bank—an essential condition for establishing a viable, contiguous Palestinian state. It is particularly important that this precedent is set by Sharon, a key architect of the settlement project (even though, from Sharon's point of view, a major purpose of disengaging from Gaza is to make it possible to hold on to most of the West Bank and the settlements there). Failure of the Gaza disengagement would set the opposite precedent by demonstrating that the settler movement and its supporters—a distinct minority in Israeli society—can exercise a veto over any step toward peace, even a modest step that has the support of a broad consensus in Israeli society. Along with their full support of the Gaza disengagement, advocates of a negotiated peace have rightly stressed the critical importance of carefully planning for the day after. Otherwise, the disengagement could easily become a dangerous trap for proponents of a two-state solution. As a unilateral initiative, it has succeeded in marginalizing negotiations and diverting attention from efforts, such as the Road Map, to move toward establishment of a Palestinian state. It has focused the internal debate in Israel on the pros and cons of disengagement at the expense of addressing final-status issues. It has given Sharon an excuse for putting off negotiations toward ending the occupation of the West Bank and an opportunity, in the meantime, to continue expanding and consolidating West Bank settlements and erecting the separation barrier within the West Bank and the area of East Jerusalem. It has fostered within the Israeli public (despite its majority support for a negotiated two-state solution) a sense of pessimism about further progress and an inclination to put final-status negotiations on hold, while waiting to see what happens in Gaza in the aftermath of the disengagement. This attitude, which plays right into Sharon's hands, probably reflects fatigue arising from the internal Israeli conflict over the evacuation of the Gaza settlements and reluctance to take further risks without assurance of Palestinian reciprocation, which, of course, cannot be offered in the absence of a bilateral process. Perhaps the greatest threat to the peace process posed by the Gaza disengagement would be linking the resumption of negotiations to what happens in Gaza in the wake of the Israeli withdrawal. According to this view, further steps in the peace process would depend on evidence that Palestinian President Mahmoud Abbas can establish an effective government in Gaza and prevent anti-Israeli violence. But the unilateral character of the Israeli withdrawal severely undermines the prospects for a post-disengagement Gaza that is governable, economically viable, and peaceful. Unless there is detailed planning, in close coordination and cooperation between Israel and the Palestinian Authority, and with the active support of the international community, Gaza may end up being cut off from the outside world, restricted in the ability to move people and goods across its borders, lacking in opportunities for economic activity and development, plagued by internal violence and lawlessness, and possibly devastated (if there is anti-Israeli violence during the disengagement, which is likely to draw a massive response). If Gaza is left in disarray, Abbas will not be able to govern effectively or prevent terrorist actions, and he might even lose power. More generally, in order to maintain public support and control violence in the West Bank, as well as in Gaza, Abbas needs to achieve concrete benefits in the daily lives of the population and show progress in negotiations toward an end of the occupation and the establishment of a Palestinian state. Thus, to condition negotiations on Abbas's effectiveness in governing Gaza and controlling violence creates a vicious circle. Only coordination before the Gaza disengagement and the resumption of negotiations immediately after the disengagement will enable Abbas to govern effectively and control violence. Under the circumstances, there are two clear priorities at this time for the proponents of a negotiated two-state solution. First, in the preparation, execution, and follow-up of the Gaza disengagement, it is essential to assure in every way possible that Gaza emerges from the process as a secure, economically viable, and governable area, and to strengthen the hands of Abbas and his administration by enabling them to present concrete achievements on the ground and in the peace process to the Palestinian population. The United States and its partners that drew up the Road Map must encourage Israeli and Palestinian coordination and cooperation for a secure withdrawal and disposition of the properties left behind in the settlements; by helping to plan and coordinate arrangements for mutual security and movement across Gaza's borders; by providing financial and technical assistance for economic development, for reopening the airport, and for building a seaport in Gaza; and by providing international observation and peacekeeping teams. The United States could make a significant contribution by appointing a high-level envoy and a team of monitors to help coordinate and implement agreements, as urged by Brit Tzedek v'Shalom, the US-based Jewish Alliance for Justice and Peace. Second, it is essential to put the resumption of negotiations over the final terms of the two-state solution on top of the agenda for the coming fall. The United States and the international community can make important contributions by encouraging an immediate return to the negotiating table, reminding the parties of their obligations under the Road Map, and offering ideas for the outlines of a final agreement. The most important work, however, needs to be done within and between the two societies, with an emphasis on countering the pervasive mood of pessimism and mutual distrust, reviving the lost sense of possibility, and creating a vision of a positive common future. Joint, non-official Israeli-Palestinian efforts to formulate the terms of a final agreement, such as the Geneva initiative, have made extremely valuable contributions by demonstrating that a pragmatic solution to the conflict that addresses the vital concerns of both parties is possible. But, even though majorities on both sides have consistently supported a negotiated two-state solution, the two publics have not fully embraced these initiatives because of their profound mutual distrust. The initiatives ask the public to make major concessions, on deeply emotional and existential issues, at a time when they have no confidence that the other side will reciprocate and follow through on its commitments. The Gaza disengagement has, if anything, increased the level of mutual distrust and the reluctance to make risky concessions. There is a need, therefore, to go beyond pragmatic formulations, essential though they be, in order to overcome the profound mutual distrust and assure the public that it is possible to negotiate a solution that is fair, safe, and conducive to a better future for both peoples. Calls for renewed negotiations and proposals for a final agreement, like the Geneva initiative, must now be complemented and framed by a joint vision of a principled peace, based on a historic compromise that meets the fundamental needs of both peoples, validates the national identity of both sides, and allows them to declare an end to the conflict consistent with the requirements of attainable justice. A jointly constructed framework for a principled peace might include the following components: Acknowledgment of both peoples' historic roots in the land and authentic links to it. Expression of regret for the suffering that the two peoples have caused each other in the pursuit of their national aspirations. Recognition that this destructive conflict cannot be solved by military means and commitment to ending it with a historic compromise, whereby the two peoples agree to share the land to which both are so deeply attached in a way that allows each to fulfill its national aspirations in a state of its own, in peaceful coexistence with its neighboring state. Affirmation that the logic of the historic compromise requires each people to make adjustments in its national narrative—in particular, for Palestinians to accept limitations on the return of refugees to the state of Israel, for Israelis to remove settlements with extraterritorial rights from the Palestinian state, and for both to give up the claim to exclusive sovereignty over Jerusalem or its holy places—in order to enable the other to maintain its national existence and express its national identity in its own state. Development of a positive vision of a common future for the two peoples in the land to which both are attached and which they have agreed to share a vision that contemplates a secure and prosperous existence for each society, mutually beneficial cooperation in various spheres between the societies, regional development, and stable peace and ultimate reconciliation.

A doctor without borders - Sege, Irene (Boston Globe, 2004)
Jennifer Leaning, just back from a taxing trip to Sudanese refugee sites, travels the world in the name of human rights CAMBRIDGE—The after-lunch meeting has just begun—and snacks of broccoli rabe and ricotta pizza have been brought to tables draped in white linen—when Dr. Jennifer Leaning strides into UpStairs on the Square. She is recently returned from a harrowing two-week trip to the Chad-Sudan border, and the gulf between that desperate place and here seems even greater than the 5,700 miles separating the two. Now she discusses the plight of Sudanese refugees with 15 activists and congressional staffers convened by Physicians for Human Rights and Amnesty International. "There is a systematic attack on villages, livelihoods, and people of the non-Arab population," Leaning tells them, "not just to terrorize them but to expunge them from that part of the earth." Leaning is an emergency room physician who turned her political conscience and love of travel into an avocation of fighting for human rights, then turned her avocation into her vocation when, in 1999, she was named director of the Program on Humanitarian Crises and Human Rights at Harvard's School of Public Health. She is a pragmatic intellectual who believes Sudan is practicing genocide in Darfur. An official finding of genocide would trigger a legal obligation for other countries to intervene, but Leaning doesn't want debate over labeling the crisis to distract from helping the more than 300,000 people now at risk of dying. She is part of a cadre of doctors affiliated with PHR who interrupt comfortable lives to use their medical expertise to investigate alleged violations of international law in far-flung places. "I can see a line of sight between making a living here and making a difference," says Leaning, 59. "Maybe I could contribute to a public debate about human suffering." "She's very brave, very smart, and very effective," says John Shattuck, the former assistant secretary of state for human rights now at the Kennedy Library. "Not many people," says former PHR president Robert Lawrence, "combine her clinical capacity to understand the urgent health needs of a population in a large refugee area and at the same time have a real thorough grounding in international human rights law and know the binding conventions and the universal declarations and all the other things Jennifer could probably recite in her sleep." What Leaning and John Heffernan, a PHR staffer from Washington D.C., found on their June trip to Chad dovetails with what others have reported is going on in Sudan's Darfur region. After government aircraft bomb non-Arab villages, Janjaweed militia, often on camelback, kill and rape, destroy dwellings and livestock, and poison wells. The government has obstructed humanitarian aid to more than 1 million people displaced within Darfur, and the rainy season will add more obstacles. An estimated 30,000 have been killed, and about 200,000 have fled to Chad. The physician group's conclusion that this constitutes an unfolding genocide goes further than other human rights organizations and adds to pressure on the United Nations and individual countries to intervene. "The issue of whether you call it genocide is a complicated one, but we're not letting it split us. There's unanimity that this is a colossal calamity, and we have to act in the next month," Leaning says. Leaning faced a challenge in Chad she never encountered on 14 missions to Afghanistan, Kosovo, Somalia, Soviet Georgia, and the West Bank. She suffered life-threatening dehydration and gastroenteritis. "It was very chastening," Leaning says. "It made me appreciate how tough the people there are, and also how vulnerable," she adds. "When you deracinate them from their life supports, although they will live longer than I would, the environment will still kill them." In her office at Harvard's Bagnoud Center for Health and Human Rights in Boston, Leaning talks of the difficulties of doing research in such places as eastern Chad. On the wall is a copy of a graph showing the number of Napoleon's troops marching to and from Moscow in 1812, its simple lines a stark depiction of the cost of a campaign in which hundreds of thousands of soldiers died. Leaning is tall, with intense blue eyes and the habit of folding the edge of the binding at the top of a pad of paper back and forth as she speaks. "You always have the feeling," Lawrence says, "that Jennifer has just had three cups of coffee." Getting from N'Djamena, the capital of Chad, to the first area Leaning and Heffernan visited took four days. They had to hire translators and a driver they felt would slow down at a woman's behest. They inspected tires and brakes, but, in a fateful oversight, forgot to check for a cigarette lighter, a crucial power source. Temperatures, Leaning says, hit 120, and sandstorms felt like smothering, swirling talc. At dusk on their third day, the SUV got stuck on a rock. Finally, a lorry approached. Leaning waved a flashlight, and men armed with Kalashnikovs alit. "This was an area known to have bandits," Leaning says. "One of them said, `You're lucky we didn't shoot. We didn't know who you were.' " With their help, the car was eventually dislodged. At the first refugee site Leaning's entourage reached, Goz Amer, the UN worker had too little food to share. "Goz Amer," says Leaning, "was much better than other parts." Thus their trip began. Though the temperature inside the air-conditioned SUV hit 90 degrees, they could keep windows closed and sand out. Quarters could be as spartan as a sheet sack on a hard floor. They carried prepackaged cheese and biscuits and bottled water. Leaning is a vegetarian who often travels to places where cooked meat is the safest food. "I've lived on bread and rice and PowerBars," she says. "The sanitation in rural Chad is really poor. Flies and sand and other elements go into what's being cooked that I didn't want to identify." They interviewed refugees about their experiences in Darfur and promised to use their stories to try to effect change. "It validates their private sense of outrage," Leaning says. "It's not just a personal tragedy but a grave disruption of what the international community thinks is right." One young man had a leg swollen from serious infection following a machete accident. Leaning tried, in vain, to convince him to come with them to get medical care, then left him money for antibiotics. She met a woman who fled Darfur with a baby at her breast and three other children. The Janjaweed shot at her, striking her in the elbow and side and taking a piece of her baby's finger. For 10 days, she walked and hid, wounded, scrounging for water and food. "I will never forget either of those people," Leaning says. "The guy with the calf wound who was so courteous and brave but who could not organize his mind to get the medical care he needed either because of his responsibilities or fear of the unknown. Or this young woman, who was so heroic in saving herself and her four children. And these are two people of 200,000." Near the end of the trip, Leaning got sick, probably from the carrot and beet salad she ate before they went to the desolate desert on Chad's northern border with Sudan. "We felt a fair amount of pressure to cover a lot of ground despite the rainy season and poor terrain. We didn't have that much sleep and we weren't eating that much. We were drinking, but the air conditioning can prevent you from realizing you're getting dehydrated," Leaning says. She was hardly perspiring when they arrived at the Bahai area. "It is an appalling place," Leaning says. Eighteen thousand refugees were there, many huddled under scattered, scraggly trees. Their animals were dying of thirst. Here, feeling faint, Leaning had to lie down. By the time she started vomiting, she was already dehydrated. She needed intravenous fluids. She carried sterile equipment, because of AIDS, but the rudimentary site had only a liter of rehydrating fluid and their sugar water wouldn't replace crucial salts and electrolytes. "My pulse was 140, and it was hard to find," Leaning says. Afraid her veins would soon collapse, she quickly had the only other doctor there at the time put in an IV. She asked to be evacuated that night. Their satellite phone was low on power, and the car had no cigarette lighter. Nobody would fly in at night in a sandstorm. Land mines and bandits made it too risky to drive four hours to a clinic in Iriba. They called Brigham and Women's Hospital to see if they could add oral rehydration salts to the IV sugar water, but the phone died. So, for six hours, Heffernan gave Leaning a tiny cupful of the salts every 30 seconds, and Leaning willed herself not to vomit or lose consciousness. At dawn they could drive to Iriba. "You have this animal sense when you know it's bad," she says. "I became entirely focused on finding a way out." The aborted call to Boston had been enough to get word to PHR, which, for the first time in its 18-year history, activated its emergency medical services. Leaning was treated in Iriba, then airlifted to N'Djamena. So ended Leaning's most recent mission, more than a half-century after her first. When she was in first grade in New Paltz, N.Y., she was one of six children selected to deliver the chickens the class had hatched to poor, immigrant farmers from Eastern Europe. "I don't recall the encounter with the farmers or the transmission of the chickens," Leaning says. "I just remember being part of this important charitable mission." Thoreau may have been content to travel widely in Concord, but for Leaning, who lives in an expansive center-entrance colonial on a bucolic street in Lincoln, staying close to home has never been enough. Her mother grew up in Japan, the daughter of YMCA missionaries. Her father was a former British diplomat who had friends around the world. They split when Leaning was 6. "Current events, the news, and insights about the news were extremely relevant and salient in our household," she says. In 1965, when Leaning was an undergraduate at Radcliffe College, she took a leave to spend a year in Tanzania. She taught in Dar Es Salaam, then set up child care in a village experimenting with rural agriculture. In 1967, she and the husband she later divorced (she just remarried) honeymooned with a trip around the world. They hitchhiked from Nairobi to Cape Town, traveled steerage on a freighter between Singapore and Ceylon, now Sri Lanka. In 1969, she visited Kabul, where her mother was teaching; in 2002, she returned to Afghanistan on a PHR mission during which she visited prisoners and uncovered a mass grave. "Consciousness and appetite for life and yearning for a future is something everybody is born with," she says. "I was fortunate that I was born in a time and context that allowed me to thrive and prosper. I feel connected, and not intimately, personally responsible for everyone's grief and suffering, but in a complex, organized social way, I feel responsible." The afternoon that starts with the meeting at the restaurant ends with Leaning participating in a crowded public forum on Sudan at Harvard's Kennedy School of Government. In the month since she's been home, an additional 12,000 refugees are estimated to have fled to the Bahai site where she got ill. "The chance is now," Leaning says. "It's almost slipping past us."

'Peace with honor' in Iraq - Arreguin-Toft, Ivan; Toft, Monica Duffy (The Boston Globe, 2004)
IMAGINE the following speech explaining to the American people why we are in Iraq: "Why are we in Iraq? "We are there because we have a promise to keep. Since 2003 we offered support to the people of Iraq. We have helped to build, and we have helped to defend. Thus, over the past year, we have made a national pledge to help Iraq defend its independence. "And I intend to keep that promise. "To dishonor that pledge, to abandon this small and brave nation to its enemies, and to the terror that must follow, would be an unforgivable wrong. "We are also there to strengthen world order . . . "There are those who wonder why we have a responsibility there. Well, we have it there for the same reason that we have a responsibility for the defense of Europe. World War II was fought in both Europe and Asia, and when it ended we found ourselves with continued responsibility for the defense of freedom. . . . " This speech sounds familiar, and not just because we hear many of the same sentiments from our leaders today. Change the name of the country and the date, and you'll have a speech given by President Lyndon Johnson at Johns Hopkins University in May 1965. The country in question then was Vietnam, and by the time of the commitment of US ground forces in March of that year, the war to save South Vietnam's independence was already lost. Furthermore, it had never been a war that could be won by military means alone. Although many in the Johnson administration recognized this at the time, then as now, the weight of institutional inertia restricted nonmilitary support to mere rhetoric. President George Bush was wrong to commit US armed forces to the removal of Saddam Hussein from power in Iraq. Even had he been justified in doing so -- had Iraq possessed operational weapons of mass destruction -- the lack of planning to manage post-Hussein Iraq, to balance military and nonmilitary approaches to reconstructing Iraq, would have doomed our efforts there to failure. This is why we, along with more than 650 fellow academics and former foreign policy practitioners of all partisan stripes have signed an open letter of protest to the American people. (It is available online at www.sensibleforeignpolicy.net.) President Bush can no more succeed with our current approach in Iraq than LBJ did in Vietnam. This is true even though Bush is not hindered by a superpower rival or an ambitious plan to eliminate domestic poverty. President Johnson recognized the hopelessness of our position in Vietnam well before the failed Tet offensive of 1968 and well before March of that year, when he declared he would not stand for reelection. Then as now, the United States tried to train and equip a domestic armed force capable of providing security. But, with little international support, the insurgents were able to portray South Vietnam's military as lackeys of US imperial interests. Then as now, the United States tried to use its unmatched technology to support combat missions to surround and destroy insurgent strongholds, only to find their foes slip away, sometimes across international borders to safe areas in neighboring states. Then as now, in spite of their best efforts, US forces continually injured and killed noncombatants, thereby expanding the pool of supporters, informers, and future recruits for the insurgents. In the end, the war in Vietnam became exactly what the North Vietnamese propaganda machine had always (at first wrongly) claimed it to be: an antisocial war. It became a war that pitted the US military against the people of another country. Whatever the justice of the original mission, the character of the war changed, and it became an unjust war. President Johnson, to his credit, refused to preside over the continuance of that war. It fell instead to President Nixon to manage "peace with honor": declaring a US victory and then abandoning South Vietnam to its own compromised resources. This is now the Bush administration's best course in Iraq. The only other remaining policy option is to expand military service, and if history is any guide, providing security in Iraq will require an army of at least a million soldiers. Unfortunately, due to the more widespread and intensified threat we now face, a future Bush administration may attempt to do both. In the meantime, Al Qaeda remains dangerous, North Korea has nuclear weapons, and Iran is bent on acquiring them. And until we rethink our policy, American men and women, along with the Iraqi citizens whose freedom Bush so doggedly claims to defend, will continue to die in a war we never needed to fight.

A hard line on visas can only harm America - Newland, Kathleen; Adrian Fortescue (Financial Times, 2004)
Not since the Vietnam war has international public opinion about America sunk so low. US officials praise "American values" when abroad, but they are competing with images of prisoner abuse and torture, and even Fahrenheit 9/11, Michael Moore's wildly successful anti-Bush polemic. The best way to counter such negative views has been to encourage others to come and see for themselves the strengths of American society. But in this particular battle for hearts and minds, the US government is currently engaged in unilateral disarmament. By making admission of foreigners so difficult and intimidating, America is depriving itself of a formidable strategic advantage. The US State Department issued 36 per cent fewer visas in the 2003 fiscal year than in 2001—cutting total visitors by almost 1m. The fall is almost universally attributed to the more stringent security procedures introduced after September 11, 2001. No one questions the need for measures to prevent terrorists entering US territory, but many question whether new entry procedures meet even minimum standards of efficiency and cost effectiveness. Foremost among the sceptics are US research and educational establishments. Some 560,000 student visas were issued in 2001, but only 474,000 in 2003. US universities depend heavily on foreign graduate students and scholars - especially in mathematics, the sciences and engineering. In May, more than 20 professional associations representing some 95 per cent of the US research community made an unprecedented joint declaration describing the current visa-processing logjam as a crisis. Larry Summers, Harvard's president, warned in April that if visa procedures remained so complicated and lengthy, "we risk losing some of our most talented scientists and compromising our country's position at the forefront of technological innovation". American business has been somewhat less vocal than the universities, but the fact remains that immigrants accounted for half the growth of the US labour force in the last decade. In addition, US companies are finding it harder to move international staff in and out of the US for meetings and assignments; potential business partners are discouraged from visiting to make deals and start new ventures. US business leaders say the new obstacles have cost them billions. Casual visitors are also important to the US economy. The travel and tourism industry, catering to US residents as well as foreign visitors, employs one of every eight people in the US civilian labour force. Visitors spend more than Dollars 80bn (Pounds 43bn) a year on travel to the US and once there generate extra sales and tax revenue in excess of Dollars 90bn. The State Department has moved to expedite visas for students and scholars. But a much more focused, government-wide effort aimed at all kinds of visitors is needed. Special procedures for "low-risk" repeat visitors should be created. The visa process needs to be streamlined and properly staffed, its costs to applicants reduced, its technological tools upgraded and its consistency assured through clear guidelines. Issuing visas remains the classic entry-level job for young foreign service officers—a relic of the days when it was considered a function in which one could do little harm. The US needs a professional corps of visa officers, who can accumulate knowledge and experience. If the steps taken are inadequate, many more potential visitors undoubtedly will decide to go elsewhere—to Australia or Canada or Europe—for leisure, study or business. Universities in the English-speaking world, in particular, have a serious opportunity to fill the gap left by America's obstacle course. Rather than ratcheting up fees for foreign students, they should be courting the world's best and brightest to join their science and engineering faculties and then move on to research institutions and companies. After the second world war America grew to world-beating prominence in part by attracting talent from all over the world to its critical nodes of scientific research, entrepreneurship and industry. Its post-September 11 failure of nerve may be a moment of high opportunity for Europe and other countries. The US is not the only country to have suffered at the hands of terrorists, but it seems to be uniquely intent on supplementing them with wounds of the self-inflicted variety.

Blair Falls out of Favor with Europe - Le Corre, Philippe (Boston Globe, 2004)
The expansion of the European Union this week, as well as elections to the European Parliament in June, make 2004 a crucial year for the EU. In many ways it was also supposed to be Tony Blair's year. For many Europeans, the British prime minister was the top contender for the political leadership of Europe. The position of president of the European Union, whose creation he advocated, was meant to be his. However, the past 12 months have had a devastating impact on Britain's position in Europe. Blair's support of the Bush administration's invasion of Iraq has compromised his European ideals and ignored the views of European public opinion. Just like Italy's Silvio Berlusconi or Australia's John Howard, Blair now faces the risk of an electoral fiasco. Many of his Labor voters still have not fully digested the implications of going along with the US "preemptive strike" against Saddam Hussein's regime. The elections to the European Parliament in June will most probably give a warning to the British leader. As for his U-turn announcement on a possible referendum on the EU's new constitution, British and European commentators have unanimously condemned it as an opportunistic move by the prime minister in order to outplay his Conservative opponents during the upcoming electoral campaign. Fellow European politicians such as the former Irish premier John Bruton accused Blair of showing "no leadership on European issues." From his 1997 landslide victory to the fall of 2002, Blair was the dream politician of many Europeans who saw in him the hope of their generation. In Germany, Spain, Italy, and even France, known for their conservative if not old-fashioned politicians, people were fascinated with this cosmopolitan British prime minister. He had promised to put his country at the "center of Europe" in order to end 50 years of misunderstandings between Britain and its continental neighbors. French members of Parliament remember Blair's March 1998 pro-European speech and are still struck by the fact that he was praised by both right and center-left parties. In Germany, the ruling SPD party had had strong links with the Labor government until last year. Meanwhile, the Blair administration was filled with ambitious foreign affairs specialists open to the world, especially to Europe. Blairites then started to play a larger role in European institutions; not only the UK Representative Office in Brussels but also European Commission directorates, and even the European Parliament's main political groups became powerful instruments of Blair's dynamic policies. In less than five years, the number of British bureaucrats increased in senior EU positions in Brussels. That was before last year's Iraqi diplomatic crisis, the most serious rift within the EU since Britain joined in 1973. Meanwhile, Britons have become more pro-European. They have traveled more extensively across the continent and bought property. Moreover, they are encountering more and more Europeans in their own country. Whether in lifestyle, business, or the way public services are run, they realize they have a lot more in common with their continental cousins. In addition, the spread of the English language is now making them particularly comfortable with communications across Europe. It is likely that the arrival of 10 new EU members will help to unify the continent even more under a common banner. Sadly, by splitting Europe and not calling for a British referendum on the European currency in the spring of 2003 (as originally planned), Blair has failed to recognize his countrymen's ideological and emotional proximity with continental Europe. Despite attempts to reconcile with President Jacques Chirac of France and Chancellor Gerhard Schroeder of Germany on issues such as European defense and economic reforms, Blair may well have missed his chance to play a major leadership role in the new Europe. Many pro-European British diplomats, politicians, and businessmen—not to mention pro-British Europeans—are disillusioned. In the eyes of many Europeans, Blair is now no more than an interesting politician unwilling to chose between the two sides of the Atlantic.

La Argentina tuvo un golpe de mala suerte, an interview with Jorge Domínguez - Rosales, Juan (La Nación, 2004)
WASHINGTON.- "Con las crisis recurrentes que ha vivido en los últimos años, la Argentina no se ha convertido en latinoamericana. Se convirtió en sublatinoamericana." Este concepto, duro para la estima de los argentinos, parte del profesor Jorge Domínguez, uno de los politicólogos más reconocidos de Estados Unidos sobre cuestiones de América latina, que dirige el Centro de Asuntos Internacionales Weatherhead, de la Universidad de Harvard. Desde su oficina en el campus de Harvard, ubicado en la ciudad de Cambridge, a pocos kilómetros de Boston, Massachusetts, Domínguez dijo a LA NACION que "debería ser un objetivo optimista de la Argentina llegar a tener resultados tan buenos como Brasil, Chile o México". "Si se hubieran latinoamericanizado a lo Brasil, Chile o México, las cosas no estarían tan mal", sostuvo el politicólogo respecto de la idea de que, después de las crisis económicas, la Argentina comenzó a parecerse más a los países de América latina que a Europa, como buena parte de la dirigencia argentina repitió por décadas. "Lo triste del caso argentino es que es peor. El país puede ser comparado con los de la región andina, como Bolivia y Ecuador, que han tenido una experiencia similar a la argentina", dijo el profesor de Harvard. Domínguez, ciudadano norteamericano de origen cubano, considera que el gobierno del presidente George W. Bush desatendió los problemas de América latina. "La prioridad de Bush para la defensa de los regímenes democráticos y constitucionales en el continente ha sido débil", dijo. Y cuestionó el apoyo norteamericano al derrocamiento de Jean-Bertrand Aristide, en Haití, este año, y la fallida promoción del golpe en Venezuela, en 2002. "Los últimos dos o tres años han sido un período muy difícil, prácticamente, en todo el continente. Sin embargo, no veo la situación como para llegar a un nivel de pánico, que a veces cunde en discusiones sobre el tema", señaló. En una radiografía de la región, Domínguez dijo que en Brasil "el proceso electoral introdujo una innovación en América latina, que fue el hecho de que hubo, antes de las elecciones, una negociación entre el FMI y la oposición. El primer caso de ese tipo de negociación ocurrió en Corea del Sur, después de la crisis financiera en 1997. En Brasil tuvo un par de consecuencias importantes. La primera fue la consagración de Lula, porque le ayudó a quitarle su única carta al candidato oficialista, José Serra. De pronto, Lula podía ser elegido con el respaldo del FMI", expresó Domínguez. "La segunda consecuencia es que en el gobierno de Lula se ha venido cumpliendo el acuerdo con el FMI, que ha tenido dimensiones muy positivas. Por ejemplo, la reforma del sistema de jubilación. Es una especie de matrimonio entre el saneamiento de las cuentas fiscales y la posibilidad de desarrollar un programa de un presidente socialdemócrata", añadió. Entonces, surge de inmediato la pregunta sobre la Argentina. "En el caso argentino, en el que parecía que todo salía mal, hay cosas que dentro de un contexto terrible no salieron tan mal. No hubo un golpe de Estado. Por la experiencia argentina, no era algo descartable, ya que, en circunstancias parecidas, hace rato que hubieran venido ocurriendo múltiples golpes de Estado. Cuando la frase que pedía «que se vayan todos» calaba en la opinión pública, los únicos que se fueron fueron los radicales, aunque hay un proceso de reconstrucción del Partido Justicialista que no ha terminado, porque el justicialismo siempre se está reconstruyendo. No es posible gobernar sin partidos políticos. Me sorprendería mucho que no se produjera la reconstrucción del radicalismo, ya sea con la forma de la vieja UCR o bajo alguna otra que le permita hacer su tarea opositora de una forma más efectiva." -¿Cómo hace América latina para salir de estos períodos de estabilidad e inestabilidad, que parecen ser cíclicos? -Donde, lamentablemente, los ciclos se observan más es en la Argentina. En el caso brasileño, veo que hay un paso al frente. Que el principal candidato de la oposición de izquierda, que había sido derrotado en consecutivas elecciones, de pronto gane y adopte políticas eficaces, tanto en términos económicos como sociales, no es repetir un ciclo: es un paso adelante. En Perú, si bien son lamentables algunos aspectos del comportamiento personal de Toledo, hay pasos institucionales importantes, como la reforma del Poder Judicial, el restablecimiento del poder civil contra la prepotencia de las fuerzas armadas, el crecimiento de la economía, la contención de los niveles de violencia… No veo esto como un ciclo. La expresión cíclica sí les pega a la Argentina y a Bolivia, dos casos en los que se dan estas circunstancias trágicas, y también Ecuador. En los casos de la Argentina y de Bolivia es algo particularmente lamentable, porque si hubiéramos tenido esta conversación hace diez años ambos hubiéramos pensado que por fin esos países habían salido de esos ciclos. -En el caso argentino, ¿cuál es la raíz de estas repeticiones? ¿Es económica, es un problema de la dirigencia política? -Lo que voy a decir parecerá, a lo mejor, una gran tontería, aunque no creo que sea así. Parte de lo que ocurre en la Argentina, aunque no es todo, es producto de la mala suerte. Y mala suerte quiere decir algo relativamente preciso: la coincidencia de una serie de factores, no vinculados entre sí, pero que ocurrieron en un mismo instante histórico. La Argentina ejecutó una reforma en su sistema de jubilaciones, con un costo importante, como ocurre en cualquier país del mundo que lo hace. Esto coincide, y no es más que una triste coincidencia, con un retraimiento de la financiación internacional, porque los inversores prefirieron poner sus ahorros en la Bolsa de Nueva York y no en los países en vías de desarrollo, tras la crisis asiática de 1997 y de la rusa de 1998. Otro aspecto coincidente, que no tiene que ver con lo primero, pero sí con lo segundo, es la crisis brasileña de enero de 1999, que azota a la Argentina. Otro factor, analíticamente independiente de los demás, es el aumento del gasto fiscal en las provincias y en el nivel nacional, que tuvo un elemento político, que fue el intento del presidente Menem de buscar otra reelección. Si hubiera ocurrido uno solo de estos distintos elementos coincidentes en el tiempo, no creo que la crisis argentina hubiese sido tan grave. La coincidencia de estos factores, independientes uno de otro, desembocó en una catástrofe. -El presidente Néstor Kirchner planteó que América latina necesita un Plan Marshall. ¿Es posible o es sólo una quimera? -No creo que vaya a haber un Plan Marshall. Tampoco creo que sea una retórica presidencial inútil, porque es un buen llamado de atención. Lo que, sin duda, ni la Argentina ni el resto del continente requiere es lo que se podría llamar el Plan O’Neill, que fue otro de los elementos coincidentes y lamentables de la reciente experiencia argentina. Le tocó un secretario del Tesoro de los Estados Unidos que, aun en sus declaraciones públicas, innecesarias, socavó cualquier tipo de medida internacional adoptada por la Argentina en aquel momento. Esto sigue siendo insólito para mí. No porque fuera incorrecto, contrario a los hechos observables de la Argentina en los diez años anteriores, sino porque no parecían servir a ningún propósito de la política exterior de los Estados Unidos. No es menos cierto, por otra parte, que O’Neill era ministro del presidente norteamericano y, por lo tanto, lo suyo sí tuvo un costo real para la Argentina. -¿Esto no es, entonces, el cambio en el paradigma frente a la asistencia de los países en crisis financieras, del que habla el ministro de Economía, Roberto Lavagna? ¿Era sólo el pensamiento de O’Neill o era una estrategia del gobierno de Bush? -Me sentiría feliz si pudiera afirmar que hay una estrategia del gobierno de Bush con relación a estos temas en América latina. No creo que haya una estrategia; sí una falta de atención. Bush es un presidente, lógicamente, distraído: una guerra en Irak que no se termina; una elección presidencial que parece ser muy reñida. Creo, y en esto Lavagna tiene razón, que ha ocurrido un cambio de política de Bush con relación a la política tradicional de Estados Unidos, no solamente bajo el mandato de Clinton, sino del padre del actual presidente, George Bush, y, en algunos aspectos, en la segunda presidencia de Ronald Reagan. La segunda presidencia de Reagan tuvo el Plan Baker, para intentar resolver algunos problemas de financiación en América latina y la presidencia del primer Bush arrancó con lo que se llamó el Plan Brady. Si comparamos a Brady con O’Neill, estamos frente a las dos caras de la luna. El primero asumía que, en efecto, la crisis financiera latinoamericana es real, que no puede resolverse sólo pidiéndoles a los países que hagan mayores esfuerzos, sino que parte de la solución debe ser compartida. Ese fue el Plan Brady. Y esto no lo hemos escuchado recientemente. -¿Qué otras diferencias hay? -La defensa de la democracia, que fue un elemento importante en la segunda presidencia de Reagan—no en la primera—, en la de Bush padre y en la de Clinton. Limitémonos a los dos Bush y tomemos un político que no es de mi agrado: Jean-Bertrand Aristide. Cuando fue derrocado, en 1991, por un golpe militar en Haití, Bush padre condenó el golpe militar, aplicó las normas de la OEA, impuso sanciones económicas a los golpistas y le dio asilo a Aristide. La actual presidencia de Bush públicamente le dijo a Aristide que se vaya. El apoyo a la democracia bajo la presidencia de Bush padre también se vio con el autogolpe de Alberto Fujimori en Perú. Le dijo que no estaba a favor de esas maniobras y Fujimori tuvo que dar marcha atrás e, inclusive, garantizar el proceso electoral futuro. Esta vez, lo menos que se puede decir con el intento de golpe de 2002 para derrocar al presidente Hugo Chávez es que el gobierno de Bush fue incompetente. Otro caso: la renuncia obligada de Gonzalo Sánchez de Lozada, en Bolivia. Un presidente sudamericano más cercano a los criterios políticos y económicos del actual gobierno de Estados Unidos sería difícil de encontrar. Lo único que Sánchez de Lozada requería era un poco de ayuda financiera y lo que le dieron fueron migajas. -Es decir que la presidencia de Bush desatiende a América latina y cuando se mete genera problemas… -Así es. Y la comparación la hacemos con su padre. Si comparamos a Bush uno con Bush dos y observamos el comportamiento frente a la deuda latinoamericana, el apoyo a la democracia, ¡caray!, son dos presidencias muy distintas, a pesar de que muchos de sus integrantes sean los mismos. Uno puede ir repasando los hechos y se da cuenta de que las reglas han cambiado. -Frente a este esquema, ¿cuál es el futuro que ve en la relación de América latina con Estados Unidos, gane Bush o gane el demócrata John Kerry en noviembre? -No veo raíces institucionales o políticas para imaginar que una segunda presidencia del actual mandatario sería distinta de la actual. La guerra en Irak tendría otros matices, pero seguiría ocupando buena parte de las prioridades de este presidente. La amenaza terrorista no está por terminar. -¿Qué cambiaría con un presidente demócrata? -No supongo que los cambios serían dramáticos. Kerry parece más propenso a acudir a los organismos multilaterales, buscar consensos, la construcción de coaliciones y de ser fiel a sus amigos internacionales. Kerry no ha sido un político que haya dedicado mucha atención a los aspectos financieros internacionales, como el tema de la deuda. De manera que sobre ese tema en particular no estoy muy seguro de que cambie considerablemente, pero tampoco me sorprendería si hubiera un intento de retorno a lo que fue la política de Clinton, del primer Bush y de la última parte del mandato de Reagan. Tendría cierta sensatez decir que ésa es una manera de hacer las cosas mejor de lo que ha ocurrido en los últimos tres años. Sobre la defensa de los regímenes constitucionales, Kerry criticó el comportamiento del gobierno de Bush con relación al derrocamiento de Aristide, no por la defensa de él sino por la decisión de tumbar un régimen democrático. -Kirchner y Lula han hecho un llamado para que haya cambios en los parámetros de la discusión de los organismos internacionales con los países de América latina. ¿Tiene futuro o es sólo un llamado de atención? -Parte de lo que se observó en la relación entre el Fondo y Lula, cuando era el candidato de la oposición, sugiere la posibilidad de que el FMI en particular y otros organismos en general estarían dispuestos a discutir diversos aspectos de la relación entre las instituciones financieras internacionales y los países en vías de desarrollo. No creo, sin embargo, que se trate de cambios dramáticos, pero sí de sentarse a discutir sobre temas concretos. La señal más importante fue la negociación del FMI con la oposición brasileña antes de las elecciones.

Negotiation is the Road to Mideast Peace - Kelman, Herbert C. (Boston Globe, 2004)
Prime Minister Ariel Sharon of Israel is seeking US support for his government's planned unilateral steps to address the current Israeli-Palestinian crisis, including the construction of a barrier around and within the West Bank and the removal of Israeli settlements and troops from the Gaza Strip. Such unilateral steps would have disastrous consequences. They would divide the West Bank into disconnected, fenced-off enclaves and further erode the Palestinian economy and quality of life. They would make Gaza ungovernable and probably put it under the control of Islamic extremists. They would make it impossible to form a viable Palestinian state and to resolve the deadly conflict between the two peoples. The US administration should strongly discourage these unilateral steps and promote a return to serious negotiation of a comprehensive, final agreement between the parties. Negotiations are the only way to develop a formula for ending the conflict that meets the basic needs of both parties, that engenders their commitment, and that is conducive to stable peace, mutually enhancing cooperation, and ultimate reconciliation between the two societies. Sharon's argument in favor of unilateral steps is that there is no partner for peace on the other side. This view has been widely shared within the Israeli public since the breakdown of the Camp David talks in 2000 and the onset of the second intifada. Indeed, this view is mirrored on the Palestinian side, where there is an equally strong belief that there is no Israeli partner for a solution that would establish an independent, viable Palestinian state. These mirror images are dangerous because they justify acts of violence and unilateral steps that create self-fulfilling prophecies: The belief or claim that there is no negotiating partner on the other side—that the only language “they” understand is force—leads to actions that destroy the possibility of negotiations. There is ample evidence that these images are not only dangerous, but unwarranted. Public opinion data on both sides continue to show majorities in favor of negotiations and of a compromise based on a two-state solution (while believing that the other side is not ready for such a compromise). Furthermore, in recent months, politically influential Israelis and Palestinians have issued joint proposals for resolving the conflict on the basis of a mutually acceptable two-state formula. The most elaborate of these proposals is the Geneva accord, developed under the leadership of Yossi Beilin and Yasser Abed Rabbo, Cabinet members and leading negotiators of the Israeli and Palestinian governments, respectively. The Geneva initiative represents a particularly significant contribution to the peace process. Given the character, background, and experience of the prime movers of this initiative and of the people who joined them in the effort, it suggests very strongly that there is a credible negotiating partner on each side. Given the specific and detailed agreements it achieved on many of the most contentious issues in the conflict, it suggests very strongly that there is a mutually acceptable formula for a two-state solution that can be successfully negotiated. The Geneva accord itself is not a negotiated agreement in any formal sense of the term, but it is a first-class simulation of such an agreement. As such, it offers a powerful demonstration that a mutually acceptable agreement can be negotiated. It does not substitute for official negotiations, but it provides an impetus for renewed negotiations, by highlighting the principles on which an agreement must and can be based. Moreover, it should help speed up the negotiation process because it offers concrete ideas for dealing with many of the difficult practical and political issues that a final agreement would have to encompass. Above all, it breaks through the pervasive pessimism, mistrust, and despair that have hampered return to the negotiating table. The Geneva initiative has already gained considerable support around the world, including the United States. The possibilities for successful negotiations that it demonstrates can serve as an effective counterweight to Sharon's argument that he has no partner for peace and hence no alternative to the unilateral use of force. But gaining American and international support is only part of the problem faced by the architects and promoters of the Geneva initiative. The critical challenge they confront is to garner public support for the principles and terms of the accord within their own societies. The compromises envisaged by the Geneva accord entail high costs for the two peoples. In particular, there is strong resistance to provisions requiring them to relinquish claims heavily laden with emotion and symbolic meaning and central to their national identities and associated narratives—such as those touching on the right of return of Palestinian refugees or sovereignty over the holy sites in Jerusalem. Even among the majorities in each public who support compromise to achieve a two-state solution, there is great reluctance to bear these costs in the face of profound distrust in the other side's willingness or ability to reciprocate and to conclude a genuine, acceptable agreement. These concerns are exacerbated by a structural problem in the way proponents of the Geneva accord present it to their respective publics. For understandable reasons, they may emphasize to their own constituencies how favorable the accord is to their own interests and how much the other side has conceded. What may encourage their own public, however, may well discourage the public on the other side—who inevitably also hear these messages—and may reinforce the prevailing distrust. For example, when Palestinians hear Israelis stress that Palestinians have in effect given up the right of return, and Israelis hear Palestinians deny that this is the case, both may come to feel that the accord is a bad deal or that it is sufficiently ambiguous to allow the other side to exploit it to their own side's disadvantage. There is a need, therefore, for common messages, jointly constructed by thoughtful and credible representatives of both sides, and brought to both populations. Joint construction is essential to ensure that proponents of the Geneva initiative avoid working at cross-purposes as they seek to mobilize their own constituencies—to ensure that their messages are responsive to the concerns and sensitivities of each side without unduly threatening the other side. Furthermore, to build on the enormous achievement represented by the Geneva accord, its provisions must be communicated in a way that captures the publics' imagination and generates trust and hope. The two publics must be persuaded that a solution along the lines envisioned in the Geneva accord is not only necessary, but that it is possible, that it is safe, that it is fair, and that it promises a better future. To this end, the Geneva initiative—as inserted into the public debate—should be framed in terms of a principled peace that represents, not just the best available deal, but a historic compromise, which meets the basic needs of both societies, validates the national identity of each people, and conforms to the requirements of attainable justice. I envisage three central elements to a jointly constructed framework for a principled peace: Acknowledgment of the other's nationhood and humanity, through explicit recognition of each people's right to national self-determination in a state of its own, acceptance of each other's authentic links to the land, and rejection of language that denies the other people's political legitimacy and historical authenticity; and through words and actions demonstrating that the other side's lives, welfare, and dignity are considered to be as valuable as one's own. Affirmation of the meaning and logic of a historic compromise, by framing the agreement as a commitment to end the conflict and share the land both sides claim through the establishment and peaceful coexistence of two states, in which the two peoples can fulfill their respective rights to national self-determination, give political expression to their national identities, and pursue independent, secure, and prosperous national lives; and by clearly spelling out the implications of such a commitment in terms of both the costs that the logic of the historic compromise imposes on each side, and the benefits provided by a principled peace. Creating a positive vision of a common future, by framing the agreement as an opportunity for the two peoples to build a common life in the land they share and to which they both have emotional attachments, rather than as an arrangement being forced on them by outside pressure and the unending cycle of violence. Consistent with the high degree of interdependence between the two societies, the agreement should be presented to both publics as the foundation of a future relationship based on mutually beneficial cooperation in many spheres, conducive to stable peace, sustainable development, and ultimate reconciliation.

Look at the Small Victories - Andrew Moravcsik (Newsweek, 2003)
Sept. 29 issue—The Swedes reject the euro by the resounding margin of 56 percent to 42 percent. Politicians and pundits proclaim the European Union has reached a crisis. Well, yes and no. The Swedish vote was no isolated bout of Nordic crankiness. To the contrary, it was sign of the deep disillusionment sweeping Europe. Yes, Estonia just voted overwhelmingly to join the Union, and Latvia probably will do the same this week. But note how, in a recent referenda, a slew of existing members have either voted down a variety of proposed community reforms or approved them by only slender margins. In Sweden’s case, a broad coalition of female, working-class, poor and rural voters rose to defend the welfare state against what they perceived as collusion between neo-liberal business and government elites in Stockholm and distant and unaccountable technocrats in Brussels. It's hard to interpret this as anything but a resounding sign of the times. Over the coming year the leaders of at least five countries have promised to submit the landmark new European constitution, currently in the final stages of negotiation, to national votes. Even a single no could consign the whole lofty enterprise to failure. It will be a rough ride, underscoring the EU’s accelerating fragmentation. In Britain last week, Tory euroskeptics watched gleefully as government officials admitted that adopting the euro is “completely off the radar screen” until 2007. In Brussels, the president of the European Commission, Romano Prodi, warned that the EU might split, relegating Sweden (along with fellow Eurozone holdouts Britain, Denmark and some East European members-in-waiting) to a sort of second tier of financially less-influential countries. Acrimonious splits between “old” and “new” Europeans over the Iraq war have undermined any semblance of unified foreign and security policies. And when it comes to common economic policy, budget-busting fiscal “unilateralists”—France, Italy and Germany—have all but killed the EU stability pact. This is not the end (or even the beginning of the end) for European integration. But it is the end of the cherished Euro-federalist dream (and Euro-skeptic nightmare) of a single European state, centralized in Brussels. To be sure, every member accepts certain core commitments—the single market, the European Parliament and the supremacy of European law in most economic matters. In a plethora of regulatory areas—from anti-monopoly policy to cellular-phone design to food-safety standards—EU rules are the rules. Still, the EU has crossed the Rubicon. Once a relatively small and homogeneous organization, cherishing “ever closer union” above all else, it has become a large and far more diverse, flexible and pragmatic one. “Multispeed” arrangements, whereby countries advance toward integration at their own pace, have become the norm. Eurocrats have even invented a positive term for it: “enhanced cooperation." Many West Europeans from the old core of the European Community are still ambivalent about the swathe of 10 eastern and southern European countries about to join their club. Their reservations, albeit to a lesser degree, are shared by the new entrants. Yet for all the bumps encountered along the way, enlargement is an admirable achievement. Over the next decade the EU will likely become a zone of enviable peace and democracy from the Arctic Circle to the border of Iraq. The lesson of the Swedish referendum is that the success of the EU cannot be measured by polls. Public opinion may swing back and forth, but the thousands of small decisions taken in common cannot be reversed. The EU remains the most ambitious and the most successful example of peaceful international cooperation in world history.

Affirmative Action: The Sequel - Patterson, Orlando (New York Times, 2003)
No issue better reveals the American tension between principle and pragmatism than the debate over affirmative action. This week the Supreme Court is expected to enter the debate with a widely anticipated ruling on the University of Michigan's admissions policies, which favor black and other minority applicants. More important than the decision the court reaches will be the reasoning it uses. As pragmatic public policy, it is easy to show that the benefits of affirmative action far outweigh its social or individual costs. It ensures the integration of our best universities and thereby promotes (if indirectly) a heterogeneous professional elite. In conjunction with anti-discrimination laws, it has directly fostered the growth of an African-American and Latino middle class. Corporate America has also embraced the policy, mostly by choice. As a result, minorities make up a large part of the middle and top ranks at many of the country's most recognizable firms. On Fortune magazine's latest list of the 50 best companies for minorities, for example, 24 percent of officials and managers are minorities. Affirmative action has transformed the American military, making it the most ethnically varied at all levels of its organization of all the world's great forces. And, along with changing ethnic and racial attitudes, affirmative action has helped promote a powerful global popular culture, many areas of which are dominated by minorities. Negative achievements—that is, what affirmative action has spared us—are hard to prove. But it is surely reasonable to attribute the relative infrequency of ethnic or racial riots in America to the presence of minority leadership in many of the nation's mainstream institutions. All these gains have been achieved at very little cost to America's economic or political efficiency: our economy dominates the world; our army is history's most awesome; our great universities have few equals; our arts, science and scholarship are the envy of the world. There are indeed costs at the individual level, borne by those whites who may not have gained places or jobs as a result of preferences for minorities. But nearly all research indicates that these costs are minuscule. Repeated surveys indicate that no more than 7 percent of Americans of European heritage claim to have been adversely affected by affirmative action programs, and it has been shown that affirmative action reduces the chances of whites getting into top colleges by only 1.5 percentage points. For all its achievements, however, many critics fear that affirmative action violates fundamental principles that have guided this country. It is indeed difficult to reconcile affirmative action with the nation's manifest ideals of individualism and merit-based competition. But America's history is replete with just such pragmatic fudging of these ideals. In foreign policy the United States has defended dictators, destabilized democracies and invaded other countries in the pragmatic promotion of the national interest. Domestically, Congress regularly passes laws that favor special interests—veterans, millionaire ranchers, farmers, oil-well owners, holders of patents about to expire, people with home mortgages—many with no economic justification, all costing billions of tax dollars. Why, then, the obsession with the principle of colorblindness, especially among right-wing activists who otherwise exhibit little enthusiasm for the equality principle enshrined in the Declaration of Independence? It is hard to resist the conclusion that principles are invoked in public life to rationalize the control of the vulnerable. In relations among equals, meanwhile, pragmatism trumps virtue. Yet these critics miss a more compelling, and more subtle, argument against affirmative action. In spite of its benefits, there are serious problems in the long run for its beneficiaries if affirmative action is not decisively modified. First, while diversity is a goal that deserves to be pursued in its own right, it was a major strategic error for African-American leaders to have advocated it as the main justification for affirmative action. In doing so, they greatly expanded the number of groups entitled to preferences—including millions of immigrants whose claims on the nation pale in comparison to those who have been historically discriminated against. Such a development understandably alarmed many whites who were otherwise prepared to turn a pragmatic blind eye to their principled concerns about affirmative action. Using diversity as a rationale for affirmative action also distorts the aims of affirmative action. The original, morally incontestable goal of the policy was the integration of African-Americans in all important areas of the public and private sectors from which they had been historically excluded. But if diversity is the goal, the purpose of affirmative action shifts from improving the condition of blacks to transforming America into a multicultural society. Thus the pursuit of inclusion is replaced by the celebration of separate identities. In a more profound sense, the diversity rationale undermines a hopeful view of America. If the purpose of affirmative action is to redress past wrongs, then it requires both the minority and the majority to do the cultural work necessary to create what Martin Luther King Jr. called the "beloved community" of an integrated nation. Instead, many of its supporters see affirmative action as an entitlement, requiring little or no effort on the part of minorities. Another consequence of this view is that it allows no recognition of the brute historical fact that the very patterns of social, educational and cultural adjustments that ensured survival, and even conferred nobility, under the extreme conditions of racist oppression no longer apply. In fact, now they may even be dysfunctional. The gravest danger, however, and what perhaps alarms the majority most, is the tendency to view affirmative action as a permanent program for preferred minorities and, simultaneously, the refusal even to consider it a topic for public discourse. Indeed, among the black middle class, especially on the nation's campuses, blind support for affirmative action has become an essential signal of ethnic solidarity and commitment. The nation needs this policy, but it must be modified. For starters, it should exclude all immigrants and be confined to African-Americans, Native Americans and most Latinos. It should include an economic means test. Only those who are poor or grew up in deprived neighborhoods should benefit. At the same time, poor whites from deprived neighborhoods should be phased into the program, a development that would counter the arguments of right-wing critics. Finally, affirmative action should be severed from the goal of diversity—which, as the legal scholar Peter Schuck has argued, is best left to the private sector. Middle-class blacks and Latinos would continue to benefit from such voluntary programs, properly understood as a sharing of diverse experiences and perspectives rather than a withdrawal into ethnic glorification. There is every reason to believe the nation's corporations and universities will continue to find such a policy to be in their own best interests, and the nation's. Americans have always recognized that high ideals, however desirable, inevitably clash with reality, and that good public policy requires compromise. But only through the struggle of affirmative action are they coming to realize that such compromises, wisely pursued, can actually serve a higher principle: the supreme virtue of being fair to those who have been most unfairly treated.

Iranian Ambitions Call for a United Reaction - Nye, Joseph S., Jr. (Financial Times, 2003)
After months of resistance, Iran has agreed to accept stricter international inspections and temporarily suspend its production of enriched uranium. That is progress, but not enough to stop an Iranian nuclear bomb. Last summer, while Americans were searching fruitlessly for evidence of a nuclear weapons program in Iraq, international inspectors found disturbing evidence next door in Iran. According to the International Atomic Energy Agency, Iran began enriching uranium at a pilot centrifuge plant last August and is also constructing larger underground enrichment facilities. Within a year, the plant could make enough highly enriched uranium for one bomb a year and the larger facilities could make 15 to 20 times as much. Iran said that its program were for peaceful generation of nuclear energy; but inspectors found traces of weapons-grade, highly enriched uranium. The IAEA set an October 31 deadline for full compliance. And now, under pressure from Europe, Iran has called a temporary halt to enrichment. But it would be a mistake to stop at this point. Iran correctly claims that, as a party to the non-proliferation treaty, it has the right to enrich uranium for peaceful purposes. In a sense, the NPT was born with a loophole. Even if a country allows inspections, it can legally accumulate enriched uranium (or reprocessed plutonium) under the guise of a peaceful energy program and then suddenly declare that circumstances have changed, and withdraw from the treaty. It could then produce nuclear weapons at short notice. If Iran were to do this, it would add to the dangers in an unstable region and would be likely to begin unraveling the non-proliferation regime worldwide. For these good reasons, President George W. Bush has declared an Iranian nuclear weapon unacceptable. Our unilateral options, however, are limited. Not only is our military plate full in trying to stabilize and reconstruct Iraq but it would also be difficult to recruit allies. Fortunately, there is a precedent from something we began in the mid-1970s. India had recently exploded a nuclear device, France was selling a reprocessing plant to Pakistan and Germany began to sell enrichment technology to Brazil. Many parties to the NPT planned to import or develop enrichment and reprocessing facilities. We feared that the non-proliferation regime was unraveling. The Jimmy Carter administration successfully persuaded France and Germany to curtail their exports, and countries as diverse as the Soviet Union and Japan joined us to form a Nuclear Suppliers Group. In 1977, we signed an agreement to restrict the export of enrichment and reprocessing facilities. We were able to plug part of the loophole without amending the treaty. Mr. Bush should build on recent progress by approaching Europe, Russia and others and persuading them to offer Iran a deal that would fully plug this loophole. Russia, which is helping Iran to construct a nuclear energy reactor at Bushehr, would offer it a guarantee of low-enriched uranium fuel and reprocessing of the reactor's spent fuel in Russia. The deal would be given teeth by a United Nations Security Council resolution, endorsed by the US. The resolution would include a stick declaring that further proliferation of nuclear weapons would be a threat to peace under the Charter and that any country moving in such a direction would be subject to sanctions. The resolution would also include a carrot—guaranteeing Iran access to the non-dangerous aspects of nuclear energy technology. The deal could be sweetened by offers to relax existing sanctions and a security guarantee if Iran remains non-nuclear. At best, such a proposal would head off a looming danger in the Middle East. At worst, if Iran rejected the deal, it would have served notice of its real intentions. European foreign ministers have produced a useful first step. Russia has refused our requests to cancel the Bushehr reactor but has indicated it would be willing to provide such fuel services. Given Iran's suspicion of the US, subtle American diplomacy would be needed to persuade Europe and Russia to launch the proposal, and we would then announce our support. There have been few recent issues on which the US, Russia, Europe and the UN are in close agreement. Such a proposal offers a rare opportunity to co-operate on an issue of vital concern.

The Mideast's Ticking Clock - Sheehan, Edward R. F. (Boston Globe, 2003)
THE GAZA STRIP has been called "a refugee state." Indeed it is humbling to wander through the Beach Camp, built to the edge of the Mediterranean Sea in Gaza City. A lonely child, severely underfed, sits on an oil drum, talking to himself and staring at the sea. An old, toothless woman invites me to sip mint tea in her dark shack, then shows me photographs of of herself as a beautiful young girl. "Where was this taken?" I ask. In Jaffa, she explains, now part of Israel. "I fled in 1948. I've lived here ever since." Gaza City is an odd place. Dusty, hot, and teeming with children, it offers scenes of squalor juxtaposed with bursts of opulence. Donkey carts coexist with Jaguars roaring by. Futuristic buildings colored pink and periwinkle—built recently when the Palestinian Authority came here to govern and rich Arabs invested in the city—tower over neighborhoods where older buildings have been ripped apart by Israeli bombs. Despite the unrest, people carry on. Shops sell furniture and mobile telephones; people go out to dinner. One afternoon, I passed a school when the gates opened. Children gushed out, the boys in T-shirts and blue denim, the girls in head scarves and long smocks—separate from the boys since the society is Muslim. As I traveled throughout the Gaza Strip, I kept encountering multitudes of children. In the north at Beit Hanoun, they played soccer in streets chewed up by Israeli bulldozers, hide and seek in the rubble of demolished houses, and even romped on jagged water pipes and bridges that the Israelis had bombed. I thought it sad that the Israeli government found collective punishment necessary, inflicting wounds on neighborhoods, villages, and towns for the crimes of single terrorists. The policy is disproportionate, and it has not worked. Most Palestinians are ambivalent about Hamas and the other militant Muslim groups. On the one hand, they admire Hamas for its fierce resistance to Israel and the United States; on the other they want peace and quiet, work to feed their families, and they hold Hamas responsible for the paralysis of their economy and the horrors of collective punishment. Yet these huge Palestinian families may one day unlock the riddle of the Arab-Israeli conflict. I mentioned the mobs of children thoughout Gaza—and the same is so in the West Bank. Palestinians generally do not practice birth control; it is not unusual to meet a Palestinian father who has eight, 10, or even 15 children. Israeli families normally do not exceed two or three children. This phenomenon is what sociologists call a "demographic time bomb"—and it terrifies Israelis across the political spectrum. Within the next two decades, Arabs between the Mediterranean and the Jordan River will surpass Jews in numbers. Many Palestinians consider the road map a bad joke, and are willing to wait until Arabs command a majority in all of historical Palestine. Michael Tarazi, a legal adviser to the Palestinian Authority, urges patience until Arabs and Jews become in effect one entity throughout Israel and the West Bank and Arabs can demand equal rights. He argues that eventually the world will impose a one man, one vote system on Israel. Soon enough, with an Arab majority, a Palestinian will be elected president of a new state embracing all of Israel, Gaza, and the West Bank. The argument is full of holes, but demographically it contains a certain logic. Liberal Israelis are determined to retain Israel's mostly Jewish character. They realize that time for a two-state solution is running out. They agree with the Arabs that Ariel Sharon's plan for a minimal Palestinian state will never work. Thus they are thrown back on President Bush's "road map." This process—already so vague about final borders and how a Palestinian state will be achieved—will inevitably fail unless Bush makes decisions from which his predecessors have recoiled. Of course he will put pressure on the Palestinian Authority to crack down on terrorism. But how will he confront the obstructions and delaying tactics of Sharon, who palpably has no intention of dismantling major settlements or surrendering East Jerusalem? One wonders whether Bush has a clear idea of the mountains he must move. Does he realize that to move Sharon he may have to withhold spare parts for the Apache helicopters, F-16 aircraft, and other military equipment that the United States sells or gives to Israel? Polls show that most Israelis still want to exchange land for peace. Reports reaching Israel suggest that Bush is furious with the Sharon government for impeding the road map. Possibly he senses that this is the last chance for a two-state solution. Those multitudes of children in Gaza and the West Bank will soon grow up, and then the demographic time bomb may explode.

O'Malley Pick for Charity Chief Is Hailed - Paulson, Michael (Boston Globe, 2003)
Archbishop Sean P. O'Malley, demonstrating the high priority he places on services to the poor, yesterday named a priest who is a national leader in Catholic social services and the former dean of Harvard Divinity School to oversee Catholic Charities of the Archdiocese of Boston. O'Malley's choice of the Rev. J. Bryan Hehir as president of the largest private social services agency in the state places an outspoken and highly regarded intellectual in the inner circle of the church's hard-pressed local administration. Hehir, who will now be a member of O'Malley's cabinet, has spoken widely about the sexual abuse crisis in the church, and has been critical of the hierarchy, declaring just last week at Boston College that "we've got to treat adults as adults in the church." He succeeds current Catholic Charities president Joseph Doolin, who had announced plans to retire. Hehir, 63, who currently serves as president and chief executive of Catholic Charities USA in Alexandria, Va., will assume his new post in January. The Boston agency provides social services to hundreds of thousands of poor people, most of whom are not Catholic and many of whom are immigrants. "There is rising human need, and there are declining resources to meet those needs, rooted in the fact that we're coming out of a recession, state budgets all across the country have been devastated, and the church across the country has been impacted by the [abuse] crisis," Hehir said in a telephone interview. "We're working on housing, nutrition, helping people with employment searches, but in Boston we're doing that under an overarching reality, which is the need for a pastoral rebuilding of trust within the church, and a public rebuilding of trust within society as a whole." O'Malley, who as a Franciscan Capuchin friar has expressed a pastoral preference for the poor, declared privately shortly after his installation July 30 that he wanted a priest to take over the agency upon the retirement of Doolin, the social worker who has headed the agency since 1989. O'Malley consulted with the agency's board of trustees, but made the choice himself. "Archbishop O'Malley, as the bishop of Boston, has a great concern for the poor and needy of Boston, and his own charisma as a Franciscan gives him a deeper love for the poor and underprivileged," said O'Malley's spokesman, the Rev. Christopher J. Coyne. "The appointment of Father Hehir to this position is going to strengthen the church's mission to the neediest among us." Many church observers were surprised that such a prominent figure would move from the national organization to a local one. But it was hailed in Boston. "In the world that Bryan Hehir lives in, he's a giant," said Neal F. Finnegan, chairman of the Catholic Charities board of trustees. "This certainly makes a statement about the importance of Catholic Charities in the array of things this archbishop is trying to strengthen." Peter Meade, the board's vice chairman, called the appointment "an incredible signal to the priests of the diocese that the archbishop wants to hear from everyone, and a signal to us of how important he believes Catholic Charities is to Boston." Voice of the Faithful, a lay organization that has been contributing money to Catholic Charities because the Archdiocese of Boston has refused to accept the group's contributions, also welcomed the move. "This is . . . an extraordinary coup for the Archdiocese of Boston," said James E. Post, the president of the Voice of the Faithful. "Father Hehir is a scholar, a passionate advocate for social justice, and a gifted leader who well understands the impact of this crisis on Catholics and Catholic institutions." Hehir will face numerous challenges at Catholic Charities, a 100-year-old agency that served 200,000 people last year and had a budget of approximately $40 million, most of which came from the state government and private fund-raising. Doolin is credited with building up the board of the organization, which includes numerous prominent business leaders, and with spearheading an ongoing but painful reorganization in which the agency expects to consolidate about 75 facilities around Greater Boston to fewer than 10. Hehir is not a well-known public figure, but in the worlds of academia and in church circles, he is highly regarded for his intellect and communication skills. He is one of the leading Catholic experts on the theory of just war. Educated at St. John's Seminary in Boston and ordained in 1966, Hehir worked from 1973 to 1992 on the staff of the National Conference of Catholic Bishops, where he was regarded as the architect of the bishops' influential 1982 pastoral letter on nuclear weapons, which called for reducing the nation's nuclear arsenal. In 1984 he won a so-called genius grant from the MacArthur Foundation, and he has won more than 25 honorary degrees from various universities. While at the bishops' conference, Hehir taught at Georgetown, and then he moved back to Boston, where from 1993 to 2001 he was a professor of the practice of religion and society at Harvard Divinity School. From 1998 to 2001, he served as the first Catholic priest to lead Harvard Divinity School, but he refused to take the title of dean or to live in the dean's mansion to demonstrate that his first duty was to the church. Cardinal Bernard F. Law, then archbishop of Boston, made it clear he was unhappy with Hehir being stationed at Harvard, a historically Unitarian school with a reputation for progressive theology. In 2001 Hehir left to head the national Catholic Charities agency, which does not provide direct services but rather serves as an umbrella organization advocating in Washington for the interests of Catholic Charities agencies around the country. Over the course of the church crisis, Hehir has been much in demand as a public speaker, and has addressed the crisis at multiple venues, including Regis College and Boston College. He has also spoken on the subject to the Boston Priests Forum. At BC last week, he declared that the church is still in crisis, saying, "We've had the nuclear explosion, the blast is over, but the radiation is still in the air," and warning that "if we lose the people who have become disillusioned by this, the next two or three generations of their families are gone, too. . . . That will be devastating." Hehir said yesterday that even as the archbishop's secretary for social services, he expects to continue to speak his mind. "You need to know when you're working in a given framework, that you're not a freelancer. But I've always found people give you the scope to speak as honestly as you can to problems, and that you should try and be as direct and clear as you can," he said.

Serious News in U.S. Early Victim of Iraq War - Helen Shaw (Irish Times, 2003)
Next month the Federal Communications Commission in the US is likely to lift remaining restrictions on media cross-ownership. Michael Powell, chairman of the FCC and son of Secretary of State, Colin Powell, has made it clear he believes the marketplace should be the mechanism by which the media business is managed. It sounds fair. But in a country where about six major conglomerates control the bulk of all forms of news and entertainment media from books, film, newspapers, radio and television, the June decision will open the way for further consolidation where a single company could own newspapers, radio and network/cable TV in the same city. The debate in the US has been limited since the public's main source of news—television—has not covered the issues of how media monopolies affect the public's news since they are owned by the main media giants. For the American public the obscured debate—which occasionally makes the business pages of mainstream newspapers—highlights the very dangers of a hyper-commercialisation of news. It is not so much a matter of bias but the absence of information which truly disenfranchises people. The recent Iraq conflict was a showcase for the commoditisation of news. The key media winner in the US was Fox News—the 24/7 cable news channel owned by Rupert Murdoch's company, News Corporation, which claimed a 300 per cent increase in viewers during the war. The network channels ABC, NBC and CBS all lost viewers, while the cable channels, led by Fox's example, won audiences by being there on demand and also for selling the war news through a patriotic filter where the US flag was put front of screen and both anchors and reporters embedded with the troops used "we" throughout their coverage. The battlefield war for the cable channels was a means to fight the ratings war. They used it as a hook to break the news connections with the network houses, and CNN, a very different product in the US to what is broadcast in Europe and the Middle East, chased Fox in an opinion-led war coverage style. In the US, the weakness of public broadcasting, particularly on TV where PBS has neither the resources nor newsroom to compete on war coverage, means that the counter balance to the market-led extremities is absent. NPR and PBS relied on relays of the BBC on radio and television to maintain a concept of full coverage and hence the BBC's man in Baghdad, Rageh Omaar, was named the "Scud Stud" by the New York Post - ironically another Murdoch house. Once CNN was thrown out by the Iraqis at the end of the first week no US TV crew remained to report the news. The BBC is using the opportunity to expand its news profile in the US. Its audiences are up 28 per cent and it will put its 24 hour news channel on cable here later in the year. The BBC director general, Greg Dyke, bluntly told an audience at Harvard Business School, during the war, that the US electronic media had "wrapped the flag around itself and given up the ghost of real journalism". And that's the point. For the AOL Times Warner, Disney, Viacom and News Corporations of the world it is not "real journalism" or informed democracy, which is the end game—it is the rewards of the market—the profit margin. It is unrealistic to expect a commercial conglomerate without legal requirements (there's no longer a legal fairness statute in the US) to behave like a not-for-profit trust or public service broadcaster. But for the US, which has the most deregulated news media market and the weakest public broadcasting sector in the developed world, the real losers are the citizens who at the end of the "war" were still left in the dark about key events like the use of cluster bombs, the impact on civilians, and the conflicting statements of record on what happened in a range of incidents, including the market bombing ones. This week both the BBC and the Guardian boasted that their websites had taken off in the US during the war. BBC News on-line increased by 47 per cent, while traffic to the Guardian news site was up 83 per cent (obviously from a relatively low base). While it's good news for the two UK media groups, the real trend is that the gap in public services or not for profit news provision in the US is being increasing met by overseas sources—indeed by the British licence—fee payers in the case of BBC News. It is ironic that at a time when the US is debating its lonely super-power status that it lacks a super news media. France's President Jacques Chirac has already set aside a budget for the creation of a French language 24/7 global news television channel to compete with the growth of global "soft power" forces like the BBC. For Europeans and indeed small countries like Ireland, the Iraq war with its image saturated 24/7 coverage; from embedded, largely US/British journalists (two thirds of the 600 embedded reporters were American) has underscored the need to debate the fate of a public's access to information. Market forces can lead to monopolies that are just as undesirable for citizens as state-controlled monopolies. The threat to public access to information was clear in totalitarian states but the threat may be just as significant in a news media world run solely to generate profit rather than spread information and seek the truth. A world where a handful of business interests dominate the provision of news needs a balance. It may be too late for the US public to engage the FCC in debate before the June deadline, but for those of us on the other side of the Atlantic, where the wave of global media is hitting, it is the time to start learning lessons not just from the inspiration of Thomas Jefferson, who said the right to information protected every other right, but also from the reality of the limits of a free falling market.

We're still vulnerable - Allison, Graham T., Jr. (Boston Globe, 2003)
Observing the second anniversary of Al Qaeda's assault on the World Trade Center and Pentagon, administration spokesmen sought to highlight progress in the war on terrorism to support President Bush's claim that we're getting safer every day. But if one stands back and asks whether Americans are actually safer from terrorist attacks than we were 12 months ago, a serious answer requires a net assessment. Our safety is a function not only of what our government does, but also of changes in our adversaries' capabilities and motivation. Assessing that balance, I conclude that the threat of terrorist attacks on America in the year ahead remains at least as high as it was last year. Consider four fronts in this war: the international campaign against Al Qaeda; homeland security; preventing nuclear and biological terrorism; and Iraq. In the first 12 months after the attack, America organized an extraordinary worldwide campaign against terrorism. Universal sympathy for American victims of 9/11 led governments and citizens around the world to proclaim solidarity under the banner, "We are all Americans." Through the UN, the United States enlisted more than 100 nations in a global effort to share intelligence information, enforce antiterrorist legislation in each local setting, and stop terrorists' flow of funds. In the past year, this global coalition has frayed. America's standing in the world has fallen further and faster than at any time in the history of polling. When asked recently whom they trust to "do the right thing regarding world affairs," more Pakistanis, Indonesians, and Jordanians chose Osama bin Laden than President Bush. Why does this matter? The essence of effective counter-terrorism is intelligence and police enforcement at the local level. The mastermind of Al Qaeda's Southeast Asian operations was captured in Thailand as a result of a tip from suspicious neighbors combined with active cooperation between local Thai agents and the CIA. The "hearts and minds" of governments and citizens provide either a sympathetic sea in which terrorists swim and hide, or alternatively, millions of eyes and ears from which terrorists cannot escape. Although the United States caught three of Al Qaeda's top leaders in the past year, bin Laden and his second-in-command are still on the lam and Al Qaeda recruitment is up. Second, in defending the American homeland, the US government has taken many significant actions, most notably the creation of the Department of Homeland Security. In time, this will yield security dividends. But realism requires recognition that in the first year after such disruptive changes, capabilities are more likely to decline than increase. Former Senator Warren Rudman's recent Council on Foreign Relations report finds a shortfall of $98 billion in priority investments in homeland security over the next five years. Third, the campaign to prevent a nuclear or biological 9/11 is failing. Despite lots of talk, North Korea is today producing plutonium that could be sold to terrorists for use in a nuclear attack. Russian and Pakistani nuclear weapons and materials remain as vulnerable to theft as they were last year. Orphaned research reactors in a dozen countries around the world, including Libya and Ghana, contain highly enriched uranium sufficient to make a number of nuclear weapons. And while Saddam no longer rules Iraq, he has gone missing, and with him a sophisticated smuggling network and whatever biological weapons Iraq had. While the administration rightly recognized the threat of a bioterrorist attack with smallpox or other agents, the campaign to protect American citizens flopped. The announced goal of vaccinating 500,000 first responders against smallpox was recently disbanded after vaccinating fewer than 40,000. Long term, Project Bioshield will create new vaccines and therapeutics. Short term, the public health system's capacity to identify and respond to bioterrorism remains dangerously inadequate. Iraq is the wild card. Analytically, Iraq was tangential to the immediate war on terrorism. The CIA found no links between Saddam and 9/11 and no evidence of Iraqi support for terrorist attacks on American targets since the early 1990s. But President Bush's decision to market war on Iraq as a centerpiece of the war on terrorism has now forged an inextricable link. While the demonstration of America's military might has surely sobered regimes that wish America harm, the administration's incompetence in postwar Iraq has attracted both terrorists and jihadi wannabes in what now threatens to become a terrorist incubator akin to Afghanistan during Soviet occupation. For the year ahead, Americans are at least as vulnerable to terrorist attacks as we were in the year past. After the next mega-terrorist attack, Americans will find our government's failure to mount a more effective war on terrorism as inexplicable as they found the failure to prevent 9/11.

Will Bush Stand by Volunteers Who Heeded His Call? Washington Politics Has Put the AmeriCorps Program in Jeopardy - Putnam, Robert D. (Los Angeles Times, 2003)
Five years ago, Haven Acres—a largely African American neighborhood of Tupelo, Miss.—showed familiar signs of urban decay: gangs, drugs, trash, dilapidated housing, for-sale signs, distrust and hopelessness. Haven Acres was so dangerous that armed cops were afraid to enter the neighborhood unless they had backup. But last month I walked at dusk through a miraculously transformed Haven Acres. Crime rates have fallen by 86%, and the drug dealers and for-sale signs are gone. Larry Otis, the white Republican mayor of Tupelo, understandably brags about this grass-roots accomplishment as the proudest success of the city during his tenure. At the heart of this change is the community center that houses a booming Boys and Girls Club, created to give the kids of Haven Acres a positive alternative to gang life. Ron Green, who grew up in Haven Acres and now runs the Boys and Girls Clubs of northern Mississippi, says the mentors at the Haven Acres club served 260 kids each day this summer, saving them from drugs, crime and maybe even death as they learned self-esteem and civic virtue. Youths whom he would not have trusted with the keys to his office six months ago now stay there late to clean up, proud of the community they are creating. And then Green's face falls. More than half of the mentors at Haven Acres were supported by the AmeriCorps program, which offers young people a modest living allowance and a promise of help toward college expenses in return for a year of full-time community service. Cutbacks in AmeriCorps have forced him to fire all those mentors and slash his services to Haven Acres children. Haven Acres is not alone. Federal politicking has forced AmeriCorps to renege on its commitments to community service programs across the country. In the three-state Mississippi Delta, the nation's poorest region, AmeriCorps' support for programs has been chopped by 90%. And thousands of other programs from coast to coast have been similarly cut. Like Green, the harried leaders of those programs have been forced to eliminate positions for volunteers—nationally, 20,000 such AmeriCorps slots have been cut, nearly half the total planned for this year. During the closing decades of the 20th century, as I wrote three years ago in "Bowling Alone," Americans became steadily less connected with one another and with collective life. We voted less, joined less, gave less, trusted less, invested less time in public affairs and disengaged from friends and neighbors and even from our own families. Our "we" steadily shriveled. In this context, the attacks of 9/11 represented not just a national tragedy but also an extraordinary opportunity for civic renewal. After these decades of disengagement from our communities, Americans surprised themselves in their post-9/11 solidarity. Many people recognized that this was a "teachable moment." If we caught that moment to build the foundation for a new culture of service and civic engagement, we could create a new "greatest generation." President Bush articulated this national yearning in his 2002 State of the Union address. The president proposed a substantial expansion of the federal government's support for national and community service through AmeriCorps. The program was already a proven success at helping young people from all walks of life—not just the wealthy who can afford full-time volunteering—invest a year of their lives in community service. Now it would be expanded to 75,000 posts a year. Bush's call to action caught the imagination of the nation's youth. Applications to AmeriCorps jumped, and organizations in thousands of communities worked to absorb and direct these new energies. But now Washington is betraying the hopes of these idealistic youngsters. Despite support for AmeriCorps from 44 governors, 79 senators, 250 corporate leaders and the vast majority of the American public, right-wing ideologues in the House have blocked the funding needed to keep the program even close to the growth path that the president laid out nearly two years ago. The House and Senate appropriation committees recently proposed allocating $340 million to $345 million to AmeriCorps for next year, but this initiative does nothing to forestall the draconian cuts facing its programs this year. The president has so far remained above the fray, seemingly reluctant to commit himself to defending his own promise. Discussing his call to service two days after the 2002 State of the Union address, Bush told volunteers in Daytona Beach: "I'm one of these accountability guys. I understand sometimes in political process all you hear are words. I like to back them up with action. It's one thing to lay it out; it's another thing to follow up. I'm a follow-up guy." Mr. President, now's the time for you personally to follow up. The nation's young people responded enthusiastically to your leadership two years ago, and now's the time to make good on your commitments to them. Now's the time for you to persuade the House to act. This is indeed a "teachable moment," and American youth—in Haven Acres and across the country—are listening. What civics lesson will you teach?

Are the costs of going to war worth it? - Hoffmann, Stanley H. (Boston Globe, 2003)
We know what the benefits of a war on Iraq would be: the ouster of a cruel tyrant and the elimination of his weapons of mass destruction. But we also know what the costs would be: prohibitive. The Bush administration believes that the overthrow of Saddam Hussein could bring democracy to Iraq and then spread to the rest of the Arab world. This is a fantasy. It will be difficult to introduce democracy in a heterogeneous country that has never experienced it. After 30 years of repression, there could be violence between ethnic and religious groups that US forces would have to cope with; moreover, a prolonged occupation and military rule would squander the good will we as liberators expect to prevail at first. Arab governments will try to contain the spread of democracy in order to stay in power. Moreover, as long as we haven't decisively intervened in the Israeli-Palestinian conflict and suggest that it may have to wait until Arab regimes have changed, Arab suspicion of the United States will mount. Indeed, American control of Iraq could contribute to Muslim terrorism and foster a xenophobic fundamentalism aimed at US "imperialism." Already the administration's obsession with Iraq and its bullying way of obtaining support have provoked considerable anti-American resentment abroad. The image of the United States has been tarnished by our manipulation of the United Nations and our alliances with NATO countries, our efforts to split the European Union, and our disdain for public opinion abroad. More seriously, the Bush administration has recklessly attacked the very foundations of world order that this country helped put in place: the UN, international law, and the EU have been the casualties of a team that has repudiated a distinction we had wisely preserved throughout the Cold War, between leadership and dictation. This may result in something we had avoided: an anti-American ganging-up of countries threatened by the growth of unchecked American power. Then there are the economic costs of the war as well as those of rebuilding Iraq and not neglecting its needs, which would encourage those who doubt American good intentions. Are these costs worth it? We have two main reasons to go to war. Both are shaky. Iraq is effectively defanged and incapable of constituting a real threat to us or its neighbors as long as we operate freely in two no-fly zones, the Kurds have autonomy under Anglo-American protection, and inspectors roam freely. Contrary to the administration's assertions, containment can continue to work in the long run, especially if the no-fly zones and the inspections are maintained, a tight naval blockade prevents military imports into Iraq, and ground forces remain stationed at Iraq's borders. War is not necessary to render Iraq harmless to others. The more difficult issue is that of Saddam Hussein. Like preventive war, forcible regime change violates international law. The exceptions to state sovereignty that were made legitimate through the so-called humanitarian interventions in the 1990s have never involved "regime change" and had to be justified by the argument that the violation of human rights constituted a threat to international and regional security. This could have been an argument for intervening against Saddam Hussein's regime in 1991; the opportunity was missed, and since then he has not committed mass crimes against humanity. Still, his regime is based on fear and terror. Sooner or later all governments may realize their citizens are entitled to basic human rights. But this principle will need international support, not unilateral action, to be established, and a clear understanding of the differences between "ordinary" bad regimes and truly evil ones. Meanwhile, those who sympathize with the plight of the Iraqi people yet do not want to increase their suffering through war should do all they can to make Saddam Hussein's position increasingly difficult. The International Criminal Court or a special criminal tribunal can try him for crimes against humanity, order a ban on travel by all top officials, deprive them of their fortunes abroad, and indicate that a recovery by Iraq of its full sovereignty will depend on its compliance with those decisions. Furthermore, we can provide covert assistance to groups of Iraqis willing to act against Saddam Hussein and overt aid if they try to overthrow him. For these purposes, we could lead a "coalition of the willing" far bigger, and less resentful, than the one we're trying to force into supporting us for a risky and unpopular war. The democracy we say we champion should begin by recognizing that listening to what the public says is not tantamount to appeasement and inaction. Gaining more victories in the difficult war against terrorism is a far more widely shared goal, and one that could be imperiled by American hubris in the war against Iraq.

Europe Comes of Age - Andrew Moravcsik (Newsweek, 2003)
Here’s how to think about the EU’s new constitution Alas, to be born into the world without friends. That seems to be the fate of the draft constitution of the new European Union, to be presented at the summit in Thessaloniki on Friday. To a contemptuous Romano Prodi, the head of the European Commission who dreamed of building a stronger "federal" union, the document "lacks vision and ambition." By contrast, British Tories and tabloids are positively twitching with Europhobia. The proposed constitution will "sweep away 1,000 years of history," proclaims the Sun. DON’T BE FOOLED. Prodi and his federalists are right. The Convention on the Future of Europe has deliberated—and delivered a mouse. When they began their work 18 months ago, Prodi and other Euro-insiders were convinced that they would dominate. They intended to exploit the bold rhetoric of constitutionalism to craft an idealistic document that centralized ever more power and democratic control in Brussels. There was heady talk of a new name, "United Europe." There were proposals for introducing majority voting on sensitive issues of foreign and defense policy. Brussels’s influence would be extended over national fiscal and social policies. National vetoes would be eliminated. A new EU president would be directly elected, by and for the people. Farewell, faceless Eurocracy. Welcome, democracy. Little of this has come to pass. The convention’s canny chieftain, former French president Valery Giscard d’Estaing, knows where real power in the EU lies. Any radical draft would be picked apart by national governments when they begin reviewing the document this autumn. To encourage them to accept his draft intact, Giscard faced down the federalists and struck backroom deals with the member states. Case in point: last week’s wrangling over whether to allow EU foreign policy to be determined via qualified majority voting. Bottom line? It won’t be. Most of the reforms that remain are simply good public management. With enlargement and a union of 25 member states, many of them tiny, it was high time to replace the revolving six-month council presidency, responsible for organizing the overall agenda. Thus there will be a new EU president, appointed by the states for a five-year term. Both "old" and "new" Europeans agree that crises like Iraq require greater integration. Thus the two top EU foreign-policy posts—currently held by Javier Solana and Chris Patten—will be consolidated into the new position of EU foreign minister. For most European countries the management of asylum, crime and defense procurement justifies a minimum set of intergovernmental standards. Thus a smattering of consensual policies will be newly governed by qualified majority voting and European Parliament oversight. Otherwise, the new constitution merely consolidates current practice—a fact that should be welcomed rather than scorned. For too long, the debate over union has been divided between radical federalists who would move forward toward a centralized Europe and excessively cautious skeptics who would roll it back. What has emerged from the constitutional convention is a Europe in equilibrium. Henceforth, policies of greatest concern to citizens—social welfare, taxation, pensions, health care, education, culture, infrastructure—will remain essentially national and local. Those of less interest—trade, banking, industrial standardization, technical harmonization—will be European. In the middle, a few policies—immigration, policing and defense—will be shared. This is a heartening outcome. In coming to terms with its strengths as well as its limitations, the European Union has at long last entered its maturity.

How Europe Can Win Without an Army - Andrew Moravcsik (Financial Times, 2003)
For many transatlantic pundits, the Iraq crisis is further proof that Europe needs an autonomous military force. This view was forcefully expressed last week by Laurent Fabius, the former French prime minister, who said in the Financial Times that Europe "was unable to make its voice heard in the US because it was divided and lacked a unified defence force". For some years now politicians have found European defence irresistible. European public opinion strongly favours it. European federalists want the European Union to have greater powers. French Gaullists, long convinced that military might means great power prestige, trumpet the idea. Tony Blair, Britain's prime minister, has exploited it to become more "European"; Joschka Fischer, Germany's foreign minister, has exploited it to become more military. The logic is seductive: if the US respects only military power, a European army will surely command respect. Yet European defence is a dangerous pipe dream. And the Iraq crisis demonstrates why. A co-ordinated military force with the global capabilities to fight a high-technology, low-casualty war would require Europeans to increase military spending, currently 2 per cent of gross domestic product, to more than the US rate of 4 per cent if it is to overcome a decades-long US lead. No European public would accept this. However heavily they were deployed, European transport aircraft, satellites and multilingual soldiers would not add up to an effective policy response to US unilateralism. Do Europeans propose to use military force against the US? Launch "pre-preventive" interventions? Or is the goal to reduce European dependency on Nato? If so, the result would be to encourage precisely the withdrawal from Europe advocated by US hawks. A European rapid reaction force might be useful for peacekeeping but neither it nor a larger force would reverse determined US unilateralism. The entire notion is in fact incoherent. Europeans have claimed from the start of the Iraq crisis that non-military means should be used more intensively. Yet when Washington sends in the marines, Europeans call for a stronger defence. The real problem is that European defence schemes distract Europe from its true comparative advantage in world politics: the cultivation of civilian and quasi-military power. Europe is the "quiet superpower". There are at least five ways in which Europe can wield influence over peace and war as great as that of the US. First, EU accession—perhaps the single most powerful policy instrument for peace and security in the world today. In 10-15 potential member states, authoritarian, intolerant or corrupt governments have recently lost elections to democratic, market-oriented coalitions held together by the promise of eventual EU membership. Second, Europeans provide more than 70 per cent of all civilian development assistance. This is four times more than the US and is far more equitably disbursed, often by multilateral organisations. When the shooting stopped in Kosovo and Afghanistan, it was the Europeans who were called on to rebuild, reconstruct and reform. Third, European troops, generally under multilateral auspices, help keep the peace in trouble spots as disparate as Guatemala and Eritrea. EU members and applicants contribute 10 times as many peacekeeping troops as the US. No one outside Washington believes US troops will be able to do the job after the Iraq war. Fourth, monitoring by international institutions, supported by Europe, builds the global trust that is needed to manage crises. The Iraq crisis might have developed very differently if the Europeans had been able to offer the option of sending, say, 10 times as many weapons inspectors in, 10 months earlier. Last, the Iraq crisis demonstrates the extraordinary effect of multilateral institutions on global opinion. In country after country, polls have shown that a second United Nations Security Council resolution would have given public opinion a 30-40 per cent swing towards military action. With the US stance apparently lacking international legitimacy, American troops have been unable to open a second front from Turkish territory; and the bill for the war is likely to fall largely to the US. Americans are not just unwilling but also—for complex domestic, cultural and institutional reasons—apparently unable to deploy civilian power effectively. That is the true weakness of US strategy today, for without trade, aid, peacekeeping, monitoring and legitimacy, no amount of unilateral military might can stabilise an unruly world. Rather than criticising US military power, or hankering after it, Europe would do better to invest its political and budgetary capital in a distinctive complement to it. European civilian power, if wielded shrewdly and more coherently, could be an effective and credible instrument of modern European statecraft, not just to compel compliance by smaller countries but perhaps even to induce greater American understanding. Europe might get its way more often—and without a bigger army.

The Right War at the Wrong Time - Putnam, Robert D. (Boston Globe, 2003)
President Bush used three main arguments to justify sending American troops into Iraq. The first tied Saddam Hussein to Al Qaeda, but the evidence that was presented publicly remained thin. Public opinion polls show that many Americans accepted the administration's word on the connection, but overseas responses were more skeptical. The second argument was that replacing Saddam Hussein with a democratic regime was a way to transform the politics of the Middle East. A number of neo-conservative members of the administration had urged this before taking office but were unable to turn it into policy during the first eight months of the administration. After Sept. 11, however, they quickly moved through the window of opportunity (even though North Korea posed a more imminent danger). President Bush spoke often of regime change. The plausibility of this argument was debated at home and abroad, and the merits probably lie somewhere between the proponents and skeptics. Our dedication to the broad values of democracy and human rights is part of our ''soft'' or attractive power and an essential part of our foreign policy. But democracy is a fragile plant that requires carefully cultivated soil. It is not easily transplanted. Of the places where the United States has sent troops in the last half-century, only a minority of the interventions resulted in democratic governments. Optimists cite the role of American military occupation in the democratization of Germany and Japan after World War II. But conditions in the Middle East today are not like Germany and Japan in 1945. Both of those countries had large middle classes, prior experience with democracy, and a prolonged and largely unopposed American military presence. Given its history and internal divisions, postwar Iraq is unlikely to look like democracy as we know it, but it will be a better and more pluralistic regime than now exists. American military success may lead Iran and Syria to temper their policies, but if President Bush is unable to persuade Israeli Prime Minister Ariel Sharon to reach a compromise acceptable to the Palestinians, the map of the region may change less dramatically than the optimists hope. The third argument was the clearest and most widely accepted. It focused on preventing Saddam Hussein from possessing weapons of mass destruction. Most countries agreed that Saddam had defied UN Security Council resolutions for a dozen years. Moreover, Resolution 1441 unanimously put the burden of proof on him to demonstrate what had happened to weapons that UN inspectors had been concerned about before they left Iraq in 1998. If President Bush had focused on this third argument and been willing to work out a compromise along the lines suggested by Canada, he could have built a far broader coalition for the war (Canada, and later Britain, suggested an agreement to give the UN inspectors more time in return for clear benchmarks and a date certain to declare the end of the process.) I believe France might have gone along, but even if it had used its veto, American actions would have been legitimized by a majority in the Security Council similar to that we enjoyed when we intervened in Kosovo in 1999. Unfortunately, the administration sent mixed messages. The more the unilateralists in the administration talked about regime change and going ahead no matter what the UN did, the more other countries became convinced we were not serious about cooperation, and the more the issue became the legitimacy of American power rather than the transgressions of Saddam Hussein. The result is the right war at the wrong time, but the point is now moot. Those of us who are critical of the clumsy handling and timing of the war must admit that indefinite containment was unlikely to succeed. Saddam Hussein had a record of taking high risks, a clear intention to develop weapons of mass destruction, and a proven willingness to use them. Enforcing Security Council Resolutions 687 and 1441 is better than returning to the evasive politics of the 1990s when Saddam Hussein successfully defied a divided United Nations. We multilateralists must now hope that the war is brief, that the Iraqi people will visibly welcome the removal of a tyrant, and that the reconstruction of Iraq will involve many countries and a United Nations role. Perhaps that will allow us to recover some of the legitimacy after the fact that the administration squandered before the war.

A Tory Plebiscite - Andrew Moravcsik (Prospect, 2003)
There would be something charming—quaintly reminiscent of Trollope perhaps—in the image of Britons "from pub landlords to vicars" forming a queue to vote in the Daily Mail "referendum" on the proposed EU constitution. Charming, that is, if it were not so corrosive of proper democratic debate. The current campaign for a referendum shows just what is wrong with plebiscitary democracy. It is a clever campaign because it uses and abuses two of the highest political values in the west: limited government and democracy. Limiting government by blocking activities of "foreign" institutions may seem prudent, yet it is impractical in an interdependent world. Plebiscitary democracy—politics by referendum—seems unimpeachably "democratic" on the surface, yet in fact it empowers the rich, the ignorant, the negative, and the ideological. Voters lack the time, commitment or expertise to engage fully in complex issues—particularly when, as in the case of the EU, their main concerns are not on the agenda. Referendums in the US have shown that under such circumstances, huge amounts of money, slick consultants and access to the media are required to win...

Move Yasser Arafat Up--Not Out - Kelman, Herbert C. (Boston Globe, 2003)
The Israeli security cabinet's decision to “remove” Palestinian Authority President Yasser Arafat is ominous. Though the stated justification for the decision is the assertion that Arafat is an obstacle to peace, it actually seems to be designed to ensure the failure of the peace process envisaged by the road map. This is not a time for passivity, subtlety, or ambiguity in Washington's response. Vehement US opposition to such a project is essential to averting reckless actions that are likely, at the very least, to set back the Israeli-Palestinian peace process for a long time to come. There is no Palestinian leader who would be able to negotiate a peace agreement in the wake of Arafat's expulsion. Worse yet, if the expulsion causes the death of Arafat and/or the deaths of Palestinians who gather to protect their leader, the likely result is a further escalation of violence, with disastrous consequences for both communities. Washington, unfortunately, prepared the ground for this dangerous turn of events by framing the appointment of Prime Minister Mahmoud Abbas (Abu Mazen) as another case of "regime change" in the Middle East—as the replacement of Arafat with Abu Mazen—and by shunning and seeking to isolate Arafat and pressuring European officials to break all contacts with him. This approach has compromised Abu Mazen's legitimacy in the eyes of the Palestinian population and seriously undermined his position. He came to be seen by many as a tool and accomplice in US efforts to reorder the Middle East and Israeli efforts to perpetuate the occupation. It also encouraged a power struggle between Abu Mazen and Arafat, who had an incentive to block some of Abu Mazen's initiatives in order to maintain his personal control. Defining Abu Mazen, and now his designated successor, Ahmed Qurei (Abu Ala), as replacements and rivals of Arafat, flies in the face of an important reality: Both men are long-term, close associates of Arafat and derive whatever domestic legitimacy they have and can potentially enhance from this association. Furthermore, the political strategy pursued by these two men—and, indeed, by all of the Palestinian leaders who have been committed to negotiating a historic compromise with Israel, in the form of a two-state solution—is ultimately the strategy of Arafat. Where Arafat's leadership has gone awry is in his tactics: his continuing embrace of the bankrupt idea that violence can be used as a bargaining tool; his unwillingness to share control and credit. The appeal of Abu Mazen and Abu Ala is that they are ready to advocate an end to violence and to engage in realistic negotiations in pursuit of the goal that Arafat has enunciated and persuaded the majority of the Palestinian population to accept: an independent Palestinian state in the West Bank and Gaza, with its capital in Jerusalem, in peaceful co-existence with the State of Israel. The irony of the situation is that, by the time of Abu Mazen's appointment as prime minister, there was growing dissatisfaction with Arafat's leadership—including, significantly, his inability to end the violence and advance the negotiations—within the Palestinian political elite and general population. The idea of appointing a prime minister was generated within the Palestinian community itself and represented a significant accomplishment under trying circumstances. US pressure no doubt contributed to Arafat's decision to accept his Legislative Council's recommendation. But by defining the action as a US-sponsored regime change, we were in effect saying to the Palestinian leadership: ”We will force you to appoint a new prime minister, even if you have independently decided to do so.” As a result, not only was the legitimacy of the new prime minister undermined, but Palestinians felt further humiliated because their elected president, the father of their nation, and the symbol of their collective identity was being denied the respect and dignity due to his status. Not surprisingly, Arafat's popularity has increased—and will increase even further if he is forcibly removed. With the designation of Abu Ala as the new prime minister, we have another chance to frame this political development constructively, in a way consistent with the intentions of the Palestinian reformers and the dignity of the Palestinian public. Far from removing Arafat or replacing him with the new prime minister, we should endorse a redefinition of the role of the Palestinian president. Arafat, as president, would become the head-of-state, occupying a position that is essentially ceremonial and symbolic (similar to the position of the president of Israel), while the prime minister would be the head-of-government, responsible for conducting the internal and external affairs of the Palestinian Authority, including internal security and peace negotiations. As head-of-state, Arafat would be treated with the full respect that is due to his office and would be recognized in his historical role as the symbol and father of the Palestinian people and its incipient state. There is no guarantee that, under such an arrangement, Arafat would readily abandon his life-long habit of maintaining personal control. But his incentive to cooperate with his prime minister would be greatly enhanced. Above all, the prime minister would start out with the domestic legitimacy that he needs to function effectively and would have the opportunity to enhance his legitimacy by pursuing a meaningful peace process and achieving positive changes in the daily lives of his constituency.

The Major Roadblock on Road Map to Peace - Kelman, Herbert C. (Boston Globe, 2003)
The Israeli settlements in the West Bank and Gaza present major obstacles on the road to Israeli-Palestinian peace. First, the presence of the settlements—along with the roads built to connect them and the troops deployed to protect them restricts Palestinians' freedom of movement, interferes with their livelihood, and generally makes their life unbearable. Second, the continued expansion of settlements even after the 1993 Oslo agreement has undermined Palestinians' trust in Israel's readiness to make peace: They ask why Israel continues settlement activities in territories slated for Israeli withdrawal and establishment of a Palestinian state. Third, the number and distribution of settlements may soon make it physically and politically impossible to create an independent, viable, and contiguous Palestinian state and thus put in place the two-state formula that is widely accepted today as the optimal solution to the conflict. The “road map” released by the State Department on behalf of the United States, the European Union, Russia, and the United Nations earlier this month recognizes the centrality of the settlements problem. It calls for immediate dismantlement of settlement outposts erected since March 2001 and a freeze of all settlement activity (including natural growth) in Phase I of the plan and further action on settlements in Phase II. Achievement of these goals will not be easy. Prime Minister Ariel Sharon, though acknowledging that Israel will have to make“painful concessions,” has given no indication so far of willingness to dismantle any settlement—even in Gaza or the West Bank's heartland. He has also insisted that he will not contemplate the steps on settlements mandated for Phase I of the road map until the Palestinian Authority puts an end to violence, even though the road map calls for simultaneous actions by both sides. It is unlikely that the Palestinian Authority, despite Prime Minister Mahmoud Abbas's clear stand against violence, can prevent all acts of violence to the satisfaction of Sharon. The irony is that Palestinian violence is most likely to lose public support and hence diminish if Abbas can demonstrate that his policies produce visible political benefits—such as halting settlement activities. Thus, making Israeli actions on settlements contingent on a total halt to Palestinian violence increases the probability that both violence and settlement activities will continue. Despite these difficulties, if the road map is to have any chance of success, the United States and its coauthors must exert pressure on the Israeli government to take immediate steps and make firm commitments on the issue of settlements—parallel to the steps and commitments on the issue of violence demanded of the Palestinian Authority. At the same time, however, we need to complement these pressures with positive incentives to reverse the settlement process that do not depend on the Israeli government. A creative idea along these lines is at the center of a campaign to “bring the settlers home” just launched by Brit Tzedek V'Shalom—the Jewish Alliance for Justice and Peace—which describes itself as—a national organization of American Jews deeply committed to Israel's well-being through the achievement of a negotiated settlement of the Israeli-Palestinian conflict.” The campaign's logic derives from the fact that a large majority of the settler population is not motivated by ideological or religious commitments to the settlement enterprise. Thus, in a recent poll of settlers, 80 percent said they moved to the territories to improve their quality of life, taking advantage of economic incentives offered by the Israeli government that enabled them to obtain better housing at a lower cost. The same poll revealed that 60 percent of the settlers were prepared to accept a withdrawal from the settlements in exchange for suitable financial compensation. The alliance's campaign calls on the US government: to urge the Israeli government to reverse its financial inducements to settlers and instead redirect these funds to settlers willing to return to Israel. to take the initiative in an international effort to provide financial incentives for the settlers to relocate, whether or not the Israeli government agrees to participate. An orderly move back by thousands of settlers would not in itself resolve the settlements issue, but it would greatly reduce its negative impact on the peace process and help to break the deadlock that is likely to stymie the road map. It would make it easier for the Israeli public to accept the major compromises on the settlements issue that a final agreement requires. It would give the Palestinian public a palpable sense that change is underway. It would create the momentum that is now so desperately needed.

The New Rome Meets the New Barbarians: How America Should Wield Its Power - Nye, Joseph S., Jr. (Economist, 2002)
Shortly after September 11th, President Bush's father observed that just as Pearl Harbor awakened this country from the notion that we could somehow avoid the call of duty to defend freedom in Europe and Asia in World War Two, so, too, should this most recent surprise attack erase the concept in some quarters that America can somehow go it alone in the fight against terrorism or in anything else for that matter. But America's allies have begun to wonder whether that is the lesson that has been learned - or whether the Afghanistan campaign's apparent success shows that unilateralism works just fine. The United States, that argument goes, is so dominant that it can largely afford to go it alone. It is true that no nation since Rome has loomed so large above the others, but even Rome eventually collapsed. Only a decade ago, the conventional wisdom lamented an America in decline. Bestseller lists featured books that described America's fall. Japan would soon become "Number One". That view was wrong at the time, and when I wrote "Bound to Lead" in 1989, I, like others, predicted the continuing rise of American power. But the new conventional wisdom that America is invincible is equally dangerous if it leads to a foreign policy that combines unilateralism, arrogance and parochialism. A number of adherents of "realist" international-relations theory have also expressed concern about America's staying-power. Throughout history, coalitions of countries have arisen to balance dominant powers, and the search for traditional shifts in the balance of power and new state challengers is well under way. Some see China as the new enemy; others envisage a Russia-China-India coalition as the threat. But even if China maintains high growth rates of 6% while the United States achieves only 2%, it will not equal the United States in income per head (measured in purchasing-power parity) until the last half of the century. Still others see a uniting Europe as a potential federation that will challenge the United States for primacy. But this forecast depends on a high degree of European political unity, and a low state of transatlantic relations. Although realists raise an important point about the levelling of power in the international arena, their quest for new cold-war-style challengers is largely barking up the wrong tree. They are ignoring deeper changes in the distribution and nature of power in the contemporary world. Three kinds of power At first glance, the disparity between American power and that of the rest of the world looks overwhelming. In terms of military power, the United States is the only country with both nuclear weapons and conventional forces with global reach. American military expenditures are greater than those of the next eight countries combined, and it leads in the information-based "revolution in military affairs". In economic size, America's 31% share of world product (at market prices) is equal to the next four countries combined (Japan, Germany, Britain and France). In terms of cultural prominence, the United States is far and away the number-one film and television exporter in the world. It also attracts the most foreign students each year to its colleges and universities. After the collapse of the Soviet Union, some analysts described the resulting world as uni-polar, others as multi-polar. Both are wrong, because each refers to a different dimension of power that can no longer be assumed to be homogenized by military dominance. Uni-polarity exaggerates the degree to which the United States is able to get the results it wants in some dimensions of world politics, but multi-polarity implies, wrongly, several roughly equal countries. Instead, power in a global information age is distributed among countries in a pattern that resembles a complex three-dimensional chess game. On the top chessboard, military power is largely uni-polar. To repeat, the United States is the only country with both intercontinental nuclear weapons and large state-of-the-art air, naval and ground forces capable of global deployment. But on the middle chessboard, economic power is multi-polar, with the United States, Europe and Japan representing two-thirds of world product, and with China's dramatic growth likely to make it the fourth big player. On this economic board, the United States is not a hegemon, and must often bargain as an equal with Europe. The bottom chessboard is the realm of transnational relations that cross borders outside government control. This realm includes actors as diverse as bankers electronically transferring sums larger than most national budgets at one extreme, and terrorists transferring weapons or hackers disrupting Internet operations at the other. On this bottom board, power is widely dispersed, and it makes no sense to speak of uni-polarity, multi-polarity or hegemony. Those who recommend a hegemonic American foreign policy based on such traditional descriptions of American power are relying on woefully inadequate analysis. When you are in a three-dimensional game, you will lose if you focus only on the top board and fail to notice the other boards and the vertical connections among them. A shrinking and merging world Because of its leading position in the information revolution and its past investment in traditional power resources, the United States will probably remain the world's most powerful single country well into this new century. While potential coalitions to check American power could be created, it is unlikely that they would become firm alliances unless the United States handles its hard coercive power in an overbearing unilateral manner that undermines its soft or attractive power—the important ability to get others to want what you want. As Josef Joffe, editor of Die Zeit, has written, "Unlike centuries past, when war was the great arbiter, today the most interesting types of power do not come out of the barrel of a gun." Today there is a much bigger payoff in "getting others to want what you want", and that has to do with cultural attraction and ideology, along with agenda-setting and economic incentives for co-operation. Soft power is particularly important in dealing with issues arising from the bottom chessboard of transnational relations. The real challenges to American power are coming on cat's feet in the night and, ironically, the temptation to unilateralism may ultimately weaken the United States. The contemporary information revolution and the globalization that goes with it are transforming and shrinking the world. At the beginning of this new century, these two forces have combined to increase American power. But, with time, technology will spread to other countries and peoples, and America's relative pre-eminence will diminish. For example, today the American twentieth of the global population represents more than half the Internet. In a decade or two, Chinese will probably be the dominant language of the Internet. It will not dethrone English as a lingua franca, but at some point in the future the Asian cyber-community and economy will loom larger than the American. Even more important, the information revolution is creating virtual communities and networks that cut across national borders. Transnational corporations and non-governmental actors (terrorists included) will play larger roles. Many of these organizations will have soft power of their own as they attract citizens into coalitions that cut across national boundaries. It is worth noting that, in the 1990s, a coalition based on NGOs created a landmines treaty against the opposition of the strongest bureaucracy in the strongest country. September 11th was a terrible symptom of the deeper changes that were already occurring in the world. Technology has been diffusing power away from governments, and empowering individuals and groups to play roles in world politics—including wreaking massive destruction—which were once reserved to governments. Privatization has been increasing, and terrorism is the privatization of war. Globalization is shrinking distance, and events in faraway places, like Afghanistan, can have a great impact on American lives. At the end of the cold war, many observers were haunted by the spectre of the return of American isolationism. But in addition to the historic debate between isolationists and internationalists, there was a split within the internationalist camp between unilateralists and multilateralists. Some, like the columnist Charles Krauthammer, urge a "new unilateralism" whereby the United States refuses to play the role of "docile international citizen" and unashamedly pursues its own ends. They speak of a uni-polar world because of America's unequalled military power. But military power alone cannot produce the outcomes Americans want on many of the issues that matter to their safety and prosperity. As an assistant secretary of defense in 1994-95, I would be the last to deny the importance of military security. It is like oxygen. Without it, all else pales. America's military power is essential to global stability and an essential part of the response to terrorism. But the metaphor of war should not blind us to the fact that suppressing terrorism will take years of patient, unspectacular civilian co-operation with other countries. The military success in Afghanistan dealt with the easiest part of the problem, and al-Qaeda retains cells in some 50 countries. Rather than proving the unilateralists' point, the partial nature of the success in Afghanistan illustrates the continuing need for co-operation. The perils of going alone The problem for Americans in the 21st century is that more and more things fall outside the control of even the most powerful state. Although the United States does well on the traditional measures, there is increasingly more going on in the world that those measures fail to capture. Under the influence of the information revolution and globalization, world politics is changing in a way that means Americans cannot achieve all their international goals by acting alone. For example, international financial stability is vital to the prosperity of Americans, but the United States needs the co-operation of others to ensure it. Global climate change too will affect Americans' quality of life, but the United States cannot manage the problem alone. And in a world where borders are becoming more porous to everything from drugs to infectious diseases to terrorism, America must mobilize international coalitions to address shared threats and challenges. The barbarian threat In light of these new circumstances, how should the only superpower guide its foreign policy in a global information age? Some Americans are tempted to believe that the United States could reduce its vulnerability if it withdrew troops, curtailed alliances and followed a more isolationist foreign policy. But isolationism would not remove the vulnerability. The terrorists who struck on September 11th were not only dedicated to reducing American power, but wanted to break down what America stands for. Even if the United States had a weaker foreign policy, such groups would resent the power of the American economy which would still reach well beyond its shores. American corporations and citizens represent global capitalism, which some see as anathema. Moreover, American popular culture has a global reach regardless of what the government does. There is no escaping the influence of Hollywood, CNN and the Internet. American films and television express freedom, individualism and change, but also sex and violence. Generally, the global reach of American culture helps to enhance America's soft power. But not, of course, with everyone. Individualism and liberties are attractive to many people but repulsive to some, particularly fundamentalists. American feminism, open sexuality and individual choices are profoundly subversive of patriarchal societies. But those hard nuggets of opposition are unlikely to catalyze broad hatred unless the United States abandons its values and pursues arrogant and overbearing policies that let the extremists appeal to the majority in the middle. On the other hand, those who look at the American preponderance, see an empire, and urge unilateralism, risk an arrogance that alienates America's friends. Granted, there are few pure multilateralists in practice, and multilateralism can be used by smaller states to tie the United States down like Gulliver among the Lilliputians, but this does not mean that a multilateral approach is not generally in America's interests. By embedding its policies in a multilateral framework, the United States can make its disproportionate power more legitimate and acceptable to others. No large power can afford to be purely multilateralist, but that should be the starting point for policy. And when that great power defines its national interests broadly to include global interests, some degree of unilateralism is more likely to be acceptable. Such an approach will be crucial to the longevity of American power. At the moment, the United States is unlikely to face a challenge to its pre-eminence from other states unless it acts so arrogantly that it helps the others to overcome their built-in limitations. The greater challenge for the United States will be to learn how to work with other countries to control more effectively the non-state actors that will increasingly share the stage with nation-states. How to control the bottom chessboard in a three-dimensional game, and how to make hard and soft power reinforce each other are the key foreign policy challenges. As Henry Kissinger has argued, the test of history for this generation of American leaders will be whether they can turn the current predominant power into an international consensus and widely-accepted norms that will be consistent with American values and interests as America's dominance ebbs later in the century. And that cannot be done unilaterally. Rome succumbed not to the rise of a new empire, but to internal decay and a death of a thousand cuts from various barbarian groups. While internal decay is always possible, none of the commonly cited trends seem to point strongly in that direction at this time. Moreover, to the extent it pays attention, the American public is often realistic about the limits of their country's power. Nearly two-thirds of those polled oppose, in principle, the United States acting alone overseas without the support of other countries. The American public seems to have an intuitive sense for soft power, even if the term is unfamiliar. On the other hand, it is harder to exclude the barbarians. The dramatically decreased cost of communication, the rise of transnational domains (including the Internet) that cut across borders, and the "democratization" of technology that puts massive destructive power into the hands of groups and individuals, all suggest dimensions that are historically new. In the last century, Hitler, Stalin and Mao needed the power of the state to wreak great evil. As the Hart-Rudman Commission on National Security observed last year, "Such men and women in the 21st century will be less bound than those of the 20th by the limits of the state, and less obliged to gain industrial capabilities in order to wreak havoc... Clearly the threshold for small groups or even individuals to inflict massive damage on those they take to be their enemies is falling dramatically." Since this is so, homeland defense takes on a new importance and a new meaning. If such groups were to obtain nuclear materials and produce a series of events involving great destruction or great disruption of society, American attitudes might change dramatically, though the direction of the change is difficult to predict. Faced with such a threat, a certain degree of unilateral action, such as the war in Afghanistan, is justified if it brings global benefits. After all, the British navy reduced the scourge of piracy well before international conventions were signed in the middle of the 19th century. Number one, but... The United States is well placed to remain the leading power in world politics well into the 21st century. This prognosis depends upon assumptions that can be spelled out. For example, it assumes that the American economy and society will remain robust and not decay; that the United States will maintain its military strength, but not become over-militarized; that Americans will not become so unilateral and arrogant in their strength that they squander the nation's considerable fund of soft power; that there will not be some catastrophic series of events that profoundly transforms American attitudes in an isolationist direction; and that Americans will define their national interest in a broad and far-sighted way that incorporates global interests. Each of these assumptions can be questioned, but they currently seem more plausible than their alternatives. If the assumptions hold, America will remain number one. But number one "ain't gonna be what it used to be." The information revolution, technological change and globalization will not replace the nation-state but will continue to complicate the actors and issues in world politics. The paradox of American power in the 21st century is that the largest power since Rome cannot achieve its objectives unilaterally in a global information age.

Three R'S for a new Afghanistan - Reddaway, David (Boston Globe, 2002)
New Crises elsewhere have replaced Afghanistan in the headlines, but this week is an important anniversary. A year ago on Thursday, Afghan leaders signed the Bonn Agreement, a roadmap to take Afghanistan from the wreckage of years of conflict toward democratic elections in 2004. So it is a good time to ask whether Afghanistan is still important to anyone but the Afghans and whether the Bonn roadmap is steering Afghanistan in the right direction. The answer to both questions is yes. Until the Taliban fell, Afghanistan gave haven to the world's most dangerous terrorists, who would be quick to return if coalition troops withdrew. They, the drug barons and the warlords, would plunge Afghanistan back into darkness. Sept. 11 showed why the world must work with the Afghans to prevent this and why we should commit ourselves to achieving a universally acceptable vision for Afghanistan: the establishment of a sovereign, stable, and secure country with a self-sustaining economy, strong institutions, and a broad-based, multiethnic regime committed to eradicating terrorism and opium production, reducing poverty, and honoring its international obligations - most notably the human rights of minority groups and women. These aspirations are undeniably ambitious. They should be more easily achievable if we apply three R's to Afghanistan. Not, in this case, the traditional reading, 'riting and 'rithmetic, but realism, respect, and resilience. Realism reminds us that Afghanistan cannot be magically transformed into a modern democracy. Progress toward anything like it will take time. Meanwhile, holding together the myriad Afghan groups means focusing on the essential and the achievable. This applies even to human rights. Those responsible for past atrocities should be called to account. But not yet. At this stage, Afghanistan's fragile consensus could not survive a comprehensive investigation of past excesses. Nor, realistically, can all the warlords simply be swept away. Instead, the immediate goal must be to draw them into greater dependence on the Kabul administration, with reconstruction aid for their fiefdoms made conditional on good behavior, and to find other work for their foot soldiers. In time, the nascent national army should outgun the private armies. Realism also suggests that those still calling for the deployment of large numbers of foreign troops to several Afghan cities should drop the idea. Static foreign garrisons would be expensive and vulnerable targets. The present "light footprint" system, backed by the threat of US air power, has worked well. Developments on that theme, not garrisons, can best help keep the peace in the provinces. Respect means remembering that Afghanistan belongs to the Afghans. Building Afghan capacity must underpin everything we do. Hence the need to nurture viable Afghan institutions, drawing on Afghanistan's cultural and religious heritage. Hence, too, the importance of eradicating opium production and providing alternative livelihoods for farmers. If the rule of law does not prevail, Afghanistan—and we—will fail. Resilience, in terms of commitment and stamina, will be needed to overcome the many daunting challenges we will continue to face. The international community moved Afghanistan from the top of the "in" basket to the "too difficult" basket after the Soviet occupiers left. Warlords, Taliban, and Al Qaeda took advantage. Whatever difficulties and distractions surface now, we must not snatch defeat from victory by abandoning the Afghans again. The solutions we develop must also be resilient. Regional neighbors like Pakistan and Iran now tacitly accept the unacceptable—the presence of Western forces—to underwrite peace in Afghanistan. The West, in turn, must accept that Afghanistan's neighbors should be involved in finding solutions, not dismissed as part of the problem. An imperial outpost in Afghanistan in the face of regional hostility isn't a long-term solution. Ask the British. Ask the Russians. The Afghans and the international community can be proud of what has been achieved in Afghanistan in the last year, with progress in bringing relative stability and normality to daily life, delivering humanitarian aid, providing education and health care, and removing land mines. The return of so many refugees testifies to that success. But Afghanistan is still fragile, and nobody can be complacent about the size of the task ahead. Realism, respect, and resilience are three essential tools if we are to do the job right. It is in our own interests, as well as those of the Afghans, that we should.

African Famine, Made in Europe - Paarlberg, Robert L. (Wall Street Journal, 2002)
Southern Africa is suffering its worst drought in a decade. The U.N. World Food Program estimates some 13 million people in six countries will need 1.2 million tons of food aid till March 2003 to avoid famine. Yet two countries, Zimbabwe and Zambia, have spent most of the summer rejecting food aid shipments of corn from the U.S. because some varieties of U.S. corn are "genetically modified" (GM). Incredibly, African leaders facing famine are rejecting perfectly safe food. What is going on here? Regulatory Authorities   Farmers in the U.S. have been planting (and Americans have been consuming) genetically engineered corn, soybeans and cotton since 1995. Regulatory authorities in the EU and Japan have also approved such GM crops, but in Europe food safety regulators have been mistrusted by consumers ever since the unrelated but traumatizing mad cow disease crisis of 1996. EU Commissioner for Health and Consumer Affairs David Byrne repeatedly states there is no scientific evidence of added risk to human health or the environment from any of the GM products approved for the market so far, and he can point to 81 separate scientific studies, all EU-funded, that bolster this conclusion. But greens and GM critics in Europe say this absence of expected or known risks is no longer a sufficient regulatory standard. Touting the "precautionary principle," they argue that powerful new technologies should be kept under wraps until tested for unexpected or unknown risks as well. Never mind that testing for something unknown is logically impossible (the only way to avoid a completely unknown risk is never to do anything for the first time). Europeans can perhaps afford hyper-caution regarding new crop technologies. Even without planting any GM seeds, European farmers will continue to prosper—thanks to lavish subsidies—and consumers will remain well fed. The same is not true in the developing world, especially in Africa, where hunger is worsening in part because farmers are not yet productive. Two-thirds of all Africans are farmers, most are women, and they are poor and hungry in part because they lack improved crop technologies to battle against drought, poor soil fertility, crop disease, weeds and endemic insect problems. The productivity of African agriculture, per farm worker, has actually declined by 9% over the past two decades, which helps explain why one-third of all Africans are malnourished. This ought to change the calculus of precaution. If GM-improved crops are kept out of the hands of African farmers, pending tests for the "nth" hypothetical risk, or the "nth" year of exposure to that risk, the misery of millions will be needlessly prolonged. But now we are seeing an even less justified application of regulatory caution toward GM foods. Governments in Africa that are facing an actual famine have been rejecting some food aid shipments because they contain GM seeds. In May 2002, the government of Robert Mugabe in Zimbabwe rejected 10,000 tons of corn shipped from the U.S. because it was not certified as GM-free. This at a time when four to six million Zimbabweans approached a risk of starvation. Next, the government of Zambia banned all imports of GM corn, including food-aid imports, even though some 2.3 million people in the country were at risk. On Aug. 16, Zambian Information Minister Newstead Zimba announced on state TV that the government had decided, in light of the uncertainties surrounding GM foods, that it would be best to "take the precautionary principle on this matter" and not accept or distribute GM food aid. Silumelume Mubukwanu, Zambia`s High Commissioner to London, explained that food aid was being rejected because "too much is unknown about GM foods yet." Precautionary European policies toward the environment are also keeping Africans from growing their own food. The EU has been insisting that governments in Africa treat GM crops as a potentially serious threat to rural "biological safety." This helps explain why there are no GM crops yet being planted commercially anywhere on the continent, except in the nation of South Africa. Instead of helping Africa`s hungry to grow more food, European donors are helping them grow more regulations. African governments also must worry that accepting GM food aid will cost them commercial export sales to Europe. The EU has not been importing any U.S. corn since 1998, because U.S. shipments can contain some GM varieties not yet approved in Europe. African governments now worry that any illicit planting of U.S. corn by farmers could jeopardize their own exports to Europe. Trying to remain GM-free for commercial export reasons is a policy that does not help poor subsistence farmers, but it may soon become the norm in Africa, once the EU moves next year toward much tighter labeling and traceability regulations on all imported GM foods and animal feeds. Documentary Records Even while professing that GM foods are safe, EU officials will soon require that they be traced individually through the marketing chain, with legal documentary records to be saved by all producers and handlers for five years. African countries won't have the institutional capacity to implement this traceability regulation, so they will have to remain GM-free to retain their access to the EU market. Meat products raised with GM feed are not yet covered by this new EU regulation, but Zambia's initial rejection of GM corn in food aid shipments was partly based on a fear that if the country lost its GM-free animal feed status, poultry and dairy exports to the UK would slump. By inducing African governments to embrace excessively cautious biosafety regulations and by requiring stigmatizing labels and costly traceability certificates for all imported GM foods and feeds, wealthy and comfortable officials in Europe have made it harder for drought-stricken societies in Africa to accept food aid from the U.S. European critics of GM foods did not foresee this potentially deadly misapplication of their precautionary principle. Yet here it is.

Is Bush Provoking an Attack? - Allison, Graham T., Jr. (Boston Globe, 2002)
Ranchers have learned painfully the wisdom of the maxim: when pursuing deadly rattlesnakes, don't provoke the fatal attack you are aiming to prevent. Does the Bush administration's chosen strategy of publicized preemption risk violating that prescription? President George W. Bush believes not. In this week's address to the nation, the essence of his argument for acting now is that we must hit Saddam before he hits us. Unless we take preemptive action to disarm Iraq and eliminate Saddam, he argued "on any given morning," Saddam could surprise us with a chemical or biological 9/11. The nation's best intelligence analysts disagree. As the latest National Intelligence Estimate, declassified this week, states unequivocally: in the absence of a US attack, the likelihood of Saddam attacking us with chemical and biological weapons in the foreseeable future is "low." On the other hand, if Saddam becomes convinced that we really are about to attack him to topple his regime, intelligence analysts conclude the likelihood that he would attack us with chemical or biological weapons is "high." In sum: to prevent an attack the likelihood of which is low, the US is taking action that makes the likelihood of that attack high. Which of these conflicting judgments seems more likely to be correct: the president's or the intelligence community's? Since the competing bets are driven by strategic logic, not secret information, let us consider the question. Bush presented the basic facts clearly in Monday's address. We know that Saddam has chemical and biological weapons including "anthrax and other deadly biological agents*mdash;capable of killing millions." We know that Iraq has "a growing fleet of manned and unmanned aerial vehicles that could be used to disperse chemical or biological weapons across broad areas." We know that he "is exploring ways of using these UAV's for missions targeting the United States." We know that "a small container and one terrorist or Iraqi intelligence operative could deliver" biological agents to an American city. We know that those who hate America would be "eager to use biological or chemical or nuclear weapons." Thus "we have an urgent duty to prevent the worst from occurring." The issue remains how best to prevent the worst from occurring. On the current path, for more than a year the Bush administration has broadcast its firm intention to change the regime in Iraq: to kill Saddam and everything he holds dear. Currently, the US is positioning military forces in the region in preparation for such an attack. A congressional resolution authorizing the president to take "all necessary means" has been passed. Shortly thereafter, a Security Council resolution authorizing intrusive inspections and, after Saddam stiffs inspectors, permitting a US-led military attack to disarm Iraq seems assured. Given this picture, what do we imagine Saddam is now planning for us? Given Bush's summary of Saddam's character (evil), his history (homicidal), and his intentions (ruthlessly hostile), is he likely to go down with a whimper—or a bang? Will he attack Americans here at home? Has he already dispatched operatives to American cities with biological weapons like smallpox? Will he attack Israel with biological weapons? Will he infect bases in the region where American troops are preparing to launch an attack upon him? If Saddam's overriding objective is his own survival, as we launch, or finalize plans to launch, an attack that threatens to extinguish him, is there any reason to expect him to do less than his best to kill as many Americans as possible? If the evidence the president cites is correct, the logic of the snake hunter's maxim would appear to lead inexorably to the National Intelligence Estimate's conclusion: "Conducting a WMD attack against the United States would be his last chance to exact vengeance by taking a large number of victims with him." Therefore, what to do? If one finds a pair of rattlesnakes in his backyard, backing off and hoping they slink away is not the answer. Nonetheless, prudence requires that before attacking a coiled rattler that has no escape route, we are as prepared as we can be to blunt its strike. President Bush asked: "Does it make any sense for the world to wait to confront him as he grows even stronger and develops even more dangerous weapons?" The answer is: it depends. Specifically, it depends on whether his offensive capabilities to harm us are growing faster than our capabilities to defend ourselves against the counterattack our action may provoke. Before taking action that will likely provoke the very attack we seek to prevent, Bush should assure Americans that our troops in the field and citizens here at home are prepared for the biological and chemical attacks the country's best intelligence analysts judge to be "likely." Have you gotten your anthrax and smallpox vaccinations yet?

Defeating Desperate Dictators - Rosen, Stephen Peter (Wall Street Journal, 2002)
How can the United States conduct a war to remove Saddam Hussein from power if Saddam Hussein has weapons of mass destruction and the means to deliver them? Senator Edward Kennedy, echoing the standard views of political scientists, has questioned the wisdom of pursuing regime change in Iraq by military means. If a war to remove him is going well, the argument goes, Saddam will see that he, personally, is doomed, and will decide that he might as well inflict as much pain as he can on his enemies before he dies. The logic of pure reason says that you cannot deter a leader who has nothing to lose. There are several things wrong this argument. The first is history. This is not the first time a war has been waged to effect regime change against a leader who had weapons of mass destruction. Adolf Hitler’s Third Reich had stockpiles of nerve gas and a weakened but still effective military chain of command to execute his orders. But when the Red Army was entering Berlin, there were no clouds of Sarin or Tabun unleashed against the Soviet soldiers who would, without doubt, deal out the roughest kind of justice to Germany and Hitler himself. Not only that, but earlier in the war, Hitler’s orders to destroy Paris as the Germans withdrew were not obeyed. As German defeat became more certain, even the killings of Jews and others in the death camps were halted, at least for some periods of time. Tyrants do not commit mass murder with their own hands. They have subjects who carry out their commands. Tyrants are obeyed because they are feared, and go to great lengths to ensure that their subjects fear them more than they fear the external enemies of the regime. But when they begin to lose a total war, the balance of fear among those they have been oppressing begins to shift. People begin looking around them to see if it is safe to turn their coats, defect, or mutiny. If one prominent subordinate successfully disobeys orders, others learn the lesson and act accordingly, creating a cascade of increasing numbers of defections. This is why dictatorships that seem so solid can so rapidly fall apart when the first cracks in the regime become publicly visible. In a regime guilty of crimes against humanity, subordinates will not want to be taken prisoner while in the act of committing mass murder, defending a tyrant who is on the verge of total defeat. Logically, this suggests that tyrants might unleash their stockpiles of weapons of mass destruction before it is obvious to their subordinates that they will be overthrown. If Saddam Hussein saw the inevitable coming early enough, he could order his remaining SCUDs loaded with biological weapons and launched against Israel, by generals who still feared him more than the American armies that might falter before they got to Baghdad. This overlooks another major characteristics of tyrants. They tend to have hefty amounts of self-confidence. They have, after, all gained and held absolute power against all comers. They have survived attempts to kill or defeat them. They have difficulty believing that they can lose. Hitler, when hearing of the death of Franklin Roosevelt in April of 1945 cheered himself up with the thought that, like Frederick the Great, he would still pull through because a key adversary had died. In addition, tyrants are not surrounded by people who bring them down to earth. All the evidence we have from the Hitler, Stalin, and Mao regimes shows that their subordinates did not present, but rather concealed, information that revealed the ongoing failure of policies ordered by the tyrant. The subordinates of the tyrant know, long before the tyrant is forced to believe, that the game is up. The idea that men like Saddam Hussein will believe that they are doomed, and order apocalyptic action before the very last moment, is to ignore everything we know about the most basic part of their personalities. If what is written above is correct, there are some clear policy implications for the United States as it plans its war against Saddam Hussein. First, we should say, publicly and often, that Iraqi commanders who commit mass murder will be found and executed, and that those who forbear will be treated mercifully. We should state publicly that we know that Saddam Hussein has given his commanders operational control of chemical and biological weapons, so that if the weapons are used, it is because of the actions of local commanders, who will be held accountable. We should state, finally, that the war will be waged to destroy Saddam Hussein’s secret police, so that military commanders will not have the excuse that they were acting under compulsion. If nothing else, this is sure to initiate a round of purges by Saddam Hussein of his military before the war starts that will weaken it, just as the Red Army was weakened in the years before World War II. When the war starts, inducing senior Iraqi military defections will be an objective as important as gaining territory or destroying Iraqi SCUDs, and the news of the defections should be broadcast continuously back into Iraq. Second, the first American military actions should be massive. Saddam Hussein’s command structure and military capabilities should be hit as hard as possible with air and ground forces in the first days of the war, while he still believes that he will dodge the bullet with his name on it one more time. By the time he realizes that he is history, there should be as little possible left of his military and security structure. This will require a war very different from the war we recently waged in Afghanistan, in which logistical and legal considerations led to a tempo of war that built slowly to a climax. It should be even more different from the 1991 war in which the air campaign was waged for weeks before the ground campaign began. It should be a new form of lightning war, the purpose of which is to shock and paralyze the enemy leadership with air strikes, special forces, helicopter air assaults, and whatever special devices have been invented over the last year. It should be augmented by and coordinated with Israeli military action. The problems associated with attacking a tyrant with weapons of mass destruction are real, but not insuperable. They do require new modes of military thought and action. And they will be even larger in a few years time if we do not act now.

El Futuro de la Política Exterior de Estados Unidos - Hidalgo, Diego (El País, 2002)
Reconociendo las dificultades para analizar una situación mundial cada vez más compleja, Mijaíl Gorbachov y yo tratamos de identificar hace apenas un año los principales problemas con los que parecía enfrentarse la humanidad en los albores del siglo XXI. Dejando aparte los medioambientales y el avance del sida y otras enfermedades infecciosas, dos problemas destacaban entre todos: la pobreza y desigualdad crecientes y el hecho de que la tercera ola democrática se hubiera detenido. Los acontecimientos desde el 11 de septiembre de 2001 han añadido tres problemas más, relacionados con los anteriores. El primero, evidente, es que han aumentado las sensaciones de inseguridad e incertidumbre. Muchas de las certezas que un ciudadano de cualquier país del mundo tenía entonces se han convertido en incógnitas que nos preocupan, angustian o aterran, y que nos hace temer con fundamento que el mundo en el que vivirán nuestros hijos y nietos será mucho más difícil y, desde luego, peor que el nuestro. El segundo, que añadió el presidente Clinton a mi lista, es "el círculo vicioso que existe en la mayoría de países musulmanes en Oriente Próximo y el Magreb": la escasa educación que reciben las mujeres lleva a tasas elevadas de natalidad, y éstas, a que un porcentaje demasiado elevado de la población sea de niños con escasas posibilidades de integrarse dignamente en la sociedad al llegar a la edad adulta. La mitad femenina de estos niños apenas recibe educación, mientras que la masculina la recibe sólo de organizaciones islámicas que imparten una versión intransigente del Corán. Clinton recordaba que un niño paquistaní de diez años, guapo y de voz dulce, que sabía el Corán de memoria, declaraba que su mayor felicidad cuando fuera mayor sería morir matando a todos los americanos que pudiera. El presidente Clinton opina que este problema, unido a los de la pobreza y crisis democrática, es el principal responsable de la emergencia del terrorismo y la inseguridad. Hay un tercer problema, que añado a los anteriores, y que podría simplificarse como el de un unilateralismo creciente de Estados Unidos. La lista de temas importantes con grandes diferencias de posición entre su Gobierno y el resto del mundo (como Oriente Próximo, América Latina, la Corte Penal Internacional, el Convenio de Kioto, el sistema antimisiles, el proteccionismo a su sector siderúrgico, su casi nula ayuda externa, etc.) crece aceleradamente; pero estas discrepancias, lejos de incitar a Estados Unidos a reexaminar sus posturas, van acompañadas por una arrogancia cada vez mayor. Creo que los estadounidenses tienen dificultades para ver que la falta de un contrapeso a su poder hegemónico, que no tiene precedentes históricos, y el escaso interés de sus electores por todo lo que ocurre más allá de sus fronteras les está llevando a una política exterior que en lugar de ganar corazones y voluntades en el mundo los está alienando. Hace dos semanas, el Weatherhead Center for International Affairs, de la Universidad de Harvard, organizó en Talloires, junto al lago de Annecy, una conferencia titulada El futuro de la política exterior de los Estados Unidos. La política del WCFIA de impedir la atribución de las opiniones a los participantes, acertada para estimular su libertad y espontaneidad, me obliga a no hacer citas. Sin embargo, puedo asegurar que la conferencia reunió a unos treinta de los mejores especialistas en relaciones internacionales procedentes de unos veinte países, entre ellos a varios profesores norteamericanos, algunos de ellos demócratas y otros próximos a la Administración de Bush. Creo poder afirmar que casi todos los europeos y asiáticos, y espero que algunos americanos, salimos de Talloires extraordinariamente preocupados por las exposiciones que hicieron personas próximas a la mentalidad del Gobierno de Estados Unidos. La discusión en la conferencia estuvo dominada por dos análisis, actitudes y predicciones contrapuestas: a) una autoproclamada imperialista, que considera legítimo el intervencionismo de Estados Unidos en cualquier situación de amenaza; b) otra (offshore balancer) aislacionista, que postula que Estados Unidos no debe intervenir, sino enfrentar una contra otra a potencias regionales para que se controlen o eliminen entre sí (ejemplos, Irán contra Irak, India contra Pakistán, China contra Rusia o contra Japón). Ambas posturas son unilateralistas; están basadas en la aplastante superioridad militar de Estados Unidos y ninguna considera necesario ningún tipo de coalición o consenso internacional, ni la participación de un organismo multilateral como las Naciones Unidas, ni siquiera la aquiescencia previa de la Unión Europea y de otros antiguos aliados de Estados Unidos, a quienes se considera irrelevantes. La postura imperialista ha acogido con entusiasmo los discursos del presidente Bush, que, tras la reacción moderada inmediatamente después del 11 de septiembre, han crecido en belicosidad a lo largo de 2002; al del Eje del Mal del Estado de la Unión ha sucedido el reciente de West Point, en el que Bush considera un error esperar a que las amenazas militares o terroristas se materialicen y considera legítimo el derecho a iniciar ataques y guerras preventivas. La doctrina de la necesidad de efectivos militares se puede resumir en un "4+2+1". El 4 representa el número de lugares en los que Estados Unidos debe ser capaz de ejercer su poder disuasivo. El 2 representa el número de guerras simultáneas (por ejemplo, Irak y Corea del Norte), y el 1, la capacidad de Estados Unidos de forzar un cambio de régimen, lo cual presupone la necesidad de ocupar ese país por un ejército terrestre. Naturalmente, esta postura defiende incrementos presupuestarios importantes en un momento en el que el superávit se ha convertido en serio déficit y en una coyuntura económica desfavorable. La postura aislacionista tiene tres premisas basadas en la vieja doctrina de Monroe, que ha regido la política exterior de Estados Unidos durante más de siglo y medio. Estados Unidos debe a) establecer su hegemonía regional en las Américas, b) vigilar para que ninguna potencia domine de igual manera en Europa o en Asia y c) tratar con esas potencias rivales sólo si otras demuestran ser incapaces de controlarlas. Por ejemplo, es esencial que ninguna potencia local (Irán o Irak) predomine en el golfo Pérsico amenazando el acceso al petróleo de la zona. "A los americanos no les gusta perder vidas". EE UU debe intervenir sólo en caso de extrema necesidad: la amenaza directa de una potencia rival. Mis reflexiones durante esta discusión entre dos posturas "alucinantes", que dirían mis hijos, pero "realistas" y reales, me llevaron a varias observaciones y conclusiones. Primero, tras el 11-S cabían dos preguntas: 1) ¿quién nos ha hecho esto?, y 2) ¿por qué? Plantear sólo la primera conduce a la paranoia, y sólo la segunda lleva a las verdaderas causas—es decir, a los problemas enumerados al principio de este artículo—y supone un paso hacia las soluciones. Mi temor es que muchos analistas se han quedado en la primera pregunta. No analizar las causas que llevan a personas a morir matando por una causa y creer que el problema se puede solucionar por métodos militares es ignorar las lecciones de la historia. Segundo, fue muy revelador que en una conferencia sobre política exterior se hablara exclusivamente de intereses, temas militares y de seguridad, y en ningún momento de valores, solidaridad, ayuda, apertura de mercados, diplomacia y paz. Tercero, América Latina y África no fueron tema de discusión. Igual que noviembre de 1989, fecha de la caída del muro de Berlín, supuso la marginalización definitiva para África, el 11 de septiembre lo ha supuesto para América Latina. Por último, los europeos y asiáticos y algunos de los americanos alejados del poder proclamamos nuestra preocupación. Casi todos opinamos que un Estados Unidos aislacionista es más peligroso que uno intervencionista. En todo caso, el predominio de intereses sobre valores, de temas militares sobre económicos y diplomáticos, de Rumsfeld sobre Powell, de la guerra sobre la paz, indica un divorcio creciente entre Europa y EE.UU. La hora del diálogo entre ambos ha sonado y es, sin embargo, más difícil que nunca. Diego Hidalgo is a former CFIA Fellow, 1994-1995. He was a Division Chief for Africa at the World Bank (1968-1977), President of FRIDA (1978-1983) and Alianza Editorial in Spain (1983-89) as well as cofounder of EL PAIS.

Lessons from Afghanistan - Nye, Joseph S., Jr. (Boston Globe, 2002)
The battle in east Afghanistan is winding down, and President Bush has offered to train other governments for the second stage in the war on terrorism. Though the American military officials assure us that much remains to be done in Afghanistan, the lessons of the campaign are already being drawn. And, before they become engraved in conventional wisdom, we should distinguish the accurate lessons from the misleading ones. Most important, in an age of globalization, the United States cannot ignore problems in distant regions. During the Cold War, we thought Afghanistan important enough to support its struggle against the Soviet invasion. During the 1990s, to the extent that we noticed the deteriorating conditions, we felt it was not our affair. Yet we learned on Sept. 11 that events in poor countries half way around the world can do us great harm. Our military success in Afghanistan has shown clearly to any state ready to support terrorism that this is no longer a safe option. Terrorism is to this century what piracy was to an earlier era when some governments gave pirates and privateers safe harbor to earn revenues or harass their enemies. In this era, some states have harbored terrorists in order to attack their enemies or because they were too weak to control powerful fanatical groups. For too long our country simply looked the other way on the mistaken assumption that such alliances would have little world consequence. The United States and its allies must consistently condemn state support for terrorism and use the stick of the Afghanistan campaign to demonstrate the consequences that can befall these states. The success to date in Afghanistan also shows that force can be used effectively and with discrimination even in difficult settings. Although there were civilian casualties, the combination of US Special Forces on the ground and precision air power proved to be a powerful one. On the other hand, we would be mistaken if we concluded that the Afghanistan formula can fit all sizes and situations. The Northern Alliance provided important proxy forces already on the scene, and without them, air power would not have been sufficient. Indeed, some military critics believe that the United States failure to insert more of its own ground forces led to the failure to capture Al Qaeda fighters in the battle of the Tora Bora caves. We also have to realize that the last act in Afghanistan is far from over, and more outside forces will be needed to keep the peace if our success is not to erode. Perhaps the most dangerous lesson learned is by those in the administration and outside commentators who believe that Afghanistan shows that unilateralism works. It is true that the United States accomplished the military tasks with little help from allies except Pakistan, Uzbekistan, and Britain. But the lesson is misleading because it implies that there is a purely military solution to the war on terrorism. According to the CIA, while the fighting in Afghanistan toppled the Taliban government, it killed or captured less than a quarter to a third of the Al Qaeda network. The military success in Afghanistan dealt with the tip of the iceberg of terrorist threats. Al Qaeda retains cells in some 50 countries, few susceptible to military solutions. We are not about to bomb Rome, Hamburg, or Jakarta. And Al Qaeda is not the only transnational terrorist organization. Suppressing terrorism will take years of patient international civilian cooperation involving intelligence sharing, police work, tracing financial flows, customs and immigration. Rather than proving the unilateralists' point, the partial success in Afghanistan illustrates the continuing need for international cooperation. Sept. 11 was a terrible symptom of deeper changes occurring in the world. Technology has been diffusing power away from governments and empowering individuals and groups. With the use of desktop computers and the Internet, terrorist networks can now exchange high-tech secrets and coordinate complex campaigns across continents that only governments could conduct 20 years ago. Privatization has been increasing, and terrorism is the privatization of war. Nor is terrorism the only issue. Many other important problems that can cause great harm&madash;such as international financial instability, global climate change, or the spread of diseases—are inherently multilateral. The ultimate lesson of Afghanistan is that the United States is so large that these crucial problems cannot be solved without us, but we are not large enough to solve them alone.

Pious Words Won't Heal the Hurt - McTernan, Oliver (Times, 2002)
A former priest, Oliver McTernan, explains why American Catholics feel betrayed by the Church The fact that Pope John Paul II has chosen to meet only cardinals today, many of whom are themselves subject to public criticism for their mishandling of the sex abuse scandals traumatising the American Roman Catholic Church, highlights one of the real issues at the centre of this crisis. The absence of victims, laity and priests, all of whom have been affected by the unfolding scandal, suggests that, for the Vatican, this meeting is no more than a crisis-management session aimed at damage limitation and deflecting further criticism at its moral ineptness to deal with a serious problem that has beleaguered the Catholic Church globally for decades. If Vatican officials believe that a few pious exhortations and a new set of policy guidelines on how to handle future child-abusing clerics will allow the Church to continue with its existing style of governance, they have clearly failed to understand the depth of hurt and anger that is felt not only by the victims of abuse who have come forward, but also by conservative and progressive Catholics in America who feel equally betrayed by a church leadership that has gone to such extraordinary lengths to cover up the crimes of paedophile priests. The relentless media coverage over the past four months has exposed a culture of denial among bishops and priests that has caused as much scandal as the sex abuse itself. Many Americans are questioning not only the credibility of those responsible for the cover-ups, the buying of silence and the moving of offenders, but also the very church structures that allow bishops to act as if they are outside the law and accountable to no one for their moral decisions and their use of church funds. People and priests are openly calling for a place at the table and a voice that is heard if the broken trust between them and their bishops is to be restored. In the Boston Archdiocese, what began a few weeks ago as a small, ad hoc gathering of concerned priests now has more than 100 members who are committed to working together to promote a new style of church leadership. Six months ago, such an initiative would have been unthinkable because Cardinal Bernard Law, who is at the centre of the current crisis, would immediately have prohibited it. The Pope's first public response to this scandal was to scapegoat the victimisers, the paedophile priests whom he accused of casting a shadow over the whole Church. The fact that he did not acknowledge, let alone condemn, the culture of denial lying at the heart of the problem makes one wonder whether those around him, including his American visitors, are capable of grasping the potential seriousness of this crisis for the Church as a whole. The problem of paedophile priests and bishops covering their tracks for the "good of the Church" is not exclusive to the US, nor is the unfolding drama that we are witnessing now on the Vatican stage of a clash between Roman and American cultures. The cardinals sitting in conference with the Pope and his advisers are one-minded on matters of church doctrine and discipline; otherwise they would not have been appointed to the positions they now occupy. The real clash that this present crisis exposes is one of theology. It is part of the unfinished business of the Second Vatican Council of the early 1960s, which left us with two equally valid, but competing, models or images of what the Church should be. One is a hierarchical structure governed by the Pope and his appointees, the bishops;the other the pilgrim people of God, each of equal standing as they gather around the Eucharistic table. In the immediate aftermath of the council people were encouraged to explore the wonder and mystery of being part of a Church that was not locked within the cultural and legal structures of previous centuries. John Paul II's papacy began with a sense of renewed excitement, but it soon evaporated as the Vatican's efforts to micromanage the life of the local churches became more obvious. The Pope replaced the bishops who had spearheaded the reforms of Vatican II with men who felt more comfortable operating in an exclusively hierarchical model of Church. What we are seeing now is the unravelling of this counter-reform movement, as it is clear that some of these trusted appointees have feet of clay.

U.S. Must Help Argentina Recover - Domínguez, Jorge I.; Levitsky, Steven (Miami Herald, 2002)
The Bush administration, like its two predecessors, has expressed strong support for democracy in the Americas. It is now time to put its money where its mouth is. Argentina's story in the 1990s was, in many respects, exactly what the United States would like to see happen throughout the hemisphere. The country has been a democracy since 1983, its longest span of constitutional government since the 1920s. It has undergone a major foreign policy shift. Argentina resolved territorial disputes that once brought it to the edge of war with its neighbors, dismantled programs that could have led to the development of nuclear weapons, downsized its armed forces and became one of the most reliable U.S. allies in Latin America. Poster Child Argentina also became a poster child for market-oriented economic reform in the 1990s. The 1991 Convertibility Law, which pegged the Argentine peso to the dollar at a one-to-one rate, ended a devastating period of hyperinflation and helped to reintegrate Argentina into the global economy. The first Bush administration was a key ally in this process, supporting Argentina politically and financially. Yet today Argentina is bankrupt, and its hard-won democracy is in danger. Mass riots and looting left at least two dozen people dead and forced President Fernando de la Rúa to resign in December. After more riots last weekend, Adolfo Rodríguez Saá also resigned a week after being appointed interim president. A nearly four-year-long recession has pushed the unemployment rate to almost 20 percent and, according to one study, more than three million people into poverty in the last year alone. Argentina now stands on the brink of a huge debt default and a political meltdown. The causes of the current crisis are disputed, but most observers agree that the same convertibility scheme that had ended the hyperinflationary crisis a decade ago left Argentine governments without instruments to respond to the recession that hit the country in the wake of the 1997 Asian financial crisis. Unable to increase the money supply or devalue the currency, governments were left only with fiscal policy instruments. The de la Rúa government was also shackled by its $132 billion debt burden. Rather than boosting the economy through a fiscal or monetary stimulus, as governments normally do, Argentine governments did the opposite in their increasingly desperate effort to sustain international financial credibility: They cut spending in the face of recession and refused to dismantle the currency peg that once ended hyperinflation. The recession deepened, unemployment soared, poverty widened and tax revenues plummeted. No Easy Way Out There is no easy way out of this crisis. Indeed, any interim government will have to undertake one or both of the two Ds that its predecessor desperately sought to avoid: default and devaluation. Both options will entail massive economic and political costs. This is where the Bush administration can help. Argentina's successful economic adjustment requires approximately $50 billion in international support for its evolving international-debt and exchange-rate policies, consistent with its economic realities and its international financial obligations. That large sum can be assembled only with the direct, active and immediate support of the Bush administration, working with the International Monetary Fund and other governments and public and private financial institutions. One reason to assemble the large sum is to deter a worse panic. Why should the U.S. government help soften Argentina's difficult landing? During the 1990s, Republican and Democratic administrations actively pursued the twin goals of democracy and economic integration in the Americas. Those goals are now imperiled. Argentina's further collapse would directly or indirectly damage other South American economies, provoking cumulative financial panics. And the breakdown of one of the region's largest democracies would undermine two decades of gains across the hemisphere. Only two decades ago, dictatorship, not democracy, dominated much of Latin America. Argentina suffered six military coups between 1930 and 1976. Since 1983, Argentines have put political violence and instability behind them. Presidents are now regularly and freely elected, and power has passed peacefully several times from government to opposition. Civil liberties are now widely respected, and the country possesses a vibrant free press and civil society. Losing Hope The current crisis threatens to undo these democratic gains. After four years of recession, Argentines are beginning to lose hope. Trust in government has eroded. Many citizens no longer believe their elected leaders are able to address their most pressing problems. The de la Rúa 2-year-old government suffered such a dramatic loss of support because it was increasingly perceived to be sacrificing its citizens' well-being to meet the demands of financial markets. In his wake, Rodríguez Saá's grace period lasted only a week. The danger today is that frustration has spread to include the entire political elite, and perhaps even Argentina's political institutions—patterns similar to those that gave rise to Alberto Fujimori in Peru and Hugo Chávez in Venezuela. If that occurs, the prospects for democracy will dim considerably. It has not come to that yet. Neither de la Rúa's or Rodríguez Saá's resignation was a military coup, and no Argentine Hugo Chávez has yet emerged. No one doubts that the election to choose de la Rúa's successor will be free and fair. But if Argentina is to steer clear of a Venezuela-like fate, its new government must deliver economic solutions to Argentines. To do so, it will require external assistance. A successful model of such U.S.-backed support was tested in Mexico. The U.S. government's decision to organize a financial assistance package to help Mexico address the 1994-95 financial panic was bold and politically risky. But it clearly worked. A worse panic was deterred, economic growth was soon restored and Mexico made an impressive transition to democracy. Argentina deserves similar help. Few, if any, Latin American countries combined democracy and market reforms as successfully as Argentina did in the 1990s. Argentine democracy has proven remarkably resilient, weathering hyperinflation and radical economic reform. But if something is not done soon to give Argentines a realistic expectation that their politicians and democratic institutions can provide solutions to their problems, someone else will try to convince them that those politicians and those institutions are themselves the problem. If that happens, U.S. interests will suffer badly in Argentina and elsewhere in the Americas.

Needed: A Manifesto for Mideast Peace - Kelman, Herbert C. (Boston Globe, 2002)
Israel and the Palestinian territories are on the brink of an all-out war with disastrous consequences for these two traumatized nations. The Israeli government and the Palestinian street are controlled by elements that see such a war as an opportunity to achieve their maximalist goals. Under the circumstances, there is a compelling need for vigorous intervention by outside powers—the Arab League, the European Union, the United Nations, and, perhaps most important, the United States—to pull the parties away from the brink and back to the negotiating table. Outside intervention, however, cannot by itself restore the working trust required for negotiating an agreement conducive to the stable peace and mutually enhancing relationship between the two nations on which their survival in the small land they share ultimately depends. To succeed, the outside intervention must be accompanied by creative, courageous acts of leadership emanating from the two societies themselves. The most likely candidates to perform such leadership roles are the two surviving members of the triad that received the Nobel Peace Prize in 1994: Palestinian Authority President Yasser Arafat and Israel's Foreign Minister Shimon Peres. Both men have suffered losses in power and prestige. Both have been criticized for their roles in legitimizing the extremes of violence in their respective communities. And yet they are probably the only leaders with the authority and the domestic and international standing to take the initiative proposed here. The scenario I envisage calls for a meeting or a series of meetings between the two men (and a small number of close advisers) in Arafat's headquarters in Ramallah. Refusal by Prime Minister Ariel Sharon to authorize such an initiative would provide the appropriate moment for Peres to resign from the government: He would be resigning in pursuit of an initiative with the potential for achieving a dramatic breakthrough. The meetings between the two leaders would aim to produce a joint manifesto with the following components: First, a call for an end to the violence and for the resumption of negotiations designed to achieve a just solution to the conflict, addressing the fundamental needs of both parties. Second, a commitment to the final outcome of the negotiations: an agreement that would end the conflict on the basis of a historic compromise in the form of a two-state solution. Third, a delineation of the broad outlines of the historic compromise, including: establishment of a viable, independent, and sovereign Palestinian state consisting of the West Bank and Gaza, with contiguous territory within each of these two units and safe passage between them; acceptance of the legitimacy of Israel as a Jewish-majority state with the proviso that it assure full democratic rights for its Arab minority; designation of Jerusalem, including the Old City and the holy sites, as a shared city, containing the capitals of both states; and development of a comprehensive, multifaceted solution to the problem of Palestinian refugees, including resettlement and compensation, which would satisfy Palestinians' sense of justice and Israelis' concern about the stability of their state. Fourth, a specification of the issues that remain to be negotiated within the framework of the historic compromise, such as border adjustments and territorial exchange, arrangements for governance and security of a shared Jerusalem, and procedures for addressing both the symbolic and the practical aspects of a solution for the refugee problem. Finally, an unambiguous and honest account of the costs that a historic compromise would entail for both peoples, stressing, in particular, the need to recognize that Israeli dreams of settling Judea, Samaria, and Gaza, and Palestinian dreams of returning in large numbers to the homes they lost in 1948 cannot be realized. A manifesto along these lines would demonstrate to the Israeli and Palestinian publics that there are courageous leaders who are prepared to commit themselves to a historic compromise and honestly spell out its implications. It would help revive the belief in each community that there is a credible negotiating partner on the other side and that there is a mutually acceptable formula for a final agreement. The manifesto would gain symbolic strength if Arafat and Peres dedicated it to the memory of their fellow Nobelist, Yitzhak Rabin, who paid with his life for the pursuit of a historic compromise and whose assassination was a major contributing factor to deterioration of the peace process.

How to Protect the Homeland - Nye, Joseph S., Jr. (the New York Times, 2001)
Five years ago, with James Woolsey, former director of the Central Intelligence Agency, I headed a government study that found a lack of preparedness to face catastrophic terrorism. Our warnings and those of similar groups went largely unheeded. On Sept. 11, complacency was wiped away, but the fragmented bureaucratic structure and procedures of our government remain a barrier to action, despite President Bush's decision to name Gov. Tom Ridge of Pennsylvania to head a new Office of Homeland Defense. By using the rhetoric of war to frame our response to the terror attacks, President Bush has marshaled the public's patriotism and persuaded Congress to provide financing. But the danger in the rhetoric is that the new office may be structured like a military organization. There are many types of terrorism and many kinds of terrorist weapons. Even if we succeed in eliminating Osama bin Laden, we have to remember that Timothy McVeigh was home-grown. And as we succeed in battening down the cockpits to prevent civilian aircraft being used again as giant cruise missiles, terrorists will be exploring other vulnerabilities in our open society and investigating even more devastating weapons. Fortunately, nuclear and biological weapons are not as easy to make as popular fiction suggests, but there have been reports that Mr. bin Laden and others have tried to purchase stolen nuclear weapons from the former Soviet inventory. We also know that a few years ago the Japanese Aum Shinrikyo cult killed people with both chemical and biological agents. Suppressing terrorism is very different from a military campaign. It requires continuous, patient, undramatic civilian work and close cooperation with other countries. And it requires coordination within our government. The C.I.A. and F.B.I. must improve their ability to work together on detection and must reconcile their different authorities and programs in intelligence and law enforcement. The F.B.I., the Immigration and Naturalization Service, the Customs Service, the Defense Department and other agencies must improve their cooperation. Because of poor coordination, two suspects were able to enter this country even after their names had been placed on a watch list, and the jet fighters that scrambled after the Federal Aviation Administration notification of the hijackings arrived too late. The Federal Emergency Management Agency has to work with local governments on domestic responses. New federally funded research and development programs are needed to address each phase of a crisis, as well as to accelerate new technologies and devise special training and testing exercises. It would be a mistake if the Office of Homeland Defense merely added another layer of bureaucracy. Instead, Governor Ridge should head a committee of deputy secretaries from the agencies with control over budgets and programs involved with terrorism defense. He should create a small staff that works closely with the Office of Management and Budget to monitor plans to be carried out by existing agencies. His office should be supported by new research corporations created to deal with terrorism, as the RAND corporation was created in the cold war to deal with the nuclear threat. These groups should not be bound by the rigidities and inadequate salaries of the federal bureaucracy. Their independence should allow them to plan an antiterror system that can find gaps and overlaps in government agencies' antiterror efforts and examine weaknesses in private systems like computer networks. Planners should conduct regular exercises with teams simulating terrorists and defenders, trying to outsmart each other. Had we done this for our airport security system, we might have realized that it was designed to detect guns and bombs but not to stop suicide pilots armed with knives and box cutters. As recently as last spring, a commission on national security headed by former Senators Gary Hart and Warren Rudman also warned of our lack of preparedness. Sadly, the commissioners were right. Now we must organize ourselves effectively to combat terrorism.

Quid Pro Quo: Aid for Pakistan, Not Its Army - Kapur, Devesh (Asian Wall Street Journal, 2001)
As the international community reflects on the forms and magnitude of the assistance that can be rendered to Pakistan, it is worth pondering how a country that has been one of the world's largest recipients of foreign financial aid—nearly $58 billion from 1960-98, the third-highest of any country—still finds itself in such a beleaguered and impoverished state. In particular, the international community has to grapple with the reality that the very institution whose help is critical in efforts to break the power of terrorists groups in South Asia, the Pakistani military, is also deeply responsible for creating and nurturing these groups. The role of the Pakistani army is central not only to the well being of Pakistan's citizens, and to the region. It is also critical to stopping the global spread of terrorism. Pakistan's current economic, political and social fragility is primarily the result of the country's history as a beneficiary of geostrategic rents—from the U.S. during the 1950s and `60s, and again in the '80s; from the Middle East, especially in the '70s and '80s; and from China in the '90s. These substantial rents have shaped the country's political economy and its institutions. And they have underpinned the continued preeminence of the Pakistani military even as militaries in most other developing countries have gone back to the barracks. The consequences have been devastating. Internally, Pakistan's institutions have atrophied, which has in turn provided the justification for the military to maintain its monopoly on power. Gen. Pervez Musharraf has promised to return the country to full democracy with provincial and federal elections in October 2002. And yet there is ample evidence to suggest that the proposed power devolution, carried out via constitutional reforms, will actually marginalize secular political parties and the civilian bureaucracy, thereby allowing the army an even wider role in the country's political future. Moreover, the military's hegemonic role has had a negative effect on the nation's economy. The military has claimed a disproportionate fraction of the country's modest resources while expenditures on health, education and business development programs have suffered. Even today, military expenditures are twice that of the latter, in a country that has one of the weakest indicators of human development. Another consequence stems from the chronic quest for legitimacy that authoritarian regimes need to retain power. Pakistan's military has used two instruments to shore up its domestic support. First, beginning with President Muhammad Zia ul-Haq in the early '80s, the military cultivated the Islamic religious establishment using religious parties to outflank their mainstream counterparts. This Faustian bargain resulted in the rapid growth of Islamic schools, the madraasas, with financial support from Saudi Arabia, which was eager to enlarge the influence of Wahabist Islam and the Islamicization of the Pakistani military and society. The weakening of secular political parties further justified the military establishment's grip on political power. The second instrument of the military government's legitimacy comes from the perennial tension with India. The need to "protect the integrity of Pakistan" against the alleged wily machinations of India has always been a handy tool to whip up nationalist sentiment and justify the military's hold on power. The May 1999 Kargil invasion, engineered by Gen. Musharraf even as the country's own civilian government was engaged in a dialogue with its Indian counterpart, ensured that dialogue was still-born and the military's hegemony unchallenged. But even if the Pakistani security establishment's bleeding of India in Kashmir can be justified by India's actions, it is Afghanistan, much more than India, that has suffered egregiously from the Pakistani military's actions. Driven by its obsession with India, the Pakistani military sought to create a client state in Afghanistan in its quest for "strategic depth," and thereby build a staging area from which to infiltrate Kashmir. From funding, logistics and indirect military support, the Pakistani military intervened in Afghanistan's affairs to a degree that even the superpowers rarely managed during the Cold War. Although the ultimate rationale of the Pakistani security establishment's involvement in Afghanistan has been India, the net result was to further hasten the destruction of the country begun by the Soviets. A third instrument of control has been the military's contention that it is a protector of Muslims throughout South Asia. This claim is made by an institution that was responsible for one of the world's worst slaughters of Muslims in the last century—at least half a million people in what was then East Pakistan, now Bangladesh, in 1971. Western, and in particular American policy makers and media, have long been apologists for the Pakistani army. Nevertheless, though the strategic calculations of the Cold War have given way to the tactical imperatives of the current Afghan campaign, this alone cannot justify blind support for the military, nor glossing over the long-term consequences of that support for Pakistan and the region, and the West itself. There can be no doubt that given Pakistan's importance on the global stage and its current weaknesses, the country both needs and deserves considerable and sustained international financial assistance. But in doing so, there should be a clear target for the aid: a country and its people. The international community must ensure that, unlike the foreign assistance offered to Pakistan in the 1980s, new resources don't simply help to further strengthen the very institution that has been at the root of the country's—and increasingly the region's—problems. Proposals to cut Pakistan's debt servicing and reschedule the debt are basically steps in the right direction. However, unless the resulting savings are channeled toward sharply increasing social expenditures on human capital development and poverty-oriented programs, they will serve little more than to further entrench the military regime. It is not surprising that during his recent visit to Washington, Gen. Musharraf was more interested in securing the release of a package of F-16 fighter jets from the Bush administration than in obtaining aid for his country's devastated education system. External assistance should therefore be contingent on curbing military expenditures (which continue to be one of the highest in the world) as well as funding for the madraasas that serve as jihadi prep schools (although it should be emphasized that many madraasas are simply parochial schools and not training grounds for zealots). However, these initiatives will also require the cooperation of "moderate" Arab countries, especially Saudi Arabia and the United Arab Emirates, whose citizens are an important source of funds not only in Pakistan, but also in other parts of South and Southeast Asia. The manner in which the international community helps Pakistan will have broader implications as it grapples to assist other weak, undemocratic states. Unfortunately, for much of the past half-century, foreign aid has too often served as the palatable cover for what were essentially bribes to friendly regimes to secure their cooperation than as resources whose intent was the long term political and economic development of a country and its people. In the process, hundreds of billions of dollars have been spent with little to show for it; regimes that have caused untold misery to their people in a variety of contexts have been entrenched; donor institutions have been seriously discredited. This is a lesson American policy makers should heed in helping Pakistan to secure a promising future for its 140 million people.

A Better Society in a Time of War - Putnam, Robert D. (New York Times, 2001)
CAMBRIDGE, Mass. -- The America of six decades ago now seems achingly familiar. The attack on Pearl Harbor, like the attacks of Sept. 11, evoked feelings of pride and citizenship - as well as anxiety and helplessness - in every American. In the days and weeks following Dec. 7, 1941, Americans sought meaning and comfort in their communities, just as we do now. And we can find inspiration in the very institutions and practices they created 60 years ago. A durable community cannot be built on mere images of disaster, however vivid or memorable. It arises from countless individual acts of concern and solidarity. Television images of ash-covered firefighters cannot create community bonds any more than radio reports of burning battleships could. What created the civic community in the United States in the aftermath of Pearl Harbor? The victory gardens in nearly everyone's backyard, the Boy Scouts at filling stations collecting floor mats for scrap rubber, the affordable war bonds, the practice of giving rides to hitchhiking soldiers and war workers - all these taught "the greatest generation" an enduring lesson in civic involvement. Their involvement was as varied as it was deep. The Civilian Defense Corps grew to 12 million Americans in mid-1943, from 1.2 million in 1942. In Chicago, 16,000 block captains in the corps took an oath of allegiance in a mass ceremony; they practiced first aid, supervised blackouts and planned gas decontamination. Nationwide, Red Cross volunteers swelled to 7.5 million in 1945, from 1.1 million in 1940. By 1943, volunteers at 4,300 civilian-defense volunteer offices were fixing school lunches, providing day care and organizing scrap drives. All these endeavors represented cooperation between the federal government and civic society. Sometimes the government merely offered encouragement and approval, as it did with the victory gardens. Often it played an active role, or even the prime role. The United States financed the war effort in part through small-denomination war bonds sold to the general public, not because it was economically efficient - Treasury Secretary Henry Morgenthau conceded it wasn't - but because of the importance of weaving the actions of millions of Americans together in pursuit of larger national goals. America's young people, especially, were taught practical civic lessons. Over a two-year period, the historian Richard Lingeman writes in his book "Don't You Know There's a War On?" eighth graders in Gary, Ind., were especially busy. They sold an average of $40,000 worth of war stamps a month. They campaigned against buying black-market goods. They took auxiliary fire- and police-training courses. They held tin-can drives. And this was just in one medium-sized Midwestern city. Such sacrifice was reinforced by popular culture from radio shows to comic strips. All Americans felt they had to do their share, thereby enhancing each American's sense that her commitment and contribution mattered. As one said later in an oral history of the home front: "You just felt that the stranger sitting next to you in a restaurant, or someplace, felt the same way you did about the basic issues." Society is different now, of course, as is the war we are fighting. Americans have become more transient, and involvement in civic institutions is in decline. The war itself involves far fewer Americans in battle; it creates few material hardships; the enemy is largely invisible. Nonetheless, we can take action to ensure that this resurgence of community involvement continues. Since Sept. 11, we Americans have surprised ourselves in our solidarity. Roughly a quarter of all Americans, and more than a third of all New Yorkers, report giving blood in the aftermath of the attacks. Financial donations for the victims and their rescuers have reached almost $1 billion. Attendance at places of worship has increased. Still, underneath all this mutual concern lies an unsettling question: Will this new mood last? I believe it can. Even 60 years ago, civic involvement took hold and flourished only with government support. It was not all spontaneous. This is both instructive and reassuring; instructive because it shows that the most selfless civic duties cannot be performed without government help, reassuring because it shows us a path toward a more civil society today. President Bush's recent call to America's children and teenagers to wash cars or rake yards to earn money to benefit the children of Afghanistan was well-intentioned. But government can do more. It should urge America's religious congregations to plan interfaith services over Thanksgiving weekend. It should also expand national service programs like AmeriCorps. And just as those Boy Scouts at filling stations learned firsthand the value of civic life, this new period of crisis can make real to us and our children the value of deeper community connections.

A Vision for Compromise - Kelman, Herbert C. (Boston Globe, 2001)
The continuing deadly escalation of the Israeli-Palestinian conflict threatens to become an all-out war with devastating consequences for both communities. What makes this situation particularly tragic is the fact that the formula and the will for negotiating a mutually satisfactory agreement to end the conflict remain in place. The negotiators were able to come very close to agreement in Taba last January, and the two populations are still open to a negotiated agreement if they could be convinced that the other side can be trusted. The breakdown in negotiations and the resulting cycle of violence led to the reemergence on both sides—in classical mirror-image fashion—of the belief that there is no negotiating partner on the other side, that “they” do not want to make the compromises required for peace, and that the only language “they” understand is force. Counteracting these beliefs requires a clear endorsement by the leadership on each side of a political solution that would meet the basic needs of the other. The dynamics of escalating violence prevent the leaders from speaking the words and taking the actions that would reassure the other, lest they be seen as weak and yielding to violence. Moreover, Ariel Sharon's strategy and Yasser Arafat's tactics make it particularly difficult for them to make an unambiguous commitment, in advance, to the kind of political outcome on which the resumption of fruitful negotiations now depends. Under the circumstances, outside parties, especially the United States, can make a unique contribution, not only by encouraging the parties to resume serious negotiations but by offering a vision of the broad outlines of the final agreement to which these negotiations must be directed. Following up on Secretary of State Colin Powell's constructive policy address, this vision should be based on the historic compromise that was implicit in the Oslo agreement. Anchored in UN Resolutions 242 and 338, this compromise has the added advantage of international legitimacy. It is predicated on an agreement to end the conflict by sharing the land both peoples claim, through the establishment and peaceful coexistence of two states, in which the two peoples can fulfill their respective rights to national self-determination, give political expression to their national identities, and pursue independent, secure, and prosperous lives. The vision of such a historic compromise must spell out three implications for resolving outstanding issues in the conflict. Each of these implications is painful to one or both parties, but they follow directly from the essence of the compromise. First, the historic compromise must enable Palestinians to establish an independent, sovereign state consisting of the West Bank and the Gaza Strip. To be viable and governable, the state must have contiguous territory within each of its two units and a secure corridor between them. It cannot, therefore, accommodate Israeli settlements with extraterritorial rights, a separate network of roads, and protection by Israeli forces. Second, the historic compromise implies Palestinian acceptance of the legitimacy of Israel as a Jewish-majority state (with full democratic rights for its Arab minority). Therefore, to maintain its Jewish character and its cohesion, Israel cannot accommodate an automatic, large-scale return of Palestinian refugees to the country. Third, the historic compromise calls on the two peoples to share Jerusalem, as an open city, containing the capitals of both states and ensuring full access to the holy sites of all religious communities. Within the broad parameters of these three principles, it is necessary and possible to negotiate mutual accommodations central to the narratives and the internal cohesion of the two societies. Thus, on the issue of settlements, negotiations need to take cognizance of the domestic turmoil that dismantling large numbers of settlements would create for Israel and consider exchanging small segments of the West Bank that have a heavy concentration of Israeli settlers for Israeli territory of equal size and value. On the issue of refugees, recognizing its centrality to the Palestinian identity and narrative, negotiations need to agree on language whereby Israel would acknowledge its share of responsibility and express regret for the plight of the refugees and on a comprehensive program of resettlement and compensation for refugees, including return of a limited number to Israel. On the issue of Jerusalem, negotiations need to work out arrangements for sharing sovereignty and use of both holy sites and public spaces vital to both communities and for providing governance, security, and municipal services on a citywide basis. Formulas for dealing with many of these issues in a mutually satisfactory way have already been explored in previous negotiations, although further efforts are required to shape them into a comprehensive package. That work must and can be done by the parties themselves. Where the United States can make an indispensable contribution is in bringing the parties back to the negotiating table by offering a broad vision of the historic compromise toward which the negotiations must be directed.